Bi-allelic ACBD6 variants lead to a neurodevelopmental syndrome with progressive and complex movement disorders. - Kaiyrzhanov, Rauan; Rad, Aboulfazl; Lin, Sheng-Jia; Bertoli-Avella, Aida; Kallemeijn, Wouter W; Godwin, Annie; Zaki, Maha S; Huang, Kevin; Lau, Tracy; Petree, Cassidy; Efthymiou, Stephanie; Karimiani, Ehsan Ghayoor; et al. (Brain, 2024)
The acyl-CoA-binding domain-containing protein 6 (ACBD6) is ubiquitously expressed, plays a role in the acylation of lipids and proteins and regulates the N-myristoylation of proteins via N-myristoyltransferase enzymes (NMTs). However, its precise function in cells is still unclear, as is the consequence of ACBD6 defects on human pathophysiology. Using exome sequencing and extensive international data sharing efforts, we identified 45 affected individuals from 28 unrelated families (consanguinity 93%) with bi-allelic pathogenic, predominantly loss-of-function (18/20) variants in ACBD6. We generated zebrafish and Xenopus tropicalis acbd6 knockouts by CRISPR/Cas9 and characterized the role of ACBD6 on protein N-myristoylation with myristic acid alkyne (YnMyr) chemical proteomics in the model organisms and human cells, with the latter also being subjected further to ACBD6 peroxisomal localization studies. The affected individuals (23 males and 22 females), aged 1-50 years, typically present with a complex and progressive disease involving moderate-to-severe global developmental delay/intellectual disability (100%) with significant expressive language impairment (98%), movement disorders (97%), facial dysmorphism (95%) and mild cerebellar ataxia (85%) associated with gait impairment (94%), limb spasticity/hypertonia (76%), oculomotor (71%) and behavioural abnormalities (65%), overweight (59%), microcephaly (39%) and epilepsy (33%). The most conspicuous and common movement disorder was dystonia (94%), frequently leading to early-onset progressive postural deformities (97%), limb dystonia (55%) and cervical dystonia (31%). A jerky tremor in the upper limbs (63%), a mild head tremor (59%), parkinsonism/hypokinesia developing with advancing age (32%) and simple motor and vocal tics were among other frequent movement disorders. Midline brain malformations including corpus callosum abnormalities (70%), hypoplasia/agenesis of the anterior commissure (66%), short midbrain and small inferior cerebellar vermis (38% each) as well as hypertrophy of the clava (24%) were common neuroimaging findings. Acbd6-deficient zebrafish and Xenopus models effectively recapitulated many clinical phenotypes reported in patients including movement disorders, progressive neuromotor impairment, seizures, microcephaly, craniofacial dysmorphism and midbrain defects accompanied by developmental delay with increased mortality over time. Unlike ACBD5, ACBD6 did not show a peroxisomal localization and ACBD6-deficiency was not associated with altered peroxisomal parameters in patient fibroblasts. Significant differences in YnMyr-labelling were observed for 68 co- and 18 post-translationally N-myristoylated proteins in patient-derived fibroblasts. N-myristoylation was similarly affected in acbd6-deficient zebrafish and X. tropicalis models, including Fus, Marcks and Chchd-related proteins implicated in neurological diseases. The present study provides evidence that bi-allelic pathogenic variants in ACBD6 lead to a distinct neurodevelopmental syndrome accompanied by complex and progressive cognitive and movement disorders.
Keywords: Adolescent; Adult; Animals; ATP-Binding Cassette Transporters; Child; Child, Preschool; Female; Humans; Infant; Intellectual Disability; Male; Microcephaly; Middle Aged; Movement Disorders; Nervous System Malformations; Neurodevelopmental Disorders; Tremor; Young Adult; Zebrafish

Biallelic variants in SLC4A10 encoding a sodium-dependent bicarbonate transporter lead to a neurodevelopmental disorder. - Maroofian, Reza; Zamani, Mina; Kaiyrzhanov, Rauan; Liebmann, Lutz; Karimiani, Ehsan Ghayoor; Vona, Barbara; Huebner, Antje K; Calame, Daniel G; Misra, Vinod K; Sadeghian, Saeid; Azizimalamiri, Reza; Mohammadi, Mohammad Hasan; et al. (Genet Med, 2024)
PURPOSE: SLC4A10 encodes a plasma membrane-bound transporter, which mediates Na-dependent HCO import, thus mediating net acid extrusion. Slc4a10 knockout mice show collapsed brain ventricles, an increased seizure threshold, mild behavioral abnormalities, impaired vision, and deafness. METHODS: Utilizing exome/genome sequencing in families with undiagnosed neurodevelopmental disorders and international data sharing, 11 patients from 6 independent families with biallelic variants in SLC4A10 were identified. Clinico-radiological and dysmorphology assessments were conducted. A minigene assay, localization studies, intracellular pH recordings, and protein modeling were performed to study the possible functional consequences of the variant alleles. RESULTS: The families harbor 8 segregating ultra-rare biallelic SLC4A10 variants (7 missense and 1 splicing). Phenotypically, patients present with global developmental delay/intellectual disability and central hypotonia, accompanied by variable speech delay, microcephaly, cerebellar ataxia, facial dysmorphism, and infrequently, epilepsy. Neuroimaging features range from some non-specific to distinct neuroradiological findings, including slit ventricles and a peculiar form of bilateral curvilinear nodular heterotopia. In silico analyses showed 6 of 7 missense variants affect evolutionarily conserved residues. Functional analyses supported the pathogenicity of 4 of 7 missense variants. CONCLUSION: We provide evidence that pathogenic biallelic SLC4A10 variants can lead to neurodevelopmental disorders characterized by variable abnormalities of the central nervous system, including altered brain ventricles, thus resembling several features observed in knockout mice.
Keywords: Animals; Bicarbonates; Chloride-Bicarbonate Antiporters; Humans; Intellectual Disability; Membrane Transport Proteins; Mice; Mice, Knockout; Neurodevelopmental Disorders; Sodium; Sodium Bicarbonate; Sodium-Bicarbonate Symporters

The CARD8 inflammasome dictates HIV/SIV pathogenesis and disease progression. - Wang, Qiankun; Clark, Kolin M; Tiwari, Ritudhwaj; Raju, Nagarajan; Tharp, Gregory K; Jeffrey Rogers; R. Alan Harris; Raveendran, Muthuswamy; Bosinger, Steven E; Burdo, Tricia H; Silvestri, Guido; Shan, Liang (Cell, 2024)
While CD4 T cell depletion is key to disease progression in people living with HIV and SIV-infected macaques, the mechanisms underlying this depletion remain incompletely understood, with most cell death involving uninfected cells. In contrast, SIV infection of "natural" hosts such as sooty mangabeys does not cause CD4 depletion and AIDS despite high-level viremia. Here, we report that the CARD8 inflammasome is activated immediately after HIV entry by the viral protease encapsulated in incoming virions. Sensing of HIV protease activity by CARD8 leads to rapid pyroptosis of quiescent cells without productive infection, while T cell activation abolishes CARD8 function and increases permissiveness to infection. In humanized mice reconstituted with CARD8-deficient cells, CD4 depletion is delayed despite high viremia. Finally, we discovered loss-of-function mutations in CARD8 from "natural hosts," which may explain the peculiarly non-pathogenic nature of these infections. Our study suggests that CARD8 drives CD4 T cell depletion during pathogenic HIV/SIV infections.
Keywords: Animals; CARD Signaling Adaptor Proteins; CD4-Positive T-Lymphocytes; Disease Progression; HIV; HIV Infections; Humans; Inflammasomes; Mice; Neoplasm Proteins; Simian Acquired Immunodeficiency Syndrome; Simian Immunodeficiency Virus; Viremia

Complete Genomic Assembly of Mauritian Cynomolgus Macaque Killer Ig-like Receptor and Natural Killer Group 2 Haplotypes. - Prall, Trent M; Karl, Julie A; Varghese, Joshua M; Baker, David A; Minor, Nicholas R; Raveendran, Muthuswamy; R. Alan Harris; Jeffrey Rogers; Wiseman, Roger W; O'Connor, David H (J Immunol, 2024)
Mauritian-origin cynomolgus macaques (MCMs) serve as a powerful nonhuman primate model in biomedical research due to their unique genetic homogeneity, which simplifies experimental designs. Despite their extensive use, a comprehensive understanding of crucial immune-regulating gene families, particularly killer Ig-like receptors (KIR) and NK group 2 (NKG2), has been hindered by the lack of detailed genomic reference assemblies. In this study, we employ advanced long-read sequencing techniques to completely assemble eight KIR and seven NKG2 genomic haplotypes, providing an extensive insight into the structural and allelic diversity of these immunoregulatory gene clusters. Leveraging these genomic resources, we prototype a strategy for genotyping KIR and NKG2 using short-read, whole-exome capture data, illustrating the potential for cost-effective multilocus genotyping at colony scale. These results mark a significant enhancement for biomedical research in MCMs and underscore the feasibility of broad-scale genetic investigations.
Keywords: Animals; Genomics; Genotype; Haplotypes; Macaca fascicularis; NK Cell Lectin-Like Receptor Subfamily C; Receptors, KIR

Core planar cell polarity genes and in predisposition to congenital vertebral malformations. - Feng, Xin; Ye, Yongyu; Zhang, Jianan; Zhang, Yuanqiang; Zhao, Sen; Mak, Judith C W; Otomo, Nao; Zhao, Zhengye; Niu, Yuchen; Yonezawa, Yoshiro; Li, Guozhuang; Lin, Mao; et al. (Proc Natl Acad Sci U S A, 2024)
Congenital scoliosis (CS), affecting approximately 0.5 to 1 in 1,000 live births, is commonly caused by congenital vertebral malformations (CVMs) arising from aberrant somitogenesis or somite differentiation. While Wnt/ß-catenin signaling has been implicated in somite development, the function of Wnt/planar cell polarity (Wnt/PCP) signaling in this process remains unclear. Here, we investigated the role of and in vertebral development and found that their deletion causes vertebral anomalies resembling human CVMs. Analysis of exome sequencing data from multiethnic CS patients revealed a number of rare and deleterious variants in and , many of which exhibited loss-of-function and dominant-negative effects. Zebrafish models confirmed the pathogenicity of these variants. Furthermore, we found that knock-in (p.R258H) mice exhibited vertebral malformations in a gene dose- and environment-dependent manner. Our findings highlight critical roles for PCP signaling in vertebral development and predisposition to CVMs in CS patients, providing insights into the molecular mechanisms underlying this disorder.
Keywords: Animals; Carrier Proteins; Cell Polarity; Female; Genetic Predisposition to Disease; Humans; Intracellular Signaling Peptides and Proteins; Membrane Proteins; Mice; Nerve Tissue Proteins; Scoliosis; Spine; Wnt Signaling Pathway; Zebrafish; Zebrafish Proteins

De Novo Genome Assembly for the Coppery Titi Monkey (Plecturocebus cupreus): An Emerging Nonhuman Primate Model for Behavioral Research. - Pfeifer, Susanne P; Baxter, Alexander; Savidge, Logan E; Fritz J Sedlazeck; Bales, Karen L (Genome Biol Evol, 2024)
The coppery titi monkey (Plecturocebus cupreus) is an emerging nonhuman primate model system for behavioral and neurobiological research. At the same time, the almost entire absence of genomic resources for the species has hampered insights into the genetic underpinnings of the phenotypic traits of interest. To facilitate future genotype-to-phenotype studies, we here present a high-quality, fully annotated de novo genome assembly for the species with chromosome-length scaffolds spanning the autosomes and chromosome X (scaffold N50 = 130.8 Mb), constructed using data obtained from several orthologous short- and long-read sequencing and scaffolding techniques. With a base-level accuracy of ∼99.99% in chromosome-length scaffolds as well as benchmarking universal single-copy ortholog and k-mer completeness scores of >99.0% and 95.1% at the genome level, this assembly represents one of the most complete Pitheciidae genomes to date, making it an invaluable resource for comparative evolutionary genomics research to improve our understanding of lineage-specific changes underlying adaptive traits as well as deleterious mutations associated with disease.
Keywords: Animals; Genome; Genomics; Models, Animal; Pitheciidae

Dietary Folate and Cofactors Accelerate Age-dependent p16 Epimutation to Promote Intestinal Tumorigenesis. - Yang, Li; Peery, Robert C; Farmer, Leah M; Gao, Xia; Zhang, Yiqun; Creighton, Chad J; Zhang, Lanjing; Shen, Lanlan (Cancer Res Commun, 2024)
UNLABELLED: The extent to which non-genetic environmental factors, such as diet, contribute to carcinogenesis has been long debated. One potential mechanism for the effects of environmental factors is through epigenetic modifications that affect gene expression without changing the underlying DNA sequence. However, the functional cooperation between dietary factors and cancer-causing epigenetic regulation is largely unknown. Here, we use a mouse model of age-dependent p16 epimutation, in which the p16 gene activity is directly controlled by promoter DNA methylation. We show p16 epimutation is modulated by folate and cofactors in dietary supplementation, which leads to increased colon cancer risk. Importantly, our findings provide functional evidence concerning the safety of folate fortification in the general population. SIGNIFICANCE: Our study demonstrates that dietary folate and cofactors modulate tumor-suppressor gene methylation to increase intestinal tumorigenesis. Our findings highlight the need for monitoring the long-term safety of folate fortification in high-risk individuals.
Keywords: Animals; Carcinogenesis; Cell Transformation, Neoplastic; Cyclin-Dependent Kinase Inhibitor p16; Diet; Epigenesis, Genetic; Folic Acid; Humans; Intestinal Neoplasms; Mice

Identification of constrained sequence elements across 239 primate genomes. - Kuderna, Lukas F K; Ulirsch, Jacob C; Rashid, Sabrina; Ameen, Mohamed; Sundaram, Laksshman; Hickey, Glenn; Cox, Anthony J; Gao, Hong; Kumar, Arvind; Aguet, Francois; Christmas, Matthew J; Clawson, Hiram; et al. (Nature, 2024)
Noncoding DNA is central to our understanding of human gene regulation and complex diseases, and measuring the evolutionary sequence constraint can establish the functional relevance of putative regulatory elements in the human genome. Identifying the genomic elements that have become constrained specifically in primates has been hampered by the faster evolution of noncoding DNA compared to protein-coding DNA, the relatively short timescales separating primate species, and the previously limited availability of whole-genome sequences. Here we construct a whole-genome alignment of 239 species, representing nearly half of all extant species in the primate order. Using this resource, we identified human regulatory elements that are under selective constraint across primates and other mammals at a 5% false discovery rate. We detected 111,318 DNase I hypersensitivity sites and 267,410 transcription factor binding sites that are constrained specifically in primates but not across other placental mammals and validate their cis-regulatory effects on gene expression. These regulatory elements are enriched for human genetic variants that affect gene expression and complex traits and diseases. Our results highlight the important role of recent evolution in regulatory sequence elements differentiating primates, including humans, from other placental mammals.
Keywords: Animals; Conserved Sequence; Deoxyribonuclease I; DNA; Evolution, Molecular; Female; Gene Expression Regulation; Genome; Humans; Mammals; Placenta; Pregnancy; Primates; Proteins; Regulatory Sequences, Nucleic Acid; Reproducibility of Results; Transcription Factors

Inference of phylogenetic trees directly from raw sequencing reads using Read2Tree. - Dylus, David; Altenhoff, Adrian; Majidian, Sina; Fritz J Sedlazeck; Dessimoz, Christophe (Nat Biotechnol, 2024)
Current methods for inference of phylogenetic trees require running complex pipelines at substantial computational and labor costs, with additional constraints in sequencing coverage, assembly and annotation quality, especially for large datasets. To overcome these challenges, we present Read2Tree, which directly processes raw sequencing reads into groups of corresponding genes and bypasses traditional steps in phylogeny inference, such as genome assembly, annotation and all-versus-all sequence comparisons, while retaining accuracy. In a benchmark encompassing a broad variety of datasets, Read2Tree is 10-100 times faster than assembly-based approaches and in most cases more accurate-the exception being when sequencing coverage is high and reference species very distant. Here, to illustrate the broad applicability of the tool, we reconstruct a yeast tree of life of 435 species spanning 590 million years of evolution. We also apply Read2Tree to >10,000 Coronaviridae samples, accurately classifying highly diverse animal samples and near-identical severe acute respiratory syndrome coronavirus 2 sequences on a single tree. The speed, accuracy and versatility of Read2Tree enable comparative genomics at scale.
Keywords: Animals; Genomics; Phylogeny; Sequence Analysis

NODAL variants are associated with a continuum of laterality defects from simple D-transposition of the great arteries to heterotaxy. - Dardas, Zain; Fatih, Jawid M; Jolly, Angad; Dawood, Moez; Du, Haowei; Grochowski, Christopher M; Jones, Edward G; Jhangiani, Shalini N; Wehrens, Xander H T; Liu, Pengfei; Bi, Weimin; Eric Boerwinkle; et al. (Genome Med, 2024)
BACKGROUND: NODAL signaling plays a critical role in embryonic patterning and heart development in vertebrates. Genetic variants resulting in perturbations of the TGF-β/NODAL signaling pathway have reproducibly been shown to cause laterality defects in humans. To further explore this association and improve genetic diagnosis, the study aims to identify and characterize a broader range of NODAL variants in a large number of individuals with laterality defects. METHODS: We re-analyzed a cohort of 321 proband-only exomes of individuals with clinically diagnosed laterality congenital heart disease (CHD) using family-based, rare variant genomic analyses. To this cohort we added 12 affected subjects with known NODAL variants and CHD from institutional research and clinical cohorts to investigate an allelic series. For those with candidate contributory variants, variant allele confirmation and segregation analysis were studied by Sanger sequencing in available family members. Array comparative genomic hybridization and droplet digital PCR were utilized for copy number variants (CNV) validation and characterization. We performed Human Phenotype Ontology (HPO)-based quantitative phenotypic analyses to dissect allele-specific phenotypic differences. RESULTS: Missense, nonsense, splice site, indels, and/or structural variants of NODAL were identified as potential causes of heterotaxy and other laterality defects in 33 CHD cases. We describe a recurrent complex indel variant for which the nucleic acid secondary structure predictions implicate secondary structure mutagenesis as a possible mechanism for formation. We identified two CNV deletion alleles spanning NODAL in two unrelated CHD cases. Furthermore, 17 CHD individuals were found (16/17 with known Hispanic ancestry) to have the c.778G > A:p.G260R NODAL missense variant which we propose reclassification from variant of uncertain significance (VUS) to likely pathogenic. Quantitative HPO-based analyses of the observed clinical phenotype for all cases with p.G260R variation, including heterozygous, homozygous, and compound heterozygous cases, reveal clustering of individuals with biallelic variation. This finding provides evidence for a genotypic-phenotypic correlation and an allele-specific gene dosage model. CONCLUSION: Our data further support a role for rare deleterious variants in NODAL as a cause for sporadic human laterality defects, expand the repertoire of observed anatomical complexity of potential cardiovascular anomalies, and implicate an allele specific gene dosage model.
Keywords: Animals; Arteries; Comparative Genomic Hybridization; Heart Defects, Congenital; Heterotaxy Syndrome; Humans; Phenotype; Transposition of Great Vessels

Variants in ZFX are associated with an X-linked neurodevelopmental disorder with recurrent facial gestalt. - Shepherdson, James L; Hutchison, Katie; Don, Dilan Wellalage; McGillivray, George; Choi, Tae-Ik; Allan, Carolyn A; Amor, David J; Banka, Siddharth; Basel, Donald G; Buch, Laura D; Carere, Deanna Alexis; Carroll, Renée; et al. (Am J Hum Genet, 2024)
Pathogenic variants in multiple genes on the X chromosome have been implicated in syndromic and non-syndromic intellectual disability disorders. ZFX on Xp22.11 encodes a transcription factor that has been linked to diverse processes including oncogenesis and development, but germline variants have not been characterized in association with disease. Here, we present clinical and molecular characterization of 18 individuals with germline ZFX variants. Exome or genome sequencing revealed 11 variants in 18 subjects (14 males and 4 females) from 16 unrelated families. Four missense variants were identified in 11 subjects, with seven truncation variants in the remaining individuals. Clinical findings included developmental delay/intellectual disability, behavioral abnormalities, hypotonia, and congenital anomalies. Overlapping and recurrent facial features were identified in all subjects, including thickening and medial broadening of eyebrows, variations in the shape of the face, external eye abnormalities, smooth and/or long philtrum, and ear abnormalities. Hyperparathyroidism was found in four families with missense variants, and enrichment of different tumor types was observed. In molecular studies, DNA-binding domain variants elicited differential expression of a small set of target genes relative to wild-type ZFX in cultured cells, suggesting a gain or loss of transcriptional activity. Additionally, a zebrafish model of ZFX loss displayed an altered behavioral phenotype, providing additional evidence for the functional significance of ZFX. Our clinical and experimental data support that variants in ZFX are associated with an X-linked intellectual disability syndrome characterized by a recurrent facial gestalt, neurocognitive and behavioral abnormalities, and an increased risk for congenital anomalies and hyperparathyroidism.
Keywords: Animals; Female; Humans; Hyperparathyroidism; Intellectual Disability; Male; Mutation, Missense; Neurodevelopmental Disorders; Phenotype; Transcription Factors; Zebrafish

Variant-specific pathophysiological mechanisms of AFF3 differently influence transcriptome profiles. - Bassani, Sissy; Chrast, Jacqueline; Ambrosini, Giovanna; Voisin, Norine; Schütz, Frédéric; Brusco, Alfredo; Sirchia, Fabio; Turban, Lydia; Schubert, Susanna; Abou Jamra, Rami; Schlump, Jan-Ulrich; DeMille, Desiree; et al. (Genome Med, 2024)
BACKGROUND: We previously described the KINSSHIP syndrome, an autosomal dominant disorder associated with intellectual disability (ID), mesomelic dysplasia and horseshoe kidney, caused by de novo variants in the degron of AFF3. Mouse knock-ins and overexpression in zebrafish provided evidence for a dominant-negative mode of action, wherein an increased level of AFF3 resulted in pathological effects. METHODS: Evolutionary constraints suggest that other modes-of-inheritance could be at play. We challenged this hypothesis by screening ID cohorts for individuals with predicted-to-be damaging variants in AFF3. We used both animal and cellular models to assess the deleteriousness of the identified variants. RESULTS: We identified an individual with a KINSSHIP-like phenotype carrying a de novo partial duplication of AFF3 further strengthening the hypothesis that an increased level of AFF3 is pathological. We also detected seventeen individuals displaying a milder syndrome with either heterozygous Loss-of-Function (LoF) or biallelic missense variants in AFF3. Consistent with semi-dominance, we discovered three patients with homozygous LoF and one compound heterozygote for a LoF and a missense variant, who presented more severe phenotypes than their heterozygous parents. Matching zebrafish knockdowns exhibit neurological defects that could be rescued by expressing human AFF3 mRNA, confirming their association with the ablation of aff3. Conversely, some of the human AFF3 mRNAs carrying missense variants identified in affected individuals did not rescue these phenotypes. Overexpression of mutated AFF3 mRNAs in zebrafish embryos produced a significant increase of abnormal larvae compared to wild-type overexpression further demonstrating deleteriousness. To further assess the effect of AFF3 variation, we profiled the transcriptome of fibroblasts from affected individuals and engineered isogenic cells harboring + / + , KINSSHIP/KINSSHIP, LoF/ + , LoF/LoF or KINSSHIP/LoF AFF3 genotypes. The expression of more than a third of the AFF3 bound loci is modified in either the KINSSHIP/KINSSHIP or the LoF/LoF lines. While the same pathways are affected, only about one third of the differentially expressed genes are common to the homozygote datasets, indicating that AFF3 LoF and KINSSHIP variants largely modulate transcriptomes differently, e.g. the DNA repair pathway displayed opposite modulation. CONCLUSIONS: Our results and the high pleiotropy shown by variation at this locus suggest that minute changes in AFF3 function are deleterious.
Keywords: Animals; Female; Humans; Intellectual Disability; Loss of Function Mutation; Male; Mutation, Missense; Phenotype; Transcriptome; Zebrafish

Aberrant activation of TCL1A promotes stem cell expansion in clonal haematopoiesis. - Weinstock, Joshua S; Gopakumar, Jayakrishnan; Burugula, Bala Bharathi; Uddin, Md Mesbah; Jahn, Nikolaus; Belk, Julia A; Bouzid, Hind; Daniel, Bence; Miao, Zhuang; Ly, Nghi; Mack, Taralynn M; Luna, Sofia E; et al. (Nature, 2023)
Mutations in a diverse set of driver genes increase the fitness of haematopoietic stem cells (HSCs), leading to clonal haematopoiesis. These lesions are precursors for blood cancers, but the basis of their fitness advantage remains largely unknown, partly owing to a paucity of large cohorts in which the clonal expansion rate has been assessed by longitudinal sampling. Here, to circumvent this limitation, we developed a method to infer the expansion rate from data from a single time point. We applied this method to 5,071 people with clonal haematopoiesis. A genome-wide association study revealed that a common inherited polymorphism in the TCL1A promoter was associated with a slower expansion rate in clonal haematopoiesis overall, but the effect varied by driver gene. Those carrying this protective allele exhibited markedly reduced growth rates or prevalence of clones with driver mutations in TET2, ASXL1, SF3B1 and SRSF2, but this effect was not seen in clones with driver mutations in DNMT3A. TCL1A was not expressed in normal or DNMT3A-mutated HSCs, but the introduction of mutations in TET2 or ASXL1 led to the expression of TCL1A protein and the expansion of HSCs in vitro. The protective allele restricted TCL1A expression and expansion of mutant HSCs, as did experimental knockdown of TCL1A expression. Forced expression of TCL1A promoted the expansion of human HSCs in vitro and mouse HSCs in vivo. Our results indicate that the fitness advantage of several commonly mutated driver genes in clonal haematopoiesis may be mediated by TCL1A activation.
Keywords: Alleles; Animals; Clonal Hematopoiesis; Genome-Wide Association Study; Hematopoiesis; Hematopoietic Stem Cells; Humans; Mice; Mutation; Promoter Regions, Genetic

Bi-allelic variants in the ESAM tight-junction gene cause a neurodevelopmental disorder associated with fetal intracranial hemorrhage. - Lecca, Mauro; Pehlivan, Davut; Suñer, Damià Heine; Weiss, Karin; Coste, Thibault; Zweier, Markus; Oktay, Yavuz; Danial-Farran, Nada; Rosti, Vittorio; Bonasoni, Maria Paola; Malara, Alessandro; Contrò, Gianluca; et al. (Am J Hum Genet, 2023)
The blood-brain barrier (BBB) is an essential gatekeeper for the central nervous system and incidence of neurodevelopmental disorders (NDDs) is higher in infants with a history of intracerebral hemorrhage (ICH). We discovered a rare disease trait in thirteen individuals, including four fetuses, from eight unrelated families associated with homozygous loss-of-function variant alleles of ESAM which encodes an endothelial cell adhesion molecule. The c.115del (p.Arg39Glyfs33) variant, identified in six individuals from four independent families of Southeastern Anatolia, severely impaired the in vitro tubulogenic process of endothelial colony-forming cells, recapitulating previous evidence in null mice, and caused lack of ESAM expression in the capillary endothelial cells of damaged brain. Affected individuals with bi-allelic ESAM variants showed profound global developmental delay/unspecified intellectual disability, epilepsy, absent or severely delayed speech, varying degrees of spasticity, ventriculomegaly, and ICH/cerebral calcifications, the latter being also observed in the fetuses. Phenotypic traits observed in individuals with bi-allelic ESAM variants overlap very closely with other known conditions characterized by endothelial dysfunction due to mutation of genes encoding tight junction molecules. Our findings emphasize the role of brain endothelial dysfunction in NDDs and contribute to the expansion of an emerging group of diseases that we propose to rename as "tightjunctionopathies."
Keywords: Alleles; Animals; Brain Diseases; Cell Adhesion Molecules; Endothelial Cells; Humans; Intracranial Hemorrhages; Mice; Nervous System Malformations; Neurodevelopmental Disorders; Tight Junctions

Brain monoamine vesicular transport disease caused by homozygous SLC18A2 variants: A study in 42 affected individuals. - Saida, Ken; Maroofian, Reza; Sengoku, Toru; Mitani, Tadahiro; Pagnamenta, Alistair T; Marafi, Dana; Zaki, Maha S; O'Brien, Thomas J; Karimiani, Ehsan Ghayoor; Kaiyrzhanov, Rauan; Takizawa, Marina; Ohori, Sachiko; et al. (Genet Med, 2023)
PURPOSE: Brain monoamine vesicular transport disease is an infantile-onset movement disorder that mimics cerebral palsy. In 2013, the homozygous SLC18A2 variant, p.Pro387Leu, was first reported as a cause of this rare disorder, and dopamine agonists were efficient for treating affected individuals from a single large family. To date, only 6 variants have been reported. In this study, we evaluated genotype-phenotype correlations in individuals with biallelic SLC18A2 variants. METHODS: A total of 42 affected individuals with homozygous SLC18A2 variant alleles were identified. We evaluated genotype-phenotype correlations and the missense variants in the affected individuals based on the structural modeling of rat VMAT2 encoded by Slc18a2, with cytoplasm- and lumen-facing conformations. A Caenorhabditis elegans model was created for functional studies. RESULTS: A total of 19 homozygous SLC18A2 variants, including 3 recurrent variants, were identified using exome sequencing. The affected individuals typically showed global developmental delay, hypotonia, dystonia, oculogyric crisis, and autonomic nervous system involvement (temperature dysregulation/sweating, hypersalivation, and gastrointestinal dysmotility). Among the 58 affected individuals described to date, 16 (28%) died before the age of 13 years. Of the 17 patients with p.Pro237His, 9 died, whereas all 14 patients with p.Pro387Leu survived. Although a dopamine agonist mildly improved the disease symptoms in 18 of 21 patients (86%), some affected individuals with p.Ile43Phe and p.Pro387Leu showed milder phenotypes and presented prolonged survival even without treatment. The C. elegans model showed behavioral abnormalities. CONCLUSION: These data expand the phenotypic and genotypic spectra of SLC18A2-related disorders.
Keywords: Amines; Animals; Brain; Brain Diseases; Caenorhabditis elegans; Dystonia; Humans; Movement Disorders; Rats; Vesicular Monoamine Transport Proteins

Ceramide compensation by ceramide synthases preserves retinal function and structure in a retinal dystrophy mouse model. - Qian, Xinye; Srinivasan, Tanmay; He, Jessica; Lu, Jiaxiong; Jin, Yan; Gu, Haiwei; Rui Chen (Dis Model Mech, 2023)
Increasing evidence has supported the role of ceramide as a mediator of photoreceptor dysfunction or cell death in ceramide accumulation and deficiency contexts. TLCD3B, a non-canonical ceramide synthase, was previously identified in addition to the six canonical ceramide synthases (CerSs), and the Tlcd3b-/- mouse model exhibited both retinal dysfunction and degeneration. As previous canonical CerS-deficient mouse models failed to display retinal degeneration, the mechanisms of how TLCD3B interacts with CerSs have not been investigated. Additionally, as the ceramide profile of each CerS is distinct, it is unclear whether the overall level or the homeostasis of different ceramide species plays a critical role in photoreceptor degeneration. Interactions between TLCD3B with canonical CerSs expressed in the retina were examined by subretinally injecting recombinant adeno-associated virus 8 vectors containing the Cers2 (rAAV8-CerS2), Cers4 (rAAV8-CerS4) and Cers5 (rAAV8-CerS5) genes. Injection of all three rAAV8-CerS vectors restored retinal functions as indicated by improved electroretinogram responses, but only rAAV8-CerS5 successfully retained retinal morphology in Tlcd3b-/- mice. CerSs and TLCD3B played partially redundant roles. Additionally, rather than acting as an integral entity, different ceramide species had different impacts on retinal cells, suggesting that the maintenance of the overall ceramide profile is critical for retinal function.
Keywords: Animals; Ceramides; Mice; Oxidoreductases; Retina; Retinal Dystrophies

Chimeric RNAs reveal putative neoantigen peptides for developing tumor vaccines for breast cancer. - Mistretta, Brandon; Rankothgedera, Sakuni; Castillo, Micah; Rao, Mitchell; Holloway, Kimberly; Bhardwaj, Anjana; El Noafal, Maha; Albarracin, Constance; El-Zein, Randa; Rezaei, Hengameh; Su, Xiaoping; Akbani, Rehan; et al. (Front Immunol, 2023)
INTRODUCTION: We present here a strategy to identify immunogenic neoantigen candidates from unique amino acid sequences at the junctions of fusion proteins which can serve as targets in the development of tumor vaccines for the treatment of breastcancer. METHOD: We mined the sequence reads of breast tumor tissue that are usually discarded as discordant paired-end reads and discovered cancer specific fusion transcripts using tissue from cancer free controls as reference. Binding affinity predictions of novel peptide sequences crossing the fusion junction were analyzed by the MHC Class I binding predictor, MHCnuggets. CD8+ T cell responses against the 15 peptides were assessed through in vitro Enzyme Linked Immunospot (ELISpot). RESULTS: We uncovered 20 novel fusion transcripts from 75 breast tumors of 3 subtypes: TNBC, HER2+, and HR+. Of these, the NSFP1-LRRC37A2 fusion transcript was selected for further study. The 3833 bp chimeric RNA predicted by the consensus fusion junction sequence is consistent with a read-through transcription of the 5'-gene NSFP1-Pseudo gene NSFP1 (NSFtruncation at exon 12/13) followed by trans-splicing to connect withLRRC37A2 located immediately 3' through exon 1/2. A total of 15 different 8-mer neoantigen peptides discovered from the NSFP1 and LRRC37A2 truncations were predicted to bind to a total of 35 unique MHC class I alleles with a binding affinity of IC50<500nM.); 1 of which elicited a robust immune response. CONCLUSION: Our data provides a framework to identify immunogenic neoantigen candidates from fusion transcripts and suggests a potential vaccine strategy to target the immunogenic neopeptides in patients with tumors carrying the NSFP1-LRRC37A2 fusion.
Keywords: Animals; Breast; Breast Neoplasms; Cancer Vaccines; Female; Genes, MHC Class I; Humans; Mammary Neoplasms, Animal

Clonal haematopoiesis and risk of chronic liver disease. - Wong, Waihay J; Emdin, Connor; Bick, Alexander G; Zekavat, Seyedeh M; Niroula, Abhishek; Pirruccello, James P; Dichtel, Laura; Griffin, Gabriel; Uddin, Md Mesbah; Gibson, Christopher J; Kovalcik, Veronica; Lin, Amy E; et al. (Nature, 2023)
Chronic liver disease is a major public health burden worldwide. Although different aetiologies and mechanisms of liver injury exist, progression of chronic liver disease follows a common pathway of liver inflammation, injury and fibrosis. Here we examined the association between clonal haematopoiesis of indeterminate potential (CHIP) and chronic liver disease in 214,563 individuals from 4 independent cohorts with whole-exome sequencing data (Framingham Heart Study, Atherosclerosis Risk in Communities Study, UK Biobank and Mass General Brigham Biobank). CHIP was associated with an increased risk of prevalent and incident chronic liver disease (odds ratio = 2.01, 95% confidence interval (95% CI) [1.46, 2.79]; P < 0.001). Individuals with CHIP were more likely to demonstrate liver inflammation and fibrosis detectable by magnetic resonance imaging compared to those without CHIP (odds ratio = 1.74, 95% CI [1.16, 2.60]; P = 0.007). To assess potential causality, Mendelian randomization analyses showed that genetic predisposition to CHIP was associated with a greater risk of chronic liver disease (odds ratio = 2.37, 95% CI [1.57, 3.6]; P < 0.001). In a dietary model of non-alcoholic steatohepatitis, mice transplanted with Tet2-deficient haematopoietic cells demonstrated more severe liver inflammation and fibrosis. These effects were mediated by the NLRP3 inflammasome and increased levels of expression of downstream inflammatory cytokines in Tet2-deficient macrophages. In summary, clonal haematopoiesis is associated with an elevated risk of liver inflammation and chronic liver disease progression through an aberrant inflammatory response.
Keywords: Animals; Clonal Hematopoiesis; Disease Progression; Disease Susceptibility; Hepatitis; Inflammation; Liver Cirrhosis; Mice; Non-alcoholic Fatty Liver Disease; Odds Ratio

Complex Evolutionary History With Extensive Ancestral Gene Flow in an African Primate Radiation. - Jensen, Axel; Swift, Frances; de Vries, Dorien; Beck, Robin M D; Kuderna, Lukas F K; Knauf, Sascha; Chuma, Idrissa S; Keyyu, Julius D; Kitchener, Andrew C; Farh, Kyle; Jeffrey Rogers; Marques-Bonet, Tomas; et al. (Mol Biol Evol, 2023)
Understanding the drivers of speciation is fundamental in evolutionary biology, and recent studies highlight hybridization as an important evolutionary force. Using whole-genome sequencing data from 22 species of guenons (tribe Cercopithecini), one of the world's largest primate radiations, we show that rampant gene flow characterizes their evolutionary history and identify ancient hybridization across deeply divergent lineages that differ in ecology, morphology, and karyotypes. Some hybridization events resulted in mitochondrial introgression between distant lineages, likely facilitated by cointrogression of coadapted nuclear variants. Although the genomic landscapes of introgression were largely lineage specific, we found that genes with immune functions were overrepresented in introgressing regions, in line with adaptive introgression, whereas genes involved in pigmentation and morphology may contribute to reproductive isolation. In line with reports from other systems that hybridization might facilitate diversification, we find that some of the most species-rich guenon clades are of admixed origin. This study provides important insights into the prevalence, role, and outcomes of ancestral hybridization in a large mammalian radiation.
Keywords: Animals; Biological Evolution; Gene Flow; Genome; Genomics; Hybridization, Genetic; Mammals; Phylogeny; Primates

FOXI3 pathogenic variants cause one form of craniofacial microsomia. - Mao, Ke; Borel, Christelle; Ansar, Muhammad; Jolly, Angad; Makrythanasis, Periklis; Froehlich, Christine; Iwaszkiewicz, Justyna; Wang, Bingqing; Xu, Xiaopeng; Li, Qiang; Blanc, Xavier; Zhu, Hao; et al. (Nat Commun, 2023)
Craniofacial microsomia (CFM; also known as Goldenhar syndrome), is a craniofacial developmental disorder of variable expressivity and severity with a recognizable set of abnormalities. These birth defects are associated with structures derived from the first and second pharyngeal arches, can occur unilaterally and include ear dysplasia, microtia, preauricular tags and pits, facial asymmetry and other malformations. The inheritance pattern is controversial, and the molecular etiology of this syndrome is largely unknown. A total of 670 patients belonging to unrelated pedigrees with European and Chinese ancestry with CFM, are investigated. We identify 18 likely pathogenic variants in 21 probands (3.1%) in FOXI3. Biochemical experiments on transcriptional activity and subcellular localization of the likely pathogenic FOXI3 variants, and knock-in mouse studies strongly support the involvement of FOXI3 in CFM. Our findings indicate autosomal dominant inheritance with reduced penetrance, and/or autosomal recessive inheritance. The phenotypic expression of the FOXI3 variants is variable. The penetrance of the likely pathogenic variants in the seemingly dominant form is reduced, since a considerable number of such variants in affected individuals were inherited from non-affected parents. Here we provide suggestive evidence that common variation in the FOXI3 allele in trans with the pathogenic variant could modify the phenotypic severity and accounts for the incomplete penetrance.
Keywords: Animals; Facial Asymmetry; Forkhead Transcription Factors; Goldenhar Syndrome; Mice; Pedigree

Functional characterization of age-dependent p16 epimutation reveals biological drivers and therapeutic targets for colorectal cancer. - Yang, Li; Chen, Xiaomin; Lee, Christy; Shi, Jiejun; Lawrence, Emily B; Zhang, Lanjing; Yumei Li; Gao, Nan; Jung, Sung Yun; Creighton, Chad J; Li, Jingyi Jessica; Cui, Ya; et al. (J Exp Clin Cancer Res, 2023)
BACKGROUND: Methylation of the p16 promoter resulting in epigenetic gene silencing-known as p16 epimutation-is frequently found in human colorectal cancer and is also common in normal-appearing colonic mucosa of aging individuals. Thus, to improve clinical care of colorectal cancer (CRC) patients, we explored the role of age-related p16 epimutation in intestinal tumorigenesis. METHODS: We established a mouse model that replicates two common genetic and epigenetic events observed in human CRCs: Apc mutation and p16 epimutation. We conducted long-term survival and histological analysis of tumor development and progression. Colonic epithelial cells and tumors were collected from mice and analyzed by RNA sequencing (RNA-seq), quantitative PCR, and flow cytometry. We performed single-cell RNA sequencing (scRNA-seq) to characterize tumor-infiltrating immune cells throughout tumor progression. We tested whether anti-PD-L1 immunotherapy affects overall survival of tumor-bearing mice and whether inhibition of both epigenetic regulation and immune checkpoint is more efficacious. RESULTS: Mice carrying combined Apc mutation and p16 epimutation had significantly shortened survival and increased tumor growth compared to those with Apc mutation only. Intriguingly, colon tumors with p16 epimutation exhibited an activated interferon pathway, increased expression of programmed death-ligand 1 (Pdl1), and enhanced infiltration of immune cells. scRNA-seq further revealed the presence of Foxp3 Tregs and γδT17 cells, which contribute to an immunosuppressive tumor microenvironment (TME). Furthermore, we showed that a combined therapy using an inhibitor of DNA methylation and a PD-L1 immune checkpoint inhibitor is more effective for improving survival in tumor-bearing mice than blockade of either pathway alone. CONCLUSIONS: Our study demonstrated that age-dependent p16 epimutation creates a permissive microenvironment for malignant transformation of polyps to colon cancer. Our findings provide a mechanistic rationale for future targeted therapy in patients with p16 epimutation.
Keywords: Animals; B7-H1 Antigen; Carcinogenesis; Cell Transformation, Neoplastic; Colonic Neoplasms; Colorectal Neoplasms; DNA Methylation; Epigenesis, Genetic; Humans; Mice; Tumor Microenvironment

Gene augmentation therapy to rescue degenerative photoreceptors in a Cwc27 mutant mouse model. - Lu, Jiaxiong; Zheng, Karen Q; Bertrand, Renae Elaine; Quinlan, Joseph; Ferdous, Salma; Srinivasan, Tanmay; Oh, Soo; Wang, Keqing; Rui Chen (Exp Eye Res, 2023)
Previous reports have demonstrated that defects in the spliceosome-associated protein CWC27 can lead to the degeneration of retinal cells in Cwc27 mutant mouse models. However, it is unknown whether gene replacement therapy can rescue this phenotype. The purpose of this study was to evaluate whether AAV based gene therapy could rescue the retinal degeneration observed in Cwc27 mutant mice. By 6 months of age, Cwc27 mutant mice show a retinal degenerative phenotype, including morphological and functional abnormalities, primarily driven by the death of photoreceptors. We hypothesize that subretinal injection of AAV8 to drive exogenous CWC27 protein expression will improve the retinal phenotype. We evaluated these improvements after gene therapy with electroretinography (ERG) and histology, either hematoxylin and eosin (H&E) or immunostaining. In this study, we demonstrated that subretinal injection of AAV8-GRK-Cwc27-FLAG in mutant mice can improve the functionality and morphology of the retina. Immunostaining analyses revealed a notable decrease in photoreceptor degeneration, including cone cell degeneration, in the AAV-injected eyes compared to the PBS-injected eyes. Based on these results, gene replacement therapy could be a promising method for treating retinal degeneration caused by mutations in Cwc27.
Keywords: Animals; Disease Models, Animal; Electroretinography; Genetic Therapy; Genetic Vectors; Mice; Retina; Retinal Cone Photoreceptor Cells; Retinal Degeneration

Genome-wide coancestry reveals details of ancient and recent male-driven reticulation in baboons. - Sørensen, Erik F; R. Alan Harris; Zhang, Liye; Raveendran, Muthuswamy; Kuderna, Lukas F K; Walker, Jerilyn A; Storer, Jessica M; Kuhlwilm, Martin; Fontsere, Claudia; Seshadri, Lakshmi; Bergey, Christina M; Burrell, Andrew S; et al. (Science, 2023)
Baboons (genus ) are a morphologically and behaviorally diverse clade of catarrhine monkeys that have experienced hybridization between phenotypically and genetically distinct phylogenetic species. We used high-coverage whole-genome sequences from 225 wild baboons representing 19 geographic localities to investigate population genomics and interspecies gene flow. Our analyses provide an expanded picture of evolutionary reticulation among species and reveal patterns of population structure within and among species, including differential admixture among conspecific populations. We describe the first example of a baboon population with a genetic composition that is derived from three distinct lineages. The results reveal processes, both ancient and recent, that produced the observed mismatch between phylogenetic relationships based on matrilineal, patrilineal, and biparental inheritance. We also identified several candidate genes that may contribute to species-specific phenotypes.
Keywords: Animals; Biological Evolution; Gene Flow; Male; Papio; Phenotype; Phylogeny; Sex Characteristics; Species Specificity

Genomic analysis of two phlebotomine sand fly vectors of Leishmania from the New and Old World. - Labbé, Frédéric; Abdeladhim, Maha; Abrudan, Jenica; Araki, Alejandra Saori; Araujo, Ricardo N; Arensburger, Peter; Benoit, Joshua B; Brazil, Reginaldo Pecanha; Bruno, Rafaela V; Bueno da Silva Rivas, Gustavo; Carvalho de Abreu, Vinicius; Charamis, Jason; et al. (PLoS Negl Trop Dis, 2023)
Phlebotomine sand flies are of global significance as important vectors of human disease, transmitting bacterial, viral, and protozoan pathogens, including the kinetoplastid parasites of the genus Leishmania, the causative agents of devastating diseases collectively termed leishmaniasis. More than 40 pathogenic Leishmania species are transmitted to humans by approximately 35 sand fly species in 98 countries with hundreds of millions of people at risk around the world. No approved efficacious vaccine exists for leishmaniasis and available therapeutic drugs are either toxic and/or expensive, or the parasites are becoming resistant to the more recently developed drugs. Therefore, sand fly and/or reservoir control are currently the most effective strategies to break transmission. To better understand the biology of sand flies, including the mechanisms involved in their vectorial capacity, insecticide resistance, and population structures we sequenced the genomes of two geographically widespread and important sand fly vector species: Phlebotomus papatasi, a vector of Leishmania parasites that cause cutaneous leishmaniasis, (distributed in Europe, the Middle East and North Africa) and Lutzomyia longipalpis, a vector of Leishmania parasites that cause visceral leishmaniasis (distributed across Central and South America). We categorized and curated genes involved in processes important to their roles as disease vectors, including chemosensation, blood feeding, circadian rhythm, immunity, and detoxification, as well as mobile genetic elements. We also defined gene orthology and observed micro-synteny among the genomes. Finally, we present the genetic diversity and population structure of these species in their respective geographical areas. These genomes will be a foundation on which to base future efforts to prevent vector-borne transmission of Leishmania parasites.
Keywords: Animals; Genomics; Humans; Leishmania; Leishmaniasis, Cutaneous; Phlebotomus; Psychodidae

A global catalog of whole-genome diversity from 233 primate species. - Kuderna, Lukas F K; Gao, Hong; Janiak, Mareike C; Kuhlwilm, Martin; Orkin, Joseph D; Bataillon, Thomas; Manu, Shivakumara; Valenzuela, Alejandro; Bergman, Juraj; Rousselle, Marjolaine; Silva, Felipe Ennes; Agueda, Lidia; et al. (Science, 2023)
The rich diversity of morphology and behavior displayed across primate species provides an informative context in which to study the impact of genomic diversity on fundamental biological processes. Analysis of that diversity provides insight into long-standing questions in evolutionary and conservation biology and is urgent given severe threats these species are facing. Here, we present high-coverage whole-genome data from 233 primate species representing 86% of genera and all 16 families. This dataset was used, together with fossil calibration, to create a nuclear DNA phylogeny and to reassess evolutionary divergence times among primate clades. We found within-species genetic diversity across families and geographic regions to be associated with climate and sociality, but not with extinction risk. Furthermore, mutation rates differ across species, potentially influenced by effective population sizes. Lastly, we identified extensive recurrence of missense mutations previously thought to be human specific. This study will open a wide range of research avenues for future primate genomic research.
Keywords: Animals; Biological Evolution; Genetic Variation; Genome; Humans; Mutation Rate; Phylogeny; Population Density; Primates

Global Gene Expression Analysis Reveals Complex Cuticle Organization of the Tribolium Compound Eye. - Chen, Qing; Sasikala-Appukuttan, Arun Kirshna; Husain, Zahabiya; Shrivastava, Anura; Spain, Marla; Sendler, Edward D; Daines, Bryce; Fischer, Stefan; Rui Chen; Cook, Tiffany A; Friedrich, Markus (Genome Biol Evol, 2023)
The red flour beetle Tribolium castaneum is a resource-rich model for genomic and developmental studies. To extend previous studies on Tribolium eye development, we produced transcriptomes for normal-eyed and eye-depleted heads of pupae and adults to identify differentially transcript-enriched (DE) genes in the visual system. Unexpectedly, cuticle-related genes were the largest functional class in the pupal compound eye DE gene population, indicating differential enrichment in three distinct cuticle components: clear lens facet cuticle, highly melanized cuticle of the ocular diaphragm, which surrounds the Tribolium compound eye for internal fortification, and newly identified facet margins of the tanned cuticle, possibly enhancing external fortification. Phylogenetic, linkage, and high-throughput gene knockdown data suggest that most cuticle proteins (CPs) expressed in the Tribolium compound eye stem from the deployment of ancient CP genes. Consistent with this, TcasCPR15, which we identified as the major lens CP gene in Tribolium, is a beetle-specific but pleiotropic paralog of the ancient CPR RR-2 CP gene family. The less abundant yet most likely even more lens-specific TcasCP63 is a member of a sprawling family of noncanonical CP genes, documenting a role of local gene family expansions in the emergence of the Tribolium compound eye CP repertoire. Comparisons with Drosophila and the mosquito Anopheles gambiae reveal a steady turnover of lens-enriched CP genes during insect evolution.
Keywords: Animals; Gene Expression Profiling; Insect Proteins; Phylogeny; RNA Interference; Transcriptome; Tribolium

The landscape of tolerated genetic variation in humans and primates. - Gao, Hong; Hamp, Tobias; Ede, Jeffrey; Schraiber, Joshua G; McRae, Jeremy; Singer-Berk, Moriel; Yang, Yanshen; Dietrich, Anastasia S D; Fiziev, Petko P; Kuderna, Lukas F K; Sundaram, Laksshman; Wu, Yibing; et al. (Science, 2023)
Personalized genome sequencing has revealed millions of genetic differences between individuals, but our understanding of their clinical relevance remains largely incomplete. To systematically decipher the effects of human genetic variants, we obtained whole-genome sequencing data for 809 individuals from 233 primate species and identified 4.3 million common protein-altering variants with orthologs in humans. We show that these variants can be inferred to have nondeleterious effects in humans based on their presence at high allele frequencies in other primate populations. We use this resource to classify 6% of all possible human protein-altering variants as likely benign and impute the pathogenicity of the remaining 94% of variants with deep learning, achieving state-of-the-art accuracy for diagnosing pathogenic variants in patients with genetic diseases.
Keywords: Animals; Base Sequence; Gene Frequency; Genetic Variation; Humans; Primates; Whole Genome Sequencing

Molecular basis of retinal remodeling in a zebrafish model of retinitis pigmentosa. - Santhanam, Abirami; Shihabeddin, Eyad; Wei, Haichao; Wu, Jiaqian; O'Brien, John (Cell Mol Life Sci, 2023)
A hallmark of inherited retinal degenerative diseases such as retinitis pigmentosa (RP) is progressive structural and functional remodeling of the remaining retinal cells as photoreceptors degenerate. Extensive remodeling of the retina stands as a barrier for the successful implementation of strategies to restore vision. To understand the molecular basis of remodeling, we performed analyses of single-cell transcriptome data from adult zebrafish retina of wild type AB strain (WT) and a P23H mutant rhodopsin transgenic model of RP with continuous degeneration and regeneration. Retinas from both female and male fish were pooled to generate each library, combining data from both sexes. We provide a benchmark atlas of retinal cell type transcriptomes in zebrafish and insight into how each retinal cell type is affected in the P23H model. Oxidative stress is found throughout the retina, with increases in reliance on oxidative metabolism and glycolysis in the affected rods as well as cones, bipolar cells, and retinal ganglion cells. There is also transcriptional evidence for widespread synaptic remodeling and enhancement of glutamatergic transmission in the inner retina. Notably, changes in circadian rhythm regulation are detected in cones, bipolar cells, and retinal pigmented epithelium. We also identify the transcriptomic signatures of retinal progenitor cells and newly formed rods essential for the regenerative process. This comprehensive transcriptomic analysis provides a molecular road map to understand how the retina remodels in the context of chronic retinal degeneration with ongoing regeneration.
Keywords: Animals; Disease Models, Animal; Female; Male; Retina; Retinal Degeneration; Retinal Rod Photoreceptor Cells; Retinitis Pigmentosa; Zebrafish

Monoallelic variation in DHX9, the gene encoding the DExH-box helicase DHX9, underlies neurodevelopment disorders and Charcot-Marie-Tooth disease. - Calame, Daniel G; Guo, Tianyu; Wang, Chen; Garrett, Lillian; Jolly, Angad; Dawood, Moez; Kurolap, Alina; Henig, Noa Zunz; Fatih, Jawid M; Herman, Isabella; Du, Haowei; Mitani, Tadahiro; et al. (Am J Hum Genet, 2023)
DExD/H-box RNA helicases (DDX/DHX) are encoded by a large paralogous gene family; in a subset of these human helicase genes, pathogenic variation causes neurodevelopmental disorder (NDD) traits and cancer. DHX9 encodes a BRCA1-interacting nuclear helicase regulating transcription, R-loops, and homologous recombination and exhibits the highest mutational constraint of all DDX/DHX paralogs but remains unassociated with disease traits in OMIM. Using exome sequencing and family-based rare-variant analyses, we identified 20 individuals with de novo, ultra-rare, heterozygous missense or loss-of-function (LoF) DHX9 variant alleles. Phenotypes ranged from NDDs to the distal symmetric polyneuropathy axonal Charcot-Marie-Tooth disease (CMT2). Quantitative Human Phenotype Ontology (HPO) analysis demonstrated genotype-phenotype correlations with LoF variants causing mild NDD phenotypes and nuclear localization signal (NLS) missense variants causing severe NDD. We investigated DHX9 variant-associated cellular phenotypes in human cell lines. Whereas wild-type DHX9 was restricted to the nucleus, NLS missense variants abnormally accumulated in the cytoplasm. Fibroblasts from an individual with an NLS variant also showed abnormal cytoplasmic DHX9 accumulation. CMT2-associated missense variants caused aberrant nucleolar DHX9 accumulation, a phenomenon previously associated with cellular stress. Two NDD-associated variants, p.Gly411Glu and p.Arg761Gln, altered DHX9 ATPase activity. The severe NDD-associated variant p.Arg141Gln did not affect DHX9 localization but instead increased R-loop levels and double-stranded DNA breaks. Dhx9 mice exhibited hypoactivity in novel environments, tremor, and sensorineural hearing loss. All together, these results establish DHX9 as a critical regulator of mammalian neurodevelopment and neuronal homeostasis.
Keywords: Animals; Cell Line; Charcot-Marie-Tooth Disease; DEAD-box RNA Helicases; Dichlorodiphenyl Dichloroethylene; DNA Helicases; Humans; Mammals; Mice; Neoplasm Proteins; Neurodevelopmental Disorders

Phylogenomic analyses provide insights into primate evolution. - Shao, Yong; Zhou, Long; Li, Fang; Zhao, Lan; Zhang, Bao-Lin; Shao, Feng; Chen, Jia-Wei; Chen, Chun-Yan; Bi, Xupeng; Zhuang, Xiao-Lin; Zhu, Hong-Liang; Hu, Jiang; et al. (Science, 2023)
Comparative analysis of primate genomes within a phylogenetic context is essential for understanding the evolution of human genetic architecture and primate diversity. We present such a study of 50 primate species spanning 38 genera and 14 families, including 27 genomes first reported here, with many from previously less well represented groups, the New World monkeys and the Strepsirrhini. Our analyses reveal heterogeneous rates of genomic rearrangement and gene evolution across primate lineages. Thousands of genes under positive selection in different lineages play roles in the nervous, skeletal, and digestive systems and may have contributed to primate innovations and adaptations. Our study reveals that many key genomic innovations occurred in the Simiiformes ancestral node and may have had an impact on the adaptive radiation of the Simiiformes and human evolution.
Keywords: Animals; Brain; Evolution, Molecular; Gene Rearrangement; Genome; Genomics; Humans; Phylogeny; Primates

PLS3 missense variants affecting the actin-binding domains cause X-linked congenital diaphragmatic hernia and body-wall defects. - Petit, Florence; Longoni, Mauro; Wells, Julie; Maser, Richard S; Bogenschutz, Eric L; Dysart, Matthew J; Contreras, Hannah T M; Frénois, Frederic; Pober, Barbara R; Clark, Robin D; Giampietro, Philip F; Ropers, Hilger H; et al. (Am J Hum Genet, 2023)
Congenital diaphragmatic hernia (CDH) is a relatively common and genetically heterogeneous structural birth defect associated with high mortality and morbidity. We describe eight unrelated families with an X-linked condition characterized by diaphragm defects, variable anterior body-wall anomalies, and/or facial dysmorphism. Using linkage analysis and exome or genome sequencing, we found that missense variants in plastin 3 (PLS3), a gene encoding an actin bundling protein, co-segregate with disease in all families. Loss-of-function variants in PLS3 have been previously associated with X-linked osteoporosis (MIM: 300910), so we used in silico protein modeling and a mouse model to address these seemingly disparate clinical phenotypes. The missense variants in individuals with CDH are located within the actin-binding domains of the protein but are not predicted to affect protein structure, whereas the variants in individuals with osteoporosis are predicted to result in loss of function. A mouse knockin model of a variant identified in one of the CDH-affected families, c.1497G>C (p.Trp499Cys), shows partial perinatal lethality and recapitulates the key findings of the human phenotype, including diaphragm and abdominal-wall defects. Both the mouse model and one adult human male with a CDH-associated PLS3 variant were observed to have increased rather than decreased bone mineral density. Together, these clinical and functional data in humans and mice reveal that specific missense variants affecting the actin-binding domains of PLS3 might have a gain-of-function effect and cause a Mendelian congenital disorder.
Keywords: Actins; Adult; Animals; Hernias, Diaphragmatic, Congenital; Humans; Male; Mice; Mutation, Missense; Osteoporosis

A single cell genomics atlas of the Drosophila larval eye reveals distinct photoreceptor developmental timelines. - Bollepogu Raja, Komal Kumar; Yeung, Kelvin; Shim, Yoon-Kyung; Yumei Li; Rui Chen; Mardon, Graeme (Nat Commun, 2023)
The Drosophila eye is a powerful model system to study the dynamics of cell differentiation, cell state transitions, cell maturation, and pattern formation. However, a high-resolution single cell genomics resource that accurately profiles all major cell types of the larval eye disc and their spatiotemporal relationships is lacking. Here, we report transcriptomic and chromatin accessibility data for all known cell types in the developing eye. Photoreceptors appear as strands of cells that represent their dynamic developmental timelines. As photoreceptor subtypes mature, they appear to assume a common transcriptomic profile that is dominated by genes involved in axon function. We identify cell type maturation genes, enhancers, and potential regulators, as well as genes with distinct R3 or R4 photoreceptor specific expression. Finally, we observe that the chromatin accessibility between cones and photoreceptors is distinct. These single cell genomics atlases will greatly enhance the power of the Drosophila eye as a model system.
Keywords: Animals; Ascomycota; Cell Differentiation; Chromatin; Drosophila; Genomics; Larva

SVhound: detection of regions that harbor yet undetected structural variation. - Paulin, Luis F; Raveendran, Muthuswamy; R. Alan Harris; Jeffrey Rogers; von Haeseler, Arndt; Fritz J Sedlazeck (BMC Bioinformatics, 2023)
BACKGROUND: Recent population studies are ever growing in number of samples to investigate the diversity of a population or species. These studies reveal new polymorphism that lead to important insights into the mechanisms of evolution, but are also important for the interpretation of these variations. Nevertheless, while the full catalog of variations across entire species remains unknown, we can predict which regions harbor additional not yet detected variations and investigate their properties, thereby enhancing the analysis for potentially missed variants. RESULTS: To achieve this we developed SVhound ( https://github.com/lfpaulin/SVhound ), which based on a population level SVs dataset can predict regions that harbor unseen SV alleles. We tested SVhound using subsets of the 1000 genomes project data and showed that its correlation (average correlation of 2800 tests r = 0.7136) is high to the full data set. Next, we utilized SVhound to investigate potentially missed or understudied regions across 1KGP and CCDG. Lastly we also apply SVhound on a small and novel SV call set for rhesus macaque (Macaca mulatta) and discuss the impact and choice of parameters for SVhound. CONCLUSIONS: SVhound is a unique method to identify potential regions that harbor hidden diversity in model and non model organisms and can also be potentially used to ensure high quality of SV call sets.
Keywords: Alleles; Animals; Genome, Human; Genomic Structural Variation; High-Throughput Nucleotide Sequencing; Humans; Macaca mulatta; Polymorphism, Genetic; Software

Transcriptome- and proteome-wide association studies nominate determinants of kidney function and damage. - Schlosser, Pascal; Zhang, Jingning; Liu, Hongbo; Surapaneni, Aditya L; Rhee, Eugene P; Arking, Dan E; Yu, Bing; Eric Boerwinkle; Welling, Paul A; Chatterjee, Nilanjan; Susztak, Katalin; Coresh, Josef; et al. (Genome Biol, 2023)
BACKGROUND: The pathophysiological causes of kidney disease are not fully understood. Here we show that the integration of genome-wide genetic, transcriptomic, and proteomic association studies can nominate causal determinants of kidney function and damage. RESULTS: Through transcriptome-wide association studies (TWAS) in kidney cortex, kidney tubule, liver, and whole blood and proteome-wide association studies (PWAS) in plasma, we assess for effects of 12,893 genes and 1342 proteins on kidney filtration (glomerular filtration rate (GFR) estimated by creatinine; GFR estimated by cystatin C; and blood urea nitrogen) and kidney damage (albuminuria). We find 1561 associations distributed among 260 genomic regions that are supported as putatively causal. We then prioritize 153 of these genomic regions using additional colocalization analyses. Our genome-wide findings are supported by existing knowledge (animal models for MANBA, DACH1, SH3YL1, INHBB), exceed the underlying GWAS signals (28 region-trait combinations without significant GWAS hit), identify independent gene/protein-trait associations within the same genomic region (INHBC, SPRYD4), nominate tissues underlying the associations (tubule expression of NRBP1), and distinguish markers of kidney filtration from those with a role in creatinine and cystatin C metabolism. Furthermore, we follow up on members of the TGF-beta superfamily of proteins and find a prognostic value of INHBC for kidney disease progression even after adjustment for measured glomerular filtration rate (GFR). CONCLUSION: In summary, this study combines multimodal, genome-wide association studies to generate a catalog of putatively causal target genes and proteins relevant to kidney function and damage which can guide follow-up studies in physiology, basic science, and clinical medicine.
Keywords: Animals; Creatinine; Cystatin C; Genome-Wide Association Study; Kidney; Proteome; Proteomics; Renal Insufficiency, Chronic; Transcriptome

Whole Genome Analysis of SNV and Indel Polymorphism in Common Marmosets (). - R. Alan Harris; Raveendran, Muthuswamy; Warren, Wes; LaDeana, Hillier W; Tomlinson, Chad; Graves-Lindsay, Tina; Green, Richard E; Schmidt, Jenna K; Colwell, Julia C; Makulec, Allison T; Cole, Shelley A; Cheeseman, Ian H; et al. (Genes (Basel), 2023)
The common marmoset () is one of the most widely used nonhuman primate models of human disease. Owing to limitations in sequencing technology, early genome assemblies of this species using short-read sequencing suffered from gaps. In addition, the genetic diversity of the species has not yet been adequately explored. Using long-read genome sequencing and expert annotation, we generated a high-quality genome resource creating a 2.898 Gb marmoset genome in which most of the euchromatin portion is assembled contiguously (contig N50 = 25.23 Mbp, scaffold N50 = 98.2 Mbp). We then performed whole genome sequencing on 84 marmosets sampling the genetic diversity from several marmoset research centers. We identified a total of 19.1 million single nucleotide variants (SNVs), of which 11.9 million can be reliably mapped to orthologous locations in the human genome. We also observed 2.8 million small insertion/deletion variants. This dataset includes an average of 5.4 million SNVs per marmoset individual and a total of 74,088 missense variants in protein-coding genes. Of the 4956 variants orthologous to human ClinVar SNVs (present in the same annotated gene and with the same functional consequence in marmoset and human), 27 have a clinical significance of pathogenic and/or likely pathogenic. This important marmoset genomic resource will help guide genetic analyses of natural variation, the discovery of spontaneous functional variation relevant to human disease models, and the development of genetically engineered marmoset disease models.
Keywords: Animals; Callithrix; Chromosome Mapping; Genome, Human; Genomics; Humans

AAV8-Mediated Gene Therapy Rescues Retinal Degeneration Phenotype in a Tlcd3b Knockout Mouse Model. - Qian, Xinye; Liu, Hehe; Fu, Shangyi; Lu, Jiaxiong; Hung, Yu-Ting; Turner, Cassidy; Gu, Haiwei; Rui Chen (Invest Ophthalmol Vis Sci, 2022)
PURPOSE: The purpose of this study was to assess the therapeutic efficacy of rAAV8-hGRK1-Tlcd3b in a Tlcd3b-/- mouse model of retinal generation and validate TLCD3B's role as a ceramide synthase in vivo. METHODS: Using Tlcd3b-/- mice as an inherited retinal disease animal model, we performed subretinal injection of rAAV8-hGRK1-Tlcd3b and evaluated the efficacy of gene replacement therapy. Tlcd3b-/- mice were treated at two time points: postnatal day 21 (P21) and postnatal day 120 (P120) with various dosages. RESULTS: Tlcd3b overexpression rescued retinal degeneration in the mutant mice, as indicated by significantly improved photoreceptor function and preservation of photoreceptor cells over the course of 1 year. Although Tlcd3b is expressed in all cell types in the retina, photoreceptor cell-specific expression of Tlcd3b is sufficient to rescue the phenotype, indicating the primary function of TLCD3B is in photoreceptors. Consistent with the idea that TLCD3B is a ceramide synthase, mass spectrometry analyses of the mutant retina indicate the reduction of C16-, C18-, and C20-ceramides in the retina, which are restored with Tlcd3b overexpression. CONCLUSIONS: Our findings demonstrated the therapeutic efficacy of gene therapy in treating Tlcd3b mutant retina, laying the foundation for developing future therapy for TLCD3B retinopathy.
Keywords: Animals; Disease Models, Animal; Electroretinography; Genetic Therapy; Genetic Vectors; Mice; Mice, Inbred C57BL; Mice, Knockout; Phenotype; Retina; Retinal Degeneration

Bi-allelic CAMSAP1 variants cause a clinically recognizable neuronal migration disorder. - Khalaf-Nazzal, Reham; Fasham, James; Inskeep, Katherine A; Blizzard, Lauren E; Leslie, Joseph S; Wakeling, Matthew N; Ubeyratna, Nishanka; Mitani, Tadahiro; Griffith, Jennifer L; Baker, Wisam; Al-Hijawi, Fida'; Keough, Karen C; et al. (Am J Hum Genet, 2022)
Non-centrosomal microtubules are essential cytoskeletal filaments that are important for neurite formation, axonal transport, and neuronal migration. They require stabilization by microtubule minus-end-targeting proteins including the CAMSAP family of molecules. Using exome sequencing on samples from five unrelated families, we show that bi-allelic CAMSAP1 loss-of-function variants cause a clinically recognizable, syndromic neuronal migration disorder. The cardinal clinical features of the syndrome include a characteristic craniofacial appearance, primary microcephaly, severe neurodevelopmental delay, cortical visual impairment, and seizures. The neuroradiological phenotype comprises a highly recognizable combination of classic lissencephaly with a posterior more severe than anterior gradient similar to PAFAH1B1(LIS1)-related lissencephaly and severe hypoplasia or absence of the corpus callosum; dysplasia of the basal ganglia, hippocampus, and midbrain; and cerebellar hypodysplasia, similar to the tubulinopathies, a group of monogenic tubulin-associated disorders of cortical dysgenesis. Neural cell rosette lineages derived from affected individuals displayed findings consistent with these phenotypes, including abnormal morphology, decreased cell proliferation, and neuronal differentiation. Camsap1-null mice displayed increased perinatal mortality, and RNAScope studies identified high expression levels in the brain throughout neurogenesis and in facial structures, consistent with the mouse and human neurodevelopmental and craniofacial phenotypes. Together our findings confirm a fundamental role of CAMSAP1 in neuronal migration and brain development and define bi-allelic variants as a cause of a clinically distinct neurodevelopmental disorder in humans and mice.
Keywords: Alleles; Animals; Classical Lissencephalies and Subcortical Band Heterotopias; Humans; Lissencephaly; Mice; Mice, Knockout; Microtubule-Associated Proteins; Nervous System Malformations; Phenotype; Tubulin

Clinical presentation, treatment, and genetic and histopathological analysis of juvenile cataracts and secondary glaucoma in a rhesus macaque (Macaca mulatta). - Casanova, M Isabel; Rui Chen; Garzel, Laura M; Olstad, Katherine J; Kim, Soohyun; R. Alan Harris; Yumei Li; Raveendran, Muthuswamy; Liang, Qingnan; Wang, Jun; Yiu, Glenn; Stout, John Timothy; et al. (J Med Primatol, 2022)
This report describes the clinical and histological findings, genetic study, and treatment in a 1.3-year-old rhesus macaque with bilateral cataracts and unilateral secondary glaucoma. Intravitreal injection of gentamicin decreased the intraocular pressure from 56 to <2 mm Hg. A putative genetic cause of the cataracts was not identified.
Keywords: Animals; Cataract; Glaucoma; Intraocular Pressure; Macaca mulatta

Comparative molecular genomic analyses of a spontaneous rhesus macaque model of mismatch repair-deficient colorectal cancer. - Ozirmak Lermi, Nejla; Gray, Stanton B; Bowen, Charles M; Reyes-Uribe, Laura; Dray, Beth K; Deng, Nan; R. Alan Harris; Raveendran, Muthuswamy; Benavides, Fernando; Hodo, Carolyn L; Taggart, Melissa W; Colbert Maresso, Karen; et al. (PLoS Genet, 2022)
Colorectal cancer (CRC) remains the third most common cancer in the US with 15% of cases displaying Microsatellite Instability (MSI) secondary to Lynch Syndrome (LS) or somatic hypermethylation of the MLH1 promoter. A cohort of rhesus macaques from our institution developed spontaneous mismatch repair deficient (MMRd) CRC with a notable fraction harboring a pathogenic germline mutation in MLH1 (c.1029C<G, p.Tyr343Ter). Our study aimed to provide a detailed molecular characterization of rhesus CRC for cross-comparison with human MMRd CRC. We performed PCR-based MSI testing (n = 41), transcriptomics analysis (n = 35), reduced-representation bisulfite sequencing (RRBS) (n = 28), and MLH1 DNA methylation (n = 10) using next-generation sequencing (NGS) of rhesus CRC. Systems biology tools were used to perform gene set enrichment analysis (GSEA) for pathway discovery, consensus molecular subtyping (CMS), and somatic mutation profiling. Overall, the majority of rhesus tumors displayed high levels of MSI (MSI-H) and differential gene expression profiles that were consistent with known deregulated pathways in human CRC. DNA methylation analysis exposed differentially methylated patterns among MSI-H, MSI-L (MSI-low)/MSS (MS-stable) and LS tumors with MLH1 predominantly inactivated among sporadic MSI-H CRCs. The findings from this study support the use of rhesus macaques as an alternative animal model to mice to study carcinogenesis, develop immunotherapies and vaccines, and implement chemoprevention approaches relevant to sporadic MSI-H and LS CRC in humans.
Keywords: Animals; Colonic Neoplasms; Colorectal Neoplasms; Colorectal Neoplasms, Hereditary Nonpolyposis; DNA Methylation; DNA Mismatch Repair; Genomics; Humans; Macaca mulatta; Mice; Microsatellite Instability; MutL Protein Homolog 1

Construction of a new chromosome-scale, long-read reference genome assembly for the Syrian hamster, Mesocricetus auratus. - R. Alan Harris; Raveendran, Muthuswamy; Lyfoung, Dustin T; Fritz J Sedlazeck; Mahmoud, Medhat; Prall, Trent M; Karl, Julie A; Harshavardhan Doddapaneni; Meng, Qingchang; Yi Han; Donna M Muzny; Wiseman, Roger W; et al. (Gigascience, 2022)
BACKGROUND: The Syrian hamster (Mesocricetus auratus) has been suggested as a useful mammalian model for a variety of diseases and infections, including infection with respiratory viruses such as SARS-CoV-2. The MesAur1.0 genome assembly was generated in 2013 using whole-genome shotgun sequencing with short-read sequence data. Current more advanced sequencing technologies and assembly methods now permit the generation of near-complete genome assemblies with higher quality and greater continuity. FINDINGS: Here, we report an improved assembly of the M. auratus genome (BCM_Maur_2.0) using Oxford Nanopore Technologies long-read sequencing to produce a chromosome-scale assembly. The total length of the new assembly is 2.46 Gb, similar to the 2.50-Gb length of a previous assembly of this genome, MesAur1.0. BCM_Maur_2.0 exhibits significantly improved continuity, with a scaffold N50 that is 6.7 times greater than MesAur1.0. Furthermore, 21,616 protein-coding genes and 10,459 noncoding genes are annotated in BCM_Maur_2.0 compared to 20,495 protein-coding genes and 4,168 noncoding genes in MesAur1.0. This new assembly also improves the unresolved regions as measured by nucleotide ambiguities, where ∼17.11% of bases in MesAur1.0 were unresolved compared to BCM_Maur_2.0, in which the number of unresolved bases is reduced to 3.00%. CONCLUSIONS: Access to a more complete reference genome with improved accuracy and continuity will facilitate more detailed, comprehensive, and meaningful research results for a wide variety of future studies using Syrian hamsters as models.
Keywords: Animals; Chromosomes, Mammalian; Genome; High-Throughput Nucleotide Sequencing; Mesocricetus; Whole Genome Sequencing

Cwc27, associated with retinal degeneration, functions as a splicing factor in vivo. - Bertrand, Renae Elaine; Wang, Jun; Yumei Li; Cheng, Xuesen; Wang, Keqing; Stoilov, Peter; Rui Chen (Hum Mol Genet, 2022)
Previous in vitro studies indicate that CWC27 functions as a splicing factor in the Bact spliceosome complex, interacting with CWC22 to form a landing platform for eIF4A3, a core component of the exon junction complex. However, the function of CWC27 as a splicing factor has not been validated in any in vivo systems. CWC27 variants have been shown to cause autosomal recessive retinal degeneration, in both syndromic and non-syndromic forms. The Cwc27K338fs/K338fs mouse model was shown to have significant retinal dysfunction and degeneration by 6 months of age. In this report, we have taken advantage of the Cwc27K338fs/K338fs mouse model to show that Cwc27 is involved in splicing in vivo in the context of the retina. Bulk RNA and single cell RNA-sequencing of the mouse retina showed that there were gene expression and splicing pattern changes, including alternative splice site usage and intron retention. Positive staining for CHOP suggests that ER stress may be activated in response to the splicing pattern changes and is a likely contributor to the disease mechanism. Our results provide the first evidence that CWC27 functions as a splicing factor in an in vivo context. The splicing defects and gene expression changes observed in the Cwc27K338fs/K338fs mouse retina provide insight to the potential disease mechanisms, paving the way for targeted therapeutic development.
Keywords: Alternative Splicing; Animals; Introns; Mice; Peptidylprolyl Isomerase; Retinal Degeneration; RNA Splice Sites; RNA Splicing; RNA Splicing Factors; Spliceosomes

De novo Mutations in Domestic Cat are Consistent with an Effect of Reproductive Longevity on Both the Rate and Spectrum of Mutations. - Wang, Richard J; Raveendran, Muthuswamy; R. Alan Harris; Murphy, William J; Lyons, Leslie A; Jeffrey Rogers; Hahn, Matthew W (Mol Biol Evol, 2022)
The mutation rate is a fundamental evolutionary parameter with direct and appreciable effects on the health and function of individuals. Here, we examine this important parameter in the domestic cat, a beloved companion animal as well as a valuable biomedical model. We estimate a mutation rate of 0.86 × 10-8 per bp per generation for the domestic cat (at an average parental age of 3.8 years). We find evidence for a significant paternal age effect, with more mutations transmitted by older sires. Our analyses suggest that the cat and the human have accrued similar numbers of mutations in the germline before reaching sexual maturity. The per-generation mutation rate in the cat is 28% lower than what has been observed in humans, but is consistent with the shorter generation time in the cat. Using a model of reproductive longevity, which takes into account differences in the reproductive age and time to sexual maturity, we are able to explain much of the difference in per-generation rates between species. We further apply our reproductive longevity model in a novel analysis of mutation spectra and find that the spectrum for the cat resembles the human mutation spectrum at a younger age of reproduction. Together, these results implicate changes in life-history as a driver of mutation rate evolution between species. As the first direct observation of the paternal age effect outside of rodents and primates, our results also suggest a phenomenon that may be universal among mammals.
Keywords: Animals; Cats; Child, Preschool; Humans; Longevity; Mammals; Mutation; Mutation Rate; Paternal Age; Reproduction

De novo variants in EMC1 lead to neurodevelopmental delay and cerebellar degeneration and affect glial function in Drosophila. - Chung, Hyung-Lok; Rump, Patrick; Lu, Di; Glassford, Megan R; Mok, Jung-Wan; Fatih, Jawid; Basal, Adily; Marcogliese, Paul C; Kanca, Oguz; Rapp, Michele; Fock, Johanna M; Kamsteeg, Erik-Jan; et al. (Hum Mol Genet, 2022)
BACKGROUND: The endoplasmic reticulum (ER)-membrane protein complex (EMC) is a multi-protein transmembrane complex composed of 10 subunits that functions as a membrane-protein chaperone. Variants in EMC1 lead to neurodevelopmental delay and cerebellar degeneration. Multiple families with biallelic variants have been published, yet to date, only a single report of a monoallelic variant has been described, and functional evidence is sparse. METHODS: Exome sequencing was used to investigate the genetic cause underlying severe developmental delay in three unrelated children. EMC1 variants were modeled in Drosophila, using loss-of-function (LoF) and overexpression studies. Glial-specific and neuronal-specific assays were used to determine whether the dysfunction was specific to one cell type. RESULTS: Exome sequencing identified de novo variants in EMC1 in three individuals affected by global developmental delay, hypotonia, seizures, visual impairment and cerebellar atrophy. All variants were located at Pro582 or Pro584. Drosophila studies indicated that imbalance of EMC1-either overexpression or knockdown-results in pupal lethality and suggest that the tested homologous variants are LoF alleles. In addition, glia-specific gene dosage, overexpression or knockdown, of EMC1 led to lethality, whereas neuron-specific alterations were tolerated. DISCUSSION: We establish de novo monoallelic EMC1 variants as causative of a neurological disease trait by providing functional evidence in a Drosophila model. The identified variants failed to rescue the lethality of a null allele. Variations in dosage of the wild-type EMC1, specifically in glia, lead to pupal lethality, which we hypothesize results from the altered stoichiometry of the multi-subunit protein complex EMC.
Keywords: Animals; Basic Helix-Loop-Helix Transcription Factors; Cerebellar Diseases; Drosophila; Drosophila Proteins; Intellectual Disability; Membrane Proteins; Nervous System Malformations; Neurodegenerative Diseases; Neurodevelopmental Disorders; Neuroglia; Repressor Proteins

The Earth BioGenome Project 2020: Starting the clock. - Lewin, Harris A; Stephen Richards; Lieberman Aiden, Erez; Allende, Miguel L; Archibald, John M; Bálint, Miklós; Barker, Katharine B; Baumgartner, Bridget; Belov, Katherine; Bertorelle, Giorgio; Blaxter, Mark L; Cai, Jing; et al. (Proc Natl Acad Sci U S A, 2022)
Keywords: Animals; Base Sequence; Biodiversity; Eukaryota; Genomics; Humans

An ELF4 hypomorphic variant results in NK cell deficiency. - Salinas, Sandra Andrea; Mace, Emily M; Conte, Matilde I; Park, Chun Shik; Li, Yu; Rosario-Sepulveda, Joshua I; Mahapatra, Sanjana; Moore, Emily K; Hernandez, Evelyn R; Chinn, Ivan K; Reed, Abigail E; Lee, Barclay J; et al. (JCI Insight, 2022)
NK cell deficiencies (NKD) are a type of primary immune deficiency in which the major immunologic abnormality affects NK cell number, maturity, or function. Since NK cells contribute to immune defense against virally infected cells, patients with NKD experience higher susceptibility to chronic, recurrent, and fatal viral infections. An individual with recurrent viral infections and mild hypogammaglobulinemia was identified to have an X-linked damaging variant in the transcription factor gene ELF4. The variant does not decrease expression but disrupts ELF4 protein interactions and DNA binding, reducing transcriptional activation of target genes and selectively impairing ELF4 function. Corroborating previous murine models of ELF4 deficiency (Elf4-/-) and using a knockdown human NK cell line, we determined that ELF4 is necessary for normal NK cell development, terminal maturation, and function. Through characterization of the NK cells of the proband, expression of the proband's variant in Elf4-/- mouse hematopoietic precursor cells, and a human in vitro NK cell maturation model, we established this ELF4 variant as a potentially novel cause of NKD.
Keywords: Animals; DNA-Binding Proteins; Humans; Killer Cells, Natural; Mice; Transcription Factors

Elucidating the clinical spectrum and molecular basis of HYAL2 deficiency. - Fasham, James; Lin, Siying; Ghosh, Promita; Radio, Francesca Clementina; Farrow, Emily G; Thiffault, Isabelle; Kussman, Jennifer; Zhou, Dihong; Hemming, Rick; Zahka, Kenneth; Chioza, Barry A; Rawlins, Lettie E; et al. (Genet Med, 2022)
PURPOSE: We previously defined biallelic HYAL2 variants causing a novel disorder in 2 families, involving orofacial clefting, facial dysmorphism, congenital heart disease, and ocular abnormalities, with Hyal2 knockout mice displaying similar phenotypes. In this study, we better define the phenotype and pathologic disease mechanism. METHODS: Clinical and genomic investigations were undertaken alongside molecular studies, including immunoblotting and immunofluorescence analyses of variant/wild-type human HYAL2 expressed in mouse fibroblasts, and in silico modeling of putative pathogenic variants. RESULTS: Ten newly identified individuals with this condition were investigated, and they were associated with 9 novel pathogenic variants. Clinical studies defined genotype-phenotype correlations and confirmed a recognizable craniofacial phenotype in addition to myopia, cleft lip/palate, and congenital cardiac anomalies as the most consistent manifestations of the condition. In silico modeling of missense variants identified likely deleterious effects on protein folding. Consistent with this, functional studies indicated that these variants cause protein instability and a concomitant cell surface absence of HYAL2 protein. CONCLUSION: These studies confirm an association between HYAL2 alterations and syndromic cleft lip/palate, provide experimental evidence for the pathogenicity of missense alleles, enable further insights into the pathomolecular basis of the disease, and delineate the core and variable clinical outcomes of the condition.
Keywords: Alleles; Animals; Cell Adhesion Molecules; Cleft Lip; Cleft Palate; Genetic Association Studies; GPI-Linked Proteins; Humans; Hyaluronoglucosaminidase; Mice; Phenotype

Examining the Effects of Hibernation on Germline Mutation Rates in Grizzly Bears. - Wang, Richard J; Peña-Garcia, Yadira; Bibby, Madeleine G; Raveendran, Muthuswamy; R. Alan Harris; Jansen, Heiko T; Robbins, Charles T; Jeffrey Rogers; Kelley, Joanna L; Hahn, Matthew W (Genome Biol Evol, 2022)
A male mutation bias is observed across vertebrates, and, where data are available, this bias is accompanied by increased per-generation mutation rates with parental age. While continuing mitotic cell division in the male germline post puberty has been proposed as the major cellular mechanism underlying both patterns, little direct evidence for this role has been found. Understanding the evolution of the per-generation mutation rate among species requires that we identify the molecular mechanisms that change between species. Here, we study the per-generation mutation rate in an extended pedigree of the brown (grizzly) bear, Ursus arctos horribilis. Brown bears hibernate for one-third of the year, a period during which spermatogenesis slows or stops altogether. The reduction of spermatogenesis is predicted to lessen the male mutation bias and to lower the per-generation mutation rate in this species. However, using whole-genome sequencing, we find that both male bias and per-generation mutation rates are highly similar to that expected for a non-hibernating species. We also carry out a phylogenetic comparison of substitution rates along the lineage leading to brown bear and panda (a non-hibernating species) and find no slowing of the substitution rate in the hibernator. Our results contribute to accumulating evidence that suggests that male germline cell division is not the major determinant of mutation rates and mutation biases. The results also provide a quantitative basis for improved estimates of the timing of carnivore evolution.
Keywords: Animals; Germ Cells; Germ-Line Mutation; Hibernation; Male; Mutation Rate; Phylogeny; Ursidae

Genomic resources for rhesus macaques (Macaca mulatta). - Jeffrey Rogers (Mamm Genome, 2022)
Rhesus macaques (Macaca mulatta) are among the most extensively studied of nonhuman primates. This species has been the subject of many investigations concerning basic primate biology and behavior, including studies of social organization, developmental psychology, physiology, endocrinology, and neurodevelopment. Rhesus macaques are also critically important as a nonhuman primate model of human health and disease, including use in studies of infectious diseases, metabolic diseases, aging, and drug or alcohol abuse. Current research addressing fundamental biological and/or applied biomedical questions benefits from various genetic and genomic analyses. As a result, the genome of rhesus macaques has been the subject of more study than most nonhuman primates. This paper briefly discusses a number of information resources that can provide interested researchers with access to genetic and genomic data describing the content of the rhesus macaque genome, available information regarding genetic variation within the species, results from studies of gene expression, and other aspects of genomic analysis. Specific online databases are discussed, including the US National Center for Biotechnology Information, the University of California Santa Cruz genome browser, Ensembl genome browser, the Macaque Genotype and Phenotype database (mGAP), Rhesusbase, and others.
Keywords: Animals; Genome; Genomics; Macaca mulatta

Genomic signatures of high-altitude adaptation and chromosomal polymorphism in geladas. - Chiou, Kenneth L; Janiak, Mareike C; Schneider-Crease, India A; Sen, Sharmi; Ayele, Ferehiwot; Chuma, Idrissa S; Knauf, Sascha; Lemma, Alemayehu; Signore, Anthony V; D'Ippolito, Anthony M; Abebe, Belayneh; Haile, Abebaw Azanaw; et al. (Nat Ecol Evol, 2022)
Primates have adapted to numerous environments and lifestyles but very few species are native to high elevations. Here we investigated high-altitude adaptations in the gelada (Theropithecus gelada), a monkey endemic to the Ethiopian Plateau. We examined genome-wide variation in conjunction with measurements of haematological and morphological traits. Our new gelada reference genome is highly intact and assembled at chromosome-length levels. Unexpectedly, we identified a chromosomal polymorphism in geladas that could potentially contribute to reproductive barriers between populations. Compared with baboons at low altitude, we found that high-altitude geladas exhibit significantly expanded chest circumferences, potentially allowing for greater lung surface area for increased oxygen diffusion. We identified gelada-specific amino acid substitutions in the alpha-chain subunit of adult haemoglobin but found that gelada haemoglobin does not exhibit markedly altered oxygenation properties compared with lowland primates. We also found that geladas at high altitude do not exhibit elevated blood haemoglobin concentrations, in contrast to the normal acclimatization response to hypoxia in lowland primates. The absence of altitude-related polycythaemia suggests that geladas are able to sustain adequate tissue-oxygen delivery despite environmental hypoxia. Finally, we identified numerous genes and genomic regions exhibiting accelerated rates of evolution, as well as gene families exhibiting expansions in the gelada lineage, potentially reflecting altitude-related selection. Our findings lend insight into putative mechanisms of high-altitude adaptation while suggesting promising avenues for functional hypoxia research.
Keywords: Altitude; Animals; Chromosomes; Genomics; Hypoxia; Oxygen; Theropithecus

Glutathione peroxidase 2 is a metabolic driver of the tumor immune microenvironment and immune checkpoint inhibitor response. - Ahmed, Kazi Mokim; Veeramachaneni, Ratna; Deng, Defeng; Putluri, Nagireddy; Putluri, Vasanta; Cardenas, Maria F; David A Wheeler; Decker, William K; Frederick, Andy I; Kazi, Sawad; Sikora, Andrew G; Sandulache, Vlad C; et al. (J Immunother Cancer, 2022)
BACKGROUND: The existence of immunologically 'cold tumors' frequently found across a wide spectrum of tumor types represents a significant challenge for cancer immunotherapy. Cold tumors have poor baseline pan-leukocyte infiltration, including a low prevalence of cytotoxic lymphocytes, and not surprisingly respond unfavorably to immune checkpoint (IC) inhibitors. We hypothesized that cold tumors harbor a mechanism of immune escape upstream and independent of ICs that may be driven by tumor biology rather than differences in mutational neoantigen burden. METHODS: Using a bioinformatic approach to analyze TCGA (The Cancer Genome Atlas) RNA sequencing data we identified genes upregulated in cold versus hot tumors across four different smoking-related cancers, including squamous carcinomas from the oral cavity (OCSCC) and lung (LUSC), and adenocarcinomas of the bladder (BLCA) and lung (LUAD). Biological significance of the gene most robustly associated with a cold tumor phenotype across all four tumor types, glutathione peroxidase 2 (GPX2), was further evaluated using a combination of in silico analyses and functional genomic experiments performed both in vitro and in in vivo with preclinical models of oral cancer. RESULTS: Elevated RNA expression of five metabolic enzymes including GPX2, aldo-keto reductase family 1 members AKR1C1, AKR1C3, and cytochrome monoxygenases (CP4F11 and CYP4F3) co-occurred in cold tumors across all four smoking-related cancers. These genes have all been linked to negative regulation of arachidonic acid metabolism-a well-established inflammatory pathway-and are also known downstream targets of the redox sensitive Nrf2 transcription factor pathway. In OCSCC, LUSC, and LUAD, GPX2 expression was highly correlated with Nrf2 activation signatures, also elevated in cold tumors. In BLCA, however, GPX2 correlated more strongly than Nrf2 signatures with decreased infiltration of multiple leukocyte subtypes. GPX2 inversely correlated with expression of multiple pro- inflammatory cytokines/chemokines and NF-kB activation in cell lines and knockdown of GPX2 led to increased secretion of prostaglandin E2 (PGE2) and interleukin-6. Conversely, GPX2 overexpression led to reduced PGE2 production in a murine OCSCC model (MOC1). GPX2 overexpressing MOC1 tumors had a more suppressive tumor immune microenvironment and responded less favorably to anti-cytotoxic T-lymphocytes-associated protein 4 IC therapy in mice. CONCLUSION: GPX2 overexpression represents a novel potentially targetable effector of immune escape in cold tumors.
Keywords: Animals; Dinoprostone; Glutathione Peroxidase; Immune Checkpoint Inhibitors; Mice; NF-E2-Related Factor 2; Tumor Microenvironment

Heritability of social behavioral phenotypes and preliminary associations with autism spectrum disorder risk genes in rhesus macaques: A whole exome sequencing study. - Gunter, Chris; R. Alan Harris; Kovacs-Balint, Zsofia; Raveendran, Muthuswamy; Michopoulos, Vasiliki; Bachevalier, Jocelyne; Raper, Jessica; Sanchez, Mar M; Jeffrey Rogers (Autism Res, 2022)
Nonhuman primates and especially rhesus macaques (Macaca mulatta) have been indispensable animal models for studies of various aspects of neurobiology, developmental psychology, and other aspects of neuroscience. While remarkable progress has been made in our understanding of influences on atypical human social behavior, such as that observed in autism spectrum disorders (ASD), many significant questions remain. Improved understanding of the relationships among variation in specific genes and variation in expressed social behavior in a nonhuman primate would benefit efforts to investigate risk factors, developmental mechanisms, and potential therapies for behavioral disorders including ASD. To study genetic influences on key aspects of social behavior and interactions-individual competence and/or motivation for specific aspects of social behavior-we quantified individual variation in social interactions among juvenile rhesus macaques using both a standard macaque ethogram and a macaque-relevant modification of the human Social Responsiveness Scale. Our analyses demonstrate that various aspects of juvenile social behavior exhibit significant genetic heritability, with estimated quantitative genetic effects similar to that described for ASD in human children. We also performed exome sequencing and analyzed variants in 143 genes previously suggested to influence risk for human ASD. We find preliminary evidence for genetic association between specific variants and both individual behaviors and multi-behavioral factor scores. To our knowledge, this is the first demonstration that spontaneous social behaviors performed by free-ranging juvenile rhesus macaques display significant genetic heritability and then to use exome sequencing data to examine potential macaque genetic associations in genes associated with human ASD.
Keywords: Animals; Autism Spectrum Disorder; Exome Sequencing; Humans; Macaca mulatta; Phenotype; Social Behavior

HSPA6 and its role in cancers and other diseases. - Song, Binghui; Shen, Shiyi; Fu, Shangyi; Fu, Junjiang (Mol Biol Rep, 2022)
Heat Shock Protein Family A (Hsp70) Member 6 (HSPA6) (Online Mendelian Inheritance in Man: 140555) belongs to the HSP70 family and is a partially conserved inducible protein in mammals. The HSPA6 gene locates on the human chromosome 1q23.3 and encodes a protein containing two important structural domains: The N-terminal nucleotide-binding domain and the C-terminal substrate-binding domain. Currently, studies have found that HSPA6 not only plays a role in the tumorigenesis and tumor progresses but also causes non-tumor-related diseases. Furthermore, HSPA6 exhibits to inhibit tumorigenesis and tumor progression in some types of cancers but promotes in others. Even though HSPA6 research has increased, its exact roles and mechanisms are still unclear. This article reviews the structure, expression, function, research progress, possible mechanism, and perspective of HSPA6 in cancers and other diseases, highlighting its potential role as a targeted therapeutic and prognostic marker.
Keywords: Animals; Carcinogenesis; Heat-Shock Response; Hot Temperature; HSP70 Heat-Shock Proteins; Humans; Neoplasms

Initiation of the Primate Genome Project. - Wu, Dong-Dong; Qi, Xiao-Guang; Yu, Li; Li, Ming; Liu, Zhi-Jin; Yoder, Anne D; Roos, Christian; Hayakawa, Takashi; Jeffrey Rogers; Marques-Bonet, Tomas; Su, Bing; Yao, Yong-Gang; et al. (Zool Res, 2022)
Keywords: Animals; Evolution, Molecular; Genome; Genomics; Primates

Kidney Risk Variants and Proteomics. - Chen, Teresa K; Surapaneni, Aditya L; Arking, Dan E; Ballantyne, Christie M; Eric Boerwinkle; Chen, Jingsha; Coresh, Josef; Köttgen, Anna; Susztak, Katalin; Tin, Adrienne; Yu, Bing; Grams, Morgan E (Clin J Am Soc Nephrol, 2022)
BACKGROUND AND OBJECTIVES: The risk variants (G1 and G2) are associated with kidney disease among Black adults, but the clinical presentation is heterogeneous. In mouse models and cell systems, increased gene expression of G1 and G2 confers cytotoxicity. How risk variants relate to the circulating proteome warrants further investigation. DESIGN, SETTING, PARTICIPANTS, & MEASUREMENTS: Among 461 African American Study of Kidney Disease and Hypertension (AASK) participants (mean age: 54 years; 41% women; mean GFR: 46 ml/min per 1.73 m), we evaluated associations of risk variants with 6790 serum proteins (measured SOMAscan) using linear regression models. Covariates included age, sex, percentage of European ancestry, and protein principal components 1-5. Associated proteins were then evaluated as mediators of -associated risk for kidney failure. Findings were replicated among 875 Atherosclerosis Risk in Communities (ARIC) study Black participants (mean age: 75 years; 66% women; mean eGFR: 67 ml/min per 1.73 m). RESULTS: In the AASK study, having two (versus zero or one) risk alleles was associated with lower serum levels of APOL1 (=3.11E-13; =3.12E-06 [two aptamers]), APOL2 (1.45E-10), CLSTN2 (=2.66E-06), MMP-2 (=2.96E-06), SPOCK2 (=2.57E-05), and TIMP-2 (=2.98E-05) proteins. In the ARIC study, risk alleles were associated with APOL1 (=1.28E-11); MMP-2 (=0.004) and TIMP-2 (=0.007) were associated only in an additive model, and APOL2 was not available. high-risk status was associated with a 1.6-fold greater risk of kidney failure in the AASK study; none of the identified proteins mediated this association. APOL1 protein levels were not associated with kidney failure in either cohort. CONCLUSIONS: risk variants were strongly associated with lower circulating levels of APOL1 and other proteins, but none mediated the -associated risk for kidney failure. APOL1 protein level was also not associated with kidney failure.
Keywords: Animals; Apolipoprotein L1; Creatinine; Female; Genetic Predisposition to Disease; Genotype; Humans; Kidney; Male; Matrix Metalloproteinase 2; Mice; Proteoglycans; Proteomics; Renal Insufficiency, Chronic; Risk Factors; Tissue Inhibitor of Metalloproteinase-2

Loss of non-motor kinesin KIF26A causes congenital brain malformations via dysregulated neuronal migration and axonal growth as well as apoptosis. - Qian, Xuyu; DeGennaro, Ellen M; Talukdar, Maya; Akula, Shyam K; Lai, Abbe; Shao, Diane D; Gonzalez, Dilenny; Marciano, Jack H; Smith, Richard S; Hylton, Norma K; Yang, Edward; Bazan, J Fernando; et al. (Dev Cell, 2022)
Kinesins are canonical molecular motors but can also function as modulators of intracellular signaling. KIF26A, an unconventional kinesin that lacks motor activity, inhibits growth-factor-receptor-bound protein 2 (GRB2)- and focal adhesion kinase (FAK)-dependent signal transduction, but its functions in the brain have not been characterized. We report a patient cohort with biallelic loss-of-function variants in KIF26A, exhibiting a spectrum of congenital brain malformations. In the developing brain, KIF26A is preferentially expressed during early- and mid-gestation in excitatory neurons. Combining mice and human iPSC-derived organoid models, we discovered that loss of KIF26A causes excitatory neuron-specific defects in radial migration, localization, dendritic and axonal growth, and apoptosis, offering a convincing explanation of the disease etiology in patients. Single-cell RNA sequencing in KIF26A knockout organoids revealed transcriptional changes in MAPK, MYC, and E2F pathways. Our findings illustrate the pathogenesis of KIF26A loss-of-function variants and identify the surprising versatility of this non-motor kinesin.
Keywords: Animals; Apoptosis; Brain; Focal Adhesion Protein-Tyrosine Kinases; Humans; Kinesins; Mice; Neurons

Quantitative dissection of multilocus pathogenic variation in an Egyptian infant with severe neurodevelopmental disorder resulting from multiple molecular diagnoses. - Herman, Isabella; Jolly, Angad; Du, Haowei; Dawood, Moez; Abdel-Salam, Ghada M H; Marafi, Dana; Mitani, Tadahiro; Calame, Daniel G; Coban-Akdemir, Zeynep; Fatih, Jawid M; Hegazy, Ibrahim; Jhangiani, Shalini N; et al. (Am J Med Genet A, 2022)
Genomic sequencing and clinical genomics have demonstrated that substantial subsets of atypical and/or severe disease presentations result from multilocus pathogenic variation (MPV) causing blended phenotypes. In an infant with a severe neurodevelopmental disorder, four distinct molecular diagnoses were found by exome sequencing (ES). The blended phenotype that includes brain malformation, dysmorphism, and hypotonia was dissected using the Human Phenotype Ontology (HPO). ES revealed variants in CAPN3 (c.259C > G:p.L87V), MUSK (c.1781C > T:p.A594V), NAV2 (c.1996G > A:p.G666R), and ZC4H2 (c.595A > C:p.N199H). CAPN3, MUSK, and ZC4H2 are established disease genes linked to limb-girdle muscular dystrophy (OMIM# 253600), congenital myasthenia (OMIM# 616325), and Wieacker-Wolff syndrome (WWS; OMIM# 314580), respectively. NAV2 is a retinoic-acid responsive novel disease gene candidate with biological roles in neurite outgrowth and cerebellar dysgenesis in mouse models. Using semantic similarity, we show that no gene identified by ES individually explains the proband phenotype, but rather the totality of the clinically observed disease is explained by the combination of disease-contributing effects of the identified genes. These data reveal that multilocus pathogenic variation can result in a blended phenotype with each gene affecting a different part of the nervous system and nervous system-muscle connection. We provide evidence from this n = 1 study that in patients with MPV and complex blended phenotypes resulting from multiple molecular diagnoses, quantitative HPO analysis can allow for dissection of phenotypic contribution of both established disease genes and novel disease gene candidates not yet proven to cause human disease.
Keywords: Animals; Calpain; Egypt; Exome Sequencing; Humans; Infant; Muscle Proteins; Muscular Dystrophies, Limb-Girdle; Mutation; Neurodevelopmental Disorders; Phenotype

Retinal organoids derived from rhesus macaque iPSCs undergo accelerated differentiation compared to human stem cells. - Jacobo Lopez, Antonio; Kim, Sangbae; Qian, Xinye; Jeffrey Rogers; Stout, J Timothy; Thomasy, Sara M; La Torre, Anna; Rui Chen; Moshiri, Ala (Cell Prolif, 2022)
PURPOSE: To compare the timing and efficiency of the development of Macaca mulatta, a nonhuman primate (NHP), induced pluripotent stem cell (rhiPSC) derived retinal organoids to those derived from human embryonic stem cells (hESCs). RESULTS: Generation of retinal organoids was achieved from both human and several NHP pluripotent stem cell lines. All rhiPSC lines resulted in retinal differentiation with the formation of optic vesicle-like structures similar to what has been observed in hESC retinal organoids. NHP retinal organoids had laminated structure and were composed of mature retinal cell types including cone and rod photoreceptors. Single-cell RNA sequencing was conducted at two time points; this allowed identification of cell types and developmental trajectory characterization of the developing organoids. Important differences between rhesus and human cells were measured regarding the timing and efficiency of retinal organoid differentiation. While the culture of NHP-derived iPSCs is relatively difficult compared to that of human stem cells, the generation of retinal organoids from NHP iPSCs is feasible and may be less time-consuming due to an intrinsically faster timing of retinal differentiation. CONCLUSIONS: Retinal organoids produced from rhesus monkey iPSCs using established protocols differentiate through the stages of organoid development faster than those derived from human stem cells. The production of NHP retinal organoids may be advantageous to reduce experimental time for basic biology studies in retinogenesis as well as for preclinical trials in NHPs studying retinal allograft transplantation.
Keywords: Animals; Cell Differentiation; Humans; Induced Pluripotent Stem Cells; Macaca mulatta; Organoids; Pluripotent Stem Cells; Retina

A reverse genetics and genomics approach to gene paralog function and disease: Myokymia and the juxtaparanode. - Marafi, Dana; Kozar, Nina; Duan, Ruizhi; Bradley, Stephen; Yokochi, Kenji; Al Mutairi, Fuad; Saadi, Nebal Waill; Whalen, Sandra; Brunet, Theresa; Kotzaeridou, Urania; Choukair, Daniela; Keren, Boris; et al. (Am J Hum Genet, 2022)
The leucine-rich glioma-inactivated (LGI) family consists of four highly conserved paralogous genes, LGI1-4, that are highly expressed in mammalian central and/or peripheral nervous systems. LGI1 antibodies are detected in subjects with autoimmune limbic encephalitis and peripheral nerve hyperexcitability syndromes (PNHSs) such as Isaacs and Morvan syndromes. Pathogenic variations of LGI1 and LGI4 are associated with neurological disorders as disease traits including familial temporal lobe epilepsy and neurogenic arthrogryposis multiplex congenita 1 with myelin defects, respectively. No human disease has been reported associated with either LGI2 or LGI3. We implemented exome sequencing and family-based genomics to identify individuals with deleterious variants in LGI3 and utilized GeneMatcher to connect practitioners and researchers worldwide to investigate the clinical and electrophysiological phenotype in affected subjects. We also generated Lgi3-null mice and performed peripheral nerve dissection and immunohistochemistry to examine the juxtaparanode LGI3 microarchitecture. As a result, we identified 16 individuals from eight unrelated families with loss-of-function (LoF) bi-allelic variants in LGI3. Deep phenotypic characterization showed LGI3 LoF causes a potentially clinically recognizable PNHS trait characterized by global developmental delay, intellectual disability, distal deformities with diminished reflexes, visible facial myokymia, and distinctive electromyographic features suggestive of motor nerve instability. Lgi3-null mice showed reduced and mis-localized Kv1 channel complexes in myelinated peripheral axons. Our data demonstrate bi-allelic LoF variants in LGI3 cause a clinically distinguishable disease trait of PNHS, most likely caused by disturbed Kv1 channel distribution in the absence of LGI3.
Keywords: Animals; Autoantibodies; Axons; Genomics; Humans; Intracellular Signaling Peptides and Proteins; Mammals; Mice; Myokymia; Nerve Tissue Proteins; Phenotype; Reverse Genetics

Sex-specific epigenetic development in the mouse hypothalamic arcuate nucleus pinpoints human genomic regions associated with body mass index. - MacKay, Harry; Gunasekara, Chathura J; Yam, Kit-Yi; Srisai, Dollada; Yalamanchili, Hari Krishna; Yumei Li; Rui Chen; Coarfa, Cristian; Waterland, Robert A (Sci Adv, 2022)
Recent genome-wide association studies corroborate classical research on developmental programming indicating that obesity is primarily a neurodevelopmental disease strongly influenced by nutrition during critical ontogenic windows. Epigenetic mechanisms regulate neurodevelopment; however, little is known about their role in establishing and maintaining the brain's energy balance circuitry. We generated neuron and glia methylomes and transcriptomes from male and female mouse hypothalamic arcuate nucleus, a key site for energy balance regulation, at time points spanning the closure of an established critical window for developmental programming of obesity risk. We find that postnatal epigenetic maturation is markedly cell type and sex specific and occurs in genomic regions enriched for heritability of body mass index in humans. Our results offer a potential explanation for both the limited ontogenic windows for and sex differences in sensitivity to developmental programming of obesity and provide a rich resource for epigenetic analyses of developmental programming of energy balance.
Keywords: Animals; Arcuate Nucleus of Hypothalamus; Body Mass Index; Epigenesis, Genetic; Epigenomics; Female; Genome-Wide Association Study; Humans; Hypothalamus; Male; Mice; Obesity

Single cell RNA sequencing of the adult Drosophila eye reveals distinct clusters and novel marker genes for all major cell types. - Yeung, Kelvin; Bollepogu Raja, Komal Kumar; Shim, Yoon-Kyung; Yumei Li; Rui Chen; Mardon, Graeme (Commun Biol, 2022)
The adult Drosophila eye is a powerful model system for phototransduction and neurodegeneration research. However, single cell resolution transcriptomic data are lacking for this tissue. We present single cell RNA-seq data on 1-day male and female, 3-day and 7-day old male adult eyes, covering early to mature adult eyes. All major cell types, including photoreceptors, cone and pigment cells in the adult eye were captured and identified. Our data sets identified novel cell type specific marker genes, some of which were validated in vivo. R7 and R8 photoreceptors form clusters that reflect their specific Rhodopsin expression and the specific Rhodopsin expression by each R7 and R8 cluster is the major determinant to their clustering. The transcriptomic data presented in this report will facilitate a deeper mechanistic understanding of the adult fly eye as a model system.
Keywords: Animals; Drosophila; Drosophila Proteins; Female; Male; Photoreceptor Cells, Invertebrate; Rhodopsin; Sequence Analysis, RNA

Spata7 is required for maintenance of the retinal connecting cilium. - Lu, Jiaxiong; Xiong, Kaitlyn; Qian, Xinye; Choi, Jongsu; Shim, Yoon-Kyung; Burnett, Jacob; Mardon, Graeme; Rui Chen (Sci Rep, 2022)
SPATA7, an early onset LCA3 retinal disease gene, encodes a putative scaffold protein that is essential for the proper assembly of the connecting cilium (CC) complex in photoreceptors. Previous studies have shown that SPATA7 interacts with other photoreceptor-specific ciliary proteins, such as RPGR and RPGRIP1, and maintains the integrity of CC integrity. However, although it is known that Spata7 is required for early formation of the CC, it is unclear if Spata7 is also required for the maintenance of the CC. To investigate Spata7 function in the retina at the adult stage, loss of function was induced in the adult retina upon tamoxifen induction of an inducible Spata7 knockout allele (Spata7; UbcCreERT2/). The phenotype of mutant retina was characterized by a combination of histology, immunobiochemistry, and electroretinography (ERG). Our results demonstrated that Spata7 is also essential for maintaining the integrity of the mature retinal CC. Loss of Spata7 in adults caused phenotypes similar to those seen in germline mutant mice, including photoreceptor cell degeneration and defective ERG responses. Close examination of the CC revealed significantly shortened NPHP1 length as a result of Spata7 deletion. Furthermore, mislocalization of rhodopsin, leading to ER stress-mediated apoptosis, was observed in the retinal layers. Our results indicate that Spata7 is required not only for the establishment but also for the maintenance of the CC of photoreceptors.
Keywords: Animals; Cilia; DNA-Binding Proteins; Electroretinography; Mice; Retina; Retinal Degeneration; Rhodopsin

TLR7 gain-of-function genetic variation causes human lupus. - Brown, Grant J; Cañete, Pablo F; Wang, Hao; Medhavy, Arti; Bones, Josiah; Roco, Jonathan A; He, Yuke; Qin, Yuting; Cappello, Jean; Ellyard, Julia I; Bassett, Katharine; Shen, Qian; et al. (Nature, 2022)
Although circumstantial evidence supports enhanced Toll-like receptor 7 (TLR7) signalling as a mechanism of human systemic autoimmune disease, evidence of lupus-causing TLR7 gene variants is lacking. Here we describe human systemic lupus erythematosus caused by a TLR7 gain-of-function variant. TLR7 is a sensor of viral RNA, and binds to guanosine-. We identified a de novo, previously undescribed missense TLR7 variant in a child with severe lupus and additional variants in other patients with lupus. The TLR7 variant selectively increased sensing of guanosine and 2',3'-cGMP, and was sufficient to cause lupus when introduced into mice. We show that enhanced TLR7 signalling drives aberrant survival of B cell receptor (BCR)-activated B cells, and in a cell-intrinsic manner, accumulation of CD11c age-associated B cells and germinal centre B cells. Follicular and extrafollicular helper T cells were also increased but these phenotypes were cell-extrinsic. Deficiency of MyD88 (an adaptor protein downstream of TLR7) rescued autoimmunity, aberrant B cell survival, and all cellular and serological phenotypes. Despite prominent spontaneous germinal-centre formation in Tlr7 mice, autoimmunity was not ameliorated by germinal-centre deficiency, suggesting an extrafollicular origin of pathogenic B cells. We establish the importance of TLR7 and guanosine-containing self-ligands for human lupus pathogenesis, which paves the way for therapeutic TLR7 or MyD88 inhibition.
Keywords: Animals; Autoimmunity; B-Lymphocytes; Cyclic GMP; Gain of Function Mutation; Guanosine; Humans; Lupus Erythematosus, Systemic; Mice; Myeloid Differentiation Factor 88; Toll-Like Receptor 7

Absent B cells, agammaglobulinemia, and hypertrophic cardiomyopathy in folliculin-interacting protein 1 deficiency. - Saettini, Francesco; Poli, Cecilia; Vengoechea, Jaime; Bonanomi, Sonia; Orellana, Julio C; Fazio, Grazia; Rodriguez, Fred H; Noguera, Loreani P; Booth, Claire; Jarur-Chamy, Valentina; Shams, Marissa; Iascone, Maria; et al. (Blood, 2021)
Agammaglobulinemia is the most profound primary antibody deficiency that can occur due to an early termination of B-cell development. We here investigated 3 novel patients, including the first known adult, from unrelated families with agammaglobulinemia, recurrent infections, and hypertrophic cardiomyopathy (HCM). Two of them also presented with intermittent or severe chronic neutropenia. We identified homozygous or compound-heterozygous variants in the gene for folliculin interacting protein 1 (FNIP1), leading to loss of the FNIP1 protein. B-cell metabolism, including mitochondrial numbers and activity and phosphatidylinositol 3-kinase/AKT pathway, was impaired. These defects recapitulated the Fnip1-/- animal model. Moreover, we identified either uniparental disomy or copy-number variants (CNVs) in 2 patients, expanding the variant spectrum of this novel inborn error of immunity. The results indicate that FNIP1 deficiency can be caused by complex genetic mechanisms and support the clinical utility of exome sequencing and CNV analysis in patients with broad phenotypes, including agammaglobulinemia and HCM. FNIP1 deficiency is a novel inborn error of immunity characterized by early and severe B-cell development defect, agammaglobulinemia, variable neutropenia, and HCM. Our findings elucidate a functional and relevant role of FNIP1 in B-cell development and metabolism and potentially neutrophil activity.
Keywords: Adult; Agammaglobulinemia; Animals; B-Lymphocytes; Cardiomyopathy, Hypertrophic; Carrier Proteins; Child; Child, Preschool; Chromosomes, Human, Pair 5; Codon, Nonsense; Consanguinity; Crohn Disease; Developmental Disabilities; Disease Models, Animal; Disease Susceptibility; DNA Copy Number Variations; Female; Heart Defects, Congenital; Humans; Immunologic Deficiency Syndromes; Infections; Loss of Function Mutation; Lymphopenia; Male; Mice; Neutropenia; Pedigree; Uniparental Disomy; Whole Exome Sequencing

Advanced Retinal Imaging and Ocular Parameters of the Rhesus Macaque Eye. - Lin, Kira H; Tran, Tu; Kim, Soohyun; Park, Sangwan; Stout, J Timothy; Rui Chen; Jeffrey Rogers; Yiu, Glenn; Thomasy, Sara; Moshiri, Ala (Transl Vis Sci Technol, 2021)
PURPOSE: To determine the range of normal ocular biometry and perform advanced retinal imaging and functional assessment of the rhesus macaque eye. METHODS: We performed ocular phenotyping on rhesus macaques at the California National Primate Research Center. This process consisted of anterior and posterior segment eye examination by ophthalmologists, advanced retinal imaging, and functional retinal electrophysiology. RESULTS: Full eye examinations were performed on 142 animals, consisting of pupillary light reflex, tonometry, external examination and photography, anterior slit lamp examination, and posterior segment examination by indirect ophthalmoscopy. Ages of the rhesus macaques ranged from 0.7 to 29 years (mean, 16.4 ± 7.5 years). Anterior segment measurements such as intraocular pressure (n = 142), corneal thickness (n = 84), lens thickness (n = 114), and axial length (n = 114) were acquired. Advanced retinal imaging in the form of fundus photography (n = 78), optical coherence tomography (n = 60), and quantitative autofluorescence (n = 44) was obtained. Electroretinography (n = 75) was used to assay retinal function. Quantitative analyses of the macular structure, retinal layer segmentation, and rod and cone photoreceptor electrical responses are reported. Quantitative assessments were made and variations between sexes were analyzed to compare with established sex changes in human eyes. CONCLUSIONS: The rhesus macaque has an ocular structure and function very similar to that of the human eye. In particular macular structure and retinal function is very similar to humans, making this species particularly useful for the study of macular biology and development of therapies for cone photoreceptor disorders. TRANSLATIONAL RELEVANCE: Rhesus macaques are an ideal model for future vision science studies of human eye diseases.
Keywords: Animals; Electroretinography; Intraocular Pressure; Macaca mulatta; Retina; Tomography, Optical Coherence

Age-related changes in the rhesus macaque eye. - Lin, Kira H; Tran, Tu; Kim, Soohyun; Park, Sangwan; Chen, Jiajia; Stout, J Timothy; Rui Chen; Jeffrey Rogers; Yiu, Glenn; Thomasy, Sara; Moshiri, Ala (Exp Eye Res, 2021)
PURPOSE: To assess age-related changes in the rhesus macaque eye and evaluate them to corresponding human age-related eye disease. METHODS: Data from eye exams and imaging tests including intraocular pressure (IOP), lens thickness, axial length, and retinal optical coherence tomography (OCT) images were evaluated from 142 individuals and statistically analyzed for age-related changes. Quantitative autofluorescence (qAF) was measured as was the presence of macular lesions as related to age. RESULTS: Ages of the 142 rhesus macaques ranged from 0.7 to 29 years (mean = 16.4 years, stdev = 7.5 years). Anterior segment measurements such as IOP, lens thickness, and axial length were acquired. Advanced retinal imaging in the form of optical coherence tomography and qAF were obtained. Quantitative assessments were made and variations by age groups were analyzed to compare with established age-related changes in human eyes. Quantitative analysis of data revealed age-related increase in intraocular pressure (0.165 mm Hg per increase in year of age), ocular biometry (lens thickness 7.2 μm per increase in year of age; and axial length 52.8 μm per increase in year of age), and presence of macular lesions. Age-related changes in thicknesses of retinal layers on OCT were observed and quantified, showing decreased thickness of the retinal ganglion cell layer and inner nuclear layer, and increased thickness of photoreceptor outer segment and choroidal layers. Age was correlated with increased qAF by 1.021 autofluorescence units per increase in year of age. CONCLUSIONS: The rhesus macaque has age-related ocular changes similar to humans. IOP increases with age while retinal ganglion cell layer thickness decreases. Macular lesions develop in some aged animals. Our findings support the concept that rhesus macaques may be useful for the study of important age-related diseases such as glaucoma, macular diseases, and cone disorders, and for development of therapies for these diseases.
Keywords: Aging; Animals; Biometry; Disease Models, Animal; Eye Diseases; Macaca mulatta; Retinal Ganglion Cells; Tomography, Optical Coherence

Beyond MRI: on the scientific value of combining non-human primate neuroimaging with metadata. - Poirier, Colline; Hamed, Suliann Ben; Garcia-Saldivar, Pamela; Kwok, Sze Chai; Meguerditchian, Adrien; Merchant, Hugo; Jeffrey Rogers; Wells, Sara; Fox, Andrew S (Neuroimage, 2021)
Sharing and pooling large amounts of non-human primate neuroimaging data offer new exciting opportunities to understand the primate brain. The potential of big data in non-human primate neuroimaging could however be tremendously enhanced by combining such neuroimaging data with other types of information. Here we describe metadata that have been identified as particularly valuable by the non-human primate neuroimaging community, including behavioural, genetic, physiological and phylogenetic data.
Keywords: Animals; Behavior, Animal; big data; Genotype; Information Dissemination; Magnetic Resonance Imaging; Metadata; Neuroimaging; Phylogeny; Primates

Biallelic and monoallelic variants in PLXNA1 are implicated in a novel neurodevelopmental disorder with variable cerebral and eye anomalies. - Dworschak, Gabriel C; Punetha, Jaya; Kalanithy, Jeshurun C; Mingardo, Enrico; Erdem, Haktan B; Akdemir, Zeynep C; Karaca, Ender; Mitani, Tadahiro; Marafi, Dana; Fatih, Jawid M; Jhangiani, Shalini N; Hunter, Jill V; et al. (Genet Med, 2021)
PURPOSE: To investigate the effect of PLXNA1 variants on the phenotype of patients with autosomal dominant and recessive inheritance patterns and to functionally characterize the zebrafish homologs plxna1a and plxna1b during development. METHODS: We assembled ten patients from seven families with biallelic or de novo PLXNA1 variants. We describe genotype-phenotype correlations, investigated the variants by structural modeling, and used Morpholino knockdown experiments in zebrafish to characterize the embryonic role of plxna1a and plxna1b. RESULTS: Shared phenotypic features among patients include global developmental delay (9/10), brain anomalies (6/10), and eye anomalies (7/10). Notably, seizures were predominantly reported in patients with monoallelic variants. Structural modeling of missense variants in PLXNA1 suggests distortion in the native protein. Our zebrafish studies enforce an embryonic role of plxna1a and plxna1b in the development of the central nervous system and the eye. CONCLUSION: We propose that different biallelic and monoallelic variants in PLXNA1 result in a novel neurodevelopmental syndrome mainly comprising developmental delay, brain, and eye anomalies. We hypothesize that biallelic variants in the extracellular Plexin-A1 domains lead to impaired dimerization or lack of receptor molecules, whereas monoallelic variants in the intracellular Plexin-A1 domains might impair downstream signaling through a dominant-negative effect.
Keywords: Animals; Eye Abnormalities; Genetic Association Studies; Humans; Nerve Tissue Proteins; Neurodevelopmental Disorders; Phenotype; Receptors, Cell Surface; Zebrafish

Ceramide synthase TLCD3B is a novel gene associated with human recessive retinal dystrophy. - Bertrand, Renae Elaine; Wang, Jun; Xiong, Kaitlyn H; Thangavel, Chinthana; Qian, Xinye; Ba-Abbad, Rola; Liang, Qingnan; Simões, Renata T; Sampaio, Shirley A M; Carss, Keren J; Lucy Raymond, F; Robson, Anthony G; et al. (Genet Med, 2021)
PURPOSE: Previous studies suggest that ceramide is a proapoptotic lipid as high levels of ceramides can lead to apoptosis of neuronal cells, including photoreceptors. However, no pathogenic variant in ceramide synthases has been identified in human patients and knockout of various ceramide synthases in mice has not led to photoreceptor degeneration. METHODS: Exome sequencing was used to identify candidate disease genes in patients with vision loss as confirmed by standard evaluation methods, including electroretinography (ERG) and optical coherence tomography. The vision loss phenotype in mice was evaluated by ERG and histological analyses. RESULTS: Here we have identified four patients with cone-rod dystrophy or maculopathy from three families carrying pathogenic variants in TLCD3B. Consistent with the phenotype observed in patients, the Tlcd3b mice exhibited a significant reduction of the cone photoreceptor light responses, thinning of the outer nuclear layer, and loss of cone photoreceptors across the retina. CONCLUSION: Our results provide a link between loss-of-function variants in a ceramide synthase gene and human retinal dystrophy. Establishment of the Tlcd3b knockout murine model, an in vivo photoreceptor cell degeneration model due to loss of a ceramide synthase, will provide a unique opportunity in probing the role of ceramide in survival and function of photoreceptor cells.
Keywords: Animals; Electroretinography; Humans; Mice; Oxidoreductases; Retina; Retinal Cone Photoreceptor Cells; Retinal Degeneration; Retinal Dystrophies

COPB2 loss of function causes a coatopathy with osteoporosis and developmental delay. - Marom, Ronit; Burrage, Lindsay C; Venditti, Rossella; Clément, Aurélie; Blanco-Sánchez, Bernardo; Jain, Mahim; Scott, Daryl A; Rosenfeld, Jill A; Sutton, V Reid; Shinawi, Marwan; Mirzaa, Ghayda; DeVile, Catherine; et al. (Am J Hum Genet, 2021)
Coatomer complexes function in the sorting and trafficking of proteins between subcellular organelles. Pathogenic variants in coatomer subunits or associated factors have been reported in multi-systemic disorders, i.e., coatopathies, that can affect the skeletal and central nervous systems. We have identified loss-of-function variants in COPB2, a component of the coatomer complex I (COPI), in individuals presenting with osteoporosis, fractures, and developmental delay of variable severity. Electron microscopy of COPB2-deficient subjects' fibroblasts showed dilated endoplasmic reticulum (ER) with granular material, prominent rough ER, and vacuoles, consistent with an intracellular trafficking defect. We studied the effect of COPB2 deficiency on collagen trafficking because of the critical role of collagen secretion in bone biology. COPB2 siRNA-treated fibroblasts showed delayed collagen secretion with retention of type I collagen in the ER and Golgi and altered distribution of Golgi markers. copb2-null zebrafish embryos showed retention of type II collagen, disorganization of the ER and Golgi, and early larval lethality. Copb2 mice exhibited low bone mass, and consistent with the findings in human cells and zebrafish, studies in Copb2 mouse fibroblasts suggest ER stress and a Golgi defect. Interestingly, ascorbic acid treatment partially rescued the zebrafish developmental phenotype and the cellular phenotype in Copb2 mouse fibroblasts. This work identifies a form of coatopathy due to COPB2 haploinsufficiency, explores a potential therapeutic approach for this disorder, and highlights the role of the COPI complex as a regulator of skeletal homeostasis.
Keywords: Animals; Ascorbic Acid; Bone and Bones; Brain; Child; Child, Preschool; Coat Protein Complex I; Coatomer Protein; Collagen Type I; Developmental Disabilities; Embryo, Nonmammalian; Endoplasmic Reticulum; Female; Fibroblasts; Gene Expression Regulation, Developmental; Golgi Apparatus; Haploinsufficiency; Humans; Intellectual Disability; Male; Mice; Osteoporosis; RNA, Small Interfering; Severity of Illness Index; Zebrafish

Functional interpretation of ATAD3A variants in neuro-mitochondrial phenotypes. - Yap, Zheng Yie; Park, Yo Han; Wortmann, Saskia B; Gunning, Adam C; Ezer, Shlomit; Lee, Sukyeong; Duraine, Lita; Wilichowski, Ekkehard; Wilson, Kate; Mayr, Johannes A; Wagner, Matias; Li, Hong; et al. (Genome Med, 2021)
BACKGROUND: ATPase family AAA-domain containing protein 3A (ATAD3A) is a nuclear-encoded mitochondrial membrane-anchored protein involved in diverse processes including mitochondrial dynamics, mitochondrial DNA organization, and cholesterol metabolism. Biallelic deletions (null), recessive missense variants (hypomorph), and heterozygous missense variants or duplications (antimorph) in ATAD3A lead to neurological syndromes in humans. METHODS: To expand the mutational spectrum of ATAD3A variants and to provide functional interpretation of missense alleles in trans to deletion alleles, we performed exome sequencing for identification of single nucleotide variants (SNVs) and copy number variants (CNVs) in ATAD3A in individuals with neurological and mitochondrial phenotypes. A Drosophila Atad3a Gal4 knockin-null allele was generated using CRISPR-Cas9 genome editing technology to aid the interpretation of variants. RESULTS: We report 13 individuals from 8 unrelated families with biallelic ATAD3A variants. The variants included four missense variants inherited in trans to loss-of-function alleles (p.(Leu77Val), p.(Phe50Leu), p.(Arg170Trp), p.(Gly236Val)), a homozygous missense variant p.(Arg327Pro), and a heterozygous non-frameshift indel p.(Lys568del). Affected individuals exhibited findings previously associated with ATAD3A pathogenic variation, including developmental delay, hypotonia, congenital cataracts, hypertrophic cardiomyopathy, and cerebellar atrophy. Drosophila studies indicated that Phe50Leu, Gly236Val, Arg327Pro, and Lys568del are severe loss-of-function alleles leading to early developmental lethality. Further, we showed that Phe50Leu, Gly236Val, and Arg327Pro cause neurogenesis defects. On the contrary, Leu77Val and Arg170Trp are partial loss-of-function alleles that cause progressive locomotion defects and whose expression leads to an increase in autophagy and mitophagy in adult muscles. CONCLUSION: Our findings expand the allelic spectrum of ATAD3A variants and exemplify the use of a functional assay in Drosophila to aid variant interpretation.
Keywords: Adolescent; Alleles; Amino Acid Sequence; Animals; ATPases Associated with Diverse Cellular Activities; Autophagy; Computer Simulation; Drosophila; Female; Genetic Variation; Humans; Infant; Infant, Newborn; Locomotion; Male; Membrane Proteins; Mitochondria; Mitochondrial Proteins; Mitophagy; Mutation, Missense; Neurogenesis; Neurons; Pedigree; Phenotype; Polymorphism, Single Nucleotide; Young Adult

Genome-wide ancestry and introgression in a Zambian baboon hybrid zone. - Chiou, Kenneth L; Bergey, Christina M; Burrell, Andrew S; Disotell, Todd R; Jeffrey Rogers; Jolly, Clifford J; Phillips-Conroy, Jane E (Mol Ecol, 2021)
Hybridization in nature offers unique insights into the process of natural selection in incipient species and their hybrids. In order to evaluate the patterns and targets of selection, we examine a recently discovered baboon hybrid zone in the Kafue River Valley of Zambia, where Kinda baboons (Papio kindae) and grey-footed chacma baboons (P. ursinus griseipes) coexist with hybridization. We genotyped baboons at 14,962 variable genome-wide autosomal markers using double-digest RADseq. We compared ancestry patterns from this genome-wide data set to previously reported ancestry from mitochondrial-DNA and Y-chromosome sources. We also fit a Bayesian genomic cline model to scan for genes with extreme patterns of introgression. We show that the Kinda baboon Y chromosome has penetrated the species boundary to a greater extent than either mitochondrial DNA or the autosomal chromosomes. We also find evidence for overall restricted introgression in the JAK/STAT signalling pathway. Echoing results in other species including humans, we find evidence for enhanced and/or directional introgression of immune-related genes or pathways including the toll-like receptor pathway, the blood coagulation pathway, and the LY96 gene. Finally we show enhanced introgression and excess chacma baboon ancestry in the sperm tail gene ODF2. Together, our results elucidate the dynamics of introgressive hybridization in a primate system while identifying genes and pathways possibly under selection.
Keywords: Animals; Bayes Theorem; DNA, Mitochondrial; Hybridization, Genetic; Papio; Zambia

Genomic analysis and preclinical xenograft model development identify potential therapeutic targets for MYOD1-mutant soft-tissue sarcoma of childhood. - Ting, Michelle A; Reuther, Jacquelyn; Chandramohan, Raghu; Voicu, Horatiu; Gandhi, Ilavarasi; Liu, Meng; Cortes-Santiago, Nahir; Foster, Jennifer H; Hicks, John; Nuchtern, Jed; Scollon, Sarah; Plon, Sharon E; et al. (J Pathol, 2021)
The myogenic differentiation 1 gene (MYOD1) p.L122R somatic mutation was first discovered in a subset of clinically aggressive embryonal rhabdomyosarcomas and has since been described in both pediatric and adult spindle cell/sclerosing rhabdomyosarcomas. Relatively little is known about the clinical, molecular, and histopathological features of these tumors in children. In order to further characterize the genomic and clinical features of pediatric MYOD1-mutant sarcomas, we evaluated a cohort of soft-tissue sarcoma patients treated at Texas Children's Hospital. Tumor DNA was subjected to next-generation panel sequencing and/or Sanger sequencing of the MYOD1 hotspot mutation. The MYOD1 p.L122R mutation was identified in six tumors, with a variant allele fraction greater than 0.8 in three cases, suggestive of loss of heterozygosity. One sclerosing rhabdomyosarcoma lacking the MYOD1 hotspot mutation was observed to have a MYOD1 copy number gain, also with evidence of loss of heterozygosity. Cancer gene panel sequencing revealed potentially targetable alterations in six of seven (86%) patients with MYOD1 alterations, including four patients with an alteration in the PI3K-AKT pathway: two hotspot PIK3CA mutations and deletions in PTEN and TSC2. On histopathologic review, MYOD1-altered tumors exhibited spindle and/or round cells and varying degrees of hyaline sclerosis. At last follow-up, six patients had died of disease and the seventh progressed early and was subsequently lost to follow-up. Both pre- and post-therapy patient-derived xenograft models were generated from one patient's tumor. These models were confirmed to harbor the MYOD1 and PIK3CA mutations seen in the primary tumor and were shown to be sensitive to PI3K/mTOR inhibition in vitro and in vivo. In conclusion, this study adds to recent reports describing the clinicopathologic and genomic features of MYOD1-altered soft-tissue sarcomas in children, including dismal prognosis and potential molecular targets for therapy. The novel preclinical models developed will facilitate further biological and preclinical study of this rare and aggressive tumor. © 2021 The Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.
Keywords: Adolescent; Animals; Antineoplastic Agents; Child; Female; Genomics; Humans; Imidazoles; Male; Mice; Mutation; MyoD Protein; Quinolines; Rhabdomyosarcoma; Soft Tissue Neoplasms; Xenograft Model Antitumor Assays; Young Adult

A High-throughput Approach to Identify Effective Systemic Agents for the Treatment of Anaplastic Thyroid Carcinoma. - Henderson, Ying C; Mohamed, Abdallah S R; Maniakas, Anastasios; Chen, Yunyun; Powell, Reid T; Peng, Shaohua; Cardenas, Maria; Williams, Michelle D; Bell, Diana; Zafereo, Mark E; Wang, Rui Jennifer; Steven E Scherer; et al. (J Clin Endocrinol Metab, 2021)
BACKGROUND: Despite the use of aggressive multimodality treatment, most anaplastic thyroid carcinoma (ATC) patients die within a year of diagnosis. Although the combination of BRAF and MEK inhibitors has recently been approved for use in BRAF-mutated ATC, they remain effective in a minority of patients who are likely to develop drug resistance. There remains a critical clinical need for effective systemic agents for ATC with a reasonable toxicity profile to allow for rapid translational development. MATERIAL AND METHODS: Twelve human thyroid cancer cell lines with comprehensive genomic characterization were used in a high-throughput screening (HTS) of 257 compounds to select agents with maximal growth inhibition. Cell proliferation, colony formation, orthotopic thyroid models, and patient-derived xenograft (PDX) models were used to validate the selected agents. RESULTS: Seventeen compounds were effective, and docetaxel, LBH-589, and pralatrexate were selected for additional in vitro and in vivo analysis as they have been previously approved by the US Food and Drug Administration for other cancers. Significant tumor growth inhibition (TGI) was detected in all tested models treated with LBH-589; pralatrexate demonstrated significant TGI in the orthotopic papillary thyroid carcinoma model and 2 PDX models; and docetaxel demonstrated significant TGI only in the context of mutant TP53. CONCLUSIONS: HTS identified classes of systemic agents that demonstrate preferential effectiveness against aggressive thyroid cancers, particularly those with mutant TP53. Preclinical validation in both orthotopic and PDX models, which are accurate in vivo models mimicking tumor microenvironment, may support initiation of early-phase clinical trials in non-BRAF mutated or refractory to BRAF/MEK inhibition ATC.
Keywords: Animals; Antineoplastic Agents; Carcinogenicity Tests; Cell Line, Tumor; Disease Models, Animal; High-Throughput Screening Assays; Humans; Protein Kinase Inhibitors; Proto-Oncogene Proteins B-raf; Thyroid Carcinoma, Anaplastic; Thyroid Neoplasms; Tumor Microenvironment

Infant inhibited temperament in primates predicts adult behavior, is heritable, and is associated with anxiety-relevant genetic variation. - Fox, Andrew S; R. Alan Harris; Rosso, Laura Del; Raveendran, Muthuswamy; Kamboj, Shawn; Kinnally, Erin L; Capitanio, John P; Jeffrey Rogers (Mol Psychiatry, 2021)
An anxious or inhibited temperament (IT) early in life is a major risk factor for the later development of stress-related psychopathology. Starting in infancy, nonhuman primates, like humans, begin to reveal their temperament when exposed to novel situations. Here, in Study 1 we demonstrate this infant IT predicts adult behavior. Specifically, in over 600 monkeys, we found that individuals scored as inhibited during infancy were more likely to refuse treats offered by potentially-threatening human experimenters as adults. In Study 2, using a sample of over 4000 monkeys from a large multi-generational family pedigree, we demonstrate that infant IT is partially heritable. The data revealed infant IT to reflect a co-inherited substrate that manifests across multiple latent variables. Finally, in Study 3 we performed whole-genome sequencing in 106 monkeys to identify IT-associated single-nucleotide variations (SNVs). Results demonstrated a genome-wide significant SNV near CTNNA2, suggesting a molecular target worthy of additional investigation. Moreover, we observed lower p values in genes implicated in human association studies of neuroticism and depression. Together, these data demonstrate the utility of our model of infant inhibited temperament in the rhesus monkey to facilitate discovery of genes that are relevant to the long-term inherited risk to develop anxiety and depressive disorders.
Keywords: Animals; Anxiety; Anxiety Disorders; Genetic Variation; Macaca mulatta; Temperament

Loss of C2orf69 defines a fatal autoinflammatory syndrome in humans and zebrafish that evokes a glycogen-storage-associated mitochondriopathy. - Wong, Hui Hui; Seet, Sze Hwee; Maier, Michael; Gurel, Ayse; Traspas, Ricardo Moreno; Lee, Cheryl; Zhang, Shan; Talim, Beril; Loh, Abigail Y T; Chia, Crystal Y; Teoh, Tze Shin; Sng, Danielle; et al. (Am J Hum Genet, 2021)
Human C2orf69 is an evolutionarily conserved gene whose function is unknown. Here, we report eight unrelated families from which 20 children presented with a fatal syndrome consisting of severe autoinflammation and progredient leukoencephalopathy with recurrent seizures; 12 of these subjects, whose DNA was available, segregated homozygous loss-of-function C2orf69 variants. C2ORF69 bears homology to esterase enzymes, and orthologs can be found in most eukaryotic genomes, including that of unicellular phytoplankton. We found that endogenous C2ORF69 (1) is loosely bound to mitochondria, (2) affects mitochondrial membrane potential and oxidative respiration in cultured neurons, and (3) controls the levels of the glycogen branching enzyme 1 (GBE1) consistent with a glycogen-storage-associated mitochondriopathy. We show that CRISPR-Cas9-mediated inactivation of zebrafish C2orf69 results in lethality by 8 months of age due to spontaneous epileptic seizures, which is preceded by persistent brain inflammation. Collectively, our results delineate an autoinflammatory Mendelian disorder of C2orf69 deficiency that disrupts the development/homeostasis of the immune and central nervous systems.
Keywords: Animals; Biological Evolution; Cell Line; CRISPR-Cas Systems; Encephalitis; Female; Genes, Recessive; Glycogen; Humans; Inflammation; Male; Membrane Proteins; Mitochondrial Diseases; Pedigree; Seizures; Zebrafish

Multiplexed Simian Immunodeficiency Virus-Specific Paired RNA-Guided Cas9 Nickases Inactivate Proviral DNA. - Smith, Lisa M; Ladner, Jason T; Hodara, Vida L; Parodi, Laura M; R. Alan Harris; Callery, Jessica E; Lai, Zhao; Zou, Yi; Raveedran, Muthuswamy; Jeffrey Rogers; Giavedoni, Luis D (J Virol, 2021)
Human and simian immunodeficiency virus (HIV and SIV) infections establish lifelong reservoirs of cells harboring an integrated proviral genome. Genome editing CRISPR-associated Cas9 nucleases, combined with SIV-specific guiding RNA (gRNA) molecules, inactivate integrated provirus DNA and in animal models. We generated RNA-guided Cas9 nucleases (RGNu) and nickases (RGNi) targeting conserved SIV regions with no homology in the human or rhesus macaque genome. Assays in cells cotransfected with SIV provirus and plasmids coding for RGNus identified SIV long terminal repeat (LTR), -activation response (TAR) element, and ribosome slip site (RSS) regions as the most effective at virus suppression; RGNi targeting these regions inhibited virus production significantly. Multiplex plasmids that coexpressed these three RGNu (Nu3), or six (three pairs) RGNi (Ni6), were more efficient at virus suppression than any combination of individual RGNu and RGNi plasmids. Both Nu3 and Ni6 plasmids were tested in lymphoid cells chronically infected with SIV, and whole-genome sequencing was used to determine on- and off-target mutations. Treatment with these all-in-one plasmids resulted in similar levels of mutations of viral sequences from the cellular genome; Nu3 induced indels at the 3 SIV-specific sites, whereas for Ni6 indels were present at the LTR and TAR sites. Levels of off-target effects detected by two different algorithms were indistinguishable from background mutations. In summary, we demonstrate that Cas9 nickase in association with gRNA pairs can specifically eliminate parts of the integrated provirus DNA; also, we show that careful design of an all-in-one plasmid coding for 3 gRNAs and Cas9 nuclease inhibits SIV production with undetectable off-target mutations, making these tools a desirable prospect for moving into animal studies. Our approach to HIV cure, utilizing the translatable SIV/rhesus macaque model system, aims at provirus inactivation and its removal with the least possible off-target side effects. We developed single molecules that delivered either three truncated SIV-specific gRNAs along with Cas9 nuclease or three pairs of SIV-specific gRNAs (six individual gRNAs) along with Cas9 nickase to enhance efficacy of on-target mutagenesis. Whole-genome sequencing demonstrated effective SIV sequence mutation and inactivation and the absence of demonstrable off-target mutations. These results open the possibility to employ Cas9 variants that introduce single-strand DNA breaks to eliminate integrated proviral DNA.
Keywords: Animals; CRISPR-Cas Systems; Deoxyribonuclease I; DNA; Endonucleases; Gene Editing; HEK293 Cells; Humans; Macaca mulatta; Mutagenesis; Plasmids; Proviruses; RNA, Guide, Kinetoplastida; Simian Immunodeficiency Virus

Neuropeptide S receptor 1 is a nonhormonal treatment target in endometriosis. - Tapmeier, Thomas T; Rahmioglu, Nilufer; Lin, Jianghai; De Leo, Bianca; Obendorf, Maik; Raveendran, Muthuswamy; Fischer, Oliver M; Bafligil, Cemsel; Guo, Manman; R. Alan Harris; Hess-Stumpp, Holger; Laux-Biehlmann, Alexis; et al. (Sci Transl Med, 2021)
Endometriosis is a common chronic inflammatory condition causing pelvic pain and infertility in women, with limited treatment options and 50% heritability. We leveraged genetic analyses in two species with spontaneous endometriosis, humans and the rhesus macaque, to uncover treatment targets. We sequenced DNA from 32 human families contributing to a genetic linkage signal on chromosome 7p13-15 and observed significant overrepresentation of predicted deleterious low-frequency coding variants in , the gene encoding neuropeptide S receptor 1, in cases (predominantly stage III/IV) versus controls ( = 7.8 × 10). Significant linkage to the region orthologous to human 7p13-15 was replicated in a pedigree of 849 rhesus macaques ( = 0.0095). Targeted association analyses in 3194 surgically confirmed, unrelated cases and 7060 controls revealed that a common insertion/deletion variant, rs142885915, was significantly associated with stage III/IV endometriosis ( = 5.2 × 10; odds ratio, 1.23; 95% CI, 1.09 to 1.39). Immunohistochemistry, qRT-PCR, and flow cytometry experiments demonstrated that NPSR1 was expressed in glandular epithelium from eutopic and ectopic endometrium, and on monocytes in peritoneal fluid. The NPSR1 inhibitor SHA 68R blocked NPSR1-mediated signaling, proinflammatory TNF-α release, and monocyte chemotaxis in vitro ( < 0.01), and led to a significant reduction of inflammatory cell infiltrate and abdominal pain ( < 0.05) in a mouse model of peritoneal inflammation as well as in a mouse model of endometriosis. We conclude that the NPSR1/NPS system is a genetically validated, nonhormonal target for the treatment of endometriosis with likely increased relevance to stage III/IV disease.
Keywords: Animals; Endometriosis; Endometrium; Female; Humans; Macaca mulatta; Mice; Receptors, G-Protein-Coupled; Tumor Necrosis Factor-alpha

NMIHBA results from hypomorphic PRUNE1 variants that lack short-chain exopolyphosphatase activity. - Nistala, Harikiran; Dronzek, John; Gonzaga-Jauregui, Claudia; Chim, Shek Man; Rajamani, Saathyaki; Nuwayhid, Samer; Delgado, Dennis; Burke, Elizabeth; Karaca, Ender; Franklin, Matthew C; Sarangapani, Prasad; Podgorski, Michael; et al. (Hum Mol Genet, 2021)
Neurodevelopmental disorder with microcephaly, hypotonia and variable brain anomalies (NMIHBA) is an autosomal recessive neurodevelopmental and neurodegenerative disorder characterized by global developmental delay and severe intellectual disability. Microcephaly, progressive cortical atrophy, cerebellar hypoplasia and delayed myelination are neurological hallmarks in affected individuals. NMIHBA is caused by biallelic variants in PRUNE1 encoding prune exopolyphosphatase 1. We provide in-depth clinical description of two affected siblings harboring compound heterozygous variant alleles, c.383G > A (p.Arg128Gln), c.520G > T (p.Gly174*) in PRUNE1. To gain insights into disease biology, we biochemically characterized missense variants within the conserved N-terminal aspartic acid-histidine-histidine (DHH) motif and provide evidence that they result in the destabilization of protein structure and/or loss of exopolyphosphatase activity. Genetic ablation of Prune1 results in midgestational lethality in mice, associated with perturbations to embryonic growth and vascular development. Our findings suggest that NMIHBA results from hypomorphic variant alleles in humans and underscore the potential key role of PRUNE1 exopolyphoshatase activity in neurodevelopment.
Keywords: Acid Anhydride Hydrolases; Alleles; Animals; Child, Preschool; Female; Humans; Infant; Intellectual Disability; Male; Mice; Microcephaly; Muscle Hypotonia; Mutation; Neurodevelopmental Disorders; Pedigree; Phenotype; Phosphoric Monoester Hydrolases

Novel Anaplastic Thyroid Cancer PDXs and Cell Lines: Expanding Preclinical Models of Genetic Diversity. - Maniakas, Anastasios; Henderson, Ying C; Hei, Hu; Peng, Shaohua; Chen, Yunyun; Jiang, Yujie; Ji, Shuangxi; Cardenas, Maria; Chiu, Yulun; Bell, Diana; Williams, Michelle D; Hofmann, Marie-Claude; et al. (J Clin Endocrinol Metab, 2021)
CONTEXT: Anaplastic thyroid cancer (ATC) is a rare, aggressive, and deadly disease. Robust preclinical thyroid cancer models are needed to adequately develop and study novel therapeutic agents. Patient-derived xenograft (PDX) models may resemble patient tumors by recapitulating key genetic alterations and gene expression patterns, making them excellent preclinical models for drug response evaluation. OBJECTIVE: We developed distinct ATC PDX models concurrently with cell lines and characterized them in vitro and in vivo. METHODS: Fresh thyroid tumor from patients with a preoperative diagnosis of ATC was surgically collected and divided for concurrent cell line and PDX model development. Cell lines were created by generating single cells through enzymatic digestion. PDX models were developed following direct subcutaneous implantation of fresh tumor on the flank of immune compromised/athymic mice. RESULTS: Six ATC PDX models and 4 cell lines were developed with distinct genetic profiles. Mutational characterization showed one BRAF/TP53/CDKN2A, one BRAF/CDKN2A, one BRAF/TP53, one TP53 only, one TERT-promoter/HRAS, and one TERT-promoter/KRAS/TP53/NF2/NFE2L2 mutated phenotype. Hematoxylin-eosin staining comparing the PDX models to the original patient surgical specimens show remarkable resemblance, while immunohistochemistry stains for important biomarkers were in full concordance (cytokeratin, TTF-1, PAX8, BRAF). Short tandem repeats DNA fingerprinting analysis of all PDX models and cell lines showed strong concordance with the original tumor. PDX successful establishment rate was 32%. CONCLUSION: We have developed and characterized 6 novel ATC PDX models with 4 matching cell lines. Each PDX model harbors a distinct genetic profile, making them excellent tools for preclinical therapeutic trials.
Keywords: Aged; Animals; Apoptosis; Biomarkers, Tumor; Cell Proliferation; Disease Models, Animal; Female; Gene Expression Regulation, Neoplastic; Humans; Male; Mice; Middle Aged; Phenotype; Prognosis; Survival Rate; Thyroid Carcinoma, Anaplastic; Thyroid Neoplasms; Tumor Cells, Cultured; Xenograft Model Antitumor Assays

Origins and Long-Term Patterns of Copy-Number Variation in Rhesus Macaques. - Thomas, Gregg W C; Wang, Richard J; Nguyen, Jelena; R. Alan Harris; Raveendran, Muthuswamy; Jeffrey Rogers; Hahn, Matthew W (Mol Biol Evol, 2021)
Mutations play a key role in the development of disease in an individual and the evolution of traits within species. Recent work in humans and other primates has clarified the origins and patterns of single-nucleotide variants, showing that most arise in the father's germline during spermatogenesis. It remains unknown whether larger mutations, such as deletions and duplications of hundreds or thousands of nucleotides, follow similar patterns. Such mutations lead to copy-number variation (CNV) within and between species, and can have profound effects by deleting or duplicating genes. Here, we analyze patterns of CNV mutations in 32 rhesus macaque individuals from 14 parent-offspring trios. We find the rate of CNV mutations per generation is low (less than one per genome) and we observe no correlation between parental age and the number of CNVs that are passed on to offspring. We also examine segregating CNVs within the rhesus macaque sample and compare them to a similar data set from humans, finding that both species have far more segregating deletions than duplications. We contrast this with long-term patterns of gene copy-number evolution between 17 mammals, where the proportion of deletions that become fixed along the macaque lineage is much smaller than the proportion of segregating deletions. These results suggest purifying selection acting on deletions, such that the majority of them are removed from the population over time. Rhesus macaques are an important biomedical model organism, so these results will aid in our understanding of this species and the disease models it supports.
Keywords: Animals; DNA Copy Number Variations; Female; Gene Duplication; High-Throughput Nucleotide Sequencing; Humans; Macaca mulatta; Male; Mutation; Selection, Genetic; Sequence Deletion; Whole Genome Sequencing

Pedigree reconstruction and distant pairwise relatedness estimation from genome sequence data: A demonstration in a population of rhesus macaques (Macaca mulatta). - Petty, Lauren E; Phillippi-Falkenstein, Kathrine; Kubisch, H Michael; Raveendran, Muthuswamy; R. Alan Harris; Vallender, Eric J; Huff, Chad D; Bohm, Rudolf P; Jeffrey Rogers; Below, Jennifer E (Mol Ecol Resour, 2021)
A primary challenge in the analysis of free-ranging animal populations is the accurate estimation of relatedness among individuals. Many aspects of population analysis rely on knowledge of relatedness patterns, including socioecology, demography, heritability and gene mapping analyses, wildlife conservation and the management of breeding colonies. Methods for determining relatedness using genome-wide data have improved our ability to determine kinship and reconstruct pedigrees in humans. However, methods for reconstructing complex pedigree structures and estimating distant relatedness (beyond third-degree) have not been widely applied to other species. We sequenced the genomes of 150 male rhesus macaques from the Tulane National Primate Research Center colony to estimate pairwise relatedness, reconstruct closely related pedigrees, estimate more distant relationships and augment colony records. Methods for determining relatedness developed for human genetic data were applied and evaluated in the analysis of nonhuman primates, including identity-by-descent-based methods for pedigree reconstruction and shared segment-based inference of more distant relatedness. We compared the genotype-based pedigrees and estimated relationships to available colony pedigree records and found high concordance (95.5% agreement) between expected and identified relationships for close relatives. In addition, we detected distant relationships not captured in colony records, including some as distant as twelfth-degree. Furthermore, while deep sequence coverage is preferable, we show that this approach can also provide valuable information when only low-coverage (5×) sequence data is available. Our findings demonstrate the value of these methods for determination of relatedness in various animal populations, with diverse applications to conservation biology, evolutionary and ecological research and biomedical studies.
Keywords: Animals; Breeding; Chromosome Mapping; Genetics, Population; Genome; Genotype; Macaca mulatta; Male; Pedigree; Polymorphism, Single Nucleotide

Primary Infection May Be an Underlying Factor Contributing to Lethal Hemorrhagic Disease Caused by Elephant Endotheliotropic Herpesvirus 3 in African Elephants (). - Pursell, Taylor; Spencer Clinton, Jennifer L; Tan, Jie; Peng, Rongsheng; Xiang Qin; Harshavardhan Doddapaneni; Menon, Vipin; Momin, Zeineen; Kottapalli, Kavya; Howard, Lauren; Latimer, Erin; Heaggans, Sarah; et al. (Microbiol Spectr, 2021)
Distinct but related species of elephant endotheliotropic herpesviruses (EEHVs) circulate within Asian and African elephant populations. Primary infection with EEHVs endemic among Asian elephants can cause clinical illness and lethal EEHV hemorrhagic disease (EEHV-HD). The degree to which this occurs among African elephants has not been fully established. Recent cases of EEHV-HD caused by the EEHV3 species in African elephants housed in North American zoos has heightened concern about the susceptibility of this elephant species to EEHV-HD. In this study, we utilize the luciferase immunoprecipitation system (LIPS) to generate a serological assay specific for EEHV3 in African elephants by detecting antibodies against the EEHV3 E34 protein. The results showed that the majority of tested elephants from four separate and genetically unrelated herds, including five elephants that survived clinical illness associated with EEHV3, were positive for prior infection with EEHV3. However, African elephants who succumbed to EEHV3-HD were seronegative for EEHV3 prior to lethal infection. This supports the hypothesis that fatal EEHV-HD caused by EEHV3 is associated with primary infection rather than reactivation of latent virus. Lastly, we observed that African elephants, like Asian elephants, acquire abundant anti-EEHV antibodies prenatally and that anti-EEHV3 specific antibodies were either never detected or declined to undetectable levels in those animals that died from lethal disease following EEHV3 infection. Prior to 2019, only five cases of clinical disease from EEHV infection among African elephants had been documented. Since 2019, there have been at least seven EEHV-HD cases in North American zoos, resulting in three fatalities, all associated with EEHV3. Evidence is accumulating to suggest that EEHV-associated clinical illness and death among Asian elephants is due to primary infection and may be associated with waning anti-EEHV antibody levels in young elephants. The development of the EEHV3 serological test described in this study enabled us to confirm that similar dynamics may be contributing to EEHV-HD in African elephants. The ability to screen for EEHV immune status in African elephant calves will have a major impact on managing captive African elephant herds and will provide new tools for investigating and understanding EEHV in wild populations.
Keywords: Animals; Animals, Zoo; Antibodies, Viral; Elephants; Female; Hemorrhagic Disorders; Herpesvirus 3, Equid; Male; Serologic Tests; Viral Zoonoses

TQFL12, a novel synthetic derivative of TQ, inhibits triple-negative breast cancer metastasis and invasion through activating AMPK/ACC pathway. - Wei, Chunli; Zou, Hui; Xiao, Ting; Liu, Xiaoyan; Wang, Qianqian; Cheng, Jingliang; Fu, Shangyi; Peng, Jiangzhou; Xie, Xin; Fu, Junjiang (J Cell Mol Med, 2021)
Thymoquinone (TQ) has been reported as an anti-tumour drug widely studied in various tumours, and its mechanism and effect of which has become a focus of current research. However, previous studies from our laboratory and other groups found that TQ showed weak anti-tumour effects in many cancer cell lines and animal models. Therefore, it is necessary to modify and optimize the structure of TQ to obtain new chemical entities with high efficiency and low toxicity as candidates for development of new drugs in treating cancer. Therefore, we designed and synthesized several TQ derivatives. Systematic analysis, including in vitro and in vivo, was conducted on a panel of triple-negative breast cancer (TNBC) cells and mouse model to demonstrate whether TQFL12, a new TQ derivative, is more efficient than TQ. We found that the anti-proliferative effect of TQFL12 against TNBC cells is significantly stronger than TQ. We also demonstrated TQFL12 affects different aspects in breast cancer development including cell proliferation, migration, invasion and apoptosis. Moreover, TQFL12 inhibited tumour growth and metastasis in cancer cell-derived xenograft mouse model, with less toxicity compared with TQ. Finally, mechanism research indicated that TQFL12 increased AMPK/ACC activity by stabilizing AMPKα, while molecular docking supported the direct interaction between TQFL12 and AMPKα. Taken together, our findings suggest that TQFL12, as a novel chemical entity, possesses a better inhibitory effect on TNBC cells and less toxicity in both in vitro and in vivo studies. As such, TQFL12 could serve as a potential therapeutic agent for breast cancer.
Keywords: Acetyl-CoA Carboxylase; AMP-Activated Protein Kinases; Animals; Antineoplastic Agents; Apoptosis; Benzoquinones; Cell Cycle; Cell Line, Tumor; Cell Movement; Disease Models, Animal; Drug Tapering; Humans; Mice; Models, Molecular; Protein Binding; Signal Transduction; Structure-Activity Relationship; Triple Negative Breast Neoplasms; Xenograft Model Antitumor Assays

Transcript isoforms of Reep6 have distinct functions in the retina. - Liang, Qingnan; Wu, Nathaniel; Zaneveld, Smriti; Liu, Hehe; Fu, Shangyi; Wang, Keqing; Bertrand, Renae; Wang, Jun; Yumei Li; Rui Chen (Hum Mol Genet, 2021)
Much of the complexity of the eukaryotic cell transcriptome is due to the alternative splicing of mRNA. However, knowledge on how transcriptome complexity is translated into functional complexity remains limited. For example, although different isoforms of a gene may show distinct temporal and spatial expression patterns, it is largely unknown whether these isoforms encode proteins with distinct functions matching their expression pattern. In this report, we investigated the function and relationship of the two isoforms of Reep6, namely Reep6.1 and Reep6.2, in rod photoreceptor cells. These two isoforms result from the alternative splicing of exon 5 and show mutually exclusive expression patterns. Reep6.2 is the canonical isoform that is expressed in non-retinal tissues, whereas Reep6.1 is the only expressed isoform in the adult retina. The Reep6.1 isoform-specific knockout mouse, Reep6E5/E5, is generated by deleting exon 5 and a homozygous deletion phenotypically displayed a rod degeneration phenotype comparable to a Reep6 full knockout mouse, indicating that the Reep6.1 isoform is essential for the rod photoreceptor cell survival. Consistent with the results obtained from a loss-of-function experiment, overexpression of Reep6.2 failed to rescue the rod degeneration phenotype of Reep6 knockout mice whereas overexpression of Reep6.1 does lead to rescue. These results demonstrate that, consistent with the expression pattern of the isoform, Reep6.1 has rod-specific functions that cannot be substituted by its canonical isoform. Our findings suggested that a strict regulation of splicing is required for the maintenance of photoreceptor cells.
Keywords: Alternative Splicing; Animals; Cerebral Cortex; Electroretinography; Eye Proteins; Fluorescent Antibody Technique; Gene Expression Regulation; Genotype; Humans; Immunohistochemistry; Membrane Proteins; Mice; Mice, Knockout; Phenotype; Photoreceptor Cells, Vertebrate; Protein Isoforms; Retina; RNA, Messenger

Transcriptional Reprogramming Differentiates Active from Inactive ESR1 Fusions in Endocrine Therapy-Refractory Metastatic Breast Cancer. - Gou, Xuxu; Anurag, Meenakshi; Lei, Jonathan T; Kim, Beom-Jun; Singh, Purba; Seker, Sinem; Fandino, Diana; Han, Airi; Rehman, Saif; Jianhong Hu; Korchina, Viktoriya; Harshavardhan Doddapaneni; et al. (Cancer Res, 2021)
Genomic analysis has recently identified multiple gene translocations in estrogen receptor alpha-positive (ERα) metastatic breast cancer (MBC) that encode chimeric proteins whereby the ESR1 ligand binding domain (LBD) is replaced by C-terminal sequences from many different gene partners. Here we functionally screened 15 ESR1 fusions and identified 10 that promoted estradiol-independent cell growth, motility, invasion, epithelial-to-mesenchymal transition, and resistance to fulvestrant. RNA sequencing identified a gene expression pattern specific to functionally active ESR1 gene fusions that was subsequently reduced to a diagnostic 24-gene signature. This signature was further examined in 20 ERα patient-derived xenografts and in 55 ERα MBC samples. The 24-gene signature successfully identified cases harboring gene fusions and also accurately diagnosed the presence of activating LBD point mutations. Therefore, the 24-gene signature represents an efficient approach to screening samples for the presence of diverse somatic mutations and translocations that drive endocrine treatment failure in MBC. SIGNIFICANCE: This study identifies a gene signature diagnostic for functional ESR1 fusions that drive poor outcome in advanced breast cancer, which could also help guide precision medicine approaches in patients harboring mutations.
Keywords: Animals; Antineoplastic Agents, Hormonal; Apoptosis; Biomarkers, Tumor; Breast Neoplasms; Cell Proliferation; Drug Resistance, Neoplasm; Estrogen Receptor alpha; Female; Gene Expression Regulation, Neoplastic; Humans; Mice; Mice, Nude; Mutation; Oncogene Proteins, Fusion; Prognosis; Survival Rate; Transcriptome; Tumor Cells, Cultured; Xenograft Model Antitumor Assays

Variation in predicted COVID-19 risk among lemurs and lorises. - Melin, Amanda D; Orkin, Joseph D; Janiak, Mareike C; Valenzuela, Alejandro; Kuderna, Lukas; Marrone, Frank; Ramangason, Hasinala; Horvath, Julie E; Roos, Christian; Kitchener, Andrew C; Khor, Chiea Chuen; Lim, Weng Khong; et al. (Am J Primatol, 2021)
The novel coronavirus SARS-CoV-2, which in humans leads to the disease COVID-19, has caused global disruption and more than 2 million fatalities since it first emerged in late 2019. As we write, infection rates are at their highest point globally and are rising extremely rapidly in some areas due to more infectious variants. The primary target of SARS-CoV-2 is the cellular receptor angiotensin-converting enzyme-2 (ACE2). Recent sequence analyses of the ACE2 gene predict that many nonhuman primates are also likely to be highly susceptible to infection. However, the anticipated risk is not equal across the Order. Furthermore, some taxonomic groups show high ACE2 amino acid conservation, while others exhibit high variability at this locus. As an example of the latter, analyses of strepsirrhine primate ACE2 sequences to date indicate large variation among lemurs and lorises compared to other primate clades despite low sampling effort. Here, we report ACE2 gene and protein sequences for 71 individual strepsirrhines, spanning 51 species and 19 genera. Our study reinforces previous results while finding additional variability in other strepsirrhine species, and suggests several clades of lemurs have high potential susceptibility to SARS-CoV-2 infection. Troublingly, some species, including the rare and endangered aye-aye (Daubentonia madagascariensis), as well as those in the genera Avahi and Propithecus, may be at high risk. Given that lemurs are endemic to Madagascar and among the primates at highest risk of extinction globally, further understanding of the potential threat of COVID-19 to their health should be a conservation priority. All feasible actions should be taken to limit their exposure to SARS-CoV-2.
Keywords: Angiotensin-Converting Enzyme 2; Animals; COVID-19; Lemur; Lorisidae; Primate Diseases; Risk Factors

BICRA, a SWI/SNF Complex Member, Is Associated with BAF-Disorder Related Phenotypes in Humans and Model Organisms. - Barish, Scott; Barakat, Tahsin Stefan; Michel, Brittany C; Mashtalir, Nazar; Phillips, Jennifer B; Valencia, Alfredo M; Ugur, Berrak; Wegner, Jeremy; Scott, Tiana M; Bostwick, Brett; David R Murdock; Dai, Hongzheng; et al. (Am J Hum Genet, 2020)
SWI/SNF-related intellectual disability disorders (SSRIDDs) are rare neurodevelopmental disorders characterized by developmental disability, coarse facial features, and fifth digit/nail hypoplasia that are caused by pathogenic variants in genes that encode for members of the SWI/SNF (or BAF) family of chromatin remodeling complexes. We have identified 12 individuals with rare variants (10 loss-of-function, 2 missense) in the BICRA (BRD4 interacting chromatin remodeling complex-associated protein) gene, also known as GLTSCR1, which encodes a subunit of the non-canonical BAF (ncBAF) complex. These individuals exhibited neurodevelopmental phenotypes that include developmental delay, intellectual disability, autism spectrum disorder, and behavioral abnormalities as well as dysmorphic features. Notably, the majority of individuals lack the fifth digit/nail hypoplasia phenotype, a hallmark of most SSRIDDs. To confirm the role of BICRA in the development of these phenotypes, we performed functional characterization of the zebrafish and Drosophila orthologs of BICRA. In zebrafish, a mutation of bicra that mimics one of the loss-of-function variants leads to craniofacial defects possibly akin to the dysmorphic facial features seen in individuals harboring putatively pathogenic BICRA variants. We further show that Bicra physically binds to other non-canonical ncBAF complex members, including the BRD9/7 ortholog, CG7154, and is the defining member of the ncBAF complex in flies. Like other SWI/SNF complex members, loss of Bicra function in flies acts as a dominant enhancer of position effect variegation but in a more context-specific manner. We conclude that haploinsufficiency of BICRA leads to a unique SSRIDD in humans whose phenotypes overlap with those previously reported.
Keywords: Adolescent; Animals; Child; Child, Preschool; Chromosomal Proteins, Non-Histone; Developmental Disabilities; Drosophila melanogaster; Drosophila Proteins; Female; Genes, Dominant; Genetic Variation; Haploinsufficiency; Humans; Infant; Male; Microscopy, Confocal; Mutation, Missense; Neuroglia; Neurons; Phenotype; Protein Binding; Tumor Suppressor Proteins; Zebrafish; Zebrafish Proteins

Brown marmorated stink bug, Halyomorpha halys (Stål), genome: putative underpinnings of polyphagy, insecticide resistance potential and biology of a top worldwide pest. - Sparks, Michael E; Bansal, Raman; Benoit, Joshua B; Blackburn, Michael B; Chao, Hsu; Chen, Mengyao; Cheng, Sammy; Childers, Christopher; Dinh, Huyen; Harshavardhan Doddapaneni; Dugan, Shannon; Elpidina, Elena N; et al. (BMC Genomics, 2020)
BACKGROUND: Halyomorpha halys (Stål), the brown marmorated stink bug, is a highly invasive insect species due in part to its exceptionally high levels of polyphagy. This species is also a nuisance due to overwintering in human-made structures. It has caused significant agricultural losses in recent years along the Atlantic seaboard of North America and in continental Europe. Genomic resources will assist with determining the molecular basis for this species' feeding and habitat traits, defining potential targets for pest management strategies. RESULTS: Analysis of the 1.15-Gb draft genome assembly has identified a wide variety of genetic elements underpinning the biological characteristics of this formidable pest species, encompassing the roles of sensory functions, digestion, immunity, detoxification and development, all of which likely support H. halys' capacity for invasiveness. Many of the genes identified herein have potential for biomolecular pesticide applications. CONCLUSIONS: Availability of the H. halys genome sequence will be useful for the development of environmentally friendly biomolecular pesticides to be applied in concert with more traditional, synthetic chemical-based controls.
Keywords: Animals; Ecosystem; Gene Transfer, Horizontal; Genome Size; Heteroptera; Insect Proteins; Insecticide Resistance; Introduced Species; Phylogeny; Whole Genome Sequencing

A CLN6-CLN8 complex recruits lysosomal enzymes at the ER for Golgi transfer. - Bajaj, Lakshya; Sharma, Jaiprakash; di Ronza, Alberto; Zhang, Pengcheng; Eblimit, Aiden; Pal, Rituraj; Roman, Dany; Collette, John R; Booth, Clarissa; Chang, Kevin T; Sifers, Richard N; Jung, Sung Y; et al. (J Clin Invest, 2020)
Lysosomal enzymes are synthesized in the endoplasmic reticulum (ER) and transferred to the Golgi complex by interaction with the Batten disease protein CLN8 (ceroid lipofuscinosis, neuronal, 8). Here we investigated the relationship of this pathway with CLN6, an ER-associated protein of unknown function that is defective in a different Batten disease subtype. Experiments focused on protein interaction and trafficking identified CLN6 as an obligate component of a CLN6-CLN8 complex (herein referred to as EGRESS: ER-to-Golgi relaying of enzymes of the lysosomal system), which recruits lysosomal enzymes at the ER to promote their Golgi transfer. Mutagenesis experiments showed that the second luminal loop of CLN6 is required for the interaction of CLN6 with the enzymes but dispensable for interaction with CLN8. In vitro and in vivo studies showed that CLN6 deficiency results in inefficient ER export of lysosomal enzymes and diminished levels of the enzymes at the lysosome. Mice lacking both CLN6 and CLN8 did not display aggravated pathology compared with the single deficiencies, indicating that the EGRESS complex works as a functional unit. These results identify CLN6 and the EGRESS complex as key players in lysosome biogenesis and shed light on the molecular etiology of Batten disease caused by defects in CLN6.
Keywords: Animals; Endoplasmic Reticulum; Golgi Apparatus; Lysosomes; Membrane Proteins; Mice; Mice, Knockout; Multiprotein Complexes; Neuronal Ceroid-Lipofuscinoses; Protein Transport

Combination of whole exome sequencing and animal modeling identifies TMPRSS9 as a candidate gene for autism spectrum disorder. - Chen, Chun-An; Pal, Rituraj; Yin, Jiani; Tao, Huifang; Amawi, Abdallah; Aniko Sabo; Bainbridge, Matthew N; Richard A Gibbs; Zoghbi, Huda Y; Schaaf, Christian P (Hum Mol Genet, 2020)
Autism spectrum disorders are associated with some degree of developmental regression in up to 30% of all cases. Rarely, however, is the regression so extreme that a developmentally advanced young child would lose almost all ability to communicate and interact with her surroundings. We applied trio whole exome sequencing to a young woman who experienced extreme developmental regression starting at 2.5 years of age and identified compound heterozygous nonsense mutations in TMPRSS9, which encodes for polyserase-1, a transmembrane serine protease of poorly understood physiological function. Using semiquantitative polymerase chain reaction, we showed that Tmprss9 is expressed in various mouse tissues, including the brain. To study the consequences of TMPRSS9 loss of function on the mammalian brain, we generated a knockout mouse model. Through a battery of behavioral assays, we found that Tmprss9-/- mice showed decreased social interest and social recognition. We observed a borderline recognition memory deficit by novel object recognition in aged Tmprss9-/- female mice, but not in aged Tmprss9-/- male mice or younger adult Tmprss9-/- mice in both sexes. This study provides evidence to suggest that loss of function variants in TMPRSS9 are related to an autism spectrum disorder. However, the identification of more individuals with similar phenotypes and TMPRSS9 loss of function variants is required to establish a robust gene-disease relationship.
Keywords: Adolescent; Adult; Animals; Anxiety Disorders; Autism Spectrum Disorder; Child; Child, Preschool; Codon, Nonsense; Exome Sequencing; Female; Humans; Male; Membrane Proteins; Memory Disorders; Mice; Mice, Knockout; Motor Activity; Phenotype; Serine Endopeptidases

Copy number variants and fixed duplications among 198 rhesus macaques (Macaca mulatta). - Brasó-Vives, Marina; Povolotskaya, Inna S; Hartasánchez, Diego A; Farré, Xavier; Fernandez-Callejo, Marcos; Raveendran, Muthuswamy; R. Alan Harris; Rosene, Douglas L; Lorente-Galdos, Belen; Navarro, Arcadi; Marques-Bonet, Tomas; Jeffrey Rogers; et al. (PLoS Genet, 2020)
The rhesus macaque is an abundant species of Old World monkeys and a valuable model organism for biomedical research due to its close phylogenetic relationship to humans. Copy number variation is one of the main sources of genomic diversity within and between species and a widely recognized cause of inter-individual differences in disease risk. However, copy number differences among rhesus macaques and between the human and macaque genomes, as well as the relevance of this diversity to research involving this nonhuman primate, remain understudied. Here we present a high-resolution map of sequence copy number for the rhesus macaque genome constructed from a dataset of 198 individuals. Our results show that about one-eighth of the rhesus macaque reference genome is composed of recently duplicated regions, either copy number variable regions or fixed duplications. Comparison with human genomic copy number maps based on previously published data shows that, despite overall similarities in the genome-wide distribution of these regions, there are specific differences at the chromosome level. Some of these create differences in the copy number profile between human disease genes and their rhesus macaque orthologs. Our results highlight the importance of addressing the number of copies of target genes in the design of experiments and cautions against human-centered assumptions in research conducted with model organisms. Overall, we present a genome-wide copy number map from a large sample of rhesus macaque individuals representing an important novel contribution concerning the evolution of copy number in primate genomes.
Keywords: Animals; Chromosome Mapping; DNA Copy Number Variations; Female; Gene Duplication; Genetics, Population; Genome; High-Throughput Nucleotide Sequencing; Humans; Macaca mulatta; Male; Open Reading Frames; Phylogeny; Sequence Analysis, DNA; Species Specificity

Critical Role of Cytosolic DNA and Its Sensing Adaptor STING in Aortic Degeneration, Dissection, and Rupture. - Luo, Wei; Wang, Yidan; Zhang, Lin; Ren, Pingping; Zhang, Chen; Li, Yanming; Azares, Alon R; Zhang, Michelle; Guo, Jiao; Ghaghada, Ketan B; Starosolski, Zbigniew A; Rajapakshe, Kimal; et al. (Circulation, 2020)
BACKGROUND: Sporadic aortic aneurysm and dissection (AAD), caused by progressive aortic smooth muscle cell (SMC) loss and extracellular matrix degradation, is a highly lethal condition. Identifying mechanisms that drive aortic degeneration is a crucial step in developing an effective pharmacologic treatment to prevent disease progression. Recent evidence has indicated that cytosolic DNA and abnormal activation of the cytosolic DNA sensing adaptor STING (stimulator of interferon genes) play a critical role in vascular inflammation and destruction. Here, we examined the involvement of this mechanism in aortic degeneration and sporadic AAD formation. METHODS: The presence of cytosolic DNA in aortic cells and activation of the STING pathway were examined in aortic tissues from patients with sporadic ascending thoracic AAD. The role of STING in AAD development was evaluated in -deficient () mice in a sporadic AAD model induced by challenging mice with a combination of a high-fat diet and angiotensin II. We also examined the direct effects of STING on SMC death and macrophage activation in vitro. RESULTS: In human sporadic AAD tissues, we observed the presence of cytosolic DNA in SMCs and macrophages and significant activation of the STING pathway. In the sporadic AAD model, mice showed significant reductions in challenge-induced aortic enlargement, dissection, and rupture in both the thoracic and abdominal aortic regions. Single-cell transcriptome analysis revealed that aortic challenge in wild-type mice induced the DNA damage response, the inflammatory response, dedifferentiation and cell death in SMCs, and matrix metalloproteinase expression in macrophages. These changes were attenuated in challenged mice. Mechanistically, nuclear and mitochondrial DNA damage in SMCs and the subsequent leak of DNA to the cytosol activated STING signaling, which induced cell death through apoptosis and necroptosis. In addition, DNA from damaged SMCs was engulfed by macrophages in which it activated STING and its target interferon regulatory factor 3, which directly induced matrix metalloproteinase-9 expression. We also found that pharmacologically inhibiting STING activation partially prevented AAD development. CONCLUSIONS: Our findings indicate that the presence of cytosolic DNA and subsequent activation of cytosolic DNA sensing adaptor STING signaling represent a key mechanism in aortic degeneration and that targeting STING may prevent sporadic AAD development.
Keywords: Animals; Aortic Dissection; Aortic Rupture; Cytosol; DNA; Female; Male; Membrane Proteins; Mice; Mice, Knockout; Signal Transduction

Discovery and population genomics of structural variation in a songbird genus. - Weissensteiner, Matthias H; Bunikis, Ignas; Catalán, Ana; Francoijs, Kees-Jan; Knief, Ulrich; Heim, Wieland; Peona, Valentina; Pophaly, Saurabh D; Fritz J Sedlazeck; Suh, Alexander; Warmuth, Vera M; Wolf, Jochen B W (Nat Commun, 2020)
Structural variation (SV) constitutes an important type of genetic mutations providing the raw material for evolution. Here, we uncover the genome-wide spectrum of intra- and interspecific SV segregating in natural populations of seven songbird species in the genus Corvus. Combining short-read (N = 127) and long-read re-sequencing (N = 31), as well as optical mapping (N = 16), we apply both assembly- and read mapping approaches to detect SV and characterize a total of 220,452 insertions, deletions and inversions. We exploit sampling across wide phylogenetic timescales to validate SV genotypes and assess the contribution of SV to evolutionary processes in an avian model of incipient speciation. We reveal an evolutionary young (~530,000 years) cis-acting 2.25-kb LTR retrotransposon insertion reducing expression of the NDP gene with consequences for premating isolation. Our results attest to the wealth and evolutionary significance of SV segregating in natural populations and highlight the need for reliable SV genotyping.
Keywords: Animals; Chromosome Inversion; Gene Deletion; Genetic Variation; Genetics, Population; Genome; Genomic Structural Variation; Genotype; Phylogeny; Polymorphism, Single Nucleotide; Retroelements; Sequence Analysis, DNA; Songbirds

Extensive Recombination Suppression and Epistatic Selection Causes Chromosome-Wide Differentiation of a Selfish Sex Chromosome in . - Fuller, Zachary L; Koury, Spencer A; Leonard, Christopher J; Young, Randee E; Ikegami, Kobe; Westlake, Jonathan; Stephen Richards; Schaeffer, Stephen W; Phadnis, Nitin (Genetics, 2020)
() chromosomes are selfish -chromosomes that distort Mendelian segregation and are commonly associated with inversions. These chromosomal rearrangements suppress recombination with Standard () -chromosomes and are hypothesized to maintain multiple alleles important for distortion in a single large haplotype. Here, we conduct a multifaceted study of the multiply inverted chromosome to understand the evolutionary history, genetic architecture, and present-day dynamics that shape this enigmatic selfish chromosome. The chromosome has three nonoverlapping inversions of the right arm of the metacentric -chromosome: basal, medial, and terminal. We find that 23 of 29 Mb of the -chromosome right arm is highly differentiated between the Standard and arrangements, including a 6.6 Mb collinear region between the medial and terminal inversions. Although crossing-over is heavily suppressed on this chromosome arm, we discover it is not completely eliminated, with measured rates indicating recombination suppression alone cannot explain patterns of differentiation or the near-perfect association of the three chromosome inversions in nature. We then demonstrate the ancient basal and medial inversions of the chromosome contain genes sufficient to cause weak distortion. In contrast, the younger terminal inversion cannot distort by itself, but contains at least one modifier gene necessary for full manifestation of strong sex chromosome distortion. By parameterizing population genetic models for chromosome-wide linkage disequilibrium with our experimental results, we infer that strong selection acts to maintain the near-perfect association of chromosome inversions in present-day populations. Based on comparative genomic analyses, direct recombination experiments, segregation distortion assays, and population genetic modeling, we conclude the combined action of suppressed recombination and strong, ongoing, epistatic selection shape the arrangement into a highly differentiated chromosome.
Keywords: Animals; Chromosome Inversion; Drosophila; Epistasis, Genetic; Evolution, Molecular; Genes, Modifier; Linkage Disequilibrium; Recombination, Genetic; Selection, Genetic; Suppression, Genetic; X Chromosome

Functional biology of the Steel syndrome founder allele and evidence for clan genomics derivation of COL27A1 pathogenic alleles worldwide. - Gonzaga-Jauregui, Claudia; Yesil, Gozde; Nistala, Harikiran; Gezdirici, Alper; Bayram, Yavuz; Nannuru, Kalyan C; Pehlivan, Davut; Bo Yuan; Jimenez, Johanna; Sahin, Yavuz; Paine, Ingrid S; Akdemir, Zeynep Coban; et al. (Eur J Hum Genet, 2020)
Previously we reported the identification of a homozygous COL27A1 (c.2089G>C; p.Gly697Arg) missense variant and proposed it as a founder allele in Puerto Rico segregating with Steel syndrome (STLS, MIM #615155); a rare osteochondrodysplasia characterized by short stature, congenital bilateral hip dysplasia, carpal coalitions, and scoliosis. We now report segregation of this variant in five probands from the initial clinical report defining the syndrome and an additional family of Puerto Rican descent with multiple affected adult individuals. We modeled the orthologous variant in murine Col27a1 and found it recapitulates some of the major Steel syndrome associated skeletal features including reduced body length, scoliosis, and a more rounded skull shape. Characterization of the in vivo murine model shows abnormal collagen deposition in the extracellular matrix and disorganization of the proliferative zone of the growth plate. We report additional COL27A1 pathogenic variant alleles identified in unrelated consanguineous Turkish kindreds suggesting Clan Genomics and identity-by-descent homozygosity contributing to disease in this population. The hypothesis that carrier states for this autosomal recessive osteochondrodysplasia may contribute to common complex traits is further explored in a large clinical population cohort. Our findings augment our understanding of COL27A1 biology and its role in skeletal development; and expand the functional allelic architecture in this gene underlying both rare and common disease phenotypes.
Keywords: Abnormalities, Multiple; Adolescent; Animals; Bone Development; Child; Child, Preschool; Consanguinity; Extracellular Matrix; Female; Fibrillar Collagens; Founder Effect; Gene Frequency; Hip Dislocation; Homozygote; Humans; Male; Mice; Mice, Inbred C57BL; Mutation; Pedigree; Scoliosis; Syndrome

Gene content evolution in the arthropods. - Thomas, Gregg W C; Dohmen, Elias; Hughes, Daniel S T; Murali, Shwetha C; Poelchau, Monica; Glastad, Karl; Anstead, Clare A; Ayoub, Nadia A; Batterham, Phillip; Bellair, Michelle; Binford, Greta J; Chao, Hsu; et al. (Genome Biol, 2020)
BACKGROUND: Arthropods comprise the largest and most diverse phylum on Earth and play vital roles in nearly every ecosystem. Their diversity stems in part from variations on a conserved body plan, resulting from and recorded in adaptive changes in the genome. Dissection of the genomic record of sequence change enables broad questions regarding genome evolution to be addressed, even across hyper-diverse taxa within arthropods. RESULTS: Using 76 whole genome sequences representing 21 orders spanning more than 500 million years of arthropod evolution, we document changes in gene and protein domain content and provide temporal and phylogenetic context for interpreting these innovations. We identify many novel gene families that arose early in the evolution of arthropods and during the diversification of insects into modern orders. We reveal unexpected variation in patterns of DNA methylation across arthropods and examples of gene family and protein domain evolution coincident with the appearance of notable phenotypic and physiological adaptations such as flight, metamorphosis, sociality, and chemoperception. CONCLUSIONS: These analyses demonstrate how large-scale comparative genomics can provide broad new insights into the genotype to phenotype map and generate testable hypotheses about the evolution of animal diversity.
Keywords: Animals; Arthropods; DNA Methylation; Evolution, Molecular; Genetic Speciation; Genetic Variation; Phylogeny

Genome-enabled insights into the biology of thrips as crop pests. - Rotenberg, Dorith; Baumann, Aaron A; Ben-Mahmoud, Sulley; Christiaens, Olivier; Dermauw, Wannes; Ioannidis, Panagiotis; Jacobs, Chris G C; Vargas Jentzsch, Iris M; Oliver, Jonathan E; Poelchau, Monica F; Rajarapu, Swapna Priya; Schneweis, Derek J; et al. (BMC Biol, 2020)
BACKGROUND: The western flower thrips, Frankliniella occidentalis (Pergande), is a globally invasive pest and plant virus vector on a wide array of food, fiber, and ornamental crops. The underlying genetic mechanisms of the processes governing thrips pest and vector biology, feeding behaviors, ecology, and insecticide resistance are largely unknown. To address this gap, we present the F. occidentalis draft genome assembly and official gene set. RESULTS: We report on the first genome sequence for any member of the insect order Thysanoptera. Benchmarking Universal Single-Copy Ortholog (BUSCO) assessments of the genome assembly (size = 415.8 Mb, scaffold N50 = 948.9 kb) revealed a relatively complete and well-annotated assembly in comparison to other insect genomes. The genome is unusually GC-rich (50%) compared to other insect genomes to date. The official gene set (OGS v1.0) contains 16,859 genes, of which ~ 10% were manually verified and corrected by our consortium. We focused on manual annotation, phylogenetic, and expression evidence analyses for gene sets centered on primary themes in the life histories and activities of plant-colonizing insects. Highlights include the following: (1) divergent clades and large expansions in genes associated with environmental sensing (chemosensory receptors) and detoxification (CYP4, CYP6, and CCE enzymes) of substances encountered in agricultural environments; (2) a comprehensive set of salivary gland genes supported by enriched expression; (3) apparent absence of members of the IMD innate immune defense pathway; and (4) developmental- and sex-specific expression analyses of genes associated with progression from larvae to adulthood through neometaboly, a distinct form of maturation differing from either incomplete or complete metamorphosis in the Insecta. CONCLUSIONS: Analysis of the F. occidentalis genome offers insights into the polyphagous behavior of this insect pest that finds, colonizes, and survives on a widely diverse array of plants. The genomic resources presented here enable a more complete analysis of insect evolution and biology, providing a missing taxon for contemporary insect genomics-based analyses. Our study also offers a genomic benchmark for molecular and evolutionary investigations of other Thysanoptera species.
Keywords: Animals; Crops, Agricultural; Feeding Behavior; Food Chain; Genome, Insect; Immunity, Innate; Life History Traits; Perception; Phylogeny; Reproduction; Thysanoptera; Transcriptome

In vivo modeling of metastatic human high-grade serous ovarian cancer in mice. - Kim, Olga; Park, Eun Young; Klinkebiel, David L; Pack, Svetlana D; Shin, Yong-Hyun; Abdullaev, Zied; Emerson, Robert E; Coffey, Donna M; Kwon, Sun Young; Creighton, Chad J; Kwon, Sanghoon; Chang, Edmund C; et al. (PLoS Genet, 2020)
Metastasis is responsible for 90% of human cancer mortality, yet it remains a challenge to model human cancer metastasis in vivo. Here we describe mouse models of high-grade serous ovarian cancer, also known as high-grade serous carcinoma (HGSC), the most common and deadliest human ovarian cancer type. Mice genetically engineered to harbor Dicer1 and Pten inactivation and mutant p53 robustly replicate the peritoneal metastases of human HGSC with complete penetrance. Arising from the fallopian tube, tumors spread to the ovary and metastasize throughout the pelvic and peritoneal cavities, invariably inducing hemorrhagic ascites. Widespread and abundant peritoneal metastases ultimately cause mouse deaths (100%). Besides the phenotypic and histopathological similarities, mouse HGSCs also display marked chromosomal instability, impaired DNA repair, and chemosensitivity. Faithfully recapitulating the clinical metastases as well as molecular and genomic features of human HGSC, this murine model will be valuable for elucidating the mechanisms underlying the development and progression of metastatic ovarian cancer and also for evaluating potential therapies.
Keywords: Animals; Antineoplastic Agents; Cell Line, Tumor; Chromosomal Instability; Cystadenocarcinoma, Serous; DEAD-box RNA Helicases; Disease Models, Animal; DNA Repair; Drug Resistance, Neoplasm; Drug Screening Assays, Antitumor; Feasibility Studies; Female; Humans; Mice; Mice, Knockout; Mutation; Neoplasm Grading; Neoplasm Metastasis; Ovarian Neoplasms; Peritoneal Neoplasms; Primary Cell Culture; PTEN Phosphohydrolase; Ribonuclease III; Tumor Suppressor Protein p53

An Introduction to the Callithrix Genus and Overview of Recent Advances in Marmoset Research. - Malukiewicz, Joanna; Boere, Vanner; de Oliveira, Maria Adélia Borstelmann; D'arc, Mirela; Ferreira, Jéssica V A; French, Jeffrey; Housman, Genevieve; de Souza, Claudia Igayara; Jerusalinsky, Leandro; R de Melo, Fabiano; M Valença-Montenegro, Mônica; Moreira, Silvia Bahadian; et al. (ILAR J, 2020)
We provide here a current overview of marmoset (Callithrix) evolution, hybridization, species biology, basic/biomedical research, and conservation initiatives. Composed of 2 subgroups, the aurita group (C aurita and C flaviceps) and the jacchus group (C geoffroyi, C jacchus, C kuhlii, and C penicillata), this relatively young primate radiation is endemic to the Brazilian Cerrado, Caatinga, and Atlantic Forest biomes. Significant impacts on Callithrix within these biomes resulting from anthropogenic activity include (1) population declines, particularly for the aurita group; (2) widespread geographic displacement, biological invasions, and range expansions of C jacchus and C penicillata; (3) anthropogenic hybridization; and (4) epizootic Yellow Fever and Zika viral outbreaks. A number of Brazilian legal and conservation initiatives are now in place to protect the threatened aurita group and increase research about them. Due to their small size and rapid life history, marmosets are prized biomedical models. As a result, there are increasingly sophisticated genomic Callithrix resources available and burgeoning marmoset functional, immuno-, and epigenomic research. In both the laboratory and the wild, marmosets have given us insight into cognition, social group dynamics, human disease, and pregnancy. Callithrix jacchus and C penicillata are emerging neotropical primate models for arbovirus disease, including Dengue and Zika. Wild marmoset populations are helping us understand sylvatic transmission and human spillover of Zika and Yellow Fever viruses. All of these factors are positioning marmosets as preeminent models to facilitate understanding of facets of evolution, hybridization, conservation, human disease, and emerging infectious diseases.
Keywords: Animals; Brazil; Callithrix; Genomics; Hybridization, Genetic; Yellow Fever; Zika Virus; Zika Virus Infection

Knockout of mouse receptor accessory protein 6 leads to sperm function and morphology defects†. - Devlin, Darius J; Agrawal Zaneveld, Smriti; Nozawa, Kaori; Han, Xiao; Moye, Abigail R; Liang, Qingnan; Harnish, Jacob Michael; Matzuk, Martin M; Rui Chen (Biol Reprod, 2020)
Receptor accessory protein 6 (REEP6) is a member of the REEP/Ypt-interacting protein family that we recently identified as essential for normal endoplasmic reticulum homeostasis and protein trafficking in the retina of mice and humans. Interestingly, in addition to the loss of REEP6 in our knockout (KO) mouse model recapitulating the retinal degeneration of humans with REEP6 mutations causing retinitis pigmentosa (RP), we also found that male mice are sterile. Herein, we characterize the infertility caused by loss of Reep6. Expression of both Reep6 mRNA transcripts is present in the testis; however, isoform 1 becomes overexpressed during spermiogenesis. In vitro fertilization assays reveal that Reep6 KO spermatozoa are able to bind the zona pellucida but are only able to fertilize oocytes lacking the zona pellucida. Although spermatogenesis appears normal in KO mice, cauda epididymal spermatozoa have severe motility defects and variable morphological abnormalities, including bent or absent tails. Immunofluorescent staining reveals that REEP6 expression first appears in stage IV tubules within step 15 spermatids, and REEP6 localizes to the connecting piece, midpiece, and annulus of mature spermatozoa. These data reveal an important role for REEP6 in sperm motility and morphology and is the first reported function for a REEP protein in reproductive processes. Additionally, this work identifies a new gene potentially responsible for human infertility and has implications for patients with RP harboring mutations in REEP6.
Keywords: Animals; Eye Proteins; Gene Expression Regulation; Infertility, Male; Male; Membrane Proteins; Mice; Mice, Knockout; Mutation; RNA, Messenger; Spermatozoa

Mapping the -regulatory architecture of the human retina reveals noncoding genetic variation in disease. - Cherry, Timothy J; Yang, Marty G; Harmin, David A; Tao, Peter; Timms, Andrew E; Bauwens, Miriam; Allikmets, Rando; Jones, Evan M; Rui Chen; De Baere, Elfride; Greenberg, Michael E (Proc Natl Acad Sci U S A, 2020)
The interplay of transcription factors and -regulatory elements (CREs) orchestrates the dynamic and diverse genetic programs that assemble the human central nervous system (CNS) during development and maintain its function throughout life. Genetic variation within CREs plays a central role in phenotypic variation in complex traits including the risk of developing disease. We took advantage of the retina, a well-characterized region of the CNS known to be affected by pathogenic variants in CREs, to establish a roadmap for characterizing regulatory variation in the human CNS. This comprehensive analysis of tissue-specific regulatory elements, transcription factor binding, and gene expression programs in three regions of the human visual system (retina, macula, and retinal pigment epithelium/choroid) reveals features of regulatory element evolution that shape tissue-specific gene expression programs and defines regulatory elements with the potential to contribute to Mendelian and complex disorders of human vision.
Keywords: Adult; Animals; DNA Mutational Analysis; Epigenomics; Evolution, Molecular; Female; Gene Expression Regulation, Developmental; Genetic Variation; Humans; Male; Mice; Middle Aged; Mutation; Regulatory Sequences, Nucleic Acid; Retina; Retinal Diseases; RNA-Seq; Species Specificity

Mutations in ASH1L confer susceptibility to Tourette syndrome. - Liu, Shiguo; Tian, Miaomiao; He, Fan; Li, Jiani; Xie, Hong; Liu, Wenmiao; Zhang, Yeting; Zhang, Ru; Yi, Mingji; Che, Fengyuan; Ma, Xu; Zheng, Yi; et al. (Mol Psychiatry, 2020)
Tourette syndrome (TS) is a childhood-onset neuropsychiatric disorder characterized by repetitive motor movements and vocal tics. The clinical manifestations of TS are complex and often overlap with other neuropsychiatric disorders. TS is highly heritable; however, the underlying genetic basis and molecular and neuronal mechanisms of TS remain largely unknown. We performed whole-exome sequencing of a hundred trios (probands and their parents) with detailed records of their clinical presentations and identified a risk gene, ASH1L, that was both de novo mutated and associated with TS based on a transmission disequilibrium test. As a replication, we performed follow-up targeted sequencing of ASH1L in additional 524 unrelated TS samples and replicated the association (P value = 0.001). The point mutations in ASH1L cause defects in its enzymatic activity. Therefore, we established a transgenic mouse line and performed an array of anatomical, behavioral, and functional assays to investigate ASH1L function. The Ash1l mice manifested tic-like behaviors and compulsive behaviors that could be rescued by the tic-relieving drug haloperidol. We also found that Ash1l disruption leads to hyper-activation and elevated dopamine-releasing events in the dorsal striatum, all of which could explain the neural mechanisms for the behavioral abnormalities in mice. Taken together, our results provide compelling evidence that ASH1L is a TS risk gene.
Keywords: Adolescent; Adult; Animals; Child; Child, Preschool; China; DNA-Binding Proteins; Exome Sequencing; Family; Female; Genetic Predisposition to Disease; Histone-Lysine N-Methyltransferase; Humans; Male; Mice; Mice, Transgenic; Middle Aged; Mutation; Parents; Tic Disorders; Tourette Syndrome; Transcription Factors

NEMF mutations that impair ribosome-associated quality control are associated with neuromuscular disease. - Martin, Paige B; Kigoshi-Tansho, Yu; Sher, Roger B; Ravenscroft, Gianina; Stauffer, Jennifer E; Kumar, Rajesh; Yonashiro, Ryo; Müller, Tina; Griffith, Christopher; Allen, William; Pehlivan, Davut; Harel, Tamar; et al. (Nat Commun, 2020)
A hallmark of neurodegeneration is defective protein quality control. The E3 ligase Listerin (LTN1/Ltn1) acts in a specialized protein quality control pathway-Ribosome-associated Quality Control (RQC)-by mediating proteolytic targeting of incomplete polypeptides produced by ribosome stalling, and Ltn1 mutation leads to neurodegeneration in mice. Whether neurodegeneration results from defective RQC and whether defective RQC contributes to human disease have remained unknown. Here we show that three independently-generated mouse models with mutations in a different component of the RQC complex, NEMF/Rqc2, develop progressive motor neuron degeneration. Equivalent mutations in yeast Rqc2 selectively interfere with its ability to modify aberrant translation products with C-terminal tails which assist with RQC-mediated protein degradation, suggesting a pathomechanism. Finally, we identify NEMF mutations expected to interfere with function in patients from seven families presenting juvenile neuromuscular disease. These uncover NEMF's role in translational homeostasis in the nervous system and implicate RQC dysfunction in causing neurodegeneration.
Keywords: Amino Acid Sequence; Animals; Female; Humans; Male; Mice; Mice, Knockout; Mutation; Neuromuscular Diseases; Proteolysis; Ribosomes; RNA-Binding Proteins; Saccharomyces cerevisiae; Saccharomyces cerevisiae Proteins; Sequence Alignment

Paternal age in rhesus macaques is positively associated with germline mutation accumulation but not with measures of offspring sociability. - Wang, Richard J; Thomas, Gregg W C; Raveendran, Muthuswamy; R. Alan Harris; Harshavardhan Doddapaneni; Donna M Muzny; Capitanio, John P; Radivojac, Predrag; Jeffrey Rogers; Hahn, Matthew W (Genome Res, 2020)
Mutation is the ultimate source of all genetic novelty and the cause of heritable genetic disorders. Mutational burden has been linked to complex disease, including neurodevelopmental disorders such as schizophrenia and autism. The rate of mutation is a fundamental genomic parameter and direct estimates of this parameter have been enabled by accurate comparisons of whole-genome sequences between parents and offspring. Studies in humans have revealed that the paternal age at conception explains most of the variation in mutation rate: Each additional year of paternal age in humans leads to approximately 1.5 additional inherited mutations. Here, we present an estimate of the de novo mutation rate in the rhesus macaque () using whole-genome sequence data from 32 individuals in four large pedigrees. We estimated an average mutation rate of 0.58 × 10 per base pair per generation (at an average parental age of 7.5 yr), much lower than found in direct estimates from great apes. As in humans, older macaque fathers transmit more mutations to their offspring, increasing the per generation mutation rate by 4.27 × 10 per base pair per year. We found that the rate of mutation accumulation after puberty is similar between macaques and humans, but that a smaller number of mutations accumulate before puberty in macaques. We additionally investigated the role of paternal age on offspring sociability, a proxy for normal neurodevelopment, by studying 203 male macaques in large social groups.
Keywords: Age Factors; Animals; Behavior, Animal; Female; Germ-Line Mutation; Humans; Macaca mulatta; Male; Mutation Accumulation; Mutation Rate; Paternal Age; Pregnancy; Prenatal Exposure Delayed Effects; Social Skills; Species Specificity

PCM1 is necessary for focal ciliary integrity and is a candidate for severe schizophrenia. - Monroe, Tanner O; Garrett, Melanie E; Kousi, Maria; Rodriguiz, Ramona M; Moon, Sungjin; Bai, Yushi; Brodar, Steven C; Soldano, Karen L; Savage, Jeremiah; Hansen, Thomas F; Donna M Muzny; Richard A Gibbs; et al. (Nat Commun, 2020)
The neuronal primary cilium and centriolar satellites have functions in neurogenesis, but little is known about their roles in the postnatal brain. We show that ablation of pericentriolar material 1 in the mouse leads to progressive ciliary, anatomical, psychomotor, and cognitive abnormalities. RNAseq reveals changes in amine- and G-protein coupled receptor pathways. The physiological relevance of this phenotype is supported by decreased available dopamine D2 receptor (D2R) levels and the failure of antipsychotic drugs to rescue adult behavioral defects. Immunoprecipitations show an association with Pcm1 and D2Rs. Finally, we sequence PCM1 in two human cohorts with severe schizophrenia. Systematic modeling of all discovered rare alleles by zebrafish in vivo complementation reveals an enrichment for pathogenic alleles. Our data emphasize a role for the pericentriolar material in the postnatal brain, with progressive degenerative ciliary and behavioral phenotypes; and they support a contributory role for PCM1 in some individuals diagnosed with schizophrenia.
Keywords: Adult; Aged; Alleles; Amines; Animals; Antipsychotic Agents; Brain; Cell Cycle Proteins; Cilia; Drug Resistance; Genetic Predisposition to Disease; Humans; Mice; Mice, Knockout; Middle Aged; Mutation; Phenotype; Receptors, Dopamine D2; Receptors, G-Protein-Coupled; Schizophrenia; Signal Transduction; Young Adult; Zebrafish

Primate phylogenomics uncovers multiple rapid radiations and ancient interspecific introgression. - Vanderpool, Dan; Minh, Bui Quang; Lanfear, Robert; Hughes, Daniel; Murali, Shwetha; R. Alan Harris; Raveendran, Muthuswamy; Donna M Muzny; Hibbins, Mark S; Williamson, Robert J; Richard A Gibbs; Kim C Worley; et al. (PLoS Biol, 2020)
Our understanding of the evolutionary history of primates is undergoing continual revision due to ongoing genome sequencing efforts. Bolstered by growing fossil evidence, these data have led to increased acceptance of once controversial hypotheses regarding phylogenetic relationships, hybridization and introgression, and the biogeographical history of primate groups. Among these findings is a pattern of recent introgression between species within all major primate groups examined to date, though little is known about introgression deeper in time. To address this and other phylogenetic questions, here, we present new reference genome assemblies for 3 Old World monkey (OWM) species: Colobus angolensis ssp. palliatus (the black and white colobus), Macaca nemestrina (southern pig-tailed macaque), and Mandrillus leucophaeus (the drill). We combine these data with 23 additional primate genomes to estimate both the species tree and individual gene trees using thousands of loci. While our species tree is largely consistent with previous phylogenetic hypotheses, the gene trees reveal high levels of genealogical discordance associated with multiple primate radiations. We use strongly asymmetric patterns of gene tree discordance around specific branches to identify multiple instances of introgression between ancestral primate lineages. In addition, we exploit recent fossil evidence to perform fossil-calibrated molecular dating analyses across the tree. Taken together, our genome-wide data help to resolve multiple contentious sets of relationships among primates, while also providing insight into the biological processes and technical artifacts that led to the disagreements in the first place.
Keywords: Animals; Biological Evolution; Cercopithecidae; Computational Biology; Databases, Genetic; Fossils; Gene Flow; Genetic Introgression; Genome; Models, Genetic; Phylogeny; Primates; Sequence Analysis, DNA

Reduced meiotic recombination in rhesus macaques and the origin of the human recombination landscape. - Xue, Cheng; Rustagi, Navin; Liu, Xiaoming; Raveendran, Muthuswamy; R. Alan Harris; Venkata, Manjunath Gorentla; Jeffrey Rogers; Fuli Yu (PLoS One, 2020)
Characterizing meiotic recombination rates across the genomes of nonhuman primates is important for understanding the genetics of primate populations, performing genetic analyses of phenotypic variation and reconstructing the evolution of human recombination. Rhesus macaques (Macaca mulatta) are the most widely used nonhuman primates in biomedical research. We constructed a high-resolution genetic map of the rhesus genome based on whole genome sequence data from Indian-origin rhesus macaques. The genetic markers used were approximately 18 million SNPs, with marker density 6.93 per kb across the autosomes. We report that the genome-wide recombination rate in rhesus macaques is significantly lower than rates observed in apes or humans, while the distribution of recombination across the macaque genome is more uniform. These observations provide new comparative information regarding the evolution of recombination in primates.
Keywords: Animals; Chromosome Mapping; Evolution, Molecular; Genetic Markers; Genetic Variation; Genome; Humans; Macaca mulatta; Meiosis; Polymorphism, Single Nucleotide; Recombination, Genetic; Species Specificity; Whole Genome Sequencing

Sawfly Genomes Reveal Evolutionary Acquisitions That Fostered the Mega-Radiation of Parasitoid and Eusocial Hymenoptera. - Oeyen, Jan Philip; Baa-Puyoulet, Patrice; Benoit, Joshua B; Beukeboom, Leo W; Bornberg-Bauer, Erich; Buttstedt, Anja; Calevro, Federica; Cash, Elizabeth I; Chao, Hsu; Charles, Hubert; Chen, Mei-Ju May; Childers, Christopher; et al. (Genome Biol Evol, 2020)
The tremendous diversity of Hymenoptera is commonly attributed to the evolution of parasitoidism in the last common ancestor of parasitoid sawflies (Orussidae) and wasp-waisted Hymenoptera (Apocrita). However, Apocrita and Orussidae differ dramatically in their species richness, indicating that the diversification of Apocrita was promoted by additional traits. These traits have remained elusive due to a paucity of sawfly genome sequences, in particular those of parasitoid sawflies. Here, we present comparative analyses of draft genomes of the primarily phytophagous sawfly Athalia rosae and the parasitoid sawfly Orussus abietinus. Our analyses revealed that the ancestral hymenopteran genome exhibited traits that were previously considered unique to eusocial Apocrita (e.g., low transposable element content and activity) and a wider gene repertoire than previously thought (e.g., genes for CO2 detection). Moreover, we discovered that Apocrita evolved a significantly larger array of odorant receptors than sawflies, which could be relevant to the remarkable diversification of Apocrita by enabling efficient detection and reliable identification of hosts.
Keywords: Amino Acid Sequence; Animals; Conserved Sequence; DNA Transposable Elements; Female; Gene Dosage; Genetic Speciation; Genome, Insect; Glycoproteins; Herbivory; Host-Parasite Interactions; Hymenoptera; Immunity; Insect Proteins; Male; Multigene Family; Receptors, Odorant; Social Behavior; Vision, Ocular

Sequence analysis in reveals pervasiveness of X-Y arms races in mammalian lineages. - Hughes, Jennifer F; Skaletsky, Helen; Pyntikova, Tatyana; Koutseva, Natalia; Raudsepp, Terje; Brown, Laura G; Bellott, Daniel W; Cho, Ting-Jan; Dugan-Rocha, Shannon; Ziad Khan; Kremitzki, Colin; Fronick, Catrina; et al. (Genome Res, 2020)
Studies of Y Chromosome evolution have focused primarily on gene decay, a consequence of suppression of crossing-over with the X Chromosome. Here, we provide evidence that suppression of X-Y crossing-over unleashed a second dynamic: selfish X-Y arms races that reshaped the sex chromosomes in mammals as different as cattle, mice, and men. Using super-resolution sequencing, we explore the Y Chromosome of (bull) and find it to be dominated by massive, lineage-specific amplification of testis-expressed gene families, making it the most gene-dense Y Chromosome sequenced to date. As in mice, an X-linked homolog of a bull Y-amplified gene has become testis-specific and amplified. This evolutionary convergence implies that lineage-specific X-Y coevolution through gene amplification, and the selfish forces underlying this phenomenon, were dominatingly powerful among diverse mammalian lineages. Together with Y gene decay, X-Y arms races molded mammalian sex chromosomes and influenced the course of mammalian evolution.
Keywords: Animals; Cattle; Cell Lineage; Crossing Over, Genetic; Evolution, Molecular; Female; Gene Amplification; Humans; Male; Mice; Organ Specificity; Sequence Analysis, DNA; Testis; X Chromosome; Y Chromosome

Sequence diversity analyses of an improved rhesus macaque genome enhance its biomedical utility. - Warren, Wesley C; R. Alan Harris; Haukness, Marina; Fiddes, Ian T; Murali, Shwetha C; Fernandes, Jason; Dishuck, Philip C; Storer, Jessica M; Raveendran, Muthuswamy; Hillier, LaDeana W; Porubsky, David; Mao, Yafei; et al. (Science, 2020)
The rhesus macaque () is the most widely studied nonhuman primate (NHP) in biomedical research. We present an updated reference genome assembly (Mmul_10, contig N50 = 46 Mbp) that increases the sequence contiguity 120-fold and annotate it using 6.5 million full-length transcripts, thus improving our understanding of gene content, isoform diversity, and repeat organization. With the improved assembly of segmental duplications, we discovered new lineage-specific genes and expanded gene families that are potentially informative in studies of evolution and disease susceptibility. Whole-genome sequencing (WGS) data from 853 rhesus macaques identified 85.7 million single-nucleotide variants (SNVs) and 10.5 million indel variants, including potentially damaging variants in genes associated with human autism and developmental delay, providing a framework for developing noninvasive NHP models of human disease.
Keywords: Animals; Genetic Predisposition to Disease; Genetic Variation; Genome; Humans; Macaca mulatta; Molecular Sequence Annotation; Polymorphism, Single Nucleotide; Whole Genome Sequencing

Targeted nanopore sequencing with Cas9-guided adapter ligation. - Gilpatrick, Timothy; Lee, Isac; Graham, James E; Raimondeau, Etienne; Bowen, Rebecca; Heron, Andrew; Downs, Bradley; Sukumar, Saraswati; Fritz J Sedlazeck; Timp, Winston (Nat Biotechnol, 2020)
Despite recent improvements in sequencing methods, there remains a need for assays that provide high sequencing depth and comprehensive variant detection. Current methods are limited by the loss of native modifications, short read length, high input requirements, low yield or long protocols. In the present study, we describe nanopore Cas9-targeted sequencing (nCATS), an enrichment strategy that uses targeted cleavage of chromosomal DNA with Cas9 to ligate adapters for nanopore sequencing. We show that nCATS can simultaneously assess haplotype-resolved single-nucleotide variants, structural variations and CpG methylation. We apply nCATS to four cell lines, to a cell-line-derived xenograft, and to normal and paired tumor/normal primary human breast tissue. Median sequencing coverage was 675× using a MinION flow cell and 34× using the smaller Flongle flow cell. The nCATS sequencing requires only ~3 μg of genomic DNA and can target a large number of loci in a single reaction. The method will facilitate the use of long-read sequencing in research and in the clinic.
Keywords: Animals; Cells, Cultured; Chromosomes, Human; CRISPR-Associated Protein 9; Genetic Loci; Genetic Variation; Genotype; High-Throughput Nucleotide Sequencing; Humans; Nanopore Sequencing; RNA, Guide, Kinetoplastida; Sequence Analysis, DNA

Unusual sequence characteristics of human chromosome 19 are conserved across 11 nonhuman primates. - R. Alan Harris; Raveendran, Muthuswamy; Kim C Worley; Jeffrey Rogers (BMC Evol Biol, 2020)
BACKGROUND: Human chromosome 19 has many unique characteristics including gene density more than double the genome-wide average and 20 large tandemly clustered gene families. It also has the highest GC content of any chromosome, especially outside gene clusters. The high GC content and concomitant high content of hypermutable CpG sites raises the possibility chromosome 19 exhibits higher levels of nucleotide diversity both within and between species, and may possess greater variation in DNA methylation that regulates gene expression. RESULTS: We examined GC and CpG content of chromosome 19 orthologs across representatives of the primate order. In all 12 primate species with suitable genome assemblies, chromosome 19 orthologs have the highest GC content of any chromosome. CpG dinucleotides and CpG islands are also more prevalent in chromosome 19 orthologs than other chromosomes. GC and CpG content are generally higher outside the gene clusters. Intra-species variation based on SNPs in human common dbSNP, rhesus, crab eating macaque, baboon and marmoset datasets is most prevalent on chromosome 19 and its orthologs. Inter-species comparisons based on phyloP conservation show accelerated nucleotide evolution for chromosome 19 promoter flanking and enhancer regions. These same regulatory regions show the highest CpG density of any chromosome suggesting they possess considerable methylome regulatory potential. CONCLUSIONS: The pattern of high GC and CpG content in chromosome 19 orthologs, particularly outside gene clusters, is present from human to mouse lemur representing 74 million years of primate evolution. Much CpG variation exists both within and between primate species with a portion of this variation occurring in regulatory regions.
Keywords: Animals; Base Composition; Base Sequence; Chromosomes; Chromosomes, Human, Pair 19; Conserved Sequence; CpG Islands; Dinucleoside Phosphates; DNA Methylation; Genome; Humans; Lemur; Mice; Multigene Family; Phylogeny; Primates; Promoter Regions, Genetic; Regulatory Sequences, Nucleic Acid

Activating p53 family member TAp63: A novel therapeutic strategy for targeting p53-altered tumors. - Gunaratne, Preethi H; Pan, Yinghong; Rao, Abhi K; Lin, Chunru; Hernandez-Herrera, Anadulce; Liang, Ke; Rait, Antonina S; Venkatanarayan, Avinashnarayan; Benham, Ashley L; Rubab, Farwah; Kim, Sang Soo; Rajapakshe, Kimal; et al. (Cancer, 2019)
BACKGROUND: Over 96% of high-grade ovarian carcinomas and 50% of all cancers are characterized by alterations in the p53 gene. Therapeutic strategies to restore and/or reactivate the p53 pathway have been challenging. By contrast, p63, which shares many of the downstream targets and functions of p53, is rarely mutated in cancer. METHODS: A novel strategy is presented for circumventing alterations in p53 by inducing the tumor-suppressor isoform TAp63 (transactivation domain of tumor protein p63) through its direct downstream target, microRNA-130b (miR-130b), which is epigenetically silenced and/or downregulated in chemoresistant ovarian cancer. RESULTS: Treatment with miR-130b resulted in: 1) decreased migration/invasion in HEYA8 cells (p53 wild-type) and disruption of multicellular spheroids in OVCAR8 cells (p53-mutant) in vitro, 2) sensitization of HEYA8 and OVCAR8 cells to cisplatin (CDDP) in vitro and in vivo, and 3) transcriptional activation of TAp63 and the B-cell lymphoma (Bcl)-inhibitor B-cell lymphoma 2-like protein 11 (BIM). Overexpression of TAp63 was sufficient to decrease cell viability, suggesting that it is a critical downstream effector of miR-130b. In vivo, combined miR-130b plus CDDP exhibited greater therapeutic efficacy than miR-130b or CDDP alone. Mice that carried OVCAR8 xenograft tumors and were injected with miR-130b in 1,2-dioleoyl-sn-glycero-3-phosphatidylcholine (DOPC) liposomes had a significant decrease in tumor burden at rates similar to those observed in CDDP-treated mice, and 20% of DOPC-miR-130b plus CDDP-treated mice were living tumor free. Systemic injections of scL-miR-130b plus CDDP in a clinically tested, tumor-targeted nanocomplex (scL) improved survival in 60% and complete remissions in 40% of mice that carried HEYA8 xenografts. CONCLUSIONS: The miR-130b/TAp63 axis is proposed as a new druggable pathway that has the potential to uncover broad-spectrum therapeutic options for the majority of p53-altered cancers.
Keywords: Animals; Antineoplastic Agents; Binding Sites; Cell Line, Tumor; Cell Movement; Cisplatin; Drug Resistance, Neoplasm; Female; Humans; Liposomes; Mice; Mice, Nude; MicroRNAs; Mutation, Missense; Neoplasm Invasiveness; Ovarian Neoplasms; Protein Isoforms; Signal Transduction; Transcription Factors; Transcriptional Activation; Transfection; Tumor Suppressor Protein p53; Tumor Suppressor Proteins; Xenograft Model Antitumor Assays

Arthropod Genome Sequencing and Assembly Strategies. - Stephen Richards (Methods Mol Biol, 2019)
As in any endeavor, the strategy applied to a genome project can mean the difference between success and failure. This is especially important when limited funding often means only a single approach may be tried at a given time. Although the advance of all areas of genomics and transcriptomics in recent years has led to an embarrassment of riches, methods in the field have not quite reached the turn-key production status for all species, despite being closer than ever. Here I contrast and compare the technical approaches to genome projects in the hope of enabling strategy choices with higher probabilities of success. Finally, I review the new technologies that are not yet widely distributed which are revolutionizing the future of genomics.
Keywords: Animals; Arthropods; Genome, Insect; Genomics; High-Throughput Nucleotide Sequencing; Sequence Analysis, DNA

Bi-allelic Variants in TONSL Cause SPONASTRIME Dysplasia and a Spectrum of Skeletal Dysplasia Phenotypes. - Burrage, Lindsay C; Reynolds, John J; Baratang, Nissan Vida; Phillips, Jennifer B; Wegner, Jeremy; McFarquhar, Ashley; Higgs, Martin R; Christiansen, Audrey E; Lanza, Denise G; Seavitt, John R; Jain, Mahim; Li, Xiaohui; et al. (Am J Hum Genet, 2019)
SPONASTRIME dysplasia is an autosomal-recessive spondyloepimetaphyseal dysplasia characterized by spine (spondylar) abnormalities, midface hypoplasia with a depressed nasal bridge, metaphyseal striations, and disproportionate short stature. Scoliosis, coxa vara, childhood cataracts, short dental roots, and hypogammaglobulinemia have also been reported in this disorder. Although an autosomal-recessive inheritance pattern has been hypothesized, pathogenic variants in a specific gene have not been discovered in individuals with SPONASTRIME dysplasia. Here, we identified bi-allelic variants in TONSL, which encodes the Tonsoku-like DNA repair protein, in nine subjects (from eight families) with SPONASTRIME dysplasia, and four subjects (from three families) with short stature of varied severity and spondylometaphyseal dysplasia with or without immunologic and hematologic abnormalities, but no definitive metaphyseal striations at diagnosis. The finding of early embryonic lethality in a Tonsl murine model and the discovery of reduced length, spinal abnormalities, reduced numbers of neutrophils, and early lethality in a tonsl zebrafish model both support the hypomorphic nature of the identified TONSL variants. Moreover, functional studies revealed increased amounts of spontaneous replication fork stalling and chromosomal aberrations, as well as fewer camptothecin (CPT)-induced RAD51 foci in subject-derived cell lines. Importantly, these cellular defects were rescued upon re-expression of wild-type (WT) TONSL; this rescue is consistent with the hypothesis that hypomorphic TONSL variants are pathogenic. Overall, our studies in humans, mice, zebrafish, and subject-derived cell lines confirm that pathogenic variants in TONSL impair DNA replication and homologous recombination-dependent repair processes, and they lead to a spectrum of skeletal dysplasia phenotypes with numerous extra-skeletal manifestations.
Keywords: Adolescent; Adult; Alleles; Animals; Cells, Cultured; Child; Child, Preschool; Chromosomal Instability; DNA Damage; Exome Sequencing; Female; Fibroblasts; Genetic Association Studies; Genetic Variation; Humans; Mice; Mice, Knockout; Musculoskeletal Abnormalities; NF-kappa B; Osteochondrodysplasias; Young Adult; Zebrafish

Biallelic VARS variants cause developmental encephalopathy with microcephaly that is recapitulated in vars knockout zebrafish. - Siekierska, Aleksandra; Stamberger, Hannah; Deconinck, Tine; Oprescu, Stephanie N; Partoens, Michèle; Zhang, Yifan; Sourbron, Jo; Adriaenssens, Elias; Mullen, Patrick; Wiencek, Patrick; Hardies, Katia; Lee, Jeong-Soo; et al. (Nat Commun, 2019)
Aminoacyl tRNA synthetases (ARSs) link specific amino acids with their cognate transfer RNAs in a critical early step of protein translation. Mutations in ARSs have emerged as a cause of recessive, often complex neurological disease traits. Here we report an allelic series consisting of seven novel and two previously reported biallelic variants in valyl-tRNA synthetase (VARS) in ten patients with a developmental encephalopathy with microcephaly, often associated with early-onset epilepsy. In silico, in vitro, and yeast complementation assays demonstrate that the underlying pathomechanism of these mutations is most likely a loss of protein function. Zebrafish modeling accurately recapitulated some of the key neurological disease traits. These results provide both genetic and biological insights into neurodevelopmental disease and pave the way for further in-depth research on ARS related recessive disorders and precision therapies.
Keywords: Alleles; Animals; Brain Diseases; Cell Line; Disease Models, Animal; Epilepsy; Female; Fibroblasts; Gene Knockout Techniques; Genetic Predisposition to Disease; Humans; Loss of Function Mutation; Male; Microcephaly; Models, Molecular; Neurodevelopmental Disorders; Pedigree; Prosencephalon; Valine-tRNA Ligase; Zebrafish

The comparative genomics and complex population history of baboons. - Jeffrey Rogers; Raveendran, Muthuswamy; R. Alan Harris; Mailund, Thomas; Leppälä, Kalle; Athanasiadis, Georgios; Schierup, Mikkel Heide; Cheng, Jade; Munch, Kasper; Walker, Jerilyn A; Konkel, Miriam K; Jordan, Vallmer; et al. (Sci Adv, 2019)
Recent studies suggest that closely related species can accumulate substantial genetic and phenotypic differences despite ongoing gene flow, thus challenging traditional ideas regarding the genetics of speciation. Baboons (genus ) are Old World monkeys consisting of six readily distinguishable species. Baboon species hybridize in the wild, and prior data imply a complex history of differentiation and introgression. We produced a reference genome assembly for the olive baboon () and whole-genome sequence data for all six extant species. We document multiple episodes of admixture and introgression during the radiation of baboons, thus demonstrating their value as a model of complex evolutionary divergence, hybridization, and reticulation. These results help inform our understanding of similar cases, including modern humans, Neanderthals, Denisovans, and other ancient hominins.
Keywords: Animals; Base Sequence; Biological Evolution; Female; Gene Flow; Genomics; Haplotypes; Humans; Hybridization, Genetic; Male; Papio; Phylogeny; Polymorphism, Genetic; Whole Genome Sequencing

Diversity and evolution of the transposable element repertoire in arthropods with particular reference to insects. - Petersen, Malte; Armisén, David; Richard A Gibbs; Hering, Lars; Khila, Abderrahman; Mayer, Georg; Stephen Richards; Niehuis, Oliver; Misof, Bernhard (BMC Evol Biol, 2019)
BACKGROUND: Transposable elements (TEs) are a major component of metazoan genomes and are associated with a variety of mechanisms that shape genome architecture and evolution. Despite the ever-growing number of insect genomes sequenced to date, our understanding of the diversity and evolution of insect TEs remains poor. RESULTS: Here, we present a standardized characterization and an order-level comparison of arthropod TE repertoires, encompassing 62 insect and 11 outgroup species. The insect TE repertoire contains TEs of almost every class previously described, and in some cases even TEs previously reported only from vertebrates and plants. Additionally, we identified a large fraction of unclassifiable TEs. We found high variation in TE content, ranging from less than 6% in the antarctic midge (Diptera), the honey bee and the turnip sawfly (Hymenoptera) to more than 58% in the malaria mosquito (Diptera) and the migratory locust (Orthoptera), and a possible relationship between the content and diversity of TEs and the genome size. CONCLUSION: While most insect orders exhibit a characteristic TE composition, we also observed intraordinal differences, e.g., in Diptera, Hymenoptera, and Hemiptera. Our findings shed light on common patterns and reveal lineage-specific differences in content and evolution of TEs in insects. We anticipate our study to provide the basis for future comparative research on the insect TE repertoire.
Keywords: Animals; Antarctic Regions; Base Sequence; DNA Transposable Elements; Evolution, Molecular; Genetic Variation; Genome Size; Genome, Insect; Insecta; Phylogeny

Evolution of DNA Methylation in Papio Baboons. - Vilgalys, Tauras P; Jeffrey Rogers; Jolly, Clifford J; Mukherjee, Sayan; Tung, Jenny (Mol Biol Evol, 2019)
Changes in gene regulation have long been thought to play an important role in primate evolution. However, although a number of studies have compared genome-wide gene expression patterns across primate species, fewer have investigated the gene regulatory mechanisms that underlie such patterns, or the relative contribution of drift versus selection. Here, we profiled genome-scale DNA methylation levels in blood samples from five of the six extant species of the baboon genus Papio (4-14 individuals per species). This radiation presents the opportunity to investigate DNA methylation divergence at both shallow and deeper timescales (0.380-1.4 My). In contrast to studies in human populations, but similar to studies in great apes, DNA methylation profiles clearly mirror genetic and geographic structure. Divergence in DNA methylation proceeds fastest in unannotated regions of the genome and slowest in regions of the genome that are likely more constrained at the sequence level (e.g., gene exons). Both heuristic approaches and Ornstein-Uhlenbeck models suggest that DNA methylation levels at a small set of sites have been affected by positive selection, and that this class is enriched in functionally relevant contexts, including promoters, enhancers, and CpG islands. Our results thus indicate that the rate and distribution of DNA methylation changes across the genome largely mirror genetic structure. However, at some CpG sites, DNA methylation levels themselves may have been a target of positive selection, pointing to loci that could be important in connecting sequence variation to fitness-related traits.
Keywords: Animals; DNA Methylation; Evolution, Molecular; Papio; Phylogeography

Exome sequencing of 20,791 cases of type 2 diabetes and 24,440 controls. - Flannick, Jason; Mercader, Josep M; Fuchsberger, Christian; Udler, Miriam S; Mahajan, Anubha; Wessel, Jennifer; Teslovich, Tanya M; Caulkins, Lizz; Koesterer, Ryan; Barajas-Olmos, Francisco; Blackwell, Thomas W; Eric Boerwinkle; et al. (Nature, 2019)
Protein-coding genetic variants that strongly affect disease risk can yield relevant clues to disease pathogenesis. Here we report exome-sequencing analyses of 20,791 individuals with type 2 diabetes (T2D) and 24,440 non-diabetic control participants from 5 ancestries. We identify gene-level associations of rare variants (with minor allele frequencies of less than 0.5%) in 4 genes at exome-wide significance, including a series of more than 30 SLC30A8 alleles that conveys protection against T2D, and in 12 gene sets, including those corresponding to T2D drug targets (P = 6.1 × 10) and candidate genes from knockout mice (P = 5.2 × 10). Within our study, the strongest T2D gene-level signals for rare variants explain at most 25% of the heritability of the strongest common single-variant signals, and the gene-level effect sizes of the rare variants that we observed in established T2D drug targets will require 75,000-185,000 sequenced cases to achieve exome-wide significance. We propose a method to interpret these modest rare-variant associations and to incorporate these associations into future target or gene prioritization efforts.
Keywords: Animals; Case-Control Studies; Decision Support Techniques; Diabetes Mellitus, Type 2; Exome; Exome Sequencing; Female; Gene Frequency; Genome-Wide Association Study; Humans; Male; Mice; Mice, Knockout

Framework for microRNA variant annotation and prioritization using human population and disease datasets. - Oak, Ninad; Ghosh, Rajarshi; Huang, Kuan-Lin; David A Wheeler; Ding, Li; Plon, Sharon E (Hum Mutat, 2019)
MicroRNA (miRNA) expression is frequently deregulated in human disease, in contrast, disease-associated miRNA mutations are understudied. We developed Annotative Database of miRNA Elements, ADmiRE, which combines multiple existing and new biological annotations to aid prioritization of causal miRNA variation. We annotated 10,206 mature (3,257 within seed region) miRNA variants from multiple large sequencing datasets including gnomAD (15,496 genomes; 123,136 exomes). The pattern of miRNA variation closely resembles protein-coding exonic regions, with no difference between intragenic and intergenic miRNAs (P = 0.56), and high confidence miRNAs demonstrate higher sequence constraint (P < 0.001). Conservation analysis across 100 vertebrates identified 765 highly conserved miRNAs that also have limited genetic variation in gnomAD. We applied ADmiRE to the TCGA PanCancerAtlas WES dataset containing over 10,000 individuals across 33 adult cancers and annotated 1,267 germline (rare in gnomAD) and 1,492 somatic miRNA variants. Several miRNA families with deregulated gene expression in cancer have low levels of both somatic and germline variants, e.g., let-7 and miR-10. In addition to known somatic miR-142 mutations in hematologic cancers, we describe novel somatic miR-21 mutations in esophageal cancers impacting downstream miRNA targets. Through the development of ADmiRE, we present a framework for annotation and prioritization of miRNA variation in disease datasets.
Keywords: Animals; Base Sequence; Conserved Sequence; Databases, Genetic; Disease; Exome Sequencing; Genetics, Population; Genome, Human; Germ-Line Mutation; Humans; MicroRNAs; Molecular Sequence Annotation; Neoplasms; Phylogeny; Vertebrates

Gene Therapy Rescues Retinal Degeneration in Receptor Expression-Enhancing Protein 6 Mutant Mice. - Zaneveld, Smriti Agrawal; Eblimit, Aiden; Liang, Qingnan; Bertrand, Renae; Wu, Nathaniel; Liu, Hehe; Nguyen, Quynh; Zaneveld, Jacques; Wang, Keqing; Yumei Li; Rui Chen (Hum Gene Ther, 2019)
Hereditary retinal dystrophy is clinically defined as a broad group of chronic and progressive disorders that affect visual function by causing photoreceptor degeneration. Previously, we identified mutations in the gene encoding receptor expression-enhancing protein 6 (REEP6), in individuals with autosomal recessive retinitis pigmentosa (RP), the most common form of inherited retinal dystrophy. One individual was molecularly diagnosed with biallelic REEP6 mutations, a missense mutation over a frameshift mutation. In this study, we generated Reep6 compound heterozygous mice, Reep6, which mimic the patient genotype and recapitulate the early-onset retinal degeneration phenotypes observed in the individual with RP. To determine the feasibility of rescuing the Reep6 mutant phenotype via gene replacement therapy, we delivered Reep6.1, the mouse retina-specific isoform of REEP6, to photoreceptors of Reep6 mutant mice on postnatal day 20. Evaluation of the therapeutic effects 2 months posttreatment showed improvements in the photoresponse as well as preservation of photoreceptor cells. Importantly, guanylyl cyclase 1 (GC1) expression was also restored to the outer segment after treatment. Furthermore, rAAV8-Reep6.1 single treatment in Reep6 mutant mice 1 year postinjection showed significant improvements in retinal function and morphology, suggesting that the treatment is effective even after a prolonged period. Findings from this study show that gene replacement therapy in the retina with rAAV overexpressing Reep6 is effective, preserving photoreceptor function in Reep6 mutant mice. These findings provide evidence that rAAV8-based gene therapy can prolong survival of photoreceptors in vivo and can be potentially used as a therapeutic modality for treatment of patients with RP.
Keywords: Animals; Dependovirus; Disease Models, Animal; Electrophysiological Phenomena; Electroretinography; Endoplasmic Reticulum Stress; Eye Proteins; Gene Expression; Genetic Therapy; Genetic Vectors; Genotype; Guanylate Cyclase; Immunohistochemistry; Light; Membrane Proteins; Mice; Mice, Knockout; Mutation; Photoreceptor Cells; Protein Transport; Receptors, Cell Surface; Retinal Degeneration; Transduction, Genetic; Transgenes

Genetic architecture of laterality defects revealed by whole exome sequencing. - Li, Alexander H; Hanchard, Neil A; Azamian, Mahshid; D'Alessandro, Lisa C A; Coban-Akdemir, Zeynep; Lopez, Keila N; Hall, Nancy J; Dickerson, Heather; Nicosia, Annarita; Fernbach, Susan; Boone, Philip M; Gambin, Tomaz; et al. (Eur J Hum Genet, 2019)
Aberrant left-right patterning in the developing human embryo can lead to a broad spectrum of congenital malformations. The causes of most laterality defects are not known, with variants in established genes accounting for <20% of cases. We sought to characterize the genetic spectrum of these conditions by performing whole-exome sequencing of 323 unrelated laterality cases. We investigated the role of rare, predicted-damaging variation in 1726 putative laterality candidate genes derived from model organisms, pathway analyses, and human phenotypes. We also evaluated the contribution of homo/hemizygous exon deletions and gene-based burden of rare variation. A total of 28 candidate variants (26 rare predicted-damaging variants and 2 hemizygous deletions) were identified, including variants in genes known to cause heterotaxy and primary ciliary dyskinesia (ACVR2B, NODAL, ZIC3, DNAI1, DNAH5, HYDIN, MMP21), and genes without a human phenotype association, but with prior evidence for a role in embryonic laterality or cardiac development. Sanger validation of the latter variants in probands and their parents revealed no de novo variants, but apparent transmitted heterozygous (ROCK2, ISL1, SMAD2), and hemizygous (RAI2, RIPPLY1) variant patterns. Collectively, these variants account for 7.1% of our study subjects. We also observe evidence for an excess burden of rare, predicted loss-of-function variation in PXDNL and BMS1- two genes relevant to the broader laterality phenotype. These findings highlight potential new genes in the development of laterality defects, and suggest extensive locus heterogeneity and complex genetic models in this class of birth defects.
Keywords: Animals; Body Patterning; Embryonic Development; Exome Sequencing; Female; Genetic Association Studies; Genome, Human; Genomics; GTP Phosphohydrolases; Heart Defects, Congenital; Heterotaxy Syndrome; Humans; Male; Peroxidases; Zebrafish; Zebrafish Proteins

Genome-wide patterns of transposon proliferation in an evolutionary young hybrid fish. - Dennenmoser, Stefan; Fritz J Sedlazeck; Schatz, Michael C; Altmüller, Janine; Zytnicki, Matthias; Nolte, Arne W (Mol Ecol, 2019)
Hybridization can induce transposons to jump into new genomic positions, which may result in their accumulation across the genome. Alternatively, transposon copy numbers may increase through nonallelic (ectopic) homologous recombination in highly repetitive regions of the genome. The relative contribution of transposition bursts versus recombination-based mechanisms to evolutionary processes remains unclear because studies on transposon dynamics in natural systems are rare. We assessed the genomewide distribution of transposon insertions in a young hybrid lineage ("invasive Cottus", n = 11) and its parental species Cottus rhenanus (n = 17) and Cottus perifretum(n = 9) using a reference genome assembled from long single molecule pacbio reads. An inventory of transposable elements was reconstructed from the same data and annotated. Transposon copy numbers in the hybrid lineage increased in 120 (15.9%) out of 757 transposons studied here. The copy number increased on average by 69% (range: 10%-197%). Given the age of the hybrid lineage, this suggests that they have proliferated within a few hundred generations since admixture began. However, frequency spectra of transposon insertions revealed no increase in novel and rare insertions across assembled parts of the genome. This implies that transposons were added to repetitive regions of the genome that remain difficult to assemble. Future studies will need to evaluate whether recombination-based mechanisms rather than genomewide transposition may explain the majority of the recent transposon proliferation in the hybrid lineage. Irrespectively of the underlying mechanism, the observed overabundance in repetitive parts of the genome suggests that gene-rich regions are unlikely to be directly affected.
Keywords: Animals; DNA Copy Number Variations; DNA Transposable Elements; Evolution, Molecular; Fishes; Genome; Hybridization, Genetic

Genomic Profiling of Childhood Tumor Patient-Derived Xenograft Models to Enable Rational Clinical Trial Design. - Rokita, Jo Lynne; Rathi, Komal S; Cardenas, Maria F; Upton, Kristen A; Jayaseelan, Joy; Cross, Katherine L; Pfeil, Jacob; Egolf, Laura E; Way, Gregory P; Farrel, Alvin; Kendsersky, Nathan M; Patel, Khushbu; et al. (Cell Rep, 2019)
Accelerating cures for children with cancer remains an immediate challenge as a result of extensive oncogenic heterogeneity between and within histologies, distinct molecular mechanisms evolving between diagnosis and relapsed disease, and limited therapeutic options. To systematically prioritize and rationally test novel agents in preclinical murine models, researchers within the Pediatric Preclinical Testing Consortium are continuously developing patient-derived xenografts (PDXs)-many of which are refractory to current standard-of-care treatments-from high-risk childhood cancers. Here, we genomically characterize 261 PDX models from 37 unique pediatric cancers; demonstrate faithful recapitulation of histologies and subtypes; and refine our understanding of relapsed disease. In addition, we use expression signatures to classify tumors for TP53 and NF1 pathway inactivation. We anticipate that these data will serve as a resource for pediatric oncology drug development and will guide rational clinical trial design for children with cancer.
Keywords: Animals; Cell Line, Tumor; Central Nervous System Neoplasms; Child; Clinical Trials as Topic; Disease Models, Animal; Exome Sequencing; Genomics; Humans; Mice; Mutation; Neuroblastoma; Neurofibromin 1; Osteosarcoma; Precursor Cell Lymphoblastic Leukemia-Lymphoma; Recurrence; Rhabdomyosarcoma; Sarcoma, Ewing; Tumor Suppressor Protein p53; Wilms Tumor; Xenograft Model Antitumor Assays

Insights into the evolution of social systems and species from baboon studies. - Fischer, Julia; Higham, James P; Alberts, Susan C; Barrett, Louise; Beehner, Jacinta C; Bergman, Thore J; Carter, Alecia J; Collins, Anthony; Elton, Sarah; Fagot, Joël; Ferreira da Silva, Maria Joana; Hammerschmidt, Kurt; et al. (Elife, 2019)
Baboons, members of the genus comprise six closely related species distributed throughout sub-Saharan Africa and southwest Arabia. The species exhibit more ecological flexibility and a wider range of social systems than many other primates. This article summarizes our current knowledge of the natural history of baboons and highlights directions for future research. We suggest that baboons can serve as a valuable model for complex evolutionary processes, such as speciation and hybridization. The evolution of baboons has been heavily shaped by climatic changes and population expansion and fragmentation in the African savanna environment, similar to the processes that acted during human evolution. With accumulating long-term data, and new data from previously understudied species, baboons are ideally suited for investigating the links between sociality, health, longevity and reproductive success. To achieve these aims, we propose a closer integration of studies at the proximate level, including functional genomics, with behavioral and ecological studies.
Keywords: Aging; Animals; Behavior, Animal; Biological Evolution; Ecology; Female; Genomics; Male; Models, Animal; Papio; Phylogeography; Social Behavior

MHC genotyping from rhesus macaque exome sequences. - Caskey, John R; Wiseman, Roger W; Karl, Julie A; Baker, David A; Lee, Taylor; Maddox, Robert J; Raveendran, Muthuswamy; R. Alan Harris; Jianhong Hu; Donna M Muzny; Jeffrey Rogers; O'Connor, David H (Immunogenetics, 2019)
Indian rhesus macaque major histocompatibility complex (MHC) variation can influence the outcomes of transplantation and infectious disease studies. Frequently, rhesus macaques are MHC genotyped to identify variants that could account for unexpected results. Since the MHC is only one region in the genome where variation could impact experimental outcomes, strategies for simultaneously profiling variation in the macaque MHC and the remainder of the protein coding genome would be useful. Here we determine MHC class I and class II genotypes using target-capture probes enriched for MHC sequences, a method we term macaque exome sequence (MES) genotyping. For a cohort of 27 Indian rhesus macaques, we describe two methods for obtaining MHC genotypes from MES data and demonstrate that the MHC class I and class II genotyping results obtained with these methods are 98.1% and 98.7% concordant, respectively, with expected MHC genotypes. In contrast, conventional MHC genotyping results obtained by deep sequencing of short multiplex PCR amplicons were only 92.6% concordant with expectations for this cohort.
Keywords: Animals; Exome; Exome Sequencing; Haplotypes; Histocompatibility Antigens Class I; Histocompatibility Antigens Class II; Macaca mulatta; Polymorphism, Genetic

Molecular evolutionary trends and feeding ecology diversification in the Hemiptera, anchored by the milkweed bug genome. - Panfilio, Kristen A; Vargas Jentzsch, Iris M; Benoit, Joshua B; Erezyilmaz, Deniz; Suzuki, Yuichiro; Colella, Stefano; Robertson, Hugh M; Poelchau, Monica F; Waterhouse, Robert M; Ioannidis, Panagiotis; Weirauch, Matthew T; Hughes, Daniel S T; et al. (Genome Biol, 2019)
BACKGROUND: The Hemiptera (aphids, cicadas, and true bugs) are a key insect order, with high diversity for feeding ecology and excellent experimental tractability for molecular genetics. Building upon recent sequencing of hemipteran pests such as phloem-feeding aphids and blood-feeding bed bugs, we present the genome sequence and comparative analyses centered on the milkweed bug Oncopeltus fasciatus, a seed feeder of the family Lygaeidae. RESULTS: The 926-Mb Oncopeltus genome is well represented by the current assembly and official gene set. We use our genomic and RNA-seq data not only to characterize the protein-coding gene repertoire and perform isoform-specific RNAi, but also to elucidate patterns of molecular evolution and physiology. We find ongoing, lineage-specific expansion and diversification of repressive C2H2 zinc finger proteins. The discovery of intron gain and turnover specific to the Hemiptera also prompted the evaluation of lineage and genome size as predictors of gene structure evolution. Furthermore, we identify enzymatic gains and losses that correlate with feeding biology, particularly for reductions associated with derived, fluid nutrition feeding. CONCLUSIONS: With the milkweed bug, we now have a critical mass of sequenced species for a hemimetabolous insect order and close outgroup to the Holometabola, substantially improving the diversity of insect genomics. We thereby define commonalities among the Hemiptera and delve into how hemipteran genomes reflect distinct feeding ecologies. Given Oncopeltus's strength as an experimental model, these new sequence resources bolster the foundation for molecular research and highlight technical considerations for the analysis of medium-sized invertebrate genomes.
Keywords: Amino Acid Sequence; Animals; CYS2-HIS2 Zinc Fingers; Evolution, Molecular; Feeding Behavior; Gene Dosage; Gene Expression Profiling; Gene Transfer, Horizontal; Genes, Homeobox; Genome, Insect; Hemiptera; Pigmentation; Smell; Transcription Factors

Mutations in ANKLE2, a ZIKA Virus Target, Disrupt an Asymmetric Cell Division Pathway in Drosophila Neuroblasts to Cause Microcephaly. - Link, Nichole; Chung, Hyunglok; Jolly, Angad; Withers, Marjorie; Tepe, Burak; Arenkiel, Benjamin R; Shah, Priya S; Krogan, Nevan J; Aydin, Hatip; Geckinli, Bilgen B; Tos, Tulay; Isikay, Sedat; et al. (Dev Cell, 2019)
The apical Par complex, which contains atypical protein kinase C (aPKC), Bazooka (Par-3), and Par-6, is required for establishing polarity during asymmetric division of neuroblasts in Drosophila, and its activity depends on L(2)gl. We show that loss of Ankle2, a protein associated with microcephaly in humans and known to interact with Zika protein NS4A, reduces brain volume in flies and impacts the function of the Par complex. Reducing Ankle2 levels disrupts endoplasmic reticulum (ER) and nuclear envelope morphology, releasing the kinase Ballchen-VRK1 into the cytosol. These defects are associated with reduced phosphorylation of aPKC, disruption of Par-complex localization, and spindle alignment defects. Importantly, removal of one copy of ballchen or l(2)gl suppresses Ankle2 mutant phenotypes and restores viability and brain size. Human mutational studies implicate the above-mentioned genes in microcephaly and motor neuron disease. We suggest that NS4A, ANKLE2, VRK1, and LLGL1 define a pathway impinging on asymmetric determinants of neural stem cell division.
Keywords: Animals; Asymmetric Cell Division; Cell Division; Cell Polarity; Drosophila melanogaster; Humans; Membrane Proteins; Microcephaly; Mutation; Neural Stem Cells; Neurons; Nuclear Proteins; Zika Virus

A nonhuman primate model of inherited retinal disease. - Moshiri, Ala; Rui Chen; Kim, Soohyun; R. Alan Harris; Yumei Li; Raveendran, Muthuswamy; Davis, Sarah; Liang, Qingnan; Pomerantz, Ori; Wang, Jun; Garzel, Laura; Cameron, Ashley; et al. (J Clin Invest, 2019)
Inherited retinal degenerations are a common cause of untreatable blindness worldwide, with retinitis pigmentosa and cone dystrophy affecting approximately 1 in 3500 and 1 in 10,000 individuals, respectively. A major limitation to the development of effective therapies is the lack of availability of animal models that fully replicate the human condition. Particularly for cone disorders, rodent, canine, and feline models with no true macula have substantive limitations. By contrast, the cone-rich macula of a nonhuman primate (NHP) closely mirrors that of the human retina. Consequently, well-defined NHP models of heritable retinal diseases, particularly cone disorders that are predictive of human conditions, are necessary to more efficiently advance new therapies for patients. We have identified 4 related NHPs at the California National Primate Research Center with visual impairment and findings from clinical ophthalmic examination, advanced retinal imaging, and electrophysiology consistent with achromatopsia. Genetic sequencing confirmed a homozygous R565Q missense mutation in the catalytic domain of PDE6C, a cone-specific phototransduction enzyme associated with achromatopsia in humans. Biochemical studies demonstrate that the mutant mRNA is translated into a stable protein that displays normal cellular localization but is unable to hydrolyze cyclic GMP (cGMP). This NHP model of a cone disorder will not only serve as a therapeutic testing ground for achromatopsia gene replacement, but also for optimization of gene editing in the macula and of cone cell replacement in general.
Keywords: Amino Acid Substitution; Animals; Color Vision Defects; Cone Dystrophy; Cyclic Nucleotide Phosphodiesterases, Type 6; Disease Models, Animal; Eye Proteins; Female; HEK293 Cells; Humans; Macaca mulatta; Male; Mutation, Missense; Retinitis Pigmentosa

A novel disorder involving dyshematopoiesis, inflammation, and HLH due to aberrant CDC42 function. - Lam, Michael T; Coppola, Simona; Krumbach, Oliver H F; Prencipe, Giusi; Insalaco, Antonella; Cifaldi, Cristina; Brigida, Immacolata; Zara, Erika; Scala, Serena; Di Cesare, Silvia; Martinelli, Simone; Di Rocco, Martina; et al. (J Exp Med, 2019)
Hemophagocytic lymphohistiocytosis (HLH) is characterized by immune dysregulation due to inadequate restraint of overactivated immune cells and is associated with a variable clinical spectrum having overlap with more common pathophysiologies. HLH is difficult to diagnose and can be part of inflammatory syndromes. Here, we identify a novel hematological/autoinflammatory condition (NOCARH syndrome) in four unrelated patients with superimposable features, including neonatal-onset cytopenia with dyshematopoiesis, autoinflammation, rash, and HLH. Patients shared the same de novo mutation (Chr1:22417990C>T, p.R186C) and altered hematopoietic compartment, immune dysregulation, and inflammation. mutations had been associated with syndromic neurodevelopmental disorders. In vitro and in vivo assays documented unique effects of p.R186C on CDC42 localization and function, correlating with the distinctiveness of the trait. Emapalumab was critical to the survival of one patient, who underwent successful bone marrow transplantation. Early recognition of the disorder and establishment of treatment followed by bone marrow transplant are important to survival.
Keywords: Alleles; Amino Acid Substitution; Animals; Binding Sites; cdc42 GTP-Binding Protein; Cell Line, Tumor; Child; Disease Susceptibility; Female; Genetic Association Studies; Genotype; Humans; Infant; Lymphohistiocytosis, Hemophagocytic; Male; Mice; Models, Molecular; Molecular Conformation; Mutation; Phenotype; Protein Binding

Protein-coding variants implicate novel genes related to lipid homeostasis contributing to body-fat distribution. - Justice, Anne E; Karaderi, Tugce; Highland, Heather M; Young, Kristin L; Graff, Mariaelisa; Lu, Yingchang; Turcot, Valérie; Auer, Paul L; Fine, Rebecca S; Guo, Xiuqing; Schurmann, Claudia; Lempradl, Adelheid; et al. (Nat Genet, 2019)
Body-fat distribution is a risk factor for adverse cardiovascular health consequences. We analyzed the association of body-fat distribution, assessed by waist-to-hip ratio adjusted for body mass index, with 228,985 predicted coding and splice site variants available on exome arrays in up to 344,369 individuals from five major ancestries (discovery) and 132,177 European-ancestry individuals (validation). We identified 15 common (minor allele frequency, MAF ≥5%) and nine low-frequency or rare (MAF <5%) coding novel variants. Pathway/gene set enrichment analyses identified lipid particle, adiponectin, abnormal white adipose tissue physiology and bone development and morphology as important contributors to fat distribution, while cross-trait associations highlight cardiometabolic traits. In functional follow-up analyses, specifically in Drosophila RNAi-knockdowns, we observed a significant increase in the total body triglyceride levels for two genes (DNAH10 and PLXND1). We implicate novel genes in fat distribution, stressing the importance of interrogating low-frequency and protein-coding variants.
Keywords: Animals; Body Fat Distribution; Body Mass Index; Case-Control Studies; Drosophila; Exome; Female; Gene Frequency; Genetic Predisposition to Disease; Genetic Variation; Genome-Wide Association Study; Homeostasis; Humans; Lipids; Male; Proteins; Risk Factors; Waist-Hip Ratio

Structural variant calling: the long and the short of it. - Mahmoud, Medhat; Gobet, Nastassia; Cruz-Dávalos, Diana Ivette; Mounier, Ninon; Dessimoz, Christophe; Fritz J Sedlazeck (Genome Biol, 2019)
Recent research into structural variants (SVs) has established their importance to medicine and molecular biology, elucidating their role in various diseases, regulation of gene expression, ethnic diversity, and large-scale chromosome evolution-giving rise to the differences within populations and among species. Nevertheless, characterizing SVs and determining the optimal approach for a given experimental design remains a computational and scientific challenge. Multiple approaches have emerged to target various SV classes, zygosities, and size ranges. Here, we review these approaches with respect to their ability to infer SVs across the full spectrum of large, complex variations and present computational methods for each approach.
Keywords: Animals; Genomic Structural Variation; Genomics; Humans

TBX6-associated congenital scoliosis (TACS) as a clinically distinguishable subtype of congenital scoliosis: further evidence supporting the compound inheritance and TBX6 gene dosage model. - Liu, Jiaqi; Wu, Nan; Yang, Nan; Takeda, Kazuki; Chen, Weisheng; Li, Weiyu; Du, Renqian; Liu, Sen; Zhou, Yangzhong; Zhang, Ling; Liu, Zhenlei; Zuo, Yuzhi; et al. (Genet Med, 2019)
PURPOSE: To characterize clinically measurable endophenotypes, implicating the TBX6 compound inheritance model. METHODS: Patients with congenital scoliosis (CS) from China(N = 345, cohort 1), Japan (N = 142, cohort 2), and the United States (N = 10, cohort 3) were studied. Clinically measurable endophenotypes were compared according to the TBX6 genotypes. A mouse model for Tbx6 compound inheritance (N = 52) was investigated by micro computed tomography (micro-CT). A clinical diagnostic algorithm (TACScore) was developed to assist in clinical recognition of TBX6-associated CS (TACS). RESULTS: In cohort 1, TACS patients (N = 33) were significantly younger at onset than the remaining CS patients (P = 0.02), presented with one or more hemivertebrae/butterfly vertebrae (P = 4.9 × 10), and exhibited vertebral malformations involving the lower part of the spine (T8-S5, P = 4.4 × 10); observations were confirmed in two replication cohorts. Simple rib anomalies were prevalent in TACS patients (P = 3.1 × 10), while intraspinal anomalies were uncommon (P = 7.0 × 10). A clinically usable TACScore was developed with an area under the curve (AUC) of 0.9 (P = 1.6 × 10). A Tbx6 mouse model supported that a gene dosage effect underlies the TACS phenotype. CONCLUSION: TACS is a clinically distinguishable entity with consistent clinically measurable endophenotypes. The type and distribution of vertebral column abnormalities in TBX6/Tbx6 compound inheritance implicate subtle perturbations in gene dosage as a cause of spine developmental birth defects responsible for about 10% of CS.
Keywords: Animals; Cohort Studies; Disease Models, Animal; Gene Dosage; Humans; Inheritance Patterns; Mice; Models, Genetic; Scoliosis; Spine; T-Box Domain Proteins

Transcriptomic profiles of retinal ganglion cells are defined by the magnitude of intraocular pressure elevation in adult mice. - Park, Yong H; Snook, Joshua D; Ostrin, Edwin J; Kim, Sangbae; Rui Chen; Frankfort, Benjamin J (Sci Rep, 2019)
Elevated intraocular pressure (IOP) is the major risk factor for glaucoma, a sight threatening disease of retinal ganglion cells (RGCs) and their axons. Despite the central importance of IOP, details of the impact of IOP elevation on RGC gene expression remain elusive. We developed a 4-step immunopanning protocol to extract adult mouse RGCs with high fidelity and used it to isolate RGCs from wild type mice exposed to 2 weeks of IOP elevation generated by the microbead model. IOP was elevated to 2 distinct levels which were defined as Mild (IOP increase >1 mmHg and <4 mmHg) and Moderate (IOP increase ≥4 mmHg). RNA sequencing was used to compare the transcriptional environment at each IOP level. Differentially expressed genes were markedly different between the 2 groups, and pathway analysis revealed frequently opposed responses between the IOP levels. These results suggest that the magnitude of IOP elevation has a critical impact on RGC transcriptional changes. Furthermore, it is possible that IOP-based set points exist within RGCs to impact the direction of transcriptional change. It is possible that this improved understanding of changes in RGC gene expression can ultimately lead to novel diagnostics and therapeutics for glaucoma.
Keywords: Animals; Biomarkers; Disease Models, Animal; Female; Glaucoma; Intraocular Pressure; Male; Mice; Mice, Inbred C57BL; Retinal Ganglion Cells; Sequence Analysis, RNA; Transcriptome

Unraveling the functional role of the orphan solute carrier, SLC22A24 in the transport of steroid conjugates through metabolomic and genome-wide association studies. - Yee, Sook Wah; Stecula, Adrian; Chien, Huan-Chieh; Zou, Ling; Feofanova, Elena V; van Borselen, Marjolein; Cheung, Kit Wun Kathy; Yousri, Noha A; Suhre, Karsten; Kinchen, Jason M; Eric Boerwinkle; Irannejad, Roshanak; et al. (PLoS Genet, 2019)
Variation in steroid hormone levels has wide implications for health and disease. The genes encoding the proteins involved in steroid disposition represent key determinants of interindividual variation in steroid levels and ultimately, their effects. Beginning with metabolomic data from genome-wide association studies (GWAS), we observed that genetic variants in the orphan transporter, SLC22A24 were significantly associated with levels of androsterone glucuronide and etiocholanolone glucuronide (sentinel SNPs p-value <1x10-30). In cells over-expressing human or various mammalian orthologs of SLC22A24, we showed that steroid conjugates and bile acids were substrates of the transporter. Phylogenetic, genomic, and transcriptomic analyses suggested that SLC22A24 has a specialized role in the kidney and appears to function in the reabsorption of organic anions, and in particular, anionic steroids. Phenome-wide analysis showed that functional variants of SLC22A24 are associated with human disease such as cardiovascular diseases and acne, which have been linked to dysregulated steroid metabolism. Collectively, these functional genomic studies reveal a previously uncharacterized protein involved in steroid homeostasis, opening up new possibilities for SLC22A24 as a pharmacological target for regulating steroid levels.
Keywords: Androsterone; Animals; Biological Transport; Genome-Wide Association Study; HEK293 Cells; Humans; Metabolomics; Models, Molecular; Organic Cation Transport Proteins; Phylogeny; Polymorphism, Single Nucleotide; Steroids; Symporters

Adding resolution and dimensionality to comparative genomics: moving from reference genomes to clade genomics. - Jeffrey Rogers (Genome Biol, 2018)
The main goal and promise of comparative genomics has been to create a comprehensive catalog of genomic information and function across the phenomenal diversity of living systems. A recent study has demonstrated the evolutionary insights possible by generating high-quality whole-genome assemblies from multiple species of a clade.
Keywords: Animals; Computational Biology; Genome; Genomics; Humans; Phylogeny; Reference Standards; Sequence Analysis, DNA

Additive genetic variation in the craniofacial skeleton of baboons (genus Papio) and its relationship to body and cranial size. - Joganic, Jessica L; Willmore, Katherine E; Richtsmeier, Joan T; Weiss, Kenneth M; Mahaney, Michael C; Jeffrey Rogers; Cheverud, James M (Am J Phys Anthropol, 2018)
OBJECTIVES: Determining the genetic architecture of quantitative traits and genetic correlations among them is important for understanding morphological evolution patterns. We address two questions regarding papionin evolution: (1) what effect do body and cranial size, age, and sex have on phenotypic (V ) and additive genetic (V ) variation in baboon crania, and (2) how might additive genetic correlations between craniofacial traits and body mass affect morphological evolution? MATERIALS AND METHODS: We use a large captive pedigreed baboon sample to estimate quantitative genetic parameters for craniofacial dimensions (EIDs). Our models include nested combinations of the covariates listed above. We also simulate the correlated response of a given EID due to selection on body mass alone. RESULTS: Covariates account for 1.2-91% of craniofacial V . EID V decreases across models as more covariates are included. The median genetic correlation estimate between each EID and body mass is 0.33. Analysis of the multivariate response to selection reveals that observed patterns of craniofacial variation in extant baboons cannot be attributed solely to correlated response to selection on body mass, particularly in males. DISCUSSION: Because a relatively large proportion of EID V is shared with body mass variation, different methods of correcting for allometry by statistically controlling for size can alter residual V patterns. This may conflate direct selection effects on craniofacial variation with those resulting from a correlated response to body mass selection. This shared genetic variation may partially explain how selection for increased body mass in two different papionin lineages produced remarkably similar craniofacial phenotypes.
Keywords: Animals; Anthropology, Physical; Biological Evolution; Body Size; Cephalometry; Face; Female; Genetic Variation; Genetics, Population; Male; Papio; Skull

The behavioral genetics of nonhuman primates: Status and prospects. - Jeffrey Rogers (Am J Phys Anthropol, 2018)
The complexity and diversity of primate behavior have long attracted the attention of ethologists, psychologists, behavioral ecologists, and neuroscientists. Recent studies have advanced our understanding of the nature of genetic influences on differences in behavior among individuals within species. A number of analyses have focused on the genetic analysis of behavioral reactions to specific experimental tests, providing estimates of the degree of genetic control over reactivity, and beginning to identify the genes involved. Substantial progress is also being made in identifying genetic factors that influence the structure and function of the primate brain. Most of the published studies on these topics have examined either cercopithecines or chimpanzees, though a few studies have addressed these questions in other primate species. One potentially important line of research is beginning to identify the epigenetic processes that influence primate behavior, thus revealing specific cellular and molecular mechanisms by which environmental experiences can influence gene expression or gene function relevant to behavior. This review summarizes many of these studies of non-human primate behavioral genetics. The primary focus is on analyses that address the nature of the genes and genetic processes that affect differences in behavior among individuals within non-human primate species. Analyses of between species differences and potential avenues for future research are also discussed.
Keywords: Animals; Behavior, Animal; Brain; Epigenesis, Genetic; Female; Genetics, Behavioral; Interpersonal Relations; Male; Primates

A biallelic ANTXR1 variant expands the anthrax toxin receptor associated phenotype to tooth agenesis. - Dinckan, Nuriye; Du, Renqian; Akdemir, Zeynep C; Bayram, Yavuz; Jhangiani, Shalini N; Harshavardhan Doddapaneni; Jianhong Hu; Donna M Muzny; Guven, Yeliz; Aktoren, Oya; Kayserili, Hulya; Eric Boerwinkle; et al. (Am J Med Genet A, 2018)
Tooth development is regulated by multiple genetic pathways, which ultimately drive the complex interactions between the oral epithelium and mesenchyme. Disruptions at any time point during this process may lead to failure of tooth development, also known as tooth agenesis (TA). TA is a common craniofacial abnormality in humans and represents the failure to develop one or more permanent teeth. Many genes and potentially subtle variants in these genes contribute to the TA phenotype. We report the clinical and genetic impact of a rare homozygous ANTXR1 variant (c.1312C>T), identified by whole exome sequencing (WES), in a consanguineous Turkish family with TA. Mutations in ANTXR1 have been associated with GAPO (growth retardation, alopecia, pseudoanodontia, and optic atrophy) syndrome and infantile hemangioma, however no clinical characteristics associated with these conditions were observed in our study family. We detected the expression of Antxr1 in oral and dental tissues of developing mouse embryos, further supporting a role for this gene in tooth development. Our findings implicate ANTXR1 as a candidate gene for isolated TA, suggest the involvement of specific hypomorphic alleles, and expand the previously known ANTXR1-associated phenotypes.
Keywords: Alleles; Amino Acid Substitution; Animals; Anodontia; Child; Consanguinity; Exome Sequencing; Facies; Genetic Association Studies; Genotype; Humans; Male; Mice; Microfilament Proteins; Mutation; Neoplasm Proteins; Pedigree; Phenotype; Radiography; Receptors, Cell Surface

CD163+ macrophages promote angiogenesis and vascular permeability accompanied by inflammation in atherosclerosis. - Guo, Liang; Akahori, Hirokuni; Harari, Emanuel; Smith, Samantha L; Polavarapu, Rohini; Karmali, Vinit; Otsuka, Fumiyuki; Gannon, Rachel L; Braumann, Ryan E; Dickinson, Megan H; Gupta, Anuj; Jenkins, Audrey L; et al. (J Clin Invest, 2018)
Intake of hemoglobin by the hemoglobin-haptoglobin receptor CD163 leads to a distinct alternative non-foam cell antiinflammatory macrophage phenotype that was previously considered atheroprotective. Here, we reveal an unexpected but important pathogenic role for these macrophages in atherosclerosis. Using human atherosclerotic samples, cultured cells, and a mouse model of advanced atherosclerosis, we investigated the role of intraplaque hemorrhage on macrophage function with respect to angiogenesis, vascular permeability, inflammation, and plaque progression. In human atherosclerotic lesions, CD163+ macrophages were associated with plaque progression, microvascularity, and a high level of HIF1α and VEGF-A expression. We observed irregular vascular endothelial cadherin in intraplaque microvessels surrounded by CD163+ macrophages. Within these cells, activation of HIF1α via inhibition of prolyl hydroxylases promoted VEGF-mediated increases in intraplaque angiogenesis, vascular permeability, and inflammatory cell recruitment. CD163+ macrophages increased intraplaque endothelial VCAM expression and plaque inflammation. Subjects with homozygous minor alleles of the SNP rs7136716 had elevated microvessel density, increased expression of CD163 in ruptured coronary plaques, and a higher risk of myocardial infarction and coronary heart disease in population cohorts. Thus, our findings highlight a nonlipid-driven mechanism by which alternative macrophages promote plaque angiogenesis, leakiness, inflammation, and progression via the CD163/HIF1α/VEGF-A pathway.
Keywords: Adult; Animals; Antigens, CD; Antigens, Differentiation, Myelomonocytic; Atherosclerosis; Coronary Disease; Coronary Vessels; Disease Progression; Female; Hemoglobins; Humans; Inflammation; Macrophages; Male; Mice; Mice, Inbred C57BL; Middle Aged; Myocardial Infarction; Neovascularization, Pathologic; Oxidative Stress; Permeability; Phenotype; Polymorphism, Single Nucleotide; Receptors, Cell Surface; Signal Transduction

Comparative genomics of the miniature wasp and pest control agent Trichogramma pretiosum. - Lindsey, Amelia R I; Kelkar, Yogeshwar D; Wu, Xin; Sun, Dan; Martinson, Ellen O; Yan, Zhichao; Rugman-Jones, Paul F; Hughes, Daniel S T; Murali, Shwetha C; Qu, Jiaxin; Dugan, Shannon; Lee, Sandra L; et al. (BMC Biol, 2018)
BACKGROUND: Trichogrammatids are minute parasitoid wasps that develop within other insect eggs. They are less than half a millimeter long, smaller than some protozoans. The Trichogrammatidae are one of the earliest branching families of Chalcidoidea: a diverse superfamily of approximately half a million species of parasitoid wasps, proposed to have evolved from a miniaturized ancestor. Trichogramma are frequently used in agriculture, released as biological control agents against major moth and butterfly pests. Additionally, Trichogramma are well known for their symbiotic bacteria that induce asexual reproduction in infected females. Knowledge of the genome sequence of Trichogramma is a major step towards further understanding its biology and potential applications in pest control. RESULTS: We report the 195-Mb genome sequence of Trichogramma pretiosum and uncover signatures of miniaturization and adaptation in Trichogramma and related parasitoids. Comparative analyses reveal relatively rapid evolution of proteins involved in ribosome biogenesis and function, transcriptional regulation, and ploidy regulation. Chalcids also show loss or especially rapid evolution of 285 gene clusters conserved in other Hymenoptera, including many that are involved in signal transduction and embryonic development. Comparisons between sexual and asexual lineages of Trichogramma pretiosum reveal that there is no strong evidence for genome degradation (e.g., gene loss) in the asexual lineage, although it does contain a lower repeat content than the sexual lineage. Trichogramma shows particularly rapid genome evolution compared to other hymenopterans. We speculate these changes reflect adaptations to miniaturization, and to life as a specialized egg parasitoid. CONCLUSIONS: The genomes of Trichogramma and related parasitoids are a valuable resource for future studies of these diverse and economically important insects, including explorations of parasitoid biology, symbiosis, asexuality, biological control, and the evolution of miniaturization. Understanding the molecular determinants of parasitism can also inform mass rearing of Trichogramma and other parasitoids for biological control.
Keywords: Animals; Evolution, Molecular; Genomics; Moths; Pest Control, Biological; Phylogeny; Wasps; Whole Genome Sequencing

Comparison of vitamin D metabolites in wild and captive baboons. - Ziegler, Toni E; Kapoor, Amita; Binkley, Neil C; Rice, Karen S; Jeffrey Rogers; Jolly, Clifford J; Phillips-Conroy, Jane E (Am J Primatol, 2018)
Vitamin D adequacy is essential for multiple physiologic processes. With limited exposure to sunlight for vitamin D synthesis, captive primates are supplemented with vitamin D (cholecalciferol). Vitamin D metabolite data from wild primates living indigenously could suggest optimum levels. The purpose of this study was to: 1) to explore whether baboons, a speciose genus whose members have significant exposed skin, coat color variation and wide geographical distribution, mirrors the skin pigmentation-vitamin D relationship found in humans; 2) compare vitamin D metabolite levels in wild and captive members of the same or similar baboon species; and 3) apply a recently developed method currently used in humans for measuring multiple vitamin D metabolites as a panel to explore if/how these metabolites can inform us on vitamin D sufficiency. Serum samples from males of three baboon species in the wild: Papio anubis (olive baboon, dark exposed skin), P. cynocephalus (yellow baboon, brown exposed skin), and P. hamadryas (hamadryas baboon, pink exposed skin), were compared with vitamin D supplemented captive olive baboons with sun exposure. Liquid chromatography/tandem mass spectrometry (LC/MS/MS) measured vitamin D and its main metabolites. Cholecalciferol, 25 hydroxyvitamin D (25(OH)D ), and 24,25 dihydroxyvitamin D (24,25(OH) D ), showed significant differences by species. The levels of cholecalciferol due to supplements in the captive olive baboons did not convert to higher 25(OH)D while the wild olive baboons exhibited the lowest levels for both cholecalciferol and 25(OH)D . Further metabolic conversion of 25(OH)D to 24,25(OH) D indicated that all baboons had more similar conversion ratios and these were within the same range found for humans that are depicted as having adequate vitamin D levels. This study provided evidence that exposed skin color does influence vitamin D3 levels, with lower levels in darker skinned species, but these differences are eliminated in the downstream metabolite conversion indicating strong regulatory control.
Keywords: Africa South of the Sahara; Aging; Animal Distribution; Animals; Animals, Wild; Animals, Zoo; Dietary Supplements; Male; Papio; Skin Pigmentation; Species Specificity; Vitamin D; Vitamin D Deficiency

Conditional loss of Spata7 in photoreceptors causes progressive retinal degeneration in mice. - Eblimit, Aiden; Agrawal, Smriti Akshay; Thomas, Kandace; Anastassov, Ivan Assenov; Abulikemu, Tajiguli; Moayedi, Yalda; Mardon, Graeme; Rui Chen (Exp Eye Res, 2018)
The mammalian retina consists of multiple cell layers including photoreceptor cells, which are light sensing neurons that play essential functions in the visual process. Previously, we identified mutations in SPATA7, encoding spermatogenesis associated protein 7, in families with Leber Congenital Amaurosis (LCA) and juvenile Retinitis Pigmentosa (RP), and showed that Spata7 null mice recapitulate the human disease phenotype of retinal degeneration. SPATA7 is expressed in the connecting cilium of photoreceptor (PR) cells in the mouse retina, as well as in retinal pigment epithelium (RPE) cells, but the functional role of Spata7 in the RPE remains unknown. To investigate whether Spata7 is required in PRs, the RPE, or both, we conditionally knocked out Spata7 in photoreceptors and RPE cells using Crx-Cre and Best1-Cre transgenic mouse lines, respectively. In Spata7 photoreceptor-specific conditional (cKO) mice, both rod and cone photoreceptor dysfunction and degeneration is observed, characterized by progressive thinning of the outer nuclear layer and reduced response to light; however, RPE-specific deletion of Spata7 does not impair retinal function or cell survival. Furthermore, our findings show that both Rhodopsin and RPGRIP1 are mislocalized in the Spata7; Crx-Cre cKO mice, suggesting that loss of Spata7 in photoreceptors alone can result in altered trafficking of these proteins in the connecting cilium. Together, our findings suggest that loss of Spata7 in photoreceptors alone is sufficient to cause photoreceptor degeneration, but its function in the RPE is not required for photoreceptor survival; therefore, loss of Spata7 in photoreceptors alters both rod and cone function and survival, consistent with the clinical phenotypes observed in LCA and RP patients with mutations in SPATA7.
Keywords: Animals; Cytoskeletal Proteins; Disease Models, Animal; DNA-Binding Proteins; Electroretinography; Mice; Mice, Knockout; Proteins; Retina; Retinal Cone Photoreceptor Cells; Retinal Degeneration; Retinal Rod Photoreceptor Cells; Retinitis Pigmentosa; Rhodopsin

Editorial overview: Insect genomics: Arthropod genomic resources for the 21st century: It only counts if it's in the database! - Stephen Richards; Childers, Anna; Childers, Christopher (Curr Opin Insect Sci, 2018)
Keywords: Animals; Arthropods; Databases, Genetic; Genome, Insect; Insecta; Transcriptome

Expansions of key protein families in the German cockroach highlight the molecular basis of its remarkable success as a global indoor pest. - Harrison, Mark C; Arning, Nicolas; Kremer, Lukas P M; Ylla, Guillem; Belles, Xavier; Bornberg-Bauer, Erich; Huylmans, Ann Kathrin; Jongepier, Evelien; Piulachs, Maria-Dolors; Stephen Richards; Schal, Coby (J Exp Zool B Mol Dev Evol, 2018)
The German cockroach, Blattella germanica, is a worldwide pest that infests buildings, including homes, restaurants, and hospitals, often living in unsanitary conditions. As a disease vector and producer of allergens, this species has major health and economic impacts on humans. Factors contributing to the success of the German cockroach include its resistance to a broad range of insecticides, immunity to many pathogens, and its ability, as an extreme generalist omnivore, to survive on most food sources. The recently published genome shows that B. germanica has an exceptionally high number of protein coding genes. In this study, we investigate the functions of the 93 significantly expanded gene families with the aim to better understand the success of B. germanica as a major pest despite such inhospitable conditions. We find major expansions in gene families with functions related to the detoxification of insecticides and allelochemicals, defense against pathogens, digestion, sensory perception, and gene regulation. These expansions might have allowed B. germanica to develop multiple resistance mechanisms to insecticides and pathogens, and enabled a broad, flexible diet, thus explaining its success in unsanitary conditions and under recurrent chemical control. The findings and resources presented here provide insights for better understanding molecular mechanisms that will facilitate more effective cockroach control.
Keywords: Animals; Blattellidae; Diet; Evolution, Molecular; Genome, Insect; Inactivation, Metabolic; Insect Proteins; Insecticide Resistance; Multigene Family; Pest Control; Receptors, Cell Surface

Full disclosure: Genome assembly is still hard. - Stephen Richards (PLoS Biol, 2018)
Two recent papers highlight the fascinating comparative genomics of anhydrobiosis, the ability to withstand complete desiccation, in bdelloid rotifers and tardigrades. However, both groups had to openly deal with the significant difficulties of generating and interpreting short-read draft assemblies-especially challenging in microscopic species with high sequence polymorphism. These exemplars demonstrate the need to go beyond single draft-quality reference genomes to high-quality multiple species comparative genomics if we are to fully capture the value of genomics.
Keywords: Animals; Desiccation; Genome; Genomics; Rotifera; Tardigrada

The genome of the water strider Gerris buenoi reveals expansions of gene repertoires associated with adaptations to life on the water. - Armisén, David; Rajakumar, Rajendhran; Friedrich, Markus; Benoit, Joshua B; Robertson, Hugh M; Panfilio, Kristen A; Ahn, Seung-Joon; Poelchau, Monica F; Chao, Hsu; Dinh, Huyen; Harshavardhan Doddapaneni; Dugan, Shannon; et al. (BMC Genomics, 2018)
BACKGROUND: Having conquered water surfaces worldwide, the semi-aquatic bugs occupy ponds, streams, lakes, mangroves, and even open oceans. The diversity of this group has inspired a range of scientific studies from ecology and evolution to developmental genetics and hydrodynamics of fluid locomotion. However, the lack of a representative water strider genome hinders our ability to more thoroughly investigate the molecular mechanisms underlying the processes of adaptation and diversification within this group. RESULTS: Here we report the sequencing and manual annotation of the Gerris buenoi (G. buenoi) genome; the first water strider genome to be sequenced thus far. The size of the G. buenoi genome is approximately 1,000 Mb, and this sequencing effort has recovered 20,949 predicted protein-coding genes. Manual annotation uncovered a number of local (tandem and proximal) gene duplications and expansions of gene families known for their importance in a variety of processes associated with morphological and physiological adaptations to a water surface lifestyle. These expansions may affect key processes associated with growth, vision, desiccation resistance, detoxification, olfaction and epigenetic regulation. Strikingly, the G. buenoi genome contains three insulin receptors, suggesting key changes in the rewiring and function of the insulin pathway. Other genomic changes affecting with opsin genes may be associated with wavelength sensitivity shifts in opsins, which is likely to be key in facilitating specific adaptations in vision for diverse water habitats. CONCLUSIONS: Our findings suggest that local gene duplications might have played an important role during the evolution of water striders. Along with these findings, the sequencing of the G. buenoi genome now provides us the opportunity to pursue exciting research opportunities to further understand the genomic underpinnings of traits associated with the extreme body plan and life history of water striders.
Keywords: Adaptation, Physiological; Animals; Evolution, Molecular; Genome; Genomics; Heteroptera; Insect Proteins; Phenotype; Phylogeny

Genomes of Diptera. - Wiegmann, Brian M; Stephen Richards (Curr Opin Insect Sci, 2018)
Diptera (true flies) are among the most diverse holometabolan insect orders and were the first eukaryotic order to have a representative genome fully sequenced. 110 fly species have publically available genome assemblies and many hundreds of population-level genomes have been generated in the model organisms Drosophila melanogaster and the malaria mosquito Anopheles gambiae. Comparative genomics carried out in a phylogenetic context is illuminating many aspects of fly biology, providing unprecedented insight into variability in genome structure, gene content, genetic mechanisms, and rates and patterns of evolution in genes, populations, and species. Despite the rich availability of genomic resources in flies, there remain many fly lineages to which new genome sequencing efforts should be directed. Such efforts would be most valuable in fly families or clades that exhibit multiple origins of key fly behaviors such as blood feeding, phytophagy, parasitism, pollination, and mycophagy.
Keywords: Animals; Diptera; Genome, Insect; Genomics; Phylogeny

Genomes of the Hymenoptera. - Branstetter, Michael G; Childers, Anna K; Cox-Foster, Diana; Hopper, Keith R; Kapheim, Karen M; Toth, Amy L; Worley, Kim C (Curr Opin Insect Sci, 2018)
Hymenoptera is the second-most sequenced arthropod order, with 52 publically archived genomes (71 with ants, reviewed elsewhere), however these genomes do not capture the breadth of this very diverse order (Figure 1, Table 1). These sequenced genomes represent only 15 of the 97 extant families. Although at least 55 other genomes are in progress in an additional 11 families (see Table 2), stinging wasps represent 35 (67%) of the available and 42 (76%) of the in progress genomes. A more comprehensive catalog of hymenopteran genomes is needed for research into the evolutionary processes underlying the expansive diversity in terms of ecology, behavior, and physiological traits within this group. Additional sequencing is needed to generate an assembly for even 0.05% of the estimated 1 million hymenopteran species, and we recommend premier level assemblies for at least 0.1% of the >150,000 named species dispersed across the order. Given the haplodiploid sex determination in Hymenoptera, haploid male sequencing will help minimize genome assembly issues to enable higher quality genome assemblies.
Keywords: Animals; Female; Genome, Insect; Haploidy; Hymenoptera; Male; Phylogeny

Hemimetabolous genomes reveal molecular basis of termite eusociality. - Harrison, Mark C; Jongepier, Evelien; Robertson, Hugh M; Arning, Nicolas; Bitard-Feildel, Tristan; Chao, Hsu; Childers, Christopher P; Dinh, Huyen; Harshavardhan Doddapaneni; Dugan, Shannon; Gowin, Johannes; Greiner, Carolin; et al. (Nat Ecol Evol, 2018)
Around 150 million years ago, eusocial termites evolved from within the cockroaches, 50 million years before eusocial Hymenoptera, such as bees and ants, appeared. Here, we report the 2-Gb genome of the German cockroach, Blattella germanica, and the 1.3-Gb genome of the drywood termite Cryptotermes secundus. We show evolutionary signatures of termite eusociality by comparing the genomes and transcriptomes of three termites and the cockroach against the background of 16 other eusocial and non-eusocial insects. Dramatic adaptive changes in genes underlying the production and perception of pheromones confirm the importance of chemical communication in the termites. These are accompanied by major changes in gene regulation and the molecular evolution of caste determination. Many of these results parallel molecular mechanisms of eusocial evolution in Hymenoptera. However, the specific solutions are remarkably different, thus revealing a striking case of convergence in one of the major evolutionary transitions in biological complexity.
Keywords: Animals; Biological Evolution; Blattellidae; Evolution, Molecular; Genome; Isoptera; Phylogeny; Social Behavior

Integrative genomic analysis reveals novel regulatory mechanisms of eyeless during Drosophila eye development. - Yeung, Kelvin; Wang, Feng; Yumei Li; Wang, Keqing; Mardon, Graeme; Rui Chen (Nucleic Acids Res, 2018)
Eyeless (ey) is one of the most critical transcription factors for initiating the entire eye development in Drosophila. However, the molecular mechanisms through which Ey regulates target genes and pathways have not been characterized at the genomic level. Using ChIP-Seq, we generated an endogenous Ey-binding profile in Drosophila developing eyes. We found that Ey binding occurred more frequently at promoter compared to non-promoter regions. Ey promoter binding was correlated with the active transcription of genes involved in development and transcription regulation. An integrative analysis revealed that Ey directly regulated a broad and highly connected genetic network, including many essential patterning pathways, and known and novel eye genes. Interestingly, we observed that Ey could target multiple components of the same pathway, which might enhance its control of these pathways during eye development. In addition to protein-coding genes, we discovered Ey also targeted non-coding RNAs, which represents a new regulatory mechanism employed by Ey. These findings suggest that Ey could use multiple molecular mechanisms to regulate target gene expression and pathway function, which might enable Ey to exhibit a greater flexibility in controlling different processes during eye development.
Keywords: Animals; Body Patterning; Cell Lineage; Compound Eye, Arthropod; DNA-Binding Proteins; Drosophila melanogaster; Drosophila Proteins; Enhancer Elements, Genetic; Gene Expression Regulation, Developmental; Genomics; Photoreceptor Cells, Invertebrate; Promoter Regions, Genetic; RNA, Untranslated

MLH1-rheMac hereditary nonpolyposis colorectal cancer syndrome in rhesus macaques. - Brammer, David W; Gillespie, Patrick J; Tian, Mei; Young, Daniel; Raveendran, Muthuswamy; Williams, Lawrence E; Gagea, Mihai; Benavides, Fernando J; Perez, Carlos J; Broaddus, Russell R; Bernacky, Bruce J; Barnhart, Kirstin F; et al. (Proc Natl Acad Sci U S A, 2018)
Over the past two decades, 33 cases of colonic adenocarcinomas have been diagnosed in rhesus macaques () at the nonhuman primate colony of the Keeling Center for Comparative Medicine and Research at The University of Texas MD Anderson Cancer Center. The distinctive feature in these cases, based on PET/computed tomography (CT) imaging, was the presence of two or three tumor lesions in different locations, including proximal to the ileocecal juncture, proximal to the hepatic flexure, and/or in the sigmoid colon. These colon carcinoma lesions selectively accumulated [F]fluorodeoxyglucose ([F]FDG) and [F]fluoroacetate ([F]FACE) at high levels, reflecting elevated carbohydrate and fatty acid metabolism in these tumors. In contrast, the accumulation of [F]fluorothymidine ([F]FLT) was less significant, reflecting slow proliferative activity in these tumors. The diagnoses of colon carcinomas were confirmed by endoscopy. The expression of MLH1, MSH2, and MSH6 proteins and the degree of microsatellite instability (MSI) was assessed in colon carcinomas. The loss of MLH1 protein expression was observed in all tumors and was associated with a deletion mutation in the promoter region and/or multiple single-nucleotide polymorphism (SNP) mutations in the gene. All tumors exhibited various degrees of MSI. The pedigree analysis of this rhesus macaque population revealed several clusters of affected animals related to each other over several generations, suggesting an autosomal dominant transmission of susceptibility for colon cancer. The newly discovered hereditary nonpolyposis colorectal cancer syndrome in rhesus macaques, termed -rheMac, may serve as a model for development of novel approaches to diagnosis and therapy of Lynch syndrome in humans.
Keywords: Animals; Colorectal Neoplasms, Hereditary Nonpolyposis; Female; Macaca mulatta; Male; Microsatellite Instability; MutL Protein Homolog 1; Polymorphism, Single Nucleotide; Positron Emission Tomography Computed Tomography; Primate Diseases

Mutation in the intracellular chloride channel CLCC1 associated with autosomal recessive retinitis pigmentosa. - Li, Lin; Jiao, Xiaodong; D'Atri, Ilaria; Ono, Fumihito; Nelson, Ralph; Chan, Chi-Chao; Nakaya, Naoki; Ma, Zhiwei; Ma, Yan; Cai, Xiaoying; Zhang, Longhua; Lin, Siying; et al. (PLoS Genet, 2018)
We identified a homozygous missense alteration (c.75C>A, p.D25E) in CLCC1, encoding a presumptive intracellular chloride channel highly expressed in the retina, associated with autosomal recessive retinitis pigmentosa (arRP) in eight consanguineous families of Pakistani descent. The p.D25E alteration decreased CLCC1 channel function accompanied by accumulation of mutant protein in granules within the ER lumen, while siRNA knockdown of CLCC1 mRNA induced apoptosis in cultured ARPE-19 cells. TALEN KO in zebrafish was lethal 11 days post fertilization. The depressed electroretinogram (ERG) cone response and cone spectral sensitivity of 5 dpf KO zebrafish and reduced eye size, retinal thickness, and expression of rod and cone opsins could be rescued by injection of wild type CLCC1 mRNA. Clcc1+/- KO mice showed decreased ERGs and photoreceptor number. Together these results strongly suggest that intracellular chloride transport by CLCC1 is a critical process in maintaining retinal integrity, and CLCC1 is crucial for survival and function of retinal cells.
Keywords: Animals; Asian People; Cell Line; Chloride Channels; Cytoplasm; Eye Proteins; HEK293 Cells; Homozygote; Humans; Mice; Mice, Knockout; Mutation, Missense; Pakistan; Retina; Retinal Cone Photoreceptor Cells; Retinal Rod Photoreceptor Cells; Retinitis Pigmentosa; Zebrafish

Mutations in the mitochondrial ribosomal protein MRPS22 lead to primary ovarian insufficiency. - Chen, Anlu; Tiosano, Dov; Guran, Tulay; Baris, Hagit N; Bayram, Yavuz; Mory, Adi; Shapiro-Kulnane, Laura; Hodges, Craig A; Akdemir, Zeynep C; Turan, Serap; Jhangiani, Shalini N; van den Akker, Focco; et al. (Hum Mol Genet, 2018)
Primary ovarian insufficiency (POI) is characterized by amenorrhea and loss or dysfunction of ovarian follicles prior to the age of 40. POI has been associated with autosomal recessive mutations in genes involving hormonal signaling and folliculogenesis, however, the genetic etiology of POI most often remains unknown. Here we report MRPS22 homozygous missense variants c.404G>A (p.R135Q) and c.605G>A (p.R202H) identified in four females from two independent consanguineous families as a novel genetic cause of POI in adolescents. Both missense mutations identified in MRPS22 are rare, occurred in highly evolutionarily conserved residues, and are predicted to be deleterious to protein function. In contrast to prior reports of mutations in MRPS22 associated with severe mitochondrial disease, the POI phenotype is far less severe. Consistent with this genotype-phenotype correlation, mitochondrial defects in oxidative phosphorylation or rRNA levels were not detected in fibroblasts derived from the POI patients, suggesting a non-bioenergetic or tissue-specific mitochondrial defect. Furthermore, we demonstrate in a Drosophila model that mRpS22 deficiency specifically in somatic cells of the ovary had no effect on fertility, whereas flies with mRpS22 deficiency specifically in germ cells were infertile and agametic, demonstrating a cell autonomous requirement for mRpS22 in germ cell development. These findings collectively identify that MRPS22, a component of the small mitochondrial ribosome subunit, is critical for ovarian development and may therefore provide insight into the pathophysiology and treatment of ovarian dysfunction.
Keywords: Adolescent; Adult; Amenorrhea; Animals; Disease Models, Animal; Drosophila; Drosophila Proteins; Female; Fertility; Homozygote; Humans; Menopause, Premature; Mitochondrial Proteins; Mutation, Missense; Ovarian Follicle; Primary Ovarian Insufficiency; Ribosomal Proteins; Young Adult

NMNAT1 E257K variant, associated with Leber Congenital Amaurosis (LCA9), causes a mild retinal degeneration phenotype. - Eblimit, Aiden; Zaneveld, Smriti Agrawal; Liu, Wei; Thomas, Kandace; Wang, Keqing; Yumei Li; Mardon, Graeme; Rui Chen (Exp Eye Res, 2018)
NMNAT1 (nicotinamide mononucleotide adenylyltransferase 1) encodes a rate-limiting enzyme that catalyzes the biosynthesis of NAD and plays a role in neuroprotection. Mutations in NMNAT1 have been identified to cause a recessive, non-syndromic early form of blindness genetically defined as Leber Congenital Amaurosis 9 (LCA9). One of the most common alleles reported so far in NMNAT1 is the c.769G > A (E257K) missense mutation, which occurs in 70% of all LCA9 cases. However, given its relatively high population frequency and the observation of individuals with homozygous E257K variant without phenotype, the pathogenicity of this allele has been questioned. To address this issue, we have studied the pathogenic effects of this allele by generating a knock-in mouse model. Interestingly, no obvious morphological or functional defects are observed in Nmnat1 E257K homozygous mice up to one year old, even after light-damage. Together with the previous clinical reports, we propose that the E257K allele is a weak hypomorphic allele that has significantly reduced penetrance in the homozygous state. In contrast, compound heterozygous Nmnat1 mice exhibit photoreceptor defects which are exacerbated upon exposure to light. Furthermore, retina tissue- specific Nmnat1 conditional knockout mice exhibit photoreceptor degeneration before the retina has terminally differentiated. These findings suggest that NMNAT1 plays an important role in photoreceptors and is likely involved in both retinal development and maintenance of photoreceptor integrity.
Keywords: Alleles; Animals; Electroretinography; Exons; Female; Gene Knock-In Techniques; Genetic Variation; Leber Congenital Amaurosis; Light; Male; Mice; Mice, Knockout; Mice, Mutant Strains; Nicotinamide-Nucleotide Adenylyltransferase; Phenotype; Point Mutation; Radiation Injuries, Experimental; Retina; Retinal Degeneration

Piercing the dark matter: bioinformatics of long-range sequencing and mapping. - Fritz J Sedlazeck; Lee, Hayan; Darby, Charlotte A; Schatz, Michael C (Nat Rev Genet, 2018)
Several new genomics technologies have become available that offer long-read sequencing or long-range mapping with higher throughput and higher resolution analysis than ever before. These long-range technologies are rapidly advancing the field with improved reference genomes, more comprehensive variant identification and more complete views of transcriptomes and epigenomes. However, they also require new bioinformatics approaches to take full advantage of their unique characteristics while overcoming their complex errors and modalities. Here, we discuss several of the most important applications of the new technologies, focusing on both the currently available bioinformatics tools and opportunities for future research.
Keywords: Animals; Chromosome Mapping; Computational Biology; Gene Expression Profiling; Genomics; High-Throughput Nucleotide Sequencing; Humans; Transcriptome

POU6f1 Mediates Neuropeptide-Dependent Plasticity in the Adult Brain. - McClard, Cynthia K; Kochukov, Mikhail Y; Herman, Isabella; Liu, Zhandong; Eblimit, Aiden; Moayedi, Yalda; Ortiz-Guzman, Joshua; Colchado, Daniel; Pekarek, Brandon; Panneerselvam, Sugi; Mardon, Graeme; Arenkiel, Benjamin R (J Neurosci, 2018)
The mouse olfactory bulb (OB) features continued, activity-dependent integration of adult-born neurons, providing a robust model with which to examine mechanisms of plasticity in the adult brain. We previously reported that local OB interneurons secrete the neuropeptide corticotropin-releasing hormone (CRH) in an activity-dependent manner onto adult-born granule neurons and that local CRH signaling promotes expression of synaptic machinery in the bulb. This effect is mediated via activation of the CRH receptor 1 (), which is developmentally regulated during adult-born neuron maturation. CRHR1 is a G-protein-coupled receptor that activates CREB-dependent transcription in the presence of CRH. Therefore, we hypothesized that locally secreted CRH activates CRHR1 to initiate circuit plasticity programs. To identify such programs, we profiled gene expression changes associated with CRHR1 activity in adult-born neurons of the OB. Here, we show that CRHR1 activity influences expression of the brain-specific Homeobox-containing transcription factor POU Class 6 Homeobox 1 (). To elucidate the contributions of toward activity-dependent circuit remodeling, we targeted CRHR1 neurons in male and female mice for cell-type-specific manipulation of expression. Whereas loss of in CRHR1 neurons resulted in reduced dendritic complexity and decreased synaptic connectivity, overexpression of in CRHR1 neurons promoted dendritic outgrowth and branching and influenced synaptic function. Together, these findings suggest that the transcriptional program directed by downstream of local CRH signaling in adult-born neurons influences circuit dynamics in response to activity-dependent peptide signaling in the adult brain. Elucidating mechanisms of plasticity in the adult brain is helpful for devising strategies to understand and treat neurodegeneration. Circuit plasticity in the adult mouse olfactory bulb is exemplified by both continued cell integration and synaptogenesis. We previously reported that these processes are influenced by local neuropeptide signaling in an activity-dependent manner. Here, we show that local corticotropin-releasing hormone (CRH) signaling induces dynamic gene expression changes in CRH receptor expressing adult-born neurons, including altered expression of the transcription factor We further show that is necessary for proper dendrite specification and patterning, as well as synapse development and function in adult-born neurons. Together, these findings reveal a novel mechanism by which peptide signaling modulates adult brain circuit plasticity.
Keywords: Animals; Behavior, Animal; Brain; Corticotropin-Releasing Hormone; Female; Gene Knock-In Techniques; Male; Mice; Mice, Knockout; Neuronal Plasticity; Neurons; Neuropeptides; Octamer Transcription Factor-3; Olfactory Bulb; Receptors, Corticotropin-Releasing Hormone; Smell

Pro-inflammation Associated with a Gain-of-Function Mutation (R284S) in the Innate Immune Sensor STING. - Konno, Hiroyasu; Chinn, Ivan K; Hong, Diana; Orange, Jordan S; Lupski, James R; Mendoza, Alejandra; Pedroza, Luis A; Barber, Glen N (Cell Rep, 2018)
The cellular sensor stimulator of interferon genes (STING) initiates type I interferon (IFN) and cytokine production following association with cyclic dinucleotides (CDNs) generated from intracellular bacteria or via a cellular synthase, cGAS, after binding microbial or self-DNA. Although essential for protecting the host against infection, unscheduled STING signaling is now known to be responsible for a variety of autoinflammatory disorders. Here, we report a gain-of-function mutation in STING (R284S), isolated from a patient who did not require CDNs to augment activity and who manifested a constitutively active phenotype. Control of the Unc-51-like autophagy activating kinase 1 (ULK1) pathway, which has previously been shown to influence STING function, was potently able to suppress STING (R284S) activity to alleviate cytokine production. Our findings add to the growing list of inflammatory syndromes associated with spontaneous STING signaling and provide a therapeutic strategy for the treatment of STING-induced inflammatory disease.
Keywords: Animals; Autophagy; Autophagy-Related Protein-1 Homolog; Gain of Function Mutation; HEK293 Cells; Humans; Inflammation; Intracellular Signaling Peptides and Proteins; Membrane Proteins; Mice; Mice, Knockout

Protein-altering variants associated with body mass index implicate pathways that control energy intake and expenditure in obesity. - Turcot, Valérie; Lu, Yingchang; Highland, Heather M; Schurmann, Claudia; Justice, Anne E; Fine, Rebecca S; Bradfield, Jonathan P; Esko, Tõnu; Giri, Ayush; Graff, Mariaelisa; Guo, Xiuqing; Hendricks, Audrey E; et al. (Nat Genet, 2018)
Genome-wide association studies (GWAS) have identified >250 loci for body mass index (BMI), implicating pathways related to neuronal biology. Most GWAS loci represent clusters of common, noncoding variants from which pinpointing causal genes remains challenging. Here we combined data from 718,734 individuals to discover rare and low-frequency (minor allele frequency (MAF) < 5%) coding variants associated with BMI. We identified 14 coding variants in 13 genes, of which 8 variants were in genes (ZBTB7B, ACHE, RAPGEF3, RAB21, ZFHX3, ENTPD6, ZFR2 and ZNF169) newly implicated in human obesity, 2 variants were in genes (MC4R and KSR2) previously observed to be mutated in extreme obesity and 2 variants were in GIPR. The effect sizes of rare variants are ~10 times larger than those of common variants, with the largest effect observed in carriers of an MC4R mutation introducing a stop codon (p.Tyr35Ter, MAF = 0.01%), who weighed ~7 kg more than non-carriers. Pathway analyses based on the variants associated with BMI confirm enrichment of neuronal genes and provide new evidence for adipocyte and energy expenditure biology, widening the potential of genetically supported therapeutic targets in obesity.
Keywords: Adult; Animals; Body Mass Index; Drosophila; Energy Intake; Energy Metabolism; Female; Gene Frequency; Genetic Variation; Humans; Male; Obesity; Proteins; Syndrome

Reproductive Longevity Predicts Mutation Rates in Primates. - Thomas, Gregg W C; Wang, Richard J; Puri, Arthi; R. Alan Harris; Raveendran, Muthuswamy; Hughes, Daniel S T; Murali, Shwetha C; Williams, Lawrence E; Harshavardhan Doddapaneni; Donna M Muzny; Richard A Gibbs; Abee, Christian R; et al. (Curr Biol, 2018)
Mutation rates vary between species across several orders of magnitude, with larger organisms having the highest per-generation mutation rates. Hypotheses for this pattern typically invoke physiological or population-genetic constraints imposed on the molecular machinery preventing mutations [1]. However, continuing germline cell division in multicellular eukaryotes means that organisms with longer generation times and of larger size will leave more mutations to their offspring simply as a byproduct of their increased lifespan [2, 3]. Here, we deeply sequence the genomes of 30 owl monkeys (Aotus nancymaae) from six multi-generation pedigrees to demonstrate that paternal age is the major factor determining the number of de novo mutations in this species. We find that owl monkeys have an average mutation rate of 0.81 × 10 per site per generation, roughly 32% lower than the estimate in humans. Based on a simple model of reproductive longevity that does not require any changes to the mutational machinery, we show that this is the expected mutation rate in owl monkeys. We further demonstrate that our model predicts species-specific mutation rates in other primates, including study-specific mutation rates in humans based on the average paternal age. Our results suggest that variation in life history traits alone can explain variation in the per-generation mutation rate among primates, and perhaps among a wide range of multicellular organisms.
Keywords: Animals; Aotidae; Genetic Fitness; Genetics, Population; Genome; Humans; Longevity; Mutation; Mutation Rate; Pedigree; Population Density; Primates; Reproduction

The role of FREM2 and FRAS1 in the development of congenital diaphragmatic hernia. - Jordan, Valerie K; Beck, Tyler F; Hernandez-Garcia, Andres; Kundert, Peter N; Kim, Bum-Jun; Jhangiani, Shalini N; Gambin, Tomasz; Starkovich, Molly; Punetha, Jaya; Paine, Ingrid S; Posey, Jennifer E; Li, Alexander H; et al. (Hum Mol Genet, 2018)
Congenital diaphragmatic hernia (CDH) has been reported twice in individuals with a clinical diagnosis of Fraser syndrome, a genetic disorder that can be caused by recessive mutations affecting FREM2 and FRAS1. In the extracellular matrix, FREM2 and FRAS1 form a self-stabilizing complex with FREM1, a protein whose deficiency causes sac CDH in humans and mice. By sequencing FREM2 and FRAS1 in a CDH cohort, and searching online databases, we identified five individuals who carried recessive or double heterozygous, putatively deleterious variants in these genes which may represent susceptibility alleles. Three of these alleles were significantly enriched in our CDH cohort compared with ethnically matched controls. We subsequently demonstrated that 8% of Frem2ne/ne and 1% of Fras1Q1263*/Q1263* mice develop the same type of anterior sac CDH seen in FREM1-deficient mice. We went on to show that development of sac hernias in FREM1-deficient mice is preceded by failure of anterior mesothelial fold progression resulting in the persistence of an amuscular, poorly vascularized anterior diaphragm that is abnormally adherent to the underlying liver. Herniation occurs in the perinatal period when the expanding liver protrudes through this amuscular region of the anterior diaphragm that is juxtaposed to areas of muscular diaphragm. Based on these data, we conclude that deficiency of FREM2, and possibly FRAS1, are associated with an increased risk of developing CDH and that loss of the FREM1/FREM2/FRAS1 complex, or its function, leads to anterior sac CDH development through its effects on mesothelial fold progression.
Keywords: Animals; Child; Child, Preschool; Epithelium; Extracellular Matrix Proteins; Female; Hernias, Diaphragmatic, Congenital; Humans; Infant; Infant, Newborn; Male; Mice; Mice, Knockout; Mutation; Pregnancy; Receptors, Interleukin

Sheep genome functional annotation reveals proximal regulatory elements contributed to the evolution of modern breeds. - Naval-Sanchez, Marina; Nguyen, Quan; McWilliam, Sean; Porto-Neto, Laercio R; Tellam, Ross; Vuocolo, Tony; Reverter, Antonio; Perez-Enciso, Miguel; Brauning, Rudiger; Clarke, Shannon; McCulloch, Alan; Zamani, Wahid; et al. (Nat Commun, 2018)
Domestication fundamentally reshaped animal morphology, physiology and behaviour, offering the opportunity to investigate the molecular processes driving evolutionary change. Here we assess sheep domestication and artificial selection by comparing genome sequence from 43 modern breeds (Ovis aries) and their Asian mouflon ancestor (O. orientalis) to identify selection sweeps. Next, we provide a comparative functional annotation of the sheep genome, validated using experimental ChIP-Seq of sheep tissue. Using these annotations, we evaluate the impact of selection and domestication on regulatory sequences and find that sweeps are significantly enriched for protein coding genes, proximal regulatory elements of genes and genome features associated with active transcription. Finally, we find individual sites displaying strong allele frequency divergence are enriched for the same regulatory features. Our data demonstrate that remodelling of gene expression is likely to have been one of the evolutionary forces that drove phenotypic diversification of this common livestock species.
Keywords: Animals; Breeding; Evolution, Molecular; Female; Gene Frequency; Genome; Male; Molecular Sequence Annotation; Phylogeny; Regulatory Elements, Transcriptional; Sheep

Sooty mangabey genome sequence provides insight into AIDS resistance in a natural SIV host. - Palesch, David; Bosinger, Steven E; Tharp, Gregory K; Vanderford, Thomas H; Paiardini, Mirko; Chahroudi, Ann; Johnson, Zachary P; Kirchhoff, Frank; Hahn, Beatrice H; Norgren, Robert B; Patel, Nirav B; Sodora, Donald L; et al. (Nature, 2018)
In contrast to infections with human immunodeficiency virus (HIV) in humans and simian immunodeficiency virus (SIV) in macaques, SIV infection of a natural host, sooty mangabeys (Cercocebus atys), is non-pathogenic despite high viraemia. Here we sequenced and assembled the genome of a captive sooty mangabey. We conducted genome-wide comparative analyses of transcript assemblies from C. atys and AIDS-susceptible species, such as humans and macaques, to identify candidates for host genetic factors that influence susceptibility. We identified several immune-related genes in the genome of C. atys that show substantial sequence divergence from macaques or humans. One of these sequence divergences, a C-terminal frameshift in the toll-like receptor-4 (TLR4) gene of C. atys, is associated with a blunted in vitro response to TLR-4 ligands. In addition, we found a major structural change in exons 3-4 of the immune-regulatory protein intercellular adhesion molecule 2 (ICAM-2); expression of this variant leads to reduced cell surface expression of ICAM-2. These data provide a resource for comparative genomic studies of HIV and/or SIV pathogenesis and may help to elucidate the mechanisms by which SIV-infected sooty mangabeys avoid AIDS.
Keywords: Acquired Immunodeficiency Syndrome; Amino Acid Sequence; Animals; Cell Adhesion Molecules; Cercocebus atys; Exons; Female; Frameshift Mutation; Genetic Predisposition to Disease; Genetic Variation; Genome; Genomics; HIV; Host Specificity; Humans; Macaca; Sequence Deletion; Simian Acquired Immunodeficiency Syndrome; Simian Immunodeficiency Virus; Species Specificity; Toll-Like Receptor 4; Transcriptome; Whole Genome Sequencing

SPATA7 maintains a novel photoreceptor-specific zone in the distal connecting cilium. - Dharmat, Rachayata; Eblimit, Aiden; Robichaux, Michael A; Zhang, Zhixian; Nguyen, Thanh-Minh T; Jung, Sung Yun; He, Feng; Jain, Antrix; Yumei Li; Qin, Jun; Overbeek, Paul; Roepman, Ronald; et al. (J Cell Biol, 2018)
Photoreceptor-specific ciliopathies often affect a structure that is considered functionally homologous to the ciliary transition zone (TZ) called the connecting cilium (CC). However, it is unclear how mutations in certain ciliary genes disrupt the photoreceptor CC without impacting the primary cilia systemically. By applying stochastic optical reconstruction microscopy technology in different genetic models, we show that the CC can be partitioned into two regions: the proximal CC (PCC), which is homologous to the TZ of primary cilia, and the distal CC (DCC), a photoreceptor-specific extension of the ciliary TZ. This specialized distal zone of the CC in photoreceptors is maintained by SPATA7, which interacts with other photoreceptor-specific ciliary proteins such as RPGR and RPGRIP1. The absence of results in the mislocalization of DCC proteins without affecting the PCC protein complexes. This collapse results in destabilization of the axonemal microtubules, which consequently results in photoreceptor degeneration. These data provide a novel mechanism to explain how genetic disruption of ubiquitously present ciliary proteins exerts tissue-specific ciliopathy phenotypes.
Keywords: Adaptor Proteins, Signal Transducing; Animals; Antigens, Neoplasm; Carrier Proteins; Cell Cycle Proteins; Cytoskeletal Proteins; DNA-Binding Proteins; Eye Proteins; Mice; Mice, Inbred C57BL; Nuclear Proteins; Photoreceptor Connecting Cilium; Protein Transport

Spontaneous Spongiform Brainstem Degeneration in a Young Mouse Lemur () with Conspicuous Behavioral, Motor, Growth, and Ocular Pathologies. - Schmidtke, Daniel; Lempp, Charlotte; Dubicanac, Marko; Radespiel, Ute; Zimmermann, Elke; Baumgärtner, Wolfgang; Kästner, Sabine; Meier, Martin; Balkema-Buschmann, Anne; R. Alan Harris; Raveendran, Muthuswamy; Donna M Muzny; et al. (Comp Med, 2018)
Here we report a case of severe growth retardation and neurologic abnormalities in a female gray mouse lemur (), a small NHP species for which the genomic sequence recently became available. The female lemur we present here died on postnatal day 125. This lemur had impaired development of motor skills and showed severe ataxia and tremors. In addition, hearing seemed normal whereas ophthalmic examination revealed incipient bilateral cataracts, abnormal pigmentation in the lens of the left eye, and a missing optokinetic nystagmus, which indicated impaired vision. Most prominently, the lemur showed severe growth retardation. Necropsy revealed maldevelopment of the left reproductive organs and unilateral dilation of the right lateral ventricle, which was confirmed on brain MRI. Brain histology further revealed large, bilateral areas of vacuolation within the brainstem, but immunohistochemistry indicated no sign of pathologic prion protein deposition. Full genomic sequencing of the lemur revealed a probably pathologic mutation in of the LARGE gene family, which has been associated with congenital muscular dystrophies. However, potentially functional mutations in other genes were also present. The observed behavioral and motor signs in the presented animal might have been linked to spongiform degeneration and resulting brainstem dysfunction and progressive muscle weakness. The macroscopic developmental abnormalities and ophthalmic findings might be genetic in origin and linked to the mutation in .
Keywords: Animals; Behavior, Animal; Brain Stem; Cheirogaleidae; Eye; Female; Growth Disorders; Neurodegenerative Diseases; Primate Diseases; Walker-Warburg Syndrome

SYT1-associated neurodevelopmental disorder: a case series. - Baker, Kate; Gordon, Sarah L; Melland, Holly; Bumbak, Fabian; Scott, Daniel J; Jiang, Tess J; Owen, David; Turner, Bradley J; Boyd, Stewart G; Rossi, Mari; Al-Raqad, Mohammed; Elpeleg, Orly; et al. (Brain, 2018)
Synaptotagmin 1 (SYT1) is a critical mediator of fast, synchronous, calcium-dependent neurotransmitter release and also modulates synaptic vesicle endocytosis. This paper describes 11 patients with de novo heterozygous missense mutations in SYT1. All mutations alter highly conserved residues, and cluster in two regions of the SYT1 C2B domain at positions Met303 (M303K), Asp304 (D304G), Asp366 (D366E), Ile368 (I368T) and Asn371 (N371K). Phenotypic features include infantile hypotonia, congenital ophthalmic abnormalities, childhood-onset hyperkinetic movement disorders, motor stereotypies, and developmental delay varying in severity from moderate to profound. Behavioural characteristics include sleep disturbance and episodic agitation. Absence of epileptic seizures and normal orbitofrontal head circumference are important negative features. Structural MRI is unremarkable but EEG disturbance is universal, characterized by intermittent low frequency high amplitude oscillations. The functional impact of these five de novo SYT1 mutations has been assessed by expressing rat SYT1 protein containing the equivalent human variants in wild-type mouse primary hippocampal cultures. All mutant forms of SYT1 were expressed at levels approximately equal to endogenous wild-type protein, and correctly localized to nerve terminals at rest, except for SYT1M303K, which was expressed at a lower level and failed to localize at nerve terminals. Following stimulation, SYT1I368T and SYT1N371K relocalized to nerve terminals at least as efficiently as wild-type SYT1. However, SYT1D304G and SYT1D366E failed to relocalize to nerve terminals following stimulation, indicative of impairments in endocytic retrieval and trafficking of SYT1. In addition, the presence of SYT1 variants at nerve terminals induced a slowing of exocytic rate following sustained action potential stimulation. The extent of disturbance to synaptic vesicle kinetics is mirrored by the severity of the affected individuals' phenotypes, suggesting that the efficiency of SYT1-mediated neurotransmitter release is critical to cognitive development. In summary, de novo dominant SYT1 missense mutations are associated with a recognizable neurodevelopmental syndrome, and further cases can now be diagnosed based on clinical features, electrophysiological signature and mutation characteristics. Variation in phenotype severity may reflect mutation-specific impact on the diverse physiological functions of SYT1.
Keywords: Action Potentials; Adolescent; Animals; Calcium; Child; Child, Preschool; Electrophysiological Phenomena; Endocytosis; Female; Humans; Intellectual Disability; Male; Mice; Mice, Inbred C57BL; Movement Disorders; Mutation, Missense; Neurodevelopmental Disorders; Neurons; Rats; Synaptic Transmission; Synaptic Vesicles; Synaptotagmin I; Young Adult

Temporal development of the gut microbiome in early childhood from the TEDDY study. - Stewart, Christopher J; Ajami, Nadim J; O'Brien, Jacqueline L; Hutchinson, Diane S; Smith, Daniel P; Wong, Matthew C; Ross, Matthew C; Lloyd, Richard E; Harshavardhan Doddapaneni; Ginger A Metcalf; Donna M Muzny; Richard A Gibbs; et al. (Nature, 2018)
The development of the microbiome from infancy to childhood is dependent on a range of factors, with microbial-immune crosstalk during this time thought to be involved in the pathobiology of later life diseases such as persistent islet autoimmunity and type 1 diabetes. However, to our knowledge, no studies have performed extensive characterization of the microbiome in early life in a large, multi-centre population. Here we analyse longitudinal stool samples from 903 children between 3 and 46 months of age by 16S rRNA gene sequencing (n = 12,005) and metagenomic sequencing (n = 10,867), as part of the The Environmental Determinants of Diabetes in the Young (TEDDY) study. We show that the developing gut microbiome undergoes three distinct phases of microbiome progression: a developmental phase (months 3-14), a transitional phase (months 15-30), and a stable phase (months 31-46). Receipt of breast milk, either exclusive or partial, was the most significant factor associated with the microbiome structure. Breastfeeding was associated with higher levels of Bifidobacterium species (B. breve and B. bifidum), and the cessation of breast milk resulted in faster maturation of the gut microbiome, as marked by the phylum Firmicutes. Birth mode was also significantly associated with the microbiome during the developmental phase, driven by higher levels of Bacteroides species (particularly B. fragilis) in infants delivered vaginally. Bacteroides was also associated with increased gut diversity and faster maturation, regardless of the birth mode. Environmental factors including geographical location and household exposures (such as siblings and furry pets) also represented important covariates. A nested case-control analysis revealed subtle associations between microbial taxonomy and the development of islet autoimmunity or type 1 diabetes. These data determine the structural and functional assembly of the microbiome in early life and provide a foundation for targeted mechanistic investigation into the consequences of microbial-immune crosstalk for long-term health.
Keywords: Adolescent; Animals; Bifidobacterium; Breast Feeding; Case-Control Studies; Child; Child, Preschool; Cluster Analysis; Datasets as Topic; Diabetes Mellitus, Type 1; Female; Firmicutes; Gastrointestinal Microbiome; Humans; Infant; Male; Milk, Human; Pets; RNA, Ribosomal, 16S; Siblings; Surveys and Questionnaires; Time Factors

The Toxicogenome of Hyalella azteca: A Model for Sediment Ecotoxicology and Evolutionary Toxicology. - Poynton, Helen C; Hasenbein, Simone; Benoit, Joshua B; Sepulveda, Maria S; Poelchau, Monica F; Hughes, Daniel S T; Murali, Shwetha C; Chen, Shuai; Glastad, Karl M; Goodisman, Michael A D; Werren, John H; Vineis, Joseph H; et al. (Environ Sci Technol, 2018)
Hyalella azteca is a cryptic species complex of epibenthic amphipods of interest to ecotoxicology and evolutionary biology. It is the primary crustacean used in North America for sediment toxicity testing and an emerging model for molecular ecotoxicology. To provide molecular resources for sediment quality assessments and evolutionary studies, we sequenced, assembled, and annotated the genome of the H. azteca U.S. Lab Strain. The genome quality and completeness is comparable with other ecotoxicological model species. Through targeted investigation and use of gene expression data sets of H. azteca exposed to pesticides, metals, and other emerging contaminants, we annotated and characterized the major gene families involved in sequestration, detoxification, oxidative stress, and toxicant response. Our results revealed gene loss related to light sensing, but a large expansion in chemoreceptors, likely underlying sensory shifts necessary in their low light habitats. Gene family expansions were also noted for cytochrome P450 genes, cuticle proteins, ion transporters, and include recent gene duplications in the metal sequestration protein, metallothionein. Mapping of differentially expressed transcripts to the genome significantly increased the ability to functionally annotate toxicant responsive genes. The H. azteca genome will greatly facilitate development of genomic tools for environmental assessments and promote an understanding of how evolution shapes toxicological pathways with implications for environmental and human health.
Keywords: Amphipoda; Animals; Ecotoxicology; Geologic Sediments; North America; Toxicity Tests; Water Pollutants, Chemical

Whole-exome sequencing revealed HKDC1 as a candidate gene associated with autosomal-recessive retinitis pigmentosa. - Zhang, Lin; Sun, Zixi; Zhao, Peiquan; Huang, Lulin; Xu, Mingchu; Yang, Yeming; Chen, Xue; Lu, Fang; Zhang, Xiang; Wang, Hui; Zhang, Shanshan; Liu, Wenjing; et al. (Hum Mol Genet, 2018)
Retinitis pigmentosa (RP) is an inheritable retina degenerative disease leading to blindness. Despite the identification of 70 genes associated with RP, the genetic cause of ∼40% of RP patients remains to be elucidated. Whole-exome sequencing was applied on the probands of a RP cohort of 68 unsolved cases to identify candidate genetic mutations. A homozygous missense variant (c.173C > T, p.T58 M) was found in HKDC1 in two unrelated families presenting late-onset retinal degeneration. This variant affects highly conserved amino acid residue and is very rare in several databases and absent in 4000 ethnic-matched controls. Mutant HKDC1 protein partially lost hexokinase activity. Hkdc1 is expressed in the mouse retina and localized to photoreceptor inner segments. To elucidate the in vivo roles of Hkdc1 in the retina, we generated Hkdc1 knockout (KO) mouse models using CRISPR/Cas9 technique. Two independent alleles were identified and backcrossed to C57BL/6 J for 6 generations. Absence of HKDC1 expression in the Hkdc1 KO retina was confirmed by western blot and immunostaning using HKDC1 antibody. Hkdc1 KO mice exhibited reduced scotopic electroretinogram response and thinner outer nuclear layer, similar to some of the human patient phenotypes. Loss of Hkdc1 led to mislocalization of rhodopsin to the inner segments and cell bodies of rods in some regions in the retina. Taken together, our data demonstrated that HKDC1 is associated with autosomal recessively inherited RP.
Keywords: Animals; Disease Models, Animal; Exome; Exome Sequencing; Female; Genetic Association Studies; Hexokinase; Homozygote; Humans; Male; Mice, Knockout; Mutation; Pedigree; Retina; Retinal Degeneration; Retinitis Pigmentosa

Alu Insertion Polymorphisms as Evidence for Population Structure in Baboons. - Steely, Cody J; Walker, Jerilyn A; Jordan, Vallmer E; Beckstrom, Thomas O; McDaniel, Cullen L; St Romain, Corey P; Bennett, Emily C; Robichaux, Arianna; Clement, Brooke N; Raveendran, Muthuswamy; Worley, Kim C; Phillips-Conroy, Jane; et al. (Genome Biol Evol, 2017)
Male dispersal from the natal group at or near maturity is a feature of most baboon (Papio) species. It potentially has profound effects upon population structure and evolutionary processes, but dispersal, especially for unusually long distances, is not readily documented by direct field observation. In this pilot study, we investigate the possibility of retrieving baboon population structure in yellow (Papio cynocephalus) and kinda (Papio kindae) baboons from the distribution of variation in a genome-wide set of 494 Alu insertion polymorphisms, made available via the recently completed Baboon Genome Analysis Consortium. Alu insertion variation in a mixed population derived from yellow and olive (Papio anubis) baboons identified each individual's proportion of heritage from either parental species. In an unmixed yellow baboon population, our analysis showed greater similarity between neighboring than between more distantly situated groups, suggesting structuring of the population by male dispersal distance. Finally (and very provisionally), an unexpectedly sharp difference in Alu insertion frequencies between members of neighboring social groups of kinda baboons suggests that intergroup migration may be more rare than predicted in this little known species.
Keywords: Alu Elements; Animals; Evolution, Molecular; Female; Genome; Male; Papio; Phylogeny; Polymorphism, Genetic

ANGPTL3 Deficiency and Protection Against Coronary Artery Disease. - Stitziel, Nathan O; Khera, Amit V; Wang, Xiao; Bierhals, Andrew J; Vourakis, A Christina; Sperry, Alexandra E; Natarajan, Pradeep; Klarin, Derek; Emdin, Connor A; Zekavat, Seyedeh M; Nomura, Akihiro; Erdmann, Jeanette; et al. (J Am Coll Cardiol, 2017)
BACKGROUND: Familial combined hypolipidemia, a Mendelian condition characterized by substantial reductions in all 3 major lipid fractions, is caused by mutations that inactivate the gene angiopoietin-like 3 (ANGPTL3). Whether ANGPTL3 deficiency reduces risk of coronary artery disease (CAD) is unknown. OBJECTIVES: The study goal was to leverage 3 distinct lines of evidence-a family that included individuals with complete (compound heterozygote) ANGPTL3 deficiency, a population based-study of humans with partial (heterozygote) ANGPTL3 deficiency, and biomarker levels in patients with myocardial infarction (MI)-to test whether ANGPTL3 deficiency is associated with lower risk for CAD. METHODS: We assessed coronary atherosclerotic burden in 3 individuals with complete ANGPTL3 deficiency and 3 wild-type first-degree relatives using computed tomography angiography. In the population, ANGPTL3 loss-of-function (LOF) mutations were ascertained in up to 21,980 people with CAD and 158,200 control subjects. LOF mutations were defined as nonsense, frameshift, and splice-site variants, along with missense variants resulting in <25% of wild-type ANGPTL3 activity in a mouse model. In a biomarker study, circulating ANGPTL3 concentration was measured in 1,493 people who presented with MI and 3,232 control subjects. RESULTS: The 3 individuals with complete ANGPTL3 deficiency showed no evidence of coronary atherosclerotic plaque. ANGPTL3 gene sequencing demonstrated that approximately 1 in 309 people was a heterozygous carrier for an LOF mutation. Compared with those without mutation, heterozygous carriers of ANGPTL3 LOF mutations demonstrated a 17% reduction in circulating triglycerides and a 12% reduction in low-density lipoprotein cholesterol. Carrier status was associated with a 34% reduction in odds of CAD (odds ratio: 0.66; 95% confidence interval: 0.44 to 0.98; p = 0.04). Individuals in the lowest tertile of circulating ANGPTL3 concentrations, compared with the highest, had reduced odds of MI (adjusted odds ratio: 0.65; 95% confidence interval: 0.55 to 0.77; p < 0.001). CONCLUSIONS: ANGPTL3 deficiency is associated with protection from CAD.
Keywords: Adult; Angiopoietin-Like Protein 3; Angiopoietin-like Proteins; Angiopoietins; Animals; Atherosclerosis; Case-Control Studies; Coronary Artery Disease; Female; Humans; Lipids; Male; Mice, Inbred C57BL; Mice, Knockout; Middle Aged; Mutation, Missense; Myocardial Infarction; Risk Factors

Characterization of chromosomal abnormalities in pregnancy losses reveals critical genes and loci for human early development. - Chen, Yiyun; Bartanus, Justin; Liang, Desheng; Zhu, Hongmin; Breman, Amy M; Smith, Janice L; Wang, Hua; Ren, Zhilin; Patel, Ankita; Stankiewicz, Pawel; Cram, David S; Cheung, Sau Wai; et al. (Hum Mutat, 2017)
Detailed characterization of chromosomal abnormalities, a common cause for congenital abnormalities and pregnancy loss, is critical for elucidating genes for human fetal development. Here, 2,186 product-of-conception samples were tested for copy-number variations (CNVs) at two clinical diagnostic centers using whole-genome sequencing and high-resolution chromosomal microarray analysis. We developed a new gene discovery approach to predict potential developmental genes and identified 275 candidate genes from CNVs detected from both datasets. Based on Mouse Genome Informatics (MGI) and Zebrafish model organism database (ZFIN), 75% of identified genes could lead to developmental defects when mutated. Genes involved in embryonic development, gene transcription, and regulation of biological processes were significantly enriched. Especially, transcription factors and gene families sharing specific protein domains predominated, which included known developmental genes such as HOX, NKX homeodomain genes, and helix-loop-helix containing HAND2, NEUROG2, and NEUROD1 as well as potential novel developmental genes. We observed that developmental genes were denser in certain chromosomal regions, enabling identification of 31 potential genomic loci with clustered genes associated with development.
Keywords: Animals; Chromosome Aberrations; Chromosome Disorders; DNA Copy Number Variations; Embryonic Development; Female; Genome, Human; Humans; Mice; Microarray Analysis; Pregnancy; Transcription Factors; Zebrafish

Copy number increases of transposable elements and protein-coding genes in an invasive fish of hybrid origin. - Dennenmoser, Stefan; Fritz J Sedlazeck; Iwaszkiewicz, Elzbieta; Li, Xiang-Yi; Altmüller, Janine; Nolte, Arne W (Mol Ecol, 2017)
Evolutionary dynamics of structural genetic variation in lineages of hybrid origin is not well explored, although structural mutations may increase in controlled hybrid crosses. We therefore tested whether structural variants accumulate in a fish of recent hybrid origin, invasive Cottus, relative to both parental species Cottus rhenanus and Cottus perifretum. Copy-number variation in exons of 10,979 genes was assessed using comparative genome hybridization arrays. Twelve genes showed significantly higher copy numbers in invasive Cottus compared to both parents. This coincided with increased expression for three genes related to vision, detoxification and muscle development, suggesting possible gene dosage effects. Copy number increases of putative transposons were assessed by comparative mapping of genomic DNA reads against a de novo assembly of 1,005 repetitive elements. In contrast to exons, copy number increases of repetitive elements were common (20.7%) in invasive Cottus, whereas decrease was very rare (0.01%). Among the increased repetitive elements, 53.8% occurred at higher numbers in C. perifretum compared to C. rhenanus, while only 1.4% were more abundant in C. rhenanus. This implies a biased mutational process that amplifies genetic material from one ancestor. To assess the frequency of de novo mutations through hybridization, we screened 64 laboratory-bred F offspring between the parental species for copy-number changes at five candidate loci. We found no evidence for new structural variants, indicating that they are too rare to be detected given our sampling scheme. Instead, they must have accumulated over more generations than we observed in a controlled cross.
Keywords: Animals; Biological Evolution; DNA Copy Number Variations; DNA Transposable Elements; Hybridization, Genetic; Introduced Species; Perciformes

De Novo Disruption of the Proteasome Regulatory Subunit PSMD12 Causes a Syndromic Neurodevelopmental Disorder. - Küry, Sébastien; Besnard, Thomas; Ebstein, Frédéric; Khan, Tahir N; Gambin, Tomasz; Douglas, Jessica; Bacino, Carlos A; Craigen, William J; Sanders, Stephan J; Lehmann, Andrea; Latypova, Xénia; Khan, Kamal; et al. (Am J Hum Genet, 2017)
Degradation of proteins by the ubiquitin-proteasome system (UPS) is an essential biological process in the development of eukaryotic organisms. Dysregulation of this mechanism leads to numerous human neurodegenerative or neurodevelopmental disorders. Through a multi-center collaboration, we identified six de novo genomic deletions and four de novo point mutations involving PSMD12, encoding the non-ATPase subunit PSMD12 (aka RPN5) of the 19S regulator of 26S proteasome complex, in unrelated individuals with intellectual disability, congenital malformations, ophthalmologic anomalies, feeding difficulties, deafness, and subtle dysmorphic facial features. We observed reduced PSMD12 levels and an accumulation of ubiquitinated proteins without any impairment of proteasome catalytic activity. Our PSMD12 loss-of-function zebrafish CRISPR/Cas9 model exhibited microcephaly, decreased convolution of the renal tubules, and abnormal craniofacial morphology. Our data support the biological importance of PSMD12 as a scaffolding subunit in proteasome function during development and neurogenesis in particular; they enable the definition of a neurodevelopmental disorder due to PSMD12 variants, expanding the phenotypic spectrum of UPS-dependent disorders.
Keywords: Adolescent; Animals; Child; Child, Preschool; Disease Models, Animal; DNA Copy Number Variations; Down-Regulation; Female; Gene Deletion; Humans; Infant; Intellectual Disability; Male; Microcephaly; Neurodevelopmental Disorders; Polymorphism, Single Nucleotide; Proteasome Endopeptidase Complex; Zebrafish

Disruption of the ATXN1-CIC complex causes a spectrum of neurobehavioral phenotypes in mice and humans. - Lu, Hsiang-Chih; Tan, Qiumin; Rousseaux, Maxime W C; Wang, Wei; Kim, Ji-Yoen; Richman, Ronald; Wan, Ying-Wooi; Yeh, Szu-Ying; Patel, Jay M; Liu, Xiuyun; Lin, Tao; Lee, Yoontae; et al. (Nat Genet, 2017)
Gain-of-function mutations in some genes underlie neurodegenerative conditions, whereas loss-of-function mutations in the same genes have distinct phenotypes. This appears to be the case with the protein ataxin 1 (ATXN1), which forms a transcriptional repressor complex with capicua (CIC). Gain of function of the complex leads to neurodegeneration, but ATXN1-CIC is also essential for survival. We set out to understand the functions of the ATXN1-CIC complex in the developing forebrain and found that losing this complex results in hyperactivity, impaired learning and memory, and abnormal maturation and maintenance of upper-layer cortical neurons. We also found that CIC activity in the hypothalamus and medial amygdala modulates social interactions. Informed by these neurobehavioral features in mouse mutants, we identified five individuals with de novo heterozygous truncating mutations in CIC who share similar clinical features, including intellectual disability, attention deficit/hyperactivity disorder (ADHD), and autism spectrum disorder. Our study demonstrates that loss of ATXN1-CIC complexes causes a spectrum of neurobehavioral phenotypes.
Keywords: Animals; Ataxin-1; Autism Spectrum Disorder; Cerebellum; Female; Humans; Intellectual Disability; Interpersonal Relations; Male; Mice; Nerve Tissue Proteins; Neurodegenerative Diseases; Nuclear Proteins; Phenotype; Repressor Proteins

Evolutionary History of Chemosensory-Related Gene Families across the Arthropoda. - Eyun, Seong-Il; Soh, Ho Young; Posavi, Marijan; Munro, James B; Hughes, Daniel S T; Murali, Shwetha C; Qu, Jiaxin; Dugan, Shannon; Lee, Sandra L; Chao, Hsu; Dinh, Huyen; Yi Han; et al. (Mol Biol Evol, 2017)
Chemosensory-related gene (CRG) families have been studied extensively in insects, but their evolutionary history across the Arthropoda had remained relatively unexplored. Here, we address current hypotheses and prior conclusions on CRG family evolution using a more comprehensive data set. In particular, odorant receptors were hypothesized to have proliferated during terrestrial colonization by insects (hexapods), but their association with other pancrustacean clades and with independent terrestrial colonizations in other arthropod subphyla have been unclear. We also examine hypotheses on which arthropod CRG family is most ancient. Thus, we reconstructed phylogenies of CRGs, including those from new arthropod genomes and transcriptomes, and mapped CRG gains and losses across arthropod lineages. Our analysis was strengthened by including crustaceans, especially copepods, which reside outside the hexapod/branchiopod clade within the subphylum Pancrustacea. We generated the first high-resolution genome sequence of the copepod Eurytemora affinis and annotated its CRGs. We found odorant receptors and odorant binding proteins present only in hexapods (insects) and absent from all other arthropod lineages, indicating that they are not universal adaptations to land. Gustatory receptors likely represent the oldest chemosensory receptors among CRGs, dating back to the Placozoa. We also clarified and confirmed the evolutionary history of antennal ionotropic receptors across the Arthropoda. All antennal ionotropic receptors in E. affinis were expressed more highly in males than in females, suggestive of an association with male mate-recognition behavior. This study is the most comprehensive comparative analysis to date of CRG family evolution across the largest and most speciose metazoan phylum Arthropoda.
Keywords: Animals; Arthropods; Chemoreceptor Cells; Copepoda; Crustacea; Databases, Nucleic Acid; Evolution, Molecular; Genome; Insecta; Multigene Family; Phylogeny; Receptors, Odorant

GenomeScope: fast reference-free genome profiling from short reads. - Vurture, Gregory W; Fritz J Sedlazeck; Nattestad, Maria; Underwood, Charles J; Fang, Han; Gurtowski, James; Schatz, Michael C (Bioinformatics, 2017)
SUMMARY: GenomeScope is an open-source web tool to rapidly estimate the overall characteristics of a genome, including genome size, heterozygosity rate and repeat content from unprocessed short reads. These features are essential for studying genome evolution, and help to choose parameters for downstream analysis. We demonstrate its accuracy on 324 simulated and 16 real datasets with a wide range in genome sizes, heterozygosity levels and error rates. AVAILABILITY AND IMPLEMENTATION: http://genomescope.org , https://github.com/schatzlab/genomescope.git . CONTACT: mschatz@jhu.edu. SUPPLEMENTARY INFORMATION: Supplementary data are available at Bioinformatics online.
Keywords: Animals; Computational Biology; Evolution, Molecular; Genome; Genome Size; Heterozygote; Internet; Sequence Analysis, DNA; Software

Genomic innovations, transcriptional plasticity and gene loss underlying the evolution and divergence of two highly polyphagous and invasive Helicoverpa pest species. - Pearce, S L; Clarke, D F; East, P D; Elfekih, S; Gordon, K H J; Jermiin, L S; McGaughran, A; Oakeshott, J G; Papanicolaou, A; Perera, O P; Rane, R V; Stephen Richards; et al. (BMC Biol, 2017)
BACKGROUND: Helicoverpa armigera and Helicoverpa zea are major caterpillar pests of Old and New World agriculture, respectively. Both, particularly H. armigera, are extremely polyphagous, and H. armigera has developed resistance to many insecticides. Here we use comparative genomics, transcriptomics and resequencing to elucidate the genetic basis for their properties as pests. RESULTS: We find that, prior to their divergence about 1.5 Mya, the H. armigera/H. zea lineage had accumulated up to more than 100 more members of specific detoxification and digestion gene families and more than 100 extra gustatory receptor genes, compared to other lepidopterans with narrower host ranges. The two genomes remain very similar in gene content and order, but H. armigera is more polymorphic overall, and H. zea has lost several detoxification genes, as well as about 50 gustatory receptor genes. It also lacks certain genes and alleles conferring insecticide resistance found in H. armigera. Non-synonymous sites in the expanded gene families above are rapidly diverging, both between paralogues and between orthologues in the two species. Whole genome transcriptomic analyses of H. armigera larvae show widely divergent responses to different host plants, including responses among many of the duplicated detoxification and digestion genes. CONCLUSIONS: The extreme polyphagy of the two heliothines is associated with extensive amplification and neofunctionalisation of genes involved in host finding and use, coupled with versatile transcriptional responses on different hosts. H. armigera's invasion of the Americas in recent years means that hybridisation could generate populations that are both locally adapted and insecticide resistant.
Keywords: Animals; Gene Expression Profiling; Genome, Insect; Genomics; Herbivory; Introduced Species; Larva; Moths; Sequence Analysis, DNA

Genomics of natural populations: Evolutionary forces that establish and maintain gene arrangements in Drosophila pseudoobscura. - Fuller, Zachary L; Haynes, Gwilym D; Stephen Richards; Schaeffer, Stephen W (Mol Ecol, 2017)
The evolution of complex traits in heterogeneous environments may shape the order of genes within chromosomes. Drosophila pseudoobscura has a rich gene arrangement polymorphism that allows one to test evolutionary genetic hypotheses about how chromosomal inversions are established in populations. D. pseudoobscura has >30 gene arrangements on a single chromosome that were generated through a series of overlapping inversion mutations with >10 inversions with appreciable frequencies and wide geographic distributions. This study analyses the genomic sequences of 54 strains of Drosophila pseudoobscura that carry one of six different chromosomal arrangements to test whether (i) genetic drift, (ii) hitchhiking with an adaptive allele, (iii) direct effects of inversions to create gene disruptions caused by breakpoints, or (iv) indirect effects of inversions in limiting the formation of recombinant gametes are responsible for the establishment of new gene arrangements. We found that the inversion events do not disrupt the structure of protein coding genes at the breakpoints. Population genetic analyses of 2,669 protein coding genes identified 277 outlier loci harbouring elevated frequencies of arrangement-specific derived alleles. Significant linkage disequilibrium occurs among distant loci interspersed between regions with low levels of association indicating that distant allelic combinations are held together despite shared polymorphism among arrangements. Outlier genes showing evidence of genetic differentiation between arrangements are enriched for sensory perception and detoxification genes. The data presented here support the indirect effect of inversion hypothesis where chromosomal inversions are favoured because they maintain linked associations among multilocus allelic combinations among different arrangements.
Keywords: Alleles; Animals; Chromosome Inversion; Chromosome Mapping; Drosophila; Evolution, Molecular; Gene Frequency; Gene Order; Genetics, Population; High-Throughput Nucleotide Sequencing; Linkage Disequilibrium; Phylogeny; Sequence Analysis, DNA

Germline mutations in ABL1 cause an autosomal dominant syndrome characterized by congenital heart defects and skeletal malformations. - Wang, Xia; Charng, Wu-Lin; Chen, Chun-An; Rosenfeld, Jill A; Al Shamsi, Aisha; Al-Gazali, Lihadh; McGuire, Marianne; Mew, Nicholas Ah; Arnold, Georgianne L; Qu, Chunjing; Ding, Yan; Donna M Muzny; et al. (Nat Genet, 2017)
ABL1 is a proto-oncogene well known as part of the fusion gene BCR-ABL1 in the Philadelphia chromosome of leukemia cancer cells. Inherited germline ABL1 changes have not been associated with genetic disorders. Here we report ABL1 germline variants cosegregating with an autosomal dominant disorder characterized by congenital heart disease, skeletal abnormalities, and failure to thrive. The variant c.734A>G (p.Tyr245Cys) was found to occur de novo or cosegregate with disease in five individuals (families 1-3). Additionally, a de novo c.1066G>A (p.Ala356Thr) variant was identified in a sixth individual (family 4). We overexpressed the mutant constructs in HEK 293T cells and observed increased tyrosine phosphorylation, suggesting increased ABL1 kinase activities associated with both the p.Tyr245Cys and p.Ala356Thr substitutions. Our clinical and experimental findings, together with previously reported teratogenic effects of selective BCR-ABL inhibitors in humans and developmental defects in Abl1 knockout mice, suggest that ABL1 has an important role during organismal development.
Keywords: Abnormalities, Multiple; Animals; Bone Diseases, Developmental; Cell Line; Chromosome Disorders; Craniofacial Abnormalities; Feeding and Eating Disorders; Female; Fusion Proteins, bcr-abl; Germ-Line Mutation; Heart Defects, Congenital; HEK293 Cells; Humans; Leukemia, Myelogenous, Chronic, BCR-ABL Positive; Limb Deformities, Congenital; Male; Mice; Mice, Knockout; Philadelphia Chromosome; Phosphorylation; Proto-Oncogene Mas; Signal Transduction

A golden goat genome. - Worley, Kim C (Nat Genet, 2017)
The newly described de novo goat genome sequence is the most contiguous diploid vertebrate assembly generated thus far using whole-genome assembly and scaffolding methods. The contiguity of this assembly is approaching that of the finished human and mouse genomes and suggests an affordable roadmap to high-quality references for thousands of species.
Keywords: Aged; Animals; Diploidy; Genome; Goats; Humans; Mice

The house spider genome reveals an ancient whole-genome duplication during arachnid evolution. - Schwager, Evelyn E; Sharma, Prashant P; Clarke, Thomas; Leite, Daniel J; Wierschin, Torsten; Pechmann, Matthias; Akiyama-Oda, Yasuko; Esposito, Lauren; Bechsgaard, Jesper; Bilde, Trine; Buffry, Alexandra D; Chao, Hsu; et al. (BMC Biol, 2017)
BACKGROUND: The duplication of genes can occur through various mechanisms and is thought to make a major contribution to the evolutionary diversification of organisms. There is increasing evidence for a large-scale duplication of genes in some chelicerate lineages including two rounds of whole genome duplication (WGD) in horseshoe crabs. To investigate this further, we sequenced and analyzed the genome of the common house spider Parasteatoda tepidariorum. RESULTS: We found pervasive duplication of both coding and non-coding genes in this spider, including two clusters of Hox genes. Analysis of synteny conservation across the P. tepidariorum genome suggests that there has been an ancient WGD in spiders. Comparison with the genomes of other chelicerates, including that of the newly sequenced bark scorpion Centruroides sculpturatus, suggests that this event occurred in the common ancestor of spiders and scorpions, and is probably independent of the WGDs in horseshoe crabs. Furthermore, characterization of the sequence and expression of the Hox paralogs in P. tepidariorum suggests that many have been subject to neo-functionalization and/or sub-functionalization since their duplication. CONCLUSIONS: Our results reveal that spiders and scorpions are likely the descendants of a polyploid ancestor that lived more than 450 MYA. Given the extensive morphological diversity and ecological adaptations found among these animals, rivaling those of vertebrates, our study of the ancient WGD event in Arachnopulmonata provides a new comparative platform to explore common and divergent evolutionary outcomes of polyploidization events across eukaryotes.
Keywords: Animals; Evolution, Molecular; Female; Gene Duplication; Genome; Male; Spiders; Synteny

House spider genome uncovers evolutionary shifts in the diversity and expression of black widow venom proteins associated with extreme toxicity. - Gendreau, Kerry L; Haney, Robert A; Schwager, Evelyn E; Wierschin, Torsten; Stanke, Mario; Stephen Richards; Garb, Jessica E (BMC Genomics, 2017)
BACKGROUND: Black widow spiders are infamous for their neurotoxic venom, which can cause extreme and long-lasting pain. This unusual venom is dominated by latrotoxins and latrodectins, two protein families virtually unknown outside of the black widow genus Latrodectus, that are difficult to study given the paucity of spider genomes. Using tissue-, sex- and stage-specific expression data, we analyzed the recently sequenced genome of the house spider (Parasteatoda tepidariorum), a close relative of black widows, to investigate latrotoxin and latrodectin diversity, expression and evolution. RESULTS: We discovered at least 47 latrotoxin genes in the house spider genome, many of which are tandem-arrayed. Latrotoxins vary extensively in predicted structural domains and expression, implying their significant functional diversification. Phylogenetic analyses show latrotoxins have substantially duplicated after the Latrodectus/Parasteatoda split and that they are also related to proteins found in endosymbiotic bacteria. Latrodectin genes are less numerous than latrotoxins, but analyses show their recruitment for venom function from neuropeptide hormone genes following duplication, inversion and domain truncation. While latrodectins and other peptides are highly expressed in house spider and black widow venom glands, latrotoxins account for a far smaller percentage of house spider venom gland expression. CONCLUSIONS: The house spider genome sequence provides novel insights into the evolution of venom toxins once considered unique to black widows. Our results greatly expand the size of the latrotoxin gene family, reinforce its narrow phylogenetic distribution, and provide additional evidence for the lateral transfer of latrotoxins between spiders and bacterial endosymbionts. Moreover, we strengthen the evidence for the evolution of latrodectin venom genes from the ecdysozoan Ion Transport Peptide (ITP)/Crustacean Hyperglycemic Hormone (CHH) neuropeptide superfamily. The lower expression of latrotoxins in house spiders relative to black widows, along with the absence of a vertebrate-targeting α-latrotoxin gene in the house spider genome, may account for the extreme potency of black widow venom.
Keywords: Animals; Black Widow Spider; Coxiellaceae; Evolution, Molecular; Female; Gene Expression Profiling; Genetic Variation; Genomics; Insect Proteins; Male; Protein Domains; Sex Characteristics; Spider Venoms; Symbiosis

Hybrid de novo genome assembly and centromere characterization of the gray mouse lemur (Microcebus murinus). - Larsen, Peter A; R. Alan Harris; Liu, Yue; Murali, Shwetha C; Campbell, C Ryan; Brown, Adam D; Sullivan, Beth A; Shelton, Jennifer; Brown, Susan J; Raveendran, Muthuswamy; Dudchenko, Olga; Machol, Ido; et al. (BMC Biol, 2017)
BACKGROUND: The de novo assembly of repeat-rich mammalian genomes using only high-throughput short read sequencing data typically results in highly fragmented genome assemblies that limit downstream applications. Here, we present an iterative approach to hybrid de novo genome assembly that incorporates datasets stemming from multiple genomic technologies and methods. We used this approach to improve the gray mouse lemur (Microcebus murinus) genome from early draft status to a near chromosome-scale assembly. METHODS: We used a combination of advanced genomic technologies to iteratively resolve conflicts and super-scaffold the M. murinus genome. RESULTS: We improved the M. murinus genome assembly to a scaffold N50 of 93.32 Mb. Whole genome alignments between our primary super-scaffolds and 23 human chromosomes revealed patterns that are congruent with historical comparative cytogenetic data, thus demonstrating the accuracy of our de novo scaffolding approach and allowing assignment of scaffolds to M. murinus chromosomes. Moreover, we utilized our independent datasets to discover and characterize sequences associated with centromeres across the mouse lemur genome. Quality assessment of the final assembly found 96% of mouse lemur canonical transcripts nearly complete, comparable to other published high-quality reference genome assemblies. CONCLUSIONS: We describe a new assembly of the gray mouse lemur (Microcebus murinus) genome with chromosome-scale scaffolds produced using a hybrid bioinformatic and sequencing approach. The approach is cost effective and produces superior results based on metrics of contiguity and completeness. Our results show that emerging genomic technologies can be used in combination to characterize centromeres of non-model species and to produce accurate de novo chromosome-scale genome assemblies of complex mammalian genomes.
Keywords: Animals; Centromere; Cheirogaleidae; Computational Biology; Female; Genome; High-Throughput Nucleotide Sequencing; Sequence Analysis, DNA

IFT81 as a Candidate Gene for Nonsyndromic Retinal Degeneration. - Dharmat, Rachayata; Liu, Wei; Ge, Zhongqi; Sun, Zixi; Yang, Lizhu; Yumei Li; Wang, Keqing; Thomas, Kandace; Sui, Ruifang; Rui Chen (Invest Ophthalmol Vis Sci, 2017)
PURPOSE: IFT81, a core component of the IFT-B complex, involved in the bidirectional transport of ciliary proteins, has been recently implicated in syndromic ciliopathies. However, none of the IFT-B core complex proteins have been associated with nonsyndromic retinal dystrophies. Given the importance of ciliary transport in photoreceptor function and structural maintenance, we sought to investigate the impact of IFT (intraflagellar transport) mutations in nonsyndromic retinopathies. METHODS: Whole exome sequencing was performed on 50 cone-rod dystrophy (CRD) patients that were previously screened for mutations in known retinal disease genes. The impact of candidate mutation was studied using in vitro cell system and in vivo zebrafish assay to determine the pathogenicity of the variant. RESULTS: Compound heterozygous mutations in IFT81, including one nonsense (c.1213C>T, p.R405*) and one missense variant (c.1841T>C, p.L614P), were identified in a nonsyndromic CRD proband. Extensive functional analyses of the missense variant in cell culture and zebrafish strongly suggests its pathogenic nature. Loss of IFT81 impairs ciliogenesis and, interestingly, the missense variant displayed significantly reduced rescue of ciliogenesis in the IFT81 knockdown in vitro system. Consistently, dramatic reduction of rescue efficiency of the ift81 mutant zebrafish embryo by mRNA with the missense variant was observed, further supporting its pathogenicity. CONCLUSIONS: Consistent with the function of the IFT-B complex in the maintenance of photoreceptor cilium, we report a case of mutations in a core IFT-B protein, IFT81. This represents the first report of mutations in IFT81 as a candidate gene for nonsyndromic retinal dystrophy, hence expanding the phenotype spectrum of IFT-B components.
Keywords: Animals; Cells, Cultured; Codon, Nonsense; Disease Models, Animal; DNA; DNA Mutational Analysis; Female; Humans; Male; Muscle Proteins; Mutation; Phenotype; Retina; Retinal Degeneration; Zebrafish

Improved annotation of the insect vector of citrus greening disease: biocuration by a diverse genomics community. - Saha, Surya; Hosmani, Prashant S; Villalobos-Ayala, Krystal; Miller, Sherry; Shippy, Teresa; Flores, Mirella; Rosendale, Andrew; Cordola, Chris; Bell, Tracey; Mann, Hannah; DeAvila, Gabe; DeAvila, Daniel; et al. (Database (Oxford), 2017)
https://citrusgreening.org/.
Keywords: Animals; Citrus; Databases, Genetic; Genome, Insect; Hemiptera; Insect Vectors; Pest Control; Plant Diseases; Rhizobiaceae

Improved full-length killer cell immunoglobulin-like receptor transcript discovery in Mauritian cynomolgus macaques. - Prall, Trent M; Graham, Michael E; Karl, Julie A; Wiseman, Roger W; Ericsen, Adam J; Raveendran, Muthuswamy; R. Alan Harris; Donna M Muzny; Richard A Gibbs; Jeffrey Rogers; O'Connor, David H (Immunogenetics, 2017)
Killer cell immunoglobulin-like receptors (KIRs) modulate disease progression of pathogens including HIV, malaria, and hepatitis C. Cynomolgus and rhesus macaques are widely used as nonhuman primate models to study human pathogens, and so, considerable effort has been put into characterizing their KIR genetics. However, previous studies have relied on cDNA cloning and Sanger sequencing that lack the throughput of current sequencing platforms. In this study, we present a high throughput, full-length allele discovery method utilizing Pacific Biosciences circular consensus sequencing (CCS). We also describe a new approach to Macaque Exome Sequencing (MES) and the development of the Rhexome1.0, an adapted target capture reagent that includes macaque-specific capture probe sets. By using sequence reads generated by whole genome sequencing (WGS) and MES to inform primer design, we were able to increase the sensitivity of KIR allele discovery. We demonstrate this increased sensitivity by defining nine novel alleles within a cohort of Mauritian cynomolgus macaques (MCM), a geographically isolated population with restricted KIR genetics that was thought to be completely characterized. Finally, we describe an approach to genotyping KIRs directly from sequence reads generated using WGS/MES reads. The findings presented here expand our understanding of KIR genetics in MCM by associating new genes with all eight KIR haplotypes and demonstrating the existence of at least one KIR3DS gene associated with every haplotype.
Keywords: Animals; Exome; Gene Frequency; High-Throughput Nucleotide Sequencing; Macaca fascicularis; Receptors, KIR; Sequence Analysis, DNA

Isochlorogenic acid A promotes melanin synthesis in B16 cell through the β-catenin signal pathway. - Mamat, Nuramina; Dou, Jun; Lu, Xueying; Eblimit, Aiden; Haji Akber, Aisa (Acta Biochim Biophys Sin (Shanghai), 2017)
Isochlorogenic acid A, also called 3,5-dicaffeoylquinic acid (3,5-diCQA), is a widespread phenolic compound in the plant. Recent studies have shown that it has antioxidant and anti-inflammatory activity. In addition, oxidative stress and inflammation induced by solar ultraviolet radiation is a very significant reason for skin depigmentation. Therefore, in this study, we evaluated the effect of 3,5-diCQA on B16 cells and explored its molecular mechanism. Results showed that 3,5-diCQA upregulated intracellular melanin production in a time- and dose-dependent manner. Tyrosinase (TYR) activity was also increased after treatment with 3,5-diCQA in a dose-dependent manner. Expressions of TYR, TYR-related protein1, TYR-related protein2, and microphthalmia-associated transcription factor were upregulated in a dose-dependent manner after 48 h of treatment with 3,5-diCQA. Results also showed that 3,5-diCQA promoted the phosphorylation of Akt at Thr308 and glycogen synthase kinase-3β at Ser 9. Moreover, 3,5-diCQA increased the content of β-catenin in cell cytoplasm and nucleus by reducing the content of phosphorylated β-catenin (p-β-catenin). All these results suggest that 3,5-diCQA may mediate the acceleration of melanin synthesis by the β-catenin signal pathway.
Keywords: Animals; beta Catenin; Blotting, Western; Cell Line, Tumor; Cell Proliferation; Chlorogenic Acid; Melanins; Melanoma, Experimental; Mice; Microphthalmia-Associated Transcription Factor; Molecular Structure; Monophenol Monooxygenase; Signal Transduction; Skin Neoplasms

Loss of Nardilysin, a Mitochondrial Co-chaperone for α-Ketoglutarate Dehydrogenase, Promotes mTORC1 Activation and Neurodegeneration. - Yoon, Wan Hee; Sandoval, Hector; Nagarkar-Jaiswal, Sonal; Jaiswal, Manish; Yamamoto, Shinya; Haelterman, Nele A; Putluri, Nagireddy; Putluri, Vasanta; Sreekumar, Arun; Tos, Tulay; Aksoy, Ayse; Donti, Taraka; et al. (Neuron, 2017)
We previously identified mutations in Nardilysin (dNrd1) in a forward genetic screen designed to isolate genes whose loss causes neurodegeneration in Drosophila photoreceptor neurons. Here we show that NRD1 is localized to mitochondria, where it recruits mitochondrial chaperones and assists in the folding of α-ketoglutarate dehydrogenase (OGDH), a rate-limiting enzyme in the Krebs cycle. Loss of Nrd1 or Ogdh leads to an increase in α-ketoglutarate, a substrate for OGDH, which in turn leads to mTORC1 activation and a subsequent reduction in autophagy. Inhibition of mTOR activity by rapamycin or partially restoring autophagy delays neurodegeneration in dNrd1 mutant flies. In summary, this study reveals a novel role for NRD1 as a mitochondrial co-chaperone for OGDH and provides a mechanistic link between mitochondrial metabolic dysfunction, mTORC1 signaling, and impaired autophagy in neurodegeneration.
Keywords: Animals; Autophagy; Drosophila; Drosophila melanogaster; Drosophila Proteins; Ketoglutarate Dehydrogenase Complex; Ketoglutaric Acids; Lysine; Mechanistic Target of Rapamycin Complex 1; Metalloendopeptidases; Mitochondria; Molecular Chaperones; Multiprotein Complexes; Neurodegenerative Diseases; TOR Serine-Threonine Kinases

Mutations in the Spliceosome Component CWC27 Cause Retinal Degeneration with or without Additional Developmental Anomalies. - Xu, Mingchu; Xie, Yajing Angela; Abouzeid, Hana; Gordon, Christopher T; Fiorentino, Alessia; Sun, Zixi; Lehman, Anna; Osman, Ihab S; Dharmat, Rachayata; Riveiro-Álvarez, Rosa; Bapst-Wicht, Linda; Babino, Darwin; et al. (Am J Hum Genet, 2017)
Pre-mRNA splicing factors play a fundamental role in regulating transcript diversity both temporally and spatially. Genetic defects in several spliceosome components have been linked to a set of non-overlapping spliceosomopathy phenotypes in humans, among which skeletal developmental defects and non-syndromic retinitis pigmentosa (RP) are frequent findings. Here we report that defects in spliceosome-associated protein CWC27 are associated with a spectrum of disease phenotypes ranging from isolated RP to severe syndromic forms. By whole-exome sequencing, recessive protein-truncating mutations in CWC27 were found in seven unrelated families that show a range of clinical phenotypes, including retinal degeneration, brachydactyly, craniofacial abnormalities, short stature, and neurological defects. Remarkably, variable expressivity of the human phenotype can be recapitulated in Cwc27 mutant mouse models, with significant embryonic lethality and severe phenotypes in the complete knockout mice while mice with a partial loss-of-function allele mimic the isolated retinal degeneration phenotype. Our study describes a retinal dystrophy-related phenotype spectrum as well as its genetic etiology and highlights the complexity of the spliceosomal gene network.
Keywords: Abnormalities, Multiple; Adolescent; Animals; Child; Child, Preschool; Cyclophilins; Female; Humans; Male; Mice; Mutation; Pedigree; Peptidylprolyl Isomerase; Retinal Degeneration; Young Adult

REEP6 deficiency leads to retinal degeneration through disruption of ER homeostasis and protein trafficking. - Agrawal, Smriti A; Burgoyne, Thomas; Eblimit, Aiden; Bellingham, James; Parfitt, David A; Lane, Amelia; Nichols, Ralph; Asomugha, Chinwe; Hayes, Matthew J; Munro, Peter M; Xu, Mingchu; Wang, Keqing; et al. (Hum Mol Genet, 2017)
Retinitis pigmentosa (RP) is the most common form of inherited retinal dystrophy. We recently identified mutations in REEP6, which encodes the receptor expression enhancing protein 6, in several families with autosomal recessive RP. REEP6 is related to the REEP and Yop1p family of ER shaping proteins and potential receptor accessory proteins, but the role of REEP6 in the retina is unknown. Here we characterize the disease mechanisms associated with loss of REEP6 function using a Reep6 knockout mouse generated by CRISPR/Cas9 gene editing. In control mice REEP6 was localized to the inner segment and outer plexiform layer of rod photoreceptors. The Reep6-/- mice exhibited progressive photoreceptor degeneration from P20 onwards. Ultrastructural analyses at P20 by transmission electron microscopy and 3View serial block face scanning EM revealed an expansion of the distal ER in the Reep6-/- rods and an increase in their number of mitochondria. Electroretinograms revealed photoreceptor dysfunction preceded degeneration, suggesting potential defects in phototransduction. There was no effect on the traffic of rhodopsin, Rom1 or peripherin/rds; however, the retinal guanylate cyclases GC1 and GC2 were severely affected in the Reep6 knockout animals, with almost undetectable expression. These changes correlated with an increase in C/EBP homologous protein (CHOP) expression and the activation of caspase 12, suggesting that ER stress contributes to cell death. Collectively, these data suggest that REEP6 plays an essential role in maintaining cGMP homeostasis though facilitating the stability and/or trafficking of guanylate cyclases and maintaining ER and mitochondrial homeostasis.
Keywords: Animals; Base Sequence; Clustered Regularly Interspaced Short Palindromic Repeats; Endoplasmic Reticulum; Eye Proteins; Gene Editing; Guanylate Cyclase; Light Signal Transduction; Membrane Proteins; Membrane Transport Proteins; Mice; Mice, Knockout; Photoreceptor Cells, Vertebrate; Retinal Dystrophies; Retinal Rod Photoreceptor Cells; Rhodopsin

The SWI/SNF Protein PBRM1 Restrains VHL-Loss-Driven Clear Cell Renal Cell Carcinoma. - Nargund, Amrita M; Pham, Can G; Dong, Yiyu; Wang, Patricia I; Osmangeyoglu, Hatice U; Xie, Yuchen; Aras, Omer; Han, Song; Oyama, Toshinao; Takeda, Shugaku; Ray, Chelsea E; Dong, Zhenghong; et al. (Cell Rep, 2017)
PBRM1 is the second most commonly mutated gene after VHL in clear cell renal cell carcinoma (ccRCC). However, the biological consequences of PBRM1 mutations for kidney tumorigenesis are unknown. Here, we find that kidney-specific deletion of Vhl and Pbrm1, but not either gene alone, results in bilateral, multifocal, transplantable clear cell kidney cancers. PBRM1 loss amplified the transcriptional outputs of HIF1 and STAT3 incurred by Vhl deficiency. Analysis of mouse and human ccRCC revealed convergence on mTOR activation, representing the third driver event after genetic inactivation of VHL and PBRM1. Our study reports a physiological preclinical ccRCC mouse model that recapitulates somatic mutations in human ccRCC and provides mechanistic and therapeutic insights into PBRM1 mutated subtypes of human ccRCC.
Keywords: Animals; Carcinoma, Renal Cell; DNA-Binding Proteins; Down-Regulation; Gene Deletion; Gene Expression Profiling; Gene Expression Regulation, Neoplastic; HMGB Proteins; Humans; Hydronephrosis; Hypoxia-Inducible Factor 1, alpha Subunit; Integrases; Kidney; Kidney Neoplasms; Mechanistic Target of Rapamycin Complex 1; Mice; Nuclear Proteins; Oxidative Phosphorylation; Signal Transduction; STAT3 Transcription Factor; Transcription Factors; Transcription, Genetic; Von Hippel-Lindau Tumor Suppressor Protein

The value of new genome references. - Worley, Kim C; Stephen Richards; Jeffrey Rogers (Exp Cell Res, 2017)
Genomic information has become a ubiquitous and almost essential aspect of biological research. Over the last 10-15 years, the cost of generating sequence data from DNA or RNA samples has dramatically declined and our ability to interpret those data increased just as remarkably. Although it is still possible for biologists to conduct interesting and valuable research on species for which genomic data are not available, the impact of having access to a high quality whole genome reference assembly for a given species is nothing short of transformational. Research on a species for which we have no DNA or RNA sequence data is restricted in fundamental ways. In contrast, even access to an initial draft quality genome (see below for definitions) opens a wide range of opportunities that are simply not available without that reference genome assembly. Although a complete discussion of the impact of genome sequencing and assembly is beyond the scope of this short paper, the goal of this review is to summarize the most common and highest impact contributions that whole genome sequencing and assembly has had on comparative and evolutionary biology.
Keywords: Animals; Base Sequence; Chromosome Mapping; Computational Biology; Genome; High-Throughput Nucleotide Sequencing; Humans; Sequence Analysis, DNA

Acquired uniparental disomy of chromosome 9p in hematologic malignancies. - Wang, Linghua; Wheeler, David A; Prchal, Josef T (Exp Hematol, 2016)
Acquired uniparental disomy (aUPD) is a common and recurrent molecular event in human cancers that leads to homozygosity for tumor suppressor genes as well as oncogenes, while retaining the diploid chromosomal complement. Because of the lack of copy number change, aUPD is undetectable by comparative genome hybridization, so the magnitude of this genetic change was underappreciated in the past. 9p aUPD was first described in 2002 in patients with polycythemia vera (PV). Since then, systematic application of genomewide single-nucleotide polymorphism arrays has indicated that 9p aUPD is the most common chromosomal aberration in myeloproliferative neoplasms (MPNs), contributing to discovery of the PV-defining mutation JAK2V617F21. It was also found in other myeloid and lymphoid malignancies, though at a relatively lower frequency. By leading to JAK2V617F 23 homozygosity, 9p aUPD plays a causal role in the development of PV and is also associated with less favorable clinical outcomes. It is also possible that new targets other than JAK2V617F 25 are present within 9p aUPD that may contribute to diversity of PV outcome and phenotype. This review summarizes recent discoveries on 9p aUPD in hematologic malignancies and discusses possible underlying mechanisms and potential roles of 9p aUPD in the pathogenesis of PV, the relationship between 9p aUPD and JAK2V617F29, and possible new cancer-related targets within the 9p aUPD region.
Keywords: Animals; Chromosomes, Human, Pair 9; Disease Progression; Gene Frequency; Hematologic Neoplasms; Humans; Janus Kinase 2; Mutation; Polycythemia Vera; Prognosis; Uniparental Disomy

ADIPOR1 Is Mutated in Syndromic Retinitis Pigmentosa. - Xu, Mingchu; Eblimit, Aiden; Wang, Jing; Li, Jianli; Wang, Feng; Zhao, Li; Wang, Xia; Xiao, Ningna; Yumei Li; Wong, Lee-Jun C; Lewis, Richard A; Rui Chen (Hum Mutat, 2016)
Retinitis pigmentosa (RP) is a genetically heterogeneous retinal disorder. Despite the numerous genes associated with RP already identified, the genetic basis remains unknown in a substantial number of patients and families. In this study, we performed whole-exome sequencing to investigate the molecular basis of a syndromic RP case that cannot be solved by mutations in known disease-causing genes. After applying a series of variant filtering strategies, we identified an apparently homozygous frameshift mutation, c.31delC (p.Q11Rfs*24) in the ADIPOR1 gene. The reported phenotypes of Adipor1-null mice contain retinal dystrophy, obesity, and behavioral abnormalities, which highly mimic those in the syndromic RP patient. We further confirmed ADIPOR1 retina expression by immunohistochemistry. Our results established ADIPOR1 as a novel disease-causing gene for syndromic RP and highlight the importance of fatty acid transport in the retina.
Keywords: Adult; Animals; Exome; Female; Frameshift Mutation; Humans; Male; Mice; Mutation; Receptors, Adiponectin; Retinitis Pigmentosa; Young Adult

Are feeding preferences and insecticide resistance associated with the size of detoxifying enzyme families in insect herbivores? - Rane, Rahul V; Walsh, Tom K; Pearce, Stephen L; Jermiin, Lars S; Gordon, Karl Hj; Stephen Richards; Oakeshott, John G (Curr Opin Insect Sci, 2016)
The size of gene families associated with xenobiotic detoxification in insects may be associated with the complexity of their diets and their propensities to develop insecticide resistance. We test these hypotheses by collating the annotations of cytochrome P450, carboxyl/cholinesterase and glutathione S-transferase genes in 65 insect species with data on their host use and history of insecticide resistance. We find 2-4 fold variation across the species in the numbers of these genes and, in some orders, especially the Hymenoptera, there is a clear relationship between the numbers of genes and feeding preferences. However in other orders, in particular the Lepidoptera, no such relationship is apparent. The size of these three gene families also tend to correlate with insecticide resistance propensity but this may not be an independent effect because species with broader host ranges are more likely to be pests that are heavily sprayed with insecticides.
Keywords: Animals; Cholinesterases; Cytochrome P-450 Enzyme System; Food Preferences; Glutathione Transferase; Herbivory; Inactivation, Metabolic; Insecta; Insecticide Resistance

Association of MTOR Mutations With Developmental Brain Disorders, Including Megalencephaly, Focal Cortical Dysplasia, and Pigmentary Mosaicism. - Mirzaa, Ghayda M; Campbell, Catarina D; Solovieff, Nadia; Goold, Carleton; Jansen, Laura A; Menon, Suchithra; Timms, Andrew E; Conti, Valerio; Biag, Jonathan D; Adams, Carissa; Boyle, Evan August; Collins, Sarah; et al. (JAMA Neurol, 2016)
IMPORTANCE: Focal cortical dysplasia (FCD), hemimegalencephaly, and megalencephaly constitute a spectrum of malformations of cortical development with shared neuropathologic features. These disorders are associated with significant childhood morbidity and mortality. OBJECTIVE: To identify the underlying molecular cause of FCD, hemimegalencephaly, and diffuse megalencephaly. DESIGN, SETTING, AND PARTICIPANTS: Patients with FCD, hemimegalencephaly, or megalencephaly (mean age, 11.7 years; range, 2-32 years) were recruited from Pediatric Hospital A. Meyer, the University of Hong Kong, and Seattle Children's Research Institute from June 2012 to June 2014. Whole-exome sequencing (WES) was performed on 8 children with FCD or hemimegalencephaly using standard-depth (50-60X) sequencing in peripheral samples (blood, saliva, or skin) from the affected child and their parents and deep (150-180X) sequencing in affected brain tissue. Targeted sequencing and WES were used to screen 93 children with molecularly unexplained diffuse or focal brain overgrowth. Histopathologic and functional assays of phosphatidylinositol 3-kinase-AKT (serine/threonine kinase)-mammalian target of rapamycin (mTOR) pathway activity in resected brain tissue and cultured neurons were performed to validate mutations. MAIN OUTCOMES AND MEASURES: Whole-exome sequencing and targeted sequencing identified variants associated with this spectrum of developmental brain disorders. RESULTS: Low-level mosaic mutations of MTOR were identified in brain tissue in 4 children with FCD type 2a with alternative allele fractions ranging from 0.012 to 0.086. Intermediate-level mosaic mutation of MTOR (p.Thr1977Ile) was also identified in 3 unrelated children with diffuse megalencephaly and pigmentary mosaicism in skin. Finally, a constitutional de novo mutation of MTOR (p.Glu1799Lys) was identified in 3 unrelated children with diffuse megalencephaly and intellectual disability. Molecular and functional analysis in 2 children with FCD2a from whom multiple affected brain tissue samples were available revealed a mutation gradient with an epicenter in the most epileptogenic area. When expressed in cultured neurons, all MTOR mutations identified here drive constitutive activation of mTOR complex 1 and enlarged neuronal size. CONCLUSIONS AND RELEVANCE: In this study, mutations of MTOR were associated with a spectrum of brain overgrowth phenotypes extending from FCD type 2a to diffuse megalencephaly, distinguished by different mutations and levels of mosaicism. These mutations may be sufficient to cause cellular hypertrophy in cultured neurons and may provide a demonstration of the pattern of mosaicism in brain and substantiate the link between mosaic mutations of MTOR and pigmentary mosaicism in skin.
Keywords: Adolescent; Adult; Amino Acids; Animals; Cells, Cultured; Cerebral Cortex; Child; Child, Preschool; Developmental Disabilities; Embryo, Mammalian; Female; Gene Expression Regulation; Genetic Association Studies; Humans; Intercellular Signaling Peptides and Proteins; Male; Malformations of Cortical Development; Mechanistic Target of Rapamycin Complex 1; Megalencephaly; Mosaicism; Multiprotein Complexes; Mutation; Nerve Tissue Proteins; Neurons; Rats; Retrospective Studies; TOR Serine-Threonine Kinases; Young Adult

Avirulence gene mapping in the Hessian fly (Mayetiola destructor) reveals a protein phosphatase 2C effector gene family. - Zhao, Chaoyang; Shukle, Richard; Navarro-Escalante, Lucio; Chen, Mingshun; Stephen Richards; Stuart, Jeffrey J (J Insect Physiol, 2016)
The genetic tractability of the Hessian fly (HF, Mayetiola destructor) provides an opportunity to investigate the mechanisms insects use to induce plant gall formation. Here we demonstrate that capacity using the newly sequenced HF genome by identifying the gene (vH24) that elicits effector-triggered immunity in wheat (Triticum spp.) seedlings carrying HF resistance gene H24. vH24 was mapped within a 230-kb genomic fragment near the telomere of HF chromosome X1. That fragment contains only 21 putative genes. The best candidate vH24 gene in this region encodes a protein containing a secretion signal and a type-2 serine/threonine protein phosphatase (PP2C) domain. This gene has an H24-virulence associated insertion in its promoter that appears to silence transcription of the gene in H24-virulent larvae. Candidate vH24 is a member of a small family of genes that encode secretion signals and PP2C domains. It belongs to the fraction of genes in the HF genome previously predicted to encode effector proteins. Because PP2C proteins are not normally secreted, our results suggest that these are PP2C effectors that HF larvae inject into wheat cells to redirect, or interfere, with wheat signal transduction pathways.
Keywords: Animals; Chromosome Mapping; Crosses, Genetic; Diptera; Female; Genes, Insect; Genes, Plant; Genes, Recessive; Genes, X-Linked; Host-Parasite Interactions; Male; Phosphoprotein Phosphatases; Plant Immunity; Plant Proteins; Plant Tumors; Protein Phosphatase 2C; Telomere; Triticum; Virulence

Bi-allelic Mutations in PKD1L1 Are Associated with Laterality Defects in Humans. - Vetrini, Francesco; D'Alessandro, Lisa C A; Akdemir, Zeynep C; Braxton, Alicia; Azamian, Mahshid S; Eldomery, Mohammad K; Miller, Kathryn; Kois, Chelsea; Sack, Virginia; Shur, Natasha; Rijhsinghani, Asha; Chandarana, Jignesh; et al. (Am J Hum Genet, 2016)
Disruption of the establishment of left-right (L-R) asymmetry leads to situs anomalies ranging from situs inversus totalis (SIT) to situs ambiguus (heterotaxy). The genetic causes of laterality defects in humans are highly heterogeneous. Via whole-exome sequencing (WES), we identified homozygous mutations in PKD1L1 from three affected individuals in two unrelated families. PKD1L1 encodes a polycystin-1-like protein and its loss of function is known to cause laterality defects in mouse and medaka fish models. Family 1 had one fetus and one deceased child with heterotaxy and complex congenital heart malformations. WES identified a homozygous splicing mutation, c.6473+2_6473+3delTG, which disrupts the invariant splice donor site in intron 42, in both affected individuals. In the second family, a homozygous c.5072G>C (p.Cys1691Ser) missense mutation was detected in an individual with SIT and congenital heart disease. The p.Cys1691Ser substitution affects a highly conserved cysteine residue and is predicted by molecular modeling to disrupt a disulfide bridge essential for the proper folding of the G protein-coupled receptor proteolytic site (GPS) motif. Damaging effects associated with substitutions of this conserved cysteine residue in the GPS motif have also been reported in other genes, namely GPR56, BAI3, and PKD1 in human and lat-1 in C. elegans, further supporting the likely pathogenicity of p.Cys1691Ser in PKD1L1. The identification of bi-allelic PKD1L1 mutations recapitulates previous findings regarding phenotypic consequences of loss of function of the orthologous genes in mice and medaka fish and further expands our understanding of genetic contributions to laterality defects in humans.
Keywords: Alleles; Amino Acid Motifs; Amino Acid Sequence; Animals; Caenorhabditis elegans; Cysteine; Exome; Female; Fetal Diseases; Functional Laterality; Heart Defects, Congenital; Heterotaxy Syndrome; Homozygote; Humans; Infant, Newborn; Introns; Male; Membrane Proteins; Mice; Middle Aged; Models, Molecular; Mutation; Mutation, Missense; Oryzias; Pedigree; RNA Splicing; Situs Inversus

Chromosomal-Level Assembly of the Asian Seabass Genome Using Long Sequence Reads and Multi-layered Scaffolding. - Vij, Shubha; Kuhl, Heiner; Kuznetsova, Inna S; Komissarov, Aleksey; Yurchenko, Andrey A; Van Heusden, Peter; Singh, Siddharth; Thevasagayam, Natascha M; Prakki, Sai Rama Sridatta; Purushothaman, Kathiresan; Saju, Jolly M; Jiang, Junhui; et al. (PLoS Genet, 2016)
We report here the ~670 Mb genome assembly of the Asian seabass (Lates calcarifer), a tropical marine teleost. We used long-read sequencing augmented by transcriptomics, optical and genetic mapping along with shared synteny from closely related fish species to derive a chromosome-level assembly with a contig N50 size over 1 Mb and scaffold N50 size over 25 Mb that span ~90% of the genome. The population structure of L. calcarifer species complex was analyzed by re-sequencing 61 individuals representing various regions across the species' native range. SNP analyses identified high levels of genetic diversity and confirmed earlier indications of a population stratification comprising three clades with signs of admixture apparent in the South-East Asian population. The quality of the Asian seabass genome assembly far exceeds that of any other fish species, and will serve as a new standard for fish genomics.
Keywords: Animals; Bass; Chromosome Mapping; Genome; In Situ Hybridization, Fluorescence; Phylogeny

Comparative genomic study of arachnid immune systems indicates loss of beta-1,3-glucanase-related proteins and the immune deficiency pathway. - Bechsgaard, J; Vanthournout, B; Funch, P; Vestbo, S; Richard A Gibbs; Stephen Richards; Sanggaard, K W; Enghild, J J; Bilde, T (J Evol Biol, 2016)
Analyses of arthropod genomes have shown that the genes in the different innate humoral immune responses are conserved. These genes encode proteins that are involved in immune signalling pathways that recognize pathogens and activate immune responses. These immune responses include phagocytosis, encapsulation of the pathogen and production of effector molecules for pathogen elimination. So far, most studies have focused on insects leaving other major arthropod groups largely unexplored. Here, we annotate the immune-related genes of six arachnid genomes and present evidence for a conserved pattern of some immune genes, but also evolutionary changes in the arachnid immune system. Specifically, our results suggest that the family of recognition molecules of beta-1,3-glucanase-related proteins (βGRPs) and the genes from the immune deficiency (IMD) signalling pathway have been lost in a common ancestor of arachnids. These findings are consistent with previous work suggesting that the humoral immune effector proteins are constitutively produced in arachnids in contrast to insects, where these have to be induced. Further functional studies are needed to verify this. We further show that the full haemolymph clotting cascade found in the horseshoe crab is retrieved in most arachnid genomes. Tetranychus lacks at least one major component, although it is possible that this cascade could still function through recruitment of a different protein. The gel-forming protein in horseshoe crabs, coagulogen, was not recovered in any of the arachnid genomes; however, it is possible that the arachnid clot consists of a related protein, spätzle, that is present in all of the genomes.
Keywords: Amino Acid Sequence; Animals; Antimicrobial Cationic Peptides; Arachnida; Blood Proteins; Defensins; Gene Dosage; Genome; Genomics; Hemolymph; Immune System; Immunity, Innate; Protein Domains; Sequence Alignment; Signal Transduction

Comparative Genomics of a Parthenogenesis-Inducing Wolbachia Symbiont. - Lindsey, Amelia R I; Werren, John H; Stephen Richards; Stouthamer, Richard (G3 (Bethesda), 2016)
Wolbachia is an intracellular symbiont of invertebrates responsible for inducing a wide variety of phenotypes in its host. These host-Wolbachia relationships span the continuum from reproductive parasitism to obligate mutualism, and provide a unique system to study genomic changes associated with the evolution of symbiosis. We present the genome sequence from a parthenogenesis-inducing Wolbachia strain (wTpre) infecting the minute parasitoid wasp Trichogramma pretiosum The wTpre genome is the most complete parthenogenesis-inducing Wolbachia genome available to date. We used comparative genomics across 16 Wolbachia strains, representing five supergroups, to identify a core Wolbachia genome of 496 sets of orthologous genes. Only 14 of these sets are unique to Wolbachia when compared to other bacteria from the Rickettsiales. We show that the B supergroup of Wolbachia, of which wTpre is a member, contains a significantly higher number of ankyrin repeat-containing genes than other supergroups. In the wTpre genome, there is evidence for truncation of the protein coding sequences in 20% of ORFs, mostly as a result of frameshift mutations. The wTpre strain represents a conversion from cytoplasmic incompatibility to a parthenogenesis-inducing lifestyle, and is required for reproduction in the Trichogramma host it infects. We hypothesize that the large number of coding frame truncations has accompanied the change in reproductive mode of the wTpre strain.
Keywords: Animals; Ankyrin Repeat; Bacterial Proteins; Biological Evolution; Culicidae; Drosophila; Frameshift Mutation; Genome, Bacterial; Genomics; Host Specificity; Open Reading Frames; Parthenogenesis; Phylogeny; Symbiosis; Wasps; Wolbachia

Comparative Genomics of Two Closely Related Wolbachia with Different Reproductive Effects on Hosts. - Newton, Irene L G; Clark, Michael E; Kent, Bethany N; Bordenstein, Seth R; Qu, Jiaxin; Stephen Richards; Kelkar, Yogeshwar D; Werren, John H (Genome Biol Evol, 2016)
Wolbachia pipientis are obligate intracellular bacteria commonly found in many arthropods. They can induce various reproductive alterations in hosts, including cytoplasmic incompatibility, male-killing, feminization, and parthenogenetic development, and can provide host protection against some viruses and other pathogens. Wolbachia differ from many other primary endosymbionts in arthropods because they undergo frequent horizontal transmission between hosts and are well known for an abundance of mobile elements and relatively high recombination rates. Here, we compare the genomes of two closely related Wolbachia (with 0.57% genome-wide synonymous divergence) that differ in their reproductive effects on hosts. wVitA induces a sperm-egg incompatibility (also known as cytoplasmic incompatibility) in the parasitoid insect Nasonia vitripennis, whereas wUni causes parthenogenetic development in a different parasitoid, Muscidifurax uniraptor Although these bacteria are closely related, the genomic comparison reveals rampant rearrangements, protein truncations (particularly in proteins predicted to be secreted), and elevated substitution rates. These changes occur predominantly in the wUni lineage, and may be due in part to adaptations by wUni to a new host environment, or its phenotypic shift to parthenogenesis induction. However, we conclude that the approximately 8-fold elevated synonymous substitution rate in wUni is due to a either an elevated mutation rate or a greater number of generations per year in wUni, which occurs in semitropical host species. We identify a set of genes whose loss or pseudogenization in the wUni lineage implicates them in the phenotypic shift from cytoplasmic incompatibility to parthenogenesis induction. Finally, comparison of these closely related strains allows us to determine the fine-scale mutation patterns in Wolbachia Although Wolbachia are AT rich, mutation probabilities estimated from 4-fold degenerate sites are not AT biased, and predict an equilibrium AT content much less biased than observed (57-50% AT predicted vs. 76% current content at degenerate sites genome wide). The contrast suggests selection for increased AT content within Wolbachia genomes.
Keywords: Animals; Arthropods; Cytoplasm; Drosophila; Genome, Bacterial; Genomics; Host Specificity; Male; Mutation; Phylogeny; Reproduction; Selection, Genetic; Wolbachia

A comprehensive transcriptional map of primate brain development. - Bakken, Trygve E; Miller, Jeremy A; Ding, Song-Lin; Sunkin, Susan M; Smith, Kimberly A; Ng, Lydia; Szafer, Aaron; Dalley, Rachel A; Royall, Joshua J; Lemon, Tracy; Shapouri, Sheila; Aiona, Kaylynn; et al. (Nature, 2016)
The transcriptional underpinnings of brain development remain poorly understood, particularly in humans and closely related non-human primates. We describe a high-resolution transcriptional atlas of rhesus monkey (Macaca mulatta) brain development that combines dense temporal sampling of prenatal and postnatal periods with fine anatomical division of cortical and subcortical regions associated with human neuropsychiatric disease. Gene expression changes more rapidly before birth, both in progenitor cells and maturing neurons. Cortical layers and areas acquire adult-like molecular profiles surprisingly late in postnatal development. Disparate cell populations exhibit distinct developmental timing of gene expression, but also unexpected synchrony of processes underlying neural circuit construction including cell projection and adhesion. Candidate risk genes for neurodevelopmental disorders including primary microcephaly, autism spectrum disorder, intellectual disability, and schizophrenia show disease-specific spatiotemporal enrichment within developing neocortex. Human developmental expression trajectories are more similar to monkey than rodent, although approximately 9% of genes show human-specific regulation with evidence for prolonged maturation or neoteny compared to monkey.
Keywords: Aging; Animals; Autism Spectrum Disorder; Brain; Cell Adhesion; Conserved Sequence; Female; Humans; Intellectual Disability; Macaca mulatta; Male; Microcephaly; Neocortex; Neurodevelopmental Disorders; Neurogenesis; Risk Factors; Schizophrenia; Spatio-Temporal Analysis; Species Specificity; Transcription, Genetic; Transcriptome

Conditional knockout of retinal determination genes in differentiating cells in Drosophila. - Jin, Meng; Eblimit, Aiden; Pulikkathara, Merlyn; Corr, Stuart; Rui Chen; Mardon, Graeme (FEBS J, 2016)
Conditional gene knockout in postmitotic cells is a valuable technique which allows the study of gene function with spatiotemporal control. Surprisingly, in contrast to its long-term and extensive use in mouse studies, this technology is lacking in Drosophila. Here, we use a novel method for generating complete loss of eyes absent (eya) or sine oculis (so) function in postmitotic cells posterior to the morphogenetic furrow (MF). Specifically, genomic rescue constructs with flippase recognition target (FRT) sequences flanking essential exons are used to generate conditional null alleles. By removing gene function in differentiating cells, we show that eya and so are dispensable for larval photoreceptor differentiation, but are required for differentiation during pupal development. Both eya and so are necessary for photoreceptor survival and the apoptosis caused by loss of eya or so function is likely a secondary consequence of inappropriate differentiation. We also confirm their requirement for cone cell development and reveal a novel role in interommatidial bristle (IOB) formation. In addition, so is required for normal eye disc morphology. This is the first report of a knockout method to study eya and so function in postmitotic cells. This technology will open the door to a large array of new functional studies in virtually any tissue and at any stage of development or in adults.
Keywords: Alleles; Animals; Cell Differentiation; Drosophila; Drosophila Proteins; Eye; Eye Proteins; Gene Knockout Techniques; Homeodomain Proteins; Larva; Photoreceptor Cells, Invertebrate; Retina

Copy-Number Variation Contributes to the Mutational Load of Bardet-Biedl Syndrome. - Lindstrand, Anna; Frangakis, Stephan; Carvalho, Claudia M B; Richardson, Ellen B; McFadden, Kelsey A; Willer, Jason R; Pehlivan, Davut; Liu, Pengfei; Pediaditakis, Igor L; Aniko Sabo; Lewis, Richard Alan; Banin, Eyal; et al. (Am J Hum Genet, 2016)
Bardet-Biedl syndrome (BBS) is a defining ciliopathy, notable for extensive allelic and genetic heterogeneity, almost all of which has been identified through sequencing. Recent data have suggested that copy-number variants (CNVs) also contribute to BBS. We used a custom oligonucleotide array comparative genomic hybridization (aCGH) covering 20 genes that encode intraflagellar transport (IFT) components and 74 ciliopathy loci to screen 92 unrelated individuals with BBS, irrespective of their known mutational burden. We identified 17 individuals with exon-disruptive CNVs (18.5%), including 13 different deletions in eight BBS genes (BBS1, BBS2, ARL6/BBS3, BBS4, BBS5, BBS7, BBS9, and NPHP1) and a deletion and a duplication in other ciliopathy-associated genes (ALMS1 and NPHP4, respectively). By contrast, we found a single heterozygous exon-disruptive event in a BBS-associated gene (BBS9) in 229 control subjects. Superimposing these data with resequencing revealed CNVs to (1) be sufficient to cause disease, (2) Mendelize heterozygous deleterious alleles, and (3) contribute oligogenic alleles by combining point mutations and exonic CNVs in multiple genes. Finally, we report a deletion and a splice site mutation in IFT74, inherited under a recessive paradigm, defining a candidate BBS locus. Our data suggest that CNVs contribute pathogenic alleles to a substantial fraction of BBS-affected individuals and highlight how either deletions or point mutations in discrete splice isoforms can induce hypomorphic mutations in genes otherwise intolerant to deleterious variation. Our data also suggest that CNV analyses and resequencing studies unbiased for previous mutational burden is necessary to delineate the complexity of disease architecture.
Keywords: Adolescent; Adult; Alleles; Animals; Bardet-Biedl Syndrome; Child; Child, Preschool; Chromosome Breakpoints; Cytoskeletal Proteins; DNA Copy Number Variations; Exons; Female; Gastrulation; Genes, Recessive; Humans; Infant; Male; Mutation; Pedigree; Young Adult; Zebrafish; Zebrafish Proteins

Cross-species identification of genomic drivers of squamous cell carcinoma development across preneoplastic intermediates. - Chitsazzadeh, Vida; Coarfa, Cristian; Drummond, Jennifer A; Nguyen, Tri; Joseph, Aaron; Chilukuri, Suneel; Charpiot, Elizabeth; Adelmann, Charles H; Ching, Grace; Nguyen, Tran N; Nicholas, Courtney; Thomas, Valencia D; et al. (Nat Commun, 2016)
Cutaneous squamous cell carcinoma (cuSCC) comprises 15-20% of all skin cancers, accounting for over 700,000 cases in USA annually. Most cuSCC arise in association with a distinct precancerous lesion, the actinic keratosis (AK). To identify potential targets for molecularly targeted chemoprevention, here we perform integrated cross-species genomic analysis of cuSCC development through the preneoplastic AK stage using matched human samples and a solar ultraviolet radiation-driven Hairless mouse model. We identify the major transcriptional drivers of this progression sequence, showing that the key genomic changes in cuSCC development occur in the normal skin to AK transition. Our data validate the use of this ultraviolet radiation-driven mouse cuSCC model for cross-species analysis and demonstrate that cuSCC bears deep molecular similarities to multiple carcinogen-driven SCCs from diverse sites, suggesting that cuSCC may serve as an effective, accessible model for multiple SCC types and that common treatment and prevention strategies may be feasible.
Keywords: Animals; Antineoplastic Agents; Carcinogenesis; Carcinoma, Squamous Cell; Disease Progression; DNA Mutational Analysis; Exome Sequencing; Female; Gene Expression Profiling; Genomics; High-Throughput Nucleotide Sequencing; Humans; Keratosis, Actinic; Mice; Mice, Hairless; Molecular Targeted Therapy; Precancerous Conditions; Sequence Analysis, RNA; Skin; Skin Neoplasms; Ultraviolet Rays

The Ensembl gene annotation system. - Aken, Bronwen L; Ayling, Sarah; Barrell, Daniel; Clarke, Laura; Curwen, Valery; Fairley, Susan; Fernandez Banet, Julio; Billis, Konstantinos; García Girón, Carlos; Hourlier, Thibaut; Howe, Kevin; Kähäri, Andreas; et al. (Database (Oxford), 2016)
The Ensembl gene annotation system has been used to annotate over 70 different vertebrate species across a wide range of genome projects. Furthermore, it generates the automatic alignment-based annotation for the human and mouse GENCODE gene sets. The system is based on the alignment of biological sequences, including cDNAs, proteins and RNA-seq reads, to the target genome in order to construct candidate transcript models. Careful assessment and filtering of these candidate transcripts ultimately leads to the final gene set, which is made available on the Ensembl website. Here, we describe the annotation process in detail.Database URL: http://www.ensembl.org/index.html.
Keywords: Animals; Databases, Nucleic Acid; Databases, Protein; Humans; Internet; Mice; Molecular Sequence Annotation

Evolutionary and developmental implications of asymmetric brain folding in a large primate pedigree. - Atkinson, Elizabeth G; Jeffrey Rogers; Cheverud, James M (Evolution, 2016)
Bilateral symmetry is a fundamental property of the vertebrate central nervous system. Local deviations from symmetry provide various types of information about the development, evolution, and function of elements within the CNS, especially the cerebral hemispheres. Here, we quantify the pattern and extent of asymmetry in cortical folding within the cerebrum of Papio baboons and assess the evolutionary and developmental implications of the findings. Analyses of directional asymmetry show a population-level trend in length measurements indicating that baboons are genetically predisposed to be asymmetrical, with the right side longer than the left in the anterior cerebrum while the left side is longer than the right posteriorly. We also find a corresponding bias to display a right frontal petalia (overgrowth of the anterior pole of the cerebral cortex on the right side). By quantifying fluctuating asymmetry, we assess canalization of brain features and the susceptibility of the baboon brain to developmental perturbations. We find that features are differentially canalized depending on their ontogenetic timing. We further deduce that development of the two hemispheres is to some degree independent. This independence has important implications for the evolution of cerebral hemispheres and their separate specialization. Asymmetry is a major feature of primate brains and is characteristic of both brain structure and function.
Keywords: Animals; Biological Evolution; Cerebrum; Female; Male; Pedigree; Primates

Functional annotation of rare gene aberration drivers of pancreatic cancer. - Tsang, Yiu Huen; Dogruluk, Turgut; Tedeschi, Philip M; Wardwell-Ozgo, Joanna; Lu, Hengyu; Espitia, Maribel; Nair, Nikitha; Minelli, Rosalba; Chong, Zechen; Chen, Fengju; Chang, Qing Edward; Dennison, Jennifer B; et al. (Nat Commun, 2016)
As we enter the era of precision medicine, characterization of cancer genomes will directly influence therapeutic decisions in the clinic. Here we describe a platform enabling functionalization of rare gene mutations through their high-throughput construction, molecular barcoding and delivery to cancer models for in vivo tumour driver screens. We apply these technologies to identify oncogenic drivers of pancreatic ductal adenocarcinoma (PDAC). This approach reveals oncogenic activity for rare gene aberrations in genes including NAD Kinase (NADK), which regulates NADP(H) homeostasis and cellular redox state. We further validate mutant NADK, whose expression provides gain-of-function enzymatic activity leading to a reduction in cellular reactive oxygen species and tumorigenesis, and show that depletion of wild-type NADK in PDAC cell lines attenuates cancer cell growth in vitro and in vivo. These data indicate that annotating rare aberrations can reveal important cancer signalling pathways representing additional therapeutic targets.
Keywords: Animals; Carcinogenesis; Cell Line, Tumor; Female; Humans; Mice; Mice, Nude; Mutation; Pancreatic Neoplasms; Phosphotransferases (Alcohol Group Acceptor); Reactive Oxygen Species

Genome of the Asian longhorned beetle (Anoplophora glabripennis), a globally significant invasive species, reveals key functional and evolutionary innovations at the beetle-plant interface. - McKenna, Duane D; Scully, Erin D; Pauchet, Yannick; Hoover, Kelli; Kirsch, Roy; Geib, Scott M; Mitchell, Robert F; Waterhouse, Robert M; Ahn, Seung-Joon; Arsala, Deanna; Benoit, Joshua B; Blackmon, Heath; et al. (Genome Biol, 2016)
BACKGROUND: Relatively little is known about the genomic basis and evolution of wood-feeding in beetles. We undertook genome sequencing and annotation, gene expression assays, studies of plant cell wall degrading enzymes, and other functional and comparative studies of the Asian longhorned beetle, Anoplophora glabripennis, a globally significant invasive species capable of inflicting severe feeding damage on many important tree species. Complementary studies of genes encoding enzymes involved in digestion of woody plant tissues or detoxification of plant allelochemicals were undertaken with the genomes of 14 additional insects, including the newly sequenced emerald ash borer and bull-headed dung beetle. RESULTS: The Asian longhorned beetle genome encodes a uniquely diverse arsenal of enzymes that can degrade the main polysaccharide networks in plant cell walls, detoxify plant allelochemicals, and otherwise facilitate feeding on woody plants. It has the metabolic plasticity needed to feed on diverse plant species, contributing to its highly invasive nature. Large expansions of chemosensory genes involved in the reception of pheromones and plant kairomones are consistent with the complexity of chemical cues it uses to find host plants and mates. CONCLUSIONS: Amplification and functional divergence of genes associated with specialized feeding on plants, including genes originally obtained via horizontal gene transfer from fungi and bacteria, contributed to the addition, expansion, and enhancement of the metabolic repertoire of the Asian longhorned beetle, certain other phytophagous beetles, and to a lesser degree, other phytophagous insects. Our results thus begin to establish a genomic basis for the evolutionary success of beetles on plants.
Keywords: Animals; Coleoptera; Evolution, Molecular; Gene Transfer, Horizontal; Genome, Insect; Host-Parasite Interactions; Introduced Species; Larva; Sequence Analysis, DNA; Trees

Genome Sequencing of the Phytoseiid Predatory Mite Metaseiulus occidentalis Reveals Completely Atomized Hox Genes and Superdynamic Intron Evolution. - Hoy, Marjorie A; Waterhouse, Robert M; Wu, Ke; Estep, Alden S; Ioannidis, Panagiotis; Palmer, William J; Pomerantz, Aaron F; Simão, Felipe A; Thomas, Jainy; Jiggins, Francis M; Murphy, Terence D; Pritham, Ellen J; et al. (Genome Biol Evol, 2016)
Metaseiulus occidentalis is an eyeless phytoseiid predatory mite employed for the biological control of agricultural pests including spider mites. Despite appearances, these predator and prey mites are separated by some 400 Myr of evolution and radically different lifestyles. We present a 152-Mb draft assembly of the M. occidentalis genome: Larger than that of its favored prey, Tetranychus urticae, but considerably smaller than those of many other chelicerates, enabling an extremely contiguous and complete assembly to be built-the best arachnid to date. Aided by transcriptome data, genome annotation cataloged 18,338 protein-coding genes and identified large numbers of Helitron transposable elements. Comparisons with other arthropods revealed a particularly dynamic and turbulent genomic evolutionary history. Its genes exhibit elevated molecular evolution, with strikingly high numbers of intron gains and losses, in stark contrast to the deer tick Ixodes scapularis Uniquely among examined arthropods, this predatory mite's Hox genes are completely atomized, dispersed across the genome, and it encodes five copies of the normally single-copy RNA processing Dicer-2 gene. Examining gene families linked to characteristic biological traits of this tiny predator provides initial insights into processes of sex determination, development, immune defense, and how it detects, disables, and digests its prey. As the first reference genome for the Phytoseiidae, and for any species with the rare sex determination system of parahaploidy, the genome of the western orchard predatory mite improves genomic sampling of chelicerates and provides invaluable new resources for functional genomic analyses of this family of agriculturally important mites.
Keywords: Acari; Animals; Genes, Homeobox; Genome; Genomics; High-Throughput Nucleotide Sequencing; Introns; Pest Control, Biological; Tetranychidae; Transcriptome

Genome-culture coevolution promotes rapid divergence of killer whale ecotypes. - Foote, Andrew D; Vijay, Nagarjun; Ávila-Arcos, María C; Baird, Robin W; Durban, John W; Fumagalli, Matteo; Richard A Gibbs; Hanson, M Bradley; Korneliussen, Thorfinn S; Martin, Michael D; Robertson, Kelly M; Sousa, Vitor C; et al. (Nat Commun, 2016)
Analysing population genomic data from killer whale ecotypes, which we estimate have globally radiated within less than 250,000 years, we show that genetic structuring including the segregation of potentially functional alleles is associated with socially inherited ecological niche. Reconstruction of ancestral demographic history revealed bottlenecks during founder events, likely promoting ecological divergence and genetic drift resulting in a wide range of genome-wide differentiation between pairs of allopatric and sympatric ecotypes. Functional enrichment analyses provided evidence for regional genomic divergence associated with habitat, dietary preferences and post-zygotic reproductive isolation. Our findings are consistent with expansion of small founder groups into novel niches by an initial plastic behavioural response, perpetuated by social learning imposing an altered natural selection regime. The study constitutes an important step towards an understanding of the complex interaction between demographic history, culture, ecological adaptation and evolution at the genomic level.
Keywords: Adaptation, Biological; Animals; Biopsy; Ecotype; Evolution, Molecular; Female; Gene-Environment Interaction; Genetic Drift; Genetic Speciation; Genetic Variation; Genetics, Population; Genome; Genomics; Male; Phylogeny; Reproductive Isolation; Selection, Genetic; Skin; Sympatry; Whale, Killer

Genomic analyses identify molecular subtypes of pancreatic cancer. - Bailey, Peter; Chang, David K; Nones, Katia; Johns, Amber L; Patch, Ann-Marie; Marie-Claude Gingras; Miller, David K; Christ, Angelika N; Bruxner, Tim J C; Quinn, Michael C; Nourse, Craig; Murtaugh, L Charles; et al. (Nature, 2016)
Integrated genomic analysis of 456 pancreatic ductal adenocarcinomas identified 32 recurrently mutated genes that aggregate into 10 pathways: KRAS, TGF-β, WNT, NOTCH, ROBO/SLIT signalling, G1/S transition, SWI-SNF, chromatin modification, DNA repair and RNA processing. Expression analysis defined 4 subtypes: (1) squamous; (2) pancreatic progenitor; (3) immunogenic; and (4) aberrantly differentiated endocrine exocrine (ADEX) that correlate with histopathological characteristics. Squamous tumours are enriched for TP53 and KDM6A mutations, upregulation of the TP63∆N transcriptional network, hypermethylation of pancreatic endodermal cell-fate determining genes and have a poor prognosis. Pancreatic progenitor tumours preferentially express genes involved in early pancreatic development (FOXA2/3, PDX1 and MNX1). ADEX tumours displayed upregulation of genes that regulate networks involved in KRAS activation, exocrine (NR5A2 and RBPJL), and endocrine differentiation (NEUROD1 and NKX2-2). Immunogenic tumours contained upregulated immune networks including pathways involved in acquired immune suppression. These data infer differences in the molecular evolution of pancreatic cancer subtypes and identify opportunities for therapeutic development.
Keywords: Animals; Basic Helix-Loop-Helix Transcription Factors; Carcinoma, Pancreatic Ductal; Cell Line, Tumor; DNA Methylation; DNA-Binding Proteins; Gene Expression Regulation, Neoplastic; Gene Regulatory Networks; Genes, Neoplasm; Genome, Human; Genomics; Hepatocyte Nuclear Factor 3-beta; Hepatocyte Nuclear Factor 3-gamma; Histone Demethylases; Homeobox Protein Nkx-2.2; Homeodomain Proteins; Humans; Mice; Mutation; Nuclear Proteins; Pancreatic Neoplasms; Prognosis; Receptors, Cytoplasmic and Nuclear; Survival Analysis; Trans-Activators; Transcription Factors; Transcription, Genetic; Transcriptome; Tumor Suppressor Protein p53; Tumor Suppressor Proteins; Zebrafish Proteins

The genomic basis of circadian and circalunar timing adaptations in a midge. - Kaiser, Tobias S; Poehn, Birgit; Szkiba, David; Preussner, Marco; Fritz J Sedlazeck; Zrim, Alexander; Neumann, Tobias; Nguyen, Lam-Tung; Betancourt, Andrea J; Hummel, Thomas; Vogel, Heiko; Dorner, Silke; et al. (Nature, 2016)
Organisms use endogenous clocks to anticipate regular environmental cycles, such as days and tides. Natural variants resulting in differently timed behaviour or physiology, known as chronotypes in humans, have not been well characterized at the molecular level. We sequenced the genome of Clunio marinus, a marine midge whose reproduction is timed by circadian and circalunar clocks. Midges from different locations show strain-specific genetic timing adaptations. We examined genetic variation in five C. marinus strains from different locations and mapped quantitative trait loci for circalunar and circadian chronotypes. The region most strongly associated with circadian chronotypes generates strain-specific differences in the abundance of calcium/calmodulin-dependent kinase II.1 (CaMKII.1) splice variants. As equivalent variants were shown to alter CaMKII activity in Drosophila melanogaster, and C. marinus (Cma)-CaMKII.1 increases the transcriptional activity of the dimer of the circadian proteins Cma-CLOCK and Cma-CYCLE, we suggest that modulation of alternative splicing is a mechanism for natural adaptation in circadian timing.
Keywords: Acclimatization; Alternative Splicing; Animals; Calcium-Calmodulin-Dependent Protein Kinase Type 2; Chironomidae; Circadian Clocks; Circadian Rhythm; CLOCK Proteins; Drosophila melanogaster; Genetic Association Studies; Genetic Variation; Genome, Insect; Genomics; Male; Moon; Phenotype; Quantitative Trait Loci; Reproduction; Species Specificity; Tidal Waves; Time Factors; Transcription, Genetic

Genomics of Natural Populations: How Differentially Expressed Genes Shape the Evolution of Chromosomal Inversions in Drosophila pseudoobscura. - Fuller, Zachary L; Haynes, Gwilym D; Stephen Richards; Schaeffer, Stephen W (Genetics, 2016)
Chromosomal rearrangements can shape the structure of genetic variation in the genome directly through alteration of genes at breakpoints or indirectly by holding combinations of genetic variants together due to reduced recombination. The third chromosome of Drosophila pseudoobscura is a model system to test hypotheses about how rearrangements are established in populations because its third chromosome is polymorphic for >30 gene arrangements that were generated by a series of overlapping inversion mutations. Circumstantial evidence has suggested that these gene arrangements are selected. Despite the expected homogenizing effects of extensive gene flow, the frequencies of arrangements form gradients or clines in nature, which have been stable since the system was first described >80 years ago. Furthermore, multiple arrangements exist at appreciable frequencies across several ecological niches providing the opportunity for heterokaryotypes to form. In this study, we tested whether genes are differentially expressed among chromosome arrangements in first instar larvae, adult females and males. In addition, we asked whether transcriptional patterns in heterokaryotypes are dominant, semidominant, overdominant, or underdominant. We find evidence for a significant abundance of differentially expressed genes across the inverted regions of the third chromosome, including an enrichment of genes involved in sensory perception for males. We find the majority of loci show additivity in heterokaryotypes. Our results suggest that multiple genes have expression differences among arrangements that were either captured by the original inversion mutation or accumulated after it reached polymorphic frequencies, providing a potential source of genetic variation for selection to act upon. These data suggest that the inversions are favored because of their indirect effect of recombination suppression that has held different combinations of differentially expressed genes together in the various gene arrangement backgrounds.
Keywords: Animals; Biological Evolution; Chromosome Inversion; Chromosomes, Insect; Drosophila; Female; Gene Expression Regulation; Gene Flow; Gene Order; Genomics; Male; Metagenomics; Transcriptome

Hypomorphic mutations identified in the candidate Leber congenital amaurosis gene CLUAP1. - Soens, Zachry T; Li, Yuanyuan; Zhao, Li; Eblimit, Aiden; Dharmat, Rachayata; Yumei Li; Chen, Yiyun; Naqeeb, Mohammed; Fajardo, Norma; Lopez, Irma; Sun, Zhaoxia; Koenekoop, Robert K; et al. (Genet Med, 2016)
PURPOSE: Leber congenital amaurosis (LCA) is an early-onset form of retinal degeneration. Six of the 22 known LCA genes encode photoreceptor ciliary proteins. Despite the identification of 22 LCA genes, the genetic basis of ~30% of LCA patients remains unknown. We sought to investigate the cause of disease in the remaining 30% by examining cilia-associated genes. METHODS: Whole-exome sequencing was performed on an LCA cohort of 212 unsolved probands previously screened for mutations in known retinal-disease genes. Immunohistochemistry using mouse retinas was used to confirm protein localization and zebrafish were used to perform rescue experiments. RESULTS: A homozygous nonsynonymous mutation was found in a single proband in CLUAP1, a gene required for ciliogenesis and cilia maintenance. Cluap1 knockout zebrafish exhibit photoreceptor cell death as early as 5 days after fertilization, and rescue experiments revealed that our proband's mutation is significantly hypomorphic. CONCLUSION: Consistent with the knowledge that CLUAP1 plays an important role in cilia function and that cilia are critical to photoreceptor function, our results indicate that hypomorphic mutations in CLUAP1 can result in dysfunctional photoreceptors without systemic abnormalities. This is the first report linking mutations in CLUAP1 to human disease and establishes CLUAP1 as a candidate LCA gene.Genet Med 18 10, 1044-1051.
Keywords: Animals; Antigens, Neoplasm; Child, Preschool; Cilia; Exome; Female; High-Throughput Nucleotide Sequencing; Humans; Leber Congenital Amaurosis; Male; Mutation; Photoreceptor Cells; Retinal Degeneration; Zebrafish

Identification of a RAI1-associated disease network through integration of exome sequencing, transcriptomics, and 3D genomics. - Loviglio, Maria Nicla; Beck, Christine R; White, Janson J; Leleu, Marion; Harel, Tamar; Guex, Nicolas; Niknejad, Anne; Bi, Weimin; Chen, Edward S; Crespo, Isaac; Yan, Jiong; Charng, Wu-Lin; et al. (Genome Med, 2016)
BACKGROUND: Smith-Magenis syndrome (SMS) is a developmental disability/multiple congenital anomaly disorder resulting from haploinsufficiency of RAI1. It is characterized by distinctive facial features, brachydactyly, sleep disturbances, and stereotypic behaviors. METHODS: We investigated a cohort of 15 individuals with a clinical suspicion of SMS who showed neither deletion in the SMS critical region nor damaging variants in RAI1 using whole exome sequencing. A combination of network analysis (co-expression and biomedical text mining), transcriptomics, and circularized chromatin conformation capture (4C-seq) was applied to verify whether modified genes are part of the same disease network as known SMS-causing genes. RESULTS: Potentially deleterious variants were identified in nine of these individuals using whole-exome sequencing. Eight of these changes affect KMT2D, ZEB2, MAP2K2, GLDC, CASK, MECP2, KDM5C, and POGZ, known to be associated with Kabuki syndrome 1, Mowat-Wilson syndrome, cardiofaciocutaneous syndrome, glycine encephalopathy, mental retardation and microcephaly with pontine and cerebellar hypoplasia, X-linked mental retardation 13, X-linked mental retardation Claes-Jensen type, and White-Sutton syndrome, respectively. The ninth individual carries a de novo variant in JAKMIP1, a regulator of neuronal translation that was recently found deleted in a patient with autism spectrum disorder. Analyses of co-expression and biomedical text mining suggest that these pathologies and SMS are part of the same disease network. Further support for this hypothesis was obtained from transcriptome profiling that showed that the expression levels of both Zeb2 and Map2k2 are perturbed in Rai1 mice. As an orthogonal approach to potentially contributory disease gene variants, we used chromatin conformation capture to reveal chromatin contacts between RAI1 and the loci flanking ZEB2 and GLDC, as well as between RAI1 and human orthologs of the genes that show perturbed expression in our Rai1 mouse model. CONCLUSIONS: These holistic studies of RAI1 and its interactions allow insights into SMS and other disorders associated with intellectual disability and behavioral abnormalities. Our findings support a pan-genomic approach to the molecular diagnosis of a distinctive disorder.
Keywords: Animals; Embryo, Mammalian; Exome; Female; Gene Regulatory Networks; Genomics; Humans; Male; Mice; Mice, Inbred C57BL; Mice, Knockout; Mutation; Phenotype; Real-Time Polymerase Chain Reaction; Reverse Transcriptase Polymerase Chain Reaction; RNA, Messenger; Smith-Magenis Syndrome; Trans-Activators; Transcription Factors; Transcriptome

Identification of novel direct targets of Drosophila Sine oculis and Eyes absent by integration of genome-wide data sets. - Jin, Meng; Aibar, Sara; Ge, Zhongqi; Rui Chen; Aerts, Stein; Mardon, Graeme (Dev Biol, 2016)
Drosophila eye development is a complex process that involves many transcription factors (TFs) and interactions with their cofactors and targets. The TF Sine oculis (So) and its cofactor Eyes absent (Eya) are highly conserved and are both necessary and sufficient for eye development. Despite their many important roles during development, the direct targets of So are still largely unknown. Therefore the So-dependent regulatory network governing eye determination and differentiation is poorly understood. In this study, we intersected gene expression profiles of so or eya mutant eye tissue prepared from three different developmental stages and identified 1731 differentially expressed genes across the Drosophila genome. A combination of co-expression analyses and motif discovery identified a set of twelve putative direct So targets, including three known and nine novel targets. We also used our previous So ChIP-seq data to assess motif predictions for So and identified a canonical So binding motif. Finally, we performed in vivo enhancer reporter assays to test predicted enhancers from six candidate target genes and find that at least one enhancer from each gene is expressed in the developing eye disc and that their expression patterns overlap with that of So. We furthermore confirmed that the expression level of predicted direct So targets, for which antibodies are available, are reduced in so or eya post-mitotic knockout eye discs. In summary, we expand the set of putative So targets and show for the first time that the combined use of expression profiling of so with its cofactor eya is an effective method to identify novel So targets. Moreover, since So is highly conserved throughout the metazoa, our results provide the basis for future functional studies in a wide variety of organisms.
Keywords: Amino Acid Motifs; Amino Acid Sequence; Animals; Chromatin Immunoprecipitation; Compound Eye, Arthropod; Consensus Sequence; Drosophila melanogaster; Drosophila Proteins; Eye Proteins; Gene Expression Regulation, Developmental; Gene Ontology; Genetic Association Studies; Genome-Wide Association Study; Homeodomain Proteins; Imaginal Discs; Larva; Pupa; RNA, Messenger; Transcription, Genetic; Transcriptome

Integrative subcellular proteomic analysis allows accurate prediction of human disease-causing genes. - Zhao, Li; Chen, Yiyun; Bajaj, Amol Onkar; Eblimit, Aiden; Xu, Mingchu; Soens, Zachry T; Wang, Feng; Ge, Zhongqi; Jung, Sung Yun; He, Feng; Yumei Li; Wensel, Theodore G; et al. (Genome Res, 2016)
Proteomic profiling on subcellular fractions provides invaluable information regarding both protein abundance and subcellular localization. When integrated with other data sets, it can greatly enhance our ability to predict gene function genome-wide. In this study, we performed a comprehensive proteomic analysis on the light-sensing compartment of photoreceptors called the outer segment (OS). By comparing with the protein profile obtained from the retina tissue depleted of OS, an enrichment score for each protein is calculated to quantify protein subcellular localization, and 84% accuracy is achieved compared with experimental data. By integrating the protein OS enrichment score, the protein abundance, and the retina transcriptome, the probability of a gene playing an essential function in photoreceptor cells is derived with high specificity and sensitivity. As a result, a list of genes that will likely result in human retinal disease when mutated was identified and validated by previous literature and/or animal model studies. Therefore, this new methodology demonstrates the synergy of combining subcellular fractionation proteomics with other omics data sets and is generally applicable to other tissues and diseases.
Keywords: Animals; Eye Proteins; Gene Expression Profiling; Humans; Mice; Photoreceptor Cells; Proteomics; Retinal Diseases; Transcriptome

Multifaceted biological insights from a draft genome sequence of the tobacco hornworm moth, Manduca sexta. - Kanost, Michael R; Arrese, Estela L; Cao, Xiaolong; Chen, Yun-Ru; Chellapilla, Sanjay; Goldsmith, Marian R; Grosse-Wilde, Ewald; Heckel, David G; Herndon, Nicolae; Jiang, Haobo; Papanicolaou, Alexie; Qu, Jiaxin; et al. (Insect Biochem Mol Biol, 2016)
Manduca sexta, known as the tobacco hornworm or Carolina sphinx moth, is a lepidopteran insect that is used extensively as a model system for research in insect biochemistry, physiology, neurobiology, development, and immunity. One important benefit of this species as an experimental model is its extremely large size, reaching more than 10 g in the larval stage. M. sexta larvae feed on solanaceous plants and thus must tolerate a substantial challenge from plant allelochemicals, including nicotine. We report the sequence and annotation of the M. sexta genome, and a survey of gene expression in various tissues and developmental stages. The Msex_1.0 genome assembly resulted in a total genome size of 419.4 Mbp. Repetitive sequences accounted for 25.8% of the assembled genome. The official gene set is comprised of 15,451 protein-coding genes, of which 2498 were manually curated. Extensive RNA-seq data from many tissues and developmental stages were used to improve gene models and for insights into gene expression patterns. Genome wide synteny analysis indicated a high level of macrosynteny in the Lepidoptera. Annotation and analyses were carried out for gene families involved in a wide spectrum of biological processes, including apoptosis, vacuole sorting, growth and development, structures of exoskeleton, egg shells, and muscle, vision, chemosensation, ion channels, signal transduction, neuropeptide signaling, neurotransmitter synthesis and transport, nicotine tolerance, lipid metabolism, and immunity. This genome sequence, annotation, and analysis provide an important new resource from a well-studied model insect species and will facilitate further biochemical and mechanistic experimental studies of many biological systems in insects.
Keywords: Animals; Gene Expression; Gene Expression Profiling; Genome, Insect; Larva; Manduca; Pupa; Sequence Analysis, DNA; Synteny

Mutations in POMGNT1 cause non-syndromic retinitis pigmentosa. - Xu, Mingchu; Yamada, Takeyuki; Sun, Zixi; Eblimit, Aiden; Lopez, Irma; Wang, Feng; Manya, Hiroshi; Xu, Shan; Zhao, Li; Yumei Li; Kimchi, Adva; Sharon, Dror; et al. (Hum Mol Genet, 2016)
A growing number of human diseases have been linked to defects in protein glycosylation that affects a wide range of organs. Among them, O-mannosylation is an unusual type of protein glycosylation that is largely restricted to the muscular and nerve system. Consistently, mutations in genes involved in the O-mannosylation pathway result in infantile-onset, severe developmental defects involving skeleton muscle, brain and eye, such as the muscle-eye-brain disease (MIM no. 253280). However, the functional importance of O-mannosylation in these tissues at later stages remains largely unknown. In our study, we have identified recessive mutations in POMGNT1, which encodes an essential component in O-mannosylation pathway, in three unrelated families with autosomal recessive retinitis pigmentosa (RP), but without extraocular involvement. Enzymatic assay of these mutant alleles demonstrate that they greatly reduce the POMGNT1 enzymatic activity and are likely to be hypomorphic. Immunohistochemistry shows that POMGNT1 is specifically expressed in photoreceptor basal body. Taken together, our work identifies a novel disease-causing gene for RP and indicates that proper protein O-mannosylation is not only essential for early organ development, but also important for maintaining survival and function of the highly specialized retinal cells at later stages.
Keywords: Adult; Aged; Animals; Cells, Cultured; Exome; Female; Genes, Recessive; Genetic Predisposition to Disease; Glycosylation; Humans; Male; Mice; Middle Aged; Mutation; N-Acetylglucosaminyltransferases; Pedigree; Photoreceptor Cells, Vertebrate; Retinitis Pigmentosa; Sequence Analysis, DNA

Mutations in REEP6 Cause Autosomal-Recessive Retinitis Pigmentosa. - Arno, Gavin; Agrawal, Smriti A; Eblimit, Aiden; Bellingham, James; Xu, Mingchu; Wang, Feng; Chakarova, Christina; Parfitt, David A; Lane, Amelia; Burgoyne, Thomas; Hull, Sarah; Carss, Keren J; et al. (Am J Hum Genet, 2016)
Retinitis pigmentosa (RP) is the most frequent form of inherited retinal dystrophy. RP is genetically heterogeneous and the genes identified to date encode proteins involved in a wide range of functional pathways, including photoreceptor development, phototransduction, the retinoid cycle, cilia, and outer segment development. Here we report the identification of biallelic mutations in Receptor Expression Enhancer Protein 6 (REEP6) in seven individuals with autosomal-recessive RP from five unrelated families. REEP6 is a member of the REEP/Yop1 family of proteins that influence the structure of the endoplasmic reticulum but is relatively unstudied. The six variants identified include three frameshift variants, two missense variants, and a genomic rearrangement that disrupts exon 1. Human 3D organoid optic cups were used to investigate REEP6 expression and confirmed the expression of a retina-specific isoform REEP6.1, which is specifically affected by one of the frameshift mutations. Expression of the two missense variants (c.383C>T [p.Pro128Leu] and c.404T>C [p.Leu135Pro]) and the REEP6.1 frameshift mutant in cultured cells suggest that these changes destabilize the protein. Furthermore, CRISPR-Cas9-mediated gene editing was used to produce Reep6 knock-in mice with the p.Leu135Pro RP-associated variant identified in one RP-affected individual. The homozygous knock-in mice mimic the clinical phenotypes of RP, including progressive photoreceptor degeneration and dysfunction of the rod photoreceptors. Therefore, our study implicates REEP6 in retinal homeostasis and highlights a pathway previously uncharacterized in retinal dystrophy.
Keywords: Adolescent; Alleles; Animals; Child; Child, Preschool; Eye Proteins; Female; Genes, Recessive; Humans; Induced Pluripotent Stem Cells; Male; Membrane Proteins; Membrane Transport Proteins; Mice; Mutation; Mutation, Missense; Phenotype; Photoreceptor Cells, Vertebrate; Retinitis Pigmentosa; Young Adult

Novel patient-derived xenograft and cell line models for therapeutic testing of pediatric liver cancer. - Bissig-Choisat, Beatrice; Kettlun-Leyton, Claudia; Legras, Xavier D; Zorman, Barry; Barzi, Mercedes; Chen, Leon L; Amin, Mansi D; Huang, Yung-Hsin; Pautler, Robia G; Hampton, Oliver A; Prakash, Masand M; Yang, Diane; et al. (J Hepatol, 2016)
BACKGROUND & AIMS: Pediatric liver cancer is a rare but serious disease whose incidence is rising, and for which the therapeutic options are limited. Development of more targeted, less toxic therapies is hindered by the lack of an experimental animal model that captures the heterogeneity and metastatic capability of these tumors. METHODS: Here we established an orthotopic engraftment technique to model a series of patient-derived tumor xenograft (PDTX) from pediatric liver cancers of all major histologic subtypes: hepatoblastoma, hepatocellular cancer and hepatocellular malignant neoplasm. We utilized standard (immuno) staining methods for histological characterization, RNA sequencing for gene expression profiling and genome sequencing for identification of druggable targets. We also adapted stem cell culturing techniques to derive two new pediatric cancer cell lines from the xenografted mice. RESULTS: The patient-derived tumor xenografts recapitulated the histologic, genetic, and biological characteristics-including the metastatic behavior-of the corresponding primary tumors. Furthermore, the gene expression profiles of the two new liver cancer cell lines closely resemble those of the primary tumors. Targeted therapy of PDTX from an aggressive hepatocellular malignant neoplasm with the MEK1 inhibitor trametinib and pan-class I PI3 kinase inhibitor NVP-BKM120 resulted in significant growth inhibition, thus confirming this PDTX model as a valuable tool to study tumor biology and patient-specific therapeutic responses. CONCLUSIONS: The novel metastatic xenograft model and the isogenic xenograft-derived cell lines described in this study provide reliable tools for developing mutation- and patient-specific therapies for pediatric liver cancer. LAY SUMMARY: Pediatric liver cancer is a rare but serious disease and no experimental animal model currently captures the complexity and metastatic capability of these tumors. We have established a novel animal model using human tumor tissue that recapitulates the genetic and biological characteristics of this cancer. We demonstrate that our patient-derived animal model, as well as two new cell lines, are useful tools for experimental therapies.
Keywords: Animals; Carcinoma, Hepatocellular; Cell Line, Tumor; Child; Disease Models, Animal; Heterografts; Humans; Liver Neoplasms; Mice; Neoplasm Transplantation; Xenograft Model Antitumor Assays

The population genomics of rhesus macaques (Macaca mulatta) based on whole-genome sequences. - Xue, Cheng; Raveendran, Muthuswamy; R. Alan Harris; Fawcett, Gloria L; Liu, Xiaoming; White, Simon; Dahdouli, Mahmoud; Rio Deiros, David; Below, Jennifer E; Salerno, William; Cox, Laura; Fan, Guoping; et al. (Genome Res, 2016)
Rhesus macaques (Macaca mulatta) are the most widely used nonhuman primate in biomedical research, have the largest natural geographic distribution of any nonhuman primate, and have been the focus of much evolutionary and behavioral investigation. Consequently, rhesus macaques are one of the most thoroughly studied nonhuman primate species. However, little is known about genome-wide genetic variation in this species. A detailed understanding of extant genomic variation among rhesus macaques has implications for the use of this species as a model for studies of human health and disease, as well as for evolutionary population genomics. Whole-genome sequencing analysis of 133 rhesus macaques revealed more than 43.7 million single-nucleotide variants, including thousands predicted to alter protein sequences, transcript splicing, and transcription factor binding sites. Rhesus macaques exhibit 2.5-fold higher overall nucleotide diversity and slightly elevated putative functional variation compared with humans. This functional variation in macaques provides opportunities for analyses of coding and noncoding variation, and its cellular consequences. Despite modestly higher levels of nonsynonymous variation in the macaques, the estimated distribution of fitness effects and the ratio of nonsynonymous to synonymous variants suggest that purifying selection has had stronger effects in rhesus macaques than in humans. Demographic reconstructions indicate this species has experienced a consistently large but fluctuating population size. Overall, the results presented here provide new insights into the population genomics of nonhuman primates and expand genomic information directly relevant to primate models of human disease.
Keywords: Animals; Evolution, Molecular; Female; Genetic Fitness; High-Throughput Nucleotide Sequencing; Macaca mulatta; Models, Animal; Polymorphism, Single Nucleotide; Population Density; Whole Genome Sequencing

Rare Functional Variant in TM2D3 is Associated with Late-Onset Alzheimer's Disease. - Jakobsdottir, Johanna; van der Lee, Sven J; Bis, Joshua C; Chouraki, Vincent; Li-Kroeger, David; Yamamoto, Shinya; Grove, Megan L; Naj, Adam; Vronskaya, Maria; Salazar, Jose L; DeStefano, Anita L; Brody, Jennifer A; et al. (PLoS Genet, 2016)
We performed an exome-wide association analysis in 1393 late-onset Alzheimer's disease (LOAD) cases and 8141 controls from the CHARGE consortium. We found that a rare variant (P155L) in TM2D3 was enriched in Icelanders (~0.5% versus <0.05% in other European populations). In 433 LOAD cases and 3903 controls from the Icelandic AGES sub-study, P155L was associated with increased risk and earlier onset of LOAD [odds ratio (95% CI) = 7.5 (3.5-15.9), p = 6.6x10-9]. Mutation in the Drosophila TM2D3 homolog, almondex, causes a phenotype similar to loss of Notch/Presenilin signaling. Human TM2D3 is capable of rescuing these phenotypes, but this activity is abolished by P155L, establishing it as a functionally damaging allele. Our results establish a rare TM2D3 variant in association with LOAD susceptibility, and together with prior work suggests possible links to the β-amyloid cascade.
Keywords: Age of Onset; Aged; Alleles; Alzheimer Disease; Amyloid beta-Protein Precursor; Animals; Apolipoproteins E; Drosophila melanogaster; Drosophila Proteins; Exome; Female; Genome-Wide Association Study; Genomics; Humans; Iceland; Intracellular Signaling Peptides and Proteins; Male; Membrane Proteins; Mutation; Phenotype; Receptors, Notch; Tropomyosin; White People

Recurrent De Novo and Biallelic Variation of ATAD3A, Encoding a Mitochondrial Membrane Protein, Results in Distinct Neurological Syndromes. - Harel, Tamar; Yoon, Wan Hee; Garone, Caterina; Gu, Shen; Coban-Akdemir, Zeynep; Eldomery, Mohammad K; Posey, Jennifer E; Jhangiani, Shalini N; Rosenfeld, Jill A; Cho, Megan T; Fox, Stephanie; Withers, Marjorie; et al. (Am J Hum Genet, 2016)
ATPase family AAA-domain containing protein 3A (ATAD3A) is a nuclear-encoded mitochondrial membrane protein implicated in mitochondrial dynamics, nucleoid organization, protein translation, cell growth, and cholesterol metabolism. We identified a recurrent de novo ATAD3A c.1582C>T (p.Arg528Trp) variant by whole-exome sequencing (WES) in five unrelated individuals with a core phenotype of global developmental delay, hypotonia, optic atrophy, axonal neuropathy, and hypertrophic cardiomyopathy. We also describe two families with biallelic variants in ATAD3A, including a homozygous variant in two siblings, and biallelic ATAD3A deletions mediated by nonallelic homologous recombination (NAHR) between ATAD3A and gene family members ATAD3B and ATAD3C. Tissue-specific overexpression of bor, the Drosophila mutation homologous to the human c.1582C>T (p.Arg528Trp) variant, resulted in a dramatic decrease in mitochondrial content, aberrant mitochondrial morphology, and increased autophagy. Homozygous null bor larvae showed a significant decrease of mitochondria, while overexpression of bor resulted in larger, elongated mitochondria. Finally, fibroblasts of an affected individual exhibited increased mitophagy. We conclude that the p.Arg528Trp variant functions through a dominant-negative mechanism that results in small mitochondria that trigger mitophagy, resulting in a reduction in mitochondrial content. ATAD3A variation represents an additional link between mitochondrial dynamics and recognizable neurological syndromes, as seen with MFN2, OPA1, DNM1L, and STAT2 mutations.
Keywords: Adenosine Triphosphatases; Adult; Alleles; Animals; ATPases Associated with Diverse Cellular Activities; Axons; Cardiomyopathies; Child; Child, Preschool; Developmental Disabilities; DNA Copy Number Variations; Drosophila melanogaster; Female; Fibroblasts; Homozygote; Humans; Infant; Infant, Newborn; Male; Membrane Proteins; Mitochondria; Mitochondrial Proteins; Muscle Hypotonia; Muscles; Mutation; Nervous System Diseases; Neurons; Optic Atrophy; Phenotype; Polymorphism, Single Nucleotide; Syndrome; Young Adult

Single-cell isolation by a modular single-cell pipette for RNA-sequencing. - Zhang, Kai; Gao, Min; Chong, Zechen; Li, Ying; Han, Xin; Rui Chen; Qin, Lidong (Lab Chip, 2016)
Single-cell transcriptome sequencing highly requires a convenient and reliable method to rapidly isolate a live cell into a specific container such as a PCR tube. Here, we report a modular single-cell pipette (mSCP) consisting of three modular components, a SCP-Tip, an air-displacement pipette (ADP), and ADP-Tips, that can be easily assembled, disassembled, and reassembled. By assembling the SCP-Tip containing a hydrodynamic trap, the mSCP can isolate single cells from 5-10 cells per μL of cell suspension. The mSCP is compatible with microscopic identification of captured single cells to finally achieve 100% single-cell isolation efficiency. The isolated live single cells are in submicroliter volumes and well suitable for single-cell PCR analysis and RNA-sequencing. The mSCP possesses merits of convenience, rapidness, and high efficiency, making it a powerful tool to isolate single cells for transcriptome analysis.
Keywords: Animals; Cell Line, Tumor; Cell Separation; Mice; NIH 3T3 Cells; Sequence Analysis, RNA; Single-Cell Analysis

Sources of variation in hair cortisol in wild and captive non-human primates. - Fourie, Nicolaas H; Brown, Janine L; Jolly, Clifford J; Phillips-Conroy, Jane E; Jeffrey Rogers; Bernstein, Robin M (Zoology (Jena), 2016)
Hair cortisol analysis is a potentially powerful tool for evaluating adrenal function and chronic stress. However, the technique has only recently been applied widely to studies of wildlife, including primates, and there are numerous practical and technical factors that should be considered to ensure good quality data and the validity of results and conclusions. Here we report on various intrinsic and extrinsic sources of variation in hair cortisol measurements in wild and captive primates. Hair samples from both wild and captive primates revealed that age and sex can affect hair cortisol concentrations; these effects need to be controlled for when making comparisons between individual animals or populations. Hair growth rates also showed considerable inter-specific variation among a number of primate species. We describe technical limitations of hair analyses and variation in cortisol concentrations as a function of asynchronous hair growth, anatomical site of collection, and the amount and numbers of hair/s used for cortisol extraction. We discuss these sources of variation and their implications for proper study design and interpretation of results.
Keywords: Age Factors; Animals; Animals, Wild; Animals, Zoo; Chemistry Techniques, Analytical; Female; Hair; Hydrocortisone; Male; Primates; Sex Factors; Sonication

Structural and transcriptomic response to antenatal corticosteroids in an Erk3-null mouse model of respiratory distress. - Pew, Braden K; R. Alan Harris; Sbrana, Elena; Guaman, Milenka Cuevas; Shope, Cynthia; Rui Chen; Meloche, Sylvain; Aagaard, Kjersti (Am J Obstet Gynecol, 2016)
BACKGROUND: Neonatal respiratory distress syndrome in preterm infants is a leading cause of neonatal death. Pulmonary insufficiency-related infant mortality rates have improved with antenatal glucocorticoid treatment and neonatal surfactant replacement. However, the mechanism of glucocorticoid-promoted fetal lung maturation is not understood fully, despite decades of clinical use. We previously have shown that genetic deletion of Erk3 in mice results in growth restriction, cyanosis, and early neonatal lethality because of pulmonary immaturity and respiratory distress. Recently, we demonstrated that the addition of postnatal surfactant administration to antenatal dexamethasone treatment resulted in enhanced survival of neonatal Erk3-null mice. OBJECTIVE: To better understand the molecular underpinnings of corticosteroid-mediated lung maturation, we used high-throughput transcriptomic and high-resolution morphologic analysis of the murine fetal lung. We sought to examine the alterations in fetal lung structure and function that are associated with neonatal respiratory distress and antenatal glucocorticoid treatment. STUDY DESIGN: Dexamethasone (0.4 mg/kg) or saline solution was administered to pregnant dams on embryonic days 16.5 and 17.5. Fetal lungs were collected and analyzed by microCT and RNA-seq for differential gene expression and pathway interactions with genotype and treatment. Results from transcriptomic analysis guided further investigation of candidate genes with the use of immunostaining in murine and human fetal lung tissue. RESULTS: Erk3(-/-) mice exhibited atelectasis with decreased overall porosity and saccular space relative to wild type, which was ameliorated by glucocorticoid treatment. Of 596 differentially expressed genes (q < 0.05) that were detected by RNA-seq, pathway analysis revealed 36 genes (q < 0.05) interacting with dexamethasone, several with roles in lung development, which included corticotropin-releasing hormone and surfactant protein B. Corticotropin-releasing hormone protein was detected in wild-type and Erk3(-/-) lungs at E14.5, with significantly temporally altered expression through embryonic day 18.5. Antenatal dexamethasone attenuated corticotropin-releasing hormone at embryonic day 18.5 in both wild-type and Erk3(-/-) lungs (0.56-fold and 0.67-fold; P < .001). Wild type mice responded to glucocorticoid administration with increased pulmonary surfactant protein B (P = .003). In contrast, dexamethasone treatment in Erk3(-/-) mice resulted in decreased surfactant protein B (P = .012). In human validation studies, we confirmed that corticotropin-releasing hormone protein is present in the fetal lung at 18 weeks of gestation and increases in expression with progression towards viability (22 weeks of gestation; P < .01). CONCLUSION: Characterization of whole transcriptome gene expression revealed glucocorticoid-mediated regulation of corticotropin-releasing hormone and surfactant protein B via Erk3-independent and -dependent mechanisms, respectively. We demonstrated for the first time the expression and temporal regulation of corticotropin-releasing hormone protein in midtrimester human fetal lung. This unique model allows the effects of corticosteroids on fetal pulmonary morphologic condition to be distinguished from functional gene pathway regulation. These findings implicate Erk3 as a potentially important molecular mediator of antenatal glucocorticoid action in promoting surfactant protein production in the preterm neonatal lung and expanding our understanding of key mechanisms of clinical therapy to improve neonatal survival.
Keywords: Animals; Animals, Newborn; Corticotropin-Releasing Hormone; Dexamethasone; Disease Models, Animal; Female; Glucocorticoids; Insulin-Like Growth Factor II; Lung; Mice, Knockout; Mitogen-Activated Protein Kinase 6; Pregnancy; Pulmonary Surfactant-Associated Protein D; Respiratory Distress Syndrome, Newborn; X-Ray Microtomography

The ticking clock of Cayo Santiago macaques and its implications for understanding human circadian rhythm disorders. - Zhdanova, Irina V; Jeffrey Rogers; González-Martínez, Janis; Farrer, Lindsay A (Am J Primatol, 2016)
The circadian clock disorders in humans remain poorly understood. However, their impact on the development and progression of major human conditions, from cancer to insomnia, metabolic or mental illness becomes increasingly apparent. Addressing human circadian disorders in animal models is, in part, complicated by inverse temporal relationship between the core clock and specific physiological or behavioral processes in diurnal and nocturnal animals. Major advantages of a macaque model for translational circadian research, as a diurnal vertebrate phylogenetically close to humans, are further emphasized by the discovery of the first familial circadian disorder in non-human primates among the rhesus monkeys originating from Cayo Santiago. The remarkable similarity of their pathological phenotypes to human Delayed Sleep Phase Disorder (DSPD), high penetrance of the disorder within one branch of the colony and the large number of animals available provide outstanding opportunities for studying the mechanisms of circadian disorders, their impact on other pathological conditions, and for the development of novel and effective treatment strategies.
Keywords: Animals; Chronobiology Disorders; Circadian Clocks; Humans; Macaca mulatta; Models, Animal; Puerto Rico; Sleep

Unique features of a global human ectoparasite identified through sequencing of the bed bug genome. - Benoit, Joshua B; Adelman, Zach N; Reinhardt, Klaus; Dolan, Amanda; Poelchau, Monica; Jennings, Emily C; Szuter, Elise M; Hagan, Richard W; Gujar, Hemant; Shukla, Jayendra Nath; Zhu, Fang; Mohan, M; et al. (Nat Commun, 2016)
The bed bug, Cimex lectularius, has re-established itself as a ubiquitous human ectoparasite throughout much of the world during the past two decades. This global resurgence is likely linked to increased international travel and commerce in addition to widespread insecticide resistance. Analyses of the C. lectularius sequenced genome (650 Mb) and 14,220 predicted protein-coding genes provide a comprehensive representation of genes that are linked to traumatic insemination, a reduced chemosensory repertoire of genes related to obligate hematophagy, host-symbiont interactions, and several mechanisms of insecticide resistance. In addition, we document the presence of multiple putative lateral gene transfer events. Genome sequencing and annotation establish a solid foundation for future research on mechanisms of insecticide resistance, human-bed bug and symbiont-bed bug associations, and unique features of bed bug biology that contribute to the unprecedented success of C. lectularius as a human ectoparasite.
Keywords: Animals; Bedbugs; Ectoparasitic Infestations; Feeding Behavior; Gene Transfer, Horizontal; Genome; Host-Parasite Interactions; Humans; Insecticide Resistance; Insecticides; Sequence Analysis, DNA

The whole genome sequence of the Mediterranean fruit fly, Ceratitis capitata (Wiedemann), reveals insights into the biology and adaptive evolution of a highly invasive pest species. - Papanicolaou, Alexie; Schetelig, Marc F; Arensburger, Peter; Atkinson, Peter W; Benoit, Joshua B; Bourtzis, Kostas; Castañera, Pedro; Cavanaugh, John P; Chao, Hsu; Childers, Christopher; Curril, Ingrid; Dinh, Huyen; et al. (Genome Biol, 2016)
BACKGROUND: The Mediterranean fruit fly (medfly), Ceratitis capitata, is a major destructive insect pest due to its broad host range, which includes hundreds of fruits and vegetables. It exhibits a unique ability to invade and adapt to ecological niches throughout tropical and subtropical regions of the world, though medfly infestations have been prevented and controlled by the sterile insect technique (SIT) as part of integrated pest management programs (IPMs). The genetic analysis and manipulation of medfly has been subject to intensive study in an effort to improve SIT efficacy and other aspects of IPM control. RESULTS: The 479 Mb medfly genome is sequenced from adult flies from lines inbred for 20 generations. A high-quality assembly is achieved having a contig N50 of 45.7 kb and scaffold N50 of 4.06 Mb. In-depth curation of more than 1800 messenger RNAs shows specific gene expansions that can be related to invasiveness and host adaptation, including gene families for chemoreception, toxin and insecticide metabolism, cuticle proteins, opsins, and aquaporins. We identify genes relevant to IPM control, including those required to improve SIT. CONCLUSIONS: The medfly genome sequence provides critical insights into the biology of one of the most serious and widespread agricultural pests. This knowledge should significantly advance the means of controlling the size and invasive potential of medfly populations. Its close relationship to Drosophila, and other insect species important to agriculture and human health, will further comparative functional and structural studies of insect genomes that should broaden our understanding of gene family evolution.
Keywords: Animals; Animals, Genetically Modified; Biological Evolution; Ceratitis capitata; Genome, Insect; High-Throughput Nucleotide Sequencing; Humans; Introduced Species; Molecular Sequence Annotation; Pest Control, Biological

Zoonotic Potential of Simian Arteriviruses. - Bailey, Adam L; Lauck, Michael; Sibley, Samuel D; Friedrich, Thomas C; Kuhn, Jens H; Freimer, Nelson B; Jasinska, Anna J; Phillips-Conroy, Jane E; Jolly, Clifford J; Marx, Preston A; Apetrei, Cristian; Jeffrey Rogers; et al. (J Virol, 2016)
Wild nonhuman primates are immediate sources and long-term reservoirs of human pathogens. However, ethical and technical challenges have hampered the identification of novel blood-borne pathogens in these animals. We recently examined RNA viruses in plasma from wild African monkeys and discovered several novel, highly divergent viruses belonging to the family Arteriviridae. Close relatives of these viruses, including simian hemorrhagic fever virus, have caused sporadic outbreaks of viral hemorrhagic fever in captive macaque monkeys since the 1960s. However, arterivirus infection in wild nonhuman primates had not been described prior to 2011. The arteriviruses recently identified in wild monkeys have high sequence and host species diversity, maintain high viremia, and are prevalent in affected populations. Taken together, these features suggest that the simian arteriviruses may be "preemergent" zoonotic pathogens. If not, this would imply that biological characteristics of RNA viruses thought to facilitate zoonotic transmission may not, by themselves, be sufficient for such transmission to occur.
Keywords: Animals; Arterivirus; Arterivirus Infections; Haplorhini; Humans; Primate Diseases; Zoonoses

AAV8(Y733F)-mediated gene therapy in a Spata7 knockout mouse model of Leber congenital amaurosis and retinitis pigmentosa. - Zhong, H; Eblimit, A; Moayedi, Y; Boye, S L; Chiodo, V A; Chen, Y; Li, Y; Nichols, R M; Hauswirth, W W; Chen, R; Mardon, G (Gene Ther, 2015)
Loss of SPATA7 function causes the pathogenesis of Leber congenital amaurosis and retinitis pigmentosa. Spata7 knockout mice mimic human SPATA7-related retinal disease with apparent photoreceptor degeneration observed as early as postnatal day 15 (P15). To test the efficacy of adeno-associated virus (AAV)-mediated gene therapy for rescue of photoreceptor survival and function in Spata7 mutant mice, we employed the AAV8(Y733F) vector carrying hGRK1-driven full-length FLAG-tagged Spata7 cDNA to target both rod and cone photoreceptors. Following subretinal injection of this vector, FLAG-tagged SPATA7 was found to colocalize with endogenous SPATA7 in wild-type mice. In Spata7 mutant mice initially treated at P15, we observed improvement of photoresponse, photoreceptor ultrastructure and significant alleviation of photoreceptor degeneration. Furthermore, we performed treatments at P28 and P56 and found that all treatments (P15-P56) can ameliorate rod and cone loss in the long term (1 year); however, none efficiently protect photoreceptors from degeneration by 86 weeks of age as only a small amount of treated photoreceptors can survive to this time. This study demonstrates long-term improvement of photoreceptor function by AAV8(Y733F)-introduced Spata7 expression in a mouse model as potential treatment of the human disease, but also suggests that treated mutant photoreceptors still undergo progressive degeneration.
Keywords: Animals; Dependovirus; Disease Models, Animal; DNA-Binding Proteins; Genetic Therapy; Genetic Vectors; Leber Congenital Amaurosis; Mice, Inbred C57BL; Mice, Knockout; Retinal Cone Photoreceptor Cells; Retinal Rod Photoreceptor Cells; Retinitis Pigmentosa

ABCF1 extrinsically regulates retinal pigment epithelial cell phagocytosis. - Guo, Feiye; Ding, Ying; Caberoy, Nora; Alvarado, Gabriela; Wang, Feng; Rui Chen; Li, Wei (Mol Biol Cell, 2015)
Phagocytosis of shed photoreceptor outer segments (POSs) by retinal pigment epithelial (RPE) cells is critical to retinal homeostasis and shares many conserved signaling pathways with other phagocytes, including extrinsic regulations. Phagocytotic ligands are the key to cargo recognition, engulfment initiation, and activity regulation. In this study, we identified intracellular protein ATP-binding cassette subfamily F member 1 (ABCF1) as a novel RPE phagocytotic ligand by a new approach of functional screening. ABCF1 was independently verified to extrinsically promote phagocytosis of shed POSs by D407 RPE cells. This finding was further corroborated with primary RPE cells and RPE explants. Internalized POS vesicles were colocalized with a phagosome marker, suggesting that ABCF1-mediated engulfment is through a phagocytic pathway. ABCF1 was released from apoptotic cells and selectively bound to shed POS vesicles and apoptotic cells, possibly via externalized phosphatidylserine. ABCF1 is predominantly expressed in POSs and colocalized with the POS marker rhodopsin, providing geographical convenience for regulation of RPE phagocytosis. Collectively these results suggest that ABCF1 is released from and binds to shed POSs in an autocrine manner to facilitate RPE phagocytosis through a conserved pathway. Furthermore, the new approach is broadly applicable to many other phagocytes and will enable systematic elucidation of their ligands to understand extrinsic regulation and cargo recognition.
Keywords: Animals; ATP-Binding Cassette Transporters; Cells, Cultured; Humans; Ligands; Mice; Phagocytosis; Retinal Photoreceptor Cell Outer Segment; Retinal Pigment Epithelium

Allelic Mutations of KITLG, Encoding KIT Ligand, Cause Asymmetric and Unilateral Hearing Loss and Waardenburg Syndrome Type 2. - Zazo Seco, Celia; Serrão de Castro, Luciana; van Nierop, Josephine W; Morín, Matías; Jhangiani, Shalini; Verver, Eva J J; Schraders, Margit; Maiwald, Nadine; Wesdorp, Mieke; Venselaar, Hanka; Spruijt, Liesbeth; Oostrik, Jaap; et al. (Am J Hum Genet, 2015)
Linkage analysis combined with whole-exome sequencing in a large family with congenital and stable non-syndromic unilateral and asymmetric hearing loss (NS-UHL/AHL) revealed a heterozygous truncating mutation, c.286_303delinsT (p.Ser96Ter), in KITLG. This mutation co-segregated with NS-UHL/AHL as a dominant trait with reduced penetrance. By screening a panel of probands with NS-UHL/AHL, we found an additional mutation, c.200_202del (p.His67_Cys68delinsArg). In vitro studies revealed that the p.His67_Cys68delinsArg transmembrane isoform of KITLG is not detectable at the cell membrane, supporting pathogenicity. KITLG encodes a ligand for the KIT receptor. Also, KITLG-KIT signaling and MITF are suggested to mutually interact in melanocyte development. Because mutations in MITF are causative of Waardenburg syndrome type 2 (WS2), we screened KITLG in suspected WS2-affected probands. A heterozygous missense mutation, c.310C>G (p.Leu104Val), that segregated with WS2 was identified in a small family. In vitro studies revealed that the p.Leu104Val transmembrane isoform of KITLG is located at the cell membrane, as is wild-type KITLG. However, in culture media of transfected cells, the p.Leu104Val soluble isoform of KITLG was reduced, and no soluble p.His67_Cys68delinsArg and p.Ser96Ter KITLG could be detected. These data suggest that mutations in KITLG associated with NS-UHL/AHL have a loss-of-function effect. We speculate that the mechanism of the mutation underlying WS2 and leading to membrane incorporation and reduced secretion of KITLG occurs via a dominant-negative or gain-of-function effect. Our study unveils different phenotypes associated with KITLG, previously associated with pigmentation abnormalities, and will thereby improve the genetic counseling given to individuals with KITLG variants.
Keywords: Alleles; Animals; Female; Fluorescent Antibody Technique; Genetic Linkage; Hearing Loss, Unilateral; Humans; Male; Mice; Mutation; NIH 3T3 Cells; Pedigree; Phenotype; Prognosis; Real-Time Polymerase Chain Reaction; Reverse Transcriptase Polymerase Chain Reaction; RNA, Messenger; Stem Cell Factor; Waardenburg Syndrome

The Candida albicans Histone Acetyltransferase Hat1 Regulates Stress Resistance and Virulence via Distinct Chromatin Assembly Pathways. - Tscherner, Michael; Zwolanek, Florian; Jenull, Sabrina; Fritz J Sedlazeck; Petryshyn, Andriy; Frohner, Ingrid E; Mavrianos, John; Chauhan, Neeraj; von Haeseler, Arndt; Kuchler, Karl (PLoS Pathog, 2015)
Human fungal pathogens like Candida albicans respond to host immune surveillance by rapidly adapting their transcriptional programs. Chromatin assembly factors are involved in the regulation of stress genes by modulating the histone density at these loci. Here, we report a novel role for the chromatin assembly-associated histone acetyltransferase complex NuB4 in regulating oxidative stress resistance, antifungal drug tolerance and virulence in C. albicans. Strikingly, depletion of the NuB4 catalytic subunit, the histone acetyltransferase Hat1, markedly increases resistance to oxidative stress and tolerance to azole antifungals. Hydrogen peroxide resistance in cells lacking Hat1 results from higher induction rates of oxidative stress gene expression, accompanied by reduced histone density as well as subsequent increased RNA polymerase recruitment. Furthermore, hat1Δ/Δ cells, despite showing growth defects in vitro, display reduced susceptibility to reactive oxygen-mediated killing by innate immune cells. Thus, clearance from infected mice is delayed although cells lacking Hat1 are severely compromised in killing the host. Interestingly, increased oxidative stress resistance and azole tolerance are phenocopied by the loss of histone chaperone complexes CAF-1 and HIR, respectively, suggesting a central role for NuB4 in the delivery of histones destined for chromatin assembly via distinct pathways. Remarkably, the oxidative stress phenotype of hat1Δ/Δ cells is a species-specific trait only found in C. albicans and members of the CTG clade. The reduced azole susceptibility appears to be conserved in a wider range of fungi. Thus, our work demonstrates how highly conserved chromatin assembly pathways can acquire new functions in pathogenic fungi during coevolution with the host.
Keywords: Adaptation, Physiological; Animals; Candida albicans; Candidiasis; Chromatin Assembly and Disassembly; Chromatin Immunoprecipitation; Histone Acetyltransferases; Immunoblotting; Mass Spectrometry; Mice; Mice, Inbred C57BL; Oxidative Stress; Polymerase Chain Reaction; Virulence

Cerebral visual impairment and intellectual disability caused by PGAP1 variants. - Bosch, Daniëlle G M; Boonstra, F Nienke; Kinoshita, Taroh; Jhangiani, Shalini; de Ligt, Joep; Cremers, Frans P M; Lupski, James R; Murakami, Yoshiko; de Vries, Bert B A (Eur J Hum Genet, 2015)
Homozygous variants in PGAP1 (post-GPI attachment to proteins 1) have recently been identified in two families with developmental delay, seizures and/or spasticity. PGAP1 is a member of the glycosylphosphatidylinositol anchor biosynthesis and remodeling pathway and defects in this pathway are a subclass of congenital disorders of glycosylation. Here we performed whole-exome sequencing in an individual with cerebral visual impairment (CVI), intellectual disability (ID), and factor XII deficiency and revealed compound heterozygous variants in PGAP1, c.274_276del (p.(Pro92del)) and c.921_925del (p.(Lys308Asnfs*25)). Subsequently, PGAP1-deficient Chinese hamster ovary (CHO)-cell lines were transfected with either mutant or wild-type constructs and their sensitivity to phosphatidylinositol-specific phospholipase C (PI-PLC) treatment was measured. The mutant constructs could not rescue the PGAP1-deficient CHO cell lines resistance to PI-PLC treatment. In addition, lymphoblastoid cell lines (LCLs) of the affected individual showed no sensitivity to PI-PLC treatment, whereas the LCLs of the heterozygous carrier parents were partially resistant. In conclusion, we report novel PGAP1 variants in a boy with CVI and ID and a proven functional loss of PGAP1 and show, to our knowledge, for the first time this genetic association with CVI.
Keywords: Animals; Cell Line, Tumor; Child; CHO Cells; Cricetinae; Cricetulus; Humans; Intellectual Disability; Male; Membrane Proteins; Mutation; Phosphoinositide Phospholipase C; Phosphoric Monoester Hydrolases; Syndrome; Vision Disorders; Visual Perception

Comparative Genomic Analyses of the Human NPHP1 Locus Reveal Complex Genomic Architecture and Its Regional Evolution in Primates. - Bo Yuan; Liu, Pengfei; Gupta, Aditya; Beck, Christine R; Tejomurtula, Anusha; Campbell, Ian M; Gambin, Tomasz; Simmons, Alexandra D; Withers, Marjorie A; R. Alan Harris; Jeffrey Rogers; Schwartz, David C; et al. (PLoS Genet, 2015)
Many loci in the human genome harbor complex genomic structures that can result in susceptibility to genomic rearrangements leading to various genomic disorders. Nephronophthisis 1 (NPHP1, MIM# 256100) is an autosomal recessive disorder that can be caused by defects of NPHP1; the gene maps within the human 2q13 region where low copy repeats (LCRs) are abundant. Loss of function of NPHP1 is responsible for approximately 85% of the NPHP1 cases-about 80% of such individuals carry a large recurrent homozygous NPHP1 deletion that occurs via nonallelic homologous recombination (NAHR) between two flanking directly oriented ~45 kb LCRs. Published data revealed a non-pathogenic inversion polymorphism involving the NPHP1 gene flanked by two inverted ~358 kb LCRs. Using optical mapping and array-comparative genomic hybridization, we identified three potential novel structural variant (SV) haplotypes at the NPHP1 locus that may protect a haploid genome from the NPHP1 deletion. Inter-species comparative genomic analyses among primate genomes revealed massive genomic changes during evolution. The aggregated data suggest that dynamic genomic rearrangements occurred historically within the NPHP1 locus and generated SV haplotypes observed in the human population today, which may confer differential susceptibility to genomic instability and the NPHP1 deletion within a personal genome. Our study documents diverse SV haplotypes at a complex LCR-laden human genomic region. Comparative analyses provide a model for how this complex region arose during primate evolution, and studies among humans suggest that intra-species polymorphism may potentially modulate an individual's susceptibility to acquiring disease-associated alleles.
Keywords: Adaptor Proteins, Signal Transducing; Alleles; Animals; Comparative Genomic Hybridization; Cytoskeletal Proteins; Evolution, Molecular; Gene Dosage; Gene Rearrangement; Genome, Human; Genomic Structural Variation; Haplotypes; Humans; Kidney Diseases, Cystic; Membrane Proteins; Primates

Convergent evolution of the genomes of marine mammals. - Foote, Andrew D; Liu, Yue; Thomas, Gregg W C; Vinar, Tomas; Alföldi, Jessica; Deng, Jixin; Dugan, Shannon; van Elk, Cornelis E; Hunter, Margaret E; Joshi, Vandita; Ziad Khan; Kovar, Christie; et al. (Nat Genet, 2015)
Marine mammals from different mammalian orders share several phenotypic traits adapted to the aquatic environment and therefore represent a classic example of convergent evolution. To investigate convergent evolution at the genomic level, we sequenced and performed de novo assembly of the genomes of three species of marine mammals (the killer whale, walrus and manatee) from three mammalian orders that share independently evolved phenotypic adaptations to a marine existence. Our comparative genomic analyses found that convergent amino acid substitutions were widespread throughout the genome and that a subset of these substitutions were in genes evolving under positive selection and putatively associated with a marine phenotype. However, we found higher levels of convergent amino acid substitutions in a control set of terrestrial sister taxa to the marine mammals. Our results suggest that, whereas convergent molecular evolution is relatively common, adaptive molecular convergence linked to phenotypic convergence is comparatively rare.
Keywords: Adaptation, Physiological; Amino Acid Substitution; Animals; Evolution, Molecular; Genome; Humans; Mammals; Phenotype; Phylogeny; Selection, Genetic

Cortical Folding of the Primate Brain: An Interdisciplinary Examination of the Genetic Architecture, Modularity, and Evolvability of a Significant Neurological Trait in Pedigreed Baboons (Genus Papio). - Atkinson, Elizabeth G; Jeffrey Rogers; Mahaney, Michael C; Cox, Laura A; Cheverud, James M (Genetics, 2015)
Folding of the primate brain cortex allows for improved neural processing power by increasing cortical surface area for the allocation of neurons. The arrangement of folds (sulci) and ridges (gyri) across the cerebral cortex is thought to reflect the underlying neural network. Gyrification, an adaptive trait with a unique evolutionary history, is affected by genetic factors different from those affecting brain volume. Using a large pedigreed population of ∼1000 Papio baboons, we address critical questions about the genetic architecture of primate brain folding, the interplay between genetics, brain anatomy, development, patterns of cortical-cortical connectivity, and gyrification's potential for future evolution. Through Mantel testing and cluster analyses, we find that the baboon cortex is quite evolvable, with high integration between the genotype and phenotype. We further find significantly similar partitioning of variation between cortical development, anatomy, and connectivity, supporting the predictions of tension-based models for sulcal development. We identify a significant, moderate degree of genetic control over variation in sulcal length, with gyrus-shape features being more susceptible to environmental effects. Finally, through QTL mapping, we identify novel chromosomal regions affecting variation in brain folding. The most significant QTL contain compelling candidate genes, including gene clusters associated with Williams and Down syndromes. The QTL distribution suggests a complex genetic architecture for gyrification with both polygeny and pleiotropy. Our results provide a solid preliminary characterization of the genetic basis of primate brain folding, a unique and biomedically relevant phenotype with significant implications in primate brain evolution.
Keywords: Animals; Biological Evolution; Brain; Cerebral Cortex; Chromosome Mapping; Cluster Analysis; Papio; Pedigree; Primates; Quantitative Trait Loci; Reproducibility of Results

CRISPR-engineered mosaicism rapidly reveals that loss of Kcnj13 function in mice mimics human disease phenotypes. - Zhong, Hua; Chen, Yiyun; Yumei Li; Rui Chen; Mardon, Graeme (Sci Rep, 2015)
The era of genomics has demanded the development of more efficient and timesaving approaches to validate gene function in disease. Here, we utilized the CRISPR-Cas9 system to generate Kcnj13 mutant mice by zygote injection to verify the pathogenic role of human KCNJ13, mutations of which are thought to cause Leber congenital amaurosis (LCA), an early-onset form of blindness. We found that complete loss of Kcnj13 is likely postnatal lethal. Among surviving F0-generation mice examined, 80% show mosaic KCNJ13 expression in the retinal pigment epithelium (RPE). Mosaic expression correlates with decreased response to light and photoreceptor degeneration, indicating that Kcnj13 mutant mice mimic human KCNJ13-related LCA disease. Importantly, mosaic animals enable us to directly compare Kcnj13 mutant and wild-type RPE cells in the same eye. We found that RPE cells lacking KCNJ13 protein still survive but overlying photoreceptors exhibit cell degeneration. At the same time, wild-type RPE cells can rescue neighboring photoreceptor cells that overlie mutant RPE cells. These results suggest that KCNJ13 expression is required for RPE cells to maintain photoreceptor survival. Moreover, we show that CRISPR-Cas9 engineered mosaicism can be used to rapidly test candidate gene function in vivo.
Keywords: Animals; CRISPR-Cas Systems; Humans; Leber Congenital Amaurosis; Mice; Mice, Transgenic; Mosaicism; Potassium Channels, Inwardly Rectifying; Retinal Pigment Epithelium

Decreased expression of endogenous feline leukemia virus in cat lymphomas: a case control study. - Krunic, Milica; Ertl, Reinhard; Hagen, Benedikt; Fritz J Sedlazeck; Hofmann-Lehmann, Regina; von Haeseler, Arndt; Klein, Dieter (BMC Vet Res, 2015)
BACKGROUND: Cats infected with exogenous feline leukemia virus (exFeLV) have a higher chance of lymphoma development than uninfected cats. Furthermore, an increased exFeLV transcription has been detected in lymphomas compared to non-malignant tissues. The possible mechanisms of lymphoma development by exFeLV are insertional mutagenesis or persistent stimulation of host immune cells by viral antigens, bringing them at risk for malignant transformation. Vaccination of cats against exFeLV has in recent years decreased the overall infection rate in most countries. Nevertheless, an increasing number of lymphomas have been diagnosed among exFeLV-negative cats. Endogenous feline leukemia virus (enFeLV) is another retrovirus for which transcription has been observed in cat lymphomas. EnFeLV provirus elements are present in the germline of various cat species and share a high sequence similarity with exFeLV but, due to mutations, are incapable of producing infectious viral particles. However, recombination between exFeLV and enFeLV could produce infectious particles. RESULTS: We examined the FeLV expression in cats that have developed malignant lymphomas and discussed the possible mechanisms that could have induced malignant transformation. For expression analysis we used next-generation RNA-sequencing (RNA-Seq) and for validation reverse transcription quantitative PCR (RT-qPCR). First, we showed that there was no expression of exFeLV in all samples, which eliminates the possibility of recombination between exFeLV and enFeLV. Next, we analyzed the difference in expression of three enFeLV genes between control and lymphoma samples. Our analysis showed an average of 3.40-fold decreased viral expression for the three genes in lymphoma compared to control samples. The results were confirmed by RT-qPCR. CONCLUSIONS: There is a decreased expression of enFeLV genes in lymphomas versus control samples, which contradicts previous observations for the exFeLV. Our results suggest that a persistent stimulation of host immune cells is not an appropriate mechanism responsible for malignant transformation caused by feline endogenous retroviruses.
Keywords: Animals; Base Sequence; Case-Control Studies; Cat Diseases; Cats; Female; Gene Expression Regulation, Viral; Leukemia Virus, Feline; Lymphoma; Male; Retroviridae Infections; Reverse Transcriptase Polymerase Chain Reaction; RNA, Viral; Tumor Virus Infections

Dnmt3a loss predisposes murine hematopoietic stem cells to malignant transformation. - Mayle, Allison; Yang, Liubin; Rodriguez, Benjamin; Zhou, Ting; Chang, Edmund; Curry, Choladda V; Challen, Grant A; Li, Wei; Wheeler, David; Rebel, Vivienne I; Goodell, Margaret A (Blood, 2015)
DNA methyltransferase 3A (DNMT3A) is mutated in hematologic malignancies affecting myeloid, mixed, and lymphoid lineages, and these mutations are associated with poor prognosis. Past studies in mice revealed Dnmt3a-knockout (KO)hematopoietic stem cells (HSCs) had increased self-renewal, but no leukemia was observed. Here, all lethally irradiated mice transplanted with Dnmt3a-deleted HSCs died within 1 year. Animals were diagnosed with a spectrum of malignancies similar to those seen in patients with DNMT3A mutations, including myelodysplastic syndrome, acute myeloid leukemia, primary myelofibrosis, and T- and B-cell acute lymphocytic leukemia. In some cases, acquired malignancies exhibited secondary mutations similar to those identified in patients. Loss of Dnmt3a led to disturbed methylation patterns that were distinct in lymphoid and myeloid disease, suggesting lineage-specific methylation aberrations promoted by Dnmt3a loss. Global hypomethylation was observed in all of the malignancies, but lymphoid malignancies also exhibited hypermethylation, particularly at promoter regions. This mouse model underscores the important role of Dnmt3a in normal hematopoietic development and demonstrates that Dnmt3a loss of function confers a preleukemic phenotype on murine HSCs. This model may serve as a tool to study DNMT3A mutation associated malignancies and for developing targeted strategies for eliminating preleukemic cells for prevention and treatment of hematologic malignancies in the future.
Keywords: Animals; Cell Transformation, Neoplastic; DNA (Cytosine-5-)-Methyltransferases; DNA Methylation; DNA Methyltransferase 3A; DNA, Neoplasm; Hematologic Neoplasms; Hematopoietic Stem Cells; Mice; Mice, Knockout; Promoter Regions, Genetic

Do echinoderm genomes measure up? - Cameron, R Andrew; Kudtarkar, Parul; Gordon, Susan M; Worley, Kim C; Richard A Gibbs (Mar Genomics, 2015)
Echinoderm genome sequences are a corpus of useful information about a clade of animals that serve as research models in fields ranging from marine ecology to cell and developmental biology. Genomic information from echinoids has contributed to insights into the gene interactions that drive the developmental process at the molecular level. Such insights often rely heavily on genomic information and the kinds of questions that can be asked thus depend on the quality of the sequence information. Here we describe the history of echinoderm genomic sequence assembly and present details about the quality of the data obtained. All of the sequence information discussed here is posted on the echinoderm information web system, Echinobase.org.
Keywords: Animals; Echinodermata; Genome; History, 21st Century; Models, Genetic; Phylogeny; Sequence Analysis, DNA; Species Specificity; Transcriptome

Durable sequence stability and bone marrow tropism in a macaque model of human pegivirus infection. - Bailey, Adam L; Lauck, Michael; Mohns, Mariel; Peterson, Eric J; Beheler, Kerry; Brunner, Kevin G; Crosno, Kristin; Mejia, Andres; Mutschler, James; Gehrke, Matthew; Greene, Justin; Ericsen, Adam J; et al. (Sci Transl Med, 2015)
Human pegivirus (HPgV)-formerly known as GB virus C and hepatitis G virus-is a poorly characterized RNA virus that infects about one-sixth of the global human population and is transmitted frequently in the blood supply. We create an animal model of HPgV infection by infecting macaque monkeys with a new simian pegivirus (SPgV) discovered in wild baboons. Using this model, we provide a high-resolution, longitudinal picture of SPgV viremia where the dose, route, and timing of infection are known. We detail the highly variable acute phase of SPgV infection, showing that the viral load trajectory early in infection is dependent on the infecting dose, whereas the chronic-phase viremic set point is not. We also show that SPgV has an extremely low propensity for accumulating sequence variation, with no consensus-level variants detected during the acute phase of infection and an average of only 1.5 variants generated per 100 infection-days. Finally, we show that SPgV RNA is highly concentrated in only two tissues: spleen and bone marrow, with bone marrow likely producing most of the virus detected in plasma. Together, these results reconcile several paradoxical observations from cross-sectional analyses of HPgV in humans and provide an animal model for studying pegivirus biology.
Keywords: Acquired Immunodeficiency Syndrome; Animals; Bone Marrow; Disease Models, Animal; Evolution, Molecular; Female; Flaviviridae Infections; GB virus C; Genetic Variation; High-Throughput Nucleotide Sequencing; HIV Infections; Humans; Likelihood Functions; Macaca; Male; Papio; Phylogeny; Reverse Transcriptase Polymerase Chain Reaction; RNA, Viral; Viral Load; Viral Tropism; Viremia

Ectodysplasin signalling genes and phenotypic evolution in sculpins (Cottus). - Cheng, Jie; Fritz J Sedlazeck; Altmüller, Janine; Nolte, Arne W (Proc Biol Sci, 2015)
Despite their deeply conserved function among vertebrates, ectodysplasin (Eda) signalling genes are involved in microevolutionary change in humans and sticklebacks. If such a dual role is common, Eda signalling genes constitute hotspots for morphological evolution. Variation in sculpin (Cottus) skin prickling and body shape resembles patterns caused by variation in Eda signalling in sticklebacks. We mapped Eda signalling genes and performed quantitative trait locus mapping in crosses between Cottus rhenanus and Cottus perifretum. A genomic region containing the Eda receptor (Edar) was strongly associated with prickling and contributed to shape. The expression of Edar in developing prickles and skeletal elements in Cottus was confirmed by in situ hybridization. Coding sequence changes between Edar alleles in C. rhenanus and C. perifretum exceeded sequence differentiation in other vertebrates. However, it is likely that additional genetic elements besides coding changes affect the phenotypic variation. Although the phenotype in a natural hybrid lineage between C. rhenanus and C. perifretum resembles C. perifretum, the respective coding Edar alleles are not fully fixed (88.6%). Hence, our results support an involvement of Eda signalling in microevolutionary changes, but imply that the Edar gene is affected by multiple evolutionary processes that vary among freshwater sculpins.
Keywords: Animals; Biological Evolution; Body Patterning; Ectodysplasins; Epidermis; Genetics, Population; Hybridization, Genetic; Perciformes; Phenotype; Receptors, Ectodysplasin; Signal Transduction

Exome Sequence Analysis Suggests that Genetic Burden Contributes to Phenotypic Variability and Complex Neuropathy. - Gonzaga-Jauregui, Claudia; Harel, Tamar; Gambin, Tomasz; Kousi, Maria; Griffin, Laurie B; Francescatto, Ludmila; Ozes, Burcak; Karaca, Ender; Jhangiani, Shalini N; Bainbridge, Matthew N; Lawson, Kim S; Pehlivan, Davut; et al. (Cell Rep, 2015)
Charcot-Marie-Tooth (CMT) disease is a clinically and genetically heterogeneous distal symmetric polyneuropathy. Whole-exome sequencing (WES) of 40 individuals from 37 unrelated families with CMT-like peripheral neuropathy refractory to molecular diagnosis identified apparent causal mutations in ∼ 45% (17/37) of families. Three candidate disease genes are proposed, supported by a combination of genetic and in vivo studies. Aggregate analysis of mutation data revealed a significantly increased number of rare variants across 58 neuropathy-associated genes in subjects versus controls, confirmed in a second ethnically discrete neuropathy cohort, suggesting that mutation burden potentially contributes to phenotypic variability. Neuropathy genes shown to have highly penetrant Mendelizing variants (HPMVs) and implicated by burden in families were shown to interact genetically in a zebrafish assay exacerbating the phenotype established by the suppression of single genes. Our findings suggest that the combinatorial effect of rare variants contributes to disease burden and variable expressivity.
Keywords: Animals; Charcot-Marie-Tooth Disease; Exome; Female; Genetic Load; Genetic Variation; HSP40 Heat-Shock Proteins; Humans; Male; Mutation; Myelin P2 Protein; Pedigree; Penetrance; Peripheral Nervous System Diseases; Phenotype; Serine C-Palmitoyltransferase; Suppression, Genetic; Zebrafish

FlyVar: a database for genetic variation in Drosophila melanogaster. - Wang, Fei; Jiang, Lichun; Chen, Yong; Haelterman, Nele A; Bellen, Hugo J; Rui Chen (Database (Oxford), 2015)
FlyVar is a publicly and freely available platform that addresses the increasing need of next generation sequencing data analysis in the Drosophila research community. It is composed of three parts. First, a database that contains 5.94 million DNA polymorphisms found in Drosophila melanogaster derived from whole genome shotgun sequencing of 612 genomes of D. melanogaster. In addition, a list of 1094 dispensable genes has been identified. Second, a graphical user interface (GUI) has been implemented to allow easy and flexible queries of the database. Third, a set of interactive online tools enables filtering and annotation of genomic sequences obtained from individual D. melanogaster strains to identify candidate mutations. FlyVar permits the analysis of next generation sequencing data without the need of extensive computational training or resources. Database URL: www.iipl.fudan.edu.cn/FlyVar.
Keywords: Animals; Databases, Genetic; Drosophila melanogaster; Genes, Insect; Molecular Sequence Annotation; Polymorphism, Genetic; User-Computer Interface

Generation and characterization of antibodies against Asian elephant (Elephas maximus) IgG, IgM, and IgA. - Humphreys, Alan F; Tan, Jie; Peng, Rongsheng; Benton, Susan M; Xiang Qin; Worley, Kim C; Mikulski, Rose L; Chow, Dar-Chone; Palzkill, Timothy G; Ling, Paul D (PLoS One, 2015)
Asian elephant (Elephas maximus) immunity is poorly characterized and understood. This gap in knowledge is particularly concerning as Asian elephants are an endangered species threatened by a newly discovered herpesvirus known as elephant endotheliotropic herpesvirus (EEHV), which is the leading cause of death for captive Asian elephants born after 1980 in North America. While reliable diagnostic assays have been developed to detect EEHV DNA, serological assays to evaluate elephant anti-EEHV antibody responses are lacking and will be needed for surveillance and epidemiological studies and also for evaluating potential treatments or vaccines against lethal EEHV infection. Previous studies have shown that Asian elephants produce IgG in serum, but they failed to detect IgM and IgA, further hampering development of informative serological assays for this species. To begin to address this issue, we determined the constant region genomic sequence of Asian elephant IgM and obtained some limited protein sequence information for putative serum IgA. The information was used to generate or identify specific commercial antisera reactive against IgM and IgA isotypes. In addition, we generated a monoclonal antibody against Asian elephant IgG. These three reagents were used to demonstrate that all three immunoglobulin isotypes are found in Asian elephant serum and milk and to detect antibody responses following tetanus toxoid booster vaccination or antibodies against a putative EEHV structural protein. The results indicate that these new reagents will be useful for developing sensitive and specific assays to detect and characterize elephant antibody responses for any pathogen or vaccine, including EEHV.
Keywords: Animals; Antibodies, Anti-Idiotypic; Base Sequence; Betaherpesvirinae; Chromatography, Gel; DNA Primers; Electrophoresis, Polyacrylamide Gel; Elephants; Endangered Species; Enzyme-Linked Immunosorbent Assay; Herpesviridae Infections; Immunoglobulin A; Immunoglobulin G; Immunoglobulin M; Molecular Sequence Data; Polymerase Chain Reaction; Sequence Analysis, DNA; Tandem Mass Spectrometry

Genetic influences on response to novel objects and dimensions of personality in Papio baboons. - Johnson, Zachary; Brent, Linda; Alvarenga, Juan Carlos; Comuzzie, Anthony G; Shelledy, Wendy; Ramirez, Stephanie; Cox, Laura; Mahaney, Michael C; Huang, Yung-Yu; Mann, J John; Kaplan, Jay R; Jeffrey Rogers (Behav Genet, 2015)
Behavioral variation within and between populations and species of the genus Papio has been studied extensively, but little is known about the genetic causes of individual- or population-level differences. This study investigates the influence of genetic variation on personality (sometimes referred to as temperament) in baboons and identifies a candidate gene partially responsible for the variation in that phenotype. To accomplish these goals, we examined individual variation in response to both novel objects and an apparent novel social partner (using a mirror test) among pedigreed baboons (n = 578) from the Southwest National Primate Research Center. We investigated the frequency and duration of individual behaviors in response to novel objects and used multivariate factor analysis to identify trait-like dimensions of personality. Exploratory factor analysis identified two distinct dimensions of personality within this population. Factor 1 accounts for 46.8 % of the variance within the behavioral matrix, and consists primarily of behaviors related to the "boldness" of the subject. Factor 2 accounts for 18.8 % of the variation, and contains several "anxiety" like behaviors. Several specific behaviors, and the two personality factors, were significantly heritable, with the factors showing higher heritability than most individual behaviors. Subsequent analyses show that the behavioral reactions observed in the test protocol are associated with animals' social behavior observed later in their home social groups. Finally we used linkage analysis to map quantitative trait loci for the measured phenotypes. Single nucleotide polymorphisms in a positional candidate gene (SNAP25) are associated with variation in one of the personality factors, and CSF levels of homovanillic acid and 3-methoxy-4-hydroxyphenylglycol. This study documents heritable variation in personality among baboons and suggests that sequence variation in SNAP25 may influence differences in behavior and neurochemistry in these nonhuman primates.
Keywords: Animals; Behavior, Animal; Ethylene Glycols; Female; Genetic Linkage; Genetic Variation; Homovanillic Acid; Male; Multivariate Analysis; Papio; Pedigree; Personality; Phenols; Phenotype; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Social Behavior; Synaptosomal-Associated Protein 25

The genomes of two key bumblebee species with primitive eusocial organization. - Sadd, Ben M; Barribeau, Seth M; Bloch, Guy; de Graaf, Dirk C; Dearden, Peter; Elsik, Christine G; Gadau, Jürgen; Grimmelikhuijzen, Cornelis J P; Hasselmann, Martin; Lozier, Jeffrey D; Robertson, Hugh M; Smagghe, Guy; et al. (Genome Biol, 2015)
BACKGROUND: The shift from solitary to social behavior is one of the major evolutionary transitions. Primitively eusocial bumblebees are uniquely placed to illuminate the evolution of highly eusocial insect societies. Bumblebees are also invaluable natural and agricultural pollinators, and there is widespread concern over recent population declines in some species. High-quality genomic data will inform key aspects of bumblebee biology, including susceptibility to implicated population viability threats. RESULTS: We report the high quality draft genome sequences of Bombus terrestris and Bombus impatiens, two ecologically dominant bumblebees and widely utilized study species. Comparing these new genomes to those of the highly eusocial honeybee Apis mellifera and other Hymenoptera, we identify deeply conserved similarities, as well as novelties key to the biology of these organisms. Some honeybee genome features thought to underpin advanced eusociality are also present in bumblebees, indicating an earlier evolution in the bee lineage. Xenobiotic detoxification and immune genes are similarly depauperate in bumblebees and honeybees, and multiple categories of genes linked to social organization, including development and behavior, show high conservation. Key differences identified include a bias in bumblebee chemoreception towards gustation from olfaction, and striking differences in microRNAs, potentially responsible for gene regulation underlying social and other traits. CONCLUSIONS: These two bumblebee genomes provide a foundation for post-genomic research on these key pollinators and insect societies. Overall, gene repertoires suggest that the route to advanced eusociality in bees was mediated by many small changes in many genes and processes, and not by notable expansion or depauperation.
Keywords: Animals; Bee Venoms; Bees; Behavior, Animal; Chemoreceptor Cells; Chromosome Mapping; Databases, Genetic; Evolution, Molecular; Female; Gene Expression Regulation; Gene Rearrangement; Genes, Insect; Genomics; Interspersed Repetitive Sequences; Male; Open Reading Frames; Polymorphism, Single Nucleotide; Selenoproteins; Sequence Analysis, DNA; Social Behavior; Species Specificity; Synteny

Genomic profiling guides the choice of molecular targeted therapy of pancreatic cancer. - Frank, Thomas S; Sun, Xiaotian; Zhang, Yuqing; Yang, Jingxuan; Fisher, William E; Marie-Claude Gingras; Li, Min (Cancer Lett, 2015)
Pancreatic cancer has the worst five-year survival rate of all malignancies due to its aggressive progression and resistance to therapy. Current therapies are limited to gemcitabine-based chemotherapeutics, surgery, and radiation. The current trend toward "personalized genomic medicine" has the potential to improve the treatment options for pancreatic cancer. Gene identification and genetic alterations like single nucleotide polymorphisms and mutations will allow physicians to predict the efficacy and toxicity of drugs, which could help diagnose pancreatic cancer, guide neoadjuvant or adjuvant treatment, and evaluate patients' prognosis. This article reviews the multifaceted roles of genomics and pharmacogenomics in pancreatic cancer.
Keywords: Animals; Antineoplastic Agents; Biomarkers, Tumor; Drug Resistance, Neoplasm; Gene Expression Profiling; Genetic Predisposition to Disease; Genomics; Humans; Molecular Targeted Therapy; Pancreatic Neoplasms; Patient Selection; Pharmacogenetics; Phenotype; Precision Medicine; Predictive Value of Tests; Signal Transduction

Hemichordate genomes and deuterostome origins. - Simakov, Oleg; Kawashima, Takeshi; Marlétaz, Ferdinand; Jenkins, Jerry; Koyanagi, Ryo; Mitros, Therese; Hisata, Kanako; Bredeson, Jessen; Shoguchi, Eiichi; Gyoja, Fuki; Yue, Jia-Xing; Chen, Yi-Chih; et al. (Nature, 2015)
Acorn worms, also known as enteropneust (literally, 'gut-breathing') hemichordates, are marine invertebrates that share features with echinoderms and chordates. Together, these three phyla comprise the deuterostomes. Here we report the draft genome sequences of two acorn worms, Saccoglossus kowalevskii and Ptychodera flava. By comparing them with diverse bilaterian genomes, we identify shared traits that were probably inherited from the last common deuterostome ancestor, and then explore evolutionary trajectories leading from this ancestor to hemichordates, echinoderms and chordates. The hemichordate genomes exhibit extensive conserved synteny with amphioxus and other bilaterians, and deeply conserved non-coding sequences that are candidates for conserved gene-regulatory elements. Notably, hemichordates possess a deuterostome-specific genomic cluster of four ordered transcription factor genes, the expression of which is associated with the development of pharyngeal 'gill' slits, the foremost morphological innovation of early deuterostomes, and is probably central to their filter-feeding lifestyle. Comparative analysis reveals numerous deuterostome-specific gene novelties, including genes found in deuterostomes and marine microbes, but not other animals. The putative functions of these genes can be linked to physiological, metabolic and developmental specializations of the filter-feeding ancestor.
Keywords: Animals; Chordata, Nonvertebrate; Conserved Sequence; Echinodermata; Evolution, Molecular; Genome; Multigene Family; Phylogeny; Signal Transduction; Synteny; Transforming Growth Factor beta

Identification of Variant-Specific Functions of PIK3CA by Rapid Phenotyping of Rare Mutations. - Dogruluk, Turgut; Tsang, Yiu Huen; Espitia, Maribel; Chen, Fengju; Chen, Tenghui; Chong, Zechen; Appadurai, Vivek; Dogruluk, Armel; Eterovic, Agna Karina; Bonnen, Penelope E; Creighton, Chad J; Chen, Ken; et al. (Cancer Res, 2015)
Large-scale sequencing efforts are uncovering the complexity of cancer genomes, which are composed of causal "driver" mutations that promote tumor progression along with many more pathologically neutral "passenger" events. The majority of mutations, both in known cancer drivers and uncharacterized genes, are generally of low occurrence, highlighting the need to functionally annotate the long tail of infrequent mutations present in heterogeneous cancers. Here we describe a mutation assessment pipeline enabled by high-throughput engineering of molecularly barcoded gene variant expression clones identified by tumor sequencing. We first used this platform to functionally assess tail mutations observed in PIK3CA, which encodes the catalytic subunit alpha of the phosphatidylinositol-4,5-bisphosphate 3-kinase (PI3K) frequently mutated in cancer. Orthogonal screening for PIK3CA variant activity using in vitro and in vivo cell growth and transformation assays differentiated driver from passenger mutations, revealing that PIK3CA variant activity correlates imperfectly with its mutation frequency across breast cancer populations. Although PIK3CA mutations with frequencies above 5% were significantly more oncogenic than wild-type in all assays, mutations occurring at 0.07% to 5.0% included those with and without oncogenic activities that ranged from weak to strong in at least one assay. Proteomic profiling coupled with therapeutic sensitivity assays on PIK3CA variant-expressing cell models revealed variant-specific activation of PI3K signaling as well as other pathways that include the MEK1/2 module of mitogen-activated protein kinase pathway. Our data indicate that cancer treatments will need to increasingly consider the functional relevance of specific mutations in driver genes rather than considering all mutations in drivers as equivalent.
Keywords: Animals; Breast Neoplasms; Cell Line, Tumor; Class I Phosphatidylinositol 3-Kinases; DNA Mutational Analysis; Female; Heterografts; High-Throughput Nucleotide Sequencing; Humans; Immunoblotting; Mice; Mice, Nude; Mutagenesis, Site-Directed; Phenotype; Phosphatidylinositol 3-Kinases; Polymerase Chain Reaction; Transduction, Genetic

Initial testing (stage 1) of the PARP inhibitor BMN 673 by the pediatric preclinical testing program: PALB2 mutation predicts exceptional in vivo response to BMN 673. - Smith, Malcolm A; Hampton, Oliver A; Reynolds, C Patrick; Kang, Min H; Maris, John M; Gorlick, Richard; Kolb, E Anders; Lock, Richard; Carol, Hernan; Keir, Stephen T; Wu, Jianrong; Kurmasheva, Raushan T; et al. (Pediatr Blood Cancer, 2015)
BACKGROUND: BMN 673 is a potent inhibitor of poly-ADP ribose polymerase (PARP) that is in clinical testing with a primary focus on BRCA-mutated cancers. BMN 673 is active both through inhibiting PARP catalytic activity and by tightly trapping PARP to DNA at sites of single strand breaks. PROCEDURE: BMN 673 was tested in vitro at concentrations ranging from 0.1 nM to 1 μM and in vivo at a daily dose of 0.33 mg/kg administered orally twice daily (Mon-Fri) and once daily on weekends (solid tumors) for 28 days. RESULTS: The median relative IC50 (rIC50 ) concentration against the PPTP cell lines was 25.8 nM. The median rIC50 for the Ewing cell lines was lower than for the remaining cell lines (6.4 vs. 31.1 nM, respectively). In vivo BMN 673 induced statistically significant differences in EFS distribution in 17/43 (39.5%) xenograft models. Three objective regressions were observed: a complete response (CR) in a medulloblastoma line (BT-45), a maintained CR in a Wilms tumor line (KT-10), and a maintained CR in an ependymoma line (BT-41). BMN 673 maintained its high level of activity against KT-10 with a threefold reduction in dose. KT-10 possesses a truncating mutation in PALB2 analogous to PALB2 mutations associated with hereditary breast and ovarian cancer that abrogate homologous recombination (HR) repair. CONCLUSIONS: The PPTP results suggest that single agent BMN 673 may have limited clinical activity against pediatric cancers. Single agent activity is more likely for patients whose tumors have defects in HR repair.
Keywords: Animals; Bone Neoplasms; Drug Evaluation, Preclinical; Enzyme Inhibitors; Fanconi Anemia Complementation Group N Protein; Female; Glioblastoma; Humans; Mice; Mutation; Neuroblastoma; Nuclear Proteins; Phthalazines; Poly(ADP-ribose) Polymerase Inhibitors; Rhabdomyosarcoma; Sarcoma, Ewing; Tumor Suppressor Proteins

It's more than stamp collecting: how genome sequencing can unify biological research. - Stephen Richards (Trends Genet, 2015)
The availability of reference genome sequences, especially the human reference, has revolutionized the study of biology. However, while the genomes of some species have been fully sequenced, a wide range of biological problems still cannot be effectively studied for lack of genome sequence information. Here, I identify neglected areas of biology and describe how both targeted species sequencing and more broad taxonomic surveys of the tree of life can address important biological questions. I enumerate the significant benefits that would accrue from sequencing a broader range of taxa, as well as discuss the technical advances in sequencing and assembly methods that would allow for wide-ranging application of whole-genome analysis. Finally, I suggest that in addition to 'big science' survey initiatives to sequence the tree of life, a modified infrastructure-funding paradigm would better support reference genome sequence generation for research communities most in need.
Keywords: Animals; Evolution, Molecular; Genome; Genomics; High-Throughput Nucleotide Sequencing; Humans; Sequence Analysis, DNA

Loss of Function Mutations in NNT Are Associated With Left Ventricular Noncompaction. - Bainbridge, Matthew N; Davis, Erica E; Choi, Wen-Yee; Dickson, Amy; Martinez, Hugo R; Wang, Min; Dinh, Huyen; Donna M Muzny; Pignatelli, Ricardo; Katsanis, Nicholas; Eric Boerwinkle; Richard A Gibbs; et al. (Circ Cardiovasc Genet, 2015)
BACKGROUND: Left ventricular noncompaction (LVNC) is an autosomal-dominant, genetically heterogeneous cardiomyopathy with variable severity, which may co-occur with cardiac hypertrophy. METHODS AND RESULTS: Here, we generated whole exome sequence data from multiple members from 5 families with LVNC. In 4 of 5 families, the candidate causative mutation segregates with disease in known LVNC genes MYH7 and TPM1. Subsequent sequencing of MYH7 in a larger LVNC cohort identified 7 novel likely disease causing variants. In the fifth family, we identified a frameshift mutation in NNT, a nuclear-encoded mitochondrial protein, not implicated previously in human cardiomyopathies. Resequencing of NNT in additional LVNC families identified a second likely pathogenic missense allele. Suppression of nnt in zebrafish caused early ventricular malformation and contractility defects, probably driven by altered cardiomyocyte proliferation. In vivo complementation studies showed that mutant human NNT failed to rescue nnt morpholino-induced heart dysfunction, indicating a probable haploinsufficiency mechanism. CONCLUSIONS: Together, our data expand the genetic spectrum of LVNC and demonstrate how the intersection of whole exome sequence with in vivo functional studies can accelerate the identification of genes that drive human genetic disorders.
Keywords: Animals; Animals, Genetically Modified; Embryo, Nonmammalian; Exome; Family Health; Female; Frameshift Mutation; Genetic Complementation Test; Genetic Predisposition to Disease; Humans; Isolated Noncompaction of the Ventricular Myocardium; Luminescent Proteins; Male; Microscopy, Confocal; Mitochondrial Proteins; NADP Transhydrogenase, AB-Specific; Pedigree; Sequence Analysis, DNA; Zebrafish

Lucilia cuprina genome unlocks parasitic fly biology to underpin future interventions. - Anstead, Clare A; Korhonen, Pasi K; Young, Neil D; Hall, Ross S; Jex, Aaron R; Murali, Shwetha C; Hughes, Daniel S T; Lee, Siu F; Perry, Trent; Stroehlein, Andreas J; Ansell, Brendan R E; Breugelmans, Bert; et al. (Nat Commun, 2015)
Lucilia cuprina is a parasitic fly of major economic importance worldwide. Larvae of this fly invade their animal host, feed on tissues and excretions and progressively cause severe skin disease (myiasis). Here we report the sequence and annotation of the 458-megabase draft genome of Lucilia cuprina. Analyses of this genome and the 14,544 predicted protein-encoding genes provide unique insights into the fly's molecular biology, interactions with the host animal and insecticide resistance. These insights have broad implications for designing new methods for the prevention and control of myiasis.
Keywords: Animals; Diptera; Female; Gene Expression Regulation; Genome, Insect; Insect Proteins; Insecticide Resistance; Insecticides; Larva; Male; Transcriptome

A massive expansion of effector genes underlies gall-formation in the wheat pest Mayetiola destructor. - Zhao, Chaoyang; Escalante, Lucio Navarro; Chen, Hang; Benatti, Thiago R; Qu, Jiaxin; Chellapilla, Sanjay; Waterhouse, Robert M; Wheeler, David; Andersson, Martin N; Bao, Riyue; Batterton, Matthew; Behura, Susanta K; et al. (Curr Biol, 2015)
Gall-forming arthropods are highly specialized herbivores that, in combination with their hosts, produce extended phenotypes with unique morphologies [1]. Many are economically important, and others have improved our understanding of ecology and adaptive radiation [2]. However, the mechanisms that these arthropods use to induce plant galls are poorly understood. We sequenced the genome of the Hessian fly (Mayetiola destructor; Diptera: Cecidomyiidae), a plant parasitic gall midge and a pest of wheat (Triticum spp.), with the aim of identifying genic modifications that contribute to its plant-parasitic lifestyle. Among several adaptive modifications, we discovered an expansive reservoir of potential effector proteins. Nearly 5% of the 20,163 predicted gene models matched putative effector gene transcripts present in the M. destructor larval salivary gland. Another 466 putative effectors were discovered among the genes that have no sequence similarities in other organisms. The largest known arthropod gene family (family SSGP-71) was also discovered within the effector reservoir. SSGP-71 proteins lack sequence homologies to other proteins, but their structures resemble both ubiquitin E3 ligases in plants and E3-ligase-mimicking effectors in plant pathogenic bacteria. SSGP-71 proteins and wheat Skp proteins interact in vivo. Mutations in different SSGP-71 genes avoid the effector-triggered immunity that is directed by the wheat resistance genes H6 and H9. Results point to effectors as the agents responsible for arthropod-induced plant gall formation.
Keywords: Adaptation, Biological; Amino Acid Sequence; Animals; Base Sequence; Chromosomes; Diptera; Larva; Models, Genetic; Molecular Sequence Data; Multigene Family; Phylogeny; Plant Tumors; Sequence Analysis, DNA; Sequence Homology; Sexual Behavior, Animal; Triticum; Two-Hybrid System Techniques; Ubiquitin-Protein Ligases

Mutations in PNPLA6 are linked to photoreceptor degeneration and various forms of childhood blindness. - Kmoch, S; Majewski, J; Ramamurthy, V; Cao, S; Fahiminiya, S; Ren, H; MacDonald, I M; Lopez, I; Sun, V; Keser, V; Khan, A; Stránecký, V; et al. (Nat Commun, 2015)
Blindness due to retinal degeneration affects millions of people worldwide, but many disease-causing mutations remain unknown. PNPLA6 encodes the patatin-like phospholipase domain containing protein 6, also known as neuropathy target esterase (NTE), which is the target of toxic organophosphates that induce human paralysis due to severe axonopathy of large neurons. Mutations in PNPLA6 also cause human spastic paraplegia characterized by motor neuron degeneration. Here we identify PNPLA6 mutations in childhood blindness in seven families with retinal degeneration, including Leber congenital amaurosis and Oliver McFarlane syndrome. PNPLA6 localizes mostly at the inner segment plasma membrane in photoreceptors and mutations in Drosophila PNPLA6 lead to photoreceptor cell death. We also report that lysophosphatidylcholine and lysophosphatidic acid levels are elevated in mutant Drosophila. These findings show a role for PNPLA6 in photoreceptor survival and identify phospholipid metabolism as a potential therapeutic target for some forms of blindness.
Keywords: Amino Acid Sequence; Animals; Blindness; Child; Child, Preschool; Drosophila; Female; Humans; Male; Mice; Mice, Inbred C57BL; Microscopy, Fluorescence; Molecular Sequence Data; Mutation; Pedigree; Phenotype; Phospholipases; Phospholipids; Retina; Retinal Degeneration; Sequence Analysis, DNA; Sequence Homology, Amino Acid; Spectrometry, Mass, Electrospray Ionization

Non-coding genetic variants in human disease. - Zhang, Feng; Lupski, James R (Hum Mol Genet, 2015)
Genetic variants, including single-nucleotide variants (SNVs) and copy number variants (CNVs), in the non-coding regions of the human genome can play an important role in human traits and complex diseases. Most of the genome-wide association study (GWAS) signals map to non-coding regions and potentially point to non-coding variants, whereas their functional interpretation is challenging. In this review, we discuss the human non-coding variants and their contributions to human diseases in the following four parts. (i) Functional annotations of non-coding SNPs mapped by GWAS: we discuss recent progress revealing some of the molecular mechanisms for GWAS signals affecting gene function. (ii) Technical progress in interpretation of non-coding variants: we briefly describe some of the technologies for functional annotations of non-coding variants, including the methods for genome-wide mapping of chromatin interaction, computational tools for functional predictions and the new genome editing technologies useful for dissecting potential functional consequences of non-coding variants. (iii) Non-coding CNVs in human diseases: we review our emerging understanding the role of non-coding CNVs in human disease. (iv) Compound inheritance of large genomic deletions and non-coding variants: compound inheritance at a locus consisting of coding variants plus non-coding ones is described.
Keywords: Animals; Disease; DNA Copy Number Variations; Genetic Variation; Genome-Wide Association Study; Humans; Polymorphism, Single Nucleotide; Regulatory Sequences, Nucleic Acid

Somatic mosaicism: implications for disease and transmission genetics. - Campbell, Ian M; Shaw, Chad A; Stankiewicz, Pawel; Lupski, James R (Trends Genet, 2015)
Nearly all of the genetic material among cells within an organism is identical. However, single-nucleotide variants (SNVs), small insertions/deletions (indels), copy-number variants (CNVs), and other structural variants (SVs) continually accumulate as cells divide during development. This process results in an organism composed of countless cells, each with its own unique personal genome. Thus, every human is undoubtedly mosaic. Mosaic mutations can go unnoticed, underlie genetic disease or normal human variation, and may be transmitted to the next generation as constitutional variants. We review the influence of the developmental timing of mutations, the mechanisms by which they arise, methods for detecting mosaic variants, and the risk of passing these mutations on to the next generation.
Keywords: Animals; Genetic Diseases, Inborn; Genome, Human; Humans; Mosaicism; Mutagenesis, Insertional; Mutation; Polymorphism, Single Nucleotide; Risk; Trinucleotide Repeat Expansion

Spata7 is a retinal ciliopathy gene critical for correct RPGRIP1 localization and protein trafficking in the retina. - Eblimit, Aiden; Nguyen, Thanh-Minh T; Chen, Yiyun; Esteve-Rudd, Julian; Zhong, Hua; Letteboer, Stef; van Reeuwijk, Jeroen; Simons, David L; Ding, Qian; Wu, Ka Man; Yumei Li; Van Beersum, Sylvia; et al. (Hum Mol Genet, 2015)
Leber congenital amaurosis (LCA) and juvenile retinitis pigmentosa (RP) are severe hereditary diseases that causes visual impairment in infants and children. SPATA7 has recently been identified as the LCA3 and juvenile RP gene in humans, whose function in the retina remains elusive. Here, we show that SPATA7 localizes at the primary cilium of cells and at the connecting cilium (CC) of photoreceptor cells, indicating that SPATA7 is a ciliary protein. In addition, SPATA7 directly interacts with the retinitis pigmentosa GTPase regulator interacting protein 1 (RPGRIP1), a key connecting cilium protein that has also been linked to LCA. In the retina of Spata7 null mutant mice, a substantial reduction of RPGRIP1 levels at the CC of photoreceptor cells is observed, suggesting that SPATA7 is required for the stable assembly and localization of the ciliary RPGRIP1 protein complex. Furthermore, our results pinpoint a role of this complex in protein trafficking across the CC to the outer segments, as we identified that rhodopsin accumulates in the inner segments and around the nucleus of photoreceptors. This accumulation then likely triggers the apoptosis of rod photoreceptors that was observed. Loss of Spata7 function in mice indeed results in a juvenile RP-like phenotype, characterized by progressive degeneration of photoreceptor cells and a strongly decreased light response. Together, these results indicate that SPATA7 functions as a key member of a retinal ciliopathy-associated protein complex, and that apoptosis of rod photoreceptor cells triggered by protein mislocalization is likely the mechanism of disease progression in LCA3/ juvenile RP patients.
Keywords: Animals; Apoptosis; Cattle; Cytoskeletal Proteins; DNA-Binding Proteins; Gene Deletion; Humans; Mice; Mice, Mutant Strains; Photoreceptor Connecting Cilium; Protein Transport; Proteins; Retinal Cone Photoreceptor Cells; Retinal Rod Photoreceptor Cells; Rhodopsin

Structure-activity analysis of human ghrelin O-acyltransferase reveals chemical determinants of ghrelin selectivity and acyl group recognition. - Darling, Joseph E; Zhao, Feifei; Loftus, Rosemary J; Patton, Leslie M; Richard A Gibbs; Hougland, James L (Biochemistry, 2015)
Ghrelin O-acyltransferase (GOAT) is an integral membrane acyltransferase responsible for catalyzing a serine-octanoylation posttranslational modification within the peptide hormone ghrelin. Ghrelin requires this octanoylation for its biological activity in stimulating appetite and in regulating other physiological pathways involved in energy balance. Blocking ghrelin acylation using GOAT inhibitors is a new potential avenue to treat health conditions impacted by ghrelin signaling, such as obesity and diabetes. Designing novel and potent GOAT inhibitors as potential therapeutics requires insight into the interactions between the ghrelin and octanoyl coenzyme A substrates and the GOAT active site. Through structure-activity investigation of ghrelin-mimetic peptide substrates and inhibitors, we have analyzed the amino acid selectivity of the enzyme as well as the functional groups involved in substrate recognition by human GOAT (hGOAT). This analysis reveals that hGOAT both prefers and tolerates a distinct set of chemical properties at each position within the N-terminal sequence of ghrelin and that sequence elements downstream of the ghrelin N-terminal sequence contribute to ghrelin binding to hGOAT. We also found that the hGOAT active site exhibits a marked preference for binding an eight-carbon acyl chain, which potentially explains the biological observation of ghrelin octanoylation in light of the acyl donor promiscuity reported for GOAT. Bioinformatics analysis, guided by our reactivity data, supports the conclusion that ghrelin is a unique substrate for hGOAT within the human proteome, providing further justification for the ghrelin-hGOAT system as a desirable drug target. By defining an array of substrate-enzyme interactions used by hGOAT to bind, recognize, and acylate ghrelin, this study yields novel insight into the character of the hGOAT active site that can serve as a guide toward the rational design of hGOAT inhibitors.
Keywords: Acylation; Acyltransferases; Amino Acid Sequence; Animals; Cell Line; Ghrelin; Humans; Insecta; Molecular Sequence Data; Protein Binding; Structure-Activity Relationship

Teaser: Individualized benchmarking and optimization of read mapping results for NGS data. - Smolka, Moritz; Rescheneder, Philipp; Schatz, Michael C; von Haeseler, Arndt; Fritz J Sedlazeck (Genome Biol, 2015)
Mapping reads to a genome remains challenging, especially for non-model organisms with lower quality assemblies, or for organisms with higher mutation rates. While most research has focused on speeding up the mapping process, little attention has been paid to optimize the choice of mapper and parameters for a user's dataset. Here, we present Teaser, a software that assists in these choices through rapid automated benchmarking of different mappers and parameter settings for individualized data. Within minutes, Teaser completes a quantitative evaluation of an ensemble of mapping algorithms and parameters. We use Teaser to demonstrate how Bowtie2 can be optimized for different data.
Keywords: Animals; Benchmarking; Genomics; High-Throughput Nucleotide Sequencing; Perciformes; Sequence Alignment; Software

Tissue-specific transcriptome sequencing analysis expands the non-human primate reference transcriptome resource (NHPRTR). - Peng, Xinxia; Thierry-Mieg, Jean; Thierry-Mieg, Danielle; Nishida, Andrew; Pipes, Lenore; Bozinoski, Marjan; Thomas, Matthew J; Kelly, Sara; Weiss, Jeffrey M; Raveendran, Muthuswamy; Donna M Muzny; Richard A Gibbs; et al. (Nucleic Acids Res, 2015)
The non-human primate reference transcriptome resource (NHPRTR, available online at http://nhprtr.org/) aims to generate comprehensive RNA-seq data from a wide variety of non-human primates (NHPs), from lemurs to hominids. In the 2012 Phase I of the NHPRTR project, 19 billion fragments or 3.8 terabases of transcriptome sequences were collected from pools of ∼ 20 tissues in 15 species and subspecies. Here we describe a major expansion of NHPRTR by adding 10.1 billion fragments of tissue-specific RNA-seq data. For this effort, we selected 11 of the original 15 NHP species and subspecies and constructed total RNA libraries for the same ∼ 15 tissues in each. The sequence quality is such that 88% of the reads align to human reference sequences, allowing us to compute the full list of expression abundance across all tissues for each species, using the reads mapped to human genes. This update also includes improved transcript annotations derived from RNA-seq data for rhesus and cynomolgus macaques, two of the most commonly used NHP models and additional RNA-seq data compiled from related projects. Together, these comprehensive reference transcriptomes from multiple primates serve as a valuable community resource for genome annotation, gene dynamics and comparative functional analysis.
Keywords: Animals; Databases, Genetic; Gene Expression Profiling; Internet; Macaca; Molecular Sequence Annotation; Organ Specificity; Primates; Reference Standards; Sequence Alignment; Sequence Analysis, RNA

Whole-exome sequencing points to considerable genetic heterogeneity of cerebral palsy. - McMichael, G; Bainbridge, M N; Haan, E; Corbett, M; Gardner, A; Thompson, S; van Bon, B W M; van Eyk, C L; Broadbent, J; Reynolds, C; O'Callaghan, M E; Nguyen, L S; et al. (Mol Psychiatry, 2015)
Cerebral palsy (CP) is a common, clinically heterogeneous group of disorders affecting movement and posture. Its prevalence has changed little in 50 years and the causes remain largely unknown. The genetic contribution to CP causation has been predicted to be ~2%. We performed whole-exome sequencing of 183 cases with CP including both parents (98 cases) or one parent (67 cases) and 18 singleton cases (no parental DNA). We identified and validated 61 de novo protein-altering variants in 43 out of 98 (44%) case-parent trios. Initial prioritization of variants for causality was by mutation type, whether they were known or predicted to be deleterious and whether they occurred in known disease genes whose clinical spectrum overlaps CP. Further, prioritization used two multidimensional frameworks-the Residual Variation Intolerance Score and the Combined Annotation-dependent Depletion score. Ten de novo mutations in three previously identified disease genes (TUBA1A (n=2), SCN8A (n=1) and KDM5C (n=1)) and in six novel candidate CP genes (AGAP1, JHDM1D, MAST1, NAA35, RFX2 and WIPI2) were predicted to be potentially pathogenic for CP. In addition, we identified four predicted pathogenic, hemizygous variants on chromosome X in two known disease genes, L1CAM and PAK3, and in two novel candidate CP genes, CD99L2 and TENM1. In total, 14% of CP cases, by strict criteria, had a potentially disease-causing gene variant. Half were in novel genes. The genetic heterogeneity highlights the complexity of the genetic contribution to CP. Function and pathway studies are required to establish the causative role of these putative pathogenic CP genes.
Keywords: Adult; Animals; Cerebral Palsy; Cohort Studies; Exome; Female; Gene Library; Genetic Heterogeneity; Genetic Predisposition to Disease; Gestational Age; Humans; Male; Mutation; Parents; Sequence Analysis, DNA

ADAR2 induces reproducible changes in sequence and abundance of mature microRNAs in the mouse brain. - Vesely, Cornelia; Tauber, Stefanie; Fritz J Sedlazeck; Tajaddod, Mansoureh; von Haeseler, Arndt; Jantsch, Michael F (Nucleic Acids Res, 2014)
Adenosine deaminases that act on RNA (ADARs) deaminate adenosines to inosines in double-stranded RNAs including miRNA precursors. A to I editing is widespread and required for normal life. By comparing deep sequencing data of brain miRNAs from wild-type and ADAR2 deficient mouse strains, we detect editing sites and altered miRNA processing at high sensitivity. We detect 48 novel editing events in miRNAs. Some editing events reach frequencies of up to 80%. About half of all editing events depend on ADAR2 while some miRNAs are preferentially edited by ADAR1. Sixty-four percent of all editing events are located within the seed region of mature miRNAs. For the highly edited miR-3099, we experimentally prove retargeting of the edited miRNA to novel 3' UTRs. We show further that an abundant editing event in miR-497 promotes processing by Drosha of the corresponding pri-miRNA. We also detect reproducible changes in the abundance of specific miRNAs in ADAR2-deficient mice that occur independent of adjacent A to I editing events. This indicates that ADAR2 binding but not editing of miRNA precursors may influence their processing. Correlating with changes in miRNA abundance we find misregulation of putative targets of these miRNAs in the presence or absence of ADAR2.
Keywords: Adenosine Deaminase; Animals; Base Sequence; Brain; Cell Line; HEK293 Cells; Humans; Mice; Mice, Knockout; MicroRNAs; RNA Editing; RNA Processing, Post-Transcriptional; RNA-Binding Proteins

Analysis of prostate-specific antigen transcripts in chimpanzees, cynomolgus monkeys, baboons, and African green monkeys. - Mubiru, James N; Yang, Alice S; Olsen, Christian; Nayak, Sudhir; Livi, Carolina B; Dick, Edward J; Owston, Michael; Garcia-Forey, Magdalena; Shade, Robert E; Jeffrey Rogers (PLoS One, 2014)
The function of prostate-specific antigen (PSA) is to liquefy the semen coagulum so that the released sperm can fuse with the ovum. Fifteen spliced variants of the PSA gene have been reported in humans, but little is known about alternative splicing in nonhuman primates. Positive selection has been reported in sex- and reproductive-related genes from sea urchins to Drosophila to humans; however, there are few studies of adaptive evolution of the PSA gene. Here, using polymerase chain reaction (PCR) product cloning and sequencing, we study PSA transcript variant heterogeneity in the prostates of chimpanzees (Pan troglodytes), cynomolgus monkeys (Macaca fascicularis), baboons (Papio hamadryas anubis), and African green monkeys (Chlorocebus aethiops). Six PSA variants were identified in the chimpanzee prostate, but only two variants were found in cynomolgus monkeys, baboons, and African green monkeys. In the chimpanzee the full-length transcript is expressed at the same magnitude as the transcripts that retain intron 3. We have found previously unidentified splice variants of the PSA gene, some of which might be linked to disease conditions. Selection on the PSA gene was studied in 11 primate species by computational methods using the sequences reported here for African green monkey, cynomolgus monkey, baboon, and chimpanzee and other sequences available in public databases. A codon-based analysis (dN/dS) of the PSA gene identified potential adaptive evolution at five residue sites (Arg45, Lys70, Gln144, Pro189, and Thr203).
Keywords: Alternative Splicing; Amino Acid Sequence; Animals; Base Sequence; Bayes Theorem; Chlorocebus aethiops; Cloning, Molecular; Codon; Introns; Likelihood Functions; Macaca fascicularis; Male; Molecular Sequence Data; Pan troglodytes; Papio; Phylogeny; Prostate-Specific Antigen; Real-Time Polymerase Chain Reaction; RNA, Messenger

Association of low-frequency and rare coding-sequence variants with blood lipids and coronary heart disease in 56,000 whites and blacks. - Peloso, Gina M; Auer, Paul L; Bis, Joshua C; Voorman, Arend; Morrison, Alanna C; Stitziel, Nathan O; Brody, Jennifer A; Khetarpal, Sumeet A; Crosby, Jacy R; Fornage, Myriam; Isaacs, Aaron; Jakobsdottir, Johanna; et al. (Am J Hum Genet, 2014)
Low-frequency coding DNA sequence variants in the proprotein convertase subtilisin/kexin type 9 gene (PCSK9) lower plasma low-density lipoprotein cholesterol (LDL-C), protect against risk of coronary heart disease (CHD), and have prompted the development of a new class of therapeutics. It is uncertain whether the PCSK9 example represents a paradigm or an isolated exception. We used the "Exome Array" to genotype >200,000 low-frequency and rare coding sequence variants across the genome in 56,538 individuals (42,208 European ancestry [EA] and 14,330 African ancestry [AA]) and tested these variants for association with LDL-C, high-density lipoprotein cholesterol (HDL-C), and triglycerides. Although we did not identify new genes associated with LDL-C, we did identify four low-frequency (frequencies between 0.1% and 2%) variants (ANGPTL8 rs145464906 [c.361C>T; p.Gln121*], PAFAH1B2 rs186808413 [c.482C>T; p.Ser161Leu], COL18A1 rs114139997 [c.331G>A; p.Gly111Arg], and PCSK7 rs142953140 [c.1511G>A; p.Arg504His]) with large effects on HDL-C and/or triglycerides. None of these four variants was associated with risk for CHD, suggesting that examples of low-frequency coding variants with robust effects on both lipids and CHD will be limited.
Keywords: 1-Alkyl-2-acetylglycerophosphocholine Esterase; Adult; Aged; Alleles; Animals; Black People; Cholesterol, HDL; Cholesterol, LDL; Cohort Studies; Coronary Disease; Female; Gene Frequency; Genetic Association Studies; Genetic Code; Genetic Variation; Humans; Linear Models; Male; Mice; Mice, Inbred C57BL; Microtubule-Associated Proteins; Middle Aged; Phenotype; Sequence Analysis, DNA; Subtilisins; Triglycerides; White People

The common marmoset genome provides insight into primate biology and evolution. (Nat Genet, 2014)
We report the whole-genome sequence of the common marmoset (Callithrix jacchus). The 2.26-Gb genome of a female marmoset was assembled using Sanger read data (6×) and a whole-genome shotgun strategy. A first analysis has permitted comparison with the genomes of apes and Old World monkeys and the identification of specific features that might contribute to the unique biology of this diminutive primate, including genetic changes that may influence body size, frequent twinning and chimerism. We observed positive selection in growth hormone/insulin-like growth factor genes (growth pathways), respiratory complex I genes (metabolic pathways), and genes encoding immunobiological factors and proteases (reproductive and immunity pathways). In addition, both protein-coding and microRNA genes related to reproduction exhibited evidence of rapid sequence evolution. This genome sequence for a New World monkey enables increased power for comparative analyses among available primate genomes and facilitates biomedical research application.
Keywords: Amino Acid Sequence; Animals; Callithrix; Evolution, Molecular; Female; Genome; MicroRNAs; Molecular Sequence Data; Phylogeny; Polymorphism, Single Nucleotide; Reproduction; Sequence Analysis, DNA

Comparative primate genomics: emerging patterns of genome content and dynamics. - Jeffrey Rogers; Richard A Gibbs (Nat Rev Genet, 2014)
Advances in genome sequencing technologies have created new opportunities for comparative primate genomics. Genome assemblies have been published for various primate species, and analyses of several others are underway. Whole-genome assemblies for the great apes provide remarkable new information about the evolutionary origins of the human genome and the processes involved. Genomic data for macaques and other non-human primates offer valuable insights into genetic similarities and differences among species that are used as models for disease-related research. This Review summarizes current knowledge regarding primate genome content and dynamics, and proposes a series of goals for the near future.
Keywords: Animals; Base Sequence; Evolution, Molecular; Genetic Speciation; Genetic Variation; Genome; Genome, Human; Genomics; Humans; Primates

Comparative validation of the D. melanogaster modENCODE transcriptome annotation. - Chen, Zhen-Xia; Sturgill, David; Qu, Jiaxin; Jiang, Huaiyang; Park, Soo; Boley, Nathan; Suzuki, Ana Maria; Fletcher, Anthony R; Plachetzki, David C; FitzGerald, Peter C; Artieri, Carlo G; Atallah, Joel; et al. (Genome Res, 2014)
Accurate gene model annotation of reference genomes is critical for making them useful. The modENCODE project has improved the D. melanogaster genome annotation by using deep and diverse high-throughput data. Since transcriptional activity that has been evolutionarily conserved is likely to have an advantageous function, we have performed large-scale interspecific comparisons to increase confidence in predicted annotations. To support comparative genomics, we filled in divergence gaps in the Drosophila phylogeny by generating draft genomes for eight new species. For comparative transcriptome analysis, we generated mRNA expression profiles on 81 samples from multiple tissues and developmental stages of 15 Drosophila species, and we performed cap analysis of gene expression in D. melanogaster and D. pseudoobscura. We also describe conservation of four distinct core promoter structures composed of combinations of elements at three positions. Overall, each type of genomic feature shows a characteristic divergence rate relative to neutral models, highlighting the value of multispecies alignment in annotating a target genome that should prove useful in the annotation of other high priority genomes, especially human and other mammalian genomes that are rich in noncoding sequences. We report that the vast majority of elements in the annotation are evolutionarily conserved, indicating that the annotation will be an important springboard for functional genetic testing by the Drosophila community.
Keywords: Animals; Cluster Analysis; Computational Biology; Drosophila melanogaster; Evolution, Molecular; Exons; Female; Gene Expression Profiling; Genome, Insect; Humans; Male; Molecular Sequence Annotation; Nucleotide Motifs; Phylogeny; Position-Specific Scoring Matrices; Promoter Regions, Genetic; Reproducibility of Results; RNA Editing; RNA Splice Sites; RNA Splicing; Transcription Initiation Site; Transcriptome

Drosophila eyes absent is required for normal cone and pigment cell development. - Karandikar, Umesh C; Jin, Meng; Jusiak, Barbara; Kwak, SuJin; Rui Chen; Mardon, Graeme (PLoS One, 2014)
In Drosophila, development of the compound eye is orchestrated by a network of highly conserved transcriptional regulators known as the retinal determination (RD) network. The retinal determination gene eyes absent (eya) is expressed in most cells within the developing eye field, from undifferentiated retinal progenitors to photoreceptor cells whose differentiation begins at the morphogenetic furrow (MF). Loss of eya expression leads to an early block in retinal development, making it impossible to study the role of eya expression during later steps of retinal differentiation. We have identified two new regulatory regions that control eya expression during retinal development. These two enhancers are necessary to maintain eya expression anterior to the MF (eya-IAM) and in photoreceptors (eya-PSE), respectively. We find that deleting these enhancers affects developmental events anterior to the MF as well as retinal differentiation posterior to the MF. In line with previous results, we find that reducing eya expression anterior to the MF affects several early steps during early retinal differentiation, including cell cycle arrest and expression of the proneural gene ato. Consistent with previous observations that suggest a role for eya in cell proliferation during early development we find that deletion of eya-IAM leads to a marked reduction in the size of the adult retinal field. On the other hand, deletion of eya-PSE leads to defects in cone and pigment cell development. In addition we find that eya expression is necessary to activate expression of the cone cell marker Cut and to regulate levels of the Hedgehog pathway effector Ci. In summary, our study uncovers novel aspects of eya-mediated regulation of eye development. The genetic tools generated in this study will allow for a detailed study of how the RD network regulates key steps in eye formation.
Keywords: Animals; Basic Helix-Loop-Helix Transcription Factors; Cell Cycle Checkpoints; Cell Differentiation; DNA-Binding Proteins; Drosophila melanogaster; Drosophila Proteins; Enhancer Elements, Genetic; Eye Proteins; Gene Expression Regulation, Developmental; Homeodomain Proteins; Larva; Nerve Tissue Proteins; Nuclear Proteins; Organogenesis; Retinal Cone Photoreceptor Cells; Retinal Pigment Epithelium; Transcription Factors

A drosophila genetic resource of mutants to study mechanisms underlying human genetic diseases. - Yamamoto, Shinya; Jaiswal, Manish; Charng, Wu-Lin; Gambin, Tomasz; Karaca, Ender; Mirzaa, Ghayda; Wiszniewski, Wojciech; Sandoval, Hector; Haelterman, Nele A; Xiong, Bo; Zhang, Ke; Bayat, Vafa; et al. (Cell, 2014)
Invertebrate model systems are powerful tools for studying human disease owing to their genetic tractability and ease of screening. We conducted a mosaic genetic screen of lethal mutations on the Drosophila X chromosome to identify genes required for the development, function, and maintenance of the nervous system. We identified 165 genes, most of whose function has not been studied in vivo. In parallel, we investigated rare variant alleles in 1,929 human exomes from families with unsolved Mendelian disease. Genes that are essential in flies and have multiple human homologs were found to be likely to be associated with human diseases. Merging the human data sets with the fly genes allowed us to identify disease-associated mutations in six families and to provide insights into microcephaly associated with brain dysgenesis. This bidirectional synergism between fly genetics and human genomics facilitates the functional annotation of evolutionarily conserved genes involved in human health.
Keywords: Animals; Disease; Disease Models, Animal; Drosophila melanogaster; Genetic Testing; Humans; Inheritance Patterns; RNA Interference; X Chromosome

The effect of dietary fat intake on hepatic gene expression in LG/J AND SM/J mice. - Partridge, Charlyn G; Fawcett, Gloria L; Wang, Bing; Semenkovich, Clay F; Cheverud, James M (BMC Genomics, 2014)
BACKGROUND: The liver plays a major role in regulating metabolic homeostasis and is vital for nutrient metabolism. Identifying the genetic factors regulating these processes could lead to a greater understanding of how liver function responds to a high-fat diet and how that response may influence susceptibilities to obesity and metabolic syndrome. In this study we examine differences in hepatic gene expression between the LG/J and SM/J inbred mouse strains and how gene expression in these strains is affected by high-fat diet. LG/J and SM/J are known to differ in their responses to a high-fat diet for a variety of obesity- and diabetes-related traits, with the SM/J strain exhibiting a stronger phenotypic response to diet. RESULTS: Dietary intake had a significant effect on gene expression in both inbred lines. Genes up-regulated by a high-fat diet were involved in biological processes such as lipid and carbohydrate metabolism; protein and amino acid metabolic processes were down regulated on a high-fat diet. A total of 259 unique transcripts exhibited a significant diet-by-strain interaction. These genes tended to be associated with immune function. In addition, genes involved in biochemical processes related to non-alcoholic fatty liver disease (NAFLD) manifested different responses to diet between the two strains. For most of these genes, SM/J had a stronger response to the high-fat diet than LG/J. CONCLUSIONS: These data show that dietary fat impacts gene expression levels in SM/J relative to LG/J, with SM/J exhibiting a stronger response. This supports previous data showing that SM/J has a stronger phenotypic response to high-fat diet. Based upon these findings, we suggest that SM/J and its cross with the LG/J strain provide a good model for examining non-alcoholic fatty liver disease and its role in metabolic syndrome.
Keywords: Animals; Diabetes Mellitus; Diet, High-Fat; Down-Regulation; Female; Liver; Male; Mice; Mice, Inbred Strains; Non-alcoholic Fatty Liver Disease; Obesity; Quantitative Trait Loci; Up-Regulation

Epigenomic profiling of young and aged HSCs reveals concerted changes during aging that reinforce self-renewal. - Sun, Deqiang; Luo, Min; Jeong, Mira; Rodriguez, Benjamin; Xia, Zheng; Hannah, Rebecca; Wang, Hui; Le, Thuc; Faull, Kym F; Rui Chen; Gu, Hongcang; Bock, Christoph; et al. (Cell Stem Cell, 2014)
To investigate the cell-intrinsic aging mechanisms that erode the function of somatic stem cells during aging, we have conducted a comprehensive integrated genomic analysis of young and aged cells. We profiled the transcriptome, DNA methylome, and histone modifications of young and old murine hematopoietic stem cells (HSCs). Transcriptome analysis indicated reduced TGF-β signaling and perturbation of genes involved in HSC proliferation and differentiation. Aged HSCs exhibited broader H3K4me3 peaks across HSC identity and self-renewal genes and showed increased DNA methylation at transcription factor binding sites associated with differentiation-promoting genes combined with a reduction at genes associated with HSC maintenance. Altogether, these changes reinforce HSC self-renewal and diminish differentiation, paralleling phenotypic HSC aging behavior. Ribosomal biogenesis emerged as a particular target of aging with increased transcription of ribosomal protein and RNA genes and hypomethylation of rRNA genes. This data set will serve as a reference for future epigenomic analysis of stem cell aging.
Keywords: Animals; Cell Differentiation; Cells, Cultured; Cellular Senescence; Chromatin Immunoprecipitation; Epigenomics; Hematopoietic Stem Cells; Male; Mice; Transforming Growth Factor beta

Evidence for stabilizing selection on codon usage in chromosomal rearrangements of Drosophila pseudoobscura. - Fuller, Zachary L; Haynes, Gwilym D; Zhu, Dianhui; Batterton, Matthew; Chao, Hsu; Dugan, Shannon; Javaid, Mehwish; Jayaseelan, Joy C; Lee, Sandra; Li, Mingmei; Ongeri, Fiona; Qi, Sulan; et al. (G3 (Bethesda), 2014)
There has been a renewed interest in investigating the role of stabilizing selection acting on genome-wide traits such as codon usage bias. Codon bias, when synonymous codons are used at unequal frequencies, occurs in a wide variety of taxa. Standard evolutionary models explain the maintenance of codon bias through a balance of genetic drift, mutation and weak purifying selection. The efficacy of selection is expected to be reduced in regions of suppressed recombination. Contrary to observations in Drosophila melanogaster, some recent studies have failed to detect a relationship between the recombination rate, intensity of selection acting at synonymous sites, and the magnitude of codon bias as predicted under these standard models. Here, we examined codon bias in 2798 protein coding loci on the third chromosome of D. pseudoobscura using whole-genome sequences of 47 individuals, representing five common third chromosome gene arrangements. Fine-scale recombination maps were constructed using more than 1 million segregating sites. As expected, recombination was demonstrated to be significantly suppressed between chromosome arrangements, allowing for a direct examination of the relationship between recombination, selection, and codon bias. As with other Drosophila species, we observe a strong mutational bias away from the most frequently used codons. We find the rate of synonymous and nonsynonymous polymorphism is variable between different amino acids. However, we do not observe a reduction in codon bias or the strength of selection in regions of suppressed recombination as expected. Instead, we find that the interaction between weak stabilizing selection and mutational bias likely plays a role in shaping the composition of synonymous codons across the third chromosome in D. pseudoobscura.
Keywords: Animals; Chromosomes; Codon; Drosophila; High-Throughput Nucleotide Sequencing; Polymorphism, Single Nucleotide; Recombination, Genetic; Selection, Genetic; Sequence Analysis, DNA

Evolutionary genetics and implications of small size and twinning in callitrichine primates. - R. Alan Harris; Tardif, Suzette D; Vinar, Tomas; Wildman, Derek E; Rutherford, Julienne N; Jeffrey Rogers; Worley, Kim C; Aagaard, Kjersti M (Proc Natl Acad Sci U S A, 2014)
New World monkeys (NWMs) are characterized by an extensive size range, with clawed NWMs (subfamily Callitrichinae, or callitrichines) such as the common marmoset manifesting diminutive size and unique reproductive adaptations. Perhaps the most notable of these adaptations is their propensity toward multiple gestations (i.e., dichorionic twins and trichorionic triplets). Indeed, with the exception of Goeldi's monkey (Callimico), callitrichine singleton pregnancies rarely occur. Multiple gestations seem to have coevolved with a suite of reproductive adaptations, including hematopoetic chimerism of siblings, suppression of reproduction in nondominant females, and cooperative alloparenting. The sequencing of the common marmoset (Callithrix jacchus) genome offers the opportunity to explore the genetic basis of these unusual traits within this primate lineage. In this study, we hypothesized that genetic changes arising during callitrichine evolution resulted in multiple ovulated ova with each cycle, and that these changes triggered adaptations that minimized complications common to multiple gestations in other primates, including humans. Callitrichine-specific nonsynonymous substitutions were identified in GDF9, BMP15, BMP4, and WFIKKN1. WFIKKN1, a multidomain protease inhibitor that binds growth factors and bone morphogenetic proteins, has nonsynonymous changes found exclusively in common marmosets and other tested callitrichine species that twin. In the one callitrichine species that does not produce twins (Callimico), this change has reverted back to the ancestral (nontwinning) primate sequence. Polymorphisms in GDF9 occur among human cohorts with a propensity for dizygotic twins, and polymorphisms in GDF9 and BMP15 are associated with twinning in sheep. We postulate that positive selection affected NWM growth patterns, with callitrichine miniaturization coevolving with a series of reproductive adaptations.
Keywords: Animals; Body Size; Callithrix; Evolution, Molecular; Female; Reproduction

The first myriapod genome sequence reveals conservative arthropod gene content and genome organisation in the centipede Strigamia maritima. - Chipman, Ariel D; Ferrier, David E K; Brena, Carlo; Qu, Jiaxin; Hughes, Daniel S T; Schröder, Reinhard; Torres-Oliva, Montserrat; Znassi, Nadia; Jiang, Huaiyang; Almeida, Francisca C; Alonso, Claudio R; Apostolou, Zivkos; et al. (PLoS Biol, 2014)
Myriapods (e.g., centipedes and millipedes) display a simple homonomous body plan relative to other arthropods. All members of the class are terrestrial, but they attained terrestriality independently of insects. Myriapoda is the only arthropod class not represented by a sequenced genome. We present an analysis of the genome of the centipede Strigamia maritima. It retains a compact genome that has undergone less gene loss and shuffling than previously sequenced arthropods, and many orthologues of genes conserved from the bilaterian ancestor that have been lost in insects. Our analysis locates many genes in conserved macro-synteny contexts, and many small-scale examples of gene clustering. We describe several examples where S. maritima shows different solutions from insects to similar problems. The insect olfactory receptor gene family is absent from S. maritima, and olfaction in air is likely effected by expansion of other receptor gene families. For some genes S. maritima has evolved paralogues to generate coding sequence diversity, where insects use alternate splicing. This is most striking for the Dscam gene, which in Drosophila generates more than 100,000 alternate splice forms, but in S. maritima is encoded by over 100 paralogues. We see an intriguing linkage between the absence of any known photosensory proteins in a blind organism and the additional absence of canonical circadian clock genes. The phylogenetic position of myriapods allows us to identify where in arthropod phylogeny several particular molecular mechanisms and traits emerged. For example, we conclude that juvenile hormone signalling evolved with the emergence of the exoskeleton in the arthropods and that RR-1 containing cuticle proteins evolved in the lineage leading to Mandibulata. We also identify when various gene expansions and losses occurred. The genome of S. maritima offers us a unique glimpse into the ancestral arthropod genome, while also displaying many adaptations to its specific life history.
Keywords: Animals; Arthropods; Circadian Rhythm Signaling Peptides and Proteins; DNA Methylation; Evolution, Molecular; Female; Genome; Genome, Mitochondrial; Hormones; Male; Multigene Family; Phylogeny; Polymorphism, Genetic; Protein Kinases; Receptors, Odorant; RNA, Untranslated; Selenoproteins; Sex Chromosomes; Synteny; Transcription Factors

Functional analysis of miR-34c as a putative tumor suppressor in high-grade serous ovarian cancer. - Yu, Zhifeng; Kim, Jaeyeon; He, Lin; Creighton, Chad J; Gunaratne, Preethi H; Hawkins, Shannon M; Matzuk, Martin M (Biol Reprod, 2014)
Altered microRNA expression patterns are implicated in the formation of many human diseases, including ovarian cancer. Our laboratory previously created Dicer(fl/fl)/Pten(fl/fl)/Amhr2(cre/+) mice, which developed high-grade serous carcinomas originating from mouse fallopian tubes, while neither Dicer(fl/fl)/Amhr2(cre/+) nor Pten(fl/fl)/Amhr2(cre/+) mice developed tumors. To explore miRNAs involved in the tumorigenesis in the double-knockout (DKO) mice, tumor cell lines were established from mouse primary tumors, and the most abundant miRNAs present in mouse normal fallopian tubes, let-7b and miR-34c, were expressed in these cell lines. We found that miR-34c had a more dramatic effect on inhibiting tumor cell viability than let-7b. The action of miR-34c induced tumor cell cycle arrest in G1 phase and apoptosis, and was accompanied with the regulation of key genes involved in cell proliferation and cell cycle G1/S transition. miR-34c suppressed the expression of Ezh2 and Mybl2, which may transcriptionally and functionally activate Cdkn1c. Furthermore, miR-34c levels are extremely low in human serous adenocarcinomas compared with human normal fallopian tubes. Expression of miR-34c in human ovarian cancer cells phenocopied its effects in DKO mouse tumor cells. However, miR-34b/c(-/-)/Pten(fl/fl)/Amhr2(cre/+) mice failed to develop high-grade serous carcinomas, implicating a combination of miRNAs in the tumorigenesis process. Thus, while miR-34c is a putative tumor suppressor in high-grade serous ovarian carcinoma with potential therapeutic advantages, screening of additional miRNAs for their effects alone and in combination with miR-34c is highly warranted to uncover miRNAs that synergize with miR-34c against cancer.
Keywords: Animals; Cell Line, Tumor; Cystadenocarcinoma, Serous; DEAD-box RNA Helicases; Fallopian Tubes; Female; Gene Expression Regulation, Neoplastic; Genes, Tumor Suppressor; Humans; Mice; Mice, Knockout; MicroRNAs; Neoplasm Grading; Ovarian Neoplasms; PTEN Phosphohydrolase; Ribonuclease III

Further evidence for phenotypic signatures of hybridization in descendant baboon populations. - Ackermann, Rebecca R; Schroeder, Lauren; Jeffrey Rogers; Cheverud, James M (J Hum Evol, 2014)
Hybridization may have played a substantial role in shaping the diversity of our evolving lineage. Although recent genomic evidence has shown that hybridization occurred between anatomically modern humans (AMHS) and Neanderthals, it remains difficult to pin down precisely where and when this gene flow took place. Investigations of the hybrid phenotype in primates and other mammals are providing models for identifying signatures of hybridization in the fossil record. However, our understanding of intra- and inter-taxon variation in hybrids is still limited. Moreover, there is little evidence from these studies that is pertinent to the question of how long hybrid skeletal traits persist in descendants, and therefore it is not clear whether observed hybrid phenotypes are evidence of recent (e.g., F1) or much earlier hybridization events. Here, we present an analysis updating a previous study of cranial variation in pedigreed olive and yellow baboons and their hybrids. Results suggest that traits previously associated with hybrids in baboons and other mammalian species are also present in this expanded data set; many of these traits are highly heritable, confirming a genetic basis for their variation in this mixed population. While F1 animals - and especially F1 males - still have the highest number of dental anomalies, these and other atypical traits persist into later hybrid generations (such as F2 and B1). Moreover, non-F1 recombinants also show extremely rare trait variations, including reduced canines and rotated teeth. However, these results must be considered in light of the possibility that some founding individuals may have themselves been unrecognized hybrids. Despite this, the data are compelling, and indicate once again that further controlled research remains to be done on primates and other mammals in order to better understand variation in the hybrid phenotype.
Keywords: Animals; Female; Hybridization, Genetic; Male; Papio anubis; Papio cynocephalus; Phenotype

Genome typing of nonhuman primate models: implications for biomedical research. - Haus, Tanja; Ferguson, Betsy; Jeffrey Rogers; Doxiadis, Gaby; Certa, Ulrich; Rose, Nicola J; Teepe, Robert; Weinbauer, Gerhard F; Roos, Christian (Trends Genet, 2014)
The success of personalized medicine rests on understanding the genetic variation between individuals. Thus, as medical practice evolves and variation among individuals becomes a fundamental aspect of clinical medicine, a thorough consideration of the genetic and genomic information concerning the animals used as models in biomedical research also becomes critical. In particular, nonhuman primates (NHPs) offer great promise as models for many aspects of human health and disease. These are outbred species exhibiting substantial levels of genetic variation; however, understanding of the contribution of this variation to phenotypes is lagging behind in NHP species. Thus, there is a pivotal need to address this gap and define strategies for characterizing both genomic content and variability within primate models of human disease. Here, we discuss the current state of genomics of NHP models and offer guidelines for future work to ensure continued improvement and utility of this line of biomedical research.
Keywords: Animals; Biomedical Research; Disease Models, Animal; Genetic Variation; Genome-Wide Association Study; Genomics; Humans; Precision Medicine; Primates; Sequence Analysis, DNA

Gibbon genome and the fast karyotype evolution of small apes. - Carbone, Lucia; R. Alan Harris; Gnerre, Sante; Veeramah, Krishna R; Lorente-Galdos, Belen; Huddleston, John; Meyer, Thomas J; Herrero, Javier; Roos, Christian; Aken, Bronwen; Anaclerio, Fabio; Archidiacono, Nicoletta; et al. (Nature, 2014)
Gibbons are small arboreal apes that display an accelerated rate of evolutionary chromosomal rearrangement and occupy a key node in the primate phylogeny between Old World monkeys and great apes. Here we present the assembly and analysis of a northern white-cheeked gibbon (Nomascus leucogenys) genome. We describe the propensity for a gibbon-specific retrotransposon (LAVA) to insert into chromosome segregation genes and alter transcription by providing a premature termination site, suggesting a possible molecular mechanism for the genome plasticity of the gibbon lineage. We further show that the gibbon genera (Nomascus, Hylobates, Hoolock and Symphalangus) experienced a near-instantaneous radiation ∼5 million years ago, coincident with major geographical changes in southeast Asia that caused cycles of habitat compression and expansion. Finally, we identify signatures of positive selection in genes important for forelimb development (TBX5) and connective tissues (COL1A1) that may have been involved in the adaptation of gibbons to their arboreal habitat.
Keywords: Animals; Evolution, Molecular; Genome; Hominidae; Humans; Hylobates; Karyotype; Molecular Sequence Data; Phylogeny; Retroelements; Selection, Genetic; Transcription Termination, Genetic

The Glanville fritillary genome retains an ancient karyotype and reveals selective chromosomal fusions in Lepidoptera. - Ahola, Virpi; Lehtonen, Rainer; Somervuo, Panu; Salmela, Leena; Koskinen, Patrik; Rastas, Pasi; Välimäki, Niko; Paulin, Lars; Kvist, Jouni; Wahlberg, Niklas; Tanskanen, Jaakko; Hornett, Emily A; et al. (Nat Commun, 2014)
Previous studies have reported that chromosome synteny in Lepidoptera has been well conserved, yet the number of haploid chromosomes varies widely from 5 to 223. Here we report the genome (393 Mb) of the Glanville fritillary butterfly (Melitaea cinxia; Nymphalidae), a widely recognized model species in metapopulation biology and eco-evolutionary research, which has the putative ancestral karyotype of n=31. Using a phylogenetic analyses of Nymphalidae and of other Lepidoptera, combined with orthologue-level comparisons of chromosomes, we conclude that the ancestral lepidopteran karyotype has been n=31 for at least 140 My. We show that fusion chromosomes have retained the ancestral chromosome segments and very few rearrangements have occurred across the fusion sites. The same, shortest ancestral chromosomes have independently participated in fusion events in species with smaller karyotypes. The short chromosomes have higher rearrangement rate than long ones. These characteristics highlight distinctive features of the evolutionary dynamics of butterflies and moths.
Keywords: Animals; Base Sequence; Butterflies; Chromosome Aberrations; Chromosome Mapping; Evolution, Molecular; Genome; Karyotype; Likelihood Functions; Models, Genetic; Molecular Sequence Data; Phylogeny; Sequence Analysis, DNA; Synteny

Human CLP1 mutations alter tRNA biogenesis, affecting both peripheral and central nervous system function. - Karaca, Ender; Weitzer, Stefan; Pehlivan, Davut; Shiraishi, Hiroshi; Gogakos, Tasos; Hanada, Toshikatsu; Jhangiani, Shalini N; Wiszniewski, Wojciech; Withers, Marjorie; Campbell, Ian M; Erdin, Serkan; Isikay, Sedat; et al. (Cell, 2014)
CLP1 is a RNA kinase involved in tRNA splicing. Recently, CLP1 kinase-dead mice were shown to display a neuromuscular disorder with loss of motor neurons and muscle paralysis. Human genome analyses now identified a CLP1 homozygous missense mutation (p.R140H) in five unrelated families, leading to a loss of CLP1 interaction with the tRNA splicing endonuclease (TSEN) complex, largely reduced pre-tRNA cleavage activity, and accumulation of linear tRNA introns. The affected individuals develop severe motor-sensory defects, cortical dysgenesis, and microcephaly. Mice carrying kinase-dead CLP1 also displayed microcephaly and reduced cortical brain volume due to the enhanced cell death of neuronal progenitors that is associated with reduced numbers of cortical neurons. Our data elucidate a neurological syndrome defined by CLP1 mutations that impair tRNA splicing. Reduction of a founder mutation to homozygosity illustrates the importance of rare variations in disease and supports the clan genomics hypothesis.
Keywords: Abnormalities, Multiple; Animals; Central Nervous System Diseases; Cerebrum; Child, Preschool; Endoribonucleases; Female; Fibroblasts; Humans; Infant; Male; Mice; Mice, Inbred CBA; Microcephaly; Mutation, Missense; Nuclear Proteins; Peripheral Nervous System Diseases; Phosphotransferases; RNA, Transfer; RNA-Binding Proteins; Transcription Factors

Intrapopulation genome size variation in D. melanogaster reflects life history variation and plasticity. - Ellis, Lisa L; Huang, Wen; Quinn, Andrew M; Ahuja, Astha; Alfrejd, Ben; Gomez, Francisco E; Hjelmen, Carl E; Moore, Kristi L; Mackay, Trudy F C; Johnston, J Spencer; Tarone, Aaron M (PLoS Genet, 2014)
We determined female genome sizes using flow cytometry for 211 Drosophila melanogaster sequenced inbred strains from the Drosophila Genetic Reference Panel, and found significant conspecific and intrapopulation variation in genome size. We also compared several life history traits for 25 lines with large and 25 lines with small genomes in three thermal environments, and found that genome size as well as genome size by temperature interactions significantly correlated with survival to pupation and adulthood, time to pupation, female pupal mass, and female eclosion rates. Genome size accounted for up to 23% of the variation in developmental phenotypes, but the contribution of genome size to variation in life history traits was plastic and varied according to the thermal environment. Expression data implicate differences in metabolism that correspond to genome size variation. These results indicate that significant genome size variation exists within D. melanogaster and this variation may impact the evolutionary ecology of the species. Genome size variation accounts for a significant portion of life history variation in an environmentally dependent manner, suggesting that potential fitness effects associated with genome size variation also depend on environmental conditions.
Keywords: Adaptation, Physiological; Animals; Biological Evolution; Drosophila melanogaster; Environment; Female; Genetic Variation; Genome Size; Genome, Insect; Insect Hormones

Large conserved domains of low DNA methylation maintained by Dnmt3a. - Jeong, Mira; Sun, Deqiang; Luo, Min; Huang, Yun; Challen, Grant A; Rodriguez, Benjamin; Zhang, Xiaotian; Chavez, Lukas; Wang, Hui; Hannah, Rebecca; Kim, Sang-Bae; Yang, Liubin; et al. (Nat Genet, 2014)
Gains and losses in DNA methylation are prominent features of mammalian cell types. To gain insight into the mechanisms that promote shifts in DNA methylation and contribute to changes in cell fate, including malignant transformation, we performed genome-wide mapping of 5-methylcytosine and 5-hydroxymethylcytosine in purified mouse hematopoietic stem cells. We discovered extended regions of low methylation (canyons) that span conserved domains frequently containing transcription factors and are distinct from CpG islands and shores. About half of the genes in these methylation canyons are coated with repressive histone marks, whereas the remainder are covered by activating histone marks and are highly expressed in hematopoietic stem cells (HSCs). Canyon borders are demarked by 5-hydroxymethylcytosine and become eroded in the absence of DNA methyltransferase 3a (Dnmt3a). Genes dysregulated in human leukemias are enriched for canyon-associated genes. The new epigenetic landscape we describe may provide a mechanism for the regulation of hematopoiesis and may contribute to leukemia development.
Keywords: 5-Methylcytosine; Animals; Base Sequence; Conserved Sequence; CpG Islands; Cytosine; Databases, Genetic; DNA (Cytosine-5-)-Methyltransferases; DNA Methylation; DNA Methyltransferase 3A; Epigenesis, Genetic; Gene Expression Regulation; Hematopoietic Stem Cells; Histones; Humans; Leukemia; Male; Mice; Mice, Inbred C57BL; Mice, Mutant Strains

Large-scale identification of chemically induced mutations in Drosophila melanogaster. - Haelterman, Nele A; Jiang, Lichun; Yumei Li; Bayat, Vafa; Sandoval, Hector; Ugur, Berrak; Tan, Kai Li; Zhang, Ke; Bei, Danqing; Xiong, Bo; Charng, Wu-Lin; Busby, Theodore; et al. (Genome Res, 2014)
Forward genetic screens using chemical mutagens have been successful in defining the function of thousands of genes in eukaryotic model organisms. The main drawback of this strategy is the time-consuming identification of the molecular lesions causative of the phenotypes of interest. With whole-genome sequencing (WGS), it is now possible to sequence hundreds of strains, but determining which mutations are causative among thousands of polymorphisms remains challenging. We have sequenced 394 mutant strains, generated in a chemical mutagenesis screen, for essential genes on the Drosophila X chromosome and describe strategies to reduce the number of candidate mutations from an average of -3500 to 35 single-nucleotide variants per chromosome. By combining WGS with a rough mapping method based on large duplications, we were able to map 274 (-70%) mutations. We show that these mutations are causative, using small 80-kb duplications that rescue lethality. Hence, our findings demonstrate that combining rough mapping with WGS dramatically expands the toolkit necessary for assigning function to genes.
Keywords: Animals; Chromosome Mapping; Drosophila melanogaster; Ethyl Methanesulfonate; Female; Genes, Essential; Genes, Insect; Male; Molecular Sequence Data; Mutagenesis; Mutagens; Polymorphism, Single Nucleotide; Sequence Analysis, DNA; X Chromosome

Mammalian Y chromosomes retain widely expressed dosage-sensitive regulators. - Bellott, Daniel W; Hughes, Jennifer F; Skaletsky, Helen; Brown, Laura G; Pyntikova, Tatyana; Cho, Ting-Jan; Koutseva, Natalia; Zaghlul, Sara; Graves, Tina; Rock, Susie; Kremitzki, Colin; Fulton, Robert S; et al. (Nature, 2014)
The human X and Y chromosomes evolved from an ordinary pair of autosomes, but millions of years ago genetic decay ravaged the Y chromosome, and only three per cent of its ancestral genes survived. We reconstructed the evolution of the Y chromosome across eight mammals to identify biases in gene content and the selective pressures that preserved the surviving ancestral genes. Our findings indicate that survival was nonrandom, and in two cases, convergent across placental and marsupial mammals. We conclude that the gene content of the Y chromosome became specialized through selection to maintain the ancestral dosage of homologous X-Y gene pairs that function as broadly expressed regulators of transcription, translation and protein stability. We propose that beyond its roles in testis determination and spermatogenesis, the Y chromosome is essential for male viability, and has unappreciated roles in Turner's syndrome and in phenotypic differences between the sexes in health and disease.
Keywords: Animals; Chromosomes, Human, X; Chromosomes, Human, Y; Disease; Evolution, Molecular; Female; Gene Dosage; Gene Expression Regulation; Health; Humans; Male; Mammals; Marsupialia; Molecular Sequence Annotation; Molecular Sequence Data; Protein Biosynthesis; Protein Stability; Selection, Genetic; Sequence Homology; Sex Characteristics; Spermatogenesis; Testis; Transcription, Genetic; Turner Syndrome; X Chromosome; Y Chromosome

Monoallelic and biallelic mutations in MAB21L2 cause a spectrum of major eye malformations. - Rainger, Joe; Pehlivan, Davut; Johansson, Stefan; Bengani, Hemant; Sanchez-Pulido, Luis; Williamson, Kathleen A; Ture, Mehmet; Barker, Heather; Rosendahl, Karen; Spranger, Jürgen; Horn, Denise; Meynert, Alison; et al. (Am J Hum Genet, 2014)
We identified four different missense mutations in the single-exon gene MAB21L2 in eight individuals with bilateral eye malformations from five unrelated families via three independent exome sequencing projects. Three mutational events altered the same amino acid (Arg51), and two were identical de novo mutations (c.151C>T [p.Arg51Cys]) in unrelated children with bilateral anophthalmia, intellectual disability, and rhizomelic skeletal dysplasia. c.152G>A (p.Arg51His) segregated with autosomal-dominant bilateral colobomatous microphthalmia in a large multiplex family. The fourth heterozygous mutation (c.145G>A [p.Glu49Lys]) affected an amino acid within two residues of Arg51 in an adult male with bilateral colobomata. In a fifth family, a homozygous mutation (c.740G>A [p.Arg247Gln]) altering a different region of the protein was identified in two male siblings with bilateral retinal colobomata. In mouse embryos, Mab21l2 showed strong expression in the developing eye, pharyngeal arches, and limb bud. As predicted by structural homology, wild-type MAB21L2 bound single-stranded RNA, whereas this activity was lost in all altered forms of the protein. MAB21L2 had no detectable nucleotidyltransferase activity in vitro, and its function remains unknown. Induced expression of wild-type MAB21L2 in human embryonic kidney 293 cells increased phospho-ERK (pERK1/2) signaling. Compared to the wild-type and p.Arg247Gln proteins, the proteins with the Glu49 and Arg51 variants had increased stability. Abnormal persistence of pERK1/2 signaling in MAB21L2-expressing cells during development is a plausible pathogenic mechanism for the heterozygous mutations. The phenotype associated with the homozygous mutation might be a consequence of complete loss of MAB21L2 RNA binding, although the cellular function of this interaction remains unknown.
Keywords: Adult; Alleles; Animals; Anophthalmos; Brain Diseases, Metabolic, Inborn; Coloboma; Corneal Opacity; Exome; Eye Proteins; Female; Gene Expression; HEK293 Cells; Heterozygote; Homozygote; Humans; Intellectual Disability; Intracellular Signaling Peptides and Proteins; Male; Mice; Microcephaly; Microphthalmos; Mutation, Missense; Pedigree; Phenotype; Protein Conformation; Signal Transduction

Mutations in PURA cause profound neonatal hypotonia, seizures, and encephalopathy in 5q31.3 microdeletion syndrome. - Lalani, Seema R; Zhang, Jing; Schaaf, Christian P; Brown, Chester W; Magoulas, Pilar; Tsai, Anne Chun-Hui; El-Gharbawy, Areeg; Wierenga, Klaas J; Bartholomew, Dennis; Fong, Chin-To; Barbaro-Dieber, Tina; Kukolich, Mary K; et al. (Am J Hum Genet, 2014)
5q31.3 microdeletion syndrome is characterized by neonatal hypotonia, encephalopathy with or without epilepsy, and severe developmental delay, and the minimal critical deletion interval harbors three genes. We describe 11 individuals with clinical features of 5q31.3 microdeletion syndrome and de novo mutations in PURA, encoding transcriptional activator protein Pur-α, within the critical region. These data implicate causative PURA mutations responsible for the severe neurological phenotypes observed in this syndrome.
Keywords: Abnormalities, Multiple; Amino Acid Sequence; Animals; Base Sequence; Caenorhabditis elegans; Chromosome Deletion; Chromosome Mapping; Chromosomes, Human, Pair 5; DNA-Binding Proteins; Humans; Molecular Sequence Data; Muscle Hypotonia; Mutation; Seizures; Sequence Analysis, DNA; Syndrome; Transcription Factors

Natural variation in genome architecture among 205 Drosophila melanogaster Genetic Reference Panel lines. - Huang, Wen; Massouras, Andreas; Inoue, Yutaka; Peiffer, Jason; Ràmia, Miquel; Tarone, Aaron M; Turlapati, Lavanya; Zichner, Thomas; Zhu, Dianhui; Lyman, Richard F; Magwire, Michael M; Blankenburg, Kerstin; et al. (Genome Res, 2014)
The Drosophila melanogaster Genetic Reference Panel (DGRP) is a community resource of 205 sequenced inbred lines, derived to improve our understanding of the effects of naturally occurring genetic variation on molecular and organismal phenotypes. We used an integrated genotyping strategy to identify 4,853,802 single nucleotide polymorphisms (SNPs) and 1,296,080 non-SNP variants. Our molecular population genomic analyses show higher deletion than insertion mutation rates and stronger purifying selection on deletions. Weaker selection on insertions than deletions is consistent with our observed distribution of genome size determined by flow cytometry, which is skewed toward larger genomes. Insertion/deletion and single nucleotide polymorphisms are positively correlated with each other and with local recombination, suggesting that their nonrandom distributions are due to hitchhiking and background selection. Our cytogenetic analysis identified 16 polymorphic inversions in the DGRP. Common inverted and standard karyotypes are genetically divergent and account for most of the variation in relatedness among the DGRP lines. Intriguingly, variation in genome size and many quantitative traits are significantly associated with inversions. Approximately 50% of the DGRP lines are infected with Wolbachia, and four lines have germline insertions of Wolbachia sequences, but effects of Wolbachia infection on quantitative traits are rarely significant. The DGRP complements ongoing efforts to functionally annotate the Drosophila genome. Indeed, 15% of all D. melanogaster genes segregate for potentially damaged proteins in the DGRP, and genome-wide analyses of quantitative traits identify novel candidate genes. The DGRP lines, sequence data, genotypes, quality scores, phenotypes, and analysis and visualization tools are publicly available.
Keywords: Animals; Chromatin; Drosophila melanogaster; Female; Genetic Linkage; Genetic Variation; Genome Size; Genome, Insect; Genome-Wide Association Study; Genotype; Genotyping Techniques; High-Throughput Nucleotide Sequencing; INDEL Mutation; Linkage Disequilibrium; Male; Molecular Sequence Annotation; Phenotype; Polymorphism, Single Nucleotide; Quantitative Trait, Heritable; Reproducibility of Results

Notch activation as a driver of osteogenic sarcoma. - Tao, Jianning; Jiang, Ming-Ming; Jiang, Lichun; Salvo, Jason S; Zeng, Huan-Chang; Dawson, Brian; Bertin, Terry K; Rao, Pulivarthi H; Rui Chen; Donehower, Lawrence A; Gannon, Francis; Lee, Brendan H (Cancer Cell, 2014)
Osteogenic sarcoma (OS) is a deadly skeletal malignancy whose cause is unknown. We report here a mouse model of OS based on conditional expression of the intracellular domain of Notch1 (NICD). Expression of the NICD in immature osteoblasts was sufficient to drive the formation of bone tumors, including OS, with complete penetrance. These tumors display features of human OS; namely, histopathology, cytogenetic complexity, and metastatic potential. We show that Notch activation combined with loss of p53 synergistically accelerates OS development in mice, although p53-driven OS is not Rbpj dependent, which demonstrates a dual dominance of the Notch oncogene and p53 mutation in the development of OS. Using this model, we also reveal the osteoblasts as the potential sources of OS.
Keywords: Animals; Bone Neoplasms; Carcinogenesis; Cell Line, Tumor; Humans; Mice; Mice, 129 Strain; Mice, Inbred C57BL; Mice, Nude; Mice, Transgenic; Neoplasm Transplantation; Osteoblasts; Osteosarcoma; Protein Structure, Tertiary; Receptor, Notch1; Transcriptome

Onset of atonal expression in Drosophila retinal progenitors involves redundant and synergistic contributions of Ey/Pax6 and So binding sites within two distant enhancers. - Zhou, Qingxiang; Zhang, Tianyi; Jemc, Jennifer C; Chen, Yiyun; Rui Chen; Rebay, Ilaria; Pignoni, Francesca (Dev Biol, 2014)
Proneural transcription factors drive the generation of specialized neurons during nervous system development, and their dynamic expression pattern is critical to their function. The activation of the proneural gene atonal (ato) in the Drosophila eye disc epithelium represents a critical step in the transition from retinal progenitor cell to developing photoreceptor neuron. We show here that the onset of ato transcription depends on two distant enhancers that function differently in subsets of retinal progenitor cells. A detailed analysis of the crosstalk between these enhancers identifies a critical role for three binding sites for the Retinal Determination factors Eyeless (Ey) and Sine oculis (So). We show how these sites interact to induce ato expression in distinct regions of the eye field and confirm them to be occupied by endogenous Ey and So proteins in vivo. Our study suggests that Ey and So operate differently through the same 3' cis-regulatory sites in distinct populations of retinal progenitors.
Keywords: Animals; Basic Helix-Loop-Helix Transcription Factors; Binding Sites; DNA-Binding Proteins; Drosophila; Drosophila Proteins; Enhancer Elements, Genetic; Eye Proteins; Gene Expression Regulation, Developmental; Green Fluorescent Proteins; Homeodomain Proteins; In Situ Hybridization; Nerve Tissue Proteins; Nervous System; Neurons; Paired Box Transcription Factors; PAX6 Transcription Factor; Repressor Proteins; Retina; Stem Cells; Transcription, Genetic

Passage number is a major contributor to genomic structural variations in mouse iPSCs. - Liu, Pengfei; Kaplan, Anna; Bo Yuan; Hanna, Jacob H; James R Lupski; Reiner, Orly (Stem Cells, 2014)
Emergence of genomic instability is a practical issue in preparing neural stem cells (NSCs) and induced pluripotent stem cells (iPSCs). However, it is still not fully understood what the origins and mechanisms for formation are for the genomic alternations observed. Here, we studied the extent of genomic variation on the scale of individual cells originating from the same animal. We used mouse NSCs grown from embryonic cells and iPSCs generated from embryonic brain cells, B cells or fibroblasts, and performed comparative analysis with cultures of fibroblasts from the same mouse. In the first passage of these cell lines, aneuploidies were only observed for chromosomes 6, 11, 12, 19, and Y, which is overall at a rate lower than previously reported; de novo copy number variations (CNVs) were observed in 4.3% of neural iPSCs, 29% of B cell iPSCs, 10% of fibroblast iPSCs, and 1.3% of neurospheres. In contrast, propagation of these first passage cells to a later passage induced additional aneuploidies and CNVs. Breakpoint sequencing analysis suggested that the majority of the detected CNVs arose by replicative mechanisms. Interestingly, we detected identical de novo CNVs in different single cell colonies that appeared to have arisen independently from each other, which suggests a novel CNV formation mechanism in these cells. Our findings provide insights into mechanisms of CNV formation during reprogramming and suggest that replicative mechanisms for CNV formation accompany mitotic divisions.
Keywords: Aneuploidy; Animals; Base Sequence; Cell Proliferation; Chromosome Breakage; Clone Cells; Comparative Genomic Hybridization; DNA Copy Number Variations; Genetic Loci; Genomic Instability; Genomic Structural Variation; Induced Pluripotent Stem Cells; Mice; Molecular Sequence Data; Neural Stem Cells; Spheroids, Cellular

Recurrent CNVs and SNVs at the NPHP1 locus contribute pathogenic alleles to Bardet-Biedl syndrome. - Lindstrand, Anna; Davis, Erica E; Carvalho, Claudia M B; Pehlivan, Davut; Willer, Jason R; Tsai, I-Chun; Ramanathan, Subhadra; Zuppan, Craig; Aniko Sabo; Donna M Muzny; Richard A Gibbs; Liu, Pengfei; et al. (Am J Hum Genet, 2014)
Homozygosity for a recurrent 290 kb deletion of NPHP1 is the most frequent cause of isolated nephronophthisis (NPHP) in humans. A deletion of the same genomic interval has also been detected in individuals with Joubert syndrome (JBTS), and in the mouse, Nphp1 interacts genetically with Ahi1, a known JBTS locus. Given these observations, we investigated the contribution of NPHP1 in Bardet-Biedl syndrome (BBS), a ciliopathy of intermediate severity. By using a combination of array-comparative genomic hybridization, TaqMan copy number assays, and sequencing, we studied 200 families affected by BBS. We report a homozygous NPHP1 deletion CNV in a family with classical BBS that is transmitted with autosomal-recessive inheritance. Further, we identified heterozygous NPHP1 deletions in two more unrelated persons with BBS who bear primary mutations at another BBS locus. In parallel, we identified five families harboring an SNV in NPHP1 resulting in a conserved missense change, c.14G>T (p.Arg5Leu), that is enriched in our Hispanic pedigrees; in each case, affected individuals carried additional bona fide pathogenic alleles in another BBS gene. In vivo functional modeling in zebrafish embryos demonstrated that c.14G>T is a loss-of-function variant, and suppression of nphp1 in concert with each of the primary BBS loci found in our NPHP1-positive pedigrees exacerbated the severity of the phenotype. These results suggest that NPHP1 mutations are probably rare primary causes of BBS that contribute to the mutational burden of the disorder.
Keywords: Adaptor Proteins, Signal Transducing; Alleles; Animals; Bardet-Biedl Syndrome; Cytoskeletal Proteins; DNA Copy Number Variations; Gastrulation; Genetic Loci; Heterozygote; Homozygote; Humans; Kidney; Membrane Proteins; Mice; Pedigree; Sequence Deletion; Zebrafish

Regulation of Drosophila eye development by the transcription factor Sine oculis. - Jusiak, Barbara; Karandikar, Umesh C; Kwak, Su-Jin; Wang, Feng; Wang, Hui; Rui Chen; Mardon, Graeme (PLoS One, 2014)
Homeodomain transcription factors of the Sine oculis (SIX) family direct multiple regulatory processes throughout the metazoans. Sine oculis (So) was first characterized in the fruit fly Drosophila melanogaster, where it is both necessary and sufficient for eye development, regulating cell survival, proliferation, and differentiation. Despite its key role in development, only a few direct targets of So have been described previously. In the current study, we aim to expand our knowledge of So-mediated transcriptional regulation in the developing Drosophila eye using ChIP-seq to map So binding regions throughout the genome. We find 7,566 So enriched regions (peaks), estimated to map to 5,952 genes. Using overlap between the So ChIP-seq peak set and genes that are differentially regulated in response to loss or gain of so, we identify putative direct targets of So. We find So binding enrichment in genes not previously known to be regulated by So, including genes that encode cell junction proteins and signaling pathway components. In addition, we analyze a subset of So-bound novel genes in the eye, and find eight genes that have previously uncharacterized eye phenotypes and may be novel direct targets of So. Our study presents a greatly expanded list of candidate So targets and serves as basis for future studies of So-mediated gene regulation in the eye.
Keywords: Animals; Drosophila melanogaster; Eye; Gene Expression Regulation, Developmental; Homeodomain Proteins; Optic Disk; Organogenesis; Transcription Factors

The sheep genome illuminates biology of the rumen and lipid metabolism. - Jiang, Yu; Xie, Min; Chen, Wenbin; Talbot, Richard; Maddox, Jillian F; Faraut, Thomas; Wu, Chunhua; Donna M Muzny; Li, Yuxiang; Zhang, Wenguang; Stanton, Jo-Ann; Brauning, Rudiger; et al. (Science, 2014)
Sheep (Ovis aries) are a major source of meat, milk, and fiber in the form of wool and represent a distinct class of animals that have a specialized digestive organ, the rumen, that carries out the initial digestion of plant material. We have developed and analyzed a high-quality reference sheep genome and transcriptomes from 40 different tissues. We identified highly expressed genes encoding keratin cross-linking proteins associated with rumen evolution. We also identified genes involved in lipid metabolism that had been amplified and/or had altered tissue expression patterns. This may be in response to changes in the barrier lipids of the skin, an interaction between lipid metabolism and wool synthesis, and an increased role of volatile fatty acids in ruminants compared with nonruminant animals.
Keywords: Amino Acid Sequence; Animals; Fatty Acids, Volatile; Gene Expression Regulation; Genome; Keratins, Hair-Specific; Lipid Metabolism; Molecular Sequence Data; Phylogeny; Rumen; Sheep, Domestic; Transcriptome; Wool

Two novel simian arteriviruses in captive and wild baboons (Papio spp.). - Bailey, Adam L; Lauck, Michael; Sibley, Samuel D; Pecotte, Jerilyn; Rice, Karen; Weny, Geoffrey; Tumukunde, Alex; Hyeroba, David; Greene, Justin; Correll, Michael; Gleicher, Michael; Friedrich, Thomas C; et al. (J Virol, 2014)
UNLABELLED: Since the 1960s, simian hemorrhagic fever virus (SHFV; Nidovirales, Arteriviridae) has caused highly fatal outbreaks of viral hemorrhagic fever in captive Asian macaque colonies. However, the source(s) of these outbreaks and the natural reservoir(s) of this virus remain obscure. Here we report the identification of two novel, highly divergent simian arteriviruses related to SHFV, Mikumi yellow baboon virus 1 (MYBV-1) and Southwest baboon virus 1 (SWBV-1), in wild and captive baboons, respectively, and demonstrate the recent transmission of SWBV-1 among captive baboons. These findings extend our knowledge of the genetic and geographic diversity of the simian arteriviruses, identify baboons as a natural host of these viruses, and provide further evidence that baboons may have played a role in previous outbreaks of simian hemorrhagic fever in macaques, as has long been suspected. This knowledge should aid in the prevention of disease outbreaks in captive macaques and supports the growing body of evidence that suggests that simian arterivirus infections are common in Old World monkeys of many different species throughout Africa. IMPORTANCE: Historically, the emergence of primate viruses both in humans and in other primate species has caused devastating outbreaks of disease. One strategy for preventing the emergence of novel primate pathogens is to identify microbes with the potential for cross-species transmission in their natural state within reservoir species from which they might emerge. Here, we detail the discovery and characterization of two related simian members of the Arteriviridae family that have a history of disease emergence and host switching. Our results expand the phylogenetic and geographic range of the simian arteriviruses and define baboons as a natural host for these viruses. Our findings also identify a potential threat to captive macaque colonies by showing that simian arteriviruses are actively circulating in captive baboons.
Keywords: Animals; Animals, Wild; Animals, Zoo; Arteriviridae; Female; Genetic Variation; Male; Molecular Sequence Data; Monkey Diseases; Papio; Phylogeography; RNA Virus Infections; RNA, Viral; Sequence Analysis, DNA; Topography, Medical

Why primate models matter. - Phillips, Kimberley A; Bales, Karen L; Capitanio, John P; Conley, Alan; Czoty, Paul W; 't Hart, Bert A; Hopkins, William D; Hu, Shiu-Lok; Miller, Lisa A; Nader, Michael A; Nathanielsz, Peter W; Jeffrey Rogers; et al. (Am J Primatol, 2014)
Research involving nonhuman primates (NHPs) has played a vital role in many of the medical and scientific advances of the past century. NHPs are used because of their similarity to humans in physiology, neuroanatomy, reproduction, development, cognition, and social complexity-yet it is these very similarities that make the use of NHPs in biomedical research a considered decision. As primate researchers, we feel an obligation and responsibility to present the facts concerning why primates are used in various areas of biomedical research. Recent decisions in the United States, including the phasing out of chimpanzees in research by the National Institutes of Health and the pending closure of the New England Primate Research Center, illustrate to us the critical importance of conveying why continued research with primates is needed. Here, we review key areas in biomedicine where primate models have been, and continue to be, essential for advancing fundamental knowledge in biomedical and biological research.
Keywords: Animal Experimentation; Animals; Disease Models, Animal; Humans; Primates; United States

ARMC4 mutations cause primary ciliary dyskinesia with randomization of left/right body asymmetry. - Hjeij, Rim; Lindstrand, Anna; Francis, Richard; Zariwala, Maimoona A; Liu, Xiaoqin; Li, You; Damerla, Rama; Dougherty, Gerard W; Abouhamed, Marouan; Olbrich, Heike; Loges, Niki T; Pennekamp, Petra; et al. (Am J Hum Genet, 2013)
The motive forces for ciliary movement are generated by large multiprotein complexes referred to as outer dynein arms (ODAs), which are preassembled in the cytoplasm prior to transport to the ciliary axonemal compartment. In humans, defects in structural components, docking complexes, or cytoplasmic assembly factors can cause primary ciliary dyskinesia (PCD), a disorder characterized by chronic airway disease and defects in laterality. By using combined high resolution copy-number variant and mutation analysis, we identified ARMC4 mutations in twelve PCD individuals whose cells showed reduced numbers of ODAs and severely impaired ciliary beating. Transient suppression in zebrafish and analysis of an ENU mouse mutant confirmed in both model organisms that ARMC4 is critical for left-right patterning. We demonstrate that ARMC4 is an axonemal protein that is necessary for proper targeting and anchoring of ODAs.
Keywords: Amino Acid Sequence; Animals; Armadillo Domain Proteins; Axoneme; Body Patterning; Cilia; DNA Copy Number Variations; DNA Mutational Analysis; Dyneins; Gene Expression Regulation; Humans; Kartagener Syndrome; Mice; Microtubule-Associated Proteins; Molecular Sequence Data; Mutation; Respiratory System; Zebrafish

Bioactivity and bioavailability of ginsenosides are dependent on the glycosidase activities of the A/J mouse intestinal microbiome defined by pyrosequencing. - Niu, Tao; Smith, Diane L; Yang, Zhen; Gao, Song; Yin, Taijun; Jiang, Zhi-Hong; You, Ming; Richard A Gibbs; Petrosino, Joseph F; Hu, Ming (Pharm Res, 2013)
PURPOSE: To investigate the ability of bacteria in the intestinal microbiome to convert naturally occurring primary ginsenosides in red ginseng extract to active secondary ginsenosides. METHODS: Anti-proliferative ginsenoside activity was tested using mouse lung cancer LM1 cells. Permeabilities were evaluated in Caco-2 cell monolayers. Systemic exposure of secondary ginsenosides was determined in A/J mice. 16S rRNA gene pyrosequencing was used to determine membership and abundance of bacteria in intestinal microbiome. RESULTS: Secondary ginsenoside C-K exhibited higher anti-proliferative activity and permeability than primary ginsenosides. Significant amounts of secondary ginsenosides (F2 and C-K) were found in blood of A/J mice following oral administration of primary ginsenoside Rb1. Because mammalian cells did not hydrolyze ginsenoside, we determined the ability of bacteria to hydrolyze ginsenosides and found that Rb1 underwent stepwise hydrolysis to Rd, F2, and then C-K. Formation of F2 from Rd was the rate-limiting step in the biotransformation of Rb1 to C-K. CONCLUSION: Conversion to F2 is the rate-limiting step in bioactivation of primary ginsenosides by A/J mouse intestinal microbiome, whose characterization reveals the presence of certain bacterial families capable of enabling the formation of F2 and C-K in vivo.
Keywords: Animals; Antineoplastic Agents, Phytogenic; Bacteria; Biological Availability; Biotransformation; Caco-2 Cells; Cell Line, Tumor; Cell Proliferation; Drugs, Chinese Herbal; Ginsenosides; Glycoside Hydrolases; Humans; Hydrolysis; Intestinal Mucosa; Intestines; Male; Metagenome; Mice; Neoplasms; Panax; RNA, Bacterial

Characterization of transcriptomes from sexual and asexual lineages of a New Zealand snail (Potamopyrgus antipodarum). - Wilton, Peter R; Sloan, Daniel B; Logsdon, John M; Harshavardhan Doddapaneni; Neiman, Maurine (Mol Ecol Resour, 2013)
Understanding the evolution and maintenance of sexual reproduction is one of the central challenges of evolutionary biology, yet we know very little about how sex influences molecular evolution. The New Zealand freshwater snail Potamopyrgus antipodarum is ideally suited to address this knowledge gap because obligately sexual individuals often coexist with multiple independently derived obligately asexual lineages. This unusual situation allows direct comparisons both between sexual and asexual P. antipodarum and across populations that differ in the relative frequency of sexual individuals. As such, P. antipodarum has received a great deal of attention as a model system for the maintenance of sex in nature and is also used as a model for environmental toxicology and biological invasions. Molecular genetic resources for P. antipodarum will thus be useful to investigators in a variety of biological fields. We used 454 sequencing of cDNA libraries to generate transcriptomes from two sexual and two asexual P. antipodarum lineages. A de novo assembly of 116.7 Mb of sequence reads produced 41 396 contigs, and sequence similarity-based Gene Ontology annotations were obtained for 3740 contigs. We detected 408 315 SNP loci and 7315 microsatellite loci, which together represent the first genome-scale resource available for P. antipodarum. Raw 454 read sequences, contig sequences, annotation data and polymorphism data are publicly available in a searchable online database and for download at http://www.biology.uiowa.edu/neiman/transcriptome.php.
Keywords: Animals; Expressed Sequence Tags; Microsatellite Repeats; Phylogeny; Reproduction; Reproduction, Asexual; Sequence Analysis, DNA; Snails; Transcriptome

Combined sequence-based and genetic mapping analysis of complex traits in outbred rats. - Baud, Amelie; Hermsen, Roel; Guryev, Victor; Stridh, Pernilla; Graham, Delyth; McBride, Martin W; Foroud, Tatiana; Calderari, Sophie; Diez, Margarita; Ockinger, Johan; Beyeen, Amennai D; Gillett, Alan; et al. (Nat Genet, 2013)
Genetic mapping on fully sequenced individuals is transforming understanding of the relationship between molecular variation and variation in complex traits. Here we report a combined sequence and genetic mapping analysis in outbred rats that maps 355 quantitative trait loci for 122 phenotypes. We identify 35 causal genes involved in 31 phenotypes, implicating new genes in models of anxiety, heart disease and multiple sclerosis. The relationship between sequence and genetic variation is unexpectedly complex: at approximately 40% of quantitative trait loci, a single sequence variant cannot account for the phenotypic effect. Using comparable sequence and mapping data from mice, we show that the extent and spatial pattern of variation in inbred rats differ substantially from those of inbred mice and that the genetic variants in orthologous genes rarely contribute to the same phenotype in both species.
Keywords: Animals; Animals, Outbred Strains; Anxiety; Chromosome Mapping; Genetic Variation; Genotype; Heart Diseases; Humans; Mice; Mice, Inbred C57BL; Models, Molecular; Multiple Sclerosis; Phenotype; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Rats; Sequence Analysis, DNA

CRHR1 genotypes, neural circuits and the diathesis for anxiety and depression. - Rogers, J; Raveendran, M; Fawcett, G L; Fox, A S; Shelton, S E; Oler, J A; Cheverud, J; Donna M Muzny; Richard A Gibbs; Davidson, R J; Kalin, N H (Mol Psychiatry, 2013)
The corticotrophin-releasing hormone (CRH) system integrates the stress response and is associated with stress-related psychopathology. Previous reports have identified interactions between childhood trauma and sequence variation in the CRH receptor 1 gene (CRHR1) that increase risk for affective disorders. However, the underlying mechanisms that connect variation in CRHR1 to psychopathology are unknown. To explore potential mechanisms, we used a validated rhesus macaque model to investigate association between genetic variation in CRHR1, anxious temperament (AT) and brain metabolic activity. In young rhesus monkeys, AT is analogous to the childhood risk phenotype that predicts the development of human anxiety and depressive disorders. Regional brain metabolism was assessed with (18)F-labeled fluoro-2-deoxyglucose (FDG) positron emission tomography in 236 young, normally reared macaques that were also characterized for AT. We show that single nucleotide polymorphisms (SNPs) affecting exon 6 of CRHR1 influence both AT and metabolic activity in the anterior hippocampus and amygdala, components of the neural circuit underlying AT. We also find evidence for association between SNPs in CRHR1 and metabolism in the intraparietal sulcus and precuneus. These translational data suggest that genetic variation in CRHR1 affects the risk for affective disorders by influencing the function of the neural circuit underlying AT and that differences in gene expression or the protein sequence involving exon 6 may be important. These results suggest that variation in CRHR1 may influence brain function before any childhood adversity and may be a diathesis for the interaction between CRHR1 genotypes and childhood trauma reported to affect human psychopathology.
Keywords: Animals; Anxiety; Brain; Depression; Disease Models, Animal; Female; Fluorodeoxyglucose F18; Genetic Association Studies; Genetic Predisposition to Disease; Genotype; Macaca mulatta; Male; Polymorphism, Single Nucleotide; Positron-Emission Tomography; Receptors, Corticotropin-Releasing Hormone

DANPOS: dynamic analysis of nucleosome position and occupancy by sequencing. - Chen, Kaifu; Xi, Yuanxin; Pan, Xuewen; Li, Zhaoyu; Kaestner, Klaus; Tyler, Jessica; Dent, Sharon; He, Xiangwei; Li, Wei (Genome Res, 2013)
Recent developments in next-generation sequencing have enabled whole-genome profiling of nucleosome organizations. Although several algorithms for inferring nucleosome position from a single experimental condition have been available, it remains a challenge to accurately define dynamic nucleosomes associated with environmental changes. Here, we report a comprehensive bioinformatics pipeline, DANPOS, explicitly designed for dynamic nucleosome analysis at single-nucleotide resolution. Using both simulated and real nucleosome data, we demonstrated that bias correction in preliminary data processing and optimal statistical testing significantly enhances the functional interpretation of dynamic nucleosomes. The single-nucleotide resolution analysis of DANPOS allows us to detect all three categories of nucleosome dynamics, such as position shift, fuzziness change, and occupancy change, using a uniform statistical framework. Pathway analysis indicates that each category is involved in distinct biological functions. We also analyzed the influence of sequencing depth and suggest that even 200-fold coverage is probably not enough to identify all the dynamic nucleosomes. Finally, based on nucleosome data from the human hematopoietic stem cells (HSCs) and mouse embryonic stem cells (ESCs), we demonstrated that DANPOS is also robust in defining functional dynamic nucleosomes, not only in promoters, but also in distal regulatory regions in the mammalian genome.
Keywords: Algorithms; Animals; Computational Biology; Computer Simulation; Databases, Genetic; DNA; High-Throughput Nucleotide Sequencing; Humans; Mice; Nucleosomes; Promoter Regions, Genetic; Protein Binding; ROC Curve

Dawn of ocular gene therapy: implications for molecular diagnosis in retinal disease. - Zaneveld, Jacques; Wang, Feng; Wang, Xia; Rui Chen (Sci China Life Sci, 2013)
Personalized medicine aims to utilize genomic information about patients to tailor treatment. Gene replacement therapy for rare genetic disorders is perhaps the most extreme form of personalized medicine, in that the patients' genome wholly determines their treatment regimen. Gene therapy for retinal disorders is poised to become a clinical reality. The eye is an optimal site for gene therapy due to the relative ease of precise vector delivery, immune system isolation, and availability for monitoring of any potential damage or side effects. Due to these advantages, clinical trials for gene therapy of retinal diseases are currently underway. A necessary precursor to such gene therapies is accurate molecular diagnosis of the mutation(s) underlying disease. In this review, we discuss the application of Next Generation Sequencing (NGS) to obtain such a diagnosis and identify disease causing genes, using retinal disorders as a case study. After reviewing ocular gene therapy, we discuss the application of NGS to the identification of novel Mendelian disease genes. We then compare current, array based mutation detection methods against next NGS-based methods in three retinal diseases: Leber's Congenital Amaurosis, Retinitis Pigmentosa, and Stargardt's disease. We conclude that next-generation sequencing based diagnosis offers several advantages over array based methods, including a higher rate of successful diagnosis and the ability to more deeply and efficiently assay a broad spectrum of mutations. However, the relative difficulty of interpreting sequence results and the development of standardized, reliable bioinformatic tools remain outstanding concerns. In this review, recent advances NGS based molecular diagnoses are discussed, as well as their implications for the development of personalized medicine.
Keywords: Animals; DNA Mutational Analysis; Genetic Therapy; Genetic Vectors; High-Throughput Nucleotide Sequencing; Humans; Leber Congenital Amaurosis; Macular Degeneration; Molecular Diagnostic Techniques; Precision Medicine; Retinal Diseases; Retinitis Pigmentosa

From human genome to cancer genome: the first decade. - Wheeler, David A; Wang, Linghua (Genome Res, 2013)
The realization that cancer progression required the participation of cellular genes provided one of several key rationales, in 1986, for embarking on the human genome project. Only with a reference genome sequence could the full spectrum of somatic changes leading to cancer be understood. Since its completion in 2003, the human reference genome sequence has fulfilled its promise as a foundational tool to illuminate the pathogenesis of cancer. Herein, we review the key historical milestones in cancer genomics since the completion of the genome, and some of the novel discoveries that are shaping our current understanding of cancer.
Keywords: Animals; Cell Transformation, Neoplastic; Genes, Neoplasm; Genetic Heterogeneity; Genome, Human; Genomics; Humans; Mutation Rate; Neoplasms

The i5K Initiative: advancing arthropod genomics for knowledge, human health, agriculture, and the environment. (J Hered, 2013)
Insects and their arthropod relatives including mites, spiders, and crustaceans play major roles in the world's terrestrial, aquatic, and marine ecosystems. Arthropods compete with humans for food and transmit devastating diseases. They also comprise the most diverse and successful branch of metazoan evolution, with millions of extant species. Here, we describe an international effort to guide arthropod genomic efforts, from species prioritization to methodology and informatics. The 5000 arthropod genomes initiative (i5K) community met formally in 2012 to discuss a roadmap for sequencing and analyzing 5000 high-priority arthropods and is continuing this effort via pilot projects, the development of standard operating procedures, and training of students and career scientists. With university, governmental, and industry support, the i5K Consortium aspires to deliver sequences and analytical tools for each of the arthropod branches and each of the species having beneficial and negative effects on humankind.
Keywords: Animals; Arthropods; Chromosome Mapping; Genomics

In transition: primate genomics at a time of rapid change. - Jeffrey Rogers (ILAR J, 2013)
The field of nonhuman primate genomics is undergoing rapid change and making impressive progress. Exploiting new technologies for DNA sequencing, researchers have generated new whole-genome sequence assemblies for multiple primate species over the past 6 years. In addition, investigations of within-species genetic variation, gene expression and RNA sequences, conservation of non-protein-coding regions of the genome, and other aspects of comparative genomics are moving at an accelerating speed. This progress is opening a wide array of new research opportunities in the analysis of comparative primate genome content and evolution. It also creates new possibilities for the use of nonhuman primates as model organisms in biomedical research. This transition, based on both new technology and the new information being generated in regard to human genetics, provides an important justification for reevaluating the research goals, strategies, and study designs used in primate genetics and genomics.
Keywords: Animals; Genetic Variation; Genomics; Primates; Sequence Analysis, DNA

Metagenomic analyses of alcohol induced pathogenic alterations in the intestinal microbiome and the effect of Lactobacillus rhamnosus GG treatment. - Bull-Otterson, Lara; Feng, Wenke; Kirpich, Irina; Wang, Yuhua; Xiang Qin; Liu, Yanlong; Gobejishvili, Leila; Joshi-Barve, Swati; Ayvaz, Tulin; Petrosino, Joseph; Kong, Maiying; Barker, David; et al. (PLoS One, 2013)
Enteric dysbiosis plays an essential role in the pathogenesis of alcoholic liver disease (ALD). Detailed characterization of the alterations in the gut microbiome is needed for understanding their pathogenic role in ALD and developing effective therapeutic approaches using probiotic supplementation. Mice were fed liquid Lieber-DeCarli diet without or with alcohol (5% v/v) for 6 weeks. A subset of mice were administered the probiotic Lactobacillus rhamnosus GG (LGG) from 6 to 8 weeks. Indicators of intestinal permeability, hepatic steatosis, inflammation and injury were evaluated. Metagenomic analysis of the gut microbiome was performed by analyzing the fecal DNA by amplification of the V3-V5 regions of the 16S rRNA gene and large-scale parallel pyrosequencing on the 454 FLX Titanium platform. Chronic ethanol feeding caused a decline in the abundance of both Bacteriodetes and Firmicutes phyla, with a proportional increase in the gram negative Proteobacteria and gram positive Actinobacteria phyla; the bacterial genera that showed the biggest expansion were the gram negative alkaline tolerant Alcaligenes and gram positive Corynebacterium. Commensurate with the qualitative and quantitative alterations in the microbiome, ethanol caused an increase in plasma endotoxin, fecal pH, hepatic inflammation and injury. Notably, the ethanol-induced pathogenic changes in the microbiome and the liver were prevented by LGG supplementation. Overall, significant alterations in the gut microbiome over time occur in response to chronic alcohol exposure and correspond to increases in intestinal barrier dysfunction and development of ALD. Moreover, the altered bacterial communities of the gut may serve as significant therapeutic target for the prevention/treatment of chronic alcohol intake induced intestinal barrier dysfunction and liver disease.
Keywords: Animals; Anti-Infective Agents, Local; Bacteria; Biodiversity; Claudin-1; Ethanol; Feces; Gene Expression; Genetic Variation; Hydrogen-Ion Concentration; Intestinal Mucosa; Intestines; Lacticaseibacillus rhamnosus; Liver Diseases, Alcoholic; Male; Metagenome; Metagenomics; Mice; Mice, Inbred C57BL; Probiotics; Reverse Transcriptase Polymerase Chain Reaction; RNA, Ribosomal, 16S; Sequence Analysis, DNA; Species Specificity; Zonula Occludens-1 Protein

OikoBase: a genomics and developmental transcriptomics resource for the urochordate Oikopleura dioica. - Danks, Gemma; Campsteijn, Coen; Parida, Mrutyunjaya; Butcher, Stephen; Harshavardhan Doddapaneni; Fu, Bolei; Petrin, Raul; Metpally, Raghu; Lenhard, Boris; Wincker, Patrick; Chourrout, Daniel; Thompson, Eric M; et al. (Nucleic Acids Res, 2013)
We report the development of OikoBase (http://oikoarrays.biology.uiowa.edu/Oiko/), a tiling array-based genome browser resource for Oikopleura dioica, a metazoan belonging to the urochordates, the closest extant group to vertebrates. OikoBase facilitates retrieval and mining of a variety of useful genomics information. First, it includes a genome browser which interrogates 1260 genomic sequence scaffolds and features gene, transcript and CDS annotation tracks. Second, we annotated gene models with gene ontology (GO) terms and InterPro domains which are directly accessible in the browser with links to their entries in the GO (http://www.geneontology.org/) and InterPro (http://www.ebi.ac.uk/interpro/) databases, and we provide transcript and peptide links for sequence downloads. Third, we introduce the transcriptomics of a comprehensive set of developmental stages of O. dioica at high resolution and provide downloadable gene expression data for all developmental stages. Fourth, we incorporate a BLAST tool to identify homologs of genes and proteins. Finally, we include a tutorial that describes how to use OikoBase as well as a link to detailed methods, explaining the data generation and analysis pipeline. OikoBase will provide a valuable resource for research in chordate development, genome evolution and plasticity and the molecular ecology of this important marine planktonic organism.
Keywords: Animals; Data Mining; Databases, Genetic; Gene Expression Profiling; Genomics; Internet; Molecular Sequence Annotation; Oligonucleotide Array Sequence Analysis; Transcriptome; Urochordata

RNA interference knockdown of DNA methyl-transferase 3 affects gene alternative splicing in the honey bee. - Li-Byarlay, Hongmei; Li, Yang; Stroud, Hume; Feng, Suhua; Newman, Thomas C; Kaneda, Megan; Hou, Kirk K; Worley, Kim C; Elsik, Christine G; Wickline, Samuel A; Jacobsen, Steven E; Ma, Jian; et al. (Proc Natl Acad Sci U S A, 2013)
Studies of DNA methylation from fungi, plants, and animals indicate that gene body methylation is ancient and highly conserved in eukaryotic genomes, but its role has not been clearly defined. It has been postulated that regulation of alternative splicing of transcripts was an original function of DNA methylation, but a direct experimental test of the effect of methylation on alternative slicing at the whole genome level has never been performed. To do this, we developed a unique method to administer RNA interference (RNAi) in a high-throughput and noninvasive manner and then used it to knock down the expression of DNA methyl-transferase 3 (dnmt3), which is required for de novo DNA methylation. We chose the honey bee (Apis mellifera) for this test because it has recently emerged as an important model organism for studying the effects of DNA methylation on development and social behavior, and DNA methylation in honey bees is predominantly on gene bodies. Here we show that dnmt3 RNAi decreased global genomic methylation level as expected and in addition caused widespread and diverse changes in alternative splicing in fat tissue. Four different types of splicing events were affected by dnmt3 gene knockdown, and change in two types, exon skipping and intron retention, was directly related to decreased methylation. These results demonstrate that one function of gene body DNA methylation is to regulate alternative splicing.
Keywords: Alternative Splicing; Animals; Bees; Behavior, Animal; DNA (Cytosine-5-)-Methyltransferases; DNA Methylation; Gene Knockdown Techniques; Insect Proteins; RNA Interference; Social Behavior

Seafood consumption and blood mercury concentrations in Jamaican children with and without autism spectrum disorders. - Rahbar, Mohammad H; Samms-Vaughan, Maureen; Loveland, Katherine A; Ardjomand-Hessabi, Manouchehr; Chen, Zhongxue; Bressler, Jan; Shakespeare-Pellington, Sydonnie; Grove, Megan L; Bloom, Kari; Pearson, Deborah A; Lalor, Gerald C; Eric Boerwinkle (Neurotox Res, 2013)
Mercury is a toxic metal shown to have harmful effects on human health. Several studies have reported high blood mercury concentrations as a risk factor for autism spectrum disorders (ASDs), while other studies have reported no such association. The goal of this study was to investigate the association between blood mercury concentrations in children and ASDs. Moreover, we investigated the role of seafood consumption in relation to blood mercury concentrations in Jamaican children. Based on data for 65 sex- and age-matched pairs (2-8 years), we used a General Linear Model to test whether there is an association between blood mercury concentrations and ASDs. After controlling for the child's frequency of seafood consumption, maternal age, and parental education, we did not find a significant difference (P = 0.61) between blood mercury concentrations and ASDs. However, in both cases and control groups, children who ate certain types of seafood (i.e., salt water fish, sardine, or mackerel fish) had significantly higher (all P < 0.05) geometric means blood mercury concentration which were about 3.5 times that of children living in the US or Canada. Our findings also indicate that Jamaican children with parents who both had education up to high school are at a higher risk of exposure to mercury compared to children with at least one parent who had education beyond high school. Based on our findings, we recommend additional education to Jamaican parents regarding potential hazards of elevated blood mercury concentrations, and its association with seafood consumption and type of seafood.
Keywords: Adult; Age Factors; Animals; Biomarkers; Case-Control Studies; Child; Child Development Disorders, Pervasive; Child, Preschool; Female; Humans; Jamaica; Male; Mercury; Seafood; Socioeconomic Factors; Surveys and Questionnaires

Adenosine deaminases that act on RNA induce reproducible changes in abundance and sequence of embryonic miRNAs. - Vesely, Cornelia; Tauber, Stefanie; Fritz J Sedlazeck; von Haeseler, Arndt; Jantsch, Michael F (Genome Res, 2012)
Adenosine deaminases that act on RNA bind double-stranded and structured RNAs and convert adenosines to inosines by hydrolytic deamination. Inosines are recognized as guanosines, and, hence, RNA editing alters the sequence information but also structure of RNAs. Editing by ADARs is widespread and essential for normal life and development. Precursors of miRNAs are abundantly edited by ADARs, but neither the abundance nor the consequences of miRNA editing has been firmly established. Using transgenic mouse embryos that are deficient in the two enzymatically active editing enzymes ADAR and ADARB1, we compare relative frequencies but also sequence composition of miRNAs in these genetically modified backgrounds to wild-type mice by "next-generation sequencing." Deficiency of ADARB1 leads to a reproducible change in abundance of specific miRNAs and their predicted targets. Changes in miRNA abundance seem unrelated to editing events. Additional deletion of ADAR has surprisingly little impact on the mature miRNA repertoire, indicating that miRNA expression is primarily dependent on ADARB1. A-to-G transitions reflecting A-to-I editing events can be detected at few sites and at low frequency during the early embryonic stage investigated. Again, most editing events are ADARB1-dependent with only few editing sites being specifically edited by ADAR. Besides known editing events in miRNAs, a few novel, previously unknown editing events were identified. Some editing events are located to the seed region of miRNAs, opening the possibility that editing leads to their retargeting.
Keywords: Adenosine Deaminase; Animals; Base Sequence; Binding Sites; Embryo, Mammalian; Embryonic Development; Female; Gene Expression Regulation, Developmental; Gene Expression Regulation, Enzymologic; Mice; Mice, Knockout; MicroRNAs; RNA Editing; RNA, Messenger; RNA-Binding Proteins; Sequence Deletion

Analysis of microsatellite variation in Drosophila melanogaster with population-scale genome sequencing. - Fondon, John W; Martin, Andy; Stephen Richards; Richard A Gibbs; Mittelman, David (PLoS One, 2012)
Genome sequencing technologies promise to revolutionize our understanding of genetics, evolution, and disease by making it feasible to survey a broad spectrum of sequence variation on a population scale. However, this potential can only be realized to the extent that methods for extracting and interpreting distinct forms of variation can be established. The error profiles and read length limitations of early versions of next-generation sequencing technologies rendered them ineffective for some sequence variant types, particularly microsatellites and other tandem repeats, and fostered the general misconception that such variants are inherently inaccessible to these platforms. At the same time, tandem repeats have emerged as important sources of functional variation. Tandem repeats are often located in and around genes, and frequent mutations in their lengths exert quantitative effects on gene function and phenotype, rapidly degrading linkage disequilibrium between markers and traits. Sensitive identification of these variants in large-scale next-gen sequencing efforts will enable more comprehensive association studies capable of revealing previously invisible associations. We present a population-scale analysis of microsatellite repeats using whole-genome data from 158 inbred isolates from the Drosophila Genetics Reference Panel, a collection of over 200 extensively phenotypically characterized isolates from a single natural population, to uncover processes underlying repeat mutation and to enable associations with behavioral, morphological, and life-history traits. Analysis of repeat variation from next-generation sequence data will also enhance studies of genome stability and neurodegenerative diseases.
Keywords: Animals; Drosophila melanogaster; Genetic Variation; Genetics, Population; Genome; Genotype; Microsatellite Repeats; Mutation

Androgen receptor CAG repeat polymorphism in males of six non-human primate species. - Mubiru, James N; Cavazos, Nicole; Hemmat, Peggah; Garcia-Forey, Magdalena; Shade, Robert E; Jeffrey Rogers (J Med Primatol, 2012)
BACKGROUND: Androgen receptor [CAG](n) microsatellite has been linked to human diseases. METHODS: Six non-human primates were genotyped for the [CAG](n) microsatellite. RESULTS: Marmosets and macaques are monomorphic, while mangabeys, baboons, and chimpanzees are polymorphic. CONCLUSIONS: Non-human primates that are polymorphic for the microsatellite are candidate animal models for CAG-related diseases.
Keywords: Animals; DNA; Male; Pan troglodytes; Polymerase Chain Reaction; Polymorphism, Genetic; Primates; Receptors, Androgen; Trinucleotide Repeats

Atypical angiopoietin-like protein that regulates ANGPTL3. - Quagliarini, Fabiana; Wang, Yan; Kozlitina, Julia; Grishin, Nick V; Hyde, Rhonda; Eric Boerwinkle; Valenzuela, David M; Murphy, Andrew J; Cohen, Jonathan C; Hobbs, Helen H (Proc Natl Acad Sci U S A, 2012)
Angiopoietin-like proteins (ANGPTLs) play major roles in the trafficking and metabolism of lipids. Inactivation of ANGPTL3, a gene located in an intron of DOCK7, results in very low levels of LDL-cholesterol (C), HDL-C and triglyceride (TAG). We identified another ANGPTL family member, ANGPTL8, which is located in the corresponding intron of DOCK6. A variant in this family member (rs2278426, R59W) was associated with lower plasma LDL-C and HDL-C levels in three populations. ANGPTL8 is expressed in liver and adipose tissue, and circulates in plasma of humans. Expression of ANGPTL8 was reduced by fasting and increased by refeeding in both mice and humans. To examine the functional relationship between the two ANGPTL family members, we expressed ANGPTL3 at physiological levels alone or together with ANGPTL8 in livers of mice. Plasma TAG level did not change in mice expressing ANGPTL3 alone, whereas coexpression with ANGPTL8 resulted in hypertriglyceridemia, despite a reduction in circulating ANGPTL3. ANGPTL8 coimmunoprecipitated with the N-terminal domain of ANGPTL3 in plasma of these mice. In cultured hepatocytes, ANGPTL8 expression increased the appearance of N-terminal ANGPTL3 in the medium, suggesting ANGPTL8 may activate ANGPTL3. Consistent with this scenario, expression of ANGPTL8 in Angptl3(-/-) mice failed to promote hypertriglyceridemia. Thus, ANGPTL8, a paralog of ANGPTL3 that arose through duplication of an ancestral DOCK gene, regulates postprandial TAG and fatty acid metabolism by controlling activation of its progenitor, and perhaps other ANGPTLs. Inhibition of ANGPTL8 provides a new therapeutic strategy for reducing plasma lipoprotein levels.
Keywords: Amino Acid Sequence; Angiopoietin-Like Protein 3; Angiopoietin-like Proteins; Angiopoietins; Animals; Cholesterol, HDL; Cholesterol, LDL; GTPase-Activating Proteins; Guanine Nucleotide Exchange Factors; Hypertriglyceridemia; Introns; Liver; Mice; Molecular Sequence Data; Sequence Homology, Amino Acid; Triglycerides

Biological characterization and next-generation genome sequencing of the unclassified Cotia virus SPAn232 (Poxviridae). - Afonso, Priscila P; Silva, Patrícia M; Schnellrath, Laila C; Jesus, Desyreé M; Jianhong Hu; Yang, Yajie; Renne, Rolf; Attias, Marcia; Condit, Richard C; Moussatché, Nissin; Damaso, Clarissa R (J Virol, 2012)
Cotia virus (COTV) SPAn232 was isolated in 1961 from sentinel mice at Cotia field station, São Paulo, Brazil. Attempts to classify COTV within a recognized genus of the Poxviridae have generated contradictory findings. Studies by different researchers suggested some similarity to myxoma virus and swinepox virus, whereas another investigation characterized COTV SPAn232 as a vaccinia virus strain. Because of the lack of consensus, we have conducted an independent biological and molecular characterization of COTV. Virus growth curves reached maximum yields at approximately 24 to 48 h and were accompanied by virus DNA replication and a characteristic early/late pattern of viral protein synthesis. Interestingly, COTV did not induce detectable cytopathic effects in BSC-40 cells until 4 days postinfection and generated viral plaques only after 8 days. We determined the complete genomic sequence of COTV by using a combination of the next-generation DNA sequencing technologies 454 and Illumina. A unique contiguous sequence of 185,139 bp containing 185 genes, including the 90 genes conserved in all chordopoxviruses, was obtained. COTV has an interesting panel of open reading frames (ORFs) related to the evasion of host defense, including two novel genes encoding C-C chemokine-like proteins, each present in duplicate copies. Phylogenetic analysis revealed the highest amino acid identity scores with Cervidpoxvirus, Capripoxvirus, Suipoxvirus, Leporipoxvirus, and Yatapoxvirus. However, COTV grouped as an independent branch within this clade, which clearly excluded its classification as an Orthopoxvirus. Therefore, our data suggest that COTV could represent a new poxvirus genus.
Keywords: Amino Acid Sequence; Animals; Chick Embryo; Chlorocebus aethiops; Cross Reactions; Cytopathogenic Effect, Viral; Genes, Viral; Genome, Viral; High-Throughput Nucleotide Sequencing; Humans; Macaca mulatta; Mice; Molecular Sequence Data; Neutralization Tests; Phylogeny; Poxviridae; Rabbits; Rats; Sequence Alignment; Swine; Viral Tropism; Virus Replication

Butterfly genome reveals promiscuous exchange of mimicry adaptations among species. (Nature, 2012)
The evolutionary importance of hybridization and introgression has long been debated. Hybrids are usually rare and unfit, but even infrequent hybridization can aid adaptation by transferring beneficial traits between species. Here we use genomic tools to investigate introgression in Heliconius, a rapidly radiating genus of neotropical butterflies widely used in studies of ecology, behaviour, mimicry and speciation. We sequenced the genome of Heliconius melpomene and compared it with other taxa to investigate chromosomal evolution in Lepidoptera and gene flow among multiple Heliconius species and races. Among 12,669 predicted genes, biologically important expansions of families of chemosensory and Hox genes are particularly noteworthy. Chromosomal organization has remained broadly conserved since the Cretaceous period, when butterflies split from the Bombyx (silkmoth) lineage. Using genomic resequencing, we show hybrid exchange of genes between three co-mimics, Heliconius melpomene, Heliconius timareta and Heliconius elevatus, especially at two genomic regions that control mimicry pattern. We infer that closely related Heliconius species exchange protective colour-pattern genes promiscuously, implying that hybridization has an important role in adaptive radiation.
Keywords: Adaptation, Physiological; Animals; Bombyx; Butterflies; Chromosomes, Insect; Evolution, Molecular; Gene Flow; Genes, Homeobox; Genes, Insect; Genome, Insect; Genomics; Hybridization, Genetic; Molecular Mimicry; Molecular Sequence Data; Phylogeny; Pigmentation; Sequence Analysis, DNA; Species Specificity; Synteny; Wings, Animal

The Drosophila melanogaster Genetic Reference Panel. - Mackay, Trudy F C; Stephen Richards; Stone, Eric A; Barbadilla, Antonio; Ayroles, Julien F; Zhu, Dianhui; Casillas, Sònia; Yi Han; Magwire, Michael M; Cridland, Julie M; Richardson, Mark F; Anholt, Robert R H; et al. (Nature, 2012)
A major challenge of biology is understanding the relationship between molecular genetic variation and variation in quantitative traits, including fitness. This relationship determines our ability to predict phenotypes from genotypes and to understand how evolutionary forces shape variation within and between species. Previous efforts to dissect the genotype-phenotype map were based on incomplete genotypic information. Here, we describe the Drosophila melanogaster Genetic Reference Panel (DGRP), a community resource for analysis of population genomics and quantitative traits. The DGRP consists of fully sequenced inbred lines derived from a natural population. Population genomic analyses reveal reduced polymorphism in centromeric autosomal regions and the X chromosome, evidence for positive and negative selection, and rapid evolution of the X chromosome. Many variants in novel genes, most at low frequency, are associated with quantitative traits and explain a large fraction of the phenotypic variance. The DGRP facilitates genotype-phenotype mapping using the power of Drosophila genetics.
Keywords: Alleles; Animals; Centromere; Chromosomes, Insect; Drosophila melanogaster; Genome-Wide Association Study; Genomics; Genotype; Phenotype; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Selection, Genetic; Starvation; Telomere; X Chromosome

Epistasis dominates the genetic architecture of Drosophila quantitative traits. - Huang, Wen; Stephen Richards; Carbone, Mary Anna; Zhu, Dianhui; Anholt, Robert R H; Ayroles, Julien F; Duncan, Laura; Jordan, Katherine W; Lawrence, Faye; Magwire, Michael M; Warner, Crystal B; Blankenburg, Kerstin; et al. (Proc Natl Acad Sci U S A, 2012)
Epistasis-nonlinear genetic interactions between polymorphic loci-is the genetic basis of canalization and speciation, and epistatic interactions can be used to infer genetic networks affecting quantitative traits. However, the role that epistasis plays in the genetic architecture of quantitative traits is controversial. Here, we compared the genetic architecture of three Drosophila life history traits in the sequenced inbred lines of the Drosophila melanogaster Genetic Reference Panel (DGRP) and a large outbred, advanced intercross population derived from 40 DGRP lines (Flyland). We assessed allele frequency changes between pools of individuals at the extremes of the distribution for each trait in the Flyland population by deep DNA sequencing. The genetic architecture of all traits was highly polygenic in both analyses. Surprisingly, none of the SNPs associated with the traits in Flyland replicated in the DGRP and vice versa. However, the majority of these SNPs participated in at least one epistatic interaction in the DGRP. Despite apparent additive effects at largely distinct loci in the two populations, the epistatic interactions perturbed common, biologically plausible, and highly connected genetic networks. Our analysis underscores the importance of epistasis as a principal factor that determines variation for quantitative traits and provides a means to uncover genetic networks affecting these traits. Knowledge of epistatic networks will contribute to our understanding of the genetic basis of evolutionarily and clinically important traits and enhance predictive ability at an individualized level in medicine and agriculture.
Keywords: Animals; Drosophila melanogaster; Epistasis, Genetic; Genes, Insect; Polymorphism, Single Nucleotide; Quantitative Trait, Heritable

Exome capture reveals ZNF423 and CEP164 mutations, linking renal ciliopathies to DNA damage response signaling. - Chaki, Moumita; Airik, Rannar; Ghosh, Amiya K; Giles, Rachel H; Rui Chen; Slaats, Gisela G; Wang, Hui; Hurd, Toby W; Zhou, Weibin; Cluckey, Andrew; Gee, Heon Yung; Ramaswami, Gokul; et al. (Cell, 2012)
Nephronophthisis-related ciliopathies (NPHP-RC) are degenerative recessive diseases that affect kidney, retina, and brain. Genetic defects in NPHP gene products that localize to cilia and centrosomes defined them as "ciliopathies." However, disease mechanisms remain poorly understood. Here, we identify by whole-exome resequencing, mutations of MRE11, ZNF423, and CEP164 as causing NPHP-RC. All three genes function within the DNA damage response (DDR) pathway. We demonstrate that, upon induced DNA damage, the NPHP-RC proteins ZNF423, CEP164, and NPHP10 colocalize to nuclear foci positive for TIP60, known to activate ATM at sites of DNA damage. We show that knockdown of CEP164 or ZNF423 causes sensitivity to DNA damaging agents and that cep164 knockdown in zebrafish results in dysregulated DDR and an NPHP-RC phenotype. Our findings link degenerative diseases of the kidney and retina, disorders of increasing prevalence, to mechanisms of DDR.
Keywords: Animals; Cilia; DNA Damage; DNA-Binding Proteins; Exome; Gene Knockdown Techniques; Genes, Recessive; Humans; Kidney Diseases, Cystic; Mice; Microtubule Proteins; MRE11 Homologue Protein; Proteins; Signal Transduction; Zebrafish

Gene structure in the sea urchin Strongylocentrotus purpuratus based on transcriptome analysis. - Tu, Qiang; Cameron, R Andrew; Worley, Kim C; Richard A Gibbs; Davidson, Eric H (Genome Res, 2012)
A comprehensive transcriptome analysis has been performed on protein-coding RNAs of Strongylocentrotus purpuratus, including 10 different embryonic stages, six feeding larval and metamorphosed juvenile stages, and six adult tissues. In this study, we pooled the transcriptomes from all of these sources and focused on the insights they provide for gene structure in the genome of this recently sequenced model system. The genome had initially been annotated by use of computational gene model prediction algorithms. A large fraction of these predicted genes were recovered in the transcriptome when the reads were mapped to the genome and appropriately filtered and analyzed. However, in a manually curated subset, we discovered that more than half the computational gene model predictions were imperfect, containing errors such as missing exons, prediction of nonexistent exons, erroneous intron/exon boundaries, fusion of adjacent genes, and prediction of multiple genes from single genes. The transcriptome data have been used to provide a systematic upgrade of the gene model predictions throughout the genome, very greatly improving the research usability of the genomic sequence. We have constructed new public databases that incorporate information from the transcriptome analyses. The transcript-based gene model data were used to define average structural parameters for S. purpuratus protein-coding genes. In addition, we constructed a custom sea urchin gene ontology, and assigned about 7000 different annotated transcripts to 24 functional classes. Strong correlations became evident between given functional ontology classes and structural properties, including gene size, exon number, and exon and intron size.
Keywords: Animals; Computational Biology; Databases, Nucleic Acid; Exons; Female; Gene Expression Profiling; Genome; Introns; Male; Models, Genetic; Molecular Sequence Annotation; Molecular Sequence Data; Open Reading Frames; RNA, Spliced Leader; Strongylocentrotus purpuratus; Trans-Splicing; Transcriptome

Gene therapy rescues cilia defects and restores olfactory function in a mammalian ciliopathy model. - McIntyre, Jeremy C; Davis, Erica E; Joiner, Ariell; Williams, Corey L; Tsai, I-Chun; Jenkins, Paul M; McEwen, Dyke P; Zhang, Lian; Escobado, John; Thomas, Sophie; Szymanska, Katarzyna; Johnson, Colin A; et al. (Nat Med, 2012)
Cilia are evolutionarily conserved microtubule-based organelles that are crucial for diverse biological functions, including motility, cell signaling and sensory perception. In humans, alterations in the formation and function of cilia manifest clinically as ciliopathies, a growing class of pleiotropic genetic disorders. Despite the substantial progress that has been made in identifying genes that cause ciliopathies, therapies for these disorders are not yet available to patients. Although mice with a hypomorphic mutation in the intraflagellar transport protein IFT88 (Ift88Tg737Rpw mice, also known as ORPK mice)5 have been well studied, the relevance of IFT88 mutations to human pathology is unknown. We show that a mutation in IFT88 causes a hitherto unknown human ciliopathy. In vivo complementation assays in zebrafish and mIMCD3 cells show the pathogenicity of this newly discovered allele. We further show that ORPK mice are functionally anosmic as a result of the loss of cilia on their olfactory sensory neurons (OSNs). Notably, adenoviral-mediated expression of IFT88 in mature, fully differentiated OSNs of ORPK mice is sufficient to restore ciliary structures and rescue olfactory function. These studies are the first to use in vivo therapeutic treatment to reestablish cilia in a mammalian ciliopathy. More broadly, our studies indicate that gene therapy is a viable option for cellular and functional rescue of the complex ciliary organelle in established differentiated cells.
Keywords: Adenoviridae; Animals; Cilia; Genetic Complementation Test; Genetic Diseases, Inborn; Genetic Therapy; Genetic Vectors; Humans; Mice; Microscopy, Fluorescence; Mutation; Olfactory Receptor Neurons; Smell; Tubulin; Tumor Suppressor Proteins; Zebrafish

Genetic contributions to the midsagittal area of the corpus callosum. - Phillips, Kimberley A; Jeffrey Rogers; Barrett, Elizabeth A; Glahn, David C; Kochunov, Peter (Twin Res Hum Genet, 2012)
The degree to which genes and environment determine variations in brain structure and function is fundamentally important to understanding normal and disease-related patterns of neural organization and activity. We studied genetic contributions to the midsagittal area of the corpus callosum (CC) in pedigreed baboons (68 males, 112 females) to replicate findings of high genetic contribution to that area of the CC reported in humans, and to determine if the heritability of the CC midsagittal area in adults was modulated by fetal development rate. Measurements of callosal area were obtained from high-resolution MRI scans. Heritability was estimated from pedigree-based maximum likelihood estimation of genetic and non-genetic variance components as implemented in Sequential Oligogenic Linkage Analysis Routines (SOLAR). Our analyses revealed significant heritability for the total area of the CC and all of its subdivisions, with h2 = .46 for the total CC, and h2 = .54, .37, .62, .56, and .29 for genu, anterior midbody, medial midbody, posterior midbody and splenium, respectively. Genetic correlation analysis demonstrated that the individual subdivisions shared between 41% and 98% of genetic variability. Combined with previous research reporting high heritability of other brain structures in baboons, these results reveal a consistent pattern of high heritability for brain morphometric measures in baboons.
Keywords: Animals; Corpus Callosum; Female; Gene-Environment Interaction; Magnetic Resonance Imaging; Male; Organ Size; Papio; Quantitative Trait, Heritable

Genomic sequencing of key genes in mouse pancreatic cancer cells. - Wang, Y; Zhang, Y; Yang, J; Ni, X; Liu, S; Li, Z; Hodges, S E; Fisher, W E; Brunicardi, F C; Richard A Gibbs; Marie-Claude Gingras; Li, M (Curr Mol Med, 2012)
Pancreatic cancer is a multiple genetic disorder with many mutations identified during the progression. Two mouse pancreatic cancer cell lines were established which showed different phenotype in vivo: a non-metastatic cell line, Panc02, and a highly metastatic cell line, Panc02-H7, a derivative of Panc02. In order to investigate whether the genetic mutations of key genes in pancreatic cancer such as KRAS, TP53 (p53), CDKN2A (p16), SMAD4, ZIP4, and PDX-1 contribute to the phenotypic difference of these two mouse pancreatic cancer cells, we sequenced the exonic regions of these key genes in both cell lines and in the normal syngeneic mouse pancreas and compared them with the reference mouse genome sequence. The exons of KRAS, SMAD4, CDKN2A (p16), TP53 (p53), ZIP4, and PDX-1 genes were amplified and the genotype of these genes was determined by Sanger sequencing. The sequences were analyzed with Sequencher software. A mutation in SMAD4 was identified in both cell lines. This homozygote G to T mutation in the first position of codon 174 (GAA) generated a stop codon resulting in the translation of a truncated protein. Further functional analysis indicates that different TGF-β/SMAD signaling pathways were involved in those two mouse cell lines, which may explain the phonotypic difference between the two cells. A single nucleotide polymorphism (SNP) in KRAS gene (TAT to TAC at codon 32) was also identified in the normal pancreas DNA of the syngenic mouse and in both derived tumoral Panc02 and Panc02-H7 cells. No mutation or SNP was found in CDKN2A (p16), TP53 (p53), ZIP4, and PDX-1 genes in these two cell lines. The absence of mutations in genes such as KRAS, TP53, and CDKN2A, which are considered as key genes in the development of human pancreatic cancer suggests that SMAD4 might play a central and decisive role in mouse pancreatic cancer. These results also suggest that other mechanisms are involved in the substantial phenotypic difference between these two mouse pancreatic cancer cell lines. Further studies are warranted to elucidate the molecular pathways that lead to the aggressive metastatic potential of Panc02-H7.
Keywords: Animals; Cell Line, Tumor; Cyclin-Dependent Kinase Inhibitor p16; Homeodomain Proteins; Mice; Pancreatic Neoplasms; Polymerase Chain Reaction; Proto-Oncogene Proteins p21(ras); Sequence Analysis, DNA; Smad4 Protein; Trans-Activators; Tumor Suppressor Protein p53

Genomics: Gorilla gorilla gorilla. - Richard A Gibbs; Jeffrey Rogers (Nature, 2012)
Keywords: Animals; Evolution, Molecular; Female; Genetic Speciation; Genome; Gorilla gorilla; Humans

High throughput sequencing methods for microbiome profiling: application to food animal systems. - Highlander, Sarah K (Anim Health Res Rev, 2012)
Analysis of microbial communities using high throughput sequencing methods began in the mid 2000s permitting the production of 1000s to 10,000s of sequence reads per sample and megabases of data per sequence run. This then unprecedented depth of sequencing allowed, for the first time, the discovery of the 'rare biosphere' in environmental samples. The technology was quickly applied to studies in several human subjects. Perhaps these early studies served as a reminder that though the microbes that inhabit mammals are known to outnumber host cells by an order of magnitude or more, most of these are unknown members of our second genome, or microbiome (as coined by Joshua Lederberg), because of our inability to culture them. High throughput methods for microbial 16S ribosomal RNA gene and whole genome shotgun (WGS) sequencing have now begun to reveal the composition and identity of archaeal, bacterial and viral communities at many sites, in and on the human body. Surveys of the microbiota of food production animals have been published in the past few years and future studies should benefit from protocols and tools developed from large-scale human microbiome studies. Nevertheless, production animal-related resources, such as improved host genome assemblies and increased numbers and diversity of host-specific microbial reference genome sequences, will be needed to permit meaningful and robust analysis of 16S rDNA and WGS sequence data.
Keywords: Animals; Animals, Domestic; Archaea; Bacteria; DNA, Ribosomal; Genes, rRNA; High-Throughput Nucleotide Sequencing; Humans; Meat; Metagenome; Metagenomics; RNA, Ribosomal, 16S; Sequence Analysis, RNA; Viruses

Identical genomic organization of two hemichordate hox clusters. - Freeman, Robert; Ikuta, Tetsuro; Wu, Michael; Koyanagi, Ryo; Kawashima, Takeshi; Tagawa, Kunifumi; Humphreys, Tom; Fang, Guang-Chen; Fujiyama, Asao; Saiga, Hidetoshi; Lowe, Christopher; Worley, Kim; et al. (Curr Biol, 2012)
Genomic comparisons of chordates, hemichordates, and echinoderms can inform hypotheses for the evolution of these strikingly different phyla from the last common deuterostome ancestor. Because hox genes play pivotal developmental roles in bilaterian animals, we analyzed the Hox complexes of two hemichordate genomes. We find that Saccoglossus kowalevskii and Ptychodera flava both possess 12-gene clusters, with mir10 between hox4 and hox5, in 550 kb and 452 kb intervals, respectively. Genes hox1-hox9/10 of the clusters are in the same genomic order and transcriptional orientation as their orthologs in chordates, with hox1 at the 3' end of the cluster. At the 5' end, each cluster contains three posterior genes specific to Ambulacraria (the hemichordate-echinoderm clade), two forming an inverted terminal pair. In contrast, the echinoderm Strongylocentrotus purpuratus contains a 588 kb cluster of 11 orthologs of the hemichordate genes, ordered differently, plausibly reflecting rearrangements of an ancestral hemichordate-like ambulacrarian cluster. Hox clusters of vertebrates and the basal chordate amphioxus have similar organization to the hemichordate cluster, but with different posterior genes. These results provide genomic evidence for a well-ordered complex in the deuterostome ancestor for the hox1-hox9/10 region, with the number and kind of posterior genes still to be elucidated.
Keywords: Animals; Biological Evolution; Chordata, Nonvertebrate; Genes, Homeobox; Genome; Molecular Sequence Data; Multigene Family; Phylogeny; Transcription, Genetic

Loss-of-function mutations in TGFB2 cause a syndromic presentation of thoracic aortic aneurysm. - Lindsay, Mark E; Schepers, Dorien; Bolar, Nikhita Ajit; Doyle, Jefferson J; Gallo, Elena; Fert-Bober, Justyna; Kempers, Marlies J E; Fishman, Elliot K; Chen, Yichun; Myers, Loretha; Bjeda, Djahita; Oswald, Gretchen; et al. (Nat Genet, 2012)
Loeys-Dietz syndrome (LDS) associates with a tissue signature for high transforming growth factor (TGF)-β signaling but is often caused by heterozygous mutations in genes encoding positive effectors of TGF-β signaling, including either subunit of the TGF-β receptor or SMAD3, thereby engendering controversy regarding the mechanism of disease. Here, we report heterozygous mutations or deletions in the gene encoding the TGF-β2 ligand for a phenotype within the LDS spectrum and show upregulation of TGF-β signaling in aortic tissue from affected individuals. Furthermore, haploinsufficient Tgfb2(+/-) mice have aortic root aneurysm and biochemical evidence of increased canonical and noncanonical TGF-β signaling. Mice that harbor both a mutant Marfan syndrome (MFS) allele (Fbn1(C1039G/+)) and Tgfb2 haploinsufficiency show increased TGF-β signaling and phenotypic worsening in association with normalization of TGF-β2 expression and high expression of TGF-β1. Taken together, these data support the hypothesis that compensatory autocrine and/or paracrine events contribute to the pathogenesis of TGF-β-mediated vasculopathies.
Keywords: Animals; Aortic Aneurysm, Thoracic; Disease Models, Animal; Female; Fibrillin-1; Fibrillins; Haploinsufficiency; Humans; Loeys-Dietz Syndrome; Male; Marfan Syndrome; Mice; Mice, Knockout; Mice, Mutant Strains; Microfilament Proteins; Mutation; Pedigree; Phenotype; Signal Transduction; Syndrome; Transforming Growth Factor beta2

MAPK target sites of eyes absent are not required for eye development or survival in Drosophila. - Jusiak, Barbara; Abulimiti, Abuduaini; Haelterman, Nele; Rui Chen; Mardon, Graeme (PLoS One, 2012)
Eyes absent (Eya) is a highly conserved transcription cofactor and protein phosphatase that plays an essential role in eye development and survival in Drosophila. Ectopic eye induction assays using cDNA transgenes have suggested that mitogen activated protein kinase (MAPK) activates Eya by phosphorylating it on two consensus target sites, S402 and S407, and that this activation potentiates the ability of Eya to drive eye formation. However, this mechanism has never been tested in normal eye development. In the current study, we generated a series of genomic rescue transgenes to investigate how loss- and gain-of-function mutations at these two MAPK target sites within Eya affect Drosophila survival and normal eye formation: eya(+)GR, the wild-type control; eya(SA)GR, which lacks phosphorylation at the two target residues; and eya(SDE)GR, which contains phosphomimetic amino acids at the same two residues. Contrary to the previous studies in ectopic eye development, all eya genomic transgenes tested rescue both eye formation and survival equally effectively. We conclude that, in contrast to ectopic eye formation, MAPK-mediated phosphorylation of Eya on S402 and S407 does not play a role in normal development. This is the first study in Drosophila to evaluate the difference in outcomes between genomic rescue and ectopic cDNA-based overexpression of the same gene. These findings indicate similar genomic rescue strategies may prove useful for re-evaluating other long-standing Drosophila developmental models.
Keywords: Animals; Compound Eye, Arthropod; Drosophila; Drosophila Proteins; Eye Proteins; Gene Expression Regulation, Developmental; Mitogen-Activated Protein Kinases; Mutation; Phenotype; Phosphorylation; Signal Transduction

Microarray-based capture of novel expressed cell type-specific transfrags (CoNECT) to annotate tissue-specific transcription in Drosophila melanogaster. - Hong, X; Harshavardhan Doddapaneni; Comeron, J M; Rodesch, M J; Halvensleben, H A; Nien, C Y; Bolei, F; Metpally, R; Richmond, T A; Albert, T J; Manak, J R (G3 (Bethesda), 2012)
Faithful annotation of tissue-specific transcript isoforms is important not only to understand how genes are organized and regulated but also to identify potential novel, unannotated exons of genes, which may be additional targets of mutation in disease states or while performing mutagenic screens. We have developed a microarray enrichment methodology followed by long-read, next-generation sequencing for identification of unannotated transcript isoforms expressed in two Drosophila tissues, the ovary and the testis. Even with limited sequencing, these studies have identified a large number of novel transcription units, including 5' exons and extensions, 3' exons and extensions, internal exons and exon extensions, gene fusions, and both germline-specific splicing events and promoters. Additionally, comparing our capture dataset with tiling array and traditional RNA-seq analysis, we demonstrate that our enrichment strategy is able to capture low-abundance transcripts that cannot readily be identified by the other strategies. Finally, we show that our methodology can help identify transcriptional signatures of minority cell types within the ovary that would otherwise be difficult to reveal without the CoNECT enrichment strategy. These studies introduce an efficient methodology for cataloging tissue-specific transcriptomes in which specific classes of genes or transcripts can be targeted for capture and sequence, thus reducing the significant sequencing depth normally required for accurate annotation. Ovary and testis isotigs over 200 bp have been deposited with the GenBank Transcriptome Shotgun Assembly Sequence Database as bioproject no.PRJNA89451 (accession nos. JV208106–JV230865).
Keywords: Animals; Databases, Genetic; Drosophila melanogaster; Drosophila Proteins; Exons; Female; Male; Oligonucleotide Array Sequence Analysis; Ovary; Promoter Regions, Genetic; Protein Isoforms; RNA Splicing; Testis; Transcriptome

Mind the gap: upgrading genomes with Pacific Biosciences RS long-read sequencing technology. - English, Adam C; Stephen Richards; Yi Han; Wang, Min; Vee, Vanesa; Qu, Jiaxin; Xiang Qin; Donna M Muzny; Reid, Jeffrey G; Worley, Kim C; Richard A Gibbs (PLoS One, 2012)
Many genomes have been sequenced to high-quality draft status using Sanger capillary electrophoresis and/or newer short-read sequence data and whole genome assembly techniques. However, even the best draft genomes contain gaps and other imperfections due to limitations in the input data and the techniques used to build draft assemblies. Sequencing biases, repetitive genomic features, genomic polymorphism, and other complicating factors all come together to make some regions difficult or impossible to assemble. Traditionally, draft genomes were upgraded to "phase 3 finished" status using time-consuming and expensive Sanger-based manual finishing processes. For more facile assembly and automated finishing of draft genomes, we present here an automated approach to finishing using long-reads from the Pacific Biosciences RS (PacBio) platform. Our algorithm and associated software tool, PBJelly, (publicly available at https://sourceforge.net/projects/pb-jelly/) automates the finishing process using long sequence reads in a reference-guided assembly process. PBJelly also provides "lift-over" co-ordinate tables to easily port existing annotations to the upgraded assembly. Using PBJelly and long PacBio reads, we upgraded the draft genome sequences of a simulated Drosophila melanogaster, the version 2 draft Drosophila pseudoobscura, an assembly of the Assemblathon 2.0 budgerigar dataset, and a preliminary assembly of the Sooty mangabey. With 24× mapped coverage of PacBio long-reads, we addressed 99% of gaps and were able to close 69% and improve 12% of all gaps in D. pseudoobscura. With 4× mapped coverage of PacBio long-reads we saw reads address 63% of gaps in our budgerigar assembly, of which 32% were closed and 63% improved. With 6.8× mapped coverage of mangabey PacBio long-reads we addressed 97% of gaps and closed 66% of addressed gaps and improved 19%. The accuracy of gap closure was validated by comparison to Sanger sequencing on gaps from the original D. pseudoobscura draft assembly and shown to be dependent on initial reference quality.
Keywords: Animals; Base Sequence; Cercocebus atys; Databases, Genetic; Decision Making; Drosophila; Genome; Melopsittacus; Reproducibility of Results; Sequence Analysis, DNA; Software

Mis-assembled "segmental duplications" in two versions of the Bos taurus genome. - Zimin, Aleksey V; Kelley, David R; Roberts, Michael; Marçais, Guillaume; Salzberg, Steven L; Yorke, James A (PLoS One, 2012)
We analyzed the whole genome sequence coverage in two versions of the Bos taurus genome and identified all regions longer than five kilobases (Kbp) that are duplicated within chromosomes with >99% sequence fidelity in both copies. We call these regions High Fidelity Duplications (HFDs). The two assemblies were Btau 4.2, produced by the Human Genome Sequencing Center at Baylor College of Medicine, and UMD Bos taurus 3.1 (UMD 3.1), produced by our group at the University of Maryland. We found that Btau 4.2 has a far greater number of HFDs, 3111 versus only 69 in UMD 3.1. Read coverage analysis shows that 39 million base pairs (Mbp) of sequence in HFDs in Btau 4.2 appear to be a result of a mis-assembly and therefore cannot be qualified as segmental duplications. UMD 3.1 has only 0.41 Mbp of sequence in HFDs that are due to a mis-assembly.
Keywords: Animals; Cattle; Genome; Humans; Reproducibility of Results; Segmental Duplications, Genomic

Mutations in KAT6B, encoding a histone acetyltransferase, cause Genitopatellar syndrome. - Campeau, Philippe M; Kim, Jaeseung C; Lu, James T; Schwartzentruber, Jeremy A; Abdul-Rahman, Omar A; Schlaubitz, Silke; Murdock, David M; Jiang, Ming-Ming; Lammer, Edward J; Enns, Gregory M; Rhead, William J; Rowland, Jon; et al. (Am J Hum Genet, 2012)
Genitopatellar syndrome (GPS) is a skeletal dysplasia with cerebral and genital anomalies for which the molecular basis has not yet been determined. By exome sequencing, we found de novo heterozygous truncating mutations in KAT6B (lysine acetyltransferase 6B, formerly known as MYST4 and MORF) in three subjects; then by Sanger sequencing of KAT6B, we found similar mutations in three additional subjects. The mutant transcripts do not undergo nonsense-mediated decay in cells from subjects with GPS. In addition, human pathological analyses and mouse expression studies point to systemic roles of KAT6B in controlling organismal growth and development. Myst4 (the mouse orthologous gene) is expressed in mouse tissues corresponding to those affected by GPS. Phenotypic differences and similarities between GPS, the Say-Barber-Biesecker variant of Ohdo syndrome (caused by different mutations of KAT6B), and Rubinstein-Taybi syndrome (caused by mutations in other histone acetyltransferases) are discussed. Together, the data support an epigenetic dysregulation of the limb, brain, and genital developmental programs.
Keywords: Abnormalities, Multiple; Animals; Blepharophimosis; Blepharoptosis; Bone Diseases, Developmental; Cerebellum; Epigenomics; Exome; Female; Heart Defects, Congenital; Heterozygote; Histone Acetyltransferases; Humans; Intellectual Disability; Male; Mice; Mice, Inbred C57BL; Musculoskeletal Abnormalities; Mutation; Phenotype; Rubinstein-Taybi Syndrome; Sequence Analysis, DNA; Urogenital Abnormalities

Mutations in the TGF-β repressor SKI cause Shprintzen-Goldberg syndrome with aortic aneurysm. - Doyle, Alexander J; Doyle, Jefferson J; Bessling, Seneca L; Maragh, Samantha; Lindsay, Mark E; Schepers, Dorien; Gillis, Elisabeth; Mortier, Geert; Homfray, Tessa; Sauls, Kimberly; Norris, Russell A; Huso, Nicholas D; et al. (Nat Genet, 2012)
Elevated transforming growth factor (TGF)-β signaling has been implicated in the pathogenesis of syndromic presentations of aortic aneurysm, including Marfan syndrome (MFS) and Loeys-Dietz syndrome (LDS). However, the location and character of many of the causal mutations in LDS intuitively imply diminished TGF-β signaling. Taken together, these data have engendered controversy regarding the specific role of TGF-β in disease pathogenesis. Shprintzen-Goldberg syndrome (SGS) has considerable phenotypic overlap with MFS and LDS, including aortic aneurysm. We identified causative variation in ten individuals with SGS in the proto-oncogene SKI, a known repressor of TGF-β activity. Cultured dermal fibroblasts from affected individuals showed enhanced activation of TGF-β signaling cascades and higher expression of TGF-β-responsive genes relative to control cells. Morpholino-induced silencing of SKI paralogs in zebrafish recapitulated abnormalities seen in humans with SGS. These data support the conclusions that increased TGF-β signaling is the mechanism underlying SGS and that high signaling contributes to multiple syndromic presentations of aortic aneurysm.
Keywords: Animals; Aortic Aneurysm; Arachnodactyly; Cells, Cultured; Craniosynostoses; DNA-Binding Proteins; Fibroblasts; Humans; Loeys-Dietz Syndrome; Marfan Syndrome; Mice; Mutation; Phenotype; Phosphorylation; Proto-Oncogene Mas; Proto-Oncogene Proteins; Signal Transduction; Transforming Growth Factor beta; Zebrafish

Pancreatic cancer genomes reveal aberrations in axon guidance pathway genes. - Biankin, Andrew V; Waddell, Nicola; Kassahn, Karin S; Marie-Claude Gingras; Muthuswamy, Lakshmi B; Johns, Amber L; Miller, David K; Wilson, Peter J; Patch, Ann-Marie; Wu, Jianmin; Chang, David K; Cowley, Mark J; et al. (Nature, 2012)
Pancreatic cancer is a highly lethal malignancy with few effective therapies. We performed exome sequencing and copy number analysis to define genomic aberrations in a prospectively accrued clinical cohort (n = 142) of early (stage I and II) sporadic pancreatic ductal adenocarcinoma. Detailed analysis of 99 informative tumours identified substantial heterogeneity with 2,016 non-silent mutations and 1,628 copy-number variations. We define 16 significantly mutated genes, reaffirming known mutations (KRAS, TP53, CDKN2A, SMAD4, MLL3, TGFBR2, ARID1A and SF3B1), and uncover novel mutated genes including additional genes involved in chromatin modification (EPC1 and ARID2), DNA damage repair (ATM) and other mechanisms (ZIM2, MAP2K4, NALCN, SLC16A4 and MAGEA6). Integrative analysis with in vitro functional data and animal models provided supportive evidence for potential roles for these genetic aberrations in carcinogenesis. Pathway-based analysis of recurrently mutated genes recapitulated clustering in core signalling pathways in pancreatic ductal adenocarcinoma, and identified new mutated genes in each pathway. We also identified frequent and diverse somatic aberrations in genes described traditionally as embryonic regulators of axon guidance, particularly SLIT/ROBO signalling, which was also evident in murine Sleeping Beauty transposon-mediated somatic mutagenesis models of pancreatic cancer, providing further supportive evidence for the potential involvement of axon guidance genes in pancreatic carcinogenesis.
Keywords: Animals; Axons; Carcinoma, Pancreatic Ductal; Gene Dosage; Gene Expression Regulation, Neoplastic; Genome; Humans; Kaplan-Meier Estimate; Mice; Mutation; Pancreatic Neoplasms; Proteins; Signal Transduction

PDX-1 is a therapeutic target for pancreatic cancer, insulinoma and islet neoplasia using a novel RNA interference platform. - Liu, Shi-He; Rao, Donald D; Nemunaitis, John; Senzer, Neil; Zhou, Guisheng; Dawson, David; Marie-Claude Gingras; Wang, Zhaohui; Richard A Gibbs; Norman, Michael; Templeton, Nancy S; DeMayo, Francesco J; et al. (PLoS One, 2012)
Pancreatic and duodenal homeobox-1 (PDX-1) is a transcription factor that regulates insulin expression and islet maintenance in the adult pancreas. Our recent studies demonstrate that PDX-1 is an oncogene for pancreatic cancer and is overexpressed in pancreatic cancer. The purpose of this study was to demonstrate that PDX-1 is a therapeutic target for both hormonal symptoms and tumor volume in mouse models of pancreatic cancer, insulinoma and islet neoplasia. Immunohistochemistry of human pancreatic and islet neoplasia specimens revealed marked PDX-1 overexpression, suggesting PDX-1 as a "drugable" target within these diseases. To do so, a novel RNA interference effector platform, bifunctional shRNA(PDX-1), was developed and studied in mouse and human cell lines as well as in mouse models of pancreatic cancer, insulinoma and islet neoplasia. Systemic delivery of bi-shRNA(humanPDX-1) lipoplexes resulted in marked reduction of tumor volume and improved survival in a human pancreatic cancer xenograft mouse model. bi-shRNA(mousePDX-1) lipoplexes prevented death from hyperinsulinemia and hypoglycemia in an insulinoma mouse model. shRNA(mousePDX-1) lipoplexes reversed hyperinsulinemia and hypoglycemia in an immune-competent mouse model of islet neoplasia. PDX-1 was overexpressed in pancreatic neuroendocrine tumors and nesidioblastosis. These data demonstrate that PDX-1 RNAi therapy controls hormonal symptoms and tumor volume in mouse models of pancreatic cancer, insulinoma and islet neoplasia, therefore, PDX-1 is a potential therapeutic target for these pancreatic diseases.
Keywords: Animals; Cell Line, Tumor; Cell Proliferation; Disease Models, Animal; Glucose Tolerance Test; Homeodomain Proteins; Humans; Immunohistochemistry; In Situ Nick-End Labeling; Insulin; Insulinoma; Islets of Langerhans; Male; Mice; Mice, SCID; Neoplasm Transplantation; Pancreas; Pancreatic Neoplasms; RNA Interference; Trans-Activators

Quantitative trait loci affecting liver fat content in mice. - Minkina, Olga; Cheverud, James M; Fawcett, Gloria; Semenkovich, Clay F; Kenney-Hunt, Jane P (G3 (Bethesda), 2012)
Nonalcoholic fatty liver disease, a condition in which excess fat accumulates in the liver, is strongly associated with the metabolic syndrome, including obesity and other related conditions. This disease has the potential to progress from steatosis to steatohepatitis, fibrosis, and cirrhosis. The recent increase in the prevalence of the metabolic syndrome is largely driven by changes in diet and activity levels. Individual variation in the response to this obesogenic environment, however, is attributable in part to genetic variation between individuals, but very few mammalian genetic loci have been identified with effects on fat accumulation in the liver. To study the genetic basis for variation in liver fat content in response to dietary fat, liver fat proportion was determined using quantitative magnetic resonance imaging in 478 mice from 16 LG/J X SM/J recombinant inbred strains fed either a high-fat (42% kcal from fat) or low-fat (15% kcal from fat) diet. An analysis of variance confirmed that there is a genetic basis for variation in liver fat content within the population with significant effects of sex and diet. Three quantitative trail loci that contribute to liver fat content also were mapped.
Keywords: Animals; Diabetes Mellitus; Diet, Fat-Restricted; Diet, High-Fat; Fats; Fatty Liver; Female; Liver; Male; Mice; Non-alcoholic Fatty Liver Disease; Obesity; Quantitative Trait Loci

Serum prostate specific antigen changes in cynomolgus monkeys (Macaca fascicularis) on a high sugar high fat diet. - Mubiru, James N; Garcia-Forey, Magdalena; Cavazos, Nicole; Hemmat, Peggah; Dick, Edward J; Owston, Michael A; Bauer, Cassondra A; Shade, Robert E; Jeffrey Rogers (Prostate, 2012)
BACKGROUND: An inverse relationship between serum prostate specific antigen (PSA) levels and body mass index (BMI) has been reported in men but not in any animal model. METHODS: Serum PSA in a colony of cynomolgus monkeys was assayed and correlated to body weight, prostate weight, and age. In addition, 15 animals were selected and fed a high sugar high fat (HSHF) diet for 49 weeks to increase their BMI and correlate it to PSA RESULTS: Serum PSA levels were positively correlated to prostate weight (r = 0.515, P = 0.025) and age (r = 0.548, P = 0.00072) but was not significantly correlated to body weight (r = -0.032, P = 0.419). For the animals on the HSHF diet, body weight, lean mass, fat mass, and BMI were significantly higher at 49 weeks than at baseline (P < 0.01). PSA was not significantly correlated to body weight and insulin at both baseline and 49 weeks. PSA was negatively correlated to BMI and insulin resistance (HOMA-IR) at 49 weeks but not at baseline. In addition, we observed hepatic steatosis and increases in serum liver enzymes. CONCLUSIONS: Increases in BMI in cynomolgus monkeys as a result of consuming a HSHF diet resulted in PSA changes similar to those in humans with increased BMI. Cynomolgus monkeys are a useful model for investigating the relationship between obesity, diabetes, and PSA changes resulting from prostate gland pathology.
Keywords: Absorptiometry, Photon; Animals; Blood Glucose; Body Mass Index; Body Weight; Dietary Carbohydrates; Dietary Fats; Disease Models, Animal; Insulin; Insulin Resistance; Macaca fascicularis; Male; Obesity; Organ Size; Prostate; Prostate-Specific Antigen

SINE retrotransposons cause epigenetic reprogramming of adjacent gene promoters. - Estécio, Marcos R H; Gallegos, Juan; Dekmezian, Mhair; Lu, Yue; Liang, Shoudan; Issa, Jean-Pierre J (Mol Cancer Res, 2012)
Almost half of the human genome and as much as 40% of the mouse genome is composed of repetitive DNA sequences. The majority of these repeats are retrotransposons of the SINE and LINE families, and such repeats are generally repressed by epigenetic mechanisms. It has been proposed that these elements can act as methylation centers from which DNA methylation spreads into gene promoters in cancer. Contradictory to a methylation center function, we have found that retrotransposons are enriched near promoter CpG islands that stay methylation-free in cancer. Clearly, it is important to determine which influence, if any, these repetitive elements have on nearby gene promoters. Using an in vitro system, we confirm here that SINE B1 elements can influence the activity of downstream gene promoters, with acquisition of DNA methylation and loss of activating histone marks, thus resulting in a repressed state. SINE sequences themselves did not immediately acquire DNA methylation but were marked by H3K9me2 and H3K27me3. Moreover, our bisulfite sequencing data did not support that gain of DNA methylation in gene promoters occurred by methylation spreading from SINE B1 repeats. Genome-wide analysis of SINE repeats distribution showed that their enrichment is directly correlated with the presence of USF1, USF2, and CTCF binding, proteins with insulator function. In summary, our work supports the concept that SINE repeats interfere negatively with gene expression and that their presence near gene promoters is counter-selected, except when the promoter is protected by an insulator element.
Keywords: Adaptor Proteins, Signal Transducing; Alu Elements; Animals; Antigens, CD; Cadherins; Cellular Reprogramming; Chromatin; Cyclin-Dependent Kinase Inhibitor p19; DNA Methylation; Epigenesis, Genetic; Gene Silencing; Genes; Humans; Insulator Elements; Long Interspersed Nucleotide Elements; Mice; MutL Protein Homolog 1; NIH 3T3 Cells; Nuclear Proteins; Promoter Regions, Genetic; Protein Binding; Short Interspersed Nucleotide Elements; Transcription Initiation Site; Transcription, Genetic; Tumor Suppressor Protein p14ARF

Strict evolutionary conservation followed rapid gene loss on human and rhesus Y chromosomes. - Hughes, Jennifer F; Skaletsky, Helen; Brown, Laura G; Pyntikova, Tatyana; Graves, Tina; Fulton, Robert S; Dugan, Shannon; Ding, Yan; Buhay, Christian J; Kremitzki, Colin; Wang, Qiaoyan; Shen, Hua; et al. (Nature, 2012)
The human X and Y chromosomes evolved from an ordinary pair of autosomes during the past 200-300 million years. The human MSY (male-specific region of Y chromosome) retains only three percent of the ancestral autosomes' genes owing to genetic decay. This evolutionary decay was driven by a series of five 'stratification' events. Each event suppressed X-Y crossing over within a chromosome segment or 'stratum', incorporated that segment into the MSY and subjected its genes to the erosive forces that attend the absence of crossing over. The last of these events occurred 30 million years ago, 5 million years before the human and Old World monkey lineages diverged. Although speculation abounds regarding ongoing decay and looming extinction of the human Y chromosome, remarkably little is known about how many MSY genes were lost in the human lineage in the 25 million years that have followed its separation from the Old World monkey lineage. To investigate this question, we sequenced the MSY of the rhesus macaque, an Old World monkey, and compared it to the human MSY. We discovered that during the last 25 million years MSY gene loss in the human lineage was limited to the youngest stratum (stratum 5), which comprises three percent of the human MSY. In the older strata, which collectively comprise the bulk of the human MSY, gene loss evidently ceased more than 25 million years ago. Likewise, the rhesus MSY has not lost any older genes (from strata 1-4) during the past 25 million years, despite its major structural differences to the human MSY. The rhesus MSY is simpler, with few amplified gene families or palindromes that might enable intrachromosomal recombination and repair. We present an empirical reconstruction of human MSY evolution in which each stratum transitioned from rapid, exponential loss of ancestral genes to strict conservation through purifying selection.
Keywords: Animals; Chromosomes, Human, Y; Conserved Sequence; Crossing Over, Genetic; Evolution, Molecular; Gene Amplification; Gene Deletion; Humans; In Situ Hybridization, Fluorescence; Macaca mulatta; Male; Models, Genetic; Molecular Sequence Data; Pan troglodytes; Radiation Hybrid Mapping; Selection, Genetic; Time Factors; Y Chromosome

Transcriptional enhancers in protein-coding exons of vertebrate developmental genes. - Ritter, Deborah I; Dong, Zhiqiang; Guo, Su; Chuang, Jeffrey H (PLoS One, 2012)
Many conserved noncoding sequences function as transcriptional enhancers that regulate gene expression. Here, we report that protein-coding DNA also frequently contains enhancers functioning at the transcriptional level. We tested the enhancer activity of 31 protein-coding exons, which we chose based on strong sequence conservation between zebrafish and human, and occurrence in developmental genes, using a Tol2 transposable GFP reporter assay in zebrafish. For each exon we measured GFP expression in hundreds of embryos in 10 anatomies via a novel system that implements the voice-recognition capabilities of a cellular phone. We find that 24/31 (77%) exons drive GFP expression compared to a minimal promoter control, and 14/24 are anatomy-specific (expression in four anatomies or less). GFP expression driven by these coding enhancers frequently overlaps the anatomies where the host gene is expressed (60%), suggesting self-regulation. Highly conserved coding sequences and highly conserved noncoding sequences do not significantly differ in enhancer activity (coding: 24/31 vs. noncoding: 105/147) or tissue-specificity (coding: 14/24 vs. noncoding: 50/105). Furthermore, coding and noncoding enhancers display similar levels of the enhancer-related histone modification H3K4me1 (coding: 9/24 vs noncoding: 34/81). Meanwhile, coding enhancers are over three times as likely to contain an H3K4me1 mark as other exons of the host gene. Our work suggests that developmental transcriptional enhancers do not discriminate between coding and noncoding DNA and reveals widespread dual functions in protein-coding DNA.
Keywords: Animals; Enhancer Elements, Genetic; Exons; Genes, Developmental; Humans; Vertebrates; Zebrafish

Treponema pallidum infection in the wild baboons of East Africa: distribution and genetic characterization of the strains responsible. - Harper, Kristin N; Fyumagwa, Robert D; Hoare, Richard; Wambura, Philemon N; Coppenhaver, Dorian H; Sapolsky, Robert M; Alberts, Susan C; Tung, Jenny; Jeffrey Rogers; Kilewo, Morris; Batamuzi, Emmanuel K; Leendertz, Fabian H; et al. (PLoS One, 2012)
It has been known for decades that wild baboons are naturally infected with Treponema pallidum, the bacterium that causes the diseases syphilis (subsp. pallidum), yaws (subsp. pertenue), and bejel (subsp. endemicum) in humans. Recently, a form of T. pallidum infection associated with severe genital lesions has been described in wild baboons at Lake Manyara National Park in Tanzania. In this study, we investigated ten additional sites in Tanzania and Kenya using a combination of macroscopic observation and serology, in order to determine whether the infection was present in each area. In addition, we obtained genetic sequence data from six polymorphic regions using T. pallidum strains collected from baboons at two different Tanzanian sites. We report that lesions consistent with T. pallidum infection were present at four of the five Tanzanian sites examined, and serology was used to confirm treponemal infection at three of these. By contrast, no signs of treponemal infection were observed at the six Kenyan sites, and serology indicated T. pallidum was present at only one of them. A survey of sexually mature baboons at Lake Manyara National Park in 2006 carried out as part of this study indicated that roughly ten percent displayed T. pallidum-associated lesions severe enough to cause major structural damage to the genitalia. Finally, we found that T. pallidum strains from Lake Manyara National Park and Serengeti National Park were genetically distinct, and a phylogeny suggested that baboon strains may have diverged prior to the clade containing human strains. We conclude that T. pallidum infection associated with genital lesions appears to be common in the wild baboons of the regions studied in Tanzania. Further study is needed to elucidate the infection's transmission mode, its associated morbidity and mortality, and the relationship between baboon and human strains.
Keywords: Africa, Eastern; Animals; Antibodies, Bacterial; DNA, Bacterial; Evolution, Molecular; Female; Humans; Male; Monkey Diseases; Papio; Phylogeny; Sequence Analysis, DNA; Species Specificity; Syphilis; Treponema pallidum

Using whole-genome sequence data to predict quantitative trait phenotypes in Drosophila melanogaster. - Ober, Ulrike; Ayroles, Julien F; Stone, Eric A; Stephen Richards; Zhu, Dianhui; Richard A Gibbs; Stricker, Christian; Gianola, Daniel; Schlather, Martin; Mackay, Trudy F C; Simianer, Henner (PLoS Genet, 2012)
Predicting organismal phenotypes from genotype data is important for plant and animal breeding, medicine, and evolutionary biology. Genomic-based phenotype prediction has been applied for single-nucleotide polymorphism (SNP) genotyping platforms, but not using complete genome sequences. Here, we report genomic prediction for starvation stress resistance and startle response in Drosophila melanogaster, using ∼2.5 million SNPs determined by sequencing the Drosophila Genetic Reference Panel population of inbred lines. We constructed a genomic relationship matrix from the SNP data and used it in a genomic best linear unbiased prediction (GBLUP) model. We assessed predictive ability as the correlation between predicted genetic values and observed phenotypes by cross-validation, and found a predictive ability of 0.239±0.008 (0.230±0.012) for starvation resistance (startle response). The predictive ability of BayesB, a Bayesian method with internal SNP selection, was not greater than GBLUP. Selection of the 5% SNPs with either the highest absolute effect or variance explained did not improve predictive ability. Predictive ability decreased only when fewer than 150,000 SNPs were used to construct the genomic relationship matrix. We hypothesize that predictive power in this population stems from the SNP-based modeling of the subtle relationship structure caused by long-range linkage disequilibrium and not from population structure or SNPs in linkage disequilibrium with causal variants. We discuss the implications of these results for genomic prediction in other organisms.
Keywords: Animals; Bayes Theorem; Chromosome Mapping; Drosophila melanogaster; Genetics, Population; Genome, Insect; Genotype; Linkage Disequilibrium; Models, Genetic; Models, Theoretical; Phenotype; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Selection, Genetic; Sequence Analysis, DNA

Characterization of single-nucleotide variation in Indian-origin rhesus macaques (Macaca mulatta). - Fawcett, Gloria L; Raveendran, Muthuswamy; Deiros, David Rio; Chen, David; Fuli Yu; R. Alan Harris; Ren, Yanru; Donna M Muzny; Reid, Jeffrey G; Wheeler, David A; Worley, Kimberly C; Shelton, Steven E; et al. (BMC Genomics, 2011)
BACKGROUND: Rhesus macaques are the most widely utilized nonhuman primate model in biomedical research. Previous efforts have validated fewer than 900 single nucleotide polymorphisms (SNPs) in this species, which limits opportunities for genetic studies related to health and disease. Extensive information about SNPs and other genetic variation in rhesus macaques would facilitate valuable genetic analyses, as well as provide markers for genome-wide linkage analysis and the genetic management of captive breeding colonies. RESULTS: We used the available rhesus macaque draft genome sequence, new sequence data from unrelated individuals and existing published sequence data to create a genome-wide SNP resource for Indian-origin rhesus monkeys. The original reference animal and two additional Indian-origin individuals were resequenced to low coverage using SOLiD™ sequencing. We then used three strategies to validate SNPs: comparison of potential SNPs found in the same individual using two different sequencing chemistries, and comparison of potential SNPs in different individuals identified with either the same or different sequencing chemistries. Our approach validated approximately 3 million SNPs distributed across the genome. Preliminary analysis of SNP annotations suggests that a substantial number of these macaque SNPs may have functional effects. More than 700 non-synonymous SNPs were scored by Polyphen-2 as either possibly or probably damaging to protein function and these variants now constitute potential models for studying functional genetic variation relevant to human physiology and disease. CONCLUSIONS: Resequencing of a small number of animals identified greater than 3 million SNPs. This provides a significant new information resource for rhesus macaques, an important research animal. The data also suggests that overall genetic variation is high in this species. We identified many potentially damaging non-synonymous coding SNPs, providing new opportunities to identify rhesus models for human disease.
Keywords: Animals; Genetic Variation; India; Macaca mulatta; Polymorphism, Single Nucleotide; Sequence Analysis, DNA; Species Specificity

Comparative and demographic analysis of orang-utan genomes. - Locke, Devin P; Hillier, LaDeana W; Warren, Wesley C; Worley, Kim C; Nazareth, Lynne V; Donna M Muzny; Yang, Shiaw-Pyng; Wang, Zhengyuan; Chinwalla, Asif T; Minx, Pat; Mitreva, Makedonka; Cook, Lisa; et al. (Nature, 2011)
'Orang-utan' is derived from a Malay term meaning 'man of the forest' and aptly describes the southeast Asian great apes native to Sumatra and Borneo. The orang-utan species, Pongo abelii (Sumatran) and Pongo pygmaeus (Bornean), are the most phylogenetically distant great apes from humans, thereby providing an informative perspective on hominid evolution. Here we present a Sumatran orang-utan draft genome assembly and short read sequence data from five Sumatran and five Bornean orang-utan genomes. Our analyses reveal that, compared to other primates, the orang-utan genome has many unique features. Structural evolution of the orang-utan genome has proceeded much more slowly than other great apes, evidenced by fewer rearrangements, less segmental duplication, a lower rate of gene family turnover and surprisingly quiescent Alu repeats, which have played a major role in restructuring other primate genomes. We also describe a primate polymorphic neocentromere, found in both Pongo species, emphasizing the gradual evolution of orang-utan genome structure. Orang-utans have extremely low energy usage for a eutherian mammal, far lower than their hominid relatives. Adding their genome to the repertoire of sequenced primates illuminates new signals of positive selection in several pathways including glycolipid metabolism. From the population perspective, both Pongo species are deeply diverse; however, Sumatran individuals possess greater diversity than their Bornean counterparts, and more species-specific variation. Our estimate of Bornean/Sumatran speciation time, 400,000 years ago, is more recent than most previous studies and underscores the complexity of the orang-utan speciation process. Despite a smaller modern census population size, the Sumatran effective population size (N(e)) expanded exponentially relative to the ancestral N(e) after the split, while Bornean N(e) declined over the same period. Overall, the resources and analyses presented here offer new opportunities in evolutionary genomics, insights into hominid biology, and an extensive database of variation for conservation efforts.
Keywords: Animals; Centromere; Cerebrosides; Chromosomes; Evolution, Molecular; Female; Gene Rearrangement; Genetic Speciation; Genetic Variation; Genetics, Population; Genome; Humans; Male; Phylogeny; Pongo abelii; Pongo pygmaeus; Population Density; Population Dynamics; Species Specificity

Cortical sulcal areas in baboons (Papio hamadryas spp.) with generalized interictal epileptic discharges on scalp EEG. - Szabó, C A; Kochunov, P; Knape, K D; McCoy, K J M; Leland, M M; Lancaster, J L; Fox, P T; Williams, J T; Rogers, J (Epilepsy Res, 2011)
Brain MRI studies in people with idiopathic generalized epilepsies demonstrate regional morphometric differences, though variable in magnitude and location. As the baboon provides an excellent electroclinical and neuroimaging model for photosensitive generalized epilepsy in humans, this study evaluated MRI volumetric and morphometric differences between baboons with interictal epileptic discharges (IEDs) on scalp EEG and baboons with normal EEG studies. Seventy-seven baboons underwent high-resolution brain MRI and scalp EEG studies. The scans were acquired using an 8-channel primate head coil (Siemens TRIO 3T scanner, Erlangen, Germany). After spatial normalization, sulcal measurements were obtained by object-based-morphology methods. One-hour scalp EEG studies were performed in animals sedated with ketamine. Thirty-eight (22F/16M) baboons had normal EEGs (IED-), while 39 (22F/17M) had generalized IEDs (IED+). The two groups were compared for age, total brain volume, and sulcal areas (Hotelling's Trace) as well as between-subjects comparison of 11 individual sulcal areas (averaged between left and right hemispheres). There were no differences between IED- and IED+ groups with respect to age or total brain (gray or white matter) volume, and multivariate tests demonstrated a marginally significant decrease of sulcal areas in IED+ baboons (p=0.075). Tests of between-subjects effects showed statistically significant decreases in the intraparietal (p=0.002), central (p=0.03) and cingulate sulci (p=0.02), and marginal decreases involving the lunate (p=0.07) and superior temporal sulci (p=0.08). Differences in sulcal areas in IED+ baboons may reflect global developmental abnormalities, while decreases of areas of specific sulci reflect anatomical markers for potential generators or cortical nodes of the networks underlying spontaneous seizures and photosensitivity in the baboon.
Keywords: Animals; Brain; Cerebral Cortex; Data Interpretation, Statistical; Electroencephalography; Epilepsy; Female; Functional Laterality; Image Processing, Computer-Assisted; Magnetic Resonance Imaging; Male; Papio; Parietal Lobe; Seizures

Dicer-mediated upregulation of BCRP confers tamoxifen resistance in human breast cancer cells. - Selever, Jennifer; Gu, Guowei; Lewis, Michael T; Beyer, Amanda; Herynk, Matthew H; Covington, Kyle R; Tsimelzon, Anna; Dontu, Gabriela; Provost, Patrick; Di Pietro, Attilio; Boumendjel, Ahcène; Albain, Kathy; et al. (Clin Cancer Res, 2011)
PURPOSE: Tamoxifen (Tam) is the most prescribed hormonal agent for treatment of estrogen receptor α (ERα)-positive breast cancer patients. Using microarray analysis, we observed that metastatic breast tumors resistant to Tam therapy had elevated levels of Dicer. EXPERIMENTAL DESIGN: We overexpressed Dicer in ERα-positive MCF-7 human breast cancer cells and observed a concomitant increase in expression of the breast cancer resistance protein (BCRP). We thus hypothesized that Tam resistance associated with Dicer overexpression in ERα-positive breast cancer cells may involve BCRP. We analyzed BCRP function in Dicer-overexpressing cells using growth in soft agar and mammosphere formation and evaluated intracellular Tam efflux. RESULTS: In the presence of Tam, Dicer-overexpressing cells formed resistant colonies in soft agar, and treatment with BCRP inhibitors restored Tam sensitivity. Tumor xenograft studies confirmed that Dicer-overexpressing cells were resistant to Tam in vivo. Tumors and distant metastases could be initiated with as few as five mammosphere cells from both vector and Dicer-overexpressing cells, indicating that the mammosphere assay selected for cells with enhanced tumor-initiating and metastatic capacity. Dicer-overexpressing cells with elevated levels of BCRP effluxed Tam more efficiently than control cells, and BCRP inhibitors were able to inhibit efflux. CONCLUSION: Dicer-overexpressing breast cancer cells enriched for cells with enhanced BCRP function. We hypothesize that it is this population which may be involved in the emergence of Tam-resistant growth. BCRP may be a novel clinical target to restore Tam sensitivity.
Keywords: Animals; Antineoplastic Agents, Hormonal; ATP Binding Cassette Transporter, Subfamily G, Member 2; ATP-Binding Cassette Transporters; Breast Neoplasms; Cell Line, Tumor; DEAD-box RNA Helicases; Disease Models, Animal; Drug Resistance, Neoplasm; Estrogen Antagonists; Estrogen Receptor alpha; Female; Humans; Mice; Mice, Nude; Neoplasm Proteins; Neoplasms, Hormone-Dependent; Ribonuclease III; Tamoxifen; Up-Regulation

Diet-dependent genetic and genomic imprinting effects on obesity in mice. - Cheverud, James M; Lawson, Heather A; Fawcett, Gloria L; Wang, Bing; Pletscher, L Susan; R Fox, Ashley; Maxwell, Taylor J; Ehrich, Thomas H; Kenney-Hunt, Jane P; Wolf, Jason B; Semenkovich, Clay F (Obesity (Silver Spring), 2011)
Although the current obesity epidemic is of environmental origin, there is substantial genetic variation in individual response to an obesogenic environment. In this study, we perform a genome-wide scan for quantitative trait loci (QTLs) affecting obesity per se, or an obese response to a high-fat diet in mice from the LG/J by SM/J Advanced Intercross (AI) Line (Wustl:LG,SM-G16). A total of 1,002 animals from 78 F₁₆ full sibships were weaned at 3 weeks of age and half of each litter placed on high- and low-fat diets. Animals remained on the diet until 20 weeks of age when they were necropsied and the weights of the reproductive, kidney, mesenteric, and inguinal fat depots were recorded. Effects on these phenotypes, along with total fat depot weight and carcass weight at necropsy, were mapped across the genome using 1,402 autosomal single-nucleotide polymorphism (SNP) markers. Haplotypes were reconstructed and additive, dominance, and imprinting genotype scores were derived every 1 cM along the F₁₆ map. Analysis was performed using a mixed model with additive, dominance, and imprinting genotype scores, their interactions with sex, diet, and with sex-by-diet as fixed effects and with family and its interaction with sex, diet, and sex-by-diet as random effects. We discovered 95 trait-specific QTLs mapping to 40 locations. Most QTLs had additive effects with dominance and imprinting effects occurring at two-thirds of the loci. Nearly every locus interacted with sex and/or diet in important ways demonstrating that gene effects are primarily context dependent, changing depending on sex and/or diet.
Keywords: Adipose Tissue; Adiposity; Animals; Body Weight; Diet; Epigenesis, Genetic; Female; Genome-Wide Association Study; Genomic Imprinting; Male; Mice; Obesity; Organ Size; Polymorphism, Single Nucleotide; Quantitative Trait Loci

Disruptive TP53 mutation is associated with aggressive disease characteristics in an orthotopic murine model of oral tongue cancer. - Sano, Daisuke; Xie, Tong-Xin; Ow, Thomas J; Zhao, Mei; Pickering, Curtis R; Zhou, Ge; Sandulache, Vlad C; Wheeler, David A; Richard A Gibbs; Caulin, Carlos; Myers, Jeffrey N (Clin Cancer Res, 2011)
PURPOSE: To characterize tumor growth and metastatic potential in head and neck squamous cell carcinoma (HNSCC) cell lines in an orthotopic murine model of oral tongue cancer and to correlate TP53 mutation status with these findings. EXPERIMENTAL DESIGN: Cells from each of 48 HNSCC cell lines were orthotopically injected into the oral tongues of nude mice. Tumor volume, cervical lymph node metastasis, and mouse survival were recorded. Direct sequencing of the TP53 gene and Western blot analysis for the p53 protein after induction with 5-fluorouracil was conducted. Cell lines were categorized as either mutant TP53 or wild-type TP53, and lines with TP53 mutation were further categorized on the basis of type of mutation (disruptive or nondisruptive) and level of p53 protein expression. The behavior of tumors in these different groups was compared. RESULTS: These 48 HNSCC cell lines showed a wide range of behavior from highly aggressive and metastatic to no tumor formation. Mice injected with cells harboring disruptive TP53 mutations had faster tumor growth, greater incidence of cervical lymph node metastasis, and shorter survival than mice injected with cells lacking these mutations. CONCLUSIONS: HNSCC cell lines display a wide spectrum of behavior in an orthotopic model of oral cancer. Cell lines with disruptive TP53 mutations are more aggressive in this system, corroborating clinical reports that have linked these mutations to poor patient outcome.
Keywords: Animals; Carcinoma, Squamous Cell; Cell Line, Tumor; Disease Models, Animal; Genes, p53; Head and Neck Neoplasms; Humans; Male; Mice; Mice, Nude; Mutation; Squamous Cell Carcinoma of Head and Neck; Tongue Neoplasms; Transplantation, Heterologous; Tumor Suppressor Protein p53

The Drosophila melanogaster transcriptome by paired-end RNA sequencing. - Daines, Bryce; Wang, Hui; Wang, Liguo; Yumei Li; Yi Han; Emmert, David; Gelbart, William; Wang, Xia; Li, Wei; Richard A Gibbs; Rui Chen (Genome Res, 2011)
RNA-seq was used to generate an extensive map of the Drosophila melanogaster transcriptome by broad sampling of 10 developmental stages. In total, 142.2 million uniquely mapped 64-100-bp paired-end reads were generated on the Illumina GA II yielding 356× sequencing coverage. More than 95% of FlyBase genes and 90% of splicing junctions were observed. Modifications to 30% of FlyBase gene models were made by extension of untranslated regions, inclusion of novel exons, and identification of novel splicing events. A total of 319 novel transcripts were identified, representing a 2% increase over the current annotation. Alternate splicing was observed in 31% of D. melanogaster genes, a 38% increase over previous estimations, but significantly less than that observed in higher organisms. Much of this splicing is subtle such as tandem alternate splice sites.
Keywords: Alternative Splicing; Animals; Drosophila melanogaster; Female; Gene Expression Profiling; Genes, Y-Linked; Male; Molecular Sequence Annotation; Molecular Sequence Data; Oligonucleotide Array Sequence Analysis; Sequence Analysis, RNA

Evolution of pleiotropy: epistatic interaction pattern supports a mechanistic model underlying variation in genotype-phenotype map. - Pavlicev, Mihaela; Norgard, Elizabeth A; Fawcett, Gloria L; Cheverud, James M (J Exp Zool B Mol Dev Evol, 2011)
The genotype-phenotype (GP) map consists of developmental and physiological mechanisms mapping genetic onto phenotypic variation. It determines the distribution of heritable phenotypic variance on which selection can act. Comparative studies of morphology as well as of gene regulatory networks show that the GP map itself evolves, yet little is known about the actual evolutionary mechanisms involved. The study of such mechanisms requires exploring the variation in GP maps at the population level, which presently is easier to quantify by statistical genetic methods rather than by regulatory network structures. We focus on the evolution of pleiotropy, a major structural aspect of the GP map. Pleiotropic genes affect multiple traits and underlie genetic covariance between traits, often causing evolutionary constraints. Previous quantitative genetic studies have demonstrated population-level variation in pleiotropy in the form of loci, at which genotypes differ in the genetic covariation between traits. This variation can potentially fuel evolution of the GP map under selection and/or drift. Here, we propose a developmental mechanism underlying population genetic variation in covariance and test its predictions. Specifically, the mechanism predicts that the loci identified as responsible for genetic variation in pleiotropy are involved in trait-specific epistatic interactions. We test this prediction for loci affecting allometric relationships between traits in an advanced intercross between inbred mouse strains. The results consistently support the prediction. We further find a high degree of sign epistasis in these interactions, which we interpret as an indication of adaptive gene complexes within the diverged parental lines.
Keywords: Animals; Biological Evolution; Crosses, Genetic; Epistasis, Genetic; Evolution, Molecular; Gene Regulatory Networks; Genetic Pleiotropy; Genetic Variation; Genotype; Mice; Mice, Inbred Strains; Models, Genetic; Phenotype; Quantitative Trait Loci

Exome capture sequencing identifies a novel mutation in BBS4. - Wang, Hui; Chen, Xianfeng; Dudinsky, Lynn; Patenia, Claire; Chen, Yiyun; Yumei Li; Wei, Yue; Abboud, Emad B; Al-Rajhi, Ali A; Lewis, Richard Alan; Lupski, James R; Mardon, Graeme; et al. (Mol Vis, 2011)
PURPOSE: Leber congenital amaurosis (LCA) is one of the most severe eye dystrophies characterized by severe vision loss at an early stage and accounts for approximately 5% of all retinal dystrophies. The purpose of this study was to identify a novel LCA disease allele or gene and to develop an approach combining genetic mapping with whole exome sequencing. METHODS: Three patients from King Khaled Eye Specialist Hospital (KKESH205) underwent whole genome single nucleotide polymorphism genotyping, and a single candidate region was identified. Taking advantage of next-generation high-throughput DNA sequencing technologies, whole exome capture sequencing was performed on patient KKESH205#7. Sanger direct sequencing was used during the validation step. The zebrafish model was used to examine the function of the mutant allele. RESULTS: A novel missense mutation in Bardet-Biedl syndrome 4 protein (BBS4) was identified in a consanguineous family from Saudi Arabia. This missense mutation in the fifth exon (c.253G>C;p.E85Q) of BBS4 is likely a disease-causing mutation as it segregates with the disease. The mutation is not found in the single nucleotide polymorphism (SNP) database, the 1000 Genomes Project, or matching normal controls. Functional analysis of this mutation in zebrafish indicates that the G253C allele is pathogenic. Coinjection of the G253C allele cannot rescue the mislocalization of rhodopsin in the retina when BBS4 is knocked down by morpholino injection. Immunofluorescence analysis in cell culture shows that this missense mutation in BBS4 does not cause obvious defects in protein expression or pericentriolar localization. CONCLUSIONS: This mutation likely mainly reduces or abolishes BBS4 function in the retina. Further studies of this allele will provide important insights concerning the pleiotropic nature of BBS4 function.
Keywords: Alleles; Animals; Base Sequence; Chromosome Mapping; Consanguinity; Exome; Exons; Female; Genotype; High-Throughput Nucleotide Sequencing; Humans; Infant; Leber Congenital Amaurosis; Male; Microtubule-Associated Proteins; Molecular Sequence Data; Mutation, Missense; Pedigree; Polymorphism, Single Nucleotide; Proteins; Retina; Rhodopsin; Saudi Arabia; Zebrafish

Genetical genomics of Th1 and Th2 immune response in a baboon model of atherosclerosis risk factors. - Vinson, A; Curran, J E; Johnson, M P; Dyer, T D; Moses, E K; Blangero, J; Cox, L A; Rogers, J; Havill, L M; VandeBerg, J L; Mahaney, M C (Atherosclerosis, 2011)
OBJECTIVE: CD4(+) T-cells mediate inflammation in atherosclerosis, but additive genetic effects on associated pathways of Th1 and Th2 immune response have not been described. We sought to characterize heritability, pleiotropy, and QTL effects on the expression of genes implicated in Th1 and Th2 immune response in a baboon model of risk factors for atherosclerosis. METHODS: We employed a maximum likelihood-based variance decomposition approach to estimate additive genetic effects on transcript levels generated from a gene expression profile of lymphocytes in 499 pedigreed baboons maintained on a basal diet. Transcript levels for 57 genes implicated in Th1 and Th2 immune response were selected for analysis based on significant heritability in this profile. Multipoint whole genome scans were conducted on heritable transcript levels to localize QTLs influencing these measures. To evaluate pleiotropic effects on transcript levels, we estimated genetic and phenotypic correlations among transcript measures, and assessed their correspondence using a Mantel test. Network analysis using GeneGo's MetaCore™ software was conducted to characterize known interaction among coded proteins. RESULTS: Heritabilities for candidate gene transcript levels ranged from 0.092-0.786 (median h(2)=0.278, P=4.72×10(-4)). Linkage analyses yielded significant evidence (LOD≥2.73) for 14 eQTLs (LOD score range 2.76-14.87, genome-wide P=4.9×10(-2)-1.03×10(-14)). Estimates of genetic correlation supported shared additive genetic effects incorporating all 57 transcripts (null hypothesis of ρ(G)=0 rejected at FDR≤0.05 for 522 of 1596 estimates), and accounted for most of the observed phenotypic correlation among transcripts (Mantel test, r([ρP],)([ρG])=0.781, P<0.0001). Network analysis revealed direct interactions among 54 of the 57 coded proteins. CONCLUSIONS: We conclude that major genetic effects influence expression levels of multiple genes implicated in Th1 and Th2 immune response. Additionally, we find that expression levels of these candidate genes are characterized by extensive pleiotropy, consistent with known interaction among their coded proteins, many of which are independently associated with atherosclerosis.
Keywords: Animals; Atherosclerosis; Disease Models, Animal; Female; Gene Expression Profiling; Gene Regulatory Networks; Genetic Pleiotropy; Genetic Predisposition to Disease; Heredity; Inflammation; Male; Models, Genetic; Papio hamadryas; Phenotype; Quantitative Trait Loci; Risk Assessment; Risk Factors; Th1 Cells; Th2 Cells; Transcription, Genetic

The genome of th17 cell-inducing segmented filamentous bacteria reveals extensive auxotrophy and adaptations to the intestinal environment. - Sczesnak, Andrew; Segata, Nicola; Xiang Qin; Gevers, Dirk; Petrosino, Joseph F; Huttenhower, Curtis; Littman, Dan R; Ivanov, Ivaylo I (Cell Host Microbe, 2011)
Perturbations of the composition of the symbiotic intestinal microbiota can have profound consequences for host metabolism and immunity. In mice, segmented filamentous bacteria (SFB) direct the accumulation of potentially proinflammatory Th17 cells in the intestinal lamina propria. We present the genome sequence of SFB isolated from monocolonized mice, which classifies SFB phylogenetically as a unique member of Clostridiales with a highly reduced genome. Annotation analysis demonstrates that SFB depend on their environment for amino acids and essential nutrients and may utilize host and dietary glycans for carbon, nitrogen, and energy. Comparative analyses reveal that SFB are functionally related to members of the genus Clostridium and several pathogenic or commensal "minimal" genera, including Finegoldia, Mycoplasma, Borrelia, and Phytoplasma. However, SFB are functionally distinct from all 1200 examined genomes, indicating a gene complement representing biology relatively unique to their role as a gut commensal closely tied to host metabolism and immunity.
Keywords: Adaptation, Physiological; Animals; Bacteria; Bacterial Physiological Phenomena; Clostridium; Genome, Bacterial; Humans; Intestines; Mice; Mice, Inbred C57BL; Molecular Sequence Data; Th17 Cells

Genome sequence of an Australian kangaroo, Macropus eugenii, provides insight into the evolution of mammalian reproduction and development. - Renfree, Marilyn B; Papenfuss, Anthony T; Deakin, Janine E; Lindsay, James; Heider, Thomas; Belov, Katherine; Rens, Willem; Waters, Paul D; Pharo, Elizabeth A; Shaw, Geoff; Wong, Emily S W; Lefèvre, Christophe M; et al. (Genome Biol, 2011)
BACKGROUND: We present the genome sequence of the tammar wallaby, Macropus eugenii, which is a member of the kangaroo family and the first representative of the iconic hopping mammals that symbolize Australia to be sequenced. The tammar has many unusual biological characteristics, including the longest period of embryonic diapause of any mammal, extremely synchronized seasonal breeding and prolonged and sophisticated lactation within a well-defined pouch. Like other marsupials, it gives birth to highly altricial young, and has a small number of very large chromosomes, making it a valuable model for genomics, reproduction and development. RESULTS: The genome has been sequenced to 2 × coverage using Sanger sequencing, enhanced with additional next generation sequencing and the integration of extensive physical and linkage maps to build the genome assembly. We also sequenced the tammar transcriptome across many tissues and developmental time points. Our analyses of these data shed light on mammalian reproduction, development and genome evolution: there is innovation in reproductive and lactational genes, rapid evolution of germ cell genes, and incomplete, locus-specific X inactivation. We also observe novel retrotransposons and a highly rearranged major histocompatibility complex, with many class I genes located outside the complex. Novel microRNAs in the tammar HOX clusters uncover new potential mammalian HOX regulatory elements. CONCLUSIONS: Analyses of these resources enhance our understanding of marsupial gene evolution, identify marsupial-specific conserved non-coding elements and critical genes across a range of biological systems, including reproduction, development and immunity, and provide new insight into marsupial and mammalian biology and genome evolution.
Keywords: Animals; Australia; Biological Evolution; Chromosome Mapping; Chromosomes, Mammalian; Female; Gene Expression Regulation; Genome; Genomic Imprinting; In Situ Hybridization, Fluorescence; Macropodidae; MicroRNAs; Molecular Sequence Data; Reproduction; Sequence Alignment; Sequence Analysis, DNA; Transcriptome

Heritability of alveolar bone loss from periodontal disease in a baboon population: a pilot study. - Miley, D Douglas; Baumgartner, Mark H; Cheverud, James M; Roseman, Charles C; Jeffrey Rogers; McLeod, Dwight E; Reyes, Elio; Hildebolt, Charles F (J Periodontol, 2011)
BACKGROUND: Reports from studies of twins, disease aggregation in families, animal models for periodontal disease, and various genetic-analysis studies have determined that genetics plays a role in the susceptibility to periodontal disease. The purpose of this pilot study is to evaluate the effect of genetics on periodontal disease by evaluating the heritability of alveolar bone loss in a captive baboon population. METHODS: A collection of baboon skulls from a pedigreed colony (for which scientists and veterinarians maintain complete genealogic and veterinary records) was obtained from the Southwest National Primate Research Center, San Antonio, Texas and used in this pilot study. Measurements of alveolar bone loss were performed on 390 dry baboon skulls. A periodontal probe was used to measure alveolar bone loss. Maximum likelihood methods (designed to handle complex genealogies) were used to determine the heritability of alveolar bone loss. This software used known pedigrees in the captive baboon sample and tested the relationship between pairwise kinship and alveolar bone loss data to determine the heritability of alveolar bone loss from periodontal disease. RESULTS: Genetic data were available for 347 of the 390 specimens. Using age and sex as covariates, genetic analysis indicated a heritability of 35% (standard error = 20%; P = 0.01). Although gender was not a significant factor in periodontal disease (P = 0.96), age was highly significantly associated with periodontal disease (P <0.0001). CONCLUSIONS: In this pilot study, analysis of alveolar bone loss measurements from captive baboons indicates that bone loss increases with age and that a portion of periodontal disease risk may be caused by genetic variance. These findings provide evidence that periodontal disease is heritable in captive baboons and indicate that a larger, more-detailed study is warranted.
Keywords: Age Factors; Alveolar Bone Loss; Animals; Disease Models, Animal; Female; Genetic Predisposition to Disease; Male; Mandible; Papio; Periodontal Diseases; Pilot Projects

High-resolution identity by descent mapping uncovers the genetic basis for blood pressure differences between spontaneously hypertensive rat lines. - Bell, Rebecca; Herring, Stacy M; Gokul, Nisha; Monita, Monique; Grove, Megan L; Eric Boerwinkle; Doris, Peter A (Circ Cardiovasc Genet, 2011)
BACKGROUND: The recent development of a large panel of genome-wide single nucleotide polymorphisms (SNPs) provides the opportunity to examine genetic relationships between distinct SHR lines that share hypertension but differ in their susceptibility to hypertensive end-organ disease. METHODS AND RESULTS: We compared genotypes at nearly 10,000 SNPs obtained for the hypertension end-organ injury-susceptible spontaneously hypertensive rat (SHR)-A3 (SHRSP, SHR-stroke prone) line and the injury-resistant SHR-B2 line. This revealed that that the 2 lines were genetically identical by descent (IBD) across 86.6% of the genome. Areas of the genome that were not IBD were distributed across 19 of the 20 autosomes and the X chromosome. A block structure of non-IBD comprising a total of 121 haplotype blocks was formed by clustering of SNPs inherited from different ancestors. To test the null hypothesis that distinct SHR lines share a common set of hypertension susceptibility alleles, we compared blood pressure in adult SHR animals from both lines and their F1 and F2 progeny using telemetry. In 16- to 18-week-old animals fed a normal diet, systolic blood pressure (SBP, mm Hg) in SHR-A3 was 205.7 ± 3.86 (mean ± SEM, n = 26), whereas in similar SHR-B2 animals, SBP was 186.7 ± 2.53 (n = 20). In F1 and F2 animals, SBP was 188.2 ± 4.23 (n = 19) and 185.6 ± 1.1 (n = 211), respectively (P<10(-6), ANOVA). To identify non-IBD haplotype blocks contributing to blood pressure differences between these SHR lines, we developed a high-throughput SNP genotyping system to genotype SNPs marking non-IBD blocks. We mapped a single non-IBD block on chromosome 17 extending over <10 Mb, at which SHR-A3 alleles significantly elevate blood pressure compared with SHR-B2. CONCLUSIONS: Thus hypertension in SHR-A3 and -B2 appears to arise from an overlapping set of susceptibility alleles, with SHR-A3 possessing an additional hypertension locus that contributes to further increase blood pressure.
Keywords: Animals; Blood Pressure; Chromosome Mapping; Female; Gene Expression; Genetic Predisposition to Disease; Genotype; Haplotypes; Lod Score; Male; Molecular Sequence Data; Polymorphism, Single Nucleotide; Rats; Rats, Inbred SHR

A high-resolution map of human evolutionary constraint using 29 mammals. - Lindblad-Toh, Kerstin; Garber, Manuel; Zuk, Or; Lin, Michael F; Parker, Brian J; Washietl, Stefan; Kheradpour, Pouya; Ernst, Jason; Jordan, Gregory; Mauceli, Evan; Ward, Lucas D; Lowe, Craig B; et al. (Nature, 2011)
The comparison of related genomes has emerged as a powerful lens for genome interpretation. Here we report the sequencing and comparative analysis of 29 eutherian genomes. We confirm that at least 5.5% of the human genome has undergone purifying selection, and locate constrained elements covering ∼4.2% of the genome. We use evolutionary signatures and comparisons with experimental data sets to suggest candidate functions for ∼60% of constrained bases. These elements reveal a small number of new coding exons, candidate stop codon readthrough events and over 10,000 regions of overlapping synonymous constraint within protein-coding exons. We find 220 candidate RNA structural families, and nearly a million elements overlapping potential promoter, enhancer and insulator regions. We report specific amino acid residues that have undergone positive selection, 280,000 non-coding elements exapted from mobile elements and more than 1,000 primate- and human-accelerated elements. Overlap with disease-associated variants indicates that our findings will be relevant for studies of human biology, health and disease.
Keywords: Animals; Disease; Evolution, Molecular; Exons; Genome; Genome, Human; Genomics; Health; Humans; Mammals; Molecular Sequence Annotation; Phylogeny; RNA; Selection, Genetic; Sequence Alignment; Sequence Analysis, DNA

The hypofunctional effect of P335L single nucleotide polymorphism on SSTR5 function. - Zhou, Guisheng; Marie-Claude Gingras; Liu, Shi-He; Li, Donghui; Li, Zhijun; Catania, Robbi L; Stehling, Kelly M; Li, Min; Paganelli, Giovanni; Richard A Gibbs; DeMayo, Francesco J; Fisher, William E; et al. (World J Surg, 2011)
BACKGROUND: Somatostatin receptor subtype 5 (SSTR5) mediates the inhibitory effect of somatostatin on insulin expression/secretion and cell proliferation. A number of single nucleotide polymorphisms (SNPs) of SSTR5 have been identified, including P335L, a nonsynonymous SNP located in the protein C-terminal region and encrypted by the codon CCG (proline) or the codon CTG (leucine). In the present study we sought to determine the distribution of the SSTR5 P335L SNP in a cohort of pancreatic cancer patients and whether the P335L SNP affected cellular function of SSTR5 in human pancreatic cancer. METHODS: The P335L germline genotype of 246 patients with pancreatic cancer (213 Caucasians, 16 Hispanics, and 17 African Americans) and 17 human pancreatic cell lines was determined with the TaqMan SNP Genotyping assay. Human SSTR5 leucine variant (L335) was generated by performing site-directed mutagenesis using SSTR5 proline variant (P335) as a template. Transient transfections were performed in HEK293, Mia PaCa-2, and β-TC-6 cells using Lipofectamine 2000. The expression of SSTR5 L335 was determined with a mouse monoclonal anti-SSTR5 L335 antibody generated in our laboratory. The cell proliferation rate was measured by performing MTS assays. Insulin concentration was measured by performing ELISA assays. RESULTS: Genotyping of the patients' blood indicated that the frequency of the T allele (CT and TT genotypes) in codon 335 of SSTR5 in Caucasians, Hispanics, and African Americans was 52, 69, and 35%, respectively, which was race-dependent. Statistical analysis indicated that association between the frequency of the T allele and the existence of pancreatic cancer in each race missed significance perhaps due to limited sample size. In 17 tested human pancreatic cancer cell lines, 5 (Capan-2, HPAF-II, Panc03.27, Panc-1, and -3) were homozygous (TT genotype) and 9, including Mia PaCa-2, were heterozygous (CT genotype). Overexpression of SSTR5 L335 in Mia PaCa-2 cells enhanced cell proliferation compared to overexpression of SSTR5 P335. Overexpression of SSTR5 P335 enhanced the inhibitory effect of SSTR5 agonist RPL-1980 on cell proliferation of Mia PaCa-2 cells and glucose-stimulated insulin secretion from mouse insulinoma cells, while overexpression of SSTR5 L335 blocked the inhibitory effect of RPL-1980. Overexpression of SSTR5 L335 enhanced PDX-1 expression in Mia PaCa-2 cells. A specific monoclonal antibody was generated to detect SSTR5 P335L. CONCLUSION: SSTR5 P335L SNP widely exists in the human population, in patients with pancreatic cancer, and is race-dependent. The SNP is also present in selected human pancreatic cancer cell lines. In contrast to SSTR5 P335, overexpression of the SSTR5 L335 variant resulted in cellular proliferation and PDX-1 overexpression in human pancreatic cancer cells. Its overexpression blocked the inhibitory effect of an SSTR5-specific analog on human pancreatic cancer cell proliferation and on glucose-stimulated insulin secretion from mouse insulinoma cells. These data suggest that SSTR5 P335L is a hypofunctional protein with a potentially harmful effect on function, as well as potential latent effect, and therefore it could affect the clinical response to somatostatin analog therapy for patients with pancreatic cancer.
Keywords: Adenocarcinoma; Alleles; Animals; Antibodies, Monoclonal; Black or African American; Cell Line, Tumor; Cell Proliferation; Codon; Gene Expression Regulation, Neoplastic; Gene Frequency; Genotype; Hispanic or Latino; Humans; Insulin; Insulin Secretion; Mice; Mice, Inbred BALB C; Pancreatic Neoplasms; Polymorphism, Single Nucleotide; Receptors, Somatostatin; White People

Immunoglobulin locus associates with serum IgG levels and albuminuria. - Herring, Stacy M; Gokul, Nisha; Monita, Monique; Bell, Rebecca; Eric Boerwinkle; Wenderfer, Scott E; Braun, Michael C; Doris, Peter A (J Am Soc Nephrol, 2011)
The interaction between IgG and Fc-γ receptors in glomeruli contributes to the development of several types of proteinuric glomerular disease, but the involvement of immunological mechanisms in hypertensive renal injury is incompletely understood. Here, we investigated serum IgG levels in SHR-A3 rats, which develop hypertensive injury, and compared them with the injury-resistant SHR-B2 line. At 18 weeks old, SHR-A3 rats had serum total IgG levels nearly twice those of SHR-B2 rats, although subclass IgG2b was undetectable in SHR-A3 rats compared with mean levels (± SEM) of 80.7 ± 12.8 mg/dl (18 weeks) and 116.6 ± 19.0 mg/dl (30 weeks) in SHR-B2 rats. In addition, these two strains had significantly different serum levels of IgG1, IgG2a, and IgG2c; differences persisted at 30 weeks for all subclasses except IgG2a. Genetic mapping revealed that a locus on chromosome 6 linked to IgG subclass levels that affected IgG1, IgG2b, and IgG2c but not IgG2a. The mapped haplotype block contains IgH, suggesting regulation of three of four serum IgG subclass levels in cis. Resequencing revealed variation in the sequence of the Fc portion of the IgG heavy chain, which predicts important functional changes. To examine whether there is any relationship between this haplotype block and susceptibility to renal injury, we examined the effect of SHR-A3 and SHR-B2 alleles at this block on albumin excretion in an F2 intercross. Albuminuria doubled with inheritance of SHR-A3 alleles. In summary, allelic variation in IgH or nearby genes may modulate the susceptibility to hypertensive renal injury in SHR-A3 rats.
Keywords: Albuminuria; Animals; Chromosome Mapping; Female; Haplotypes; Hypertension; Immunoglobulin G; Immunoglobulin Heavy Chains; Male; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Rats; Rats, Inbred SHR

The importance of context to the genetic architecture of diabetes-related traits is revealed in a genome-wide scan of a LG/J × SM/J murine model. - Lawson, Heather A; Lee, Arthur; Fawcett, Gloria L; Wang, Bing; Pletscher, L Susan; Maxwell, Taylor J; Ehrich, Thomas H; Kenney-Hunt, Jane P; Wolf, Jason B; Semenkovich, Clay F; Cheverud, James M (Mamm Genome, 2011)
Variations in diabetic phenotypes are caused by complex interactions of genetic effects, environmental factors, and the interplay between the two. We tease apart these complex interactions by examining genome-wide genetic and epigenetic effects on diabetes-related traits among different sex, diet, and sex-by-diet cohorts in a Mus musculus model. We conducted a genome-wide scan for quantitative trait loci that affect serum glucose and insulin levels and response to glucose stress in an F(16) Advanced Intercross Line of the LG/J and SM/J intercross (Wustl:LG,SM-G16). Half of each sibship was fed a high-fat diet and half was fed a relatively low-fat diet. Context-dependent genetic (additive and dominance) and epigenetic (parent-of-origin imprinting) effects were characterized by partitioning animals into sex, diet, and sex-by-diet cohorts. We found that different cohorts often have unique genetic effects at the same loci, and that genetic signals can be masked or erroneously assigned to specific cohorts if they are not considered individually. Our data demonstrate that the effects of genes on complex trait variation are highly context-dependent and that the same genomic sequence can affect traits differently depending on an individual's sex and/or dietary environment. Our results have important implications for studies of complex traits in humans.
Keywords: Animals; Animals, Outbred Strains; Blood Glucose; Diabetes Mellitus, Type 2; Disease Models, Animal; Female; Genome-Wide Association Study; Humans; Hybridization, Genetic; Insulin; Male; Mice; Quantitative Trait Loci

Kinda baboons (Papio kindae) and grayfoot chacma baboons (P. ursinus griseipes) hybridize in the Kafue river valley, Zambia. - Jolly, C J; Burrell, A S; Phillips-Conroy, J E; Bergey, C; Rogers, J (Am J Primatol, 2011)
The ranges of small kinda (Papio kindae) and much larger grayfooted chacma (P. ursinus griseipes) baboons adjoin in the Kafue National Park, Zambia. In a visual survey of baboons at 48 sites in the Kafue River drainage we found that, contrary to previous reports, groups at the species interface near the town of Ngoma are phenotypically diverse and presumably formed by multigenerational hybridization. Mitochondrial and/or Y-chromosome genetic markers from fecal samples (N=164) collected at 29 sites support this conclusion. Groups with phenotypic signs of a history of hybridization also had taxon-specific mitochondria and Y-haplotypes from both parental species. Although the distribution of mitochondrial haplotypes largely mirrored that of external phenotypes, a significant proportion of male specimens from grayfoot as well as hybrid groups carried kinda Y-chromosomes, and kinda Y-chromosomes were involved in all observed cases of mitochondrial/Y-chromosome discordance. These observations are consistent with, though they do not prove, a population history in which the range of chacmas and the hybrid zone have advanced at the expense of the kinda range. They also suggest that, unexpectedly, kinda male×chacma female matings are much more common than the reciprocal cross in the ancestry of hybrids. We suggest that distinctive male kinda behavior and the "juvenile" appearance of kinda baboons of both sexes, perhaps combined with obstetric difficulties of a small kinda female carrying the large offspring of a chacma male, may account for this bias.
Keywords: Animals; Animals, Wild; DNA, Mitochondrial; Female; Genes, Y-Linked; Genetic Markers; Genetic Variation; Haplotypes; Hybridization, Genetic; Male; Papio; Papio ursinus; Phenotype; Sexual Behavior, Animal; Zambia

Loss of Rho GDIα and resistance to tamoxifen via effects on estrogen receptor α. - Barone, Ines; Brusco, Lauren; Gu, Guowei; Selever, Jennifer; Beyer, Amanda; Covington, Kyle R; Tsimelzon, Anna; Wang, Tao; Hilsenbeck, Susan G; Chamness, Gary C; Andò, Sebastiano; Fuqua, Suzanne A W (J Natl Cancer Inst, 2011)
BACKGROUND: Estrogen receptor (ER) α is a successful therapeutic target in breast cancer, but patients eventually develop resistance to antiestrogens such as tamoxifen. METHODS: To identify genes whose expression was associated with the development of tamoxifen resistance and metastasis, we used microarrays to compare gene expression in four primary tumors from tamoxifen-treated patients whose breast cancers did not recur vs five metastatic tumors from patients whose cancers progressed during adjuvant tamoxifen treatment. Because Rho guanine dissociation inhibitor (GDI) α was underexpressed in the tamoxifen-resistant group, we stably transfected ERα-positive MCF-7 breast cancer cells with a plasmid encoding a short hairpin (sh) RNA to silence Rho GDIα expression. We used immunoblots and transcription assays to examine the role of Rho GDIα in ER-related signaling and growth of cells in vitro and as xenografts in treated nude mice (n = 8-9 per group) to examine the effects of Rho GDIα blockade on hormone responsiveness and metastatic behavior. The time to tumor tripling as the time in weeks from randomization to a threefold increase in total tumor volume over baseline was examined in treated mice. The associations of Rho GDIα and MTA2 levels with tamoxifen resistance were examined in microarray data from patients. All statistical tests were two-sided. RESULTS: Rho GDIα was expressed at lower levels in ERα-positive tumors that recurred during tamoxifen treatment than in ERα-positive tamoxifen-sensitive primary tumors. MCF-7 breast cancer cells in which Rho GDIα expression had been silenced were tamoxifen-resistant, had increased Rho GTPase and p21-activated kinase 1 activity, increased phosphorylation of ERα at serine 305, and enhanced tamoxifen-induced ERα transcriptional activity compared with control cells. MCF-7 cells in which Rho GDIα expression was silenced metastasized with high frequency when grown as tumor xenografts. When mice were treated with estrogen or estrogen withdrawal, tripling times for xenografts from cells with Rho GDIα silencing were similar to those from vector-containing control cells; however, tripling times were statistically significantly faster than control when mice were treated with tamoxifen (median tripling time for tumors with Rho GDIα small interfering RNA = 2.34 weeks; for control tumors = not reached, hazard ratio = 4.13, 95% confidence interval = 1.07 to 15.96, P = .040 [adjusted for multiple comparisons, P = .119]). Levels of the metastasis-associated protein MTA2 were also increased upon Rho GDIα silencing, and combined Rho GDIα and MTA2 levels were associated with recurrence in 250 tamoxifen-treated patients. CONCLUSION: Loss of Rho GDIα enhances metastasis and resistance to tamoxifen via effects on both ERα and MTA2 in models of ERα-positive breast cancer and in tumors of tamoxifen-treated patients.
Keywords: Animals; Antineoplastic Agents, Hormonal; Breast Neoplasms; Cell Line, Tumor; Down-Regulation; Drug Resistance, Neoplasm; Enzyme Activation; Estrogen Antagonists; Estrogen Receptor alpha; Female; Gene Expression Regulation, Neoplastic; Gene Silencing; Genome-Wide Association Study; Guanine Nucleotide Dissociation Inhibitors; Histone Deacetylases; Humans; Immunoblotting; Immunohistochemistry; Immunoprecipitation; Mice; Mice, Nude; Neoplasm Recurrence, Local; Odds Ratio; Phenotype; Plasmids; Protein Array Analysis; Random Allocation; Repressor Proteins; Retrospective Studies; rho GTP-Binding Proteins; rho Guanine Nucleotide Dissociation Inhibitor alpha; rho-Specific Guanine Nucleotide Dissociation Inhibitors; RNA, Small Interfering; Secondary Prevention; Selective Estrogen Receptor Modulators; Signal Transduction; Tamoxifen; Time Factors; Transcriptional Activation; Transplantation, Heterologous; Tumor Stem Cell Assay

PDX-1: demonstration of oncogenic properties in pancreatic cancer. - Liu, Shi-He; Patel, Sanjeet; Marie-Claude Gingras; Nemunaitis, John; Zhou, Guisheng; Chen, Changyi; Li, Min; Fisher, William; Richard A Gibbs; Brunicardi, F Charles (Cancer, 2011)
BACKGROUND: Pancreatic-duodenal homeobox 1 (PDX-1) is a transcription factor that regulates embryologic pancreas development and insulin expression in the adult islet; however, it is overexpressed in many types of cancer, including pancreatic cancer. The purpose of this study was to investigate the role of PDX-1 in tumorigenesis in human cells. METHODS: In vitro cell proliferation, invasion, and transformation were performed in human embryonic kidney cell line (HEK 293), pancreatic cancer cell line MIA PaCa2, and human pancreatic ductal epithelial (HPDE) cells transiently or stably expressing PDX-1 or green fluorescent protein (GFP) PDX-1, with or without cotransfection of PDX-1 short hairpin RNA (shRNA). In vivo tumor formation was carried out in severe combined immunodeficiency (SCID) mice with subcutaneous injection of HEK 293 and MIA PaCa2 stably transfected cells. Cell cycle was analyzed by Western blot or immunostaining. Microarray of RNA from pancreatic adenocarcinoma cells with and without PDX-1 shRNA was performed and analyzed. RESULTS: Transient and stable expressing PDX-1 significantly increased cell proliferation and invasion in HEK 293, human pancreatic ductal epithelial (HPDE), and MIA PaCa2 cells versus controls (P < .05), human PDX-1 shRNA reversed these effects. Expression of PDX-1 significantly increased colony formation in HEK 293, HPDE, and MIA PaCa2 cells versus controls in vitro (P < .05). PDX-1 promoted HEK 293 and MIA PaCa2 tumor formation in SCID mice as compared with that of control (P < .05). PDX-1 overexpression disrupted cell cycles proteins. PDX-1 expression was confirmed by Western blot and tracked by viewing of GFP-PDX-1 expression. Microarray data support an oncogenic role of PDX-1 in pancreas cancer cells. CONCLUSIONS: PDX-1 induced increased cell proliferation, invasion, and colony formation in vitro, and resulted in markedly increased HEK 293 and MIA PaCa2 tumor formation in SCID mice. These data suggest that PDX-1 is a potential oncogene that regulates tumorigenesis.
Keywords: Animals; Cell Cycle; Cell Line, Tumor; Cell Proliferation; HEK293 Cells; Homeodomain Proteins; Humans; Mice; Mice, SCID; Neoplasm Transplantation; Oncogenes; Pancreatic Neoplasms; RNA, Small Interfering; Trans-Activators; Transfection; Up-Regulation

A preliminary report on the feeding of cynomolgus monkeys (Macaca fascicularis) with a high-sugar high-fat diet for 33 weeks. - Mubiru, James N; Garcia-Forey, Magdalena; Higgins, Paul B; Hemmat, Peggah; Cavazos, Nicole E; Dick, Edward J; Owston, Michael A; Bauer, Cassondra A; Shade, Robert E; Comuzzie, Anthony G; Jeffrey Rogers (J Med Primatol, 2011)
BACKGROUND: The metabolic syndrome is common in populations exposed to a typical Western diet. There is a lack of an animal model that mimics this condition. METHODS: We fed 15 cynomolgus monkeys ad libitum a high-sugar high-fat (HSHF) diet for 33 weeks. Body weight, body composition, serum lipids, and insulin were measured at baseline and at 33 weeks. RESULTS: The animals tolerated the HSHF diet very well. In the intervention group, total serum cholesterol and low-density lipoprotein cholesterol were 3- and 5-fold higher, respectively, at 33 weeks as compared with their baseline levels. Serum high-density lipoprotein cholesterol and triglycerides were not significantly affected. Dual-energy X-ray absorptiometry (DXA) analysis of the intervention group indicated that the trunk fat mass increased by 187% during this period. CONCLUSIONS: Cynomolgus monkeys should be a useful model for investigating the interactions of diet and other factors such as genetics in the development of the metabolic syndrome.
Keywords: Absorptiometry, Photon; Animals; Biomarkers; Blood Glucose; Body Composition; Body Weight; Cholesterol; Dietary Carbohydrates; Dietary Fats; Energy Metabolism; Insulin; Macaca fascicularis; Male; Metabolic Syndrome; Models, Animal; Triglycerides

Transcriptomic analysis supports similar functional roles for the two thymuses of the tammar wallaby. - Wong, Emily S W; Papenfuss, Anthony T; Heger, Andreas; Hsu, Arthur L; Ponting, Chris P; Miller, Robert D; Fenelon, Jane C; Renfree, Marilyn B; Richard A Gibbs; Belov, Katherine (BMC Genomics, 2011)
BACKGROUND: The thymus plays a critical role in the development and maturation of T-cells. Humans have a single thoracic thymus and presence of a second thymus is considered an anomaly. However, many vertebrates have multiple thymuses. The tammar wallaby has two thymuses: a thoracic thymus (typically found in all mammals) and a dominant cervical thymus. Researchers have known about the presence of the two wallaby thymuses since the 1800s, but no genome-wide research has been carried out into possible functional differences between the two thymic tissues. Here, we used pyrosequencing to compare the transcriptomes of a cervical and thoracic thymus from a single 178 day old tammar wallaby. RESULTS: We show that both the tammar thoracic and the cervical thymuses displayed gene expression profiles consistent with roles in T-cell development. Both thymuses expressed genes that mediate distinct phases of T-cells differentiation, including the initial commitment of blood stem cells to the T-lineage, the generation of T-cell receptor diversity and development of thymic epithelial cells. Crucial immune genes, such as chemokines were also present. Comparable patterns of expression of non-coding RNAs were seen. 67 genes differentially expressed between the two thymuses were detected, and the possible significance of these results are discussed. CONCLUSION: This is the first study comparing the transcriptomes of two thymuses from a single individual. Our finding supports that both thymuses are functionally equivalent and drive T-cell development. These results are an important first step in the understanding of the genetic processes that govern marsupial immunity, and also allow us to begin to trace the evolution of the mammalian immune system.
Keywords: Animals; Antigens; Gene Expression Profiling; Macropodidae; Organ Specificity; RNA, Untranslated; Thorax; Thymus Gland

TTC21B contributes both causal and modifying alleles across the ciliopathy spectrum. - Davis, Erica E; Zhang, Qi; Liu, Qin; Diplas, Bill H; Davey, Lisa M; Hartley, Jane; Stoetzel, Corinne; Szymanska, Katarzyna; Ramaswami, Gokul; Logan, Clare V; Donna M Muzny; Young, Alice C; et al. (Nat Genet, 2011)
Ciliary dysfunction leads to a broad range of overlapping phenotypes, collectively termed ciliopathies. This grouping is underscored by genetic overlap, where causal genes can also contribute modifier alleles to clinically distinct disorders. Here we show that mutations in TTC21B, which encodes the retrograde intraflagellar transport protein IFT139, cause both isolated nephronophthisis and syndromic Jeune asphyxiating thoracic dystrophy. Moreover, although resequencing of TTC21B in a large, clinically diverse ciliopathy cohort and matched controls showed a similar frequency of rare changes, in vivo and in vitro evaluations showed a significant enrichment of pathogenic alleles in cases (P < 0.003), suggesting that TTC21B contributes pathogenic alleles to ∼5% of ciliopathy cases. Our data illustrate how genetic lesions can be both causally associated with diverse ciliopathies and interact in trans with other disease-causing genes and highlight how saturated resequencing followed by functional analysis of all variants informs the genetic architecture of inherited disorders.
Keywords: Adaptor Proteins, Signal Transducing; Alleles; Animals; Ciliary Motility Disorders; Genetic Variation; Humans; Mice; Mutation; Pedigree; Photoreceptor Cells; Zebrafish

Amygdalar and hippocampal substrates of anxious temperament differ in their heritability. - Oler, Jonathan A; Fox, Andrew S; Shelton, Steven E; Jeffrey Rogers; Dyer, Thomas D; Davidson, Richard J; Shelledy, Wendy; Oakes, Terrence R; Blangero, John; Kalin, Ned H (Nature, 2010)
Anxious temperament (AT) in human and non-human primates is a trait-like phenotype evident early in life that is characterized by increased behavioural and physiological reactivity to mildly threatening stimuli. Studies in children demonstrate that AT is an important risk factor for the later development of anxiety disorders, depression and comorbid substance abuse. Despite its importance as an early predictor of psychopathology, little is known about the factors that predispose vulnerable children to develop AT and the brain systems that underlie its expression. To characterize the neural circuitry associated with AT and the extent to which the function of this circuit is heritable, we studied a large sample of rhesus monkeys phenotyped for AT. Using 238 young monkeys from a multigenerational single-family pedigree, we simultaneously assessed brain metabolic activity and AT while monkeys were exposed to the relevant ethological condition that elicits the phenotype. High-resolution (18)F-labelled deoxyglucose positron-emission tomography (FDG-PET) was selected as the imaging modality because it provides semi-quantitative indices of absolute glucose metabolic rate, allows for simultaneous measurement of behaviour and brain activity, and has a time course suited for assessing temperament-associated sustained brain responses. Here we demonstrate that the central nucleus region of the amygdala and the anterior hippocampus are key components of the neural circuit predictive of AT. We also show significant heritability of the AT phenotype by using quantitative genetic analysis. Additionally, using voxelwise analyses, we reveal significant heritability of metabolic activity in AT-associated hippocampal regions. However, activity in the amygdala region predictive of AT is not significantly heritable. Furthermore, the heritabilities of the hippocampal and amygdala regions significantly differ from each other. Even though these structures are closely linked, the results suggest differential influences of genes and environment on how these brain regions mediate AT and the ongoing risk of developing anxiety and depression.
Keywords: Amygdala; Animals; Anxiety; Depression; Female; Freezing Reaction, Cataleptic; Genetic Predisposition to Disease; Glucose; Heredity; Hippocampus; Macaca mulatta; Male; Models, Animal; Neural Pathways; Pedigree; Phenotype; Positron-Emission Tomography; Stress, Psychological; Temperament; Temporal Lobe; Vocalization, Animal

Calpain-10 is a component of the obesity-related quantitative trait locus Adip1. - Cheverud, James M; Fawcett, Gloria L; Jarvis, Joseph P; Norgard, Elizabeth A; Pavlicev, Mihaela; Pletscher, L Susan; Polonsky, Kenneth S; Ye, Honggang; Bell, Graeme I; Semenkovich, Clay F (J Lipid Res, 2010)
We previously mapped Adip1, an obesity quantitative trait locus (QTL), to the central portion of murine chromosome 1 containing the calpain-10 (Capn10) gene. Human studies have associated calpain-10 (CAPN10) variants with type 2 diabetes and various metabolic traits. We performed a quantitative hybrid complementation test (QHCT) to determine whether differences attributed to Adip1 are the result of variant Capn10 alleles in LG/J and SM/J mice. We crossed LG/J and SM/J to wild-type (C57BL/6J) and Capn10 knockout (Capn10(-/-)) mice to form four F(1) hybrid groups: LG/J by wild-type, LG/J by Capn10(-/-), SM/J by wild-type, and SM/J by Capn10(-/-). We performed a two-way ANOVA with the experimental strain, tester strain, and their interaction as the factors. Significant interaction indicates a quantitative failure to complement. We found failure to complement for fat, organ, and body weights, and leptin, female free fatty acid, and triglyceride levels. Capn10(-/-) resulted in heavier weights and higher serum levels in LG/J crosses but not in SM/J crosses. For glucose tolerance and insulin response tests, the Capn10(-/-) allele resulted in lower glucose levels in crosses with SM/J but had no effect in the LG/J crosses. Differences between the LG/J and SM/J Capn10 alleles are the likely source of some of the QTL effects mapped to Adip1 in the LG/J-by-SM/J cross. Capn10 plays an important role in regulating obesity and diabetes in mice.
Keywords: Alleles; Animals; Calpain; Female; Gene Knockout Techniques; Genetic Complementation Test; Genetic Variation; Hybridization, Genetic; Male; Mice; Obesity; Quantitative Trait Loci

A full-length cDNA resource for the pea aphid, Acyrthosiphon pisum. - Shigenobu, S; Stephen Richards; Cree, A G; Morioka, M; Fukatsu, T; Kudo, T; Miyagishima, S; Richard A Gibbs; Stern, D L; Nakabachi, A (Insect Mol Biol, 2010)
Large collections of full-length cDNAs are important resources for genome annotation and functional genomics. We report the creation of a collection of 50 599 full-length cDNA clones from the pea aphid, Acyrthosiphon pisum. Sequencing from 5' and 3' ends of the clones generated 97 828 high-quality expressed sequence tags, representing approximately 9000 genes. These sequences were imported to AphidBase and are shown to play crucial roles in both automatic gene prediction and manual annotation. Our detailed analyses demonstrated that the full-length cDNAs can further improve gene models and can even identify novel genes that are not included in the current version of the official gene set. This full-length cDNA collection can be utilized for a wide variety of functional studies, serving as a community resource for the study of the functional genomics of the pea aphid.
Keywords: 3' Untranslated Regions; 5' Untranslated Regions; Animals; Aphids; Base Sequence; DNA Primers; DNA, Complementary; Expressed Sequence Tags; Gene Library; Genome, Insect; Host-Pathogen Interactions; Models, Genetic; Pisum sativum

Functional and evolutionary insights from the genomes of three parasitoid Nasonia species. - Werren, John H; Stephen Richards; Desjardins, Christopher A; Niehuis, Oliver; Gadau, Jürgen; Colbourne, John K; Werren, John H; Stephen Richards; Desjardins, Christopher A; Niehuis, Oliver; Gadau, Jürgen; Colbourne, John K; et al. (Science, 2010)
We report here genome sequences and comparative analyses of three closely related parasitoid wasps: Nasonia vitripennis, N. giraulti, and N. longicornis. Parasitoids are important regulators of arthropod populations, including major agricultural pests and disease vectors, and Nasonia is an emerging genetic model, particularly for evolutionary and developmental genetics. Key findings include the identification of a functional DNA methylation tool kit; hymenopteran-specific genes including diverse venoms; lateral gene transfers among Pox viruses, Wolbachia, and Nasonia; and the rapid evolution of genes involved in nuclear-mitochondrial interactions that are implicated in speciation. Newly developed genome resources advance Nasonia for genetic research, accelerate mapping and cloning of quantitative trait loci, and will ultimately provide tools and knowledge for further increasing the utility of parasitoids as pest insect-control agents.
Keywords: Animals; Arthropods; Biological Evolution; DNA Methylation; DNA Transposable Elements; Female; Gene Transfer, Horizontal; Genes, Insect; Genetic Speciation; Genetic Variation; Genome, Insect; Host-Parasite Interactions; Insect Proteins; Insect Viruses; Insecta; Male; Molecular Sequence Data; Quantitative Trait Loci; Recombination, Genetic; Sequence Analysis, DNA; Wasp Venoms; Wasps; Wolbachia

Genetic and environmental contributions to variation in baboon cranial morphology. - Roseman, Charles C; Willmore, Katherine E; Jeffrey Rogers; Hildebolt, Charles; Sadler, Brooke E; Richtsmeier, Joan T; Cheverud, James M (Am J Phys Anthropol, 2010)
The development, function, and integration of morphological characteristics are all hypothesized to influence the utility of traits for phylogenetic reconstruction by affecting the way in which morphological characteristics evolve. We use a baboon model to test the hypotheses about phenotypic and quantitative genetic variation of traits in the cranium that bear on a phenotype's propensity to evolve. We test the hypotheses that: 1) individual traits in different functionally and developmentally defined regions of the cranium are differentially environmentally, genetically, and phenotypically variable; 2) genetic covariance with other traits constrains traits in one region of the cranium more than those in others; 3) and regions of the cranium subject to different levels of mechanical strain differ in the magnitude of variation in individual traits. We find that the levels of environmental and genetic variation in individual traits are randomly distributed across regions of the cranium rather than being structured by developmental origin or degree of exposure to strain. Individual traits in the cranial vault tend to be more constrained by covariance with other traits than those in other regions. Traits in regions subject to high degrees of strain during mastication are not any more variable at any level than other traits. If these results are generalizable to other populations, they indicate that there is no reason to suppose that individual traits from any one part of the cranium are intrinsically less useful for reconstructing patterns of evolution than those from any other part.
Keywords: Analysis of Variance; Animals; Anthropology, Physical; Cephalometry; Environment; Genetic Variation; Models, Genetic; Papio; Phenotype; Phylogeny; Skull; Species Specificity

On the genetic architecture of cortical folding and brain volume in primates. - Jeffrey Rogers; Kochunov, Peter; Zilles, Karl; Shelledy, Wendy; Lancaster, Jack; Thompson, Paul; Duggirala, Ravindranath; Blangero, John; Fox, Peter T; Glahn, David C (Neuroimage, 2010)
Understanding the evolutionary forces that produced the human brain is a central problem in neuroscience and human biology. Comparisons across primate species show that both brain volume and gyrification (the degree of folding in the cerebral cortex) have progressively increased during primate evolution and there is a strong positive correlation between these two traits across primate species. The human brain is exceptional among primates in both total volume and gyrification, and therefore understanding the genetic mechanisms influencing variation in these traits will improve our understanding of a landmark feature of our species. Here we show that individual variation in gyrification is significantly heritable in both humans and an Old World monkey (baboons, Papio hamadryas). Furthermore, contrary to expectations based on the positive phenotypic correlation across species, the genetic correlation between cerebral volume and gyrification within both humans and baboons is estimated as negative. These results suggest that the positive relationship between cerebral volume and cortical folding across species cannot be explained by one set of selective pressures or genetic changes. Our data suggest that one set of selective pressures favored the progressive increase in brain volume documented in the primate fossil record, and that a second independent selective process, possibly related to parturition and neonatal brain size, may have favored brains with progressively greater cortical folding. Without a second separate selective pressure, natural selection favoring increased brain volume would be expected to produce less folded, more lissencephalic brains. These results provide initial evidence for the heritability of gyrification, and possibly a new perspective on the evolutionary mechanisms underlying long-term changes in the nonhuman primate and human brain.
Keywords: Animals; Biological Evolution; Cerebral Cortex; Female; Humans; Image Processing, Computer-Assisted; Magnetic Resonance Imaging; Male; Papio; Primates; Species Specificity

Genetic, epigenetic, and gene-by-diet interaction effects underlie variation in serum lipids in a LG/JxSM/J murine model. - Lawson, Heather A; Zelle, Kathleen M; Fawcett, Gloria L; Wang, Bing; Pletscher, L Susan; Maxwell, Taylor J; Ehrich, Thomas H; Kenney-Hunt, Jane P; Wolf, Jason B; Semenkovich, Clay F; Cheverud, James M (J Lipid Res, 2010)
Variation in serum cholesterol, free-fatty acids, and triglycerides is associated with cardiovascular disease (CVD) risk factors. There is great interest in characterizing the underlying genetic architecture of these risk factors, because they vary greatly within and among human populations and between the sexes. We present results of a genome-wide scan for quantitative trait loci (QTL) affecting serum cholesterol, free-fatty acids, and triglycerides in an F(16) advanced intercross line of LG/J and SM/J (Wustl:LG,SM-G16). Half of the population was fed a high-fat diet and half was fed a relatively low-fat diet. Context-dependent genetic (additive and dominance) and epigenetic (imprinting) effects were characterized by partitioning animals into sex, diet, and sex-by-diet cohorts. Here we examine genetic, environmental, and genetic-by-environmental interactions of QTL overlapping previously identified loci associated with CVD risk factors, and we add to the serum lipid QTL landscape by identifying new loci.
Keywords: Animals; Cardiovascular Diseases; Crosses, Genetic; Diet; Epigenesis, Genetic; Genetic Variation; Humans; Lipids; Mice; Models, Animal; Quantitative Trait Loci

Genetics: Decoding a national treasure. - Worley, Kim C; Richard A Gibbs (Nature, 2010)
Keywords: Animals; Contig Mapping; Genetics, Population; Genome; Genomics; Humans; Sequence Analysis, DNA; Ursidae

Genetics of primary cerebral gyrification: Heritability of length, depth and area of primary sulci in an extended pedigree of Papio baboons. - Kochunov, P; Glahn, D C; Fox, P T; Lancaster, J L; Saleem, K; Shelledy, W; Zilles, K; Thompson, P M; Coulon, O; Mangin, J F; Blangero, J; Rogers, J (Neuroimage, 2010)
Genetic control over morphological variability of primary sulci and gyri is of great interest in the evolutionary, developmental and clinical neurosciences. Primary structures emerge early in development and their morphology is thought to be related to neuronal differentiation, development of functional connections and cortical lateralization. We measured the proportional contributions of genetics and environment to regional variability, testing two theories regarding regional modulation of genetic influences by ontogenic and phenotypic factors. Our measures were surface area, and average length and depth of eleven primary cortical sulci from high-resolution MR images in 180 pedigreed baboons. Average heritability values for sulcal area, depth and length (h(2)(Area)=.38+/-.22; h(2)(Depth)=.42+/-.23; h(2)(Length)=.34+/-.22) indicated that regional cortical anatomy is under genetic control. The regional pattern of genetic contributions was complex and, contrary to previously proposed theories, did not depend upon sulcal depth, or upon the sequence in which structures appear during development. Our results imply that heritability of sulcal phenotypes may be regionally modulated by arcuate U-fiber systems. However, further research is necessary to unravel the complexity of genetic contributions to cortical morphology.
Keywords: Animals; Brain; Female; Image Processing, Computer-Assisted; Magnetic Resonance Imaging; Male; Papio; Quantitative Trait, Heritable

Genome sequence of the pea aphid Acyrthosiphon pisum. (PLoS Biol, 2010)
Aphids are important agricultural pests and also biological models for studies of insect-plant interactions, symbiosis, virus vectoring, and the developmental causes of extreme phenotypic plasticity. Here we present the 464 Mb draft genome assembly of the pea aphid Acyrthosiphon pisum. This first published whole genome sequence of a basal hemimetabolous insect provides an outgroup to the multiple published genomes of holometabolous insects. Pea aphids are host-plant specialists, they can reproduce both sexually and asexually, and they have coevolved with an obligate bacterial symbiont. Here we highlight findings from whole genome analysis that may be related to these unusual biological features. These findings include discovery of extensive gene duplication in more than 2000 gene families as well as loss of evolutionarily conserved genes. Gene family expansions relative to other published genomes include genes involved in chromatin modification, miRNA synthesis, and sugar transport. Gene losses include genes central to the IMD immune pathway, selenoprotein utilization, purine salvage, and the entire urea cycle. The pea aphid genome reveals that only a limited number of genes have been acquired from bacteria; thus the reduced gene count of Buchnera does not reflect gene transfer to the host genome. The inventory of metabolic genes in the pea aphid genome suggests that there is extensive metabolite exchange between the aphid and Buchnera, including sharing of amino acid biosynthesis between the aphid and Buchnera. The pea aphid genome provides a foundation for post-genomic studies of fundamental biological questions and applied agricultural problems.
Keywords: Animals; Aphids; Buchnera; Gene Transfer, Horizontal; Genome, Insect; Symbiosis

Identification and removal of colanic acid from plasmid DNA preparations: implications for gene therapy. - Firozi, P; Zhang, W; Chen, L; Quiocho, F A; Worley, K C; Templeton, N S (Gene Ther, 2010)
Polysaccharide contaminants in plasmid DNA, including current good manufacturing practices (cGMP) clinical preparations, must be removed to provide the greatest safety and efficacy for use in gene therapy and other clinical applications. We developed assays and methods for the detection and removal of these polysaccharides, our Super Clean DNA (SC-DNA) process, and have shown that these contaminants in plasmid DNA preparations are responsible for toxicity observed post-injection in animals. Furthermore, these contaminants limit the efficacy of low and high doses of plasmid DNA administered by numerous delivery routes. In particular, colanic acid (CA) that is mainly long-chained, branched and has high molecular weight (MW) is most refractory when complexed to cationic delivery vehicles and injected intravenously (IV). Because CA is often extremely large and tightly intertwined with DNA, it must be degraded, in order, to be effectively removed. We have produced a recombinant, truncated colanic acid degrading enzyme (CAE) that successfully accomplishes this task. Initially, we isolated a newly identified CAE from a bacteriophage that required truncation for proper folding while retaining its full enzymatic activity during production. Any plasmid DNA preparation can be digested with CAE and further purified, providing a critical advance to non-viral gene therapy.
Keywords: Animals; Base Sequence; Biotechnology; Enzymes; Fluoresceins; Fucose; Genetic Therapy; Humans; Mice; Mice, Inbred BALB C; Mice, SCID; Molecular Sequence Data; Plasmids; Polysaccharides; Recombinant Proteins; Toxicity Tests, Acute; Uronic Acids

Identification of a QTL for adipocyte volume and of shared genetic effects with aspartate aminotransferase. - Bose, Tanushree; Voruganti, V Saroja; Tejero, M Elizabeth; Proffit, J Michael; Cox, Laura A; VandeBerg, John L; Mahaney, Michael C; Jeffrey Rogers; Freeland-Graves, Jeanne H; Cole, Shelley A; Comuzzie, Anthony G (Biochem Genet, 2010)
Plasma levels of aspartate aminotransferase (AST), a liver enzyme, are elevated in patients with visceral obesity. This study examined whether adipocyte volume is under the influence of genetic factors and evaluated its genetic correlations with AST. Fasting plasma levels of 344 pedigreed baboons from the Southwest National Primate Research Center in San Antonio, TX, USA, were assayed for AST. Adipocyte volume was measured using biopsies of omental adipose tissue. Adipocyte volume, body weight, and plasma AST were heritable. Genetic correlations between the measured adiposity-related phenotypes and AST were significant. A quantitative trait locus (LOD score 3.2) for adipocyte volume was identified on the baboon homolog of human chromosome 6 near marker D6S1028. These results suggest that omental adipocyte volume is under genetic regulation and that shared genetic factors influence adiposity-associated traits and AST.
Keywords: Adipocytes; Animals; Aspartate Aminotransferases; Biomarkers; Cell Size; Female; Genomics; Humans; Male; Obesity; Papio; Quantitative Trait Loci

The importance of being cis: evolution of orthologous fish and mammalian enhancer activity. - Ritter, Deborah I; Li, Qiang; Kostka, Dennis; Pollard, Katherine S; Guo, Su; Chuang, Jeffrey H (Mol Biol Evol, 2010)
Conserved noncoding elements (CNEs) in vertebrate genomes often act as developmental enhancers, but a critical issue is how well orthologous CNE sequences retain the same activity in their respective species, a characteristic important for generalization of model organism studies. To quantify how well CNE enhancer activity has been preserved, we compared the anatomy-specific activities of 41 zebra fish CNEs in zebra fish embryos with the activities of orthologous human CNEs in mouse embryos. We found that 13/41 (∼30%) of the orthologous CNE pairs exhibit conserved positive activity in zebra fish and mouse. Conserved positive activity is only weakly associated with either sequence conservation or the absence of bases undergoing accelerated evolution. A stronger effect is that disparate activity is associated with transcription factor binding site divergence. To distinguish the contributions of cis- versus trans-regulatory changes, we analyzed 13 CNEs in a three-way experimental comparison: human CNE tested in zebra fish, human CNE tested in mouse, and orthologous zebra fish CNE tested in zebra fish. Both cis- and trans-changes affect a significant fraction of CNEs, although human and zebra fish sequences exhibit disparate activity in zebra fish (indicating cis regulatory changes) twice as often as human sequences show disparate activity when tested in mouse and zebra fish (indicating trans regulatory changes). In all four cases where the zebra fish and human CNE display a similar expression pattern in zebra fish, the human CNE also displays a similar expression pattern in mouse. This suggests that the endogenous enhancer activity of ∼30% of human CNEs can be determined from experiments in zebra fish alone, and to identify these CNEs, both the zebra fish and the human sequences should be tested.
Keywords: Animals; Conserved Sequence; DNA, Intergenic; Enhancer Elements, Genetic; Evolution, Molecular; Gene Expression Profiling; Gene Regulatory Networks; Humans; Mice; ROC Curve; Transcription Factors; Zebrafish

Mutational analysis of the latency-associated nuclear antigen DNA-binding domain of Kaposi's sarcoma-associated herpesvirus reveals structural conservation among gammaherpesvirus origin-binding proteins. - Han, Soo-Jin; Jianhong Hu; Pierce, Brian; Weng, Zhiping; Renne, Rolf (J Gen Virol, 2010)
The latency-associated nuclear antigen (LANA) of Kaposi's sarcoma-associated herpesvirus functions as an origin-binding protein (OBP) and transcriptional regulator. LANA binds the terminal repeats via the C-terminal DNA-binding domain (DBD) to support latent DNA replication. To date, the structure of LANA has not been solved. Sequence alignments among OBPs of gammaherpesviruses have revealed that the C terminus of LANA is structurally related to EBNA1, the OBP of Epstein-Barr virus. Based on secondary structure predictions for LANA(DBD) and published structures of EBNA1(DBD), this study used bioinformatics tools to model a putative structure for LANA(DBD) bound to DNA. To validate the predicted model, 38 mutants targeting the most conserved motifs, namely three alpha-helices and a conserved proline loop, were constructed and functionally tested. In agreement with data for EBNA1, residues in helices 1 and 2 mainly contributed to sequence-specific DNA binding and replication activity, whilst mutations in helix 3 affected replication activity and multimer formation. Additionally, several mutants were isolated with discordant phenotypes, which may aid further studies into LANA function. In summary, these data suggest that the secondary and tertiary structures of LANA and EBNA1 DBDs are conserved and are critical for (i) sequence-specific DNA binding, (ii) multimer formation, (iii) LANA-dependent transcriptional repression, and (iv) DNA replication.
Keywords: Amino Acid Sequence; Amino Acid Substitution; Animals; Antigens, Viral; Binding Sites; Cell Line; Chlorocebus aethiops; Conserved Sequence; DNA Replication; DNA, Viral; Electrophoretic Mobility Shift Assay; Epstein-Barr Virus Nuclear Antigens; Evolution, Molecular; Gammaherpesvirinae; Herpesvirus 8, Human; Humans; Models, Molecular; Molecular Sequence Data; Mutant Proteins; Mutation; Nuclear Proteins; Protein Multimerization; Protein Structure, Quaternary; Protein Structure, Tertiary; Sequence Homology, Amino Acid; Structural Homology, Protein

Pretranscriptional regulation of Tgf-beta1 by PI polyamide prevents scarring and accelerates wound healing of the cornea after exposure to alkali. - Chen, Min; Matsuda, Hiroyuki; Wang, Linghua; Watanabe, Takayoshi; Kimura, Makoto T; Igarashi, Jun; Wang, Xiaofei; Sakimoto, Tohru; Fukuda, Noboru; Sawa, Mitsuru; Nagase, Hiroki (Mol Ther, 2010)
Corneal alkali burns are a serious clinical problem that often leads to permanent visual impairment. In this process, transforming growth factor (Tgf)-beta1 is upregulated and involved in the response to corneal injury and the process of corneal stromal scarring. To develop an efficient compound to inhibit Tgf-beta1 in the cornea, we designed GB1201, a pyrrole-imidazole (PI) polyamide targeting rat Tgf-beta1 gene promoter to the activator protein-1 (AP-1) binding site. GB1201 showed a high binding affinity to the target DNA sequence in the gel mobility shift and Biacore assays. GB1201 significantly inhibited the rat Tgf-beta1 gene promoter activity in HEK (human embryonic kidney) 293 cells in a concentration-dependent manner. Topically administrated GB1201 was distributed immediately to the nuclei of all cell layers of the cornea and remained for 24 hours. A corneal alkali burn model in rats was used to evaluate the therapeutic efficacy of GB1201. GB1201 suppressed the upregulation of Tgf-beta1 in the burned cornea, both in the mRNA and protein levels. Moreover, daily treatment with GB1201 for a week significantly improved the corneal tissue wound healing, reduced corneal stromal scarring, and prevented corneal haze formation. Our data suggest that PI polyamide may open new opportunities for therapeutic intervention in the treatment of chemically burned corneas.
Keywords: Animals; Binding Sites; Cicatrix; Cornea; Dose-Response Relationship, Drug; Gene Expression Regulation; Humans; Imidazoles; Nylons; Promoter Regions, Genetic; Pyrroles; Rats; RNA, Messenger; Transforming Growth Factor beta1; Wound Healing

Rapid identification of heterozygous mutations in Drosophila melanogaster using genomic capture sequencing. - Wang, Hui; Chattopadhyay, Abanti; Li, Zhe; Daines, Bryce; Yumei Li; Gao, Chunxu; Richard A Gibbs; Zhang, Kun; Rui Chen (Genome Res, 2010)
One of the key advantages of using Drosophila melanogaster as a genetic model organism is the ability to conduct saturation mutagenesis screens to identify genes and pathways underlying a given phenotype. Despite the large number of genetic tools developed to facilitate downstream cloning of mutations obtained from such screens, the current procedure remains labor intensive, time consuming, and costly. To address this issue, we designed an efficient strategy for rapid identification of heterozygous mutations in the fly genome by combining rough genetic mapping, targeted DNA capture, and second generation sequencing technology. We first tested this method on heterozygous flies carrying either a previously characterized dac(5) or sens(E2) mutation. Targeted amplification of genomic regions near these two loci was used to enrich DNA for sequencing, and both point mutations were successfully identified. When this method was applied to uncharacterized twr mutant flies, the underlying mutation was identified as a single-base mutation in the gene Spase18-21. This targeted-genome-sequencing method reduces time and effort required for mutation cloning by up to 80% compared with the current approach and lowers the cost to <$1000 for each mutant. Introduction of this and other sequencing-based methods for mutation cloning will enable broader usage of forward genetics screens and have significant impacts in the field of model organisms such as Drosophila.
Keywords: Animals; Animals, Genetically Modified; Base Sequence; Cost-Benefit Analysis; DNA Mutational Analysis; Drosophila melanogaster; Genetic Carrier Screening; Genome, Insect; Heterozygote; Models, Biological; Molecular Sequence Data; Point Mutation; Sequence Homology, Nucleic Acid; Time Factors

A systematic approach to identify functional motifs within vertebrate developmental enhancers. - Li, Qiang; Ritter, Deborah; Yang, Nan; Dong, Zhiqiang; Li, Hao; Chuang, Jeffrey H; Guo, Su (Dev Biol, 2010)
Uncovering the cis-regulatory logic of developmental enhancers is critical to understanding the role of non-coding DNA in development. However, it is cumbersome to identify functional motifs within enhancers, and thus few vertebrate enhancers have their core functional motifs revealed. Here we report a combined experimental and computational approach for discovering regulatory motifs in developmental enhancers. Making use of the zebrafish gene expression database, we computationally identified conserved non-coding elements (CNEs) likely to have a desired tissue-specificity based on the expression of nearby genes. Through a high throughput and robust enhancer assay, we tested the activity of approximately 100 such CNEs and efficiently uncovered developmental enhancers with desired spatial and temporal expression patterns in the zebrafish brain. Application of de novo motif prediction algorithms on a group of forebrain enhancers identified five top-ranked motifs, all of which were experimentally validated as critical for forebrain enhancer activity. These results demonstrate a systematic approach to discover important regulatory motifs in vertebrate developmental enhancers. Moreover, this dataset provides a useful resource for further dissection of vertebrate brain development and function.
Keywords: Animals; Base Sequence; Brain; Computational Biology; Conserved Sequence; Databases, Genetic; DNA, Intergenic; Enhancer Elements, Genetic; Gene Expression Regulation, Developmental; Molecular Sequence Data; Mutation; Organ Specificity; Reproducibility of Results; Time Factors; Zebrafish

Bos taurus genome assembly. - Liu, Yue; Xiang Qin; Song, Xing-Zhi Henry; Jiang, Huaiyang; Shen, Yufeng; Durbin, K James; Lien, Sigbjørn; Kent, Matthew Peter; Sodeland, Marte; Ren, Yanru; Zhang, Lan; Sodergren, Erica; et al. (BMC Genomics, 2009)
BACKGROUND: We present here the assembly of the bovine genome. The assembly method combines the BAC plus WGS local assembly used for the rat and sea urchin with the whole genome shotgun (WGS) only assembly used for many other animal genomes including the rhesus macaque. RESULTS: The assembly process consisted of multiple phases: First, BACs were assembled with BAC generated sequence, then subsequently in combination with the individual overlapping WGS reads. Different assembly parameters were tested to separately optimize the performance for each BAC assembly of the BAC and WGS reads. In parallel, a second assembly was produced using only the WGS sequences and a global whole genome assembly method. The two assemblies were combined to create a more complete genome representation that retained the high quality BAC-based local assembly information, but with gaps between BACs filled in with the WGS-only assembly. Finally, the entire assembly was placed on chromosomes using the available map information.Over 90% of the assembly is now placed on chromosomes. The estimated genome size is 2.87 Gb which represents a high degree of completeness, with 95% of the available EST sequences found in assembled contigs. The quality of the assembly was evaluated by comparison to 73 finished BACs, where the draft assembly covers between 92.5 and 100% (average 98.5%) of the finished BACs. The assembly contigs and scaffolds align linearly to the finished BACs, suggesting that misassemblies are rare. Genotyping and genetic mapping of 17,482 SNPs revealed that more than 99.2% were correctly positioned within the Btau_4.0 assembly, confirming the accuracy of the assembly. CONCLUSION: The biological analysis of this bovine genome assembly is being published, and the sequence data is available to support future bovine research.
Keywords: Animals; Cattle; Chromosome Mapping; Chromosomes, Artificial, Bacterial; Genetic Markers; Genome; Genomics; Sequence Analysis, DNA

A common allele in RPGRIP1L is a modifier of retinal degeneration in ciliopathies. - Khanna, Hemant; Davis, Erica E; Murga-Zamalloa, Carlos A; Estrada-Cuzcano, Alejandro; Lopez, Irma; den Hollander, Anneke I; Zonneveld, Marijke N; Othman, Mohammad I; Waseem, Naushin; Chakarova, Christina F; Maubaret, Cecilia; Diaz-Font, Anna; et al. (Nat Genet, 2009)
Despite rapid advances in the identification of genes involved in disease, the predictive power of the genotype remains limited, in part owing to poorly understood effects of second-site modifiers. Here we demonstrate that a polymorphic coding variant of RPGRIP1L (retinitis pigmentosa GTPase regulator-interacting protein-1 like), a ciliary gene mutated in Meckel-Gruber (MKS) and Joubert (JBTS) syndromes, is associated with the development of retinal degeneration in individuals with ciliopathies caused by mutations in other genes. As part of our resequencing efforts of the ciliary proteome, we identified several putative loss-of-function RPGRIP1L mutations, including one common variant, A229T. Multiple genetic lines of evidence showed this allele to be associated with photoreceptor loss in ciliopathies. Moreover, we show that RPGRIP1L interacts biochemically with RPGR, loss of which causes retinal degeneration, and that the Thr229-encoded protein significantly compromises this interaction. Our data represent an example of modification of a discrete phenotype of syndromic disease and highlight the importance of a multifaceted approach for the discovery of modifier alleles of intermediate frequency and effect.
Keywords: Adaptor Proteins, Signal Transducing; Alleles; Animals; Bardet-Biedl Syndrome; Ciliary Body; Europe; Genetic Variation; GTP Phosphohydrolases; Humans; Mutation; Polymorphism, Single Nucleotide; Retinal Degeneration; Retinitis Pigmentosa; RNA, Messenger; Uveitis; Zebrafish

Complete genome sequence of citrus huanglongbing bacterium, 'Candidatus Liberibacter asiaticus' obtained through metagenomics. - Duan, Yongping; Zhou, Lijuan; Hall, David G; Li, Wenbin; Harshavardhan Doddapaneni; Lin, Hong; Liu, Li; Vahling, Cheryl M; Gabriel, Dean W; Williams, Kelly P; Dickerman, Allan; Sun, Yijun; et al. (Mol Plant Microbe Interact, 2009)
Citrus huanglongbing is the most destructive disease of citrus worldwide. It is spread by citrus psyllids and is associated with a low-titer, phloem-limited infection by any of three uncultured species of alpha-Proteobacteria, 'Candidatus Liberibacter asiaticus', 'Ca. L. americanus', and 'Ca. L. africanus'. A complete circular 'Ca. L. asiaticus' genome has been obtained by metagenomics, using the DNA extracted from a single 'Ca. L. asiaticus'-infected psyllid. The 1.23-Mb genome has an average 36.5% GC content. Annotation revealed a high percentage of genes involved in both cell motility (4.5%) and active transport in general (8.0%), which may contribute to its virulence. 'Ca. L. asiaticus' appears to have a limited ability for aerobic respiration and is likely auxotrophic for at least five amino acids. Consistent with its intracellular nature, 'Ca. L. asiaticus' lacks type III and type IV secretion systems as well as typical free-living or plant-colonizing extracellular degradative enzymes. 'Ca. L. asiaticus' appears to have all type I secretion system genes needed for both multidrug efflux and toxin effector secretion. Multi-protein phylogenetic analysis confirmed 'Ca. L. asiaticus' as an early-branching and highly divergent member of the family Rhizobiaceae. This is the first genome sequence of an uncultured alpha-proteobacteria that is both an intracellular plant pathogen and insect symbiont.
Keywords: Animals; Bacterial Proteins; Carrier Proteins; Citrus; Genome, Bacterial; Genomics; Hemiptera; Molecular Sequence Data; Phylogeny; Rhizobiaceae; Sequence Analysis, DNA; Symbiosis

The completion of the Mammalian Gene Collection (MGC). - Temple, Gary; Gerhard, Daniela S; Rasooly, Rebekah; Feingold, Elise A; Good, Peter J; Robinson, Cristen; Mandich, Allison; Derge, Jeffrey G; Lewis, Jeanne; Shoaf, Debonny; Collins, Francis S; Jang, Wonhee; et al. (Genome Res, 2009)
Since its start, the Mammalian Gene Collection (MGC) has sought to provide at least one full-protein-coding sequence cDNA clone for every human and mouse gene with a RefSeq transcript, and at least 6200 rat genes. The MGC cloning effort initially relied on random expressed sequence tag screening of cDNA libraries. Here, we summarize our recent progress using directed RT-PCR cloning and DNA synthesis. The MGC now contains clones with the entire protein-coding sequence for 92% of human and 89% of mouse genes with curated RefSeq (NM-accession) transcripts, and for 97% of human and 96% of mouse genes with curated RefSeq transcripts that have one or more PubMed publications, in addition to clones for more than 6300 rat genes. These high-quality MGC clones and their sequences are accessible without restriction to researchers worldwide.
Keywords: Animals; Cloning, Molecular; Computational Biology; DNA; DNA, Complementary; Gene Library; Genes; Humans; Mammals; Mice; National Institutes of Health (U.S.); Rats; Reverse Transcriptase Polymerase Chain Reaction; United States

Copy number variation of CCL3-like genes affects rate of progression to simian-AIDS in Rhesus Macaques (Macaca mulatta). - Degenhardt, Jeremiah D; de Candia, Paola; Chabot, Adrien; Schwartz, Stuart; Henderson, Les; Ling, Binhua; Hunter, Meredith; Jiang, Zhaoshi; Palermo, Robert E; Katze, Michael; Eichler, Evan E; Ventura, Mario; et al. (PLoS Genet, 2009)
Variation in genes underlying host immunity can lead to marked differences in susceptibility to HIV infection among humans. Despite heavy reliance on non-human primates as models for HIV/AIDS, little is known about which host factors are shared and which are unique to a given primate lineage. Here, we investigate whether copy number variation (CNV) at CCL3-like genes (CCL3L), a key genetic host factor for HIV/AIDS susceptibility and cell-mediated immune response in humans, is also a determinant of time until onset of simian-AIDS in rhesus macaques. Using a retrospective study of 57 rhesus macaques experimentally infected with SIVmac, we find that CCL3L CNV explains approximately 18% of the variance in time to simian-AIDS (p<0.001) with lower CCL3L copy number associating with more rapid disease course. We also find that CCL3L copy number varies significantly (p<10(-6)) among rhesus subpopulations, with Indian-origin macaques having, on average, half as many CCL3L gene copies as Chinese-origin macaques. Lastly, we confirm that CCL3L shows variable copy number in humans and chimpanzees and report on CCL3L CNV within and among three additional primate species. On the basis of our findings we suggest that (1) the difference in population level copy number may explain previously reported observations of longer post-infection survivorship of Chinese-origin rhesus macaques, (2) stratification by CCL3L copy number in rhesus SIV vaccine trials will increase power and reduce noise due to non-vaccine-related differences in survival, and (3) CCL3L CNV is an ancestral component of the primate immune response and, therefore, copy number variation has not been driven by HIV or SIV per se.
Keywords: Animals; Calibration; Chemokine CCL3; Disease Progression; DNA Primers; Gene Dosage; Genetics, Population; Immune System; Likelihood Functions; Macaca mulatta; Microsatellite Repeats; Models, Statistical; Proportional Hazards Models; Reverse Transcriptase Polymerase Chain Reaction; Simian Acquired Immunodeficiency Syndrome

Endometriosis is associated with progesterone resistance in the baboon (Papio anubis) oviduct: evidence based on the localization of oviductal glycoprotein 1 (OVGP1). - Wang, Chaohua; Mavrogianis, Patricia A; Fazleabas, Asgerally T (Biol Reprod, 2009)
Endometriosis has been associated with a reduced response to progesterone in both the eutopic and ectopic endometrium. In this study we evaluated OVGP1 and steroid receptor expression in oviducts of baboons with endometriosis during the midsecretory phase and determined whether progesterone resistance associated with endometriosis also occurs in the oviduct. Oviducts obtained during the window of uterine receptivity (Day 10 postovulation [PO]) from animals with induced and spontaneous disease were compared to control animals during the proliferative stage and in the implantation window as well as animals treated with the progesterone receptor (PGR) antagonist ZK 137.299 (ZK). OVGP1 was significantly higher in animals with endometriosis compared with Day 10 PO controls and was similar to that seen in the late proliferative phase and in ZK-treated animals. Baboons with spontaneous endometriosis also showed a similar persistence of OVGP1, which was correlated with the maintenance of estrogen receptor 1 (ESR1) in the epithelial cells of animals with endometriosis. However, epithelial cell height and the percentage of ciliation were not affected by endometriosis. These data imply that the normal antagonism of progesterone on ESR and OVGP1, which results in their downregulation during the window of implantation, is absent in animals with endometriosis. This was confirmed further when the action of PGR was antagonized in animals without disease, which also resulted in the persistence of ESR1 and OVGP1. These studies suggest that an aberrant oviductal environment may be an additive factor that contributes to endometriosis-associated infertility.
Keywords: Animals; Drug Resistance; Endometriosis; Endometrium; Estrogen Receptor alpha; Fallopian Tubes; Female; Glycoproteins; Papio anubis; Peritoneal Diseases; Progesterone; Receptors, Progesterone; Tissue Distribution

Fine mapping of chromosome 6q23-25 region in familial lung cancer families reveals RGS17 as a likely candidate gene. - You, Ming; Wang, Daolong; Liu, Pengyuan; Vikis, Haris; James, Michael; Lu, Yan; Wang, Yian; Wang, Min; Chen, Qiong; Jia, Dongmei; Liu, Yan; Wen, Weidong; et al. (Clin Cancer Res, 2009)
PURPOSE: We have previously mapped a major susceptibility locus influencing familial lung cancer risk to chromosome 6q23-25. However, the causal gene at this locus remains undetermined. In this study, we further refined this locus to identify a single candidate gene, by fine mapping using microsatellite markers and association studies using high-density single nucleotide polymorphisms (SNP). EXPERIMENTAL DESIGN: Six multigenerational families with five or more affected members were chosen for fine-mapping the 6q linkage region using microsatellite markers. For association mapping, we genotyped 24 6q-linked cases and 72 unrelated noncancer controls from the Genetic Epidemiology of Lung Cancer Consortium resources using the Affymetrix 500K chipset. Significant associations were validated in two independent familial lung cancer populations: 226 familial lung cases and 313 controls from the Genetic Epidemiology of Lung Cancer Consortium, and 154 familial cases and 325 controls from Mayo Clinic. Each familial case was chosen from one high-risk lung cancer family that has three or more affected members. RESULTS: A region-wide scan across 6q23-25 found significant association between lung cancer susceptibility and three single nucleotide polymorphisms in the first intron of the RGS17 gene. This association was further confirmed in two independent familial lung cancer populations. By quantitative real-time PCR analysis of matched tumor and normal human tissues, we found that RGS17 transcript accumulation is highly and consistently increased in sporadic lung cancers. Human lung tumor cell proliferation and tumorigenesis in nude mice are inhibited upon knockdown of RGS17 levels. CONCLUSION: RGS17 is a major candidate for the familial lung cancer susceptibility locus on chromosome 6q23-25.
Keywords: Aged; Animals; Cell Line, Tumor; Chromosome Mapping; Chromosomes, Human, Pair 6; Female; Gene Knockdown Techniques; Genetic Predisposition to Disease; Genotype; Haplotypes; Humans; Lung; Lung Neoplasms; Male; Mice; Mice, Nude; Microsatellite Repeats; Middle Aged; Oligonucleotide Array Sequence Analysis; Polymorphism, Single Nucleotide; RGS Proteins; RNA, Small Interfering; Transplantation, Heterologous

Genetic variation in baboon craniofacial sexual dimorphism. - Willmore, Katherine E; Roseman, Charles C; Jeffrey Rogers; Richtsmeier, Joan T; Cheverud, James M (Evolution, 2009)
Sexual dimorphism is a widespread phenomenon and contributes greatly to intraspecies variation. Despite a long history of active research, the genetic basis of dimorphism for complex traits remains unknown. Understanding the sex-specific differences in genetic architecture for cranial traits in a highly dimorphic species could identify possible mechanisms through which selection acts to produce dimorphism. Using distances calculated from three-dimensional landmark data from CT scans of 402 baboon skulls from a known genealogy, we estimated genetic variance parameters in both sexes to determine the presence of gene-by-sex (G x S) interactions and X-linked heritability. We hypothesize that traits exhibiting the greatest degree of sexual dimorphism (facial traits in baboons) will demonstrate either stronger G x S interactions or X-linked effects. We found G x S interactions and X-linked effects for a few measures that span the areas connecting the face to the neurocranium but for no traits restricted to the face. This finding suggests that facial traits will have a limited response to selection for further evolution of dimorphism in this population. We discuss the implications of our results with respect to the origins of cranial sexual dimorphism in this baboon sample, and how the genetic architecture of these traits affects their potential for future evolution.
Keywords: Animals; Biological Evolution; Female; Genes, X-Linked; Genetic Variation; Male; Papio hamadryas; Sex Characteristics; Skull

The genome sequence of taurine cattle: a window to ruminant biology and evolution. - Elsik, Christine G; Tellam, Ross L; Worley, Kim C; Richard A Gibbs; Donna M Muzny; Weinstock, George M; Adelson, David L; Eichler, Evan E; Elnitski, Laura; Guigó, Roderic; Hamernik, Debora L; Kappes, Steve M; et al. (Science, 2009)
To understand the biology and evolution of ruminants, the cattle genome was sequenced to about sevenfold coverage. The cattle genome contains a minimum of 22,000 genes, with a core set of 14,345 orthologs shared among seven mammalian species of which 1217 are absent or undetected in noneutherian (marsupial or monotreme) genomes. Cattle-specific evolutionary breakpoint regions in chromosomes have a higher density of segmental duplications, enrichment of repetitive elements, and species-specific variations in genes associated with lactation and immune responsiveness. Genes involved in metabolism are generally highly conserved, although five metabolic genes are deleted or extensively diverged from their human orthologs. The cattle genome sequence thus provides a resource for understanding mammalian evolution and accelerating livestock genetic improvement for milk and meat production.
Keywords: Alternative Splicing; Animals; Animals, Domestic; Biological Evolution; Cattle; Evolution, Molecular; Female; Genetic Variation; Genome; Humans; Male; MicroRNAs; Molecular Sequence Data; Proteins; Sequence Analysis, DNA; Species Specificity; Synteny

Genome-wide identification of allelic expression in hypertensive rats. - Dmitrieva, Renata I; Hinojos, Cruz A; Grove, Megan L; Bell, Rebecca J; Eric Boerwinkle; Fornage, Myriam; Doris, Peter A (Circ Cardiovasc Genet, 2009)
BACKGROUND: Identification of genes involved in complex cardiovascular disease traits has proven challenging. Inbred animal models can facilitate genetic studies of disease traits. The spontaneously hypertensive rat (SHR) is an inbred model of hypertension that exists in several closely related but genetically distinct lines. METHODS AND RESULTS: We used renal gene-expression profiling across 3 distinct SHR lines to identify genes that show different expression in SHR than in the genetically related normotensive control strain, Wistar-Kyoto. To ensure robust discovery of genes showing SHR-specific expression differences, we considered only those genes in which differential expression is replicated in multiple animals of each of multiple hypertensive rat lines at multiple time points during the ontogeny of hypertension. Mutation analysis was performed on the identified genes to uncover allelic variation. We identified those genes in which all SHR lines share a single allele of the gene when normotensive controls (Wistar-Kyoto) have fixed the alternative allele. We then identified which of the differentially expressed genes show expression that is controlled by the alleleic variation present in and around the gene. Allelic expression was demonstrated by observing the effect on gene expression of alleles inherited in the freely segregating F(2) progeny of a cross between SHR and Wistar-Kyoto animals. CONCLUSIONS: The result of these studies is the identification of several genes (Ptprj, Ela1, Dapk-2, and Gstt2) in which each of 4 SHR lines examined have fixed the same allele and in which each of 2 Wistar-Kyoto lines have a contrasting allele for which the inherited allele influences the level of gene expression. We further show that alleles of these genes lie in extensive haplotype blocks that have been inherited identical by descent in the hypertensive lines.
Keywords: Alleles; Animals; Blood Pressure; Disease Models, Animal; Female; Gene Expression Profiling; Genome-Wide Association Study; Humans; Hypertension; Kidney; Male; Pedigree; Polymorphism, Single Nucleotide; Rats; Rats, Inbred SHR; Rats, Inbred WKY

Genome-wide survey of SNP variation uncovers the genetic structure of cattle breeds. - Richard A Gibbs; Taylor, Jeremy F; Van Tassell, Curtis P; Barendse, William; Eversole, Kellye A; Gill, Clare A; Green, Ronnie D; Hamernik, Debora L; Kappes, Steven M; Lien, Sigbjørn; Matukumalli, Lakshmi K; McEwan, John C; et al. (Science, 2009)
The imprints of domestication and breed development on the genomes of livestock likely differ from those of companion animals. A deep draft sequence assembly of shotgun reads from a single Hereford female and comparative sequences sampled from six additional breeds were used to develop probes to interrogate 37,470 single-nucleotide polymorphisms (SNPs) in 497 cattle from 19 geographically and biologically diverse breeds. These data show that cattle have undergone a rapid recent decrease in effective population size from a very large ancestral population, possibly due to bottlenecks associated with domestication, selection, and breed formation. Domestication and artificial selection appear to have left detectable signatures of selection within the cattle genome, yet the current levels of diversity within breeds are at least as great as exists within humans.
Keywords: Animals; Breeding; Cattle; Female; Gene Frequency; Genetic Variation; Genome; Male; Molecular Sequence Data; Mutation; Polymorphism, Single Nucleotide; Population Density

High-throughput multiplex sequencing to discover copy number variants in Drosophila. - Daines, Bryce; Wang, Hui; Yumei Li; Yi Han; Richard A Gibbs; Rui Chen (Genetics, 2009)
Copy number variation (CNV) contributes in phenotypically relevant ways to the genetic variability of many organisms. Cost-effective genomewide methods for identifying copy number variation are necessary to elucidate the contribution that these structural variants make to the genomes of model organisms. We have developed a novel approach for the identification of copy number variation by next generation sequencing. As a proof of concept our method has been applied to map the deletions of three Drosophila deficiency strains. We demonstrate that low sequence coverage is sufficient for identifying and mapping large deletions at kilobase resolution, suggesting that data generated from high-throughput sequencing experiments are sufficient for simultaneously analyzing many strains. Genomic DNA from two Drosophila deficiency stocks was barcoded and sequenced in multiplex, and the breakpoints associated with each deletion were successfully identified. The approach we describe is immediately applicable to the systematic exploration of copy number variation in model organisms and humans.
Keywords: Animals; DNA Copy Number Variations; Drosophila melanogaster; Genome, Insect; Methods; Sequence Analysis, DNA; Sequence Deletion

Identification of differentially expressed miRNAs in chicken lung and trachea with avian influenza virus infection by a deep sequencing approach. - Wang, Ying; Brahmakshatriya, Vinayak; Zhu, Huifeng; Lupiani, Blanca; Reddy, Sanjay M; Yoon, Byung-Jun; Gunaratne, Preethi H; Kim, Jong Hwan; Rui Chen; Wang, Junjun; Zhou, Huaijun (BMC Genomics, 2009)
BACKGROUND: MicroRNAs (miRNAs) play critical roles in a wide spectrum of biological processes and have been shown to be important effectors in the intricate host-pathogen interaction networks. Avian influenza virus (AIV) not only causes significant economic losses in poultry production, but also is of great concern to human health. The objective of this study was to identify miRNAs associated with AIV infections in chickens. RESULTS: Total RNAs were isolated from lung and trachea of low pathogenic H5N3 infected and non-infected SPF chickens at 4 days post-infection. A total of 278,398 and 340,726 reads were obtained from lung and trachea, respectively. And 377 miRNAs were detected in lungs and 149 in tracheae from a total of 474 distinct chicken miRNAs available at the miRBase, respectively. Seventy-three and thirty-six miRNAs were differentially expressed between infected and non-infected chickens in lungs and tracheae, respectively. There were more miRNAs highly expressed in non-infected tissues than in infected tissues. Interestingly, some of these differentially expressed miRNAs, including miR-146, have been previously reported to be associated with immune-related signal pathways in mammals. CONCLUSION: To our knowledge, this is the first study on miRNA gene expression in AIV infected chickens using a deep sequencing approach. During AIV infection, many host miRNAs were differentially regulated, supporting the hypothesis that certain miRNAs might be essential in the host-pathogen interactions. Elucidation of the mechanism of these miRNAs on the regulation of host-AIV interaction will lead to the development of new control strategies to prevent or treat AIV infections in poultry.
Keywords: Animals; Base Sequence; Chickens; Gene Expression Profiling; Gene Expression Regulation; Influenza A virus; Influenza in Birds; Lung; MicroRNAs; Molecular Sequence Data; Poultry Diseases; Sequence Analysis, DNA; Trachea; Virus Replication

Involvement of SSRP1 in latent replication of Kaposi's sarcoma-associated herpesvirus. - Jianhong Hu; Liu, Eugene; Renne, Rolf (J Virol, 2009)
Kaposi's sarcoma-associated herpesvirus (also named human herpesvirus 8) is a gamma-herpesvirus that undergoes both lytic and latent infection. During latent infection, two viral elements are required: latency-associated nuclear antigen (LANA), which functions as an origin binding protein, and the latent origin, which resides within the terminal repeats (TRs) of the viral genome. Previously, we identified two cis-elements within the TRs which are required for latent DNA replication: two LANA binding sites (LBS1 and LBS2 [LBS1/2]) and a GC-rich replication element (RE) upstream of LBS1/2. To further characterize the RE, we constructed a 71-bp minimal replicon (MR) and performed a detailed mutational analysis. Our data indicate that the first 8 nucleotides within the RE are critical for replication. Moreover, both the position and the distance between the RE and LBS1/2 can affect origin replication activity, suggesting that the RE may function as a loading pad for cellular proteins involved in replication. Using biotinylated DNA fragments of wild-type or mutant MRs as probes, we identified 30 proteins that preferentially bind to the origin. Among these proteins, structure-specific recognition protein 1 (SSRP1), a subunit of the FACT complex, and telomeric repeat binding factor 2 (TRF2) formed complexes with LANA at the MR region. Furthermore, the small interfering RNA-based knockdown of SSRP1, but not the dominant-negative-based knockdown of TRF2, significantly decreased the efficiency of LANA-dependent DNA replication. These results indicate that SSRP1 is a novel cellular protein involved in LANA-dependent DNA replication.
Keywords: Animals; Antigens, Viral; Binding Sites; Cell Line; DNA Replication; DNA, Viral; DNA-Binding Proteins; Genome, Viral; Herpesviridae Infections; Herpesvirus 8, Human; High Mobility Group Proteins; Humans; Molecular Sequence Data; Nuclear Proteins; RNA, Small Interfering; Terminal Repeat Sequences; Transcriptional Elongation Factors; Virus Latency; Virus Replication

Localization of multiple pleiotropic genes for lipoprotein metabolism in baboons. - Rainwater, David L; Cox, Laura A; Jeffrey Rogers; VandeBerg, John L; Mahaney, Michael C (J Lipid Res, 2009)
We employed a novel approach to identify the key loci that harbor genes influencing lipoprotein metabolism in approximately 2,000 pedigreed baboons fed various diets differing in levels of fat and cholesterol. In this study, 126 overlapping traits related to both LDL and HDL metabolism were normalized and subjected to genome-wide linkage screening. As was expected, the traits were highly, but not completely, correlated. We exploited the information in these correlated traits by focusing on those genomic regions harboring quantitative trait loci (QTL) for multiple traits, reasoning that the more influential genes would impact a larger number of traits. This study identified five major QTL clusters (each with at least two significant logarithm of the odds scores >4.7), two of which had not been previously reported in baboons. One of these mapped to the baboon ortholog of human chromosome 1p32-p34 and influenced concentrations of LDL-cholesterol on Basal and high-fat, low-cholesterol diets. The other novel QTL cluster mapped to the baboon ortholog of human chromosome 12q13.13-q14.1 and influenced LDL size properties on high-fat, low-cholesterol and high-fat, high-cholesterol, but not Basal, diets. Confirming the value of this approach, three of the QTL clusters replicated published linkage findings for the same or similar traits.
Keywords: Animals; Chromosomes, Mammalian; Diet; Gene Expression Regulation; Genetic Linkage; Genotype; Humans; Lipid Metabolism; Lipids; Lipoproteins; Lod Score; Multigene Family; Papio; Quantitative Trait Loci

Microarray analysis of somatostatin receptor 5-regulated gene expression profiles in murine pancreas. - Patel, Sanjeet G; Zhou, Guisheng; Liu, Shi-He; Li, Min; Jeong, Jae-Wook; DeMayo, Francesco J; Marie-Claude Gingras; Richard A Gibbs; Fisher, William E; Brunicardi, F Charles (World J Surg, 2009)
BACKGROUND: We previously demonstrated that somatostatin receptor type 5 (SSTR5) gene ablation results in alterations in insulin secretion and glucose metabolism, accompanied by morphologic alterations in the islets of Langerhans. The underlying mechanism(s) by which SSTR5 exerts its cellular functions remain(s) unknown. We hypothesized that SSTR5 mediates the inhibitory effect of somatostatin (SST) on insulin secretion and islet proliferation by regulating a specific set of pancreatic genes. METHODS: To identify SSTR5-regulated pancreatic genes, gene expression microarray analysis was performed on the whole pancreas of 1- and 3-month-old wild-type (WT) and SSTR5 knockout (SSTR5-/-) male mice. Real-time RT-PCR and immunofluorescence were performed to validate selected differentially expressed genes. RESULTS: A set of 143 probes were identified to be differentially expressed in the pancreas of 1-month-old SSTR5-/- mice, 72 of which were downregulated and 71 upregulated. At 3 months of age, SSTR5 gene ablation resulted in downregulation of a set of 30 probes and upregulation of a set of 37 probes. Among these differentially expressed genes, there were 15 and 5 genes that were upregulated and downregulated, respectively, in mice at both 1 and 3 months of age. Three genes, PAP/INGAP, ANG, and TDE1, were selected to be validated by real-time RT-PCR and immunofluorescence. CONCLUSIONS: A specific set of genes linked to a wide range of cellular functions such as islet proliferation, apoptosis, angiogenesis, and tumorigenesis were either upregulated or downregulated in SSTR5-deficient male mice compared with their expression in wild-type mice. Therefore, these genes are potential SSTR5-regulated genes during normal pancreatic development and functional maintenance.
Keywords: Animals; Apoptosis; Cell Proliferation; Down-Regulation; Fluorescent Antibody Technique; Gene Expression Profiling; Islets of Langerhans; Male; Mice; Mice, Knockout; Neoplasm Proteins; Neovascularization, Pathologic; Oligonucleotide Array Sequence Analysis; Pancreas; Pancreatitis-Associated Proteins; Proteins; Receptors, Cell Surface; Receptors, Somatostatin; Reverse Transcriptase Polymerase Chain Reaction; Ribonuclease, Pancreatic; Up-Regulation

Mutations in SPATA7 cause Leber congenital amaurosis and juvenile retinitis pigmentosa. - Wang, Hui; den Hollander, Anneke I; Moayedi, Yalda; Abulimiti, Abuduaini; Yumei Li; Collin, Rob W J; Hoyng, Carel B; Lopez, Irma; Abboud, Emad B; Al-Rajhi, Ali A; Bray, Molly; Lewis, Richard Alan; et al. (Am J Hum Genet, 2009)
Leber congenital amaurosis (LCA) and juvenile retinitis pigmentosa (RP) are the most common hereditary causes of visual impairment in infants and children. Using homozygosity mapping, we narrowed down the critical region of the LCA3 locus to 3.8 Mb between markers D14S1022 and D14S1005. By direct Sanger sequencing of all genes within this region, we found a homozygous nonsense mutation in the SPATA7 gene in Saudi Arabian family KKESH-060. Three other loss-of-function mutations were subsequently discovered in patients with LCA or juvenile RP from distinct populations. Furthermore, we determined that Spata7 is expressed in the mature mouse retina. Our findings reveal another human visual-disease gene that causes LCA and juvenile RP.
Keywords: Animals; Child; Codon, Nonsense; DNA-Binding Proteins; Homozygote; Humans; Mice; Middle Aged; Pedigree; Retina; Retinal Diseases; Retinitis Pigmentosa

Phylogeny of the macaques (Cercopithecidae: Macaca) based on Alu elements. - Li, Jing; Han, Kyudong; Xing, Jinchuan; Kim, Heui-Soo; Jeffrey Rogers; Ryder, Oliver A; Disotell, Todd; Yue, Bisong; Batzer, Mark A (Gene, 2009)
Genus Macaca (Cercopithecidae: Papionini) is one of the most successful primate radiations. Despite previous studies on morphology and mitochondrial DNA analysis, a number of issues regarding the details of macaque evolution remain unsolved. Alu elements are a class of non-autonomous retroposons belonging to short interspersed elements that are specific to the primate lineage. Because retroposon insertions show very little homoplasy, and because the ancestral state (absence of the SINE) is known, Alu elements are useful genetic markers and have been utilized for analyzing primate phylogenentic relationships and human population genetic relationships. Using PCR display methodology, 298 new Alu insertions have been identified from ten species of macaques. Together with 60 loci reported previously, a total of 358 loci are used to infer the phylogenetic relationships of genus Macaca. With regard to earlier unresolved issues on the macaque evolution, the topology of our tree suggests that: 1) genus Macaca contains four monophyletic species groups; 2) within the Asian macaques, the silenus group diverged first, and members of the sinica and fascicularis groups share a common ancestor; 3) Macaca arctoides are classified in the sinica group. Our results provide a robust molecular phylogeny for genus Macaca with stronger statistical support than previous studies. The present study also illustrates that SINE-based approaches are a powerful tool in primate phylogenetic studies and can be used to successfully resolve evolutionary relationships between taxa at scales from the ordinal level to closely related species within one genus.
Keywords: Alu Elements; Animals; Macaca; Mutagenesis, Insertional; Phylogeny; Polymerase Chain Reaction

The prolonged effect of repeated maternal glucocorticoid exposure on the maternal and fetal leptin/insulin-like growth factor axis in Papio species. - Schlabritz-Loutsevitch, Natalia E; Lopez-Alvarenga, Juan C; Comuzzie, Anthony G; Miller, Myrna M; Ford, Stephen P; Li, Cun; Hubbard, Gene B; Ferry, Robert J; Nathanielsz, Peter W (Reprod Sci, 2009)
BACKGROUND: Maternal obesity represents a risk factor for pregnancy-related complications. Glucocorticoids are known to promote obesity in adults. METHODS: We evaluated maternal and fetal metabolic changes during and after 3 weekly courses of betamethasone administered to pregnant baboons (Papio subspecies) at doses equivalent to those given to pregnant women. RESULTS: Betamethasone administration during the second half of pregnancy increased maternal weight but neither maternal food intake nor fetal weight, as assessed at the end of gestation. Betamethasone increased maternal serum glucose concentration, the ratio of insulin-like growth factor-I and insulin-like growth factor binding protein-3, and serum leptin during treatment (normalized by 17, 35, and 45 days posttreatment, respectively, for each parameter). Maternal and fetal serum leptin concentrations did not differ between groups at the end of gestation. CONCLUSION: Prolonged maternal hyperleptinemia caused by betamethasone administration in the second half of gestation did not change fetal metabolic parameters measured and placental leptin distribution at the end of gestation.
Keywords: Animals; Betamethasone; Blood Glucose; Body Weight; Cesarean Section; Cholesterol; Drug Administration Schedule; Eating; Female; Fetal Blood; Fetal Weight; Fetus; Gestational Age; Glucocorticoids; Hydrocortisone; Injections, Intramuscular; Insulin-Like Growth Factor Binding Protein 3; Insulin-Like Growth Factor I; Insulin-Like Growth Factor II; Leptin; Maternal-Fetal Exchange; Papio cynocephalus; Placenta; Pregnancy

Quantitative loci regulating plasma levels of gamma glutamyl transferase and albumin and their genetic correlations with cardiovascular risk factors. - Bose, Tanushree; Voruganti, V Saroja; Tejero, M Elizabeth; Proffitt, J Michael; Cox, Laura A; VandeBerg, John L; Mahaney, Michael C; Jeffrey Rogers; Freeland-Graves, Jeanne H; Cole, Shelley A; Comuzzie, Anthony G (Exp Biol Med (Maywood), 2009)
gamma Glutamyl transferase (GGT) and albumin (ALB) are two markers of liver function. These two proteins have been associated with non-alcoholic fatty liver disease and cardiovascular disease. The objectives of this study were to explore the genetic factors that influence variation in the plasma levels of GGT and ALB and to evaluate their genetic correlations with cardiovascular risk factors. Baboons from the Southwest National Primate Research Center at the Southwest Foundation for Biomedical Research, San Antonio, TX, were used as an animal model. The baboons were fed a standard monkey chow diet ad libitum. Fasting plasma concentrations of GGT, ALB, triglycerides, total cholesterol and LDL cholesterol were measured in 350 pedigreed adult baboons by standard assay procedures. A maximum likelihood-based variance decomposition approach implemented in the computer program SOLAR was used to conduct genetic analyses. The heritabilities of GGT (h(2) = 0.55; P < 0.0001) and ALB (h(2) = 0.42; P < 0.01) were significant. No statistically significant associations were found between GGT and the cardiovascular-related phenotypes. Genetic correlations between ALB and total cholesterol, LDL cholesterol and triglycerides were significant. A QTL (LOD = 2.8) for GGT plasma levels was identified on the baboon homologue of human chromosome 22 between markers D22S304 and D22S280. A QTL (LOD = 2.3) near marker D10S1432 was detected on the baboon homologue of human chromosome 10 for ALB. These results imply that variations in the plasma levels of GGT and ALB are under significant genetic regulation and that a common genetic component influences ALB and cardiovascular risk factor phenotypes.
Keywords: Animals; Biomarkers; Cardiovascular Diseases; gamma-Glutamyltransferase; Genetic Markers; Genetic Predisposition to Disease; Humans; Liver; Lod Score; Papio hamadryas; Pedigree; Phenotype; Quantitative Trait Loci; Risk Factors; Serum Albumin

Rare loss-of-function mutations in ANGPTL family members contribute to plasma triglyceride levels in humans. - Romeo, Stefano; Yin, Wu; Kozlitina, Julia; Pennacchio, Len A; Eric Boerwinkle; Hobbs, Helen H; Cohen, Jonathan C (J Clin Invest, 2009)
The relative activity of lipoprotein lipase (LPL) in different tissues controls the partitioning of lipoprotein-derived fatty acids between sites of fat storage (adipose tissue) and oxidation (heart and skeletal muscle). Here we used a reverse genetic strategy to test the hypothesis that 4 angiopoietin-like proteins (ANGPTL3, -4, -5, and -6) play key roles in triglyceride (TG) metabolism in humans. We re-sequenced the coding regions of the genes encoding these proteins and identified multiple rare nonsynonymous (NS) sequence variations that were associated with low plasma TG levels but not with other metabolic phenotypes. Functional studies revealed that all mutant alleles of ANGPTL3 and ANGPTL4 that were associated with low plasma TG levels interfered either with the synthesis or secretion of the protein or with the ability of the ANGPTL protein to inhibit LPL. A total of 1% of the Dallas Heart Study population and 4% of those participants with a plasma TG in the lowest quartile had a rare loss-of-function mutation in ANGPTL3, ANGPTL4, or ANGPTL5. Thus, ANGPTL3, ANGPTL4, and ANGPTL5, but not ANGPTL6, play nonredundant roles in TG metabolism, and multiple alleles at these loci cumulatively contribute to variability in plasma TG levels in humans.
Keywords: Alleles; Amino Acid Sequence; Angiopoietin-Like Protein 1; Angiopoietin-like Proteins; Angiopoietins; Animals; Cell Line; Ethnicity; Genetic Variation; Humans; Mice; Mutation; Protein Isoforms; Tissue Distribution; Triglycerides

Replication of long-bone length QTL in the F9-F10 LG,SM advanced intercross. - Norgard, Elizabeth A; Jarvis, Joseph P; Roseman, Charles C; Maxwell, Taylor J; Kenney-Hunt, Jane P; Samocha, Kaitlin E; Pletscher, L Susan; Wang, Bing; Fawcett, Gloria L; Leatherwood, Christopher J; Wolf, Jason B; Cheverud, James M (Mamm Genome, 2009)
Quantitative trait locus (QTL) mapping techniques are frequently used to identify genomic regions associated with variation in phenotypes of interest. However, the F(2) intercross and congenic strain populations usually employed have limited genetic resolution resulting in relatively large confidence intervals that greatly inhibit functional confirmation of statistical results. Here we use the increased resolution of the combined F(9) and F(10) generations (n = 1455) of the LG,SM advanced intercross to fine-map previously identified QTL associated with the lengths of the humerus, ulna, femur, and tibia. We detected 81 QTL affecting long-bone lengths. Of these, 49 were previously identified in the combined F(2)-F(3) population of this intercross, while 32 represent novel contributors to trait variance. Pleiotropy analysis suggests that most QTL affect three to four long bones or serially homologous limb segments. We also identified 72 epistatic interactions involving 38 QTL and 88 novel regions. This analysis shows that using later generations of an advanced intercross greatly facilitates fine-mapping of confidence intervals, resolving three F(2)-F(3) QTL into multiple linked loci and narrowing confidence intervals of other loci, as well as allowing identification of additional QTL. Further characterization of the biological bases of these QTL will help provide a better understanding of the genetics of small variations in long-bone length.
Keywords: Animals; Bone and Bones; Crosses, Genetic; DNA Replication; Female; Hybridization, Genetic; Male; Mice; Organ Size; Quantitative Trait Loci

Resources for genetic management and genomics research on non-human primates at the National Primate Research Centers (NPRCs). - Kanthaswamy, S; Capitanio, J P; Dubay, C J; Ferguson, B; Folks, T; Ha, J C; Hotchkiss, C E; Johnson, Z P; Katze, M G; Kean, L S; Kubisch, H Michael; Lank, S; et al. (J Med Primatol, 2009)
The National Primate Research Centers (NPRCs) established Working Groups (WGs) for developing resources and mechanisms to facilitate collaborations among non-human primate (NHP) researchers. Here we report the progress of the Genome Banking and the Genetics and Genomics WGs in developing resources to advance the exchange, analysis and comparison of NHP genetic and genomic data across the NPRCs. The Genome Banking WG has established a National NHP DNA bank comprising 1250 DNA samples from unrelated animals and family trios from the 10 NHP species housed within the NPRC system. The Genetics and Genomics WG is developing SNP arrays that will provide a uniform, highly informative, efficient and low-cost method for rhesus and long-tailed macaque genotyping across the eight NPRCs. This WG is also establishing a Biomedical Informatics Research Network-based portal for shared bioinformatics resources including vital statistics, genotype and population data and information on the National NHP DNA bank.
Keywords: Animals; Genomics; National Institutes of Health (U.S.); Primates; United States

Serotonin transporter binding and genotype in the nonhuman primate brain using [C-11]DASB PET. - Christian, B T; Fox, A S; Oler, J A; Vandehey, N T; Murali, D; Rogers, J; Oakes, T R; Shelton, S E; Davidson, R J; Kalin, N H (Neuroimage, 2009)
UNLABELLED: The length polymorphism of the serotonin (5-HT) transporter gene promoter region has been implicated in altered 5-HT function and, in turn, neuropsychiatric illnesses, such as anxiety and depression. The nonhuman primate has been used as a model to study anxiety-related mechanisms in humans based upon similarities in behavior and the presence of a similar 5-HT transporter gene polymorphism. Stressful and threatening contexts in the nonhuman primate model have revealed 5-HT transporter genotype dependent differences in regional glucose metabolism. Using the rhesus monkey, we examined the extent to which serotonin transporter genotype is associated with 5-HT transporter binding in brain regions implicated in emotion-related pathology. METHODS: Genotype data and high resolution PET scans were acquired in 29 rhesus (Macaca mulatta) monkeys. [C-11]DASB dynamic PET scans were acquired for 90 min in the anesthetized animals and images of distribution volume ratio (DVR) were created to serve as a metric of 5-HT transporter binding for group comparison based on a reference region method of analysis. Regional and voxelwise statistical analysis were performed with corrections for anatomical differences in gray matter probability, sex, age and radioligand mass. RESULTS: There were no significant differences when comparing l/l homozygotes with s-carriers in the regions of the brain implicated in anxiety and mood related illnesses (amygdala, striatum, thalamus, raphe nuclei, temporal and prefrontal cortex). There was a significant sex difference in 5-HT transporter binding in all regions with females having 18%-28% higher DVR than males. CONCLUSIONS: Because these findings are consistent with similar genotype findings in humans, this further strengthens the use of the rhesus model for studying anxiety-related neuropathologies.
Keywords: Aniline Compounds; Animals; Brain; Carbon Radioisotopes; Female; Genotype; Humans; Macaca mulatta; Male; Positron-Emission Tomography; Protein Binding; Radiopharmaceuticals; Serotonin Plasma Membrane Transport Proteins; Sulfides; Tissue Distribution

A simple and evolutional approach proven to recanalise the nasolacrimal duct obstruction. - Chen, D; Ge, J; Wang, L; Gao, Q; Ma, P; Li, N; Li, D-Q; Wang, Z (Br J Ophthalmol, 2009)
AIM: To evaluate a new approach of recanalisation of nasolacrimal duct obstruction (RC-NLDO) in the treatment of the nasolacrimal duct obstruction (NLDO) and chronic dacryocystitis. METHODS: 583 patients with 641 eyes suffering from NLDO and chronic dacryocystitis were enrolled in this study. The RC-NLDO was performed in 506 eyes, with 135 eyes undergoing external dacryocystorhinostomy (EX-DCR) as controls. Patient follow-up for 54 months was evaluated by symptoms, dye disappearance test, lacrimal irrigation and digital subtraction dacryocystogram. The RC-NLDO was also performed in 12 rhesus monkeys for histopathological examination. RESULTS: The clinical success rates were 93.1% in 506 cases of RC-NLDO and 91.11% in 135 cases of EX-DCR. The success rates for second surgery were achieved in 85.19% on RC-NLDO and 40.0% on EX-DCR. No major intra- or postoperative complications were observed in the RC-NLDO group. The mean operative duration was 12.5 min for RC-NLDO and 40.3 min for EX-DCR (p<0.001). A pathological study in rhesus monkeys demonstrated that the RC-NLDO wounded epithelium in nasolacrimal duct healed completely within 1 month without granulation tissue formation. CONCLUSION: The findings demonstrate that the RC-NLDO is a simple and effective approach proven to recanalise the obstructed nasolacrimal duct with a comparable success rate to EX-DCR.
Keywords: Animals; Catheterization; Dacryocystorhinostomy; Equipment Design; Female; Humans; Lacrimal Duct Obstruction; Macaca mulatta; Male; Middle Aged; Nasolacrimal Duct; Postoperative Care; Wound Healing

Unlocking the bovine genome. - Tellam, Ross L; Lemay, Danielle G; Van Tassell, Curtis P; Lewin, Harris A; Worley, Kim C; Elsik, Christine G (BMC Genomics, 2009)
The draft genome sequence of cattle (Bos taurus) has now been analyzed by the Bovine Genome Sequencing and Analysis Consortium and the Bovine HapMap Consortium, which together represent an extensive collaboration involving more than 300 scientists from 25 different countries.
Keywords: Animals; Cattle; Chromosome Mapping; Chromosomes, Mammalian; Databases, Genetic; Evolution, Molecular; Genome; Internet; Sequence Analysis, DNA

Analysis of transcriptome data in the red flour beetle, Tribolium castaneum. - Park, Yoonseong; Aikins, Jamie; Wang, L J; Beeman, Richard W; Oppert, Brenda; Lord, Jeffrey C; Brown, Susan J; Lorenzen, Marcé D; Stephen Richards; Weinstock, George M; Richard A Gibbs (Insect Biochem Mol Biol, 2008)
The whole genome sequence of Tribolium castaneum, a worldwide coleopteran pest of stored products, has recently been determined. In order to facilitate accurate annotation and detailed functional analysis of this genome, we have compiled and analyzed all available expressed sequence tag (EST) data. The raw data consist of 61,228 ESTs, including 10,704 obtained from NCBI and an additional 50,524 derived from 32,544 clones generated in our laboratories. These sequences were amassed from cDNA libraries representing six different tissues or stages, namely: whole embryos, whole larvae, larval hindguts and Malpighian tubules, larval fat bodies and carcasses, adult ovaries, and adult heads. Assembly of the 61,228 sequences collapsed into 12,269 clusters (groups of overlapping ESTs representing single genes), of which 10,134 mapped onto 6,463 (39%) of the 16,422 GLEAN gene models (i.e. official Tribolium gene list). Approximately 1,600 clusters (13% of the total) lack corresponding GLEAN models, despite high matches to the genome, suggesting that a considerable number of transcribed sequences were missed by the gene prediction programs or were removed by GLEAN. We conservatively estimate that the current EST set represents more than 7,500 transcription units.
Keywords: Animals; Databases, Nucleic Acid; Expressed Sequence Tags; Gene Expression Profiling; Gene Library; Tribolium

APOE/C1/C4/C2 hepatic control region polymorphism influences plasma apoE and LDL cholesterol levels. - Klos, Kathy; Shimmin, Lawrence; Ballantyne, Christie; Eric Boerwinkle; Clark, Andrew; Coresh, Josef; Hanis, Craig; Liu, Kiang; Sayre, Scott; Hixson, James (Hum Mol Genet, 2008)
We characterized 102 kb of chromosome 19 containing the apolipoprotein (APO) E/C1/C4/C2 cluster and two flanking genes for common DNA variants associated with plasma low-density lipoprotein cholesterol (LDL-C) level. DNA variants were identified by comparing sequences of 48 haploid hybrid cell lines. We genotyped participants (1943 Whites and 2046 African-Americans) of the Coronary Artery Risk Development in Young Adults study for 115 variants. After controlling for the effects of the APOE epsilon2/3/4 polymorphism, a single nucleotide polymorphism, rs35136575, in the downstream hepatic control region 2 (HCR-2) was associated with LDL-C in Caucasians (P = 0.0004), accounting for 1% of variation. We genotyped rs35136575 in the Atherosclerosis Risk in Communities (ARIC) cohort (3679 African-Americans and 10 427 Whites) and in the Genetic Epidemiology Network of Arteriopathy (GENOA) sibships (1381 African-Americans in 592 sibships, 1116 Caucasians in 503 sibships and 1378 Mexican-Americans in 416 sibships), finding association with LDL-C level in ARIC Caucasians (P = 0.0064). Lower plasma LDL-C was observed with the rare allele. Plasma apoE level was strongly associated with HCR-2 variant genotype in all three GENOA samples (P </= 0.002), indicating an effect on apoE concentration. Patterns of association for plasma apo A-I, apoB, LDL-C, high-density lipoprotein cholesterol, total cholesterol and triglyceride levels with rs35136575 in the population-based samples evaluated in this study suggest a pleiotropic effect that may be context-dependent.
Keywords: Adult; Aged; Animals; Apolipoproteins; Apolipoproteins E; Black or African American; Cholesterol; Cholesterol, LDL; Chromosomes, Human, Pair 19; Female; Genotype; Humans; Hybrid Cells; Male; Mexican Americans; Mice; Middle Aged; Polymorphism, Single Nucleotide; United States; White People

cneViewer: a database of conserved non-coding elements for studies of tissue-specific gene regulation. - Persampieri, Jason; Ritter, Deborah I; Lees, Daniel; Lehoczky, Jessica; Li, Qiang; Guo, Su; Chuang, Jeffrey H (Bioinformatics, 2008)
There are thousands of strongly conserved non-coding elements (CNEs) in vertebrate genomes, and their functions remain largely unknown. However, without biologically relevant criteria for prioritizing them, selecting a particular CNE sequences to study can be haphazard. To address this problem, we present cneViewer-a database and webtool that systematizes information on conserved non-coding DNA elements in zebrafish. A key feature here is the ability to search for CNEs that may be relevant to tissue-specific gene regulation, based on known developmental expression patterns of nearby genes. cneViewer provides this and other organizing features that significantly facilitate experimental design and CNE analysis.
Keywords: Animals; Base Sequence; Computational Biology; Conserved Sequence; Databases, Genetic; DNA; Gene Expression Regulation; Humans; Internet; Molecular Sequence Data; Regulatory Sequences, Nucleic Acid; Software; Zebrafish

Complete genome sequence of Treponema pallidum ssp. pallidum strain SS14 determined with oligonucleotide arrays. - Matejková, Petra; Strouhal, Michal; Smajs, David; Norris, Steven J; Palzkill, Timothy; Petrosino, Joseph F; Sodergren, Erica; Norton, Jason E; Singh, Jaz; Richmond, Todd A; Molla, Michael N; Albert, Thomas J; et al. (BMC Microbiol, 2008)
BACKGROUND: Syphilis spirochete Treponema pallidum ssp. pallidum remains the enigmatic pathogen, since no virulence factors have been identified and the pathogenesis of the disease is poorly understood. Increasing rates of new syphilis cases per year have been observed recently. RESULTS: The genome of the SS14 strain was sequenced to high accuracy by an oligonucleotide array strategy requiring hybridization to only three arrays (Comparative Genome Sequencing, CGS). Gaps in the resulting sequence were filled with targeted dideoxy-terminators (DDT) sequencing and the sequence was confirmed by whole genome fingerprinting (WGF). When compared to the Nichols strain, 327 single nucleotide substitutions (224 transitions, 103 transversions), 14 deletions, and 18 insertions were found. On the proteome level, the highest frequency of amino acid-altering substitution polymorphisms was in novel genes, while the lowest was in housekeeping genes, as expected by their evolutionary conservation. Evidence was also found for hypervariable regions and multiple regions showing intrastrain heterogeneity in the T. pallidum chromosome. CONCLUSION: The observed genetic changes do not have influence on the ability of Treponema pallidum to cause syphilitic infection, since both SS14 and Nichols are virulent in rabbit. However, this is the first assessment of the degree of variation between the two syphilis pathogens and paves the way for phylogenetic studies of this fascinating organism.
Keywords: Animals; Chromosome Mapping; DNA Fingerprinting; Genome, Bacterial; Humans; Molecular Sequence Data; Oligonucleotide Array Sequence Analysis; Open Reading Frames; Polymorphism, Single Nucleotide; Rabbits; Reproducibility of Results; Sequence Analysis, DNA; Syphilis; Treponema pallidum

Genetic architecture of adiposity and organ weight using combined generation QTL analysis. - Fawcett, Gloria L; Roseman, Charles C; Jarvis, Joseph P; Wang, Bing; Wolf, Jason B; Cheverud, James M (Obesity (Silver Spring), 2008)
We present here a detailed study of the genetic contributions to adult body size and adiposity in the LG,SM advanced intercross line (AIL), an obesity model. This study represents a first step in fine-mapping obesity quantitative trait loci (QTLs) in an AIL. QTLs for adiposity in this model were previously isolated to chromosomes 1, 6, 7, 8, 9, 12, 13, and 18. This study focuses on heritable contributions and the genetic architecture of fatpad and organ weights. We analyzed both the F(2) and F(3) generations of the LG,SM AIL population single-nucleotide polymorphism (SNP) genotyped with a marker density of approximately 4 cM. We replicate 88% of the previously identified obesity QTLs and identify 13 new obesity QTLs. Nearly half of the single-trait QTLs were sex-specific. Several broad QTL regions were resolved into multiple, narrower peaks. The 113 single-trait QTLs for organs and body weight clustered into 27 pleiotropic loci. A large number of epistatic interactions are described which begin to elucidate potential interacting molecular networks. We present a relatively rapid means to obtain fine-mapping details from AILs using dense marker maps and consecutive generations. Analysis of the complex genetic architecture underlying fatpad and organ weights in this model may eventually help to elucidate not only heritable contributions to obesity but also common gene sets for obesity and its comorbidities.
Keywords: Adipose Tissue; Adiposity; Animals; Disease Models, Animal; Epistasis, Genetic; Female; Kidney; Liver; Male; Mice; Mice, Inbred Strains; Myocardium; Obesity; Organ Size; Quantitative Trait Loci; Sex Characteristics; Spleen

Genetic influences on behavioral inhibition and anxiety in juvenile rhesus macaques. - Rogers, J; Shelton, S E; Shelledy, W; Garcia, R; Kalin, N H (Genes Brain Behav, 2008)
In humans and other animals, behavioral responses to threatening stimuli are an important component of temperament. Among children, extreme behavioral inhibition elicited by novel situations or strangers predicts the subsequent development of anxiety disorders and depression. Genetic differences among children are known to affect risk of developing behavioral inhibition and anxiety, but a more detailed understanding of genetic influences on susceptibility is needed. Nonhuman primates provide valuable models for studying the mechanisms underlying human behavior. Individual differences in threat-induced behavioral inhibition (freezing behavior) in young rhesus monkeys are stable over time and reflect individual levels of anxiety. This study used the well-established human intruder paradigm to elicit threat-induced freezing behavior and other behavioral responses in 285 young pedigreed rhesus monkeys. We examined the overall influence of quantitative genetic variation and tested the specific effect of the serotonin transporter promoter repeat polymorphism. Quantitative genetic analyses indicated that the residual heritability of freezing duration (behavioral inhibition) is h(2) = 0.384 (P = 0.012) and of 'orienting to the intruder' (vigilance) is h(2) = 0.908 (P = 0.00001). Duration of locomotion and hostility and frequency of cooing were not significantly heritable. The serotonin transporter polymorphism showed no significant effect on either freezing or orienting to the intruder. Our results suggest that this species could be used for detailed studies of genetic mechanisms influencing extreme behavioral inhibition, including the identification of specific genes that are involved in predisposing individuals to such behavior.
Keywords: Animals; Anxiety Disorders; Behavior, Animal; Brain; Brain Chemistry; Disease Models, Animal; Fear; Female; Gene Expression Regulation, Developmental; Genetic Predisposition to Disease; Genetic Variation; Inhibition, Psychological; Macaca mulatta; Male; Neural Inhibition; Polymorphism, Single Nucleotide; Serotonin; Serotonin Plasma Membrane Transport Proteins; Social Behavior

The genome of the model beetle and pest Tribolium castaneum. - Stephen Richards; Richard A Gibbs; Weinstock, George M; Brown, Susan J; Denell, Robin; Beeman, Richard W; Richard A Gibbs; Beeman, Richard W; Brown, Susan J; Bucher, Gregor; Friedrich, Markus; Grimmelikhuijzen, Cornelis J P; et al. (Nature, 2008)
Tribolium castaneum is a member of the most species-rich eukaryotic order, a powerful model organism for the study of generalized insect development, and an important pest of stored agricultural products. We describe its genome sequence here. This omnivorous beetle has evolved the ability to interact with a diverse chemical environment, as shown by large expansions in odorant and gustatory receptors, as well as P450 and other detoxification enzymes. Development in Tribolium is more representative of other insects than is Drosophila, a fact reflected in gene content and function. For example, Tribolium has retained more ancestral genes involved in cell-cell communication than Drosophila, some being expressed in the growth zone crucial for axial elongation in short-germ development. Systemic RNA interference in T. castaneum functions differently from that in Caenorhabditis elegans, but nevertheless offers similar power for the elucidation of gene function and identification of targets for selective insect control.
Keywords: Animals; Base Composition; Body Patterning; Cytochrome P-450 Enzyme System; DNA Transposable Elements; Genes, Insect; Genome, Insect; Growth and Development; Humans; Insecticides; Neurotransmitter Agents; Oogenesis; Phylogeny; Proteome; Receptors, G-Protein-Coupled; Receptors, Odorant; Repetitive Sequences, Nucleic Acid; RNA Interference; Taste; Telomere; Tribolium; Vision, Ocular

A genomewide linkage scan for quantitative trait loci influencing the craniofacial complex in baboons (Papio hamadryas spp.). - Sherwood, Richard J; Duren, Dana L; Havill, Lorena M; Jeffrey Rogers; Cox, Laura A; Towne, Bradford; Mahaney, Michael C (Genetics, 2008)
Numerous studies have detected significant contributions of genes to variation in development, size, and shape of craniofacial traits in a number of vertebrate taxa. This study examines 43 quantitative traits derived from lateral cephalographs of 830 baboons (Papio hamadryas) from the pedigreed population housed at the Southwest National Primate Research Center. Quantitative genetic analyses were conducted using the SOLAR analytic platform, a maximum-likelihood variance components method that incorporates all familial information for parameter estimation. Heritability estimates were significant and of moderate to high magnitude for all craniofacial traits. Additionally, 14 significant quantitative trait loci (QTL) were identified for 12 traits from the three developmental components (basicranium, splanchnocranium, and neurocranium) of the craniofacial complex. These QTL were found on baboon chromosomes (and human orthologs) PHA1 (HSA1), PHA 2 (HSA3), PHA4 (HSA6), PHA11 (HSA12), PHA13 (HSA2), PHA16 (HSA17), and PHA17 (HSA13) (PHA, P. hamadryas; HSA, Homo sapiens). This study of the genetic architecture of the craniofacial complex in baboons provides the groundwork needed to establish the baboon as an animal model for the study of genetic and nongenetic influences on craniofacial variation.
Keywords: Animals; Anthropometry; Female; Genetic Linkage; Genetic Variation; Genome; Humans; Likelihood Functions; Male; Models, Biological; Models, Genetic; Papio hamadryas; Quantitative Trait Loci; Skull; Species Specificity

Genomic imprinting effects on adult body composition in mice. - Cheverud, James M; Hager, Reinmar; Roseman, Charles; Fawcett, Gloria; Wang, Bing; Wolf, Jason B (Proc Natl Acad Sci U S A, 2008)
Genomic imprinting results in the differential expression of genes, depending on which allele is inherited from the mother and which from the father. The effects of such differential gene expression are reflected in phenotypic differences between the reciprocal heterozygotes (Aa vs. aA). Although many imprinted genes have been identified and play a key role in development, little is known about the contribution of imprinting to quantitative variation in trait expression. Here, we examine this problem by mapping imprinting effects on adult body composition traits in the F(3) generation of an intercross between the Large (LG/J) and Small (SM/J) inbred mouse strains. We identified eight pleiotropic imprinted quantitative trait loci (iQTL) located throughout the genome. Most iQTL are in novel locations that have not previously been associated with imprinting effects, but those on chromosomes 7, 12, and centromeric 18 lie in regions previously identified as containing imprinted genes. Our results show that the effects of genomic imprinting are relatively small, with reciprocal heterozygotes differing by approximately 0.25 standard deviation units and the effects at each locus accounting for 1% to 4% of the phenotypic variance. We detected a variety of imprinting patterns, with paternal expression being the most common. These results indicate that genomic imprinting has small, but detectable, effects on the normal variation of complex traits in adults and is likely to be more common than usually thought.
Keywords: Aging; Animals; Body Composition; Body Weight; Female; Genomic Imprinting; Male; Mice; Quantitative Trait Loci

Genotype-by-diet effects on co-variation in Lp-PLA2 activity and LDL-cholesterol concentration in baboons fed an atherogenic diet. - Vinson, Amanda; Mahaney, Michael C; Diego, Vince P; Cox, Laura A; Jeffrey Rogers; VandeBerg, John L; Rainwater, David L (J Lipid Res, 2008)
Both lipoprotein-associated phospholipase A(2) (Lp-PLA(2)) activity, a biomarker of inflammation, and concentration of its primary associated lipoprotein, LDL, are correlated with adverse coronary outcomes. We previously reported a quantitative trait locus (QTL) corresponding to HSA2p24.3-p23.2 with pleiotropic effects on Lp-PLA(2) activity and LDL-cholesterol (LDL-C) concentration in baboons fed a basal diet. Here, our goal was to locate pleiotropic QTLs influencing both traits in the same baboons fed a high-cholesterol, high-fat (HCHF) diet, and to assess whether shared genetic effects on these traits differ between diets. We assayed Lp-PLA(2) activity and LDL-C concentration in 683 baboons fed the HCHF diet. We used a bivariate maximum likelihood-based variance components approach in whole-genome linkage screens to locate a QTL [logarithm of odds (LOD) = 3.13, genome-wide P = 0.019] corresponding to HSA19q12-q13.2 with pleiotropic effects on Lp-PLA(2) activity and LDL-C levels in the HCHF diet. We additionally found significant evidence of genetic variance in response to diet for Lp-PLA(2) activity (P = 0.0017) and for LDL-C concentration (P = 0.00001), revealing a contribution of genotype-by-diet interaction to covariation in these two traits. We conclude that the pleiotropic QTLs detected at 2p24.3-p23.2 and 19q12-q13.2 on the basal and HCHF diets, respectively, exert diet-specific effects on covariation in Lp-PLA(2) activity and LDL-C concentration.
Keywords: 1-Alkyl-2-acetylglycerophosphocholine Esterase; Animals; Cholesterol, LDL; Dietary Fats; Female; Genetic Predisposition to Disease; Genotype; Male; Papio; Quantitative Trait Loci; Risk Factors

Hepatocyte nuclear factor 1 and hypertensive nephropathy. - Dmitrieva, Renata I; Hinojos, Cruz A; Eric Boerwinkle; Braun, Michael C; Fornage, Myriam; Doris, Peter A (Hypertension, 2008)
Hypertension in spontaneously hypertensive rat (SHR) is associated with renal redox stress, and we hypothesized that nephropathy arises in SHR-A3 from altered capacity to mitigate redox stress compared with nephropathy-resistant SHR lines. We measured renal expression of redox genes in distinct lines of the spontaneously hypertensive rat (SHR-A3, SHR-B2, SHR-C) and the normotensive Wistar-Kyoto (WKY) strain. The SHR lines differ in either resisting (SHR-B2, SHR-C) or experiencing hypertensive nephropathy (SHR-A3). Immediately before the emergence of hypertensive renal injury expression of redox genes in SHR-A3 was profoundly altered compared with the injury-resistant SHR lines and WKY. This change appeared to arise in antioxidant genes where 16 of 28 were expressed at 34.3% of the level in the reference strain (WKY). No such change was observed in the injury-resistant SHR lines. We analyzed occurrence of transcription factor matrices in the promoters of the downregulated antioxidant genes. In these genes, the hepatocyte nuclear factor 1 (HNF1) transcription factor matrix was found to be nearly twice as likely to be present and the overall frequency of HNF1 sites was nearly 5 times higher, compared with HNF1 transcription factor matrices in antioxidant genes that were not downregulated. We identified 35 other (nonredox) renal genes regulated by HNF1. These were also significantly downregulated in SHR-A3, but not in SHR-B2 or SHR-C. Finally, expression of genes that comprise HNF1 (Tcf1, Tcf2, and Dcoh) was also downregulated in SHR-A3. The present experiments uncover a major change in transcriptional control by HNF1 that affects redox and other genes and precedes emergence of hypertensive renal injury.
Keywords: Animal Feed; Animals; Blood Pressure; Gene Expression Profiling; Hepatocyte Nuclear Factor 1; Hypertension, Renal; Kidney; Male; Oxidation-Reduction; Oxidative Stress; Rats; Rats, Inbred SHR; Rats, Inbred WKY; Transcription, Genetic

Identification of quantitative trait loci affecting murine long bone length in a two-generation intercross of LG/J and SM/J Mice. - Norgard, Elizabeth A; Roseman, Charles C; Fawcett, Gloria L; Pavlicev, Mihaela; Morgan, Clinton D; Pletscher, L Susan; Wang, Bing; Cheverud, James M (J Bone Miner Res, 2008)
INTRODUCTION: Study of mutations with large phenotypic effects has allowed the identification of key players in skeletal development. However, the molecular nature of variation in large, phenotypically normal populations tends to be characterized by smaller phenotypic effects that remain undefined. MATERIALS AND METHODS: We use interval mapping and quantitative trait locus (QTL) mapping techniques in the combined F2-F3 populations (n = 2111) of an LG/J x SM/J mouse intercross to detect QTLs associated with the lengths of the humerus, ulna, femur, and tibia. RESULTS: Seventy individual trait QTLs affecting long bone lengths were detected, with several chromosomes harboring multiple QTLs. The genetic architecture suggests mainly small, additive effects on long bone length, with roughly one third of the QTLs displaying dominance. Sex interactions were common, and four sex-specific QTLs were observed. Pleiotropy could not be rejected for most of the QTLs identified. Thirty-one epistatic interactions were detected, almost all affecting regions including or immediately adjacent to QTLs. CONCLUSIONS: A complex regulatory network with many gene interactions modulates bone growth, possibly with integrated skeletal modules that allow fine-tuning of developmental processes present. Candidate genes in the QTL CIs include many genes known to affect endochondral bone growth and genes that have not yet been associated with bone growth or body size but have a strong potential to influence these traits.
Keywords: Animals; Bone and Bones; Chromosomes; Epistasis, Genetic; Female; Male; Mice; Quantitative Trait Loci

Large scale variation in Enterococcus faecalis illustrated by the genome analysis of strain OG1RF. - Bourgogne, Agathe; Garsin, Danielle A; Xiang Qin; Singh, Kavindra V; Sillanpaa, Jouko; Yerrapragada, Shailaja; Ding, Yan; Dugan-Rocha, Shannon; Buhay, Christian; Shen, Hua; Chen, Guan; Williams, Gabrielle; et al. (Genome Biol, 2008)
BACKGROUND: Enterococcus faecalis has emerged as a major hospital pathogen. To explore its diversity, we sequenced E. faecalis strain OG1RF, which is commonly used for molecular manipulation and virulence studies. RESULTS: The 2,739,625 base pair chromosome of OG1RF was found to contain approximately 232 kilobases unique to this strain compared to V583, the only publicly available sequenced strain. Almost no mobile genetic elements were found in OG1RF. The 64 areas of divergence were classified into three categories. First, OG1RF carries 39 unique regions, including 2 CRISPR loci and a new WxL locus. Second, we found nine replacements where a sequence specific to V583 was substituted by a sequence specific to OG1RF. For example, the iol operon of OG1RF replaces a possible prophage and the vanB transposon in V583. Finally, we found 16 regions that were present in V583 but missing from OG1RF, including the proposed pathogenicity island, several probable prophages, and the cpsCDEFGHIJK capsular polysaccharide operon. OG1RF was more rapidly but less frequently lethal than V583 in the mouse peritonitis model and considerably outcompeted V583 in a murine model of urinary tract infections. CONCLUSION: E. faecalis OG1RF carries a number of unique loci compared to V583, but the almost complete lack of mobile genetic elements demonstrates that this is not a defining feature of the species. Additionally, OG1RF's effects in experimental models suggest that mediators of virulence may be diverse between different E. faecalis strains and that virulence is not dependent on the presence of mobile genetic elements.
Keywords: Animals; Anti-Bacterial Agents; Bacterial Proteins; Biofilms; DNA, Bacterial; Drug Resistance, Bacterial; Enterococcus faecalis; Fusidic Acid; Genetic Variation; Genome, Bacterial; Genomics; Interspersed Repetitive Sequences; Membrane Proteins; Mice; Operon; Repetitive Sequences, Nucleic Acid; Rifampin; Sequence Homology, Nucleic Acid

Mouse let-7 miRNA populations exhibit RNA editing that is constrained in the 5'-seed/ cleavage/anchor regions and stabilize predicted mmu-let-7a:mRNA duplexes. - Reid, Jeffrey G; Nagaraja, Ankur K; Lynn, Francis C; Drabek, Rafal B; Donna M Muzny; Shaw, Chad A; Weiss, Michelle K; Naghavi, Arash O; Khan, Mahjabeen; Zhu, Huifeng; Tennakoon, Jayantha; Gunaratne, Gemunu H; et al. (Genome Res, 2008)
Massively parallel sequencing of millions of < 30-nt RNAs expressed in mouse ovary, embryonic pancreas (E14.5), and insulin-secreting beta-cells (betaTC-3) reveals that approximately 50% of the mature miRNAs representing mostly the mmu-let-7 family display internal insertion/deletions and substitutions when compared to precursor miRNA and the mouse genome reference sequences. Approximately, 12%-20% of species associated with mmu-let-7 populations exhibit sequence discrepancies that are dramatically reduced in nucleotides 3-7 (5'-seed) and 10-15 (cleavage and anchor sites). This observation is inconsistent with sequencing error and leads us to propose that the changes arise predominantly from post-transcriptional RNA-editing activity operating on miRNA:target mRNA complexes. Internal nucleotide modifications are most enriched at the ninth nucleotide position. A common ninth base edit of U-to-G results in a significant increase in stability of down-regulated let-7a targets in inhibin-deficient mice (Inha-/-). An excess of U-insertions (14.8%) over U-deletions (1.5%) and the presence of cleaved intermediates suggest that a mammalian TUTase (terminal uridylyl transferase) mediated dUTP-dependent U-insertion/U-deletion cycle may be a possible mechanism. We speculate that mRNA target site-directed editing of mmu-let-7a duplex-bulges stabilizes "loose" miRNA:mRNA target associations and functions to expand the target repertoire and/or enhance mRNA decay over translational repression. Our results also demonstrate that the systematic study of sequence variation within specific RNA classes in a given cell type from millions of sequences generated by next-generation sequencing (NGS) technologies ("intranomics") can be used broadly to infer functional constraints on specific parts of completely uncharacterized RNAs.
Keywords: Animals; Base Sequence; Cells, Cultured; Deoxyuracil Nucleotides; Embryo, Mammalian; Female; Mice; MicroRNAs; Molecular Sequence Data; Nucleic Acid Conformation; RNA Editing; RNA Nucleotidyltransferases; RNA Stability; RNA, Messenger; RNA, Small Untranslated

Nonhuman primates as models for studies of prostate specific antigen and prostatic diseases. - Mubiru, James N; Hubbard, Gene B; Dick, Edward J; Furman, Jaime; Troyer, Dean A; Jeffrey Rogers (Prostate, 2008)
BACKGROUND: Because prostate specific antigen (PSA) is released at increased levels into the blood early in the development of prostate cancer, benign prostatic hyperplasia (BPH) and prostatitis, it is widely used as a marker for these diseases. However, PSA has clinical limitations as a screen for prostatic diseases due to its low sensitivity and specificity. There is a strong need to better understand the biology of PSA and factors affecting its serum levels. METHODS: We evaluated cynomolgus macaques, rhesus macaques, baboons, and marmosets for their suitability as models for the study of PSA biology and prostatic diseases. RESULTS: Prostates of several nonhuman primates are anatomically similar to the human counterpart. Anti-human PSA antibody detected PSA antigens in all the Old World monkeys (cynomolgus macaques, rhesus macaques, and baboons) but not in marmosets. Of the Old World monkeys, cynomolgus macaques have the highest serum PSA levels; baboons have the lowest. Serum PSA levels from macaques includes a number of outlier samples with unusually high values. We also report two cases of abnormal pathologies in macaques accompanied by high serum PSA levels. One case consisted of prostatic hyperplasia involving both glandular and basal cells in a cynomolgus macaque and another of glandular hyperplasia and atrophy in a rhesus macaque. The finding that pathological changes in the prostate of macaques may lead to increases in serum PSA is worthy of further exploration. CONCLUSION: Cynomolgus macaques and rhesus macaques are promising animal models for PSA biology studies.
Keywords: Animals; Body Weight; Callithrix; Disease Models, Animal; Haplorhini; Immunoblotting; Macaca fascicularis; Macaca mulatta; Male; Organ Size; Papio; Prostate-Specific Antigen; Prostatic Hyperplasia; Prostatic Neoplasms; Racemases and Epimerases; Reverse Transcriptase Polymerase Chain Reaction; RNA

Novel microRNA candidates and miRNA-mRNA pairs in embryonic stem (ES) cells. - Gu, Peili; Reid, Jeffrey G; Gao, Xiaolian; Shaw, Chad A; Creighton, Chad; Tran, Peter L; Zhou, Xiaochuan; Drabek, Rafal B; Steffen, David L; Hoang, David M; Weiss, Michelle K; Naghavi, Arash O; et al. (PLoS One, 2008)
BACKGROUND: MicroRNAS (miRNAS: a class of short non-coding RNAs) are emerging as important agents of post transcriptional gene regulation and integral components of gene networks. MiRNAs have been strongly linked to stem cells, which have a remarkable dual role in development. They can either continuously replenish themselves (self-renewal), or differentiate into cells that execute a limited number of specific actions (pluripotence). METHODOLOGY/PRINCIPAL FINDINGS: In order to identify novel miRNAs from narrow windows of development we carried out an in silico search for micro-conserved elements (MCE) in adult tissue progenitor transcript sequences. A plethora of previously unknown miRNA candidates were revealed including 545 small RNAs that are enriched in embryonic stem (ES) cells over adult cells. Approximately 20% of these novel candidates are down-regulated in ES (Dicer(-/-)) ES cells that are impaired in miRNA maturation. The ES-enriched miRNA candidates exhibit distinct and opposite expression trends from mmu-mirs (an abundant class in adult tissues) during retinoic acid (RA)-induced ES cell differentiation. Significant perturbation of trends is found in both miRNAs and novel candidates in ES (GCNF(-/-)) cells, which display loss of repression of pluripotence genes upon differentiation. CONCLUSION/SIGNIFICANCE: Combining expression profile information with miRNA target prediction, we identified miRNA-mRNA pairs that correlate with ES cell pluripotence and differentiation. Perturbation of these pairs in the ES (GCNF(-/-)) mutant suggests a role for miRNAs in the core regulatory networks underlying ES cell self-renewal, pluripotence and differentiation.
Keywords: Algorithms; Animals; Blotting, Northern; Cell Differentiation; Computational Biology; Conserved Sequence; Embryonic Stem Cells; False Positive Reactions; Humans; MicroRNAs; Models, Biological; Models, Genetic; RNA, Messenger; Time Factors; Tretinoin

Pash 2.0: scaleable sequence anchoring for next-generation sequencing technologies. - Coarfa, Cristian; Milosavljevic, Aleksandar (Pac Symp Biocomput, 2008)
Many applications of next-generation sequencing technologies involve anchoring of a sequence fragment or a tag onto a corresponding position on a reference genome assembly. Positional Hashing method, implemented in the Pash 2.0 program, is specifically designed for the task of high-volume anchoring. In this article we present multi-diagonal gapped kmer collation and other improvements introduced in Pash 2.0 that further improve accuracy and speed of Positional Hashing. The goal of this article is to show that gapped kmer matching with cross-diagonal collation suffices for anchoring across close evolutionary distances and for the purpose of human resequencing. We propose a benchmark for evaluating the performance of anchoring programs that captures key parameters in specific applications, including duplicative structure of genomes of humans and other species. We demonstrate speedups of up to tenfold in large-scale anchoring experiments achieved by PASH 2.0 when compared to BLAT, another similarity search program frequently used for anchoring.
Keywords: Algorithms; Animals; Computational Biology; Databases, Genetic; Evolution, Molecular; Genome, Human; Humans; Sensitivity and Specificity; Sequence Alignment; Software

PDX-1 acts as a potential molecular target for treatment of human pancreatic cancer. - Liu, Shihe; Ballian, Nikiforos; Belaguli, Narasimhaswamy S; Patel, Sanjeet; Li, Min; Templeton, Nancy Smyth; Marie-Claude Gingras; Richard A Gibbs; Fisher, William; Brunicardi, F Charles (Pancreas, 2008)
OBJECTIVES: The purpose of this study was to investigate whether pancreatic and duodenal homeobox factor 1 (PDX-1) could serve as a potential molecular target for the treatment of pancreatic cancer. METHODS: Cell proliferation, invasion capacity, and protein levels of cell cycle mediators were determined in human pancreatic cancer cells transfected with mouse PDX-1 (mPDX-1) alone or with mPDX-1 short hairpin RNA (shRNA) and/or human PDX-1 shRNA (huPDX-1 shRNA). Tumor cell growth and apoptosis were also evaluated in vivo in PANC-1 tumor-bearing severe combined immunodeficient mice receiving multiple treatments of intravenous liposomal huPDX-1 shRNA. RESULTS: mPDX-1 overexpression resulted in the significant increase of cell proliferation and invasion in MIA PaCa2, but not PANC-1 cells. This effect was blocked by knocking down mPDX-1 expression with mPDX-1 shRNA. Silencing of huPDX-1 expression in PANC-1 cells inhibited cell proliferation in vitro and suppressed tumor growth in vivo which was associated with increased tumor cell apoptosis. PDX-1 overexpression resulted in dysregulation of the cell cycle with up-regulation of cyclin D, cyclin E, and Cdk2 and down-regulation of p27. CONCLUSIONS: PDX-1 regulates cell proliferation and invasion in human pancreatic cancer cells. Down-regulation of PDX-1 expression inhibits pancreatic cancer cell growth in vitro and in vivo, implying its use as a potential therapeutic target for the treatment of pancreatic cancer.
Keywords: Animals; Base Sequence; Biomarkers, Tumor; Cell Line, Tumor; Cell Proliferation; Homeodomain Proteins; Humans; Islets of Langerhans; Male; Mice; Mice, SCID; Molecular Sequence Data; Neoplasm Invasiveness; Neoplasm Transplantation; Pancreatic Neoplasms; RNA Interference; RNA, Small Interfering; Trans-Activators; Transfection; Transplantation, Heterologous

Pleiotropic patterns of quantitative trait loci for 70 murine skeletal traits. - Kenney-Hunt, Jane P; Wang, Bing; Norgard, Elizabeth A; Fawcett, Gloria; Falk, Doug; Pletscher, L Susan; Jarvis, Joseph P; Roseman, Charles; Wolf, Jason; Cheverud, James M (Genetics, 2008)
Quantitative trait locus (QTL) studies of a skeletal trait or a few related skeletal components are becoming commonplace, but as yet there has been no investigation of pleiotropic patterns throughout the skeleton. We present a comprehensive survey of pleiotropic patterns affecting mouse skeletal morphology in an intercross of LG/J and SM/J inbred strains (N = 1040), using QTL analysis on 70 skeletal traits. We identify 798 single-trait QTL, coalescing to 105 loci that affect on average 7-8 traits each. The number of traits affected per locus ranges from only 1 trait to 30 traits. Individual traits average 11 QTL each, ranging from 4 to 20. Skeletal traits are affected by many, small-effect loci. Significant additive genotypic values average 0.23 standard deviation (SD) units. Fifty percent of loci show codominance with heterozygotes having intermediate phenotypic values. When dominance does occur, the LG/J allele tends to be dominant to the SM/J allele (30% vs. 8%). Over- and underdominance are relatively rare (12%). Approximately one-fifth of QTL are sex specific, including many for pelvic traits. Evaluating the pleiotropic relationships of skeletal traits is important in understanding the role of genetic variation in the growth and development of the skeleton.
Keywords: Animals; Bone and Bones; Chromosomes, Mammalian; Mice; Quantitative Trait Loci; Quantitative Trait, Heritable

A pleiotropic QTL on 2p influences serum Lp-PLA2 activity and LDL cholesterol concentration in a baboon model for the genetics of atherosclerosis risk factors. - Vinson, A; Mahaney, M C; Cox, L A; Rogers, J; VandeBerg, J L; Rainwater, D L (Atherosclerosis, 2008)
Lipoprotein-associated phospholipase A(2) (Lp-PLA(2)), the major portion of which is bound to low-density lipoprotein, is an independent biomarker of cardiovascular disease risk. To search for common genetic determinants of variation in both Lp-PLA(2) activity and LDL cholesterol (LDL-C) concentration, we assayed these substances in serum from 679 pedigreed baboons. Using a maximum likelihood-based variance components approach, we detected significant evidence for a QTL affecting Lp-PLA(2) activity (LOD=2.79, genome-wide P=0.039) and suggestive evidence for a QTL affecting LDL-C levels (LOD=2.16) at the same location on the baboon ortholog of human chromosome 2p. Because we also found a significant genetic correlation between the two traits (rho(G)=0.50, P<0.00001), we conducted bivariate linkage analyses of Lp-PLA(2) activity and LDL-C concentration. These bivariate analyses improved the evidence (LOD=3.19, genome-wide P=0.015) for a QTL at the same location on 2p, corresponding to the human cytogenetic region 2p24.3-p23.2. The QTL-specific correlation between the traits (rho(Q)=0.62) was significantly different from both zero and 1 (P[rho(Q)=0]=0.047; P[rho(Q)=1]=0.022), rejecting the hypothesis of co-incident linkage and consistent with incomplete pleiotropy at this locus. We conclude that polymorphisms at the QTL described in this study exert some genetic effects that are shared between Lp-PLA(2) activity and LDL-C concentration.
Keywords: 1-Alkyl-2-acetylglycerophosphocholine Esterase; Animals; Atherosclerosis; Cholesterol, LDL; Disease Models, Animal; Female; Male; Multivariate Analysis; Papio hamadryas; Quantitative Trait Loci; Risk Factors

Progress and prospects in rat genetics: a community view. - Aitman, Timothy J; Critser, John K; Cuppen, Edwin; Dominiczak, Anna; Fernandez-Suarez, Xose M; Flint, Jonathan; Gauguier, Dominique; Geurts, Aron M; Gould, Michael; Harris, Peter C; Holmdahl, Rikard; Hübner, Norbert; et al. (Nat Genet, 2008)
The rat is an important system for modeling human disease. Four years ago, the rich 150-year history of rat research was transformed by the sequencing of the rat genome, ushering in an era of exceptional opportunity for identifying genes and pathways underlying disease phenotypes. Genome-wide association studies in human populations have recently provided a direct approach for finding robust genetic associations in common diseases, but identifying the precise genes and their mechanisms of action remains problematic. In the context of significant progress in rat genomic resources over the past decade, we outline achievements in rat gene discovery to date, show how these findings have been translated to human disease, and document an increasing pace of discovery of new disease genes, pathways and mechanisms. Finally, we present a set of principles that justify continuing and strengthening genetic studies in the rat model, and further development of genomic infrastructure for rat research.
Keywords: Animals; Animals, Genetically Modified; Chromosome Mapping; Disease Models, Animal; Gene Targeting; Genetic Diseases, Inborn; Genome; Genomics; Humans; Rats

Pulmonary alveolar proteinosis caused by deletion of the GM-CSFRalpha gene in the X chromosome pseudoautosomal region 1. - Martinez-Moczygemba, Margarita; Doan, Minh L; Elidemir, Okan; Fan, Leland L; Cheung, Sau Wai; Lei, Jonathan T; Moore, James P; Tavana, Ghamartaj; Lewis, Lora R; Zhu, Yiming; Donna M Muzny; Richard A Gibbs; et al. (J Exp Med, 2008)
Pulmonary alveolar proteinosis (PAP) is a rare lung disorder in which surfactant-derived lipoproteins accumulate excessively within pulmonary alveoli, causing severe respiratory distress. The importance of granulocyte/macrophage colony-stimulating factor (GM-CSF) in the pathogenesis of PAP has been confirmed in humans and mice, wherein GM-CSF signaling is required for pulmonary alveolar macrophage catabolism of surfactant. PAP is caused by disruption of GM-CSF signaling in these cells, and is usually caused by neutralizing autoantibodies to GM-CSF or is secondary to other underlying diseases. Rarely, genetic defects in surfactant proteins or the common beta chain for the GM-CSF receptor (GM-CSFR) are causal. Using a combination of cellular, molecular, and genomic approaches, we provide the first evidence that PAP can result from a genetic deficiency of the GM-CSFR alpha chain, encoded in the X-chromosome pseudoautosomal region 1.
Keywords: Animals; CD11b Antigen; Child, Preschool; Chromosomes, Human, X; Exons; Female; Genotype; Granulocyte-Macrophage Colony-Stimulating Factor; Humans; In Situ Hybridization, Fluorescence; Karyotyping; Male; Mice; Monocytes; Pulmonary Alveolar Proteinosis; Pulmonary Surfactants; Receptors, Granulocyte-Macrophage Colony-Stimulating Factor; Signal Transduction; Turner Syndrome

Quantitative monitoring of adenocarcinoma development in rodents by magnetic resonance imaging. - Garbow, Joel R; Wang, Min; Wang, Yian; Lubet, Ronald A; You, Ming (Clin Cancer Res, 2008)
PURPOSE: Accurately following the time course of tumor progression and response to therapy in animal models of cancer is key to the development of better chemopreventive and chemotherapeutic agents. The goal of this work was to monitor quantitatively the development and progression of adenocarcinoma in a time course study of mice treated with the carcinogen urethane using in vivo small-animal magnetic resonance imaging (MRI). EXPERIMENTAL DESIGN: Mice treated with a single dose of urethane were imaged at four time points beginning 8 months after treatment. High-resolution images of mouse lung were obtained in vivo using respiratory-gated MRI methods. Individual tumors were manually segmented and their volumes calculated. At the end of the study, mice were euthanized and MRI tumor quantification was validated by histology and histopathology. RESULTS: Tumors as small as 0.4 mm in diameter can be detected and quantitatively measured in mice by in vivo MRI. Total tumor burden increased consistently in all mice studied, whereas the growth rate of individual tumors varied widely. The positions and diameters of individual tumors as measured by MRI correlated well with histology results. Histologic study of large, rapidly growing tumors showed that these were adenocarcinomas, whereas small, slowly growing lesions were predominantly adenomas. CONCLUSIONS: Longitudinal in vivo MRI is a powerful modality that can be of great aid in elucidating the factors that control the onset of lung tumors and can serve as a platform for the development and preclinical testing of novel therapies having a high likelihood of efficacy in human clinical trials.
Keywords: Adenocarcinoma; Animals; Carcinogens; Disease Models, Animal; Image Interpretation, Computer-Assisted; Image Processing, Computer-Assisted; Lung Neoplasms; Magnetic Resonance Imaging; Male; Mice; Mice, Inbred A; Urethane

Rats in the genomic era. - Kim C Worley; Weinstock, G M; Richard A Gibbs (Physiol Genomics, 2008)
The rat genome project and the resources that it has generated are transforming the translation of rat biology to human medicine. The rat genome was sequenced to a high quality "draft," the structure and location of the genes were predicted, and a global assessment was published (Gibbs RA et al., Nature 428: 493-521, 2004). Since that time, researchers have made use of the genome sequence and annotations and related resources. We take this opportunity to review the currently available rat genome resources and to discuss the progress and future plans for the rat genome.
Keywords: Animals; Chromosomes, Artificial, Bacterial; Female; Genome; Genomic Library; Genomics; Humans; Mice; National Heart, Lung, and Blood Institute (U.S.); National Human Genome Research Institute (U.S.); Polymorphism, Single Nucleotide; Rats; United States

The serotonin transporter genotype is associated with intermediate brain phenotypes that depend on the context of eliciting stressor. - Kalin, N H; Shelton, S E; Fox, A S; Rogers, J; Oakes, T R; Davidson, R J (Mol Psychiatry, 2008)
A variant allele in the promoter region of the serotonin transporter gene, SLC6A4, the s allele, is associated with increased vulnerability to develop anxiety-related traits and depression. Furthermore, functional magnetic resonance imaging (fMRI) studies reveal that s carriers have increased amygdala reactivity in response to aversive stimuli, which is thought to be an intermediate phenotype mediating the influences of the s allele on emotionality. We used high-resolution microPET [18F]fluoro-2-deoxy-D-glucose (FDG) scanning to assess regional brain metabolic activity in rhesus monkeys to further explore s allele-related intermediate phenotypes. Rhesus monkeys provide an excellent model to understand mechanisms underlying human anxiety, and FDG microPET allows for the assessment of brain activity associated with naturalistic environments outside the scanner. During FDG uptake, monkeys were exposed to different ethologically relevant stressful situations (relocation and threat) as well as to the less stressful familiar environment of their home cage. The s carriers displayed increased orbitofrontal cortex activity in response to both relocation and threat. However, during relocation they displayed increased amygdala reactivity and in response to threat they displayed increased reactivity of the bed nucleus of the stria terminalis. No increase in the activity of any of these regions occurred when the animals were administered FDG in their home cages. These findings demonstrate context-dependent intermediate phenotypes in s carriers that provide a framework for understanding the mechanisms underlying the vulnerabilities of s-allele carriers exposed to different types of stressors.
Keywords: Animals; Behavior, Animal; Brain; Brain Mapping; Disease Models, Animal; Female; Fluorodeoxyglucose F18; Genotype; Macaca mulatta; Male; Phenotype; Polymorphism, Genetic; Positron-Emission Tomography; Serotonin Plasma Membrane Transport Proteins; Stress, Psychological

What everybody should know about the rat genome and its online resources. - Twigger, Simon N; Pruitt, Kim D; Fernandez-Suarez, Xose M; Karolchik, Donna; Worley, Kim C; Maglott, Donna R; Brown, Garth; Weinstock, George; Richard A Gibbs; Kent, Jim; Birney, Ewan; Jacob, Howard J (Nat Genet, 2008)
It has been four years since the original publication of the draft sequence of the rat genome. Five groups are now working together to assemble, annotate and release an updated version of the rat genome. As the prevailing model for physiology, complex disease and pharmacological studies, there is an acute need for the rat's genomic resources to keep pace with the rat's prominence in the laboratory. In this commentary, we describe the current status of the rat genome sequence and the plans for its impending 'upgrade'. We then cover the key online resources providing access to the rat genome, including the new SNP views at Ensembl, the RefSeq and Genes databases at the US National Center for Biotechnology Information, Genome Browser at the University of California Santa Cruz and the disease portals for cardiovascular disease and obesity at the Rat Genome Database.
Keywords: Animals; Computational Biology; Databases, Genetic; Disease Models, Animal; Genetic Diseases, Inborn; Genetic Variation; Genome; Genomics; Haplotypes; Humans; Internet; Polymorphism, Single Nucleotide; Rats; Rats, Mutant Strains; Sequence Analysis, DNA

28-way vertebrate alignment and conservation track in the UCSC Genome Browser. - Miller, Webb; Rosenbloom, Kate; Hardison, Ross C; Hou, Minmei; Taylor, James; Raney, Brian; Burhans, Richard; King, David C; Baertsch, Robert; Blankenberg, Daniel; Kosakovsky Pond, Sergei L; Nekrutenko, Anton; et al. (Genome Res, 2007)
This article describes a set of alignments of 28 vertebrate genome sequences that is provided by the UCSC Genome Browser. The alignments can be viewed on the Human Genome Browser (March 2006 assembly) at http://genome.ucsc.edu, downloaded in bulk by anonymous FTP from http://hgdownload.cse.ucsc.edu/goldenPath/hg18/multiz28way, or analyzed with the Galaxy server at http://g2.bx.psu.edu. This article illustrates the power of this resource for exploring vertebrate and mammalian evolution, using three examples. First, we present several vignettes involving insertions and deletions within protein-coding regions, including a look at some human-specific indels. Then we study the extent to which start codons and stop codons in the human sequence are conserved in other species, showing that start codons are in general more poorly conserved than stop codons. Finally, an investigation of the phylogenetic depth of conservation for several classes of functional elements in the human genome reveals striking differences in the rates and modes of decay in alignability. Each functional class has a distinctive period of stringent constraint, followed by decays that allow (for the case of regulatory regions) or reject (for coding regions and ultraconserved elements) insertions and deletions.
Keywords: Animals; Base Sequence; Cats; Cattle; Codon, Initiator; Codon, Terminator; Conserved Sequence; Databases, Genetic; Dogs; Genome, Human; Guinea Pigs; Humans; Mice; Molecular Sequence Data; Mutagenesis, Insertional; Rabbits; Rats; Sequence Alignment; Sequence Deletion

Analyses of deep mammalian sequence alignments and constraint predictions for 1% of the human genome. - Margulies, Elliott H; Cooper, Gregory M; Asimenos, George; Thomas, Daryl J; Dewey, Colin N; Siepel, Adam; Birney, Ewan; Keefe, Damian; Schwartz, Ariel S; Hou, Minmei; Taylor, James; Nikolaev, Sergey; et al. (Genome Res, 2007)
A key component of the ongoing ENCODE project involves rigorous comparative sequence analyses for the initially targeted 1% of the human genome. Here, we present orthologous sequence generation, alignment, and evolutionary constraint analyses of 23 mammalian species for all ENCODE targets. Alignments were generated using four different methods; comparisons of these methods reveal large-scale consistency but substantial differences in terms of small genomic rearrangements, sensitivity (sequence coverage), and specificity (alignment accuracy). We describe the quantitative and qualitative trade-offs concomitant with alignment method choice and the levels of technical error that need to be accounted for in applications that require multisequence alignments. Using the generated alignments, we identified constrained regions using three different methods. While the different constraint-detecting methods are in general agreement, there are important discrepancies relating to both the underlying alignments and the specific algorithms. However, by integrating the results across the alignments and constraint-detecting methods, we produced constraint annotations that were found to be robust based on multiple independent measures. Analyses of these annotations illustrate that most classes of experimentally annotated functional elements are enriched for constrained sequences; however, large portions of each class (with the exception of protein-coding sequences) do not overlap constrained regions. The latter elements might not be under primary sequence constraint, might not be constrained across all mammals, or might have expendable molecular functions. Conversely, 40% of the constrained sequences do not overlap any of the functional elements that have been experimentally identified. Together, these findings demonstrate and quantify how many genomic functional elements await basic molecular characterization.
Keywords: Animals; Evolution, Molecular; Genome, Human; Human Genome Project; Humans; Mammals; Open Reading Frames; Phylogeny; Sequence Alignment

Corticotropin releasing hormone (CRH) gene variation: comprehensive resequencing for variant and molecular haplotype discovery in monosomic hybrid cell lines. - Shimmin, Lawrence C; Natarajan, Sivamani; Ibarguen, Heladio; Montasser, May; Kim, Do-Kyun; Hanis, Craig L; Eric Boerwinkle; Wadhwa, Pathik D; Hixson, James E (DNA Seq, 2007)
Candidate gene association studies have met with mixed success due to many reasons including incomplete surveys of genetic variation and differences in patterns of genetic variation among study populations. We present the results of comprehensive variant discovery for the corticotropin releasing hormone gene (CRH on chromosome 8) encoding a neuropeptide that is central to many physiologic pathways. Mouse-human hybrid cell lines were constructed that are monosomic for human chromosome 8 for resequencing of separated CRH alleles to identify variants and directly determine their chromosomal phase for three major ethnic groups including African Americans (AA), Mexican Americans (MA) and European Americans (EA). We also resequenced diploid individuals to evaluate single nucleotide polymorphism (SNP) discovery in the limited numbers of monosomic hybrid cell lines. Our results show that CRH variation is very different in AA, yielding larger numbers of variants and haplotypes compared to MA and EA. Analysis of LD structure found three haplotype blocks in AA and two blocks in EA. Comparisons between AA and EA groups yielded extremely high measures of genetic differentiation (Wright's F(ST)>0.6), likely reflecting disruptive selection in CRH evolution. Network analysis showed that AA have retained an ancestral CRH haplotype, while the most common EA haplotype is derived from a single recombination event.
Keywords: Animals; Base Sequence; Cell Line; Corticotropin-Releasing Hormone; Ethnicity; Female; Haplotypes; Humans; Hybrid Cells; Linkage Disequilibrium; Male; Mice; Molecular Sequence Data; Monosomy; Phylogeny; Polymorphism, Single Nucleotide; Sequence Analysis, DNA

Demographic histories and patterns of linkage disequilibrium in Chinese and Indian rhesus macaques. - Hernandez, Ryan D; Hubisz, Melissa J; David A Wheeler; Smith, David G; Ferguson, Betsy; Jeffrey Rogers; Nazareth, Lynne; Indap, Amit; Bourquin, Traci; McPherson, John; Donna M Muzny; Richard A Gibbs; et al. (Science, 2007)
To understand the demographic history of rhesus macaques (Macaca mulatta) and document the extent of linkage disequilibrium (LD) in the genome, we partially resequenced five Encyclopedia of DNA Elements regions in 9 Chinese and 38 captive-born Indian rhesus macaques. Population genetic analyses of the 1467 single-nucleotide polymorphisms discovered suggest that the two populations separated about 162,000 years ago, with the Chinese population tripling in size since then and the Indian population eventually shrinking by a factor of four. Using coalescent simulations, we confirmed that these inferred demographic events explain a much faster decay of LD in Chinese (r(2) approximately 0.15 at 10 kilobases) versus Indian (r(2) approximately 0.52 at 10 kilobases) macaque populations.
Keywords: Animals; China; Demography; DNA, Mitochondrial; Genetics, Medical; Humans; India; Linkage Disequilibrium; Macaca mulatta; Polymorphism, Single Nucleotide

EGFR-T790M is a rare lung cancer susceptibility allele with enhanced kinase activity. - Vikis, Haris; Sato, Mitsuo; James, Michael; Wang, Daolong; Wang, Yian; Wang, Min; Jia, Dongmei; Liu, Yan; Bailey-Wilson, Joan E; Amos, Christopher I; Pinney, Susan M; Petersen, Gloria M; et al. (Cancer Res, 2007)
The use of tyrosine kinase inhibitors (TKI) has yielded great success in treatment of lung adenocarcinomas. However, patients who develop resistance to TKI treatment often acquire a somatic resistance mutation (T790M) located in the catalytic cleft of the epidermal growth factor receptor (EGFR) enzyme. Recently, a report describing EGFR-T790M as a germ-line mutation suggested that this mutation may be associated with inherited susceptibility to lung cancer. Contrary to previous reports, our analysis indicates that the T790M mutation confers increased Y992 and Y1068 phosphorylation levels. In a human bronchial epithelial cell line, overexpression of EGFR-T790M displayed a growth advantage over wild-type (WT) EGFR. We also screened 237 lung cancer family probands, in addition to 45 bronchoalveolar tumors, and found that none of them contained the EGFR-T790M mutation. Our observations show that EGFR-T790M provides a proliferative advantage with respect to WT EGFR and suggest that the enhanced kinase activity of this mutant is the basis for rare cases of inherited susceptibility to lung cancer.
Keywords: Alleles; Animals; Chlorocebus aethiops; COS Cells; DNA, Neoplasm; ErbB Receptors; Genes, erbB-1; Genetic Predisposition to Disease; Germ-Line Mutation; Humans; Lung Neoplasms; Pedigree; Phosphorylation

Evolutionary and biomedical insights from the rhesus macaque genome. - Richard A Gibbs; Jeffrey Rogers; Katze, Michael G; Bumgarner, Roger; Weinstock, George M; Mardis, Elaine R; Remington, Karin A; Strausberg, Robert L; Venter, J Craig; Wilson, Richard K; Batzer, Mark A; Bustamante, Carlos D; et al. (Science, 2007)
The rhesus macaque (Macaca mulatta) is an abundant primate species that diverged from the ancestors of Homo sapiens about 25 million years ago. Because they are genetically and physiologically similar to humans, rhesus monkeys are the most widely used nonhuman primate in basic and applied biomedical research. We determined the genome sequence of an Indian-origin Macaca mulatta female and compared the data with chimpanzees and humans to reveal the structure of ancestral primate genomes and to identify evidence for positive selection and lineage-specific expansions and contractions of gene families. A comparison of sequences from individual animals was used to investigate their underlying genetic diversity. The complete description of the macaque genome blueprint enhances the utility of this animal model for biomedical research and improves our understanding of the basic biology of the species.
Keywords: Animals; Biomedical Research; Evolution, Molecular; Female; Gene Duplication; Gene Rearrangement; Genetic Diseases, Inborn; Genetic Variation; Genome; Humans; Macaca mulatta; Male; Multigene Family; Mutation; Pan troglodytes; Sequence Analysis, DNA; Species Specificity

Fine mapping and candidate gene analyses of pulmonary adenoma resistance 1, a major genetic determinant of mouse lung adenoma resistance. - Wang, Min; Zhang, Zhongqiu; Zhang, Zhuo; Vikis, Haris; Yan, Ying; Wang, Yian; You, Ming (Cancer Res, 2007)
Pulmonary adenoma resistance 1 (Par1) is a major genetic determinant of mouse lung adenoma resistance. Although Par1 was previously mapped to mouse chromosome 11 by conventional linkage analyses, its candidate region was broad and undefined. In our present study, we generated Par1 congenic mice using two mouse strains A/J (Par1/-) and Mus spretus (Par1/+). Analyzing these congenic mice enabled us to fine map the Par1 quantitative trait loci (QTL) into a 2.0-cM (2.2 Mb) chromosomal region between genetic marker D11Mit70 and the gene Hoxb9. We then conducted systematic candidate gene screening through nucleotide polymorphism and expression analyses. Genes showing differential lung tissue expression or carrying nonsynonymous single nucleotide polymorphisms were identified and discussed. In particular, we evaluated tumor suppressor gene Tob1 for its Par1 candidacy. Our findings have narrowed the Par1 QTL region and will greatly facilitate the identification of the major genetic determinant of mouse lung adenoma resistance.
Keywords: Adenoma; Animals; Carrier Proteins; Chromosome Mapping; Female; Genes, Tumor Suppressor; Intracellular Signaling Peptides and Proteins; Lung Neoplasms; Male; Mice; Mice, Inbred A; Polymorphism, Single Nucleotide; Quantitative Trait Loci

The genome of Apis mellifera: dialog between linkage mapping and sequence assembly. - Solignac, Michel; Zhang, Lan; Mougel, Florence; Li, Bingshan; Vautrin, Dominique; Monnerot, Monique; Cornuet, Jean-Marie; Worley, Kim C; Weinstock, George M; Richard A Gibbs (Genome Biol, 2007)
Two independent genome projects for the honey bee, a microsatellite linkage map and a genome sequence assembly, interactively produced an almost complete organization of the euchromatic genome. Assembly 4.0 now includes 626 scaffolds that were ordered and oriented into chromosomes according to the framework provided by the third-generation linkage map (AmelMap3). Each construct was used to control the quality of the other. The co-linearity of markers in the sequence and the map is almost perfect and argues in favor of the high quality of both.
Keywords: Animals; Base Sequence; Bees; Chromosome Mapping; Genome; Microsatellite Repeats

Heritability of brain volume, surface area and shape: an MRI study in an extended pedigree of baboons. - Jeffrey Rogers; Kochunov, Peter; Lancaster, Jack; Shelledy, Wendy; Glahn, David; Blangero, John; Fox, Peter (Hum Brain Mapp, 2007)
To evaluate baboons (Papio hamadryas) as a primate model for the study of the genetic control of brain size and internal structure, we performed high resolution (<500 microm) magnetic resonance imaging on 109 pedigreed baboons. Quantitative genetic analysis of these MR images using a variance components approach indicates that native (untransformed) brain volume exhibits significant heritability among these baboons (h(2) = 0.52, P = 0.0049), with age and sex also accounting for substantial variation. Using global spatial normalization, we transformed all images to a standard population-specific reference, and recalculated the heritability of brain volume. The transformed images generated heritability estimates of h(2) = 0.82 (P = 0.00022) for total brain volume, h(2) = 0.86 (P = 0.0006) for cerebral volume, h(2) = 0.73 (P = 0.0069) for exposed surface area of the cerebrum and h(2) = 0.67 (P = 0.01) for gray matter volume. Regional differences in the genetic effects on brain structure were calculated using a voxel-based morphometry (VBM) approach. This analysis of regional variation shows that some areas of motor cortex and the superior temporal gyrus show relatively high heritability while other regions (e.g. superior parietal cortex) exhibit lower heritability. The general pattern of regional differences is similar to that observed in previous studies of humans. The present study demonstrates that there is substantial genetic variation underlying individual variation in brain size and structure among Papio baboons, and that broad patterns of genetic influence on variation in brain structure may be similar in baboons and humans.
Keywords: Animals; Brain; Brain Mapping; Female; Genetic Linkage; Magnetic Resonance Imaging; Male; Papio; Pedigree

High mobility group (HMG-box) genes in the honeybee fungal pathogen Ascosphaera apis. - Aronstein, K A; Murray, K D; de León, J H; Xiang Qin; Weinstock, G M (Mycologia, 2007)
The genome of the honeybee fungal pathogen Ascosphaera apis (Maassen) encodes three putative high mobility group (HMG-box) transcription factors. The predicted proteins (MAT1-2, STE11 and HTF), each of which contain a single strongly conserved HMG-box, exhibit high similarity to mating type proteins and STE11-like transcription factors previously identified in other ascomycete fungi, some of them important plant and human pathogens. In this study we characterized the A. apis HMG-box containing genes and analyzed the structure of the mating type locus (MAT1-2) and its flanking regions. The MAT1-2 locus contains a single gene encoding a protein with an HMG-box. We also have determined the transcriptional patterns of all three HMG-box containing genes in both mating type idiomorphs and discuss a potential role of these transcription factors in A. apis development and reproduction. A multiplex PCR method with primers amplifying mat1-2-1 and Ste11 gene fragments is described. This new method allows for identification of a single mating type idiomorph and might become an essential tool for applied and basic research of chalkbrood disease in honeybees.
Keywords: Amino Acid Sequence; Animals; Bees; Computational Biology; Fungal Proteins; Gene Expression Regulation, Fungal; Genes, Mating Type, Fungal; HMG-Box Domains; Molecular Sequence Data; Onygenales; Phylogeny; Polymerase Chain Reaction; Transcription Factors

Human-specific changes of genome structure detected by genomic triangulation. - R. Alan Harris; Rogers, J; Milosavljevic, A (Science, 2007)
Knowledge of the rhesus macaque genome sequence enables reconstruction of the ancestral state of the human genome before the divergence of chimpanzees. However, the draft quality of nonhuman primate genome assemblies challenges the ability of current methods to detect insertions, deletions, and copy-number variations between humans, chimpanzees, and rhesus macaques and hinders the identification of evolutionary changes between these species. Because of the abundance of segmental duplications, genome comparisons require the integration of genomic assemblies and data from large-insert clones, linkage maps, and radiation hybrid maps. With genomic triangulation, an integrative method that reconstructs ancestral states and the structural evolution of genomes, we identified 130 human-specific breakpoints in genome structure due to rearrangements at an intermediate scale (10 kilobases to 4 megabases), including 64 insertions affecting 58 genes. Comparison with a human structural polymorphism database indicates that many of the rearrangements are polymorphic.
Keywords: Animals; Chromosomes, Artificial, Bacterial; Evolution, Molecular; Gene Rearrangement; Genetic Techniques; Genome, Human; Humans; Macaca mulatta; Pan troglodytes; Polymorphism, Genetic; Species Specificity

Identification of a novel tumor suppressor gene p34 on human chromosome 6q25.1. - Wang, Min; Vikis, Haris G; Wang, Yian; Jia, Dongmei; Wang, Daolong; Bierut, Laura J; Bailey-Wilson, Joan E; Amos, Christopher I; Pinney, Susan M; Petersen, Gloria M; de Andrade, Mariza; Yang, Ping; et al. (Cancer Res, 2007)
In this study, we observed loss of heterozygosity (LOH) in human chromosomal fragment 6q25.1 in sporadic lung cancer patients. LOH was observed in 65% of the 26 lung tumors examined and was narrowed down to a 2.2-Mb region. Single-nucleotide polymorphism (SNP) analysis of genes located within this region identified a candidate gene, termed p34. This gene, also designated as ZC3H12D, C6orf95, FLJ46041, or dJ281H8.1, carries an A/G nonsynonymous SNP at codon 106, which alters the amino acid from lysine to arginine. Nearly 73% of heterozygous lung cancer tissues with LOH and the A/G SNP also exhibited loss of the A allele. In vitro clonogenic and in vivo nude mouse studies showed that overexpression of the A allele exerts tumor suppressor function compared with the G allele. p34 is located within a recently mapped human lung cancer susceptibility locus, and association of the p34 A/G SNP was tested among these families. No significant association between the less frequent G allele and lung cancer susceptibility was found. Our results suggest that p34 may be a novel tumor suppressor gene involved in sporadic lung cancer but it seems not to be the candidate familial lung cancer susceptibility gene linked to chromosomal region 6q23-25.
Keywords: Alleles; Animals; Base Sequence; Chromosomes, Human, Pair 6; Codon; Female; Genes, Tumor Suppressor; Genetic Predisposition to Disease; Humans; Loss of Heterozygosity; Lung Neoplasms; Mice; Mice, Nude; Molecular Sequence Data; Polymorphism, Single Nucleotide

A preliminary study of the baboon prostate pathophysiology. - Mubiru, James N; Hubbard, Gene B; Dick, Edward J; Butler, Stephanie D; Valente, Anthony J; Troyer, Dean A; Jeffrey Rogers (Prostate, 2007)
BACKGROUND: Prostate cancer, benign prostatic hyperplasia, and prostatitis frequently affect men worldwide. At present there are no suitable animal models for these diseases. This study explores the potential use of the baboon as a model for prostatic diseases. METHODS: Prostates of 48 baboons of different ages were studied. Prostate specific antigen (PSA) and alpha-methyl-acyl-CoA racemase (AMACR) were localized in the different lobes of the prostate by Western blotting and immunohistochemistry. PSA in baboon serum was demonstrated by radioimmunoassay and western blotting. Baboon AMACR cDNA was cloned and its expression assayed in baboon tissues. RESULTS: The baboon prostate is anatomically and histologically similar to its human counterpart, with cranial and caudal lobes corresponding to central and peripheral zones of the human prostate. We found lymphocytic infiltration (91%), and sclerosing/atrophic lesions (34%). PSA tissue immunostaining intensity and alpha-methyl-acyl-CoA racemase (AMACR) gene expression levels differed between the cranial and caudal lobes of the prostate. The cloned baboon AMACR cDNA showed 96% homology with its human counterpart. Anti-human AMACR, PSA and basal keratin antibodies stained intracellular and basement membrane structures in the baboon prostate. The sclerosing/atrophic lesions were comparable to their human counterparts. CONCLUSIONS: The similarity of baboon prostate to its human counterpart and the fact that human antibodies (AMACR, PSA, basal keratin) are reactive to baboon prostatic proteins indicates that the baboon is a promising model for human prostatic diseases.
Keywords: Animals; Cloning, Molecular; Disease Models, Animal; Immunoblotting; Immunohistochemistry; Male; Papio hamadryas; Pilot Projects; Prostate; Prostate-Specific Antigen; Prostatic Diseases; Racemases and Epimerases; Reverse Transcriptase Polymerase Chain Reaction; RNA

Quantitative trait loci for peripheral blood cell counts: a study in baboons. - Bertin, Angéline; Mahaney, Michael C; Cox, Laura A; Jeffrey Rogers; VandeBerg, John L; Brugnara, Carlo; Platt, Orah S (Mamm Genome, 2007)
Increasingly, baseline peripheral blood cell counts are implicated as risk factors for common complex diseases. While genetic influences on these hematologic parameters are firmly established, the genetic architecture of the blood counts is still poorly understood. In this article we used data from 582 healthy pedigreed baboons and variance components methods to localize quantitative trait loci (QTLs) influencing complete blood count variables. Besides performing genome-wide linkage scans for each trait individually, we conducted bivariate linkage analyses for all pairwise trait combinations to also identify pleiotropic QTLs influencing several blood counts. While significant and suggestive QTLs were localized throughout the genome (LOD range: 1.5-3.5), chromosomal regions associated with the expression of various hematologic parameters stand out. In particular, our results provide significant and consistent evidence for a QTL on the orthologous human chromosome 1p that is shared by several blood counts, mainly erythrocyte parameters. In addition, multiple suggestive evidence of linkage was detected on the orthologous human chromosomes 10 (near the q-terminus) and 19 (centromeric section). Future studies should help identify the genes responsible for these QTL and elucidate their role on baseline variation in hematologic indicators of health and disease.
Keywords: Animals; Blood Cell Count; Chromosome Mapping; Female; Humans; Male; Papio; Phenotype; Quantitative Trait Loci; Synteny

Trisomy 17 in a baboon (Papio hamadryas) with polydactyly, patent foramen ovale and pyelectasis. - Moore, Charleen M; Hubbard, Gene B; Dick, Edward; Dunn, Betty G; Raveendran, Muthuswamy; Jeffrey Rogers; Williams, Vick; Gomez, Jeremiah J; Butler, Stephanie D; Leland, M Michelle; Schlabritz-Loutsevitch, Natalia E (Am J Primatol, 2007)
Trisomy 13 in humans is the third most common autosomal abnormality at birth, after trisomy 21 and trisomy 18. It has a reported incidence of between 1:5,000 and 1:30,000 live births. It is associated with multiple abnormalities, many of which shorten lifespan. We describe here the first reported case of a baboon (Papio hamadryas) with trisomy of chromosome 17, which is homologous to human chromosome 13. The trisomic infant was born to a consanguineous pair of baboons and had morphological characteristics similar to those observed in human trisomy 13, including bilateral polydactyly in the upper limbs, a patent foramen ovale, and pyelectasis. Molecular DNA analysis using human chromosome 13 markers was consistent with the affected infant inheriting two copies of chromosome 17 derived from the same parental chromosome. This trisomy was, therefore, due to either an error in meiosis II or the result of postzygotic nondisjunction. The parental origin, however, could not be determined.
Keywords: Animals; Arm; Chromosomes, Mammalian; Dilatation, Pathologic; Female; Heart Atria; Heart Septal Defects, Atrial; Humans; Inbreeding; Kidney Pelvis; Male; Papio hamadryas; Polydactyly; Trisomy

Widespread lateral gene transfer from intracellular bacteria to multicellular eukaryotes. - Dunning Hotopp, Julie C; Clark, Michael E; Oliveira, Deodoro C S G; Foster, Jeremy M; Fischer, Peter; Muñoz Torres, Mónica C; Giebel, Jonathan D; Kumar, Nikhil; Ishmael, Nadeeza; Wang, Shiliang; Ingram, Jessica; Nene, Rahul V; et al. (Science, 2007)
Although common among bacteria, lateral gene transfer-the movement of genes between distantly related organisms-is thought to occur only rarely between bacteria and multicellular eukaryotes. However, the presence of endosymbionts, such as Wolbachia pipientis, within some eukaryotic germlines may facilitate bacterial gene transfers to eukaryotic host genomes. We therefore examined host genomes for evidence of gene transfer events from Wolbachia bacteria to their hosts. We found and confirmed transfers into the genomes of four insect and four nematode species that range from nearly the entire Wolbachia genome (>1 megabase) to short (<500 base pairs) insertions. Potential Wolbachia-to-host transfers were also detected computationally in three additional sequenced insect genomes. We also show that some of these inserted Wolbachia genes are transcribed within eukaryotic cells lacking endosymbionts. Therefore, heritable lateral gene transfer occurs into eukaryotic hosts from their prokaryote symbionts, potentially providing a mechanism for acquisition of new genes and functions.
Keywords: Animals; Chromosome Mapping; Crosses, Genetic; DNA, Bacterial; Drosophila; Female; Gene Transfer, Horizontal; Genes, Bacterial; In Situ Hybridization, Fluorescence; Insecta; Male; Molecular Sequence Data; Nematoda; Retroelements; Reverse Transcriptase Polymerase Chain Reaction; Sequence Analysis, DNA; Symbiosis; Wolbachia

Community annotation: procedures, protocols, and supporting tools. - Elsik, Christine G; Worley, Kim C; Zhang, Lan; Milshina, Natalia V; Jiang, Huaiyang; Reese, Justin T; Childs, Kevin L; Venkatraman, Anand; Dickens, C Michael; Weinstock, George M; Richard A Gibbs (Genome Res, 2006)
Investigators at the Baylor College of Medicine Human Genome Sequencing Center (BCM-HGSC) and BeeBase organized a community-wide effort to manually annotate the honey bee (Apis mellifera) genome. Although various strategies for manual annotation have been used in the past, the value of dispersed community annotation has not yet been demonstrated. Here we make a case for the merit of dispersed community annotation. We present annotation procedures, standard protocols, and tools used for sequence analysis, data submission, and data management. We also report lessons learned from this dispersed community annotation effort for a metazoan genome.
Keywords: Animals; Bees; Databases, Genetic; Genome, Human; Genomics; Humans; Models, Genetic; Molecular Sequence Data; Sequence Analysis

Comparative analysis of the bovine MHC class IIb sequence identifies inversion breakpoints and three unexpected genes. - Childers, C P; Newkirk, H L; Honeycutt, D A; Ramlachan, N; Donna M Muzny; Sodergren, E; Richard A Gibbs; Weinstock, G M; Womack, J E; Skow, L C (Anim Genet, 2006)
The bovine major histocompatibility complex (MHC) or BoLA is organized differently from typical mammalian MHCs in that a large portion of the class II region, called class IIb, has been transposed to a position near the centromere on bovine chromosome 23. Gene mapping indicated that the rearrangement resulted from a single inversion, but the boundaries and gene content of the inverted segment have not been fully determined. Here, we report the genomic sequence of BoLA IIb. Comparative sequence analysis with the human MHC revealed that the proximal inversion breakpoint occurred approximately 2.5 kb from the 3' end of the glutamate-cysteine ligase, catalytic subunit (GCLC) locus and that the distal breakpoint occurred about 2 kb from the 5' end from a divergent class IIDRbeta-like sequence designated DSB. Gene content, order and orientation of BoLA IIb are consistent with the single inversion hypothesis when compared with the corresponding region of the human class II MHC (HLA class II). Differences with HLA include the presence of a single histone H2B gene located between the proteasome subunit, beta type, 9 (PSMB9) and DMB loci and a duplicated TAP2 with a variant splice site. BoLA IIb spans approximately 450 kb DNA, with 20 apparently intact genes and no obvious pseudogenes. The region contains 227 simple sequence repeats (SSRs) and approximately 167 kb of retroviral-related repetitive DNA. Nineteen of the 20 genes identified in silico are supported by bovine EST data indicating that the functional gene content of BoLA IIb has not been diminished because it has been transposed from the remainder of BoLA genes.
Keywords: Animals; Cattle; Chromosome Inversion; Chromosomes, Mammalian; Contig Mapping; Evolution, Molecular; Genes, MHC Class II; Histones; Humans; Molecular Sequence Data; Sequence Analysis, DNA

Designing new microsatellite markers for linkage and population genetic analyses in rhesus macaques and other nonhuman primates. - Raveendran, Muthuswamy; R. Alan Harris; Milosavljevic, Aleksandar; Johnson, Zach; Shelledy, Wendy; Cameron, Judy; Jeffrey Rogers (Genomics, 2006)
Identification of polymorphic microsatellite loci in nonhuman primates is useful for various biomedical and evolutionary studies of these species. Prior methods for identifying microsatellites in nonhuman primates are inefficient. We describe a new strategy for marker development that uses the available whole genome sequence for rhesus macaques. Fifty-four novel rhesus-derived microsatellites were genotyped in large pedigrees of rhesus monkeys. Linkage analysis was used to place 51 of these loci into the existing rhesus linkage map. In addition, we find that microsatellites identified this way are polymorphic in other Old World monkeys such as baboons. This approach to marker development is more efficient than previous methods and produces polymorphisms with known locations in the rhesus genome assembly. Finally, we propose a nomenclature system that can be used for rhesus-derived microsatellites genotyped in any species or for novel loci derived from the genome sequence of any nonhuman primate.
Keywords: Animals; Chromosome Mapping; Genetic Markers; Genetic Techniques; Genetics, Population; Humans; Macaca mulatta; Microsatellite Repeats; Papio hamadryas; Pedigree; Polymorphism, Genetic

Desmosomal dysfunction due to mutations in desmoplakin causes arrhythmogenic right ventricular dysplasia/cardiomyopathy. - Yang, Zhao; Bowles, Neil E; Scherer, Steven E; Taylor, Michael D; Kearney, Debra L; Ge, Shuping; Nadvoretskiy, Vyacheslav V; DeFreitas, Gilberto; Carabello, Blasé; Brandon, Lois I; Godsel, Lisa M; Green, Kathleen J; et al. (Circ Res, 2006)
Arrhythmogenic right ventricular dysplasia/cardiomyopathy (ARVD/C) is characterized by progressive degeneration of the right ventricular myocardium, ventricular arrhythmias, fibrous-fatty replacement, and increased risk of sudden death. Mutations in 6 genes, including 4 encoding desmosomal proteins (Junctional plakoglobin (JUP), Desmoplakin (DSP), Plakophilin 2, and Desmoglein 2), have been identified in patients with ARVD/C. Mutation analysis of 66 probands identified 4 variants in DSP; V30M, Q90R, W233X, and R2834H. To establish a cause and effect relationship between those DSP missense mutations and ARVD/C, we performed in vitro and in vivo analyses of the mutated proteins. Unlike wild-type (WT) DSP, the N-terminal mutants (V30M and Q90R) failed to localize to the cell membrane in desomosome-forming cell line and failed to bind to and coimmunoprecipitate JUP. Multiple attempts to generate N-terminal DSP (V30M and Q90R) cardiac-specific transgenes have failed: analysis of embryos revealed evidence of profound ventricular dilation, which likely resulted in embryonic lethality. We were able to develop transgenic (Tg) mice with cardiac-restricted overexpression of the C-terminal mutant (R2834H) or WT DSP. Whereas mice overexpressing WT DSP had no detectable histologic, morphological, or functional cardiac changes, the R2834H-Tg mice had increased cardiomyocyte apoptosis, cardiac fibrosis, and lipid accumulation, along with ventricular enlargement and cardiac dysfunction in both ventricles. These mice also displayed interruption of DSP-desmin interaction at intercalated discs (IDs) and marked ultra-structural changes of IDs. These data suggest DSP expression in cardiomyocytes is crucial for maintaining cardiac tissue integrity, and DSP abnormalities result in ARVD/C by cardiomyocyte death, changes in lipid metabolism, and defects in cardiac development.
Keywords: Animals; Apoptosis; Arrhythmogenic Right Ventricular Dysplasia; Cardiomyopathies; Cell Communication; Cell Line, Tumor; Desmoplakins; Desmosomes; DNA Mutational Analysis; Embryo, Mammalian; Heart; Humans; Intercellular Junctions; Lipid Metabolism; Mice; Mice, Transgenic; Mutation, Missense; Myocytes, Cardiac

The DNA sequence, annotation and analysis of human chromosome 3. - Donna M Muzny; Steven E Scherer; Kaul, Rajinder; Wang, Jing; Yu, Jun; Sudbrak, Ralf; Buhay, Christian J; Rui Chen; Cree, Andrew; Ding, Yan; Dugan-Rocha, Shannon; Gill, Rachel; et al. (Nature, 2006)
After the completion of a draft human genome sequence, the International Human Genome Sequencing Consortium has proceeded to finish and annotate each of the 24 chromosomes comprising the human genome. Here we describe the sequencing and analysis of human chromosome 3, one of the largest human chromosomes. Chromosome 3 comprises just four contigs, one of which currently represents the longest unbroken stretch of finished DNA sequence known so far. The chromosome is remarkable in having the lowest rate of segmental duplication in the genome. It also includes a chemokine receptor gene cluster as well as numerous loci involved in multiple human cancers such as the gene encoding FHIT, which contains the most common constitutive fragile site in the genome, FRA3B. Using genomic sequence from chimpanzee and rhesus macaque, we were able to characterize the breakpoints defining a large pericentric inversion that occurred some time after the split of Homininae from Ponginae, and propose an evolutionary history of the inversion.
Keywords: Animals; Base Sequence; Chromosome Breakage; Chromosome Inversion; Chromosomes, Human, Pair 3; Contig Mapping; CpG Islands; DNA, Complementary; Evolution, Molecular; Expressed Sequence Tags; Human Genome Project; Humans; Macaca mulatta; Molecular Sequence Data; Pan troglodytes; Sequence Analysis, DNA; Synteny

Escherichia coli DNA polymerase II can efficiently bypass 3,N(4)-ethenocytosine lesions in vitro and in vivo. - Al Mamun, Abu Amar M; Humayun, M Zafri (Mutat Res, 2006)
Escherichia coli DNA polymerase II (pol-II) is a highly conserved protein that appears to have a role in replication restart, as well as in translesion synthesis across specific DNA adducts under some conditions. Here, we have investigated the effects of elevated expression of pol-II (without concomitant SOS induction) on translesion DNA synthesis and mutagenesis at 3,N(4)-ethenocytosine (varepsilonC), a highly mutagenic DNA lesion induced by oxidative stress as well as by exposure to industrial chemicals such as vinyl chloride. In normal cells, survival of transfected M13 single-stranded DNA bearing a single varepsilonC residue (varepsilonC-ssDNA) is about 20% of that of control DNA, with about 5% of the progeny phage bearing a mutation at the lesion site. Most mutations are C-->A and C-->T, with a slight predominance of transversions over transitions. In contrast, in cells expressing elevated levels of pol-II, survival of varepsilonC-ssDNA is close to 100%, with a concomitant mutation frequency of almost 99% suggesting highly efficient translesion DNA synthesis. Furthermore, an overwhelming majority of mutations at varepsilonC are C-->T transitions. Purified pol-II efficiently catalyzes translesion synthesis at varepsilonC in vitro, accompanied by high levels of mutagenesis with the same specificity. These results suggest that the observed in vivo effects in pol-II over-expressing cells are due to pol-II-mediated DNA synthesis. Introduction of mutations in the carboxy terminus region (beta interaction domain) of polB eliminates in vivo translesion synthesis at varepsilonC, suggesting that the ability of pol-II to compete with pol-III requires interaction with the beta processivity subunit of pol-III. Thus, pol-II can compete with pol-III for translesion synthesis.
Keywords: Animals; Base Sequence; Cattle; Cytosine; DNA Polymerase II; DNA Primers; Escherichia coli; Mutagenesis

The finished DNA sequence of human chromosome 12. - Scherer, Steven E; Donna M Muzny; Buhay, Christian J; Rui Chen; Cree, Andrew; Ding, Yan; Dugan-Rocha, Shannon; Gill, Rachel; Gunaratne, Preethi; R. Alan Harris; Hawes, Alicia C; Hernandez, Judith; et al. (Nature, 2006)
Human chromosome 12 contains more than 1,400 coding genes and 487 loci that have been directly implicated in human disease. The q arm of chromosome 12 contains one of the largest blocks of linkage disequilibrium found in the human genome. Here we present the finished sequence of human chromosome 12, which has been finished to high quality and spans approximately 132 megabases, representing approximately 4.5% of the human genome. Alignment of the human chromosome 12 sequence across vertebrates reveals the origin of individual segments in chicken, and a unique history of rearrangement through rodent and primate lineages. The rate of base substitutions in recent evolutionary history shows an overall slowing in hominids compared with primates and rodents.
Keywords: Animals; Base Composition; Chromosomes, Human, Pair 12; CpG Islands; Evolution, Molecular; Expressed Sequence Tags; Genes; Humans; Linkage Disequilibrium; Microsatellite Repeats; Molecular Sequence Data; Mutagenesis, Insertional; Pan troglodytes; Sequence Analysis, DNA; Sequence Deletion; Short Interspersed Nucleotide Elements; Synteny

The generation of a conditional Fmr1 knock out mouse model to study Fmrp function in vivo. - Mientjes, E J; Nieuwenhuizen, I; Kirkpatrick, L; Zu, T; Hoogeveen-Westerveld, M; Severijnen, L; Rifé, M; Willemsen, R; Nelson, D L; Oostra, B A (Neurobiol Dis, 2006)
The FMR1 gene, mutated in Fragile X syndrome patients, has been modeled in mice with a neomycin cassette inserted in exon 5 of the mouse Fmr1 gene creating an Fmr1 knockout (Fmr1 KO) allele. This results in animals lacking Fmr1 protein (Fmrp) expression in all tissues. We have created a new, more versatile Fmr1 in vivo KO model (Fmr1 KO2) and generated conditional Fmr1 KO (CKO) mice by flanking the promoter and first exon of Fmr1 with lox P sites. This enables us to create a null allele in specific cell types and at specific time points by crossing Fmr1 CKO mice with tissue specific or inducible cre-recombinase expressing mice. The new Fmr1 KO2 line does not express any Fmrp and also lacks detectable Fmr1 transcripts. Crossing the Fmr1 CKO line with a Purkinje cell-specific cre-recombinase expresser produces mice that are null for Fmr1 in Purkinje neurons but wild type in all other cell types.
Keywords: Animals; Blotting, Western; Disease Models, Animal; Fragile X Mental Retardation Protein; Fragile X Syndrome; Immunohistochemistry; Mice; Mice, Knockout; Purkinje Cells; Reverse Transcriptase Polymerase Chain Reaction

The genome of the sea urchin Strongylocentrotus purpuratus. - Sodergren, Erica; Weinstock, George M; Davidson, Eric H; Cameron, R Andrew; Richard A Gibbs; Angerer, Robert C; Angerer, Lynne M; Arnone, Maria Ina; Burgess, David R; Burke, Robert D; Coffman, James A; Dean, Michael; et al. (Science, 2006)
We report the sequence and analysis of the 814-megabase genome of the sea urchin Strongylocentrotus purpuratus, a model for developmental and systems biology. The sequencing strategy combined whole-genome shotgun and bacterial artificial chromosome (BAC) sequences. This use of BAC clones, aided by a pooling strategy, overcame difficulties associated with high heterozygosity of the genome. The genome encodes about 23,300 genes, including many previously thought to be vertebrate innovations or known only outside the deuterostomes. This echinoderm genome provides an evolutionary outgroup for the chordates and yields insights into the evolution of deuterostomes.
Keywords: Animals; Calcification, Physiologic; Cell Adhesion Molecules; Complement Activation; Computational Biology; Embryonic Development; Evolution, Molecular; Gene Expression Regulation, Developmental; Genes; Genome; Immunity, Innate; Immunologic Factors; Male; Nervous System Physiological Phenomena; Proteins; Sequence Analysis, DNA; Signal Transduction; Strongylocentrotus purpuratus; Transcription Factors

Genome sequences of the honey bee pathogens Paenibacillus larvae and Ascosphaera apis. - Xiang Qin; Evans, J D; Aronstein, K A; Murray, K D; Weinstock, G M (Insect Mol Biol, 2006)
Genome sequences offer a broad view of host-pathogen interactions at the systems biology level. With the completion of the sequence of the honey bee, interest in the relevant pathogens is heightened. Here we report the genome sequences of two of the major pathogens of honey bees, the bacterium Paenibacillus larvae (causative agent for American foulbrood disease) and the fungus Ascosphaera apis. (causative agent for chalkbrood disease). Ongoing efforts to characterize the genomes of these species can be used to understand and mitigate the effects of two important pathogens, and will provide a contrast with pathogenic, benign and freeliving relatives.
Keywords: Animals; Ascomycota; Bees; Genome, Bacterial; Genome, Fungal; Gram-Positive Endospore-Forming Rods

Genome-wide identification of direct targets of the Drosophila retinal determination protein Eyeless. - Ostrin, Edwin J; Yumei Li; Hoffman, Kristi; Liu, Jing; Wang, Keqing; Zhang, Li; Mardon, Graeme; Rui Chen (Genome Res, 2006)
The discovery of direct downstream targets of transcription factors (TFs) is necessary for understanding the genetic mechanisms underlying complex, highly regulated processes such as development. In this report, we have used a combinatorial strategy to conduct a genome-wide search for novel direct targets of Eyeless (Ey), a key transcription factor controlling early eye development in Drosophila. To overcome the lack of high-quality consensus binding site sequences, phylogenetic shadowing of known Ey binding sites in sine oculis (so) was used to construct a position weight matrix (PWM) of the Ey protein. This PWM was then used for in silico prediction of potential binding sites in the Drosophila melanogaster genome. To reduce the false positive rate, conservation of these potential binding sites was assessed by comparing the genomic sequences from seven Drosophila species. In parallel, microarray analysis of wild-type versus ectopic ey-expressing tissue, followed by microarray-based epistasis experiments in an atonal (ato) mutant background, identified 188 genes induced by ey. Intersection of in silico predicted conserved Ey binding sites with the candidate gene list produced through expression profiling yields a list of 20 putative ey-induced, eye-enriched, ato-independent, direct targets of Ey. The accuracy of this list of genes was confirmed using both in vitro and in vivo methods. Initial analysis reveals three genes, eyes absent, shifted, and Optix, as novel direct targets of Ey. These results suggest that the integrated strategy of computational biology, genomics, and genetics is a powerful approach to identify direct downstream targets for any transcription factor genome-wide.
Keywords: Animals; Chromosome Mapping; DNA-Binding Proteins; Drosophila; Drosophila Proteins; Gene Expression Profiling; Gene Expression Regulation; Genome, Insect; Oligonucleotide Array Sequence Analysis; Regulatory Elements, Transcriptional

High-throughput gene expression profiling--a work-in-progress with great potential for proteomics. - Roussel, Eugene; Marie-Claude Gingras (Curr Opin Drug Discov Devel, 2006)
Since the invention of Northern blot profiling more than 30 years ago, scientists have progressed from being able to analyze only a few genes at a time to whole-genome and global differential gene expression profiling. This progress has been made possible by the development of several high-throughput technologies. Such technologies have gained increasing popularity in recent years because of significant discoveries made in the field of proteomics, and have already led to huge advances in the medical field. This article reviews the high-throughput technologies that have been undergoing development during the last two years for the selection of specific cell subtypes in a tissue, for the discovery and identification of all of the genes expressed in a system without pre-selection (open systems), and for the validation of selected genes (closed systems).
Keywords: Animals; Gene Expression Profiling; Genome, Human; Humans; Proteomics

l7Rn6 encodes a novel protein required for clara cell function in mouse lung development. - Fernández-Valdivia, Rodrigo; Zhang, Ying; Pai, Sonia; Metzker, Michael L; Schumacher, Armin (Genetics, 2006)
The highly secretory Clara cells play a pivotal role in protecting the lung against inflammation and oxidative stress. This study reports the positional cloning of a novel protein required for Clara cell physiology in mouse lung development. The perinatal lethal N-ethyl-N-nitrosourea-induced l7Rn6(4234SB) allele contained a nonsense mutation in the previously hypothetical gene NM_026304 on chromosome 7. Whereas l7Rn6 mRNA levels were indistinguishable from wild type, l7Rn6(4234SB) homozygotes exhibited decreased expression of the truncated protein, suggesting protein instability. During late gestation, l7Rn6 was widely expressed in the cytoplasm of lung epithelial cells, whereas perinatal expression was restricted to the bronchiolar epithelium. Homozygosity for the l7Rn6(4234SB) allele did not affect early steps in lung patterning, growth, or cellular differentiation. Rather, mutant lungs demonstrated severe emphysematous enlargement of the distal respiratory sacs at birth. Clara cell pathophysiology was evident from decreased cytoplasmic CCSP and SP-B protein levels, enlargement and disorganization of the Golgi complex, and formation of aberrant vesicular structures. Additional support for a role in the secretory pathway derived from l7Rn6 localization to the endoplasmic reticulum. Thus, l7Rn6 represents a novel protein required for organization and/or function of the secretory apparatus in Clara cells in mouse lung.
Keywords: Amino Acid Sequence; Animals; Base Sequence; Bronchi; Cell Differentiation; Cloning, Molecular; Cytoplasm; Endoplasmic Reticulum; Enzyme Inhibitors; Epithelial Cells; Ethylnitrosourea; Female; Gene Expression Regulation, Developmental; Gestational Age; Golgi Apparatus; Lung; Mice; Mice, Transgenic; Molecular Sequence Data; Phospholipases A; Pregnancy; Proteins; Pulmonary Alveoli; Pulmonary Surfactant-Associated Protein B; Rabbits; Sequence Homology, Amino Acid; Uteroglobin

Mutant analysis of the Shal (Kv4) voltage-gated fast transient K+ channel in Caenorhabditis elegans. - Fawcett, Gloria L; Santi, Celia M; Butler, Alice; Harris, Thanawath; Covarrubias, Manuel; Salkoff, Lawrence (J Biol Chem, 2006)
Shal (Kv4) alpha-subunits are the most conserved among the family of voltage-gated potassium channels. Previous work has shown that the Shal potassium channel subfamily underlies the predominant fast transient outward current in Drosophila neurons (Tsunoda, S., and Salkoff, L. (1995) J. Neurosci. 15, 1741-1754) and the fast transient outward current in mouse heart muscle (Guo, W., Jung, W. E., Marionneau, C., Aimond, F., Xu, H., Yamada, K. A., Schwarz, T. L., Demolombe, S., and Nerbonne, J. M. (2005) Circ. Res. 97, 1342-1350). We show that Shal channels also play a role as the predominant transient outward current in Caenorhabditis elegans muscle. Green fluorescent protein promoter experiments also revealed SHL-1 expression in a subset of neurons as well as in C. elegans body wall muscle and in male-specific diagonal muscles. The shl-1 (ok1168) null mutant removed all fast transient outward current from muscle cells. SHL-1 currents strongly resembled Shal currents in other species except that they were active in a more depolarized voltage range. We also determined that the remaining delayed-rectifier current in cultured myocytes was carried by the Shaker ortholog SHK-1. In shl-1 (ok1168) mutants there was a significant compensatory increase in the SHK-1 current. Male shl-1 (ok1168) animals exhibited reduced mating efficiency resulting from an apparent difficulty in locating the hermaphrodite vulva. SHL-1 channels are apparently important in fine-tuning complex behaviors, such as mating, that play a crucial role in the survival and propagation of the species.
Keywords: Animals; Caenorhabditis elegans; DNA Mutational Analysis; Electrophysiology; Genes, Dominant; Green Fluorescent Proteins; Neurons; Oocytes; Phenotype; Promoter Regions, Genetic; RNA Interference; RNA, Complementary; Shal Potassium Channels; Xenopus

Phylogenomic analysis reveals bees and wasps (Hymenoptera) at the base of the radiation of Holometabolous insects. - Savard, Joël; Tautz, Diethard; Stephen Richards; Weinstock, George M; Richard A Gibbs; Werren, John H; Tettelin, Hervé; Lercher, Martin J (Genome Res, 2006)
Comparative studies require knowledge of the evolutionary relationships between taxa. However, neither morphological nor paleontological data have been able to unequivocally resolve the major groups of holometabolous insects so far. Here, we utilize emerging genome projects to assemble and analyze a data set of 185 nuclear genes, resulting in a fully resolved phylogeny of the major insect model species. Contrary to the most widely accepted phylogenetic hypothesis, bees and wasps (Hymenoptera) are basal to the other major holometabolous orders, beetles (Coleoptera), moths (Lepidoptera), and flies (Diptera). We validate our results by meticulous examination of potential confounding factors. Phylogenomic approaches are thus able to resolve long-standing questions about the phylogeny of insects.
Keywords: Animals; Bees; Biological Evolution; Genome, Insect; Genomics; Insect Proteins; Insecta; Models, Genetic; Phylogeny; Proteomics; Species Specificity; Wasps

Recurrent duplication-driven transposition of DNA during hominoid evolution. - Johnson, Matthew E; Cheng, Ze; Morrison, V Anne; Scherer, Steven; Ventura, Mario; Richard A Gibbs; Green, Eric D; Eichler, Evan E (Proc Natl Acad Sci U S A, 2006)
The underlying mechanism by which the interspersed pattern of human segmental duplications has evolved is unknown. Based on a comparative analysis of primate genomes, we show that a particular segmental duplication (LCR16a) has been the source locus for the formation of the majority of intrachromosomal duplications blocks on human chromosome 16. We provide evidence that this particular segment has been active independently in each great ape and human lineage at different points during evolution. Euchromatic sequence that flanks sites of LCR16a integration are frequently lineage-specific duplications. This process has mobilized duplication blocks (15-200 kb in size) to new genomic locations in each species. Breakpoint analysis of lineage-specific insertions suggests coordinated deletion of repeat-rich DNA at the target site, in some cases deleting genes in that species. Our data support a model of duplication where the probability that a segment of DNA becomes duplicated is determined by its proximity to core duplicons, such as LCR16a.
Keywords: Animals; Base Sequence; Biological Evolution; Chromosomes, Human, Pair 16; DNA; DNA Transposable Elements; Evolution, Molecular; Gene Duplication; Hominidae; Humans; Molecular Sequence Data; Phylogeny; Sequence Alignment; Sequence Analysis, DNA

Scale-invariant structure of strongly conserved sequence in genomic intersections and alignments. - Salerno, William; Havlak, Paul; Miller, Jonathan (Proc Natl Acad Sci U S A, 2006)
A power-law distribution of the length of perfectly conserved sequence from mouse/human whole-genome intersection and alignment is exhibited. Spatial correlations of these elements within the mouse genome are studied. It is argued that these power-law distributions and correlations are comprised in part by functional noncoding sequence and ought to be accounted for in estimating the statistical significance of apparent sequence conservation. These inter-genomic correlations of conservation are placed in the context of previously observed intra-genomic correlations, and their possible origins and consequences are discussed.
Keywords: Animals; Base Sequence; Cluster Analysis; Conserved Sequence; Genome; Genomics; Humans; Mice; Repetitive Sequences, Nucleic Acid; Sequence Alignment

Shedding genomic light on Aristotle's lantern. - Sodergren, Erica; Shen, Yufeng; Song, Xingzhi; Zhang, Lan; Richard A Gibbs; Weinstock, George M (Dev Biol, 2006)
Sea urchins have proved fascinating to biologists since the time of Aristotle who compared the appearance of their bony mouth structure to a lantern in The History of Animals. Throughout modern times it has been a model system for research in developmental biology. Now, the genome of the sea urchin Strongylocentrotus purpuratus is the first echinoderm genome to be sequenced. A high quality draft sequence assembly was produced using the Atlas assembler to combine whole genome shotgun sequences with sequences from a collection of BACs selected to form a minimal tiling path along the genome. A formidable challenge was presented by the high degree of heterozygosity between the two haplotypes of the selected male representative of this marine organism. This was overcome by use of the BAC tiling path backbone, in which each BAC represents a single haplotype, as well as by improvements in the Atlas software. Another innovation introduced in this project was the sequencing of pools of tiling path BACs rather than individual BAC sequencing. The Clone-Array Pooled Shotgun Strategy greatly reduced the cost and time devoted to preparing shotgun libraries from BAC clones. The genome sequence was analyzed with several gene prediction methods to produce a comprehensive gene list that was then manually refined and annotated by a volunteer team of sea urchin experts. This latter annotation community edited over 9000 gene models and uncovered many unexpected aspects of the sea urchin genetic content impacting transcriptional regulation, immunology, sensory perception, and an organism's development. Analysis of the basic deuterostome genetic complement supports the sea urchin's role as a model system for deuterostome and, by extension, chordate development.
Keywords: Animals; Chromosomes, Artificial, Bacterial; DNA; Genome; Sea Urchins

Spectrum of CHD7 mutations in 110 individuals with CHARGE syndrome and genotype-phenotype correlation. - Lalani, Seema R; Safiullah, Arsalan M; Fernbach, Susan D; Harutyunyan, Karine G; Thaller, Christina; Peterson, Leif E; McPherson, John D; Richard A Gibbs; White, Lisa D; Hefner, Margaret; Davenport, Sandra L H; Graham, John M; et al. (Am J Hum Genet, 2006)
CHARGE syndrome is a well-established multiple-malformation syndrome with distinctive consensus diagnostic criteria. Characteristic associated anomalies include ocular coloboma, choanal atresia, cranial nerve defects, distinctive external and inner ear abnormalities, hearing loss, cardiovascular malformations, urogenital anomalies, and growth retardation. Recently, mutations of the chromodomain helicase DNA-binding protein gene CHD7 were reported to be a major cause of CHARGE syndrome. We sequenced the CHD7 gene in 110 individuals who had received the clinical diagnosis of CHARGE syndrome, and we detected mutations in 64 (58%). Mutations were distributed throughout the coding exons and conserved splice sites of CHD7. Of the 64 mutations, 47 (73%) predicted premature truncation of the protein. These included nonsense and frameshift mutations, which most likely lead to haploinsufficiency. Phenotypically, the mutation-positive group was more likely to exhibit cardiovascular malformations (54 of 59 in the mutation-positive group vs. 30 of 42 in the mutation-negative group; P=.014), coloboma of the eye (55 of 62 in the mutation-positive group vs. 30 of 43 in the mutation-negative group; P=.022), and facial asymmetry, often caused by seventh cranial nerve abnormalities (36 of 56 in the mutation-positive group vs. 13 of 39 in the mutation-negative group; P=.004). Mouse embryo whole-mount and section in situ hybridization showed the expression of Chd7 in the outflow tract of the heart, optic vesicle, facio-acoustic preganglion complex, brain, olfactory pit, and mandibular component of the first branchial arch. Microarray gene-expression analysis showed a signature pattern of gene-expression differences that distinguished the individuals with CHARGE syndrome with CHD7 mutation from the controls. We conclude that cardiovascular malformations, coloboma, and facial asymmetry are common findings in CHARGE syndrome caused by CHD7 mutation.
Keywords: Abnormalities, Multiple; Adolescent; Animals; Child; Child, Preschool; Coloboma; DNA Helicases; DNA Mutational Analysis; DNA-Binding Proteins; Embryo, Mammalian; Facial Asymmetry; Female; Genotype; Heart Defects, Congenital; Humans; In Situ Hybridization, Fluorescence; Male; Mice; Molecular Sequence Data; Mutation; Pedigree; Phenotype; RNA Splice Sites; RNA, Messenger; Syndrome

Stargazin and other transmembrane AMPA receptor regulating proteins interact with synaptic scaffolding protein MAGI-2 in brain. - Deng, Fang; Price, Maureen G; Davis, Caleb F; Mori, Mayra; Burgess, Daniel L (J Neurosci, 2006)
The spatial coordination of neurotransmitter receptors with other postsynaptic signaling and structural molecules is regulated by a diverse array of cell-specific scaffolding proteins. The synaptic trafficking of AMPA receptors by the stargazin protein in some neurons, for example, depends on specific interactions between the C terminus of stargazin and the PDZ [postsynaptic density-95 (PSD-95)/Discs large/zona occludens-1] domains of membrane-associated guanylate kinase scaffolding proteins PSD-93 or PSD-95. Stargazin [Cacng2 (Ca2+ channel gamma2 subunit)] is one of four closely related proteins recently categorized as transmembrane AMPA receptor regulating proteins (TARPs) that appear to share similar functions but exhibit distinct expression patterns in the CNS. We used yeast two-hybrid screening to identify MAGI-2 (membrane associated guanylate kinase, WW and PDZ domain containing 2) as a novel candidate interactor with the cytoplasmic C termini of the TARPs. MAGI-2 [also known as S-SCAM (synaptic scaffolding molecule)] is a multi-PDZ domain scaffolding protein that interacts with several different ligands in brain, including PTEN (phosphatase and tensin homolog), dasm1 (dendrite arborization and synapse maturation 1), dendrin, axin, beta- and delta-catenin, neuroligin, hyperpolarization-activated cation channels, beta1-adrenergic receptors, and NMDA receptors. We confirmed that MAGI-2 coimmunoprecipitated with stargazin in vivo from mouse cerebral cortex and used in vitro assays to localize the interaction to the C-terminal -TTPV amino acid motif of stargazin and the PDZ1, PDZ3, and PDZ5 domains of MAGI-2. Expression of stargazin recruited MAGI-2 to cell membranes and cell-cell contact sites in transfected HEK-293T cells dependent on the presence of the stargazin -TTPV motif. These experiments identify MAGI-2 as a strong candidate for linking TARP/AMPA receptor complexes to a wide range of other postsynaptic molecules and pathways and advance our knowledge of protein interactions at mammalian CNS synapses.
Keywords: Adaptor Proteins, Signal Transducing; Animals; Brain; Calcium Channels; Extracellular Matrix; Guanylate Kinases; Mice; Mice, Inbred C57BL; Protein Transport; Proteins; Receptors, AMPA; Synapses; Synaptic Transmission

Sweetness and light: illuminating the honey bee genome. - Robinson, G E; Evans, J D; Maleszka, R; Robertson, H M; Weaver, D B; Worley, K; Richard A Gibbs; Weinstock, G M (Insect Mol Biol, 2006)
Keywords: Animals; Bees; Genome, Insect; Genomics; Sequence Analysis, DNA

Targeting iCre expression to murine progesterone receptor cell-lineages using bacterial artificial chromosome transgenesis. - Mukherjee, Atish; Soyal, Selma M; David A Wheeler; Fernández-Valdivia, Rodrigo; Nguyen, Jonathan; DeMayo, Francesco J; Lydon, John P (Genesis, 2006)
Gene-targeting in embryonic stem cells has been the dominant genetic approach when engineering mouse models to query the physiologic importance of the progesterone receptor (PR). Although these models have been instrumental in disclosing the in vivo significance of the progesterone signaling pathway, generation of such mice exacts considerable expenditure of time, effort, and expense. Considering the growing list of new PR mouse models that are urgently required to address the next questions in progestin biology, bacterial artificial chromosome (BAC) recombineering in conjunction with transgenesis was evaluated as an alternative method to accelerate the creation of these models in the future. Using this approach, we describe the generation of three PR-BAC(iCre) transgenic lines in which improved Cre recombinase (iCre) was targeted in-frame, downstream, and under the control of the PR promoter contained within a BAC transgene. Crossing with the ROSA26R revealed that the PR-BAC(iCre) transgenic expresses active iCre only in cell-lineages that express the PR. The specificity of the PR-BAC(iCre) transgene not only underscores the importance of BAC-mediated transgenesis as a quick, easy, and affordable method by which to engineer the next generation of PR mouse models, but also provides a unique opportunity to investigate transcriptional control of PR expression as well as PR structure-function relationships in vivo.
Keywords: Animals; Cell Lineage; Chromosomes, Artificial, Bacterial; Computational Biology; DNA Primers; Gene Components; Gene Transfer Techniques; Integrases; Mice; Mice, Transgenic; Models, Animal; Promoter Regions, Genetic; Receptors, Progesterone

Zebrafish dax1 is required for development of the interrenal organ, the adrenal cortex equivalent. - Zhao, Y; Yang, Z; Phelan, J K; David A Wheeler; Lin, S; McCabe, E R B (Mol Endocrinol, 2006)
Mutations in the human nuclear receptor, DAX1, cause X-linked adrenal hypoplasia congenita (AHC). We report the isolation and characterization of a DAX1 homolog, dax1, in zebrafish. The dax1 cDNA encodes a protein of 264 amino acids, including the conserved carboxy-terminal ligand binding-like motif; but the amino-terminal region lacks the unusual repeats of the DNA binding-like domain in mammals. Genomic sequence analysis indicates that the dax1 gene structure is conserved also. Whole-mount in situ hybridization revealed the onset of dax1 expression in the developing hypothalamus at approximately 26 h post fertilization (hpf). Later, at about 28 hpf, a novel expression domain for dax1 appeared in the trunk. This bilateral dax1-expressing structure was located immediately above the yolk sac, between the otic vesicle and the pronephros. Interestingly, weak and transient expression of dax1 was observed in the interrenal glands (adrenal cortical equivalents) at approximately 31 hpf. This gene was also expressed in the liver after 3 dpf in the zebrafish larvae. Disruption of dax1 function by morpholino oligonucleotides (MO) down-regulated expression of steroidogenic genes, cyp11a and star, and led to severe phenotypes similar to ff1b (SF1) MO-injected embryos. Injection of dax1 MO did not affect ff1b expression, whereas ff1b MO abolished dax1 expression in the interrenal organ. Based on these results, we propose that dax1 is the mammalian DAX1 ortholog, functions downstream of ff1b in the regulatory cascades, and is required for normal development and function of the zebrafish interrenal organ.
Keywords: Adrenal Cortex; Amino Acid Sequence; Animals; Base Sequence; DAX-1 Orphan Nuclear Receptor; DNA-Binding Proteins; Embryo, Nonmammalian; Embryonic Development; Interrenal Gland; Molecular Sequence Data; Oligonucleotides, Antisense; Phylogeny; Receptors, Retinoic Acid; Repressor Proteins; Sequence Homology, Amino Acid; Transcription Factors; Water-Electrolyte Balance; Zebrafish; Zebrafish Proteins

The alpha-amino-3-hydroxyl-5-methyl-4-isoxazolepropionate receptor trafficking regulator "stargazin" is related to the claudin family of proteins by Its ability to mediate cell-cell adhesion. - Price, Maureen G; Davis, Caleb F; Deng, Fang; Burgess, Daniel L (J Biol Chem, 2005)
Mutations in the Cacng2 gene encoding the neuronal transmembrane protein stargazin result in recessively inherited epilepsy and ataxia in "stargazer" mice. Functional studies suggest a dual role for stargazin, both as a modulatory gamma subunit for voltage-dependent calcium channels and as a regulator of post-synaptic membrane targeting for alpha-amino-3-hydroxyl-5-methyl-4-isoxazolepropionate (AMPA)-type glutamate receptors. Co-immunoprecipitation experiments demonstrate that stargazin can bind proteins of either complex in vivo, but it remains unclear whether it can associate with both complexes simultaneously. Cacng2 is one of eight closely related genes (Cacng1-8) encoding proteins with four transmembrane segments, cytoplasmic termini, and molecular masses between 25 and 44 kDa. This group of Cacng genes constitutes only one branch of a larger monophyletic assembly dominated by over 20 genes encoding proteins known as claudins. Claudins regulate cell adhesion and paracellular permeability as fundamental components of non-neuronal tight junctions. Because stargazin is structurally similar to claudins, we hypothesized that it might also have retained claudin-like functions inherited from a common ancestor. Here, we report that expression of stargazin in mouse L-fibroblasts results in cell aggregation comparable with that produced by claudins, and present evidence that the interaction is heterotypic and calcium dependent. The data suggest that the cell adhesion function of stargazin preceded its current role in neurons as a regulator of either voltage-dependent calcium channels or AMPA receptors. We speculate these complexes may have co-opted the established presence of stargazin at sites of close cell-cell contact to facilitate their own evolving intercellular signaling functions.
Keywords: Amino Acid Sequence; Animals; Base Sequence; Calcium Channels; Cell Adhesion; Cell Line; DNA; Humans; L Cells; Membrane Proteins; Mice; Microscopy, Electron; Molecular Sequence Data; Multigene Family; Mutation; Neurons; Phylogeny; Receptors, AMPA; Recombinant Proteins; Sequence Homology, Amino Acid; Signal Transduction; Transfection

Analysis of the Par2 modifier of pulmonary adenoma formation in mice. - Wang, Min; Wang, Yian; You, Ming; Devereux, Theodora R (Exp Lung Res, 2005)
Inbred strains of mouse show various susceptibilities to spontaneous and chemical-induced lung tumorigenesis. Genetic analyses have revealed that lung tumor susceptibilities of inbred mouse strains are governed by quantitative trait loci (QLTs) located on multiple chromosomes. A major lung tumor resistance QLT, designated pulmonary adenoma resistance 2 (Par2), was mapped to the mouse chromosome 18 independently by several groups and accounted for up to 60% phenotype variance between susceptible A/J and more resistant BALB/c strains. The authors recently conducted studies to positionally clone the Par2 gene. This review summarizes the effort and progress towards the identification of Par2 candidates.
Keywords: Adenoma; Amino Acid Sequence; Animals; Chromosome Mapping; Gene Expression; Genetic Predisposition to Disease; Lung Neoplasms; Mice; Molecular Sequence Data; Polymorphism, Genetic; Quantitative Trait Loci

Combined genealogical, mapping, and expression approaches to identify spontaneously hypertensive rat hypertension candidate genes. - Hinojos, Cruz A; Eric Boerwinkle; Fornage, Myriam; Doris, Peter A (Hypertension, 2005)
Allelic expression in genes has become recognized as a heritable trait by which phenotypes are generated. We have examined gene expression in the rat kidney using genome-wide microarray technology (Affymetrix). Gene expression was determined across 4 rat strains, 3 hypertensive spontaneously hypertensive rat (SHR) substrains (SHR-A3, SHR-B2, and SHR-C), and a normotensive strain (Wistar-Kyoto [WKY]). Expression measurements were made in multiple animals from all strains at 4 time points (4 weeks, 8 weeks, 12 weeks, and 18 weeks of age), covering the prehypertensive period in SHR (4 weeks), and the period of rapidly rising blood pressure (8 and 12 weeks) and of sustained hypertension (18 weeks). Regression analysis revealed a close relationship across all strains during the first 3 time points, after which SHR-A3 became a substantial outlier. SHR-B2 and SHR-C demonstrated a very close relationship in gene expression at all times but also showed increased differences compared with the other strains at 18 weeks of age. We identified genes that were consistently different in expression, comparing all SHR substrains at each time point with WKY. The resulting list of genes was compared with blood pressure quantitative trait loci reported for SHR to refine a number of genes consistently differentially expressed between SHR substrains and WKY, persistently differentially expressed across multiple time points, and located in SHR blood pressure-determinative regions of the genome. Genealogical relationships and SHR substrain intercrosses suggest that genes responsible for heritable hypertension in SHR are shared across SHR substrains. The present approach identifies a number of genes that may influence blood pressure in SHR by virtue of allelic effects on gene expression.
Keywords: Animals; Blood Pressure; Chromosome Mapping; Expressed Sequence Tags; Gene Expression; Genome; Hypertension; Kidney; Oligonucleotide Array Sequence Analysis; Pedigree; Quantitative Trait Loci; Rats; Rats, Inbred SHR; Rats, Inbred WKY; Regression Analysis; Species Specificity

Comparative genome sequencing of Drosophila pseudoobscura: chromosomal, gene, and cis-element evolution. - Stephen Richards; Liu, Yue; Bettencourt, Brian R; Hradecky, Pavel; Letovsky, Stan; Nielsen, Rasmus; Thornton, Kevin; Hubisz, Melissa J; Rui Chen; Meisel, Richard P; Couronne, Olivier; Hua, Sujun; et al. (Genome Res, 2005)
We have sequenced the genome of a second Drosophila species, Drosophila pseudoobscura, and compared this to the genome sequence of Drosophila melanogaster, a primary model organism. Throughout evolution the vast majority of Drosophila genes have remained on the same chromosome arm, but within each arm gene order has been extensively reshuffled, leading to a minimum of 921 syntenic blocks shared between the species. A repetitive sequence is found in the D. pseudoobscura genome at many junctions between adjacent syntenic blocks. Analysis of this novel repetitive element family suggests that recombination between offset elements may have given rise to many paracentric inversions, thereby contributing to the shuffling of gene order in the D. pseudoobscura lineage. Based on sequence similarity and synteny, 10,516 putative orthologs have been identified as a core gene set conserved over 25-55 million years (Myr) since the pseudoobscura/melanogaster divergence. Genes expressed in the testes had higher amino acid sequence divergence than the genome-wide average, consistent with the rapid evolution of sex-specific proteins. Cis-regulatory sequences are more conserved than random and nearby sequences between the species--but the difference is slight, suggesting that the evolution of cis-regulatory elements is flexible. Overall, a pattern of repeat-mediated chromosomal rearrangement, and high coadaptation of both male genes and cis-regulatory sequences emerges as important themes of genome divergence between these species of Drosophila.
Keywords: Animals; Chromosome Breakage; Chromosome Inversion; Chromosome Mapping; Chromosomes; Conserved Sequence; Drosophila; Drosophila melanogaster; Enhancer Elements, Genetic; Evolution, Molecular; Gene Rearrangement; Genes, Insect; Genetic Variation; Genome; Molecular Sequence Data; Predictive Value of Tests; Repetitive Sequences, Nucleic Acid; Sequence Analysis, DNA

Deletion of FMR1 in Purkinje cells enhances parallel fiber LTD, enlarges spines, and attenuates cerebellar eyelid conditioning in Fragile X syndrome. - Koekkoek, S K E; Yamaguchi, K; Milojkovic, B A; Dortland, B R; Ruigrok, T J H; Maex, R; De Graaf, W; Smit, A E; VanderWerf, F; Bakker, C E; Willemsen, R; Ikeda, T; et al. (Neuron, 2005)
Absence of functional FMRP causes Fragile X syndrome. Abnormalities in synaptic processes in the cerebral cortex and hippocampus contribute to cognitive deficits in Fragile X patients. So far, the potential roles of cerebellar deficits have not been investigated. Here, we demonstrate that both global and Purkinje cell-specific knockouts of Fmr1 show deficits in classical delay eye-blink conditioning in that the percentage of conditioned responses as well as their peak amplitude and peak velocity are reduced. Purkinje cells of these mice show elongated spines and enhanced LTD induction at the parallel fiber synapses that innervate these spines. Moreover, Fragile X patients display the same cerebellar deficits in eye-blink conditioning as the mutant mice. These data indicate that a lack of FMRP leads to cerebellar deficits at both the cellular and behavioral levels and raise the possibility that cerebellar dysfunctions can contribute to motor learning deficits in Fragile X patients.
Keywords: Animals; Cerebellum; Conditioning, Eyelid; Dendrites; Fragile X Mental Retardation Protein; Fragile X Syndrome; Gene Deletion; Humans; Long-Term Synaptic Depression; Male; Mice; Mice, Knockout; Mice, Mutant Strains; Models, Neurological; Nerve Fibers; Nerve Tissue Proteins; Purkinje Cells; Reflex, Startle; RNA-Binding Proteins

Differentiation of embryonic stem cells into corneal epithelium. - Wang, Zhichong; Ge, Jian; Huang, Bing; Gao, Qianying; Liu, Bingqian; Wang, Linghua; Yu, Ling; Fan, Zhigang; Lu, Xiaoming; Liu, Jingbo (Sci China C Life Sci, 2005)
Our project was to determine whether embryonic stem (ES) cells could be induced to differentiate into corneal epithelia by superficial corneoscleral limbal stroma. To achieve this goal, ES-GFP cell line D3 was pre-induced by retinoic acid (RA). The pre-induced cells were seeded on deepithelialized superficial corneoscleral slices (SCSS) to form a monolayer, and divided into three groups. Group 1 was cultured and passaged in vitro for direct detection. Group 2 was exposed to air-liquid interfaces for 10 days and implanted into the subcutaneous layer of nude mice for 2 weeks for further induction in vivo. Group 3 was cultured in vitro without any inducing factors for control. There were no teratomas found in nude mice which were implanted with differentiated ES cells after two weeks. The differentiated cells showed an appearance of epithelia both in vitro and in vivo. Expression of CK3, P63 and PCNA was detected by immunohistochemical staining in the differentiated cells in group 1 and 2. Microvillis and zonula occludens were observed on the surface of the differentiated cells under an electron microscope. In the control group, ES cells differentiated freely without any inducing factors. Most cells were shed and formed a neuronal dendrite-like structure, and a minority of cells appeared polymorphic. These results demonstrate that ES cells can differentiate into corneal epithelia on the surface of SCSS under the controlled condition. Differentiated ES cells could be used as epithelial seeding cells for the reconstruction of ocular surface and corneal tissue engineering in the future.
Keywords: Animals; Cell Culture Techniques; Cell Differentiation; Cell Line; Embryonic Induction; Embryonic Stem Cells; Epithelium, Corneal; Extracellular Matrix; Mice; Mice, Inbred BALB C; Mice, Nude; Rabbits

The DNA sequence of the human X chromosome. - Ross, Mark T; Grafham, Darren V; Coffey, Alison J; Scherer, Steven; McLay, Kirsten; Donna M Muzny; Platzer, Matthias; Howell, Gareth R; Burrows, Christine; Bird, Christine P; Frankish, Adam; Lovell, Frances L; et al. (Nature, 2005)
The human X chromosome has a unique biology that was shaped by its evolution as the sex chromosome shared by males and females. We have determined 99.3% of the euchromatic sequence of the X chromosome. Our analysis illustrates the autosomal origin of the mammalian sex chromosomes, the stepwise process that led to the progressive loss of recombination between X and Y, and the extent of subsequent degradation of the Y chromosome. LINE1 repeat elements cover one-third of the X chromosome, with a distribution that is consistent with their proposed role as way stations in the process of X-chromosome inactivation. We found 1,098 genes in the sequence, of which 99 encode proteins expressed in testis and in various tumour types. A disproportionately high number of mendelian diseases are documented for the X chromosome. Of this number, 168 have been explained by mutations in 113 X-linked genes, which in many cases were characterized with the aid of the DNA sequence.
Keywords: Animals; Antigens, Neoplasm; Centromere; Chromosomes, Human, X; Chromosomes, Human, Y; Contig Mapping; Crossing Over, Genetic; Dosage Compensation, Genetic; Evolution, Molecular; Female; Genetic Linkage; Genetics, Medical; Genomics; Humans; Male; Polymorphism, Single Nucleotide; Repetitive Sequences, Nucleic Acid; RNA; Sequence Analysis, DNA; Sequence Homology, Nucleic Acid; Testis

Dual regulation and redundant function of two eye-specific enhancers of the Drosophila retinal determination gene dachshund. - Pappu, Kartik S; Ostrin, Edwin J; Middlebrooks, Brooke W; Sili, Beril Tavsanli; Rui Chen; Atkins, Mardelle R; Richard A Gibbs; Mardon, Graeme (Development, 2005)
Drosophila eye development is controlled by a conserved network of retinal determination (RD) genes. The RD genes encode nuclear proteins that form complexes and function in concert with extracellular signal-regulated transcription factors. Identification of the genomic regulatory elements that govern the eye-specific expression of the RD genes will allow us to better understand how spatial and temporal control of gene expression occurs during early eye development. We compared conserved non-coding sequences (CNCSs) between five Drosophilids along the approximately 40 kb genomic locus of the RD gene dachshund (dac). Our analysis uncovers two separate eye enhancers in intron eight and the 3' non-coding regions of the dac locus defined by clusters of highly conserved sequences. Loss- and gain-of-function analyses suggest that the 3' eye enhancer is synergistically activated by a combination of eya, so and dpp signaling, and only indirectly activated by ey, whereas the 5' eye enhancer is primarily regulated by ey, acting in concert with eya and so. Disrupting conserved So-binding sites in the 3' eye enhancer prevents reporter expression in vivo. Our results suggest that the two eye enhancers act redundantly and in concert with each other to integrate distinct upstream inputs and direct the eye-specific expression of dac.
Keywords: 3' Untranslated Regions; Animals; Base Sequence; DNA-Binding Proteins; Drosophila; Drosophila Proteins; Enhancer Elements, Genetic; Eye Proteins; Gene Expression Regulation, Developmental; Genome; Homeodomain Proteins; Homozygote; Introns; Molecular Sequence Data; Mutation; Nuclear Proteins; Organ Specificity; Response Elements; Retina

Emerging technologies in DNA sequencing. - Metzker, Michael L (Genome Res, 2005)
Demand for DNA sequence information has never been greater, yet current Sanger technology is too costly, time consuming, and labor intensive to meet this ongoing demand. Applications span numerous research interests, including sequence variation studies, comparative genomics and evolution, forensics, and diagnostic and applied therapeutics. Several emerging technologies show promise of delivering next-generation solutions for fast and affordable genome sequencing. In this review article, the DNA polymerase-dependent strategies of Sanger sequencing, single nucleotide addition, and cyclic reversible termination are discussed to highlight recent advances and potential challenges these technologies face in their development for ultrafast DNA sequencing.
Keywords: Animals; Base Sequence; DNA; DNA-Directed DNA Polymerase; Humans; Sequence Analysis, DNA

Evolutionarily conserved elements in vertebrate, insect, worm, and yeast genomes. - Siepel, Adam; Bejerano, Gill; Pedersen, Jakob S; Hinrichs, Angie S; Hou, Minmei; Rosenbloom, Kate; Clawson, Hiram; Spieth, John; Hillier, LaDeana W; Stephen Richards; Weinstock, George M; Wilson, Richard K; et al. (Genome Res, 2005)
We have conducted a comprehensive search for conserved elements in vertebrate genomes, using genome-wide multiple alignments of five vertebrate species (human, mouse, rat, chicken, and Fugu rubripes). Parallel searches have been performed with multiple alignments of four insect species (three species of Drosophila and Anopheles gambiae), two species of Caenorhabditis, and seven species of Saccharomyces. Conserved elements were identified with a computer program called phastCons, which is based on a two-state phylogenetic hidden Markov model (phylo-HMM). PhastCons works by fitting a phylo-HMM to the data by maximum likelihood, subject to constraints designed to calibrate the model across species groups, and then predicting conserved elements based on this model. The predicted elements cover roughly 3%-8% of the human genome (depending on the details of the calibration procedure) and substantially higher fractions of the more compact Drosophila melanogaster (37%-53%), Caenorhabditis elegans (18%-37%), and Saccharaomyces cerevisiae (47%-68%) genomes. From yeasts to vertebrates, in order of increasing genome size and general biological complexity, increasing fractions of conserved bases are found to lie outside of the exons of known protein-coding genes. In all groups, the most highly conserved elements (HCEs), by log-odds score, are hundreds or thousands of bases long. These elements share certain properties with ultraconserved elements, but they tend to be longer and less perfectly conserved, and they overlap genes of somewhat different functional categories. In vertebrates, HCEs are associated with the 3' UTRs of regulatory genes, stable gene deserts, and megabase-sized regions rich in moderately conserved noncoding sequences. Noncoding HCEs also show strong statistical evidence of an enrichment for RNA secondary structure.
Keywords: 3' Untranslated Regions; Animals; Base Pairing; Base Sequence; Caenorhabditis elegans; Conserved Sequence; DNA, Intergenic; Evolution, Molecular; Genome; Humans; Insecta; Molecular Sequence Data; Saccharomyces; Vertebrates; Yeasts

Generation and annotation of the DNA sequences of human chromosomes 2 and 4. - Hillier, LaDeana W; Graves, Tina A; Fulton, Robert S; Fulton, Lucinda A; Pepin, Kymberlie H; Minx, Patrick; Wagner-McPherson, Caryn; Layman, Dan; Wylie, Kristine; Sekhon, Mandeep; Becker, Michael C; Fewell, Ginger A; et al. (Nature, 2005)
Human chromosome 2 is unique to the human lineage in being the product of a head-to-head fusion of two intermediate-sized ancestral chromosomes. Chromosome 4 has received attention primarily related to the search for the Huntington's disease gene, but also for genes associated with Wolf-Hirschhorn syndrome, polycystic kidney disease and a form of muscular dystrophy. Here we present approximately 237 million base pairs of sequence for chromosome 2, and 186 million base pairs for chromosome 4, representing more than 99.6% of their euchromatic sequences. Our initial analyses have identified 1,346 protein-coding genes and 1,239 pseudogenes on chromosome 2, and 796 protein-coding genes and 778 pseudogenes on chromosome 4. Extensive analyses confirm the underlying construction of the sequence, and expand our understanding of the structure and evolution of mammalian chromosomes, including gene deserts, segmental duplications and highly variant regions.
Keywords: Animals; Base Composition; Base Sequence; Centromere; Chromosomes, Human, Pair 2; Chromosomes, Human, Pair 4; Conserved Sequence; CpG Islands; Euchromatin; Expressed Sequence Tags; Gene Duplication; Genetic Variation; Genomics; Humans; Molecular Sequence Data; Physical Chromosome Mapping; Polymorphism, Genetic; Primates; Proteins; Pseudogenes; Recombination, Genetic; RNA, Messenger; RNA, Untranslated; Sequence Analysis, DNA

The genome of the social amoeba Dictyostelium discoideum. - Eichinger, L; Pachebat, J A; Glöckner, G; Rajandream, M-A; Sucgang, R; Berriman, M; Song, J; Olsen, R; Szafranski, K; Xu, Q; Tunggal, B; Kummerfeld, S; et al. (Nature, 2005)
The social amoebae are exceptional in their ability to alternate between unicellular and multicellular forms. Here we describe the genome of the best-studied member of this group, Dictyostelium discoideum. The gene-dense chromosomes of this organism encode approximately 12,500 predicted proteins, a high proportion of which have long, repetitive amino acid tracts. There are many genes for polyketide synthases and ABC transporters, suggesting an extensive secondary metabolism for producing and exporting small molecules. The genome is rich in complex repeats, one class of which is clustered and may serve as centromeres. Partial copies of the extrachromosomal ribosomal DNA (rDNA) element are found at the ends of each chromosome, suggesting a novel telomere structure and the use of a common mechanism to maintain both the rDNA and chromosomal termini. A proteome-based phylogeny shows that the amoebozoa diverged from the animal-fungal lineage after the plant-animal split, but Dictyostelium seems to have retained more of the diversity of the ancestral genome than have plants, animals or fungi.
Keywords: Animals; ATP-Binding Cassette Transporters; Base Composition; Cell Adhesion; Cell Movement; Centromere; Conserved Sequence; Dictyostelium; DNA Transposable Elements; DNA, Ribosomal; Eukaryotic Cells; Gene Duplication; Gene Transfer, Horizontal; Genome; Genomics; Humans; Molecular Sequence Data; Phylogeny; Proteome; Protozoan Proteins; Repetitive Sequences, Nucleic Acid; RNA, Transfer; Sequence Analysis, DNA; Signal Transduction; Social Behavior; Telomere

Genome scale identification of Treponema pallidum antigens. - McKevitt, Matthew; Brinkman, Mary Beth; McLoughlin, Melanie; Perez, Carla; Howell, Jerrilyn K; Weinstock, George M; Norris, Steven J; Palzkill, Timothy (Infect Immun, 2005)
Antibody responses for 882 of the 1,039 proteins in the proteome of Treponema pallidum were examined. Sera collected from infected rabbits were used to systematically identify 106 antigenic proteins, including 22 previously identified antigens and 84 novel antigens. Additionally, sera collected from rabbits throughout the course of infection demonstrated a progression in the breadth and intensity of humoral immunoreactivity against a representative panel of T. pallidum antigens.
Keywords: Animals; Antibodies, Bacterial; Antigens, Bacterial; Genome, Bacterial; Proteome; Rabbits; Treponema pallidum

Identification of genetic polymorphisms through comparative DNA sequence analysis on the K-ras gene: implications for lung tumor susceptibility. - Wang, Min; Wang, Yian; You, Ming (Exp Lung Res, 2005)
In the present study, the authors performed a comparative sequence analysis of the K-ras gene. By comparing sequences from different mouse inbred strains, the authors have identified new nucleotide polymorphisms in the noncoding regions of mouse K-ras gene. They have also identified noncoding DNA segments evolutionarily conserved among the human, mouse, and rat. Computational analysis for transcription factor binding sites suggests that these polymorphic and conserved DNA sequences harbor potential cis-regulatory elements, which may contribute to the transcriptional regulation of the K-ras gene. Further studies on these potential regulatory sites may help to elucidate the fundamental mechanism underlying allele-specific activation and expression of K-ras gene in hybrid mouse lung tumors, which determines lung tumor susceptibility in mice.
Keywords: Animals; Base Sequence; Binding Sites; Conserved Sequence; DNA, Neoplasm; Gene Deletion; Genes, ras; Genetic Predisposition to Disease; Humans; Lung Neoplasms; Mice; Mice, Inbred Strains; Molecular Sequence Data; Polymorphism, Genetic; Promoter Regions, Genetic; Rats; Sequence Homology, Nucleic Acid; Transcription Factors

Keeping an eye on the fly genome. - Rui Chen; Mardon, Graeme (Dev Biol, 2005)
With its unique structure and dynamic development, the Drosophila eye has been a powerful genetic model system for studying molecular mechanisms of cell fate specification and differentiation. Hundreds of genes that function in a complex genetic network controlling this process have been identified during the past two decades. To further advance our understanding of the molecular mechanisms of eye development, it is increasingly important to place the current genetic pathway into a whole-genome perspective. Here, we review emerging technologies and strategies that will help to achieve this goal, including generation of a complete mutant set in Drosophila, genome-wide transcription factor target identification, and systematic studies of gene function aided by computational biology.
Keywords: Animals; Cell Differentiation; Computational Biology; Drosophila; Eye; Genome; Genomics; Mutation; Transcription Factors

Lineage-specific expansions of retroviral insertions within the genomes of African great apes but not humans and orangutans. - Yohn, Chris T; Jiang, Zhaoshi; McGrath, Sean D; Hayden, Karen E; Khaitovich, Philipp; Johnson, Matthew E; Eichler, Marla Y; McPherson, John D; Zhao, Shaying; Pääbo, Svante; Eichler, Evan E (PLoS Biol, 2005)
Retroviral infections of the germline have the potential to episodically alter gene function and genome structure during the course of evolution. Horizontal transmissions between species have been proposed, but little evidence exists for such events in the human/great ape lineage of evolution. Based on analysis of finished BAC chimpanzee genome sequence, we characterize a retroviral element (Pan troglodytes endogenous retrovirus 1 [PTERV1]) that has become integrated in the germline of African great ape and Old World monkey species but is absent from humans and Asian ape genomes. We unambiguously map 287 retroviral integration sites and determine that approximately 95.8% of the insertions occur at non-orthologous regions between closely related species. Phylogenetic analysis of the endogenous retrovirus reveals that the gorilla and chimpanzee elements share a monophyletic origin with a subset of the Old World monkey retroviral elements, but that the average sequence divergence exceeds neutral expectation for a strictly nuclear inherited DNA molecule. Within the chimpanzee, there is a significant integration bias against genes, with only 14 of these insertions mapping within intronic regions. Six out of ten of these genes, for which there are expression data, show significant differences in transcript expression between human and chimpanzee. Our data are consistent with a retroviral infection that bombarded the genomes of chimpanzees and gorillas independently and concurrently, 3-4 million years ago. We speculate on the potential impact of such recent events on the evolution of humans and great apes.
Keywords: Animals; Chromosome Mapping; Endogenous Retroviruses; Gorilla gorilla; Hominidae; Humans; Introns; Molecular Sequence Data; Pan troglodytes; Pongo pygmaeus; Protein Biosynthesis; Retroelements; Species Specificity; Transcription, Genetic

Orphan nuclear receptor GCNF is required for the repression of pluripotency genes during retinoic acid-induced embryonic stem cell differentiation. - Gu, Peili; LeMenuet, Damien; Chung, Arthur C-K; Mancini, Michael; Wheeler, David A; Cooney, Austin J (Mol Cell Biol, 2005)
Embryonic stem (ES) cell pluripotency and differentiation are controlled by a network of transcription factors and signaling molecules. Transcription factors such as Oct4 and Nanog are required for self-renewal and maintain the undifferentiated state of ES cells. Decreases in the expression of these factors indicate the initiation of differentiation of ES cells. Inactivation of the gene encoding the orphan nuclear receptor GCNF showed that it plays an important role in the repression of Oct4 expression in somatic cells during early embryonic development. GCNF-/- ES cells were isolated to study the function of GCNF in the down-regulation of pluripotency genes during differentiation. Loss of repression of ES cell marker genes Oct4, Nanog, Sox2, FGF4, and Stella was observed upon treatment of GCNF-/- ES cells with retinoic acid. The loss of repression of pluripotency genes is either a direct or indirect consequence of loss of GCNF. Both the Oct4 and Nanog genes are direct targets of GCNF repression during ES cell differentiation and early mouse embryonic development. In contrast Sox2 and FGF4 are indirectly regulated by GCNF through Oct4. These findings establish a central role for GCNF in the repression of pluripotency gene expression during retinoic acid-induced ES cell differentiation.
Keywords: Animals; Blotting, Northern; Blotting, Western; Cell Differentiation; Cell Line; Cell Nucleus; Chromatin Immunoprecipitation; DNA-Binding Proteins; Down-Regulation; Embryo, Mammalian; Female; Fibroblast Growth Factor 4; Genotype; Homeodomain Proteins; In Situ Hybridization; Male; Mice; Mice, Transgenic; Microscopy, Fluorescence; Models, Genetic; Nanog Homeobox Protein; Nuclear Receptor Subfamily 6, Group A, Member 1; Octamer Transcription Factor-3; Phenotype; Plasmids; Protein Binding; Receptors, Cytoplasmic and Nuclear; Response Elements; Reverse Transcriptase Polymerase Chain Reaction; Signal Transduction; SOXB1 Transcription Factors; Stem Cells; Time Factors; Trans-Activators; Transfection; Tretinoin

Orphan nuclear receptor LRH-1 is required to maintain Oct4 expression at the epiblast stage of embryonic development. - Gu, Peili; Goodwin, Bryan; Chung, Arthur C-K; Xu, Xueping; Wheeler, David A; Price, Roger R; Galardi, Cristin; Peng, Li; Latour, Anne M; Koller, Beverly H; Gossen, Jan; Kliewer, Steven A; et al. (Mol Cell Biol, 2005)
Oct4 plays an essential role in maintaining the inner cell mass and pluripotence of embryonic stem (ES) cells. The expression of Oct4 is regulated by the proximal enhancer and promoter in the epiblast and by the distal enhancer and promoter at all other stages in the pluripotent cell lineage. Here we report that the orphan nuclear receptor LRH-1, which is expressed in undifferentiated ES cells, can bind to SF-1 response elements in the proximal promoter and proximal enhancer of the Oct4 gene and activate Oct4 reporter gene expression. LRH-1 is colocalized with Oct4 in the inner cell mass and the epiblast of embryos at early developmental stages. Disruption of the LRH-1 gene results in loss of Oct4 expression at the epiblast stage and early embryonic death. Using LRH-1(-/-) ES cells, we also show that LRH-1 is required to maintain Oct4 expression at early differentiation time points. In vitro and in vivo results show that LRH-1 plays an essential role in the maintenance of Oct4 expression in ES cells at the epiblast stage of embryonic development, thereby maintaining pluripotence at this crucial developmental stage prior to segregation of the primordial germ cell lineage at gastrulation.
Keywords: Animals; Blastocyst; Cell Differentiation; DNA-Binding Proteins; Down-Regulation; Embryo, Mammalian; Embryonic Development; Gene Expression Regulation, Developmental; Gene Silencing; Genes, Lethal; Mice; Octamer Transcription Factor-3; Receptors, Cytoplasmic and Nuclear; Response Elements; Stem Cells; Transcription Factors; Up-Regulation

Pas1c1 is a candidate for the mouse pulmonary adenoma susceptibility 1 locus. - Wang, Min; Futamura, Manabu; Wang, Yian; You, Ming (Oncogene, 2005)
Pas1 candidate 1 (Pas1c1) gene (also named Lmna-rs1) was found to encode two alternatively spliced mRNA transcripts (i.e. Pas1c1-Va and Pas1c1-Vb). In this study, we identified three additional mRNA transcripts encoded by the Pas1c1 gene, which were designated as Pas1c1-Vc, Pas1c1-Vd, and Pas1c1-Ve, respectively. Similar to Pas1c1-Vb, the newly identified transcripts were only expressed in mouse lung tissues from strains carrying the Pas1-susceptible (Pas1/s) allele. Pas1c1 transcripts were also detected in heart, testis, or brain but not in liver, spleen, or kidney. An 11-nucleotide polymorphism was found within the 3'-acceptor splice site of exon 8, which cosegregates with mouse strain Pas1 alleles and may underlie the strain-specific exon 8 skipping. We also found that ectopic expression of the Pas1c1-Va and Pas1c1-Vb in COS7 and NIH3T3 cells exhibited distinct intracellular distributions. These results support that Pas1c1 as a candidate for the Pas1 locus and the strain-specific isoforms may have differential effects on cell proliferation.
Keywords: Adenoma; Amino Acid Sequence; Animals; Base Sequence; DNA Primers; Exons; Genetic Predisposition to Disease; Lung Neoplasms; Mice; Molecular Sequence Data; Sequence Alignment; Sequence Homology, Amino Acid; Tumor Suppressor Proteins

Pooled genomic indexing of rhesus macaque. - Milosavljevic, Aleksandar; R. Alan Harris; Sodergren, Erica J; Jackson, Andrew R; Kalafus, Ken J; Hodgson, Anne; Cree, Andrew; Dai, Weilie; Csuros, Miklos; Zhu, Baoli; De Jong, Pieter J; Weinstock, George M; et al. (Genome Res, 2005)
Pooled genomic indexing (PGI) is a method for mapping collections of bacterial artificial chromosome (BAC) clones between species by using a combination of clone pooling and DNA sequencing. PGI has been used to map a total of 3858 BAC clones covering approximately 24% of the rhesus macaque (Macaca mulatta) genome onto 4178 homologous loci in the human genome. A number of intrachromosomal rearrangements were detected by mapping multiple segments within the individual rhesus BACs onto multiple disjoined loci in the human genome. Transversal pooling designs involving shuffled BAC arrays were employed for robust mapping even with modest DNA sequence read coverage. A further innovation, short-tag pooled genomic indexing (ST-PGI), was also introduced to further improve the economy of mapping by sequencing multiple, short, mapable tags within a single sequencing reaction.
Keywords: Animals; Chromosome Aberrations; Chromosomes, Artificial, Bacterial; Contig Mapping; DNA; Genetic Markers; Genome; Genome, Human; Humans; Macaca mulatta; Sequence Alignment; Sequence Analysis, DNA

Punctuated duplication seeding events during the evolution of human chromosome 2p11. - Horvath, Julie E; Gulden, Cassandra L; Vallente, Rhea U; Eichler, Marla Y; Ventura, Mario; McPherson, John D; Graves, Tina A; Wilson, Richard K; Schwartz, Stuart; Rocchi, Mariano; Eichler, Evan E (Genome Res, 2005)
Primate genomic sequence comparisons are becoming increasingly useful for elucidating the evolutionary history and organization of our own genome. Such studies are particularly informative within human pericentromeric regions--areas of particularly rapid change in genomic structure. Here, we present a systematic analysis of the evolutionary history of one approximately 700-kb region of 2p11, including the first autosomal transition from pericentromeric sequence to higher-order alpha-satellite DNA. We show that this region is composed of segmental duplications corresponding to 14 ancestral segments ranging in size from 4 kb to approximately 115 kb. These duplicons show 94%-98.5% sequence identity to their ancestral loci. Comparative FISH and phylogenetic analysis indicate that these duplicons are differentially distributed in human, chimpanzee, and gorilla genomes, whereas baboon has a single putative ancestral locus for all but one of the duplications. Our analysis supports a model where duplicative transposition events occurred during a narrow window of evolution after the separation of the human/ape lineage from the Old World monkeys (10-20 million years ago). Although dramatic secondary dispersal events occurred during the radiation of the human, chimpanzee, and gorilla lineages, duplicative transposition seeding events of new material to this particular pericentromeric region abruptly ceased after this time period. The multiplicity of initial duplicative transpositions prior to the separation of humans and great-apes suggests a punctuated model for the formation of highly duplicated pericentromeric regions within the human genome. The data further indicate that factors other than sequence are important determinants for such bursts of duplicative transposition from the euchromatin to pericentromeric regions.
Keywords: Animals; Centromere; Chromosomes, Artificial, Bacterial; Chromosomes, Human, Pair 2; Evolution, Molecular; Gene Duplication; Humans; In Situ Hybridization, Fluorescence; Models, Genetic; Molecular Sequence Data; Nucleic Acid Hybridization; Phylogeny; Polymerase Chain Reaction; Sequence Analysis, DNA

SNPdetector: a software tool for sensitive and accurate SNP detection. - Zhang, Jinghui; Wheeler, David A; Yakub, Imtiaz; Wei, Sharon; Sood, Raman; Rowe, William; Liu, Paul P; Richard A Gibbs; Buetow, Kenneth H (PLoS Comput Biol, 2005)
Identification of single nucleotide polymorphisms (SNPs) and mutations is important for the discovery of genetic predisposition to complex diseases. PCR resequencing is the method of choice for de novo SNP discovery. However, manual curation of putative SNPs has been a major bottleneck in the application of this method to high-throughput screening. Therefore it is critical to develop a more sensitive and accurate computational method for automated SNP detection. We developed a software tool, SNPdetector, for automated identification of SNPs and mutations in fluorescence-based resequencing reads. SNPdetector was designed to model the process of human visual inspection and has a very low false positive and false negative rate. We demonstrate the superior performance of SNPdetector in SNP and mutation analysis by comparing its results with those derived by human inspection, PolyPhred (a popular SNP detection tool), and independent genotype assays in three large-scale investigations. The first study identified and validated inter- and intra-subspecies variations in 4,650 traces of 25 inbred mouse strains that belong to either the Mus musculus species or the M. spretus species. Unexpected heterozygosity in CAST/Ei strain was observed in two out of 1,167 mouse SNPs. The second study identified 11,241 candidate SNPs in five ENCODE regions of the human genome covering 2.5 Mb of genomic sequence. Approximately 50% of the candidate SNPs were selected for experimental genotyping; the validation rate exceeded 95%. The third study detected ENU-induced mutations (at 0.04% allele frequency) in 64,896 traces of 1,236 zebra fish. Our analysis of three large and diverse test datasets demonstrated that SNPdetector is an effective tool for genome-scale research and for large-sample clinical studies. SNPdetector runs on Unix/Linux platform and is available publicly (http://lpg.nci.nih.gov).
Keywords: Algorithms; Alleles; Animals; Computational Biology; Gene Frequency; Genome; Genotype; Heterozygote; Humans; Polymorphism, Genetic; Polymorphism, Single Nucleotide; Reproducibility of Results; Sensitivity and Specificity; Software

Transcriptome of Treponema pallidum: gene expression profile during experimental rabbit infection. - Smajs, David; McKevitt, Matthew; Howell, Jerrilyn K; Norris, Steven J; Cai, Wei-Wen; Palzkill, Timothy; Weinstock, George M (J Bacteriol, 2005)
RNA transcript levels in the syphilis spirochete Treponema pallidum subsp. pallidum (Nichols) isolated from experimentally infected rabbits were determined by the use of DNA microarray technology. This characterization of the T. pallidum transcriptome during experimental infection provides further insight into the importance of gene expression levels for the survival and pathogenesis of this bacterium.
Keywords: Animals; Gene Expression; Gene Expression Profiling; Oligonucleotide Array Sequence Analysis; Open Reading Frames; Rabbits; RNA, Bacterial; RNA, Messenger; Syphilis; Treponema pallidum

Advances in genome biology and technology. - Gunaratne, Preethi H (Expert Rev Mol Diagn, 2004)
Keywords: Animals; Biotechnology; Expressed Sequence Tags; Gene Expression Profiling; Genome; Genomic Library; Genomics; Humans; Stem Cells

The Atlas genome assembly system. - Havlak, Paul; Rui Chen; Durbin, K James; Egan, Amy; Ren, Yanru; Song, Xing-Zhi; Weinstock, George M; Richard A Gibbs (Genome Res, 2004)
Atlas is a suite of programs developed for assembly of genomes by a "combined approach" that uses DNA sequence reads from both BACs and whole-genome shotgun (WGS) libraries. The BAC clones afford advantages of localized assembly with reduced computational load, and provide a robust method for dealing with repeated sequences. Inclusion of WGS sequences facilitates use of different clone insert sizes and reduces data production costs. A core function of Atlas software is recruitment of WGS sequences into appropriate BACs based on sequence overlaps. Because construction of consensus sequences is from local assembly of these reads, only small (<0.1%) units of the genome are assembled at a time. Once assembled, each BAC is used to derive a genomic layout. This "sequence-based" growth of the genome map has greater precision than with non-sequence-based methods. Use of BACs allows correction of artifacts due to repeats at each stage of the process. This is aided by ancillary data such as BAC fingerprint, other genomic maps, and syntenic relations with other genomes. Atlas was used to assemble a draft DNA sequence of the rat genome; its major components including overlapper and split-scaffold are also being used in pure WGS projects.
Keywords: Animals; Chromosomes, Artificial, Bacterial; Contig Mapping; Genome; Rats; Software

Biochemical and genetic interaction between the fragile X mental retardation protein and the microRNA pathway. - Jin, Peng; Zarnescu, Daniela C; Ceman, Stephanie; Nakamoto, Mika; Mowrey, Julie; Jongens, Thomas A; Nelson, David L; Moses, Kevin; Warren, Stephen T (Nat Neurosci, 2004)
Fragile X syndrome is caused by a loss of expression of the fragile X mental retardation protein (FMRP). FMRP is a selective RNA-binding protein which forms a messenger ribonucleoprotein (mRNP) complex that associates with polyribosomes. Recently, mRNA ligands associated with FMRP have been identified. However, the mechanism by which FMRP regulates the translation of its mRNA ligands remains unclear. MicroRNAs are small noncoding RNAs involved in translational control. Here we show that in vivo mammalian FMRP interacts with microRNAs and the components of the microRNA pathways including Dicer and the mammalian ortholog of Argonaute 1 (AGO1). Using two different Drosophila melanogaster models, we show that AGO1 is critical for FMRP function in neural development and synaptogenesis. Our results suggest that FMRP may regulate neuronal translation via microRNAs and links microRNAs with human disease.
Keywords: Animals; Argonaute Proteins; Blotting, Western; Disease Models, Animal; Drosophila melanogaster; Drosophila Proteins; Eye; Fragile X Syndrome; HeLa Cells; Humans; Immunohistochemistry; Male; MicroRNAs; Microscopy, Electron, Scanning; Nerve Tissue Proteins; Neuromuscular Junction; Neuronal Plasticity; Precipitin Tests; Ribonuclease III; RNA-Induced Silencing Complex

A bioinformatics analysis of memory consolidation reveals involvement of the transcription factor c-rel. - Levenson, Jonathan M; Choi, Sangdun; Lee, Sun-Young; Cao, Yun Anna; Ahn, Hyung Jin; Worley, Kim C; Pizzi, Marina; Liou, Hsiou-Chi; Sweatt, J David (J Neurosci, 2004)
Consolidation of long-term memory (LTM) is a complex process requiring synthesis of new mRNAs and proteins. Many studies have characterized the requirement for de novo mRNA and protein synthesis; however, few studies have comprehensively identified genes regulated during LTM consolidation. We show that consolidation of long-term contextual memory in the hippocampus triggers altered expression of numerous genes encompassing many aspects of neuronal function. Like contextual memory formation, this altered gene expression required NMDA receptor activation and was specific for situations in which the animal formed an association between a physical context and a sensory stimulus. Using a bioinformatics approach, we found that regulatory elements for several transcription factors are over-represented in the upstream region of genes regulated during consolidation of LTM. Using a knock-out mouse, we found that c-rel, one of the transcription factors identified in our bioinformatics study, is necessary for hippocampus-dependent long-term memory formation.
Keywords: Animals; Behavior, Animal; Chromosomes; Computational Biology; Conditioning, Classical; Electroshock; Fear; Gene Expression Profiling; Gene Expression Regulation; Hippocampus; Male; Memory; Mice; Mice, Inbred C57BL; Mice, Knockout; Oligonucleotide Array Sequence Analysis; Pain Measurement; Proto-Oncogene Proteins c-rel; Receptors, N-Methyl-D-Aspartate; Spatial Behavior

Dynamic building of a BAC clone tiling path for the Rat Genome Sequencing Project. - Rui Chen; Sodergren, Erica; Weinstock, George M; Richard A Gibbs (Genome Res, 2004)
CLONEPICKER is a software pipeline that integrates sequence data with BAC clone fingerprints to dynamically select a minimal overlapping clone set covering the whole genome. In the Rat Genome Sequencing Project (RGSP), a hybrid strategy of "clone by clone" and "whole genome shotgun" approaches was used to maximize the merits of both approaches. Like the "clone by clone" method, one key challenge for this strategy was to select a low-redundancy clone set that covered the whole genome while the sequencing is in progress. The CLONEPICKER pipeline met this challenge using restriction enzyme fingerprint data, BAC end sequence data, and sequences generated from individual BAC clones as well as WGS reads. In the RGSP, an average of 7.5 clones was identified from each side of a seed clone, and the minimal overlapping clones were reliably selected. Combined with the assembled BAC fingerprint map, a set of BAC clones that covered >97% of the genome was identified and used in the RGSP.
Keywords: Animals; Chromosomes, Artificial, Bacterial; Computational Biology; Contig Mapping; DNA Fingerprinting; Genome; Rats; Sequence Analysis, DNA; Software

Fxr1 knockout mice show a striated muscle phenotype: implications for Fxr1p function in vivo. - Mientjes, Edwin J; Willemsen, Rob; Kirkpatrick, Laura L; Nieuwenhuizen, Ingeborg M; Hoogeveen-Westerveld, Marianne; Verweij, Marcel; Reis, Surya; Bardoni, Barbara; Hoogeveen, Andre T; Oostra, Ben A; Nelson, David L (Hum Mol Genet, 2004)
FXR1 is one of the two known homologues of FMR1. FXR1 shares a high degree of sequence homology with FMR1 and also encodes two KH domains and an RGG domain, conferring RNA-binding capabilities. In comparison with FMRP, very little is known about the function of FXR1P in vivo. Mouse knockout (KO) models exist for both Fmr1 and Fxr2. To study the function of Fxr1 in vivo, we generated an Fxr1 KO mouse model. Homozygous Fxr1 KO neonates die shortly after birth most likely due to cardiac or respiratory failure. Histochemical analyses carried out on both skeletal and cardiac muscles show a disruption of cellular architecture and structure in E19 Fxr1 neonates compared with wild-type (WT) littermates. In WT E19 skeletal and cardiac muscles, Fxr1p is localized to the costameric regions within the muscles. In E19 Fxr1 KO littermates, in addition to the absence of Fxr1p, costameric proteins vinculin, dystrophin and alpha-actinin were found to be delocalized. A second mouse model (Fxr1 + neo), which expresses strongly reduced levels of Fxr1p relative to WT littermates, does not display the neonatal lethal phenotype seen in the Fxr1 KOs but does display a strongly reduced limb musculature and has a reduced life span of approximately 18 weeks. The results presented here point towards a role for Fxr1p in muscle mRNA transport/translation control similar to that seen for Fmrp in neuronal cells.
Keywords: Animals; Cytoskeletal Proteins; Fragile X Mental Retardation Protein; Hindlimb; Longevity; Mice; Mice, Knockout; Muscle, Skeletal; Myocardium; Nerve Tissue Proteins; Protein Structure, Tertiary; RNA, Messenger; RNA-Binding Proteins; Sequence Homology

Genetics. The critical region in trisomy 21. - Nelson, David L; Richard A Gibbs (Science, 2004)
Keywords: Animals; Chromosome Deletion; Chromosomes, Human, Pair 21; Chromosomes, Mammalian; Craniofacial Abnormalities; Crosses, Genetic; Disease Models, Animal; Down Syndrome; Female; Gene Duplication; Humans; Male; Mice; Recombination, Genetic; Skull; Trisomy

Genome sequence of the Brown Norway rat yields insights into mammalian evolution. - Richard A Gibbs; Weinstock, George M; Metzker, Michael L; Donna M Muzny; Sodergren, Erica J; Scherer, Steven; Scott, Graham; Steffen, David; Worley, Kim C; Burch, Paula E; Okwuonu, Geoffrey; Hines, Sandra; et al. (Nature, 2004)
The laboratory rat (Rattus norvegicus) is an indispensable tool in experimental medicine and drug development, having made inestimable contributions to human health. We report here the genome sequence of the Brown Norway (BN) rat strain. The sequence represents a high-quality 'draft' covering over 90% of the genome. The BN rat sequence is the third complete mammalian genome to be deciphered, and three-way comparisons with the human and mouse genomes resolve details of mammalian evolution. This first comprehensive analysis includes genes and proteins and their relation to human disease, repeated sequences, comparative genome-wide studies of mammalian orthologous chromosomal regions and rearrangement breakpoints, reconstruction of ancestral karyotypes and the events leading to existing species, rates of variation, and lineage-specific and lineage-independent evolutionary events such as expansion of gene families, orthology relations and protein evolution.
Keywords: Animals; Base Composition; Centromere; Chromosomes, Mammalian; CpG Islands; DNA Transposable Elements; DNA, Mitochondrial; Evolution, Molecular; Gene Duplication; Genome; Genomics; Humans; Introns; Male; Mice; Models, Molecular; Mutagenesis; Polymorphism, Single Nucleotide; Rats; Rats, Inbred BN; Regulatory Sequences, Nucleic Acid; Retroelements; RNA Splice Sites; RNA, Untranslated; Sequence Analysis, DNA; Telomere

Genome-wide linkage disequilibrium and haplotype maps. - Belmont, John W; Richard A Gibbs (Am J Pharmacogenomics, 2004)
There is currently a broad effort to produce genome-wide high-density linkage disequilibrium (LD) maps with single nucleotide polymorphisms. The hope is that the resulting maps can be exploited to find genes that affect the onset and severity of at least some common human diseases. These maps may also be useful for identifying genes that affect drug response or the likelihood of drug toxicities. The goal of this review is to provide a broad overview of some of the key concerns motivating the design of a major international project called the International Haplotype Map Project. The process of map production requires the identification of very large numbers of polymorphic sites, implementation of facile, highly accurate and inexpensive genotyping production pipelines, and provision for public access to the genotype data. Great progress has been made recently in genotyping methods and these advances are allowing very large-scale data collection. A major goal of these efforts is to enable the selection of subsets of markers that capture useful genetic information in short genomic intervals, while optimally reducing the number of markers that must be genotyped. Standard measures of LD provide a starting point but may not fully capture the complexity of the information inherent in the data. Extremely dense genotype data in several broadly representative populations (European, Chinese, Japanese, and Yoruba) should yield important insights into the genetic structure of most genes. Further study is required to determine how broadly applicable the data will be to other population groups. Significant challenges lie ahead in determining the best methods for the selection of markers in disease/phenotype studies, large-scale genotyping, and analysis of the resulting genetic data.
Keywords: Animals; Chromosome Mapping; Databases, Genetic; Genetic Markers; Genome; Haplotypes; Humans; Linkage Disequilibrium; Polymorphism, Single Nucleotide; Population; Quality Control

Genomic analysis of the nuclear receptor family: new insights into structure, regulation, and evolution from the rat genome. - Zhang, Zhengdong; Burch, Paula E; Cooney, Austin J; Lanz, Rainer B; Pereira, Fred A; Wu, Jiaqian; Richard A Gibbs; Weinstock, George; Wheeler, David A (Genome Res, 2004)
Completion of the Rattus norvegicus genome sequence enabled a global inventory and analysis of the nuclear receptors (NRs) in three mammalian species. Forty-nine NR members were found in mouse, 48 in human. Forty-seven were found in the rat, with gaps at the locations expected for the other two. Pairwise comparisons of their distribution in rat, mouse, and human identified 11 syntenic NR gene blocks, including three small clusters of two or three closely related genes, each spanning 40 kb to 1700 kb. The exon structure of the ligand-binding domain suggests that exon shuffling has played a role in the evolution of this family. An invariant splice junction in all members of the NR family except LXRbeta suggests a functional role for the intron. The ligand-binding domains of PXR and CAR are among the most divergent in the family. Their higher nucleotide substitution rates may be related to the central role played by these two NRs in the metabolism of the foreign compounds and may have resulted from limited positive selection.
Keywords: Amino Acid Sequence; Animals; Chromosome Mapping; DNA; Evolution, Molecular; Exons; Genome; Genome, Human; Humans; Ligands; Mice; Molecular Sequence Data; Phylogeny; Protein Structure, Quaternary; Protein Structure, Tertiary; Rats; Receptors, Androgen; Receptors, Cytoplasmic and Nuclear; Receptors, Estrogen; Receptors, Glucocorticoid; Receptors, Progesterone

Genomic segmental polymorphisms in inbred mouse strains. - Li, Jiangzhen; Jiang, Tao; Mao, Jian-Hua; Balmain, Allan; Peterson, Leif; Harris, Charles; Rao, Pulivarthi H; Havlak, Paul; Richard A Gibbs; Cai, Wei-Wen (Nat Genet, 2004)
By analyzing genomic copy-number differences using high-resolution mouse whole-genome BAC arrays, we uncover substantial differences in regional DNA content between inbred strains of mice. The identification of these apparently common segmental polymorphisms suggests that these differences can contribute to genetic variability and pathologic susceptibility.
Keywords: Animals; Base Sequence; Chromosomes, Artificial, Bacterial; Gene Dosage; In Situ Hybridization, Fluorescence; Mice; Mice, Inbred Strains; Polymorphism, Genetic

Identification of rat genes by TWINSCAN gene prediction, RT-PCR, and direct sequencing. - Wu, Jia Qian; Shteynberg, David; Arumugam, Manimozhiyan; Richard A Gibbs; Brent, Michael R (Genome Res, 2004)
The publication of a draft sequence of a third mammalian genome--that of the rat--suggests a need to rethink genome annotation. New mammalian sequences will not receive the kind of labor-intensive annotation efforts that are currently being devoted to human. In this paper, we demonstrate an alternative approach: reverse transcription-polymerase chain reaction (RT-PCR) and direct sequencing based on dual-genome de novo predictions from TWINSCAN. We tested 444 TWINSCAN-predicted rat genes that showed significant homology to known human genes implicated in disease but that were partially or completely missed by methods based on protein-to-genome mapping. Using primers in exons flanking a single predicted intron, we were able to verify the existence of 59% of these predicted genes. We then attempted to amplify the complete predicted open reading frames of 136 genes that were verified in the single-intron experiment. Spliced sequences were amplified in 46 cases (34%). We conclude that this procedure for elucidating gene structures with native cDNA sequences is cost-effective and will become even more so as it is further optimized.
Keywords: Animals; Computational Biology; Genes; Humans; Introns; Open Reading Frames; Predictive Value of Tests; Rats; Reverse Transcriptase Polymerase Chain Reaction; Sequence Analysis, DNA; Software; Untranslated Regions

In silico genetics: identification of a functional element regulating H2-Ealpha gene expression. - Liao, Guochun; Wang, Jianmei; Guo, Jingshu; Allard, John; Cheng, Janet; Ng, Anh; Shafer, Steve; Puech, Anne; McPherson, John D; Foernzler, Dorothee; Peltz, Gary; Usuka, Jonathan (Science, 2004)
Computational tools can markedly accelerate the rate at which murine genetic models can be analyzed. We developed a computational method for mapping phenotypic traits that vary among inbred strains onto haplotypic blocks. This method correctly predicted the genetic basis for strain-specific differences in several biologically important traits. It was also used to identify an allele-specific functional genomic element regulating H2-Ealpha gene expression. This functional element, which contained the binding sites for YY1 and a second transcription factor that is probably serum response factor, is located within the first intron of the H2-Ealpha gene. This computational method will greatly improve our ability to identify the genetic basis for a variety of phenotypic traits, ranging from qualitative trait information to quantitative gene expression data, which vary among inbred mouse strains.
Keywords: Alleles; Animals; Binding Sites; Computational Biology; Electrophoretic Mobility Shift Assay; Gene Expression Profiling; Gene Expression Regulation; Genes, MHC Class II; Genetic Variation; H-2 Antigens; Haplotypes; Hydrocarbons, Aromatic; Introns; Liver; Lung; Major Histocompatibility Complex; Mice; Mice, Inbred Strains; Oligodeoxyribonucleotides; Oligonucleotide Array Sequence Analysis; Phenotype; Polymorphism, Single Nucleotide; Receptors, Aryl Hydrocarbon; Regulatory Sequences, Nucleic Acid; Serum Response Factor; Transcription Factors

Integrated and sequence-ordered BAC- and YAC-based physical maps for the rat genome. - Krzywinski, Martin; Wallis, John; Gösele, Claudia; Bosdet, Ian; Chiu, Readman; Graves, Tina; Hummel, Oliver; Layman, Dan; Mathewson, Carrie; Wye, Natasja; Zhu, Baoli; Albracht, Derek; et al. (Genome Res, 2004)
As part of the effort to sequence the genome of Rattus norvegicus, we constructed a physical map comprised of fingerprinted bacterial artificial chromosome (BAC) clones from the CHORI-230 BAC library. These BAC clones provide approximately 13-fold redundant coverage of the genome and have been assembled into 376 fingerprint contigs. A yeast artificial chromosome (YAC) map was also constructed and aligned with the BAC map via fingerprinted BAC and P1 artificial chromosome clones (PACs) sharing interspersed repetitive sequence markers with the YAC-based physical map. We have annotated 95% of the fingerprint map clones in contigs with coordinates on the version 3.1 rat genome sequence assembly, using BAC-end sequences and in silico mapping methods. These coordinates have allowed anchoring 358 of the 376 fingerprint map contigs onto the sequence assembly. Of these, 324 contigs are anchored to rat genome sequences localized to chromosomes, and 34 contigs are anchored to unlocalized portions of the rat sequence assembly. The remaining 18 contigs, containing 54 clones, still require placement. The fingerprint map is a high-resolution integrative data resource that provides genome-ordered associations among BAC, YAC, and PAC clones and the assembled sequence of the rat genome.
Keywords: Animals; Automation; Chromosomes; Chromosomes, Artificial, Bacterial; Chromosomes, Artificial, Yeast; Cloning, Molecular; Computational Biology; Contig Mapping; DNA Fingerprinting; Genetic Markers; Genome; Physical Chromosome Mapping; Polymerase Chain Reaction; Rats; Sequence Analysis, DNA

Pash: efficient genome-scale sequence anchoring by Positional Hashing. - Kalafus, Ken J; Jackson, Andrew R; Milosavljevic, Aleksandar (Genome Res, 2004)
Pash is a computer program for efficient, parallel, all-against-all comparison of very long DNA sequences. Pash implements Positional Hashing, a novel parallelizable method for sequence comparison based on k-mer representation of sequences. The Positional Hashing method breaks the comparison problem in a unique way that avoids the quadratic penalty encountered with other sensitive methods and confers inherent low-level parallelism. Furthermore, Positional Hashing allows one to readily and predictably trade between sensitivity and speed. In a simulated comparison task, anchoring computationally mutated reads onto a genome, the sensitivity of Pash was equal to or greater than that of BLAST and BLAT, with Pash outperforming these programs as the reads became shorter and less similar to the genome. Using modest computing resources, we employed Pash for two large-scale sequence comparison tasks: comparison of three mammalian genomes, and anchoring millions of chimpanzee whole-genome shotgun sequencing reads onto the human genome. The results of these comparisons by Pash agree with those computed by other methods that use more than an order of magnitude more computing resources. These results confirm the sensitivity of Positional Hashing.
Keywords: Animals; Chromosome Mapping; Cluster Analysis; Computational Biology; DNA; Genome; Genome, Human; Humans; Mice; Pan troglodytes; Rats; Sensitivity and Specificity; Software

A physical map of the chicken genome. - Wallis, John W; Aerts, Jan; Groenen, Martien A M; Crooijmans, Richard P M A; Layman, Dan; Graves, Tina A; Scheer, Debra E; Kremitzki, Colin; Fedele, Mary J; Mudd, Nancy K; Cardenas, Marco; Higginbotham, Jamey; et al. (Nature, 2004)
Strategies for assembling large, complex genomes have evolved to include a combination of whole-genome shotgun sequencing and hierarchal map-assisted sequencing. Whole-genome maps of all types can aid genome assemblies, generally starting with low-resolution cytogenetic maps and ending with the highest resolution of sequence. Fingerprint clone maps are based upon complete restriction enzyme digests of clones representative of the target genome, and ultimately comprise a near-contiguous path of clones across the genome. Such clone-based maps are used to validate sequence assembly order, supply long-range linking information for assembled sequences, anchor sequences to the genetic map and provide templates for closing gaps. Fingerprint maps are also a critical resource for subsequent functional genomic studies, because they provide a redundant and ordered sampling of the genome with clones. In an accompanying paper we describe the draft genome sequence of the chicken, Gallus gallus, the first species sequenced that is both a model organism and a global food source. Here we present a clone-based physical map of the chicken genome at 20-fold coverage, containing 260 contigs of overlapping clones. This map represents approximately 91% of the chicken genome and enables identification of chicken clones aligned to positions in other sequenced genomes.
Keywords: Animals; Chickens; Chromosomes, Artificial, Bacterial; Cloning, Molecular; Contig Mapping; DNA Fingerprinting; Genetic Linkage; Genome; Genomics; Physical Chromosome Mapping; Sequence Tagged Sites

Pol iota is a candidate for the mouse pulmonary adenoma resistance 2 locus, a major modifier of chemically induced lung neoplasia. - Wang, Min; Devereux, Theodora R; Vikis, Haris G; McCulloch, Scott D; Holliday, Wanda; Anna, Colleen; Wang, Yian; Bebenek, Katarzyna; Kunkel, Thomas A; Guan, Kunliang; You, Ming (Cancer Res, 2004)
In this study, we performed systematic candidate gene analyses of the Pulmonary adenoma resistance 2 locus. Differential gene expression in lung tissues and nucleotide polymorphisms in coding regions between A/J and BALB/cJ mice were examined using reverse transcription-PCR and direct sequencing. Although not all genes in the interval were analyzed at this moment due to the recent database updating, we have found that the Pol iota gene, encoding the DNA polymerase iota, contains 25 nucleotide polymorphisms in its coding region between A/J and BALB/cJ mice, resulting in a total of ten amino acid changes. Primer extension assays with purified BALB/cJ and A/J proteins in vitro demonstrate that both forms of Pol iota are active but that they may differ in substrate discrimination, which may affect the formation of Kras2 mutations in mouse lung tumors. Altered expression of POL iota protein and an amino acid-changing nucleotide polymorphism were observed in human lung cancer cells, suggesting a possible role in the development of lung cancer. Thus, our data support the Pol iota gene as a modifier of lung tumorigenesis by altering DNA polymerase activity.
Keywords: Adenoma; Alternative Splicing; Amino Acid Sequence; Animals; DNA Polymerase iota; DNA-Directed DNA Polymerase; Gene Expression Regulation, Neoplastic; Humans; Immunity, Innate; Lung; Lung Neoplasms; Mice; Mice, Inbred A; Mice, Inbred BALB C; Molecular Sequence Data; Polymorphism, Single Nucleotide; Proto-Oncogene Proteins; Proto-Oncogene Proteins p21(ras); ras Proteins; RNA, Messenger; Sequence Homology, Amino Acid; Tumor Cells, Cultured

Pooled Genomic Indexing (PGI): analysis and design of experiments. - Csuros, Miklos; Milosavljevic, Aleksandar (J Comput Biol, 2004)
Pooled Genomic Indexing (PGI) is a novel method for physical mapping of clones onto known sequences. PGI is carried out by pooling arrayed clones and generating shotgun sequence reads from the pools. The shotgun sequences are compared to a reference sequence. In the simplest case, clones are placed on an array and are pooled by rows and columns. If a shotgun sequence from a row pool and another shotgun sequence from a column pool match the reference sequence at a close distance, they are both assigned to the clone at the intersection of the two pools. Accordingly, the clone is mapped onto the region of the reference sequence between the two matches. A probabilistic model for PGI is developed, and several pooling designs are described and analyzed, including transversal designs and designs from linear codes. The probabilistic model and the pooling schemes are validated in simulated experiments where 625 rat bacterial artificial chromosome (BAC) clones and 207 mouse BAC clones are mapped onto homologous human sequence.
Keywords: Animals; Chromosomes, Artificial, Bacterial; Computational Biology; Data Interpretation, Statistical; Mice; Phylogeny; Physical Chromosome Mapping; Probability; Rats; Research Design

Sequence and comparative analysis of the chicken genome provide unique perspectives on vertebrate evolution. (Nature, 2004)
We present here a draft genome sequence of the red jungle fowl, Gallus gallus. Because the chicken is a modern descendant of the dinosaurs and the first non-mammalian amniote to have its genome sequenced, the draft sequence of its genome--composed of approximately one billion base pairs of sequence and an estimated 20,000-23,000 genes--provides a new perspective on vertebrate genome evolution, while also improving the annotation of mammalian genomes. For example, the evolutionary distance between chicken and human provides high specificity in detecting functional elements, both non-coding and coding. Notably, many conserved non-coding sequences are far from genes and cannot be assigned to defined functional classes. In coding regions the evolutionary dynamics of protein domains and orthologous groups illustrate processes that distinguish the lineages leading to birds and mammals. The distinctive properties of avian microchromosomes, together with the inferred patterns of conserved synteny, provide additional insights into vertebrate chromosome architecture.
Keywords: Animals; Avian Proteins; Chickens; Conserved Sequence; DNA Transposable Elements; Evolution, Molecular; Gene Duplication; Genes; Genome; Genomics; Humans; Long Interspersed Nucleotide Elements; Multigene Family; Mutagenesis; Physical Chromosome Mapping; Pseudogenes; Retroviridae; RNA, Untranslated; Sequence Analysis, DNA; Short Interspersed Nucleotide Elements; Synteny; Vertebrates

Single nucleotide polymorphism (SNP) analysis of mouse quantitative trait loci for identification of candidate genes. - Yan, Y; Wang, M; Lemon, W J; You, M (J Med Genet, 2004)
Keywords: Acute Disease; Animals; Chromosomes, Mammalian; Disease Models, Animal; Disease Susceptibility; Genetic Predisposition to Disease; Lung; Lung Injury; Lung Neoplasms; Mice; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Reproducibility of Results; Seizures; Trypanosomiasis

The status, quality, and expansion of the NIH full-length cDNA project: the Mammalian Gene Collection (MGC). - Gerhard, Daniela S; Wagner, Lukas; Feingold, Elise A; Shenmen, Carolyn M; Grouse, Lynette H; Schuler, Greg; Klein, Steven L; Old, Susan; Rasooly, Rebekah; Good, Peter; Guyer, Mark; Peck, Allison M; et al. (Genome Res, 2004)
The National Institutes of Health's Mammalian Gene Collection (MGC) project was designed to generate and sequence a publicly accessible cDNA resource containing a complete open reading frame (ORF) for every human and mouse gene. The project initially used a random strategy to select clones from a large number of cDNA libraries from diverse tissues. Candidate clones were chosen based on 5'-EST sequences, and then fully sequenced to high accuracy and analyzed by algorithms developed for this project. Currently, more than 11,000 human and 10,000 mouse genes are represented in MGC by at least one clone with a full ORF. The random selection approach is now reaching a saturation point, and a transition to protocols targeted at the missing transcripts is now required to complete the mouse and human collections. Comparison of the sequence of the MGC clones to reference genome sequences reveals that most cDNA clones are of very high sequence quality, although it is likely that some cDNAs may carry missense variants as a consequence of experimental artifact, such as PCR, cloning, or reverse transcriptase errors. Recently, a rat cDNA component was added to the project, and ongoing frog (Xenopus) and zebrafish (Danio) cDNA projects were expanded to take advantage of the high-throughput MGC pipeline.
Keywords: Animals; Cloning, Molecular; Computational Biology; DNA Primers; DNA, Complementary; Gene Library; Humans; Mice; National Institutes of Health (U.S.); Open Reading Frames; Rats; United States; Xenopus laevis; Zebrafish

WormBase: a multi-species resource for nematode biology and genomics. - Harris, Todd W; Chen, Nansheng; Cunningham, Fiona; Tello-Ruiz, Marcela; Antoshechkin, Igor; Bastiani, Carol; Bieri, Tamberlyn; Blasiar, Darin; Bradnam, Keith; Chan, Juancarlos; Chen, Chao-Kung; Chen, Wen J; et al. (Nucleic Acids Res, 2004)
WormBase (http://www.wormbase.org/) is the central data repository for information about Caenorhabditis elegans and related nematodes. As a model organism database, WormBase extends beyond the genomic sequence, integrating experimental results with extensively annotated views of the genome. The WormBase Consortium continues to expand the biological scope and utility of WormBase with the inclusion of large-scale genomic analyses, through active data and literature curation, through new analysis and visualization tools, and through refinement of the user interface. Over the past year, the nearly complete genomic sequence and comparative analyses of the closely related species Caenorhabditis briggsae have been integrated into WormBase, including gene predictions, ortholog assignments and a new synteny viewer to display the relationships between the two species. Extensive site-wide refinement of the user interface now provides quick access to the most frequently accessed resources and a consistent browsing experience across the site. Unified single-page views now provide complete summaries of commonly accessed entries like genes. These advances continue to increase the utility of WormBase for C.elegans researchers, as well as for those researchers exploring problems in functional and comparative genomics in the context of a powerful genetic system.
Keywords: Animals; Caenorhabditis; Caenorhabditis elegans; Computational Biology; Databases, Genetic; Genomics; Information Storage and Retrieval; Internet; User-Computer Interface

Association of the T-cell regulatory gene CTLA4 with susceptibility to autoimmune disease. - Ueda, Hironori; Howson, Joanna M M; Esposito, Laura; Heward, Joanne; Snook, Hywel; Chamberlain, Giselle; Rainbow, Daniel B; Hunter, Kara M D; Smith, Annabel N; Di Genova, Gianfranco; Herr, Mathias H; Dahlman, Ingrid; et al. (Nature, 2003)
Genes and mechanisms involved in common complex diseases, such as the autoimmune disorders that affect approximately 5% of the population, remain obscure. Here we identify polymorphisms of the cytotoxic T lymphocyte antigen 4 gene (CTLA4)--which encodes a vital negative regulatory molecule of the immune system--as candidates for primary determinants of risk of the common autoimmune disorders Graves' disease, autoimmune hypothyroidism and type 1 diabetes. In humans, disease susceptibility was mapped to a non-coding 6.1 kb 3' region of CTLA4, the common allelic variation of which was correlated with lower messenger RNA levels of the soluble alternative splice form of CTLA4. In the mouse model of type 1 diabetes, susceptibility was also associated with variation in CTLA-4 gene splicing with reduced production of a splice form encoding a molecule lacking the CD80/CD86 ligand-binding domain. Genetic mapping of variants conferring a small disease risk can identify pathways in complex disorders, as exemplified by our discovery of inherited, quantitative alterations of CTLA4 contributing to autoimmune tissue destruction.
Keywords: Abatacept; Alternative Splicing; Animals; Antigens, CD; Antigens, Differentiation; Autoimmune Diseases; Base Sequence; CTLA-4 Antigen; Diabetes Mellitus, Type 1; Disease Models, Animal; Genetic Predisposition to Disease; Genotype; Graves Disease; Humans; Hypothyroidism; Immunoconjugates; Mice; Polymorphism, Single Nucleotide; Protein Isoforms; T-Lymphocytes

Clinical isolates of Enterococcus faecium exhibit strain-specific collagen binding mediated by Acm, a new member of the MSCRAMM family. - Nallapareddy, Sreedhar R; Weinstock, George M; Murray, Barbara E (Mol Microbiol, 2003)
A collagen-binding adhesin of Enterococcus faecium, Acm, was identified. Acm shows 62% similarity to the Staphylococcus aureus collagen adhesin Cna over the entire protein and is more similar to Cna (60% and 75% similarity with Cna A and B domains respectively) than to the Enterococcus faecalis collagen-binding adhesin, Ace, which shares homology with Acm only in the A domain. Despite the detection of acm in 32 out of 32 E. faecium isolates, only 11 of these (all clinical isolates, including four vancomycin-resistant endocarditis isolates and seven other isolates) exhibited binding to collagen type I (CI). Although acm from three CI-binding vancomycin-resistant E. faecium clinical isolates showed 100% identity, analysis of acm genes and their promoter regions from six non-CI-binding strains identified deletions or mutations that introduced stop codons and/or IS elements within the gene or the promoter region in five out of six strains, suggesting that the presence of an intact functional acm gene is necessary for binding of E. faecium strains to CI. Recombinant Acm A domain showed specific and concentration-dependent binding to collagen, and this protein competed with E. faecium binding to immobilized CI. Consistent with the adherence phenotype and sequence data, probing with Acm-specific IgGs purified from anti-recombinant Acm A polyclonal rabbit serum confirmed the surface expression of Acm in three out of three collagen-binding clinical isolates of E. faecium tested, but in none of the strains with a non-functional pseudo acm gene. Introduction of a functional acm gene into two non-CI-binding natural acm mutant strains conferred a CI-binding phenotype, further confirming that native Acm is sufficient for the binding of E. faecium to CI. These results demonstrate that acm, which encodes a potential virulence factor, is functional only in certain infection-derived clinical isolates of E. faecium, and suggest that Acm is the primary adhesin responsible for the ability of E. faecium to bind collagen.
Keywords: Adhesins, Bacterial; Amino Acid Sequence; Animals; Bacterial Adhesion; Cell Membrane; Collagen; Collagen Type I; Enterococcus faecium; Genetic Complementation Test; Gram-Positive Bacteria; Humans; Molecular Sequence Data; Mutation; Protein Structure, Tertiary; Pseudogenes; Rabbits; Recombinant Proteins; Sequence Homology, Amino Acid; Species Specificity

Clone-array pooled shotgun mapping and sequencing: design and analysis of experiments. - Csuros, Miklos; Li, Bingshan; Milosavljevic, Aleksandar (Genome Inform, 2003)
This paper studies sequencing and mapping methods that rely solely on pooling and shotgun sequencing of clones. First, we scrutinize and improve the recently proposed Clone-Array Pooled Shotgun Sequencing (CAPSS) method, which delivers a BAC-linked assembly of a whole genome sequence. Secondly, we introduce a novel physical mapping method, called Clone-Array Pooled Shotgun Mapping (CAPS-MAP), which computes the physical ordering of BACs in a random library. Both CAPSS and CAPS-MAP construct subclone libraries from pooled genomic BAC clones.
Keywords: Animals; Chromosomes, Artificial, Bacterial; Computational Biology; Computer Simulation; Drosophila melanogaster; Genome; Reproducibility of Results; Research Design; Sequence Alignment

Differentially expressed nucleolar TGF-beta1 target (DENTT) in mouse development. - Ozbun, Laurent L; Martínez, Alfredo; Angdisen, Jerry; Umphress, Sarah; Kang, Yang; Wang, Min; You, Ming; Jakowlew, Sonia B (Dev Dyn, 2003)
Differentially expressed nucleolar TGF-beta1 target (DENTT) is a recently identified gene whose mRNA is differentially affected by TGF-beta1 in TGF-beta1-responsive human lung cancer cells and who is a new member of the TSPY/TSPY-like/SET/NAP-1 (TTSN) protein superfamily. Here, we report that mouse DENTT mRNA contains a 2031-bp open reading frame that encodes a predicted polypeptide of 677-amino acids with a relative molecular mass of 77,671 Da. The mouse and human DENTT sequences show 77% and 78% homology at the nucleotide and amino acid level, respectively. Mouse DENTT is predicted to be a nuclear protein with two nuclear localization signals (NLS), two coiled-coil regions, and a domain that shows significant identity to a region that defines the TTSN superfamily. Green fluorescent protein (GFP)-tagged full-length mouse DENTT transfected into COS-7 cells showed localization predominantly in the nucleolus. Reverse transcription-polymerase chain reaction amplification, Northern hybridization, and Western blot analyses showed expression of mouse DENTT mRNA and protein throughout mouse embryogenesis. Immunohistochemical staining analysis showed that DENTT is expressed in multiple tissues in a defined spatiotemporal pattern during mouse embryogenesis. The heart and primitive brain were the first organs of the embryo that showed immunoreactivity for the DENTT antibody by day 8 of development (E8). In the developing mouse brain, the choroid plexus was intensely stained for DENTT in all stages of development. The spinal cord and dorsal root ganglia were also positive for DENTT staining beginning in the 11-day-old embryo (E11), where homogeneous immunostaining was observed throughout the developing neurons. By day 16 of development (E16), only a small subset of the neuronal population in the spinal cord and dorsal root ganglia was positively stained for DENTT. DENTT immunoreactivity increased steadily with maturation as the differentiation of cartilage and osteoblasts proceeded and reached a maximum in the growth plate during endochondral ossification. DENTT expression was also detected in multiple rodent cell types in vitro, including mouse F9 embryonal carcinoma (EC) cells. Addition of retinoic acid or sodium butyrate to F9 EC cells showed a rapid decrease in expression of DENTT protein occurring by 1 hr that continued to decrease to almost undetectable levels after 24 hr. Cotransfection of full-length mouse DENTT expression plasmid with 3TPLux or COL7A1Luc Luciferase reporter plasmids into F9 EC cells significantly increased the level of 3TPLux reporter transcription while decreasing the level of COL7A1Luc reporter transcription, suggesting that DENTT may play multiple roles in modulating transcriptional responses. These findings suggest new roles for the TTSN superfamily during embryogenesis and differentiation.
Keywords: 3T3 Cells; Animals; Base Sequence; Blotting, Northern; Blotting, Western; Bone and Bones; Cardiovascular System; Cell Cycle Proteins; Cell Differentiation; Cell Nucleolus; Chorion; Digestive System; DNA-Binding Proteins; Female; Gene Expression Regulation, Developmental; Genes, Reporter; Heart; Humans; Immunohistochemistry; Male; Mice; Mice, Inbred C57BL; Molecular Sequence Data; Nervous System; Nuclear Proteins; Placenta; Reverse Transcriptase Polymerase Chain Reaction; RNA, Messenger; Sequence Homology, Amino Acid; Transcriptional Activation; Transforming Growth Factor beta; Transforming Growth Factor beta1

Dissection of K+ currents in Caenorhabditis elegans muscle cells by genetics and RNA interference. - Santi, C M; Yuan, A; Fawcett, G; Wang, Z-W; Butler, A; Nonet, M L; Wei, A; Rojas, P; Salkoff, L (Proc Natl Acad Sci U S A, 2003)
GFP-promoter experiments have previously shown that at least nine genes encoding potassium channel subunits are expressed in Caenorhabditis elegans muscle. By using genetic, RNA interference, and physiological techniques we revealed the molecular identity of the major components of the outward K+ currents in body wall muscle cells in culture. We found that under physiological conditions, outward current is dominated by the products of only two genes, Shaker (Kv1) and Shal (Kv4), both expressing voltage-dependent potassium channels. Other channels may be held in reserve to respond to particular circumstances. Because GFP-promoter experiments indicated that slo-2 expression is prominent, we created a deletion mutant to identify the SLO-2 current in vivo. In both whole-cell and single-channel modes, in vivo SLO-2 channels were active only when intracellular Ca2+ and Cl- were raised above normal physiological conditions, as occurs during hypoxia. Under such conditions, SLO-2 is the largest outward current, contributing up to 87% of the total current. Other channels are present in muscle, but our results suggest that they are unlikely to contribute a large outward component under physiological conditions. However, they, too, may contribute currents conditional on other factors. Hence, the picture that emerges is of a complex membrane with a small number of household conductances functioning under normal circumstances, but with additional conductances that are activated during unusual circumstances.
Keywords: Animals; Animals, Genetically Modified; Caenorhabditis elegans; Caenorhabditis elegans Proteins; Genes, Helminth; Membrane Transport Proteins; Muscles; Mutation; Potassium Channels; Potassium Channels, Voltage-Gated; RNA Interference; Shaker Superfamily of Potassium Channels; Shal Potassium Channels

The DNA sequence and analysis of human chromosome 14. - Heilig, Roland; Eckenberg, Ralph; Petit, Jean-Louis; Fonknechten, Núria; Da Silva, Corinne; Cattolico, Laurence; Levy, Michaël; Barbe, Valérie; de Berardinis, Véronique; Ureta-Vidal, Abel; Pelletier, Eric; Vico, Virginie; et al. (Nature, 2003)
Chromosome 14 is one of five acrocentric chromosomes in the human genome. These chromosomes are characterized by a heterochromatic short arm that contains essentially ribosomal RNA genes, and a euchromatic long arm in which most, if not all, of the protein-coding genes are located. The finished sequence of human chromosome 14 comprises 87,410,661 base pairs, representing 100% of its euchromatic portion, in a single continuous segment covering the entire long arm with no gaps. Two loci of crucial importance for the immune system, as well as more than 60 disease genes, have been localized so far on chromosome 14. We identified 1,050 genes and gene fragments, and 393 pseudogenes. On the basis of comparisons with other vertebrate genomes, we estimate that more than 96% of the chromosome 14 genes have been annotated. From an analysis of the CpG island occurrences, we estimate that 70% of these annotated genes are complete at their 5' end.
Keywords: 5' Untranslated Regions; Animals; Base Composition; Chromosomes, Artificial; Chromosomes, Human, Pair 14; CpG Islands; DNA, Mitochondrial; DNA, Ribosomal; Genes; Genomics; Humans; Immunity; Mice; Microsatellite Repeats; Molecular Sequence Data; Open Reading Frames; Physical Chromosome Mapping; Pseudogenes; Reproducibility of Results; Sequence Analysis, DNA; Synteny

The DNA sequence of human chromosome 7. - Hillier, LaDeana W; Fulton, Robert S; Fulton, Lucinda A; Graves, Tina A; Pepin, Kymberlie H; Wagner-McPherson, Caryn; Layman, Dan; Maas, Jason; Jaeger, Sara; Walker, Rebecca; Wylie, Kristine; Sekhon, Mandeep; et al. (Nature, 2003)
Human chromosome 7 has historically received prominent attention in the human genetics community, primarily related to the search for the cystic fibrosis gene and the frequent cytogenetic changes associated with various forms of cancer. Here we present more than 153 million base pairs representing 99.4% of the euchromatic sequence of chromosome 7, the first metacentric chromosome completed so far. The sequence has excellent concordance with previously established physical and genetic maps, and it exhibits an unusual amount of segmentally duplicated sequence (8.2%), with marked differences between the two arms. Our initial analyses have identified 1,150 protein-coding genes, 605 of which have been confirmed by complementary DNA sequences, and an additional 941 pseudogenes. Of genes confirmed by transcript sequences, some are polymorphic for mutations that disrupt the reading frame.
Keywords: Animals; Base Sequence; Chromosomes, Human, Pair 7; Gene Duplication; Humans; Mice; Molecular Sequence Data; Physical Chromosome Mapping; Proteins; Pseudogenes; RNA, Untranslated; Sequence Analysis, DNA; Species Specificity; Williams Syndrome

Evolving methods for the assembly of large genomes. - Richard A Gibbs; Weinstock, G M (Cold Spring Harb Symp Quant Biol, 2003)
Keywords: Animals; Chromosomes, Artificial, Bacterial; Cloning, Molecular; Genetic Techniques; Genome; Genomics; Humans; Sequence Analysis, DNA

Fine mapping and identification of candidate pulmonary adenoma susceptibility 1 genes using advanced intercross lines. - Wang, Min; Lemon, William J; Liu, Gongjie; Wang, Yian; Iraqi, Fuad A; Malkinson, Alvin M; You, Ming (Cancer Res, 2003)
In the present study, we used newly developed F(11) generation mouse advanced intercross lines (AIL) to fine map Pas1-3 quantitative trait loci (QTL). The (A/J x C57BL/6) F(11) AIL mouse population was created by crossing lung tumor-resistant C57BL/6 mice with lung tumor-susceptible A/J mice. By selectively genotyping 30% of the population, we have confirmed the Pas1 QTL and narrowed it to an interval of approximately 1.0 cM or 1.3 Mb in the vicinity of the Kras2 gene. The Pas2 QTL was detected by both ANOVA and regression analysis but not by MapMaker EXP/QTL software. In addition, an interaction between the Pas1 and Pas2 QTLs was revealed. However, the Pas3 QTL was not confirmed in this study. It was either lost during the development of the AIL or too weak to be detected using AIL. The Pas1 locus is now sufficiently fine-mapped that candidate gene(s) for the Pas1 locus can be characterized by positional cloning. In this study, all 27 of the known or predicted genes located in the Pas1 candidate region were characterized as possible candidate Pas genes. Six genes were selected for additional analyses because of their relevant function in tumorigenesis or allelic changes between A/J and C57BL/6 mice. The Lrmp gene bears amino acid polymorphisms among various mouse strains that are highly correlated with the Pas1 allele status. The Pas1c1 gene (RIKEN Ak016641), encoding an intermediate filament tail domain-containing protein, produces alternatively spliced transcripts across inbred strains of mice, and its splicing pattern cosegregates with the Pas1 allele. The genetic and expression data support these two genes as strong candidates for the Pas1 locus. Of the other four genes (Eca39, RIKEN Ak015530, mHoj-1, and Krag), no functional polymorphisms or differential gene expression were found in Eca39, mHoj-1, and Krag between lung tumor-susceptible and -resistant strains. The Ak015530 carries an amino acid polymorphism, but this polymorphism does not cosegregate with mouse lung tumor susceptibility. Thus, these 4 genes are less likely candidates for the Pas1 locus.
Keywords: Adenoma; Animals; Chromosome Mapping; Crosses, Genetic; Gene Expression Profiling; Genes, ras; Genetic Predisposition to Disease; Immunity, Innate; Lod Score; Lung Neoplasms; Mice; Mice, Inbred A; Mice, Inbred C57BL; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Regression Analysis; Reverse Transcriptase Polymerase Chain Reaction; Software; Urethane

FMR2 function: insight from a mouse knockout model. - Gu, Y; Nelson, D L (Cytogenet Genome Res, 2003)
The FMR2 gene is dysregulated by the fragile X E triplet repeat expansion in patients with FRAXE mental retardation syndrome. A CCG triplet, located in the 5' untranslated region of the FRAXE gene undergoes expansion and methylation in these patients, eliminating detectable gene transcription. FRAXE syndrome is distinct from fragile X syndrome, a more common genetic form of mental retardation caused by expansion and methylation of a similar repeat in the FMR1 gene located 600 kb proximal to FRAXE. FRAXE syndrome is rare, and patients' phenotypes are highly variable, leading to difficulties with predicting specific FMR2 functions based on the human disease. Recently, Lilliputian(Lilli), a Drosophila FMR2 orthologue, was identified; this gene has been linked with several signal transduction pathways, including the transforming growth factor-beta (TGF-beta) pathway, the Raf/MEK/MAP kinase (MAPK) pathway, and the P13K/PKB pathway. Mutation of Lilli shows defects in germinal band extension, cytoskeletal structure, cell growth, and organ development. The Lilli gene suggests possible functions for FMR2 (and related genes) in humans and mice, but cannot predict specific functions. Modeling FMR2 mutation in the mouse will be useful to understand specific functions of this gene in vertebrates. This review presents what has been learned thus far from the FMR2 knockout mouse model and suggests future studies on this model in order to compare it with the human FRAXE mental retardation disorder, Lilli mutants in Drosophila and other mouse models of genes in this family.
Keywords: Amino Acid Sequence; Animals; Disease Models, Animal; Fragile X Syndrome; Gene Expression Regulation, Developmental; Genes; Humans; Mental Retardation, X-Linked; Mice; Mice, Knockout; Molecular Sequence Data; Nuclear Proteins; Sequence Homology, Amino Acid; Trans-Activators; Trinucleotide Repeat Expansion

From vulnerable plaque to vulnerable patient: a call for new definitions and risk assessment strategies: Part II. - Naghavi, Morteza; Libby, Peter; Falk, Erling; Casscells, S Ward; Litovsky, Silvio; Rumberger, John; Badimon, Juan Jose; Stefanadis, Christodoulos; Moreno, Pedro; Pasterkamp, Gerard; Fayad, Zahi; Stone, Peter H; et al. (Circulation, 2003)
Atherosclerotic cardiovascular disease results in >19 million deaths annually, and coronary heart disease accounts for the majority of this toll. Despite major advances in treatment of coronary heart disease patients, a large number of victims of the disease who are apparently healthy die suddenly without prior symptoms. Available screening and diagnostic methods are insufficient to identify the victims before the event occurs. The recognition of the role of the vulnerable plaque has opened new avenues of opportunity in the field of cardiovascular medicine. This consensus document concludes the following. (1) Rupture-prone plaques are not the only vulnerable plaques. All types of atherosclerotic plaques with high likelihood of thrombotic complications and rapid progression should be considered as vulnerable plaques. We propose a classification for clinical as well as pathological evaluation of vulnerable plaques. (2) Vulnerable plaques are not the only culprit factors for the development of acute coronary syndromes, myocardial infarction, and sudden cardiac death. Vulnerable blood (prone to thrombosis) and vulnerable myocardium (prone to fatal arrhythmia) play an important role in the outcome. Therefore, the term "vulnerable patient" may be more appropriate and is proposed now for the identification of subjects with high likelihood of developing cardiac events in the near future. (3) A quantitative method for cumulative risk assessment of vulnerable patients needs to be developed that may include variables based on plaque, blood, and myocardial vulnerability. In Part I of this consensus document, we cover the new definition of vulnerable plaque and its relationship with vulnerable patients. Part II of this consensus document will focus on vulnerable blood and vulnerable myocardium and provide an outline of overall risk assessment of vulnerable patients. Parts I and II are meant to provide a general consensus and overviews the new field of vulnerable patient. Recently developed assays (eg, C-reactive protein), imaging techniques (eg, CT and MRI), noninvasive electrophysiological tests (for vulnerable myocardium), and emerging catheters (to localize and characterize vulnerable plaque) in combination with future genomic and proteomic techniques will guide us in the search for vulnerable patients. It will also lead to the development and deployment of new therapies and ultimately to reduce the incidence of acute coronary syndromes and sudden cardiac death. We encourage healthcare policy makers to promote translational research for screening and treatment of vulnerable patients.
Keywords: Animals; Biomarkers; Coronary Artery Disease; Death, Sudden, Cardiac; Disease Susceptibility; Female; Humans; Male; Mass Screening; Myocardial Infarction; Myocardium; Risk Assessment; Severity of Illness Index; Swine; Thrombophilia

Gene expression profiling and functional proteomic analysis reveal perturbed kinase-mediated signaling in genetic stroke susceptibility. - Fornage, Myriam; Swank, Michael W; Eric Boerwinkle; Doris, Peter A (Physiol Genomics, 2003)
The stroke-prone spontaneously hypertensive rat (SHRSP) is a model of heritable hypertension-associated cerebrovascular injury. This study sought to compare SHRSP to the stroke-resistant SHR strain to identify genes and protein pathways whose expression and/or function was significantly altered between the strains prior to the onset of stroke. Cerebral cortex gene expression profiles from male SHRSPs and matched SHRs were examined by Affymetrix microarray analysis. mRNAs encoding the brain-derived neurotrophic factor receptor (TrkB) and multiple kinases of the MAPK/AKT signaling pathways, including JNK2, AKT2, and PI3K, were differentially expressed between SHRSP and SHR. Because these data suggest altered function in pathways involving MAP and AKT kinase activity, we performed Western blot using phosphorylation state-specific antibodies to characterize activity of MAP kinase and PI3K/AKT pathways. Changes in the levels of the phosphorylated forms of these kinases paralleled the changes in transcript levels observed between the strains. Two-dimensional gel electrophoresis and peptide fragment mass fingerprinting were used to identify altered protein substrates of these kinases. Protein profiling of kinase substrates further supported the notion of perturbed kinase-mediated signaling in SHRSP and identified adenylyl cyclase associated protein 2, TOAD-64, propionyl CoA carboxylase, APG-1, and valosin-containing protein as kinase targets whose phosphorylation state is altered between these strains. Altered gene and protein expression patterns in SHRSP are consistent with increased vulnerability of this strain to cerebrovascular injury.
Keywords: Animals; Blotting, Western; Cerebral Cortex; Enzyme Activation; Gene Expression Profiling; Genetic Predisposition to Disease; Male; MAP Kinase Signaling System; Mitogen-Activated Protein Kinases; Oligonucleotide Array Sequence Analysis; Phosphorylation; Protein Kinases; Proteomics; Rats; Rats, Inbred SHR; Receptor, trkB; Stroke

Genetic disruption of cortical interneuron development causes region- and GABA cell type-specific deficits, epilepsy, and behavioral dysfunction. - Powell, Elizabeth M; Campbell, Daniel B; Stanwood, Gregg D; Davis, Caleb; Noebels, Jeffrey L; Levitt, Pat (J Neurosci, 2003)
The generation of properly functioning circuits during brain development requires precise timing of cell migration and differentiation. Disruptions in the developmental plan may lead to neurological and psychiatric disorders. Neocortical circuits rely on inhibitory GABAergic interneurons, the majority of which migrate from subcortical sources. We have shown that the pleiotropic molecule hepatocyte growth factor/scatter factor (HGF/SF) mediates interneuron migration. Mice with a targeted mutation of the gene encoding urokinase plasminogen activator receptor (uPAR), a key component in HGF/SF activation and function, have decreased levels of HGF/SF and a 50% reduction in neocortical GABAergic interneurons at embryonic and perinatal ages. Disruption of interneuron development leads to early lethality in most models. Thus, the long-term consequences of such perturbations are unknown. Mice of the uPAR-/- strain survive until adulthood, and behavior testing demonstrates that they have an increased anxiety state. The uPAR-/- strain also exhibits spontaneous seizure activity and higher susceptibility to pharmacologically induced convulsions. The neocortex of the adult uPAR-/- mouse exhibits a dramatic region- and subtype-specific decrease in GABA-immunoreactive interneurons. Anterior cingulate and parietal cortical areas contain 50% fewer GABAergic interneurons compared with wild-type littermates. However, interneuron numbers in piriform and visual cortical areas do not differ from those of normal mice. Characterization of interneuron subpopulations reveals a near complete loss of the parvalbumin subtype, with other subclasses remaining intact. These data demonstrate that a single gene mutation can selectively alter the development of cortical interneurons in a region- and cell subtype-specific manner, with deficits leading to long-lasting changes in circuit organization and behavior.
Keywords: Animals; Anxiety; Behavior, Animal; Calcium-Binding Proteins; Cell Count; Darkness; Electroencephalography; Epilepsy; Exploratory Behavior; GABA Antagonists; gamma-Aminobutyric Acid; Genetic Predisposition to Disease; Interneurons; Light; Male; Mice; Mice, Inbred C57BL; Mice, Knockout; Neocortex; Receptors, Cell Surface; Receptors, Urokinase Plasminogen Activator; Spatial Behavior

Graded phenotypic response to partial and complete deficiency of a brain-specific transcript variant of the winged helix transcription factor RFX4. - Blackshear, Perry J; Graves, Joan P; Stumpo, Deborah J; Cobos, Inma; Rubenstein, John L R; Zeldin, Darryl C (Development, 2003)
One line of mice harboring a cardiac-specific epoxygenase transgene developed head swelling and rapid neurological decline in young adulthood, and had marked hydrocephalus of the lateral and third ventricles. The transgene was found to be inserted into an intron in the mouse Rfx4 locus. This insertion apparently prevented expression of a novel variant transcript of RFX4 (RFX4_v3), a member of the regulatory factor X family of winged helix transcription factors. Interruption of two alleles resulted in profound failure of dorsal midline brain structure formation and perinatal death, presumably by interfering with expression of downstream genes. Interruption of a single allele prevented formation of the subcommissural organ, a structure important for cerebrospinal fluid flow through the aqueduct of Sylvius, and resulted in congenital hydrocephalus. These data implicate the RFX4_v3 variant transcript as being crucial for early brain development, as well as for the genesis of the subcommissural organ. These findings may be relevant to human congenital hydrocephalus, a birth defect that affects approximately 0.6 per 1000 newborns.
Keywords: Alternative Splicing; Amino Acid Sequence; Animals; Brain; DNA-Binding Proteins; Embryo, Mammalian; Helix-Turn-Helix Motifs; Humans; Hydrocephalus; In Situ Hybridization; Mice; Mice, Transgenic; Molecular Sequence Data; Phenotype; Protein Isoforms; Regulatory Factor X Transcription Factors; Sequence Alignment; Tissue Distribution; Transcription Factors

How is the Drosophila research community making use of the genome sequence? - Stephen Richards (Genome Biol, 2003)
A report on the 44th Annual Drosophila Research Conference, Chicago, USA, 5-9 March, 2003.
Keywords: Animals; Drosophila; Genome; Research; Research Design

Human genetics. Primate shadow play. - Richard A Gibbs; Nelson, David L (Science, 2003)
Keywords: Animals; Biological Evolution; Cebidae; Cercopithecidae; Computational Biology; Conserved Sequence; Exons; Genome; Genome, Human; Hominidae; Humans; Models, Statistical; Phylogeny; Primates; Regulatory Sequences, Nucleic Acid; Sequence Analysis, DNA; Species Specificity

Internet Contig Explorer (iCE)--a tool for visualizing clone fingerprint maps. - Fjell, Christopher D; Bosdet, Ian; Schein, Jacqueline E; Jones, Steven J M; Marra, Marco A (Genome Res, 2003)
Fingerprinted clone physical maps have proven useful in various applications, supporting both whole-genome and region-specific DNA sequencing as well as gene cloning studies. Fingerprint maps have been generated for several genomes, including those of human, mouse, rat, the nematodes Caenorhabditis elegans and Caenorhabditis briggsae, Arabidopsis thaliana and rice. Fingerprint maps of other genomes, including those of fungi, bacteria, poplar, and the cow, are being generated. The increasing use of fingerprint maps in genomic research has spawned a need in the research community for intuitive computer tools that facilitate viewing of the maps and the underlying fingerprint data. In this report we describe a new Java-based application called iCE (Internet Contig Explorer) that has been designed to provide views of fingerprint maps and associated data. Users can search for and display individual clones, contigs, clone fingerprints, clone insert sizes and markers. Users can also load into the software lists of particular clones of interest and view their fingerprints. iCE is being used at our Genome Centre to offer up to the research community views of the mouse, rat, bovine, C. briggsae, and several fungal genome bacterial artificial chromosome (BAC) fingerprint maps we have either completed or are currently constructing. We are also using iCE as part of the Rat Genome Sequencing Project to manage our provision of rat BAC clones for sequencing at the Human Genome Sequencing Center at the Baylor College of Medicine.
Keywords: Animals; Arabidopsis; Caenorhabditis; Caenorhabditis elegans; Cloning, Molecular; Contig Mapping; DNA Fingerprinting; DNA, Helminth; DNA, Plant; Humans; Internet; Mice; Oryza; Rats; Software

Mechanism of hedgehog signaling during Drosophila eye development. - Pappu, Kartik S; Rui Chen; Middlebrooks, Brooke W; Woo, Catherine; Heberlein, Ulrike; Mardon, Graeme (Development, 2003)
Although Hedgehog (Hh) signaling is essential for morphogenesis of the Drosophila eye, its exact link to the network of tissue-specific genes that regulate retinal determination has remained elusive. In this report, we demonstrate that the retinal determination gene eyes absent (eya) is the crucial link between the Hedgehog signaling pathway and photoreceptor differentiation. Specifically, we show that the mechanism by which Hh signaling controls initiation of photoreceptor differentiation is to alleviate repression of eya and decapentaplegic (dpp) expression by the zinc-finger transcription factor Cubitus interruptus (Ci(rep)). Furthermore, our results suggest that stabilized, full length Ci (Ci(act)) plays little or no role in Drosophila eye development. Moreover, while the effects of Hh are primarily concentration dependent in other tissues, hh signaling in the eye acts as a binary switch to initiate retinal morphogenesis by inducing expression of the tissue-specific factor Eya.
Keywords: Animals; Cell Differentiation; DNA-Binding Proteins; Drosophila melanogaster; Drosophila Proteins; Eye Proteins; Hedgehog Proteins; Models, Biological; Morphogenesis; Organisms, Genetically Modified; Photoreceptor Cells, Invertebrate; Signal Transduction; Transcription Factors; Wings, Animal

Positional cloning of the major quantitative trait locus underlying lung tumor susceptibility in mice. - Zhang, Zhongqiu; Futamura, Manabu; Vikis, Haris G; Wang, Min; Li, Jie; Wang, Yian; Guan, Kun-Liang; You, Ming (Proc Natl Acad Sci U S A, 2003)
Pulmonary adenoma susceptibility 1 (Pas1), located on chromosome 6, is the major locus affecting inherited predisposition to lung tumor development in mice. We have fine mapped the Pas1 locus to a region of approximately 0.5 megabases by using congenic strains of mice, constructed by placing the Pas1 region of chromosome 6 from A/J mice onto the genetic background of C57BL/6J mice. Systematic characterization of Pas1 candidates establishes the Las1 (lung adenoma susceptibility 1) and Kras2 (Kirsten rat sarcoma oncogene 2) genes as primary candidates for the Pas1 locus. Clearly, Kras2 affects lung tumor progression only, and Las1 is likely to affect lung tumor multiplicity.
Keywords: Adenoma; Amino Acid Sequence; Animals; Base Sequence; Blotting, Northern; Chromosome Mapping; Ciona intestinalis; Cloning, Molecular; DNA Primers; Genetic Markers; Genetic Predisposition to Disease; Humans; Lung Neoplasms; Male; Mice; Mice, Inbred A; Mice, Inbred C57BL; Mice, Nude; Microsatellite Repeats; Molecular Sequence Data; Proto-Oncogene Proteins; Proto-Oncogene Proteins p21(ras); Quantitative Trait Loci; ras Proteins; Reverse Transcriptase Polymerase Chain Reaction; Sequence Alignment; Sequence Homology, Amino Acid

A proposal to sequence the amphioxus genome submitted to the Joint Genome Institute of the US Department of Energy. - Gibson-Brown, Jeremy J; Osoegawa, Kazutoyo; McPherson, John D; Waterston, Robert H; De Jong, Pieter J; Rokhsar, Daniel S; Holland, Linda Z (J Exp Zool B Mol Dev Evol, 2003)
Keywords: Animals; Chordata, Nonvertebrate; Genome; Research Design; Sequence Analysis, DNA; United States

Sequence and structure of the extrachromosomal palindrome encoding the ribosomal RNA genes in Dictyostelium. - Sucgang, Richard; Chen, Guokai; Liu, Wen; Lindsay, Ryan; Lu, Jing; Donna M Muzny; Shaulsky, Gad; Loomis, William; Richard A Gibbs; Kuspa, Adam (Nucleic Acids Res, 2003)
Ribosomal RNAs (rRNAs) are encoded by multicopy families of identical genes. In Dictyostelium and other protists, the rDNA is carried on extrachromosomal palindromic elements that comprise up to 20% of the nuclear DNA. We present the sequence of the 88 kb Dictyostelium rDNA element, noting that the rRNA genes are likely to be the only transcribed regions. By interrogating a library of ordered YAC clones, we provide evidence for a chromosomal copy of the rDNA on chromosome 4. This locus may provide master copies for the stable transmission of the extrachromosomal elements. The extrachromosomal elements were also found to form chromosome-sized clusters of DNA within nuclei of nocodazole-treated cells arrested in mitosis. These clusters resemble true chromosomes and may allow the efficient segregation of the rDNA during mitosis. These rDNA clusters may also explain the cytological observations of a seventh chromosome in this organism.
Keywords: Animals; Chromosome Mapping; Dictyostelium; DNA, Protozoan; In Situ Hybridization, Fluorescence; Molecular Sequence Data; Plasmids; RNA, Ribosomal; Sequence Analysis, DNA

Single nucleotide polymorphism (SNP) analysis of mouse pulmonary adenoma susceptibility loci 1-4 for identification of candidate genes. - Lemon, W J; Swinton, C H; Wang, M; Berbari, N; Wang, Y; You, M (J Med Genet, 2003)
Keywords: Adenoma; Animals; Chromosome Mapping; Gene Expression Profiling; Genetic Predisposition to Disease; Lung; Lung Neoplasms; Mice; Mice, Inbred BALB C; Mice, Inbred C57BL; Mice, Inbred Strains; Oligonucleotide Array Sequence Analysis; Polymorphism, Single Nucleotide; Quantitative Trait Loci

Software for automated analysis of DNA fingerprinting gels. - Fuhrmann, Daniel R; Krzywinski, Martin I; Chiu, Readman; Saeedi, Parvaneh; Schein, Jacqueline E; Bosdet, Ian E; Chinwalla, Asif; Hillier, LaDeana W; Waterston, Robert H; McPherson, John D; Jones, Steven J M; Marra, Marco A (Genome Res, 2003)
Here we describe software tools for the automated detection of DNA restriction fragments resolved on agarose fingerprinting gels. We present a mathematical model for the location and shape of the restriction fragments as a function of fragment size, with model parameters determined empirically from "marker" lanes containing molecular size standards. Automated identification of restriction fragments involves several steps, including: image preprocessing, to put the data in a form consistent with a linear model; marker lane analysis, for determination of the model parameters; and data lane analysis, a procedure for detecting restriction fragment multiplets while simultaneously determining the amplitude curve that describes restriction fragment amplitude as a function of mobility. In validation experiments conducted on fingerprinted and sequenced Bacterial Artificial Chromosome (BAC) clones, sensitivity and specificity of restriction fragment identification exceeded 96% on restriction fragments ranging in size from 600 base pairs (bp) to 30,000 bp. The integrated suite of software tools, written in MATLAB and collectively called BandLeader, is in use at the BC Cancer Agency Genome Sciences Centre (GSC) and the Washington University Genome Sequencing Center, and has been provided to the Wellcome Trust Sanger Institute and the Whitehead Institute. Employed in a production mode at the GSC, BandLeader has been used to perform automated restriction fragment identification for more than 850,000 BAC clones for mouse, rat, bovine, and poplar fingerprint mapping projects.
Keywords: Animals; Cattle; Chromosomes, Artificial, Bacterial; DNA; DNA Fingerprinting; Gels; Mice; Models, Chemical; Rats; Sepharose; Software

Using a pericentromeric interspersed repeat to recapitulate the phylogeny and expansion of human centromeric segmental duplications. - Horvath, J E; Gulden, C L; Bailey, J A; Yohn, C; McPherson, J D; Prescott, A; Roe, B A; de Jong, P J; Ventura, M; Misceo, D; Archidiacono, N; Zhao, S; et al. (Mol Biol Evol, 2003)
Despite considerable advances in sequencing of the human genome over the past few years, the organization and evolution of human pericentromeric regions have been difficult to resolve. This is due, in part, to the presence of large, complex blocks of duplicated genomic sequence at the boundary between centromeric satellite and unique euchromatic DNA. Here, we report the identification and characterization of an approximately 49-kb repeat sequence that exists in more than 40 copies within the human genome. This repeat is specific to highly duplicated pericentromeric regions with multiple copies distributed in an interspersed fashion among a subset of human chromosomes. Using this interspersed repeat (termed PIR4) as a marker of pericentromeric DNA, we recovered and sequence-tagged 3 Mb of pericentromeric DNA from a variety of human chromosomes as well as nonhuman primate genomes. A global evolutionary reconstruction of the dispersal of PIR4 sequence and analysis of flanking sequence supports a model in which pericentromeric duplications initiated before the separation of the great ape species (>12 MYA). Further, analyses of this duplication and associated flanking duplications narrow the major burst of pericentromeric duplication activity to a time just before the divergence of the African great ape and human species (5 to 7 MYA). These recent duplication exchange events substantially restructured the pericentromeric regions of hominoid chromosomes and created an architecture where large blocks of sequence are shared among nonhomologous chromosomes. This report provides the first global view of the series of historical events that have reshaped human pericentromeric regions over recent evolutionary time.
Keywords: Animals; Centromere; Chromosomes, Human; Evolution, Molecular; Gene Duplication; Genetic Variation; Genome, Human; Hominidae; Humans; In Situ Hybridization, Fluorescence; Molecular Sequence Data; Phylogeny; Physical Chromosome Mapping; Primates; Repetitive Sequences, Nucleic Acid

Efficient isolation of targeted Caenorhabditis elegans deletion strains using highly thermostable restriction endonucleases and PCR. - Wei, Aguan; Yuan, Alex; Fawcett, Gloria; Butler, Alice; Davis, Theodore; Xu, Shuang-yong; Salkoff, Lawrence (Nucleic Acids Res, 2002)
Reverse genetic approaches to understanding gene function would be greatly facilitated by increasing the efficiency of methods for isolating mutants without the reliance on a predicted phenotype. Established PCR-based methods of isolating deletion mutants are widely used for this purpose in Caenorhabditis elegans. However, these methods are inefficient at isolating small deletions. We report here a novel modification of PCR-based methods, employing thermostable restriction enzymes to block the synthesis of wild-type PCR product, so that only the deletion PCR product is amplified. This modification greatly increases the efficiency of isolating small targeted deletions in C.elegans. Using this method six new deletion strains were isolated from a small screen of approximately 400 000 haploid genomes, most with deletions <1.0 kb. Greater PCR detection sensitivity by this modification permitted approximately 10-fold greater pooling of DNA samples, reducing the effort and reagents required for screens. In addition, effective suppression of non-specific amplification allowed multiplexing with several independent primer pairs. The increased efficiency of this technique makes it more practical for small laboratories to undertake gene knock-out screens.
Keywords: Animals; Caenorhabditis elegans; Deoxyribonucleases, Type II Site-Specific; DNA Primers; DNA Restriction Enzymes; DNA, Helminth; Gene Targeting; Polymerase Chain Reaction; Sensitivity and Specificity; Sequence Deletion; Temperature

The Enterococcus faecalis fsrB gene, a key component of the fsr quorum-sensing system, is associated with virulence in the rabbit endophthalmitis model. - Mylonakis, Eleftherios; Engelbert, Michael; Xiang Qin; Sifri, Costi D; Murray, Barbara E; Ausubel, Frederick M; Gilmore, Michael S; Calderwood, Stephen B (Infect Immun, 2002)
We used a rabbit endophthalmitis model to explore the role of fsrB, a gene required for the function of the fsr quorum-sensing system of Enterococcus faecalis, in pathogenicity. A nonpolar deletion mutant of fsrB had significantly reduced virulence compared to wild type. Complementation of mutation restored virulence. These data corroborate the role of fsrB in E. faecalis pathogenesis and suggest that the rabbit endophthalmitis model can be used to study the in vivo role of quorum sensing.
Keywords: Animals; Bacterial Proteins; Disease Models, Animal; Endophthalmitis; Enterococcus faecalis; Eye; Female; Genes, Bacterial; Gram-Positive Bacterial Infections; Rabbits; Retina; Virulence; Vision, Ocular

Evolutionary traces of functional surfaces along G protein signaling pathway. - Lichtarge, Olivier; Sowa, Mathew E; Philippi, Anne (Methods Enzymol, 2002)
Keywords: Amino Acid Sequence; Animals; Binding Sites; Cell Membrane; Conserved Sequence; Evolution, Molecular; Heterotrimeric GTP-Binding Proteins; Models, Molecular; Molecular Sequence Data; Phylogeny; Protein Conformation; Protein Subunits; Receptors, Purinergic P1; RGS Proteins; Signal Transduction

Finishing a whole-genome shotgun: release 3 of the Drosophila melanogaster euchromatic genome sequence. - Celniker, Susan E; Wheeler, David A; Kronmiller, Brent; Carlson, Joseph W; Halpern, Aaron; Patel, Sandeep; Adams, Mark; Champe, Mark; Dugan, Shannon P; Frise, Erwin; Hodgson, Ann; George, Reed A; et al. (Genome Biol, 2002)
BACKGROUND: The Drosophila melanogaster genome was the first metazoan genome to have been sequenced by the whole-genome shotgun (WGS) method. Two issues relating to this achievement were widely debated in the genomics community: how correct is the sequence with respect to base-pair (bp) accuracy and frequency of assembly errors? And, how difficult is it to bring a WGS sequence to the accepted standard for finished sequence? We are now in a position to answer these questions. RESULTS: Our finishing process was designed to close gaps, improve sequence quality and validate the assembly. Sequence traces derived from the WGS and draft sequencing of individual bacterial artificial chromosomes (BACs) were assembled into BAC-sized segments. These segments were brought to high quality, and then joined to constitute the sequence of each chromosome arm. Overall assembly was verified by comparison to a physical map of fingerprinted BAC clones. In the current version of the 116.9 Mb euchromatic genome, called Release 3, the six euchromatic chromosome arms are represented by 13 scaffolds with a total of 37 sequence gaps. We compared Release 3 to Release 2; in autosomal regions of unique sequence, the error rate of Release 2 was one in 20,000 bp. CONCLUSIONS: The WGS strategy can efficiently produce a high-quality sequence of a metazoan genome while generating the reagents required for sequence finishing. However, the initial method of repeat assembly was flawed. The sequence we report here, Release 3, is a reliable resource for molecular genetic experimentation and computational analysis.
Keywords: Animals; Drosophila melanogaster; Euchromatin; Genome; Physical Chromosome Mapping; Research Design; Sequence Analysis, DNA; X Chromosome

Generation and initial analysis of more than 15,000 full-length human and mouse cDNA sequences. - Strausberg, Robert L; Feingold, Elise A; Grouse, Lynette H; Derge, Jeffery G; Klausner, Richard D; Collins, Francis S; Wagner, Lukas; Shenmen, Carolyn M; Schuler, Gregory D; Altschul, Stephen F; Zeeberg, Barry; Buetow, Kenneth H; et al. (Proc Natl Acad Sci U S A, 2002)
The National Institutes of Health Mammalian Gene Collection (MGC) Program is a multiinstitutional effort to identify and sequence a cDNA clone containing a complete ORF for each human and mouse gene. ESTs were generated from libraries enriched for full-length cDNAs and analyzed to identify candidate full-ORF clones, which then were sequenced to high accuracy. The MGC has currently sequenced and verified the full ORF for a nonredundant set of >9,000 human and >6,000 mouse genes. Candidate full-ORF clones for an additional 7,800 human and 3,500 mouse genes also have been identified. All MGC sequences and clones are available without restriction through public databases and clone distribution networks (see http:mgc.nci.nih.gov).
Keywords: Algorithms; Animals; DNA, Complementary; Gene Library; Humans; Mice; Open Reading Frames; Sequence Analysis, DNA

Glass bead purification of plasmid template DNA for high throughput sequencing of mammalian genomes. - Dederich, Debra A; Okwuonu, Geoffrey; Garner, Toni; Denn, Amanda; Sutton, Angelica; Escotto, Michael; Martindale, Ashley; Delgado, Oliver; Donna M Muzny; Richard A Gibbs; Metzker, Michael L (Nucleic Acids Res, 2002)
To meet the new challenge of generating the draft sequences of mammalian genomes, we describe the development of a novel high throughput 96-well method for the purification of plasmid DNA template using size-fractionated, acid-washed glass beads. Unlike most previously described approaches, the current method has been designed and optimized to facilitate the direct binding of alcohol-precipitated plasmid DNA to glass beads from alkaline lysed bacterial cells containing the insoluble cellular aggregate material. Eliminating the tedious step of separating the cleared lysate significantly simplifies the method and improves throughput and reliability. During a 4 month period of 96-capillary DNA sequencing of the Rattus norvegicus genome at the Baylor College of Medicine Human Genome Sequencing Center, the average success rate and read length derived from >1 800 000 plasmid DNA templates prepared by the direct lysis/glass bead method were 82.2% and 516 bases, respectively. The cost of this direct lysis/glass bead method in September 2001 was approximately 10 cents per clone, which is a significant cost saving in high throughput genomic sequencing efforts.
Keywords: Animals; DNA; Genome; Glass; Microspheres; Plasmids; Rats; Reproducibility of Results; Sequence Analysis, DNA

Initial sequencing and comparative analysis of the mouse genome. - Waterston, Robert H; Lindblad-Toh, Kerstin; Birney, Ewan; Rogers, Jane; Abril, Josep F; Agarwal, Pankaj; Agarwala, Richa; Ainscough, Rachel; Alexandersson, Marina; An, Peter; Antonarakis, Stylianos E; Attwood, John; et al. (Nature, 2002)
The sequence of the mouse genome is a key informational tool for understanding the contents of the human genome and a key experimental tool for biomedical research. Here, we report the results of an international collaboration to produce a high-quality draft sequence of the mouse genome. We also present an initial comparative analysis of the mouse and human genomes, describing some of the insights that can be gleaned from the two sequences. We discuss topics including the analysis of the evolutionary forces shaping the size, structure and sequence of the genomes; the conservation of large-scale synteny across most of the genomes; the much lower extent of sequence orthology covering less than half of the genomes; the proportions of the genomes under selection; the number of protein-coding genes; the expansion of gene families related to reproduction and immunity; the evolution of proteins; and the identification of intraspecies polymorphism.
Keywords: Animals; Base Composition; Chromosomes, Mammalian; Conserved Sequence; CpG Islands; Evolution, Molecular; Gene Expression Regulation; Genes; Genetic Variation; Genome; Genome, Human; Genomics; Humans; Mice; Mice, Knockout; Mice, Transgenic; Models, Animal; Multigene Family; Mutagenesis; Neoplasms; Physical Chromosome Mapping; Proteome; Pseudogenes; Quantitative Trait Loci; Repetitive Sequences, Nucleic Acid; RNA, Untranslated; Selection, Genetic; Sequence Analysis, DNA; Sex Chromosomes; Species Specificity; Synteny

Intron-size constraint as a mutational mechanism in Rothmund-Thomson syndrome. - Wang, Lisa L; Worley, Kim; Gannavarapu, Anu; Chintagumpala, Murali M; Levy, Moise L; Plon, Sharon E (Am J Hum Genet, 2002)
Rothmund-Thomson syndrome (RTS) is an autosomal recessive disorder caused by deleterious mutations in the RECQL4 gene on chromosome 8. The RECQL4 gene structure is unusual because it contains many small introns <100 bp. We describe a proband with RTS who has a novel 11-bp intronic deletion, and we show that this mutation results in a 66-bp intron too small for proper splicing. Constraint on intron size may represent a general mutational mechanism, since human-genome analysis reveals that approximately 15% of genes have introns <100 bp and are therefore susceptible to size constraint. Thus, monitoring of intron size may allow detection of mutations missed by exon-by-exon approaches.
Keywords: 3T3 Cells; Adenosine Triphosphatases; Animals; Base Sequence; DNA; DNA Helicases; Humans; Introns; Mice; Molecular Sequence Data; Mutation; RecQ Helicases; Reverse Transcriptase Polymerase Chain Reaction; RNA Splicing; Rothmund-Thomson Syndrome; Transfection

Polymorphism in soluble epoxide hydrolase and blood pressure in spontaneously hypertensive rats. - Fornage, Myriam; Hinojos, Cruz A; Nurowska, Barbara W; Eric Boerwinkle; Hammock, Bruce D; Morisseau, Christophe H P; Doris, Peter A (Hypertension, 2002)
We measured soluble epoxide hydrolase (sEH) renal gene expression in prehypertensive (4 to 5 weeks old) spontaneously hypertensive rats of the Heidelberg SP substrain (SHR [Heid]) and when blood pressure levels entered the hypertensive plateau (17 to 18 weeks old) and compared expression with matched Wistar-Kyoto (WKY [Heid]) rats. Less expression of the gene encoding sEH (EPHX2) was observed in SHR (Heid) than in WKY (Heid). Analysis of sEH protein abundance showed a similar difference. However, no correlation between sEH abundance and blood pressure was observed in the F(2) progeny of a parental strain cross. Measurement of protein abundance in SHR and WKY obtained from Charles River confirmed a recent report that abundance of sEH was greater in SHR (CRiv) than WKY (CRiv) strains. Polymorphisms were detected in EPHX2. Resequencing revealed that 2 alleles of EPHX2 exist in these 4 rat strains, differing by 4 single nucleotide polymorphisms, of which 3 produce nonsynonymous amino acid substitutions. The ancestral allele was shared by SHR (Heid) and WKY (CRiv), and the variant allele was shared by WKY (Heid) and SHR (CRiv). Activity of sEH was greater in animals carrying the variant allele. However, inheritance of this allele was not correlated with blood pressure in the F(2) progeny of a cross between SHR (Heid) and WKY (Heid). These data indicate that sequence variation determining functional alterations in EPHX2 is not likely to contribute to blood pressure levels in SHR.
Keywords: Animals; Blood Pressure; Epoxide Hydrolases; Hypertension; Kidney; Male; Polymorphism, Single Nucleotide; Rats; Rats, Inbred SHR; Rats, Inbred WKY; RNA, Messenger

Virulence effect of Enterococcus faecalis protease genes and the quorum-sensing locus fsr in Caenorhabditis elegans and mice. - Sifri, Costi D; Mylonakis, Eleftherios; Singh, Kavindra V; Xiang Qin; Garsin, Danielle A; Murray, Barbara E; Ausubel, Frederick M; Calderwood, Stephen B (Infect Immun, 2002)
The expression of two Enterococcus faecalis extracellular virulence-related proteins, gelatinase (GelE) and serine protease (SprE), has been shown to be positively regulated by the fsr quorum-sensing system. We recently developed a novel system for studying E. faecalis pathogenicity that involves killing of the nematode worm Caenorhabditis elegans and showed that an E. faecalis fsrB mutant (strain TX5266) exhibited attenuated killing. We explore here the role of the fsr/gelE-sprE locus in pathogenicity by comparing results obtained in the nematode system with a mouse peritonitis model of E. faecalis infection. Insertion mutants of fsrA (TX5240) and fsrC (TX5242), like fsrB (TX5266), were attenuated in their ability to kill C. elegans. A deletion mutant of gelE (TX5264) and an insertion mutant of sprE (TX5243) were also attenuated in C. elegans killing, although to a lesser extent than the fsr mutants. Complementation of fsrB (TX5266) with a 6-kb fragment containing the entire fsr locus restored virulence in both the nematode and the mouse peritonitis models. The fsr mutants were not impaired in their ability to colonize the nematode intestine. These data show that extracellular proteases and the quorum-sensing fsr system are important for E. faecalis virulence in two highly divergent hosts: nematodes and mice.
Keywords: Animals; Bacterial Proteins; Caenorhabditis elegans; DNA-Binding Proteins; Enterococcus faecalis; Escherichia coli Proteins; Female; Gelatinases; Gene Expression Regulation, Bacterial; Genes, Bacterial; Genetic Complementation Test; Mice; Mice, Inbred ICR; Mutagenesis, Insertional; Sequence Deletion; Transcription Factors; Virulence

Characterization of the rat GRIK5 kainate receptor subunit gene promoter and its intragenic regions involved in neural cell specificity. - Chew, L J; Yuan, X; Steven E Scherer; Qie, L; Huang, F; Hayes, W P; Gallo, V (J Biol Chem, 2001)
The GRIK5 (glutamate receptor ionotropic kainate-5) gene encodes the kainate-preferring glutamate receptor subunit KA2. The GRIK5 promoter is TATA-less and GC-rich, with multiple consensus initiator sequences. Transgenic mouse lines carrying 4 kilobases of the GRIK5 5'-flanking sequence showed lacZ reporter expression predominantly in the nervous system. Reporter assays in central glial (CG-4) and non-neural cells indicated that a 1200-base pair (bp) 5'-flanking region could sustain neural cell-specific promoter activity. Transcriptional activity was associated with the formation of a transcription factor IID-containing complex on an initiator sequence located 1100 bp upstream of the first intron. In transfection studies, deletion of exonic sequences downstream of the promoter resulted in reporter gene activity that was no longer neural cell-specific. When placed downstream of the GRIK5 promoter, a 77-bp sequence from the deleted fragment completely silenced reporter expression in NIH3T3 fibroblasts while attenuating activity in CG-4 cells. Analysis of the 77-bp sequence revealed a functional SP1-binding site and a sequence resembling a neuron-restrictive silencer element. The latter sequence, however, did not display cell-specific binding of REST-like proteins. Our studies thus provide evidence for intragenic control of GRIK5 promoter activity and suggest that elements contributing to tissue-specific expression are contained within the first exon.
Keywords: 5' Flanking Region; Animals; Base Sequence; Cells, Cultured; Deoxyribonuclease I; Humans; Mice; Mice, Transgenic; Molecular Sequence Data; Neurons; Organ Specificity; Promoter Regions, Genetic; Protein Subunits; Rats; Receptors, Kainic Acid; Sp1 Transcription Factor

A clone-array pooled shotgun strategy for sequencing large genomes. - Cai, W W; Chen, R; Richard A Gibbs; Bradley, A (Genome Res, 2001)
A simplified strategy for sequencing large genomes is proposed. Clone-Array Pooled Shotgun Sequencing (CAPSS) is based on pooling rows and columns of arrayed genomic clones, for shotgun library construction. Random sequences are accumulated, and the data are processed by sequential comparison of rows and columns to assemble the sequence of clones at points of intersection. Compared with either a clone-by-clone approach or whole-genome shotgun sequencing, CAPSS requires relatively few library constructions and only minimal computational power for a complete genome assembly. The strategy is suitable for sequencing large genomes for which there are no sequence-ready maps, but for which relatively high resolution STS maps and highly redundant BAC libraries are available. It is immediately applicable to the sequencing of mouse, rat, zebrafish, and other important genomes, and can be managed in a cooperative fashion to take advantage of a distributed international DNA sequencing capacity.
Keywords: Animals; Computer Simulation; Genome; Humans; Mice; Oligonucleotide Array Sequence Analysis; Software

Comparing vertebrate whole-genome shotgun reads to the human genome. - Chen, R; Bouck, J B; Weinstock, G M; Richard A Gibbs (Genome Res, 2001)
Multi-species sequence comparisons are a very efficient way to reveal conserved genes. Because sequence finishing is expensive and time consuming, many genome sequences are likely to stay incomplete. A challenge is to use these fragmented data for understanding the human genome. Methods for using cross-species whole-genome shotgun sequence (WGS) for genome annotation are described in this paper. About one-half million high-quality rat WGS reads (covering 7.5% of the rat genome) generated at the Baylor College of Medicine Human Genome Sequencing Center were compared with the human genome. Using computer-generated random reads as a negative control, a set of parameters was determined for reliable interpretation of BLAST search results. About 10% of the rat reads contain regions that are conserved in the human genomic sequence and about one-third of these include known gene-coding regions. Mapping the conserved regions to human chromosomes showed a 23-fold enrichment for coding regions compared with noncoding regions. This approach can also be applied to other mammalian genomes for gene finding. These data predicted approximately 42,500 genes in the human, slightly more than reported previously.
Keywords: Animals; Base Sequence; Computational Biology; Conserved Sequence; Databases, Genetic; Expressed Sequence Tags; Genome; Genome, Human; Heterochromatin; Humans; Mice; Molecular Sequence Data; Rats; Sequence Analysis, DNA; Sequence Homology, Nucleic Acid; Species Specificity; Transcription, Genetic

DNA binding and modulation of gene expression by the latency-associated nuclear antigen of Kaposi's sarcoma-associated herpesvirus. - Garber, A C; Shu, M A; Jianhong Hu; Renne, R (J Virol, 2001)
Kaposi's sarcoma-associated herpesvirus (KSHV) is associated with Kaposi's sarcoma, primary effusion lymphoma, and multicentric Castleman's disease. The latency-associated nuclear antigen (LANA) is highly expressed in these malignancies and has been shown to play an important role in episomal maintenance, presumably by binding to a putative oriP. In addition, LANA modulates cellular and viral gene expression and interacts with the cellular tumor suppressors p53 and retinoblastoma suppressor protein. Many of these features are reminiscent of Epstein-Barr virus nuclear antigens (EBNAs), a family of six proteins expressed during latency. EBNA-1 is required for episome maintenance, binds to oriP, and strongly activates transcription from two promoters, including its own. We have previously shown that LANA can transactivate its own promoter and therefore asked whether LANA, like EBNA-1, activates transcription by direct binding to DNA. By using recombinant LANA expressed from vaccinia virus vectors for electrophoretic mobility shift assays, we found that LANA does not bind to its own promoter. In contrast, LANA binds specifically to sequences containing an imperfect 20-bp palindrome in the terminal repeat (TR) of KSHV. We further show that the C-terminal domain of LANA is sufficient for site-specific DNA binding. Unlike EBNA-1, which activates transcription through binding of oriP, we found that LANA inhibits transcription from a single TR binding site. A multimerized TR as found in the viral genome results in strong transcriptional suppression when linked to a heterologous promoter. These data suggest that LANA, although fulfilling functions similar to those of EBNA-1, does so by very different mechanisms.
Keywords: Animals; Antigens, Viral; Binding Sites; Cell Line; DNA, Viral; DNA-Directed RNA Polymerases; Gene Expression Regulation, Viral; Genetic Vectors; Herpesvirus 8, Human; Humans; Nuclear Proteins; Promoter Regions, Genetic; Terminal Repeat Sequences; Transcription, Genetic; Transfection; Vaccinia virus; Viral Proteins

Evolution tunes the excitability of individual neurons. - Salkoff, L; Butler, A; Fawcett, G; Kunkel, M; McArdle, C; Paz-y-Mino, G; Nonet, M; Walton, N; Wang, Z W; Yuan, A; Wei, A (Neuroscience, 2001)
The relationship between the genome and the evolution of the nervous system may differ between an animal like C. elegans with 302 neurons, and mammals with tens of billions of neurons. Here we report that a class of nonconserved potassium channels highly expanded in C. elegans may play a special role in the evolution of its nervous system. The C. elegans genome contains an extended gene family of potassium channels whose members fall into two evolutionary divergent classes. One class constitutes an ancient conserved "set" of K+ channels with orthologues in both humans and Drosophila and a second larger class made up of rapidly evolving genes unique to C. elegans. Chief among this second class are novel potassium channels having four transmembrane domains per subunit that function as regulated leak conductances to modulate cell electrical excitability. This inventory of novel potassium channels is far larger in C. elegans than in humans or Drosophila. We found that, unlike conserved channel genes, the majority of these genes are expressed in very few cells. We also identified DNA enhancer elements associated with these genes that direct gene expression to individual neurons. We conclude that C. elegans may maintain an exceptionally large inventory of these channels (as well as ligand-gated channels) as an adaptive mechanism to "fine tune" individual neurons, making the most of its limited circuitry.
Keywords: Adaptation, Physiological; Animals; Base Sequence; Biological Evolution; Caenorhabditis; Caenorhabditis elegans; DNA; Enhancer Elements, Genetic; Gene Expression; Molecular Sequence Data; Multigene Family; Neurons; Potassium Channels; Protein Isoforms

Initial sequencing and analysis of the human genome. - Lander, E S; Linton, L M; Birren, B; Nusbaum, C; Zody, M C; Baldwin, J; Devon, K; Dewar, K; Doyle, M; FitzHugh, W; Funke, R; Gage, D; et al. (Nature, 2001)
The human genome holds an extraordinary trove of information about human development, physiology, medicine and evolution. Here we report the results of an international collaboration to produce and make freely available a draft sequence of the human genome. We also present an initial analysis of the data, describing some of the insights that can be gleaned from the sequence.
Keywords: Animals; Chromosome Mapping; Conserved Sequence; CpG Islands; Databases, Factual; DNA Transposable Elements; Drug Industry; Evolution, Molecular; Forecasting; GC Rich Sequence; Gene Duplication; Genes; Genetic Diseases, Inborn; Genetics, Medical; Genome, Human; Human Genome Project; Humans; Mutation; Private Sector; Proteins; Proteome; Public Sector; Repetitive Sequences, Nucleic Acid; RNA; Sequence Analysis, DNA; Species Specificity

A simple model host for identifying Gram-positive virulence factors. - Garsin, D A; Sifri, C D; Mylonakis, E; Xiang Qin; Singh, K V; Murray, B E; Calderwood, S B; Ausubel, F M (Proc Natl Acad Sci U S A, 2001)
We demonstrate the use of the nematode Caenorhabditis elegans as a facile and inexpensive model host for several Gram-positive human bacterial pathogens. Enterococcus faecalis, Streptococcus pneumoniae, and Staphylococcus aureus, but not Bacillus subtilis, Enterococcus faecium, or Streptococcus pyogenes, kill adult C. elegans. Focusing our studies on the enterococcal species, we found that both E. faecalis and E. faecium kill C. elegans eggs and hatchlings, although only E. faecalis kills the adults. In the case of adults, a low inoculum of E. faecalis grows to a high titer in the C. elegans intestine, resulting in a persistent infection that cannot be eradicated by prolonged feeding on E. faecium. Interestingly, a high titer of E. faecium also accumulates in the nematode gut, but does not affect the longevity of the worms. Two E. faecalis virulence-related factors that play an important role in mammalian models of infection, fsr, a putative quorum-sensing system, and cytolysin, are also important for nematode killing. We exploit the apparent parallels between Gram-positive infection in simple and more complex organisms by using the nematode to identify an E. faecalis virulence factor, ScrB, which is relevant to mammalian pathogenesis.
Keywords: Animals; Bacillus subtilis; Bacterial Proteins; Bacteriocins; Caenorhabditis elegans; Cytotoxins; Digestive System; Disease Models, Animal; Enterococcus faecalis; Enterococcus faecium; Gene Deletion; Gram-Positive Bacteria; Humans; Mice; Mice, Inbred ICR; Staphylococcus aureus; Streptococcus pneumoniae; Streptococcus pyogenes

Analysis of a gene cluster of Enterococcus faecalis involved in polysaccharide biosynthesis. - Xu, Y; Singh, K V; Xiang Qin; Murray, B E; Weinstock, G M (Infect Immun, 2000)
Previously, we described a gene cluster of Enterococcus faecalis OG1RF that produced an antigenic polysaccharide when cloned in Escherichia coli. The polysaccharide antigen was not detectable in E. faecalis strains, however. Here, we show by reverse transcriptase-PCR that the 16 genes in this region are transcribed in OG1RF. Gene disruption of orfde4, encoding a putative glycosyl transferase, and orfde6, a putative dTDP-rhamnose biosynthesis gene, generated two OG1RF mutants. The mutants showed delayed killing and a higher 50% lethal dose in a mouse peritonitis model. In addition, two mucoid E. faecalis isolates from patients with chronic urinary tract infections were found to produce the polysaccharide antigen.
Keywords: Animals; Enterococcus faecalis; Genes, Bacterial; Humans; Mice; Multigene Family; Mutation; Open Reading Frames; Peritonitis; Polysaccharides, Bacterial; Reverse Transcriptase Polymerase Chain Reaction; RNA, Messenger; Transcription, Genetic

A BAC-based physical map of the major autosomes of Drosophila melanogaster. - Hoskins, R A; Nelson, C R; Berman, B P; Laverty, T R; George, R A; Ciesiolka, L; Naeemuddin, M; Arenson, A D; Durbin, J; David, R G; Tabor, P E; Bailey, M R; et al. (Science, 2000)
We constructed a bacterial artificial chromosome (BAC)-based physical map of chromosomes 2 and 3 of Drosophila melanogaster, which constitute 81% of the genome. Sequence tagged site (STS) content, restriction fingerprinting, and polytene chromosome in situ hybridization approaches were integrated to produce a map spanning the euchromatin. Three of five remaining gaps are in repeat-rich regions near the centromeres. A tiling path of clones spanning this map and STS maps of chromosomes X and 4 was sequenced to low coverage; the maps and tiling path sequence were used to support and verify the whole-genome sequence assembly, and tiling path BACs were used as templates in sequence finishing.
Keywords: Animals; Centromere; Chromatin; Chromosomes, Bacterial; Cloning, Molecular; Contig Mapping; DNA Fingerprinting; Drosophila melanogaster; Euchromatin; Gene Library; Genes, Insect; Genetic Markers; Genetic Vectors; Genome; In Situ Hybridization; Repetitive Sequences, Nucleic Acid; Restriction Mapping; Sequence Analysis, DNA; Sequence Tagged Sites; Telomere

Effects of Enterococcus faecalis fsr genes on production of gelatinase and a serine protease and virulence. - Xiang Qin; Singh, K V; Weinstock, G M; Murray, B E (Infect Immun, 2000)
Three agr-like genes (fsrA, fsrB, and fsrC, for Enterococcus faecalis regulator) were found upstream of the previously reported gelatinase gene (gelE) and a downstream putative serine protease gene (sprE; accession number Z12296) of Enterococcus faecalis OG1RF. The deduced amino acid sequence of fsrA shows 26% identity and 38% similarity to Staphylococcus aureus AgrA (the response regulator of the accessory gene regulator system in the agr locus), FsrB shows 23% identity and 41% similarity to S. aureus AgrB, and FsrC shows 23% identity and 36% similarity to S. aureus AgrC (the sensor transducer of Agr system). Northern blot analysis suggested that gelE and sprE are cotranscribed and that fsrB and fsrC are also cotranscribed in OG1RF. Northern blot analysis of fsrA, fsrB, fsrC, gelE, and sprE insertion mutants showed that fsrB, fsrC, gelE, and sprE are not expressed in fsrA, fsrB, and fsrC mutants, while insertion in an open reading frame further upstream of fsrA did not effect the expression of these genes, suggesting that agr-like genes may be autoregulated and that they regulate gelE and sprE expression, as further confirmed by complementation of fsr gene mutations with a 6-kb fragment which contains all three fsr genes in the shuttle vector, pAT18. Testing of 95 other isolates of E. faecalis showed that 62% produced gelatinase (Gel(+)), while 91% (including all Gel(+) strains) hybridized to a gelE probe; 71% (including all Gel(+) strains) hybridized to an fsr probe, corroborating the conclusion that both gelE and fsr are necessary for gelatinase production. Testing of fsrA, fsrB, and sprE mutants in a mouse peritonitis model showed that sprE and agr-like gene mutants resulted in highly significantly prolonged survival compared to the parent strain OG1RF, a finding similar to what we had previously shown for a gelE mutant. These results suggest that sprE and agr-like genes contribute to the virulence of E. faecalis OG1RF in this model.
Keywords: Amino Acid Sequence; Animals; Bacterial Proteins; Base Sequence; Blotting, Northern; Databases, Factual; Dihydropteridine Reductase; Disease Models, Animal; DNA, Bacterial; DNA-Binding Proteins; Enterococcus faecalis; Escherichia coli Proteins; Gelatinases; Genes, Bacterial; Genetic Complementation Test; Hemeproteins; Mice; Molecular Sequence Data; NADH, NADPH Oxidoreductases; Peritonitis; Phenotype; Reverse Transcriptase Polymerase Chain Reaction; Sequence Analysis, DNA; Serine Endopeptidases; Trans-Activators; Transcription Factors; Virulence

Fine mapping and characterization of candidate lung tumor resistance genes for the Par2 locus on mouse chromosome 18. - Zhang, Z; Lin, L; Liu, G; Wang, M; Hill, J; Wang, Y; You, M; Devereux, T R (Exp Lung Res, 2000)
In a number of recent studies, a lung tumor resistance locus designated either Par2 or Pas7 was mapped to distal chromosome 18 in crosses between susceptible A/J and more resistant BALB/c mice. This locus is important in that it accounts for as much as 60% of the difference in lung tumor susceptibility between the A/J and BALB/c mice, both of which contain the susceptible allele of Kras2, a marker and strong candidate for the major lung tumor susceptibility gene on mouse chromosome 6. We have now fine-mapped the Par2 locus by using congenic mice that were constructed by placing part of chromosome 18 from the susceptible A/J onto the genetic background of lung tumor-resistant BALB/c mice. After 7 generations of backcrossing, N7 mice that carried 28 cM of the A/J quantitative trait locus (QTL) region were crossed to the BALB/c to generate the N8 generation. Congenic strains (N8) that contain various QTL regions were generated. N9 mice, generated from N8 males x 3 BALB/c females, were genotyped in the region of the Par2 locus and treated with an initiating dose of urethane and allowed to form lung tumors over 6 months. The mice were killed and the lung tumors counted. With this cross the Par2 locus was narrowed to a 6-cM region. Potential candidate genes in this region include Smad4, Smad2, and Dcc. Previously, we excluded Smad4 and Smad2 as candidates for Par2 based on the lack of functional polymorphism(s) and differential expression in lungs from A/J and BALB/c mice. In this study, no polymorphism of the coding sequence of Dcc was observed between A/J and BALB/c mice. Further fine mapping and positional cloning are required for the identification of the Par2 gene.
Keywords: Adenoma; Animals; Animals, Congenic; Chromosome Mapping; Disease Models, Animal; DNA, Neoplasm; Female; Genetic Markers; Genetic Predisposition to Disease; Lung Neoplasms; Male; Mice; Mice, Inbred BALB C; Polymerase Chain Reaction; Polymorphism, Single-Stranded Conformational; Pregnancy; Sequence Analysis, DNA

The genome sequence of Drosophila melanogaster. - Adams, M D; Celniker, S E; Holt, R A; Evans, C A; Gocayne, J D; Amanatides, P G; Steven E Scherer; Li, P W; Hoskins, R A; Galle, R F; George, R A; Lewis, S E; et al. (Science, 2000)
The fly Drosophila melanogaster is one of the most intensively studied organisms in biology and serves as a model system for the investigation of many developmental and cellular processes common to higher eukaryotes, including humans. We have determined the nucleotide sequence of nearly all of the approximately 120-megabase euchromatic portion of the Drosophila genome using a whole-genome shotgun sequencing strategy supported by extensive clone-based sequence and a high-quality bacterial artificial chromosome physical map. Efforts are under way to close the remaining gaps; however, the sequence is of sufficient accuracy and contiguity to be declared substantially complete and to support an initial analysis of genome structure and preliminary gene annotation and interpretation. The genome encodes approximately 13,600 genes, somewhat fewer than the smaller Caenorhabditis elegans genome, but with comparable functional diversity.
Keywords: Animals; Biological Transport; Chromatin; Cloning, Molecular; Computational Biology; Contig Mapping; Cytochrome P-450 Enzyme System; DNA Repair; DNA Replication; Drosophila melanogaster; Euchromatin; Gene Library; Genes, Insect; Genome; Heterochromatin; Insect Proteins; Nuclear Proteins; Protein Biosynthesis; Sequence Analysis, DNA; Transcription, Genetic

Haplotypes at ATM identify coding-sequence variation and indicate a region of extensive linkage disequilibrium. - Bonnen, P E; Story, M D; Ashorn, C L; Buchholz, T A; Weil, M M; Nelson, D L (Am J Hum Genet, 2000)
Genetic variation in the human population may lead to functional variants of genes that contribute to risk for common chronic diseases such as cancer. In an effort to detect such possible predisposing variants, we constructed haplotypes for a candidate gene and tested their efficacy in association studies. We developed haplotypes consisting of 14 biallelic neutral-sequence variants that span 142 kb of the ATM locus. ATM is the gene responsible for the autosomal recessive disease ataxia-telangiectasia (AT). These ATM noncoding single-nucleotide polymorphisms (SNPs) were genotyped in nine CEPH families (89 individuals) and in 260 DNA samples from four different ethnic origins. Analysis of these data with an expectation-maximization algorithm revealed 22 haplotypes at this locus, with three major haplotypes having frequencies > or = .10. Tests for recombination and linkage disequilibrium (LD) show reduced recombination and extensive LD at the ATM locus, in all four ethnic groups studied. The most striking example was found in the study population of European ancestry, in which no evidence for recombination could be discerned. The potential of ATM haplotypes for detection of genetic variants through association studies was tested by analysis of 84 individuals carrying one of three ATM coding SNPs. Each coding SNP was detected by association with an ATM haplotype. We demonstrate that association studies with haplotypes for candidate genes have significant potential for the detection of genetic backgrounds that contribute to disease.
Keywords: Algorithms; Alleles; Animals; Ataxia Telangiectasia; Ataxia Telangiectasia Mutated Proteins; Case-Control Studies; Cell Cycle Proteins; Codon; DNA-Binding Proteins; Ethnicity; Europe; Gene Frequency; Genetic Variation; Haplotypes; Hominidae; Humans; Linkage Disequilibrium; Molecular Sequence Data; Polymorphism, Single Nucleotide; Protein Serine-Threonine Kinases; Racial Groups; Recombination, Genetic; Tumor Suppressor Proteins

Intranasal immunization with HIV reverse transcriptase: effect of dose in the induction of helper T cell type 1 and 2 immunity. - Pacheco, S E; Richard A Gibbs; Ansari-Lari, A; Rogers, P (AIDS Res Hum Retroviruses, 2000)
HIV reverse transcriptase (RT) is immunologically recognized by the host after natural infection with HIV. To study the immune response to this nonenvelope protein and the effect of the antigen dose and the immunization route on the differential induction of cellular or humoral responses, CB6F1 mice were immunized intranasally with various doses of recombinant RT (0.025-25 microg/dose) in the presence of the mucosal adjuvant cholera toxin (CT). An antigen-specific, dose-dependent, in vitro proliferative response was observed in splenic cells from all mouse groups immunized with RT and CT. Proliferative responses in salivary gland-associated lymph node (SGALN) cells from the same mice were detected only with higher antigen dose immunizations (2.5, 25 microg/dose). IFN-gamma, a Th1-type cytokine, was detected in RT-stimulated culture supernatants from splenic and SGALN cells from all groups of mice immunized with RT and CT in a dose-dependent fashion. IL-4, a Th2-type cytokine, was detected in RT-stimulated culture supernatants from splenic and SGALN cells from mice immunized with higher doses of RT and CT. RT-specific IgG2a, a Th1-type-related antibody, was detected consistently in sera from all animals immunized with RT and CT and was predominant in mice immunized with lower antigen doses (0.025, 0.25 microg/dose). RT-specific IgG1, a Th2-type-related antibody, was detected consistently in mice immunized with higher antigen doses and was predominant in these groups. These studies demonstrate the immunogenicity of recombinant RT and the effect of the antigen dose in the induction of Th1-type and Th2-type immune responses after mucosal immunization.
Keywords: Administration, Intranasal; AIDS Vaccines; Animals; Cytokines; Dose-Response Relationship, Immunologic; Female; HIV Antibodies; HIV Reverse Transcriptase; Immunization; Immunoglobulin G; Lymph Nodes; Lymphocyte Activation; Mice; Recombinant Proteins; Salivary Glands; Spleen; Th1 Cells; Th2 Cells

Large expansion of the ATTCT pentanucleotide repeat in spinocerebellar ataxia type 10. - Matsuura, T; Yamagata, T; Burgess, D L; Rasmussen, A; Grewal, R P; Watase, K; Khajavi, M; McCall, A E; Davis, C F; Zu, L; Achari, M; Pulst, S M; et al. (Nat Genet, 2000)
Spinocerebellar ataxia type 10 (SCA10; MIM 603516; refs 1,2) is an autosomal dominant disorder characterized by cerebellar ataxia and seizures. The gene SCA10 maps to a 3.8-cM interval on human chromosome 22q13-qter (refs 1,2). Because several other SCA subtypes show trinucleotide repeat expansions, we examined microsatellites in this region. We found an expansion of a pentanucleotide (ATTCT) repeat in intron 9 of SCA10 in all patients in five Mexican SCA10 families. There was an inverse correlation between the expansion size, up to 22.5 kb larger than the normal allele, and the age of onset (r2=0.34, P=0.018). Analysis of 562 chromosomes from unaffected individuals of various ethnic origins (including 242 chromosomes from Mexican persons) showed a range of 10 to 22 ATTCT repeats with no evidence of expansions. Our data indicate that the new SCA10 intronic ATTCT pentanucleotide repeat in SCA10 patients is unstable and represents the largest microsatellite expansion found so far in the human genome.
Keywords: Animals; Asian People; Brain; Chromosome Mapping; Chromosomes, Human, Pair 22; DNA; Epilepsy; Female; Humans; Male; Mexican Americans; Mice; Mice, Inbred C57BL; Molecular Sequence Data; Pedigree; Polymorphism, Genetic; Repetitive Sequences, Nucleic Acid; Spinocerebellar Ataxias; United States; White People

PipMaker--a web server for aligning two genomic DNA sequences. - Schwartz, S; Zhang, Z; Frazer, K A; Smit, A; Riemer, C; Bouck, J; Richard A Gibbs; Hardison, R; Miller, W (Genome Res, 2000)
PipMaker (http://bio.cse.psu.edu) is a World-Wide Web site for comparing two long DNA sequences to identify conserved segments and for producing informative, high-resolution displays of the resulting alignments. One display is a percent identity plot (pip), which shows both the position in one sequence and the degree of similarity for each aligning segment between the two sequences in a compact and easily understandable form. Positions along the horizontal axis can be labeled with features such as exons of genes and repetitive elements, and colors can be used to clarify and enhance the display. The web site also provides a plot of the locations of those segments in both species (similar to a dot plot). PipMaker is appropriate for comparing genomic sequences from any two related species, although the types of information that can be inferred (e.g., protein-coding regions and cis-regulatory elements) depend on the level of conservation and the time and divergence rate since the separation of the species. Gene regulatory elements are often detectable as similar, noncoding sequences in species that diverged as much as 100-300 million years ago, such as humans and mice, Caenorhabditis elegans and C. briggsae, or Escherichia coli and Salmonella spp. PipMaker supports analysis of unfinished or "working draft" sequences by permitting one of the two sequences to be in unoriented and unordered contigs.
Keywords: Animals; Base Sequence; Caenorhabditis elegans; Computational Biology; DNA; Escherichia coli; Genes, Bacterial; Genes, Helminth; Genes, Protozoan; Humans; Internet; Mice; Molecular Sequence Data; Salmonella typhimurium; Sequence Alignment; Software

Shotgun sample sequence comparisons between mouse and human genomes. - Bouck, J B; Metzker, M L; Richard A Gibbs (Nat Genet, 2000)
A mixed 'clone-by-clone' and 'whole-genome shotgun' strategy will be used to determine the genomic sequence of the mouse. This method will allow a phase of rapid annotation of the contemporaneous human sequence draft, through whole-genome 'sample sequence comparisons'.
Keywords: Animals; Cloning, Molecular; Computational Biology; Female; Genome; Genomic Library; Humans; Mice; Mice, Inbred C57BL; Rats; Sequence Analysis, DNA; Sequence Homology, Nucleic Acid

Escherichia coli cells bearing mutA, a mutant glyV tRNA gene, express a recA-dependent error-prone DNA replication activity. - al Mamun, A A; Rahman, M S; Humayun, M Z (Mol Microbiol, 1999)
A base substitution mutation (mutA) in the Escherichia coli glyV tRNA gene potentiates asp --> gly mistranslation and confers a strong mutator phenotype that is SOS independent, but requires recA, recB and recC genes. Here, we demonstrate that mutA cells express an error-prone DNA polymerase by using an in vitro experimental system based on the conversion of phage M13 single-stranded viral DNA bearing a model mutagenic lesion to the double-stranded replicative form. Amplification of the newly synthesized strand followed by multiplex DNA sequence analysis revealed that mutation fixation at 3, N4-ethenocytosine (varepsilonC) was approximately 3% when the DNA was replicated by normal cell extracts, approximately 48% when replicated by mutA cell extracts and approximately 3% when replicated by mutA recA double mutant cell extracts, in complete agreement with previous in vivo results. Mutagenesis at undamaged DNA sites was significantly elevated by mutA cell-free extracts in the M13 lacZ(alpha) forward mutagenesis system. Neither polA (DNA polymerase I) nor polB (DNA polymerase II) genes are required for the mutA phenotype, suggesting that the phenotype is mediated through a modification of DNA polymerase III or the activation of a previously unidentified DNA polymerase. These findings define the major features of a novel mutagenic pathway and imply the existence of previously unrecognized links between translation, recombination and replication.
Keywords: Animals; Bacteriophage M13; Cytosine; DNA Polymerase III; DNA Replication; DNA, Single-Stranded; DNA, Viral; Escherichia coli; Escherichia coli Proteins; Exodeoxyribonuclease V; Exodeoxyribonucleases; Genes, Bacterial; Genotype; Mutation; Rec A Recombinases; RNA, Transfer, Gly; Sequence Analysis, DNA

Analysis of the quality and utility of random shotgun sequencing at low redundancies. - Bouck, J; Miller, W; Gorrell, J H; Donna M Muzny; Richard A Gibbs (Genome Res, 1998)
The currently favored approach for sequencing the human genome involves selecting representative large-insert clones (100-200 kb), randomly shearing this DNA to construct shotgun libraries, and then sequencing many different isolates from the library. This method, entitled directed random shotgun sequencing, requires highly redundant sequencing to obtain a complete and accurate finished consensus sequence. Recently it has been suggested that a rapidly generated lower redundancy sequence might be of use to the scientific community. Low-redundancy sequencing has been examined previously using simulated data sets. Here we utilize trace data from a number of projects submitted to GenBank to perform reconstruction experiments that mimic low-redundancy sequencing. These low-redundancy sequences have been examined for the completeness and quality of the consensus product, information content, and usefulness for interspecies comparisons. The data presented here suggest three different sequencing strategies, each with different utilities. (1) Nearly complete sequence data can be obtained by sequencing a random shotgun library at sixfold redundancy. This may therefore represent a good point to switch from a random to directed approach. (2) Sequencing can be performed with as little as twofold redundancy to find most of the information about exons, EST hits, and putative exon similarity matches. (3) To obtain contiguity of coding regions, sequencing at three- to fourfold redundancy would be appropriate. From these results, we suggest that a useful intermediate product for genome sequencing might be obtained by three- to fourfold redundancy. Such a product would allow a large amount of biologically useful data to be extracted while postponing the majority of work involved in producing a high quality consensus sequence.
Keywords: Animals; Contig Mapping; Expressed Sequence Tags; Gene Library; Genome, Human; Humans; Mice; Quality Control; Retrospective Studies; Sequence Analysis, DNA

A baboon (Papio hamadryas) with an isochromosome for the long arm of the X. - Moore, C M; Leland, M M; Brzyski, R G; McKeand, J; Witte, S M; Rogers, J (Cytogenet Cell Genet, 1998)
A 5.5-yr-old female baboon was evaluated for sexual immaturity. She was small for her age and had normal external female genitalia. However, she lacked cyclical perineal turgescence and displayed atypical coloration of the perineal skin. Laparoscopy revealed a small uterus and absence of both ovaries. Cytogenetic analysis revealed a 42,X,i(X)(q10) karyotype. DNA analysis using loci DXS1683, which maps to Xp22.1, and DXS297, which maps to Xq27.3, was consistent with inheritance of the normal X chromosome from the dam and formation of the isochromosome Xq from the paternal X.
Keywords: Animals; Estrus; Female; Infertility, Female; Karyotyping; Metacarpus; Papio; Radiography; Sex Chromosome Aberrations; X Chromosome

Comparative sequence analysis of a gene-rich cluster at human chromosome 12p13 and its syntenic region in mouse chromosome 6. - Ansari-Lari, M A; Oeltjen, J C; Schwartz, S; Zhang, Z; Donna M Muzny; Lu, J; Gorrell, J H; Chinault, A C; Belmont, J W; Miller, W; Richard A Gibbs (Genome Res, 1998)
The Human Genome Project has created a formidable challenge: the extraction of biological information from extensive amounts of raw sequence. With the increasing availability of genomic sequence from other species, one approach to extracting coding and regulatory element information is through cross-species sequence comparison. To assess the strengths and weaknesses of this methodology for large-scale sequence analysis, 227 kb of mouse sequence syntenic to a gene-rich cluster on human chromosome 12p13 was obtained. Primarily through percent identity plots (PIPs) of SIM comparative sequence alignments, the sequence of coding regions, putative alternative exons, conserved noncoding regions, and correlation in repetitive element insertions were easily determined. The analysis demonstrated that the number, order, and orientation of all 17 genes are conserved between the two species, whereas two human pseudogenes are absent in mouse. In addition, apart from MIRs, no direct correlation of distribution or position of the majority of repetitive elements between the two species is seen. Finally, in examining the synonymous and nonsynonymous substitution rates in the conserved genes, a large variation in nonsynonymous rates is observed indicating that the genes in this region are diverging at different rates. This study indicates the utility and strength of large-scale cross-species sequence comparisons in the extraction of biological information from raw sequence, especially when combined with other computational tools such as GRAIL and BLAST.
Keywords: Amino Acid Sequence; Animals; Chromosome Mapping; Chromosomes; Chromosomes, Human, Pair 12; Conserved Sequence; Humans; Mice; Molecular Sequence Data; Multigene Family; Repetitive Sequences, Nucleic Acid; Sequence Alignment; Sequence Analysis, DNA

Effect of disruption of a gene encoding an autolysin of Enterococcus faecalis OG1RF. - Xiang Qin; Singh, K V; Xu, Y; Weinstock, G M; Murray, B E (Antimicrob Agents Chemother, 1998)
A mutant (TX5127) of Enterococcus faecalis OG1RF was generated by disruption mutagenesis of a previously described autolysin gene. TX5127 formed longer chains (2 to 10 cells per chain) than wild-type OG1RF (mainly single cells) during growth in broth even though it had a growth rate similar to that of the parental strain as measured by turbidity and cell count. Autolysin activity, as defined by the ability to lyse heat-killed Micrococcus lysodeikticus cells, was absent in TX5127, while this activity was easily detectable in OG1RF. However, disruption of this autolysin gene did not block the ability of TX5127 to hydrolyze E. faecalis cell walls compared to that of OG1RF. The autolysis rate of cells of TX5127 in 10 mM sodium phosphate buffer (pH 6.8) was slower than that of wild-type OG1RF. TX5127 also showed a decreased rate of lysis in the presence of penicillin, as measured by changes in the turbidity of the culture during 24 h of incubation at 37 degrees C and a slightly decreased effect of penicillin as measured by time-kill curves. The virulence of TX5127 was similar to that of OG1RF in the mouse peritonitis model, indicating that the autolysin of E. faecalis is not important for infection in this model.
Keywords: Animals; Enterococcus faecalis; Female; Mice; Mice, Inbred ICR; Mutation; N-Acetylmuramoyl-L-alanine Amidase; Penicillins; Peritonitis; Virulence

Expression and regulation of kainate and AMPA receptors in the rat neural tube. - Steven E Scherer; Gallo, V (J Neurosci Res, 1998)
We analyzed the expression and regulation of glutamate receptor subunits in the rat neural tube (10 day embryos) and in cell cultures derived from this tissue. In the cultures, all cells were stained with antibodies against the neural progenitor marker nestin. More than 50% of the cells were also stained by the monoclonal antibodies LB1 or A2B5, which bind to neuronal and glial progenitors. Approximately 6% of the cells were stained with antibodies for the low affinity NGF receptor, a neural crest cell marker. A small percentage of cells differentiated to neurons or astrocytes, as determined by staining with anti-neurofilament and anti-GFAP antibodies, respectively. RT-PCR analysis of neural tube tissue and culture mRNAs demonstrated that the AMPA receptor subunits GluR3 and 4 and the kainate receptor subunits GluR6, 7, KA1 and KA2 were detectable at E10. The kainate receptor subunits GluR6 and KA2 were upregulated by culture conditions which stimulated cell differentiation, as determined by concomitant downregulation of nestin mRNA. Both in neural tube tissue and in cultured cells, GluR6 was 100% unedited. Finally, both GluR6 and KA2 proteins could be detected in subpopulations of neural progenitors and differentiated neurons. Our data indicate that kainate receptor genes are expressed in undifferentiated progenitor cells of the neural tube at E10, and are upregulated during neural cell differentiation.
Keywords: Animals; Cell Differentiation; Cells, Cultured; Central Nervous System; Embryo, Mammalian; Gene Expression Regulation, Developmental; Immunohistochemistry; Neurons; Rats; Receptors, AMPA; Receptors, Kainic Acid; Up-Regulation

Generation and testing of mutants of Enterococcus faecalis in a mouse peritonitis model. - Singh, K V; Xiang Qin; Weinstock, G M; Murray, B E (J Infect Dis, 1998)
A previously described mouse peritonitis model was used to study derivatives of Enterococcus faecalis strain OG1RF. The addition of sterile rat fecal extracts (SRFE) lowered the LD50 of OG1RF >10-fold. Hemolysin production caused a 35-fold lower LD50 and a much shorter survival, similar to previous results using a peritonitis model without SRFE. A purine (but not a pyrimidine) auxotroph was considerably less lethal than wild type; gelatinase mutants were also attenuated. A suicide vector was generated with an enterococcal selectable marker in order to disrupt a gene encoding an E. faecalis antigen; the resulting mutant was not attenuated despite a slower growth rate. In conclusion, this model allows attenuated mutants to be detected, corroborates prior reports that hemolysin is a virulence factor, and suggests a role for gelatinase in virulence of E. faecalis in mice; the attenuated purine auxotroph may provide a system for developing vectors for in vivo expression systems.
Keywords: Animals; Disease Models, Animal; Enterococcus faecalis; Feces; Female; Gelatinases; Gram-Positive Bacterial Infections; Hemolysin Proteins; Mice; Mutation; Peritonitis; Rats

The genomic organization of Isopeptidase T-3 (ISOT-3), a new member of the ubiquitin specific protease family (UBP). - Timms, K M; Ansari-Lari, M A; Morris, W; Brown, S N; Richard A Gibbs (Gene, 1998)
A novel Isopeptidase T gene (ISOT-3) has been identified on human mosome 3q26.2--q26.3. gene shows 67.3% nucleotide identity and 54.8% amino acid identity to n Isopeptidase (ISOT-1). Northern blot analysis has shown that ISOT-3 is highly essed in ovary and testes, low-level expression in six other tissues tested. In contrast, ISOT-1 is essed at high levels in brain, and there is no detectable expression in ovary. The exonic nization of these two genes highly conserved with only one variant intron position. Intron 15 in -3 is absent in ISOT-1, there is an alternate splice site at the same location. Although the --intron structure has been erved between the two genes, ISOT-3 has significantly larger intronic ons, and the overall of this gene is at least 90 kb compared to 15 kb for ISOT-1. These data suggest that both ISOT-1 and ISOT-3 have descended from a common ancestor. In addition, the low overall sequence identity and different expression patterns may reflect differences in substrate specificity.
Keywords: Amino Acid Sequence; Animals; Base Sequence; Carbon-Nitrogen Lyases; Chromosome Mapping; Chromosomes, Human, Pair 3; Consensus Sequence; DNA, Complementary; Exons; Female; Gene Library; Humans; Male; Mice; Molecular Sequence Data; Organ Specificity; Ovary; Polymerase Chain Reaction; Recombinant Proteins; Saccharomyces cerevisiae; Sequence Alignment; Sequence Homology, Amino Acid; Substrate Specificity; Testis; Ubiquitins

Autosomal dominant cerebellar ataxia (SCA6) associated with small polyglutamine expansions in the alpha 1A-voltage-dependent calcium channel. - Zhuchenko, O; Bailey, J; Bonnen, P; Ashizawa, T; Stockton, D W; Amos, C; Dobyns, W B; Subramony, S H; Zoghbi, H Y; Lee, C C (Nat Genet, 1997)
A polymorphic CAG repeat was identified in the human alpha 1A voltage-dependent calcium channel subunit. To test the hypothesis that expansion of this CAG repeat could be the cause of an inherited progressive ataxia, we genotyped a large number of unrelated controls and ataxia patients. Eight unrelated patients with late onset ataxia had alleles with larger repeat numbers (21-27) compared to the number of repeats (4-16) in 475 non-ataxia individuals. Analysis of the repeat length in families of the affected individuals revealed that the expansion segregated with the phenotype in every patient. We identified six isoforms of the human alpha 1A calcium channel subunit. The CAG repeat is within the open reading frame and is predicted to encode glutamine in three of the isoforms. We conclude that a small polyglutamine expansion in the human alpha 1A calcium channel is most likely the cause of a newly classified autosomal dominant spinocerebellar ataxia, SCA6.
Keywords: Alleles; Amino Acid Sequence; Animals; Calcium Channels; Cerebellar Ataxia; Female; Genes, Dominant; Genotype; Humans; Male; Molecular Sequence Data; Mutation; Nerve Tissue Proteins; Pedigree; Peptides; Rabbits; Sequence Homology, Amino Acid; Trinucleotide Repeats

Baboons as an animal model for genetic studies of common human disease. - Rogers, J; Hixson, J E (Am J Hum Genet, 1997)
Keywords: Animals; Arteriosclerosis; Chromosome Mapping; Disease Models, Animal; Genetic Diseases, Inborn; Humans; Models, Genetic; Osteoporosis; Papio

Beyond one gene-one disease: alternative strategies for deciphering genetic determinants of osteoporosis. - Rogers, J; Mahaney, M C; Beamer, W G; Donahue, L R; Rosen, C J (Calcif Tissue Int, 1997)
Keywords: Animals; Bone and Bones; Bone Density; Chromosome Mapping; Disease Models, Animal; Humans; Osteoporosis; Papio; Pedigree; Point Mutation; Risk Factors

Growth factor-induced transcription of GluR1 increases functional AMPA receptor density in glial progenitor cells. - Chew, L J; Fleck, M W; Wright, P; Scherer, S E; Mayer, M L; Gallo, V (J Neurosci, 1997)
We analyzed the effects of two growth factors that regulate oligodendrocyte progenitor (O-2A) development on the expression of glutamate receptor (GluR) subunits in cortical O-2A cells. In the absence of growth factors, GluR1 was the AMPA subunit mRNA expressed at the lowest relative level. Basic fibroblast growth factor (bFGF) caused an increase in GluR1 and GluR3 steady-state mRNA levels. Platelet-derived growth factor (PDGF) did not modify the mRNA levels for any of the AMPA subunits but selectively potentiated the effects of bFGF on GluR1 mRNA (4.5-fold increase). The kainate-preferring subunits GluR7, KA1, and KA2 mRNAs were increased by bFGF, but these effects were not modified by cotreatment with PDGF. Nuclear run-on assays demonstrated that PDGF+bFGF selectively increased the rate of GluR1 gene transcription (2.5-fold over control). Western blot analysis showed that GluR1 protein levels were increased selectively (sixfold over control) by PDGF+bFGF. Functional expression was assessed by rapid application of AMPA to cultured cells. AMPA receptor current densities (pA/pF) were increased nearly fivefold in cells treated with PDGF+bFGF, as compared with untreated cells. Further, AMPA receptor channels in cells treated with PDGF+bFGF were more sensitive to voltage-dependent block by intracellular polyamines, as expected from the robust and selective enhancement of GluR1 expression. Our combined molecular and electrophysiological findings indicate that AMPA receptor function can be regulated by growth factor-induced changes in the rate of gene transcription.
Keywords: Animals; Cell Division; Drug Combinations; Fibroblast Growth Factor 2; Growth Substances; Neuroglia; Oligodendroglia; Platelet-Derived Growth Factor; Rats; Rats, Sprague-Dawley; Receptors, AMPA; Receptors, Glutamate; RNA, Messenger; Stem Cells; Time Factors; Transcription, Genetic

Isolation and characterization of the platelet-derived growth factor beta receptor promoter. - Shinbrot, E; Liao, X; Williams, L T (Dev Dyn, 1997)
The PDGFbeta r gene has been implicated in many physiological processes including development and wound healing. Aberrant expression of the receptor is seen in many pathological conditions such as atherosclerosis and inflammatory diseases. To study the mechanisms of PDGFbeta r regulation, we identified the regulatory regions of the gene. We have cloned and characterized the promoter region of the platelet-derived growth factor beta receptor (PDGFbeta r). We isolated a 4.5 Kb genomic fragment which confers PDGFbeta r tissue-specific promoter activity. This fragment can direct transcription of a luciferase reporter gene in a cell-specific manner which correlates well with the known pattern of expression of the PDGFbeta r. The specificity of this clone was demonstrated by its high activity in NIH 3T3 fibroblasts and lack of activity in N-MUNG epithelial cells, a pattern that parallels the expression of the endogenous PDGFbeta r. We have defined a 614 bp region encompassing the 5' untranslated region of the gene which includes the basal promoter region. We generated transgenic mice that carry the chloramphenicol acetyltransferase (CAT) reporter gene under the control of the 4.5 Kb promoter. The expression pattern of the reporter gene was compared to that of the endogenous PDGFbeta r gene. The promoter was able to direct reporter gene expression with the same temporal and spatial pattern as the endogenous PDGFbeta r. The most prominent expression was in condensing mesenchyme of developing blood vessels, bone and tissues adjacent to epithelium. We conclude that this clone contains the regulatory regions sufficient to direct expression of the PDGFbeta r. The further analysis of this promoter will help elucidate the transcriptional regulation of expression of the PDGFbeta r, and provide a useful tool for directing expression of heterologous genes.
Keywords: 3T3 Cells; Animals; Bone Development; Chloramphenicol O-Acetyltransferase; Choroid Plexus; Clone Cells; Endothelium, Vascular; Female; Gene Deletion; Genes, Reporter; Luciferases; Mesoderm; Mice; Mice, Transgenic; Promoter Regions, Genetic; Receptors, Platelet-Derived Growth Factor; Transgenes

Large-scale comparative sequence analysis of the human and murine Bruton's tyrosine kinase loci reveals conserved regulatory domains. - Oeltjen, J C; Malley, T M; Donna M Muzny; Miller, W; Richard A Gibbs; Belmont, J W (Genome Res, 1997)
Large-scale genomic DNA sequencing of orthologous and paralogous loci in different species should contribute to a basic understanding of the evolution of both the protein-coding regions and noncoding regulatory elements. We compared 93 kb of human sequence to 89 kb of mouse sequence in the Bruton's tyrosine kinase (BTK) region. In addition to showing the conservation of both position and orientation of the five functionally unrelated genes in the region (BTK, alpha-D-galactosidase A, L44L, FTP-3, and FCI-12), the comparison revealed conservation of clusters of noncoding sequence flanking the first exon of each gene. Furthermore, in the sequence comparison at the BTK locus, the conservation of clusters of noncoding sequence extends throughout the locus; the noncoding sequence is more highly conserved in the BTK locus in comparison to the flanking loci. This suggests a correlation with the complex developmental regulation of expression of btk. To determine whether a highly conserved 3.5-kb segment flanking the first exon of BTK contains transcriptional regulatory signals, we tested various portions of the segment for promoter and expression activity in several appropriate cell lines. The results demonstrate the contribution of the conserved region flanking the first exon to the cell lineage-specific expression pattern of btk. These data show the usefulness of large scale sequence comparisons to focus investigation on regions of noncoding sequence that play essential roles in complex gene regulation.
Keywords: Agammaglobulinaemia Tyrosine Kinase; alpha-Galactosidase; Animals; Base Sequence; Conserved Sequence; Enhancer Elements, Genetic; Genetic Variation; Humans; Mice; Models, Genetic; Molecular Sequence Data; Promoter Regions, Genetic; Protein-Tyrosine Kinases; Recombinant Proteins; Regulatory Sequences, Nucleic Acid; Repetitive Sequences, Nucleic Acid; Sequence Alignment; Sequence Analysis, DNA; Sequence Homology, Nucleic Acid; Transcription Factors; Transcription, Genetic; Transfection

Simian T-lymphotropic virus type 1 (STLV-1) infection in wild yellow baboons (Papio hamadryas cynocephalus) from Mikumi National Park, Tanzania. - Voevodin, A; Samilchuk, E; Allan, J; Rogers, J; Broussard, S (Virology, 1997)
Serum and peripheral blood leukocytes from wild yellow baboons (Papio hamadryas cynocephalus) were tested for the presence of STLV-1-specific antibodies and proviral DNA. Fourteen of 30 sera tested positive by radioimmunoprecipitation assay (RIPA) with HTLV-1. Among 36 DNA samples tested by PCR 15 were positive by double nested PCR for a fragment of the STLV-1 env gene, the most sensitive assay among PCR tests employed. Of 30 animals that were tested both serologically and by PCR in only 1 case were the results discordant (PCR-positive, antibody-negative). The DNA sequences from env (378 bp), pol (212 bp), and LTR (705 bp) were determined for 5, 5, and 2 Mikumi STLV-1 isolates, respectively. The DNA sequences of Mikumi STLV-1 isolates were virtually identical and phylogenetic analysis revealed that they were clearly distinct from previously published baboon STLV-1 sequences, including those STLV-1 isolates presumed to be from yellow baboons. The results of this study suggest that reliable placement of individual STLV-1 within the PTLV-1 phylogeny requires genomic sequences of STLV-1 isolates from wild animals whose taxonomic identity and geographical origin are firmly established and that the LTR is the genomic region of STLV-1 which is the most informative for cladistic analysis of these viruses.
Keywords: Animals; Base Sequence; Deltaretrovirus Antibodies; Deltaretrovirus Infections; DNA, Viral; Gene Products, env; Gene Products, pol; Genome, Viral; Humans; Molecular Sequence Data; Monkey Diseases; Papio; Phylogeny; Polymerase Chain Reaction; Repetitive Sequences, Nucleic Acid; Sequence Homology, Nucleic Acid; Simian T-lymphotropic virus 1; Tanzania; Tumor Cells, Cultured

Simultaneous shotgun sequencing of multiple cDNA clones. - Andersson, B; Lu, J; Shen, Y; Wentland, M A; Richard A Gibbs (DNA Seq, 1997)
This study describes an efficient method for the rapid sequencing of DNA fragments in the size range 1-5 kb. Individual fragments, here cDNA inserts, are purified by restriction enzyme digestion and gel purification, pooled and concatenated by ligation. The concatamers are sheared and cloned randomly into M13, followed by random sequencing. The sequences of the individual cDNA inserts are obtained at the assembly stage using restriction enzyme sites as "tags' for the ends of each fragment. In this study the sequencing of two libraries containing 7 and 16 cDNA inserts with an average length of 2.5 kb is described. The results show that of the shotgun sequencing of large fragments, and that the method compares favorably to alternative strategies, such as primer walking.
Keywords: Animals; Cloning, Molecular; DNA, Complementary; Drosophila; Gene Expression; Gene Library; Restriction Mapping; Sequence Analysis, DNA

BCM Search Launcher--an integrated interface to molecular biology data base search and analysis services available on the World Wide Web. - Smith, R F; Wiese, B A; Wojzynski, M K; Davison, D B; Kim C Worley (Genome Res, 1996)
The BCM Search Launcher is an integrated set of World Wide Web (WWW) pages that organize molecular biology-related search and analysis services available on the WWW by function, and provide a single point of entry for related searches. The Protein Sequence Search Page, for example, provides a single sequence entry form for submitting sequences to WWW servers that offer remote access to a variety of different protein sequence search tools, including BLAST, FASTA, Smith-Waterman, BEAUTY, PROSITE, and BLOCKS searches. Other Launch pages provide access to (1) nucleic acid sequence searches, (2) multiple and pair-wise sequence alignments, (3) gene feature searches, (4) protein secondary structure prediction, and (5) miscellaneous sequence utilities (e.g., six-frame translation). The BCM Search Launcher also provides a mechanism to extend the utility of other WWW services by adding supplementary hypertext links to results returned by remote servers. For example, links to the NCBI's Entrez data base and to the Sequence Retrieval System (SRS) are added to search results returned by the NCBI's WWW BLAST server. These links provide easy access to auxiliary information, such as Medline abstracts, that can be extremely helpful when analyzing BLAST data base hits. For new or infrequent users of sequence data base search tools, we have preset the default search parameters to provide the most informative first-pass sequence analysis possible. We have also developed a batch client interface for Unix and Macintosh computers that allows multiple input sequences to be searched automatically as a background task, with the results returned as individual HTML documents directly to the user's system. The BCM Search Launcher and batch client are available on the WWW at URL http:@gc.bcm.tmc.edu:8088/search-launcher.html.
Keywords: Animals; Computer Communication Networks; Database Management Systems; Databases, Factual; Humans; Molecular Biology

A comparative transcription map of the murine bare patches (Bpa) and striated (Str) critical regions and human Xq28. - Levin, M L; Chatterjee, A; Pragliola, A; Kim C Worley; Wehnert, M; Zhuchenko, O; Smith, R F; Lee, C C; Herman, G E (Genome Res, 1996)
The X-linked developmental mouse mutations bare patches (Bpa) and striated (Str) may be homologous to human X-linked dominant chondrodysplasia punctata (CDPX2) and incontinentia pigmenti (IP2), respectively, based on their genetic mapping and clinical phenotypes. Bpa and Str have been localized to an overlapping critical region of 600 kb that demonstrates conserved gene order with loci in human Xq28 between DXS1104 and DXS52. As part of efforts to isolate the genes involved in these disorders, we have begun to develop a comparative transcription map spanning this region in both species. Using techniques of cross-species conservation and hybridization, exon trapping, and cDNA selection we have identified four known genes or members of gene families--caltractin, a member of the gamma-aminobutyric acid (GABAA) receptor gene family, a member of the melanoma antigen gene (MAGE) family, and several members of the murine-specific, X-linked lymphocyte regulated gene (Xlr3) family. Trapped exons and, in some cases, longer cDNAs have been isolated for potentially 7-9 additional genes. One cDNA demonstrates highly significant homology with members of the Krüppel family of zinc finger transcription factors. A second novel cDNA demonstrates homology at the 3' end of the predicted amino acid sequence to a LIM domain consensus. Gene order appears conserved among those cDNAs determined to be present in both human and mouse. Three of the murine transcripts appear to be present in multiple copies within the Bpa/Str critical region and could be associated with a predisposition to genomic rearrangements. Reverse transcriptase PCR (RT-PCR) and Northern analysis demonstrate that several of the transcripts are expressed in mid-gestation murine embryos and neonatal skin, making them candidates for the Bpa and Str mutations and their respective homologous human disorders.
Keywords: Amino Acid Sequence; Animals; Base Sequence; Blotting, Northern; Blotting, Southern; Chondrodysplasia Punctata; Chromosome Mapping; Cloning, Molecular; DNA, Complementary; Exons; Genetic Markers; Humans; Incontinentia Pigmenti; Mice; Molecular Sequence Data; Restriction Mapping; Sequence Analysis; Sequence Homology, Amino Acid; X Chromosome; Zinc Fingers

Conservation of human chromosome 18 in baboons (Papio hamadryas): a linkage map of eight human microsatellites. - Perelygin, A A; Kammerer, C M; Stowell, N C; Rogers, J (Cytogenet Cell Genet, 1996)
A panel of 25 microsatellite loci known to map to human chromosome 18 was screened for length polymorphisms in a multigenerational pedigree of baboons (Papio hamadryas). Eight of these loci were polymorphic in the baboon pedigrees, with observed heterozygosity values ranging from 0.16 to 0.88. All eight loci show strong evidence of linkage. The most likely map order among the microsatellite loci for Papio is completely compatible with the locus order found in the human genome, and sex differences in recombination rates are also similar in the two species. We conclude that the organization of the chromosomal region defined by these loci is largely conserved between baboons and humans.
Keywords: Animals; Chromosomes, Human, Pair 18; Evolution, Molecular; Female; Hominidae; Humans; Lod Score; Male; Microsatellite Repeats; Papio; Pedigree; Phylogeny; Polymerase Chain Reaction; Recombination, Genetic; Species Specificity

Duplication of a gene-rich cluster between 16p11.1 and Xq28: a novel pericentromeric-directed mechanism for paralogous genome evolution. - Eichler, E E; Lu, F; Shen, Y; Antonacci, R; Jurecic, V; Doggett, N A; Moyzis, R K; Baldini, A; Richard A Gibbs; Nelson, D L (Hum Mol Genet, 1996)
We have identified a 26.5 kb gene-rich duplication shared by human Xq28 and 16p11.1. Complete comparative sequence analysis of cosmids from both loci has revealed identical Xq28 and 16p11.1 genomic structures for both the human creatine transporter gene (SLC6A8) and five exons of the CDM gene (DXS1357E). Overall nucleotide similarity within the duplication was found to be 94.6%, suggesting that this interchromosomal duplication occurred within recent evolutionary time (7-10 mya). Based on comparisons between genomic and cDNA sequence, both the Xq28 creatine transporter and DXS1357E genes are transcriptionally active. Predicted translation of exons and RT-PCR analysis reveal that chromosome 16 paralogs likely represent pseudogenes. Comparative fluorescent in situ hybridization (FISH) analyses of chromosomes from various primates indicate that this gene-rich segment has undergone several duplications. In gorilla and chimpanzee, multiple pericentromeric localizations on a variety of chromosomes were found using probes from the duplicated region. In other species, such as the orangutan and gibbon, FISH signals were only identified at the distal end of the X chromosome, suggesting that the Xq28 locus represents the ancestral copy. Sequencing of the 16p 11.1/Xq28 duplication breakpoints has revealed the presence of repetitive immunoglobulin-like CAGGG pentamer sequences at or near the paralogy boundaries. The mobilization and dispersal of this gene-rich 27 kb element to the pericentromeric regions of primate chromosomes defines an unprecedented form of recent genome evolution and a novel mechanism for the generation of genetic diversity among closely related species.
Keywords: Animals; Base Sequence; Carrier Proteins; Centromere; Chromosome Mapping; Chromosomes, Human, Pair 16; Cosmids; Creatine; Evolution, Molecular; Exons; Hominidae; Humans; Hylobates; Membrane Proteins; Membrane Transport Proteins; Models, Genetic; Molecular Sequence Data; Multigene Family; Proteins; Repetitive Sequences, Nucleic Acid; Sequence Analysis, DNA; Sequence Homology, Nucleic Acid; X Chromosome

Genomic organization of the mouse double minute 2 gene. - Jones, S N; Ansari-Lari, M A; Hancock, A R; Jones, W J; Richard A Gibbs; Donehower, L A; Bradley, A (Gene, 1996)
Transfection of the mouse double minute 2 (Mdm2) oncogene has been found to induce immortalization of primary cells and to transform cultured cells. Amplification and/or overexpression of human MDM2 has been documented in a large percentage of human cancers. Mouse and human Mdm2 cDNA have been cloned from transformed cells and the cDNA sequence of both genes have been reported previously. In this report, we present the gene structure of mouse Mdm2. Comparison of the coding sequences of the Mdm2 gene with the previously reported cDNA sequence and with Mdm2 sequences obtained from an Mdm2-bearing cosmid clone capable of inducing transformation revealed that the reported cDNA sequence was in error, and that Mdm2-induced transformation of cells does not require an activating mutation in Mdm2. Ligation-anchor PCR analysis of transcripts produced from the P1 and P2 promoters indicates that transcription initiates at sites upstream of those reported previously for both promoters.
Keywords: Amino Acid Sequence; Animals; Base Sequence; Genome; Mice; Molecular Sequence Data; Nuclear Proteins; Promoter Regions, Genetic; Proto-Oncogene Proteins; Proto-Oncogene Proteins c-mdm2; Proto-Oncogenes; Transcription, Genetic

Improved ligation-anchored PCR strategy for identification of 5' ends of transcripts. - Ansari-Lari, M A; Jones, S N; Timms, K M; Richard A Gibbs (Biotechniques, 1996)
Keywords: Alternative Splicing; Animals; Bacteriophage T4; Biotin; DNA Primers; DNA, Complementary; Exons; Humans; Mice; Nuclear Proteins; Polymerase Chain Reaction; Proto-Oncogene Proteins; Proto-Oncogene Proteins c-mdm2; RNA Ligase (ATP); RNA, Messenger; Thiolester Hydrolases; Ubiquitin Thiolesterase

Potential salmon sperm origin of the E3 region insert of the adenovirus 5 dl309 mutant. - Marie-Claude Gingras; Arevalo, P; Aguilar-Cordova, E (Cancer Gene Ther, 1996)
The plasmid pJM17 is a commonly used adenoviral backbone derived from the dl309 mutant virus. It contains unknown sequences inserted in the E3 region during construction of the dl309 mutant. Complete description of the backbone sequence is required for interpretation of potential vector effects and for regulatory approval of a vector to be used in clinical trials. The anonymous E3 insert was sequenced and analyzed. The insert fragment is 646 base pairs (bp) long and is 100 bp shorter than the vector sequences it replaces. It interrupts the expression of the E3B 10.4K, 14.6K, and 14.7K genes, but not the E3A glycoprotein (gp) 19K gene. Sequence analysis and Southern blotting suggest that the insert might originate from salmon sperm DNA used as carrier during the construction of dl309. Transcription from the insert was not detected by Northern blot analysis of vector-transduced cells but was detected by reverse transcriptase polymerase chain reaction.
Keywords: Adenovirus E3 Proteins; Adenoviruses, Human; Animals; Avian Sarcoma Viruses; Base Sequence; DNA; DNA Primers; Genetic Vectors; HeLa Cells; Humans; Male; Molecular Sequence Data; Plasmids; Polymerase Chain Reaction; Prolactin; Proton-Translocating ATPases; Repetitive Sequences, Nucleic Acid; Salmon; Sequence Homology, Nucleic Acid; Spermatozoa; Thymidine Kinase; Transfection

Identification of new members of a carbohydrate kinase-encoding gene family. - Kim C Worley; King, K Y; Chua, S; McCabe, E R; Smith, R F (J Comput Biol, 1995)
In a sequence database search using the human glycerol kinase-encoding sequence (HUMGLYKINB) as a query, we identified six previously unidentified carbohydrate kinase sequences. Five of the six newly identified sequences appear to be known types of carbohydrate kinases, four are glycerol kinases and one is a gluconokinase. The sixth newly identified sequence, the Caenorhabditis elegans gene, CER08D7.7-CEF59B2.1, shows similarity to the family of carbohydrate kinases including other glycerol kinases, xylulokinases, gluconokinases, ribulokinases, rhamnulokinases, and fucokinases. A phylogenetic comparison of this newly identified Caenorhabditis elegans gene with the other members of the carbohydrate kinase family demonstrated that this sequence cannot be assigned to one of the known classes of carbohydrate kinases.
Keywords: Amino Acid Sequence; Animals; Caenorhabditis elegans; Carbohydrates; Conserved Sequence; Databases, Factual; Genes, Helminth; Glucokinase; Glycerol Kinase; Humans; Molecular Sequence Data; Multigene Family; Phosphotransferases (Alcohol Group Acceptor); Phylogeny; Sequence Alignment; Sequence Homology, Amino Acid; Software

Linkage mapping in Papio baboons: conservation of a syntenic group of six markers on human chromosome 1. - Rogers, J; Witte, S M; Kammerer, C M; Hixson, J E; MacCluer, J W (Genomics, 1995)
We have established multipoint genetic linkage among six loci in baboons (Papio hamadryas). Published PCR primers designed to amplify five human microsatellite loci were used to amplify homologous loci in 229 pedigreed baboons. Southern blotting was used to type two RFLPs in a functional gene (anti-thrombin III) in a subset of those animals. All six loci are known to map to human chromosome 1q, a region of the genome predicted by karyotype studies to be conserved in baboons. Pairwise recombination frequencies and lod scores indicate that the six loci are also linked in baboons. Recombination distances among the loci are similar to those reported for humans. Like humans, the baboons exhibit higher rates of recombination in females than in males. This study demonstrates that (1) microsatellite loci first described and characterized in the human genome can be effectively used for genetic linkage mapping in non-human primates, (2) a group of genetic loci known to be linked on human chromosome 1q are also linked in the baboon genome, and (3) sex differences in recombination frequencies among loci on human chromosome 1q are also observed in the genome of this Old World monkey. This constitutes the first reported multipoint linkage map in any nonhuman primate.
Keywords: Animals; Antithrombin III; Chromosome Mapping; Evolution, Molecular; Female; Genes; Genetic Linkage; Genetic Markers; Humans; Male; Microsatellite Repeats; Papio; Polymorphism, Restriction Fragment Length; Recombination, Genetic; Species Specificity

Pressing ahead with human genome sequencing. - Richard A Gibbs (Nat Genet, 1995)
While waiting for revolutionary techniques to emerge, conventional approaches have been used to generate more than 40 million bases of DNA sequence from large scale projects involving different organisms. About eight megabases are from the human genome. Does this progress signal the time to move ahead for a massive human genomic sequencing effort, or should we bide our time, waiting for more technical developments? The answer is to move ahead now, choosing carefully those strategies that can be easily adapted to future methodologies.
Keywords: Animals; Base Sequence; Caenorhabditis; DNA; Genome, Fungal; Genome, Human; Human Genome Project; Humans; Molecular Sequence Data; Saccharomyces cerevisiae

Variability of dopamine D4 receptor (DRD4) gene sequence within and among nonhuman primate species. - Livak, K J; Rogers, J; Lichter, J B (Proc Natl Acad Sci U S A, 1995)
The dopamine D4 receptor is one of five receptors known to function in mammalian dopaminergic pathways. The DNA sequence of the human dopamine D4 receptor gene (DRD4) has previously been investigated in several populations and found to be highly polymorphic at both the DNA and amino acid levels, exhibiting at least 25 alleles. This variation results from differences in the number and DNA sequence of a 48-bp (16-amino acid) repeat unit in the coding region of DRD4. In the present study, DRD4 DNA sequence was examined in at least two individuals from each of five nonhuman primate species. All five species exhibit intraspecies variability, including both single nucleotide substitutions and variation in the number of 48-bp repeat units. No differences were found between the two alleles of one individual from a sixth nonhuman species. Within each species, all of the DRD4 alleles share species-specific features, indicating that while repeat-unit variation is nearly ubiquitous, ancestral variation has been lost and subsequently regenerated in each of the evolutionary lineages studied. Chimpanzees and gorillas share a unique 12-bp deletion in the coding region of DRD4, outside the repeat-unit segment of the gene. This suggest that the extant chimpanzee DRD4 is more closely related to the gorilla DRD4 than either is to the human DRD4.
Keywords: Alleles; Amino Acid Sequence; Animals; Base Sequence; Codon; Genetic Variation; Gorilla gorilla; Hominidae; Molecular Sequence Data; Pan troglodytes; Papio; Phylogeny; Pongo pygmaeus; Receptors, Dopamine; Receptors, Dopamine D2; Receptors, Dopamine D4; Repetitive Sequences, Nucleic Acid; Saimiri; Sequence Deletion; Sequence Homology, Nucleic Acid; Species Specificity

When is ancient polymorphism a potential problem for molecular phylogenetics? - Rogers, J; Comuzzie, A G (Am J Phys Anthropol, 1995)
Keywords: Animals; Biological Evolution; DNA; DNA, Mitochondrial; Humans; Molecular Biology; Phylogeny; Polymorphism, Genetic; Primates; Sequence Homology, Nucleic Acid; Species Specificity

Expression of the platelet-derived growth factor beta receptor during organogenesis and tissue differentiation in the mouse embryo. - Shinbrot, E; Peters, K G; Williams, L T (Dev Dyn, 1994)
In this study we used in situ hybridization to localize expression of the platelet-derived growth factor beta (PDGF beta) receptor mRNA during organogenesis in the mouse embryo (E 9.5-16.5). Expression was first seen in periaortic mesenchyme (E 9.5-10.5). Later (E 12.5-E 16.5), the receptor was expressed in the mesenchymal component of many developing tissues and organs, particularly derivatives of the primitive gut. The expression was exceptionally high in mesenchyme directly supporting an epithelium, typical of many developing organs such as the trachea and intestine. However, as the mesenchyme differentiated into smooth muscle, PDGF beta receptor mRNA was no longer detected. The expression of the PDGF beta receptor mRNA in mesenchymal components of developing organs, along with its absence in epithelial tissues, indicates that it may play a role in mesenchymal-epithelial interactions during organ development. Somewhat unexpectedly, the PDGF beta receptor was highly expressed in the endothelium of small blood vessels and vascular structures such as the hyaloid plexus and choroid plexus. In large blood vessels, PDGF beta receptor mRNA was found in the mesenchyme surrounding the endothelium. This suggests that the PDGF beta receptor is involved in growth and development of blood vessels.
Keywords: Animals; Blood Vessels; Bone and Bones; Bone Development; Cell Differentiation; DNA; Embryo, Mammalian; Embryonic and Fetal Development; Immunohistochemistry; In Situ Hybridization; Mesoderm; Mice; Myocardium; Receptors, Platelet-Derived Growth Factor; RNA, Messenger

Infection of a yellow baboon with simian immunodeficiency virus from African green monkeys: evidence for cross-species transmission in the wild. - Jin, M J; Rogers, J; Phillips-Conroy, J E; Allan, J S; Desrosiers, R C; Shaw, G M; Sharp, P M; Hahn, B H (J Virol, 1994)
Many African primates are known to be naturally infected with simian immunodeficiency viruses (SIVs), but only a fraction of these viruses has been molecularly characterized. One primate species for which only serological evidence of SIV infection has been reported is the yellow baboon (Papio hamadryas cynocephalus). Two wild-living baboons with strong SIVAGM seroreactivity were previously identified in a Tanzanian national park where baboons and African green monkeys shared the same habitat (T. Kodama, D. P. Silva, M. D. Daniel, J. E. Phillips-Conroy, C. J. Jolly, J. Rogers, and R. C. Desrosiers, AIDS Res. Hum. Retroviruses 5:337-343, 1989). To determine the genetic identity of the viruses infecting these animals, we used PCR to examine SIV sequences directly in uncultured leukocyte DNA. Targeting two different, nonoverlapping genomic regions, we amplified and sequenced a 673-bp gag gene fragment and a 908-bp env gene fragment from one of the two baboons. Phylo-genetic analyses revealed that this baboon was infected with an SIVAGM strain of the vervet subtype. These results provide the first direct evidence for simian-to-simian cross-species transmission of SIV in the wild.
Keywords: Amino Acid Sequence; Animals; Animals, Wild; Base Sequence; Chlorocebus aethiops; DNA Primers; DNA, Viral; Female; Genes, env; Genes, gag; Genome, Viral; HIV Envelope Protein gp120; Infectious Disease Transmission, Vertical; Leukocytes; Membrane Glycoproteins; Molecular Sequence Data; Papio; Phylogeny; Polymerase Chain Reaction; Retroviridae Proteins; Sequence Homology, Amino Acid; Simian Acquired Immunodeficiency Syndrome; Simian Immunodeficiency Virus; Viral Envelope Proteins

Levels of the genealogical hierarchy and the problem of hominoid phylogeny. - Rogers, J (Am J Phys Anthropol, 1994)
Molecular data are widely used to reconstruct phylogenetic relationships among species, and these phylogenies are often used as the basis for inferences about the history of evolutionary change in other nonmolecular characters. This approach is an appropriate and powerful one in many circumstances. But when several lineages diverge over a relatively short period of time, the assumption that a molecular (gene) tree will always be a valid basis for such inferences may not hold. Empirical evidence from humans, nonhuman primates, and other mammals indicates that the relationships among molecular divergence, morphological differentiation, and the origin of reproductive isolation between diverging lineages are complex. The simple dichotomously branching trees that result from molecular systematic studies of Homo, Gorilla, and Pan may be a misleading basis for reconstructions of evolutionary change in nonmolecular characters.
Keywords: Animals; Genetic Variation; Hominidae; Humans; Phylogeny; Sequence Analysis, DNA

Multiplex PCR: advantages, development, and applications. - Edwards, M C; Richard A Gibbs (PCR Methods Appl, 1994)
Keywords: Animals; Bacteria; Gene Deletion; Humans; Mutation; Polymerase Chain Reaction; Polymorphism, Genetic; Repetitive Sequences, Nucleic Acid; Templates, Genetic; Viruses

Multiple cDNA sequences of bovine tracheal lysozyme. - Takeuchi, K; Irwin, D M; Gallup, M; Shinbrot, E; Kai, H; Stewart, C B; Basbaum, C (J Biol Chem, 1993)
The principal role of lysozyme is to prevent bacterial invasion at body surfaces. We are interested in how lysozyme is regulated at the surface of the respiratory tract, where the serous gland cell is regarded as the primary cellular source of this enzyme. Since the cow genome contains at least 10 lysozyme-like genes, our objective was to determine which of them are expressed in the cow tracheal gland serous cell. By screening tracheal cDNA libraries with a probe constructed from the cDNA encoding stomach lysozyme 2, we obtained 3 lysozyme cDNAs: 5a (1023 base pairs (bp)), 7a (1060 bp), and 14d (1249 bp). cDNA 7a corresponds to a previously reported gene (showing sequence identity to the stomach 2 lysozyme gene), whereas cDNAs 5a and 14d correspond to lysozyme genes not previously reported. Northern blot analysis of cow tracheal RNA showed lysozyme mRNAs of three distinct lengths. Based on hybridization with probes specific for each cDNA, we determined that the longest transcript corresponded to cDNA 5a, the shortest to 7a, and the intermediate-length transcript to 14d. Cultured cow tracheal gland serous cell RNA, reverse transcribed and amplified by the polymerase chain reaction with primers common to all three cDNAs, yielded a product that hybridized to oligonucleotide probes specific for all three cDNAs but most strongly to that for 5a. These results indicate that multiple lysozyme mRNAs are expressed in the cow trachea and that the lysozyme encoded by cDNA 5a is the major form expressed in the tracheal gland serous cell. This serous cell lysozyme is predicted to differ importantly in structure from both 7a and 14d lysozymes, with an arginine:lysine ratio almost 10-fold higher. The sequence differences may underlie functional differences, including variable resistance to proteolysis and variable affinity for large polyanions (e.g. mucins) found in the respiratory tract lumen.
Keywords: Amino Acid Sequence; Animals; Base Sequence; Blotting, Southern; Cattle; Cells, Cultured; DNA Primers; DNA, Complementary; Electrophoresis, Polyacrylamide Gel; Molecular Sequence Data; Muramidase; Polymerase Chain Reaction; Sequence Homology, Amino Acid; Sequence Homology, Nucleic Acid; Trachea

Multiplex DNA amplification and solid-phase direct sequencing for mutation analysis at the hprt locus in Chinese hamster cells. - Zu, Z; Yu, Y; Richard A Gibbs; Caskey, C T; Hsie, A W (Mutat Res, 1993)
We report here the development of multiplex in vitro DNA amplification and solid-phase direct exon sequencing for the analysis of mutations at the hypoxanthine-guanine phosphoribosyltransferase (hprt) locus in Chinese hamster cells. 18 representative HPRT-deficient mutants, derived either spontaneously, or after exposure to UV light or ionizing radiation, were analyzed. All 9 hprt exons were simultaneously amplified via the polymerase chain reaction (PCR) for rapid deletion detection. 5 mutants involve single- or multiple-exon deletions. Altered multiplex PCR patterns were detected in mutants Bsp-040, Bsp-065 and BGR-606. Subsequent direct sequence analysis reveals that Bsp-040 and Bsp-065 carry a 52-bp and a 13-bp intragenic DNA deletion in exon 3, respectively. BGR-606 contains a 223-bp insertion accompanied by a 10-bp deletion of intron sequence within exon 4 fragment. Other subtle DNA alterations identified by direct exon sequence analysis include single-base substitutions, small deletions and insertions, and RNA splicing mutations.
Keywords: Animals; Base Sequence; CHO Cells; Chromosome Mapping; Cricetinae; DNA Mutational Analysis; Hypoxanthine Phosphoribosyltransferase; Molecular Sequence Data; Mutation; Polymerase Chain Reaction; Sequence Analysis, DNA

Nuclear DNA polymorphisms in a wild population of yellow baboons (Papio hamadryas cynocephalus) from Mikumi National Park, Tanzania. - Rogers, J; Kidd, K K (Am J Phys Anthropol, 1993)
Yellow baboons (Papio hamadryas cynocephalus) from Mikumi National Park, Tanzania were studied for polymorphisms in nuclear DNA. The study population consists of four social groups that inhabit overlapping home ranges and exchange males. As a result, these groups are considered to be members of a single interbreeding population. Human DNA clones were used as probes to screen five loci (AT3, REN, HEXB, VIM, and APOB) for restriction fragment length polymorphisms (RFLP). A total of 14 polymorphisms, at least one at each locus, was detected in a panel of 27 baboons tested using six restriction enzymes for each locus. Eleven of these RFLP systems have average heterozygosity values greater than 0.40. This initial screening demonstrates that human DNA clones can be used to detect significant numbers of informative DNA polymorphisms in single-copy nuclear genes of this species and suggests that the average proportion of nucleotides polymorphic across nuclear loci in this population may be between 1.0% and 1.3%.
Keywords: Animals; Antithrombin III; Apolipoproteins B; beta-N-Acetylhexosaminidases; DNA; Hexosaminidase B; Papio; Polymorphism, Genetic; Polymorphism, Restriction Fragment Length; Renin; Tanzania; Vimentin

Characterization of human genomic yeast artificial chromosome inserts containing hexokinase 1 coding information on chromosome 10. - Gelb, B D; Kim C Worley; Griffin, L D; Adams, V; Chinault, A C; McCabe, E R (Biochem Med Metab Biol, 1992)
Hexokinase 1 (HK1) is one of four mammalian HK isoenzymes and maps to human chromosome 10. Two yeast artificial chromosomes (YACs) were identified in the Washington University human YAC library using polymerase chain reaction (PCR) primers designed with knowledge of the human HK1 cDNA sequence. YAC B129B12 is 120 kb in length and maps entirely to chromosome 10. YAC A159D5 is 400 kb in length and appears to have resulted from a recombination of chromosome 10 with non-chromosome 10 material. We report these YACs as potential resources for those interested in HK1 gene organization and mapping, as well as those desiring additional genomic information and markers on chromosome 10.
Keywords: Animals; Base Sequence; Chromosome Mapping; Chromosomes, Fungal; Chromosomes, Human, Pair 10; Cricetinae; DNA; Genome, Human; Hexokinase; Humans; Isoenzymes; Molecular Sequence Data; Polymerase Chain Reaction; Yeasts

A human dimorphism resulting from loss of an Alu. - Edwards, M C; Richard A Gibbs (Genomics, 1992)
The molecular phylogeny of Alu and other repeated sequences in the human genome provides clues to events during primate evolution. A subclass of human Alu's has been previously identified as dimorphic insertions within members of the medium reiteration frequency (mer) class of repeats, reflecting the complicated sequence of insertion and radiation events leading to the current human genome structure. One dimorphic Alu is located within a previously unidentified mer family member, in the first intron of the human T4 (CD4) gene. The insertion (Alu+ allele) has a frequency of approximately 70% in Europeans and Africans and is homozygous in 20 Asian samples. Polymerase chain reaction amplification, direct DNA sequencing, and Southern analysis using oligonucleotide probes revealed that the Alu- allele was derived from the Alu+ allele by loss of part of the inserted sequence. Comparison with a tightly linked marker within the human genome and studies of baboon DNA samples revealed that the original insertion was a relatively early event in primate evolution, but that the Alu sequence loss leading to the dimorphism has occurred much more recently. Loss of Alu insertions therefore represents one mechanism for the generation of human Alu dimorphisms.
Keywords: Animals; Base Sequence; Blotting, Southern; CD4 Antigens; DNA; Genetic Linkage; Humans; Molecular Sequence Data; Papio; Polymerase Chain Reaction; Polymorphism, Genetic; Repetitive Sequences, Nucleic Acid; Retroviruses, Simian; Sequence Homology, Nucleic Acid

Polymerase chain reaction-based comprehensive procedure for the analysis of the mutation spectrum at the hypoxanthine-guanine phosphoribosyltransferase locus in Chinese hamster cells. - Yu, Y J; Xu, Z; Richard A Gibbs; Hsie, A W (Environ Mol Mutagen, 1992)
We have established a comprehensive procedure based on the polymerase chain reaction (PCR) to analyze the molecular spectrum of mutations at the hypoxanthine-guanine phosphoribosyltransferase (hprt) locus in Chinese hamster cells. The procedure includes direct sequencing of PCR-amplified hprt cDNA for locating point mutations in the expressed coding sequences, multiplex PCR amplification of the hprt exons for screening large deletions, and direct sequencing of PCR-amplified hprt exons and their flanking regions for detecting intronic mutations resulting in mRNA splicing errors. Using this procedure, we have identified different types of mutations among a representative collection of spontaneous and induced HPRT-deficient Chinese hamster cell mutants. This procedure is simple, rapid, accurate, and practical for a comprehensive study of the mutation spectrum in a large number of HPRT-deficient Chinese hamster cell mutants.
Keywords: Animals; Base Sequence; CHO Cells; Cricetinae; DNA; Exons; Hypoxanthine Phosphoribosyltransferase; Molecular Sequence Data; Mutation; Polymerase Chain Reaction

Fidelity of targeted recombination in human fibroblasts and murine embryonic stem cells. - Zheng, H; Hasty, P; Brenneman, M A; Grompe, M; Richard A Gibbs; Wilson, J H; Bradley, A (Proc Natl Acad Sci U S A, 1991)
Targeted recombination in murine embryonic stem cells promises to be a powerful tool for introducing specific mutations into target genes to study development in mice and to create animal models of human disease. Gene targeting also holds potential for correcting genetic defects as an approach to human gene therapy. To precisely modify target genes, homologous recombination must proceed with high fidelity. However, several results have suggested that targeted recombination may be highly mutagenic. To test the accuracy of gene targeting we analyzed 44 independent targeted recombinants at the hypoxanthine phosphoribosyltransferase (HPRT) locus in a human fibroblast cell line and in mouse embryonic stem cells. We surveyed 80 kilobases around the sites of recombination by using chemical cleavage of mismatches. Only two mutations were found: a T----G transversion and a thymidine deletion. Thus, gene targeting in mammalian cells can be extremely accurate. These results demonstrate the feasibility of generating precise modifications of mammalian genomes by gene targeting.
Keywords: Animals; Base Sequence; Fibroblasts; Genetic Vectors; Humans; Hypoxanthine Phosphoribosyltransferase; In Vitro Techniques; Mice; Molecular Sequence Data; Oligonucleotides; Polymerase Chain Reaction; Recombination, Genetic; Stem Cells

Polymerase chain reaction techniques. - Richard A Gibbs (Curr Opin Biotechnol, 1991)
Keywords: Animals; Base Sequence; Humans; Mutation; Oligonucleotides; Polymerase Chain Reaction

Porin interaction with hexokinase and glycerol kinase: metabolic microcompartmentation at the outer mitochondrial membrane. - Adams, V; Griffin, L; Towbin, J; Gelb, B; Kim C Worley; McCabe, E R (Biochem Med Metab Biol, 1991)
Porin is the pore-forming protein involved in the movement of adenine nucleotides across the outer mitochondrial membrane (OMM). Hexokinase and glycerol kinase interact with porin on the outer surface of the OMM in a manner which provides these enzymes with preferred access to the ATP generated in the mitochondrion. We review recent evidence which permits refinement of our knowledge of these proteins and their interactions at the OMM. The involvement of this system in metabolic microcompartmentation is discussed, as well as possible pathological consequences of its disruption in malignancy and genetic deficiencies of hexokinase, glycerol kinase, and porin.
Keywords: Adenine Nucleotides; Animals; Bacterial Outer Membrane Proteins; Glycerol Kinase; Hexokinase; Humans; Ion Channels; Mitochondria; Porins

Aberrant TGF-beta production and regulation in metastatic malignancy. - Schwarz, L C; Wright, J A; Marie-Claude Gingras; Kondaiah, P; Danielpour, D; Pimentel, M; Sporn, M B; Greenberg, A H (Growth Factors, 1990)
We have examined the possible role of transforming growth factor-beta (TGF-beta) in metastatic malignancy by analyzing the production and activation of TGF-beta 1 and -beta 2 and the regulation of TGF-beta-responsive genes in oncogene-transformed metastatic fibrosarcomas. All transformed lines derived from either 10T1/2 or NIH 3T3 by either H-ras or protein-kinase encoding oncogenes produced more TGF-beta than parental cells. However, only highly metastatic fibrosarcomas secreted activated TGF-beta at rates that were greater than parental fibroblasts. Immunohistochemical staining for TGF-beta 1 showed widespread intra- and extracellular distribution in metastatic lung nodules and adjacent tissue. Cells isolated from tumors successfully metastasizing to the lung had TGF-beta 1 mRNA levels which were increased 19-fold over in vitro controls. Despite the greatly enhanced rate of secretion of activated TGF-beta, metastatic cells exhibited markedly altered responses of TGF-beta 1 and TGF-beta 2, being unable to either increase collagen secretion or enhance collagen alpha 2(1) or TGF-beta 1 mRNA levels. This lack of response was not due to either altered TGF-beta receptor affinity or numbers. Metastatic progression was, therefore, associated with an increase in the secretion of activated TGF-beta 1 and a loss of the ability to deregulate TGF-beta-responsive genes.
Keywords: Animals; Cell Line, Transformed; Fibrosarcoma; Gene Expression Regulation, Neoplastic; Immunohistochemistry; Lung Neoplasms; Mice; Mice, Inbred C3H; Oncogenes; Protein Kinases; Receptors, Cell Surface; Receptors, Transforming Growth Factor beta; RNA, Messenger; Transforming Growth Factor beta; Tumor Cells, Cultured

[Theory of microcirculation. 1: Misinterpretations in Starling's hypothesis of microcirculation]. - Petrow, J M (Z Gesamte Inn Med, 1990)
Keywords: Animals; Blood Pressure; Capillaries; Capillary Permeability; Capillary Resistance; Humans; Microcirculation; Models, Cardiovascular

Transient alterations in the expression of protease and extracellular matrix genes during metastatic lung colonization by H-ras-transformed 10T1/2 fibroblasts. - Marie-Claude Gingras; Jarolim, L; Finch, J; Bowden, G T; Wright, J A; Greenberg, A H (Cancer Res, 1990)
It has been proposed that tumor progression is a selective process and that only a minority of tumor cells survive this selection because they possess the phenotypic traits necessary for metastasis and organ colonization. Both proteases and extracellular matrix proteins have been implicated in invasion and metastasis formation. To examine the nature of the selection process, we transformed 10T1/2 fibroblasts with T24 H-ras and the neoR gene and selected a clonal line expressing the mutant ras gene. After i.v. injection of this line into syngeneic C3H/HeN mice, tumor cells were recovered from lungs by enzymatic treatment and selective outgrowth in G418. Less than one of 10(3) cells survived in the lung 30 min after inoculation, and these exhibited a unique phenotype. This was characterized by a propensity to lodge in the lung on reinjection; markedly enhanced mRNA levels of procollagen alpha 2(I), procollagen alpha 1(III), and fibronectin; and decreased levels of laminin, major excreted protein (procathepsin L), transin, and H-ras. Between 1 and 9 days after tumor injection, the phenotype of the cells surviving in the lung changed dramatically and exhibited a pattern of gene expression with increased protease and low matrix protein mRNA levels. This coincided with a 26-fold increase in the ability to colonize lungs on i.v. injection. Both the phenotype characterized by its propensity to arrest in the lung and that showing enhanced metastatic ability were unstable on prolonged in vitro culture. We hypothesize that two selection events have occurred. The first is for lung arrest and implantation of variants of the injected tumor with high matrix protein and low protease levels. A second selection then occurs for tumor cells that carry a favorable phenotype for invasion and proliferation which is associated with low matrix protein and high protease gene expression. These two phenotypes are represented within a clonal population of recently transformed tumor cells.
Keywords: Animals; Cell Line; Cell Transformation, Neoplastic; Endopeptidases; Extracellular Matrix; Fibrosarcoma; Gene Expression Regulation, Neoplastic; Genes, ras; Lung Neoplasms; Mice; Neoplasm Metastasis; Phenotype; Time Factors; Transfection

Deletion screening at the hypoxanthine-guanine phosphoribosyltransferase locus in Chinese hamster cells using the polymerase chain reaction. - Xu, Z D; Yu, Y J; Hsie, A W; Caskey, C T; Rossiter, B; Richard A Gibbs (Teratog Carcinog Mutagen, 1989)
We have developed a rapid screening method using the polymerase chain reaction (PCR) for detecting deletion mutations at the hypoxanthine-guanine phosphoribosyltransferase (hprt) locus in Chinese hamster cells. DNA was extracted from spontaneous and ultraviolet (UV) light- and X-ray-induced hprt-deficient mutants. Two primer sets were used to amplify 276 bp and 344 bp fragments containing the entire exon 3 and exon 9 coding sequence, respectively. The PCR was performed using Taq DNA polymerase for 40 cycles, and the PCR product was directly analyzed for the presence of the respective amplified DNA using electrophoresis on agarose gels stained with ethidium bromide. With this assay, we have analyzed 39 independently derived hprt-deficient mutants. Four of ten spontaneous mutants were found to have deletions in exon 9. UV light produced mutants with predominantly wild-type amplification patterns (10/14). X-ray induced mostly deletion patterns (11/15); six of these occurred only in exon 9, and five occurred in both exons 3 and 9. These observations are consistent with the classical notion that UV light induces predominantly missense mutations and X-ray produces a high proportion of deletion mutations. Deletion mutations occurred most frequently at the 3' end of the hprt gene, suggesting the possible existence of hot spots for deletions in this region. The PCR assay for deletion detection has the advantage that it can be completed in less than 4 hr without using radioisotopes. This assay should be useful for routine deletion screening.
Keywords: Animals; Cells, Cultured; Chromosome Deletion; DNA; DNA-Directed DNA Polymerase; Electrophoresis, Agar Gel; Exons; Gene Amplification; Hypoxanthine Phosphoribosyltransferase; Ultraviolet Rays; X-Rays

Detection of single DNA base differences by competitive oligonucleotide priming. - Richard A Gibbs; Nguyen, P N; Caskey, C T (Nucleic Acids Res, 1989)
Synthetic DNA oligonucleotides can serve as efficient primers for DNA synthesis even when there is a single base mismatch between the primers and the corresponding DNA template. However, when the primer-template annealing is carried out with a mixture of primers and at low stringency the binding of a perfectly matched primer is strongly favored relative to a primer differing by a single base. This primer competition is observed over a range of oligonucleotide sizes from twelve to sixteen bases and with a variety of base mismatches. When coupled with the polymerase chain reaction, for the amplification of specific DNA sequences, competitive oligonucleotide priming provides a simple general strategy for the detection of single DNA base differences.
Keywords: Animals; Base Sequence; Binding, Competitive; DNA; DNA, Single-Stranded; DNA-Directed DNA Polymerase; Gene Amplification; Mice; Mice, Mutant Strains; Molecular Sequence Data; Mutation; Oligonucleotides; Taq Polymerase; Templates, Genetic

Differential regulation of normal and tumor alpha 1-fetoprotein genes in fetal hepatocyte x hepatoma hybrids. - Marie-Claude Gingras; Szpirer, J; Turcotte, B; Bélanger, L; Szpirer, C (Cancer Res, 1988)
Fetal rat hepatocytes and mouse hepatoma cells actively expressing alpha 1-fetoprotein (AFP) and albumin genes were fused with the use of Sendai virus, and the expression of normal (rat) and tumor (mouse) AFP and albumin genes was analyzed in hybrid clones. The tumor AFP gene and both albumin genes were active in 103 hybrids. Expression of the normal fetal rat AFP gene, however, was maintained in only 3 hybrids, and it was frequently lost or decreased selectively upon subcloning. Furthermore, the normal AFP gene, when expressed, was more reactive than the tumor AFP gene to repression by a glucocorticosteroid hormone. These results suggest constitutive differences in the manner an oncofetal gene is activated and regulated in normal and neoplastic states. AFP gene expression in normal hepatocytes appears to be subordinated to a differentiation program degenerated and bypassed in hepatoma cells.
Keywords: Albumins; alpha-Fetoproteins; Animals; Cell Fusion; Fetus; Gene Expression Regulation; Liver; Liver Neoplasms, Experimental; Mice; Rats

Enhancer and promoter elements directing activation and glucocorticoid repression of the alpha 1-fetoprotein gene in hepatocytes. - Guertin, M; LaRue, H; Bernier, D; Wrange, O; Chevrette, M; Marie-Claude Gingras; Bélanger, L (Mol Cell Biol, 1988)
Mutations were introduced in 7 kilobases of 5'-flanking rat alpha 1-fetoprotein (AFP) genomic DNA, linked to the chloramphenicol acetyltransferase gene. AFP promoter activity and its repression by a glucocorticoid hormone were assessed by stable and transient expression assays. Stable transfection assays were more sensitive and accurate than transient expression assays in a Morris 7777 rat hepatoma recipient (Hepa7.6), selected for its strong AFP repression by dexamethasone. The segment of DNA encompassing a hepatocyte-constitutive chromatin DNase I-hypersensitive site at -3.7 kilobases and a liver developmental stage-specific site at -2.5 kilobases contains interacting enhancer elements sufficient for high AFP promoter activity in Hepa7.6 or HepG2 cells. Deletions and point mutations define an upstream promoter domain of AFP gene activation, operating with at least three distinct promoter-activating elements, PEI at -65 base pairs, PEII at -120 base pairs, and DE at -160 base pairs. PEI and PEII share homologies with albumin promoter sequences, PEII is a near-consensus nuclear factor I recognition sequence, and DE overlaps a glucocorticoid receptor recognition sequence. An element conferring glucocorticoid repression of AFP gene activity is located in the upstream AFP promoter domain. Receptor-binding assays indicate that this element is the glucocorticoid receptor recognition sequence which overlaps with promoter-activating element DE.
Keywords: Acetyltransferases; alpha-Fetoproteins; Animals; Base Sequence; Chloramphenicol O-Acetyltransferase; Cloning, Molecular; Cytosol; Dexamethasone; Enhancer Elements, Genetic; Enzyme Induction; Gene Expression Regulation; Genes; Genes, Regulator; Liver; Liver Neoplasms, Experimental; Molecular Sequence Data; Plasmids; Promoter Regions, Genetic; Rats; Transcriptional Activation; Transfection; Tyrosine Transaminase

Expression of the murine Duchenne muscular dystrophy gene in muscle and brain. - Chamberlain, J S; Pearlman, J A; Donna M Muzny; Richard A Gibbs; Ranier, J E; Caskey, C T; Reeves, A A (Science, 1988)
Complementary DNA clones were isolated that represent the 5' terminal 2.5 kilobases of the murine Duchenne muscular dystrophy (Dmd) messenger RNA (mRNA). Mouse Dmd mRNA was detectable in skeletal and cardiac muscle and at a level approximately 90 percent lower in brain. Dmd mRNA is also present, but at much lower than normal levels, in both the muscle and brain of three different strains of dystrophic mdx mice. The identification of Dmd mRNA in brain raises the possibility of a relation between human Duchenne muscular dystrophy (DMD) gene expression and the mental retardation found in some DMD males. These results also provide evidence that the mdx mutations are allelic variants of mouse Dmd gene mutations.
Keywords: Animals; Brain; DNA; DNA, Recombinant; Gene Expression Regulation; Intellectual Disability; Mice; Mice, Inbred ICR; Mice, Mutant Strains; Muscles; Muscular Dystrophy, Animal; Mutation; Nucleic Acid Hybridization; Ribonuclease, Pancreatic; RNA, Messenger

Generation of cDNA probes directed by amino acid sequence: cloning of urate oxidase. - Lee, C C; Wu, X W; Richard A Gibbs; Cook, R G; Donna M Muzny; Caskey, C T (Science, 1988)
Urate oxidase (E.C. 1.7.3.3) catalyzes the oxidation of uric acid to allantoin in most mammals except humans and certain primates. The amino-terminal amino acid sequence for porcine urate oxidase was determined and used in a novel procedure for generating complementary DNA (cDNA) probes to this amino acid sequence. The procedure is based on the polymerase chain reaction and utilizes mixed oligonucleotide primers complementary to the reverse translation products of an amino acid sequence. This rapid and simple cDNA cloning procedure is generally applicable and requires only a partial amino acid sequence. A cDNA probe developed by this procedure was used to isolate a full-length porcine urate oxidase cDNA and to demonstrate the presence of homologous genomic sequences in humans.
Keywords: Amino Acid Sequence; Animals; Base Sequence; Cloning, Molecular; DNA; Gene Amplification; Liver; Mice; Molecular Sequence Data; Nucleic Acid Hybridization; Swine; Urate Oxidase

The genetic structure of mouse ornithine transcarbamylase. - Steven E Scherer; Veres, G; Caskey, C T (Nucleic Acids Res, 1988)
The gene encoding the mouse urea cycle enzyme, ornithine transcarbamylase has been isolated on five partially overlapping bacteriophage lambda clones. We have characterized the gene and found that it is split between ten exons distributed over approximately 70 kb of the X chromosome. The introns range in size from 88 bases to the relatively unusual size of approximately 26 kilobases, while the splice donor/splice acceptor sequences conform to the consensus established for other eukaryotic genes.
Keywords: Animals; Base Sequence; DNA Restriction Enzymes; DNA, Recombinant; Genes; Mice; Molecular Sequence Data; Nucleic Acid Hybridization; Ornithine Carbamoyltransferase

Loss of growth factor dependence and conversion of transforming growth factor-beta 1 inhibition to stimulation in metastatic H-ras-transformed murine fibroblasts. - Schwarz, L C; Marie-Claude Gingras; Goldberg, G; Greenberg, A H; Wright, J A (Cancer Res, 1988)
Cell lines with varying tumorigenic and metastatic potentials have been obtained by transformation of 10T 1/2 fibroblasts using radiation or transfection with T-24 H-ras. We have observed an inverse relationship between metastatic potential and dependence on serum for growth. The effects of basic fibroblast growth factor, platelet-derived growth factor, epidermal growth factor, and transforming growth factor-beta 1 (TGF-beta 1) on these lines were then examined to determine if the changes in the serum dependence of metastatic cells may be due to altered responsiveness to specific growth factors (GFs). Cells were grown in monolayer culture and DNA synthesis was measured by [CH3-3H]thymidine incorporation experiments. Both metastatic and nonmetastatic cells were shown to be equivalent in their diminished responsiveness to basic fibroblast growth factor, platelet-derived growth factor, and epidermal growth factor as compared to their nontransformed, parental 10T 1/2 cells. However, a unique response of metastatic cells to TGF-beta 1 was identified. While TGF-beta 1 inhibited DNA synthesis in 10T 1/2 cells and a nonmetastatic tumor, cells with intermediate to high metastatic ability were stimulated up to 5.8-fold by TGF-beta 1. Interestingly, epidermal growth factor abrogated the TGF-beta 1 inhibition of the parental 10T 1/2 cells, but had no effect on the TGF-beta 1 response of any metastatic line. Therefore, metastatic but not nonmetastatic cells, demonstrated a dramatically altered sensitivity to TGF-beta 1, a response which may be important in determining metastatic potential.
Keywords: Animals; Cell Line; Cell Transformation, Neoplastic; DNA Replication; Epidermal Growth Factor; Fibroblast Growth Factors; Fibroblasts; Fibrosarcoma; Genes, ras; Growth Substances; Mice; Mice, Inbred BALB C; Neoplasm Metastasis; Platelet-Derived Growth Factor; Transforming Growth Factors

The molecular basis of the sparse fur mouse mutation. - Veres, G; Richard A Gibbs; Steven E Scherer; Caskey, C T (Science, 1987)
The ornithine transcarbamylase-deficient sparse fur mouse is an excellent model to study the most common human urea cycle disorder. The mutation has been well characterized by both biochemical and enzymological methods, but its exact nature has not been revealed. A single base substitution in the complementary DNA for ornithine transcarbamylase from the sparse fur mouse has been identified by means of a combination of two recently described techniques for rapid mutational analysis. This strategy is simpler than conventional complementary DNA library construction, screening, and sequencing, which has often been used to find a new mutation. The ornithine transcarbamylase gene in the sparse fur mouse contains a C to A transversion that alters a histidine residue to an asparagine residue at amino acid 117.
Keywords: Amino Acid Sequence; Animals; Base Sequence; Disease Models, Animal; DNA; Genes; Mice; Mice, Mutant Strains; Mutation; Ornithine Decarboxylase; RNA, Messenger

Molecular characterization of 125I decay and X-ray-induced HPRT mutants in CHO cells. - Richard A Gibbs; Camakaris, J; Hodgson, G S; Martin, R F (Int J Radiat Biol Relat Stud Phys Chem Med, 1987)
The predominant initial lesion induced by 125I decay in DNa is a double-strand DNA break comprising a 'mini deletion' of up to several base pairs (bp). However, Southern analysis of the structure of 125I decay-induced HPRT mutants in Chinese hamster ovary cells revealed that most of the mutants are deletions of thousands of bps. A similar predominance of substantial deletions was also found in X-ray-induced mutants.
Keywords: Animals; Chromosome Deletion; Cricetinae; DNA Repair; Gamma Rays; Hypoxanthine Phosphoribosyltransferase; Iodine Radioisotopes; Mutation; Polymorphism, Restriction Fragment Length; X-Rays

Natural killer cell regulation of implantation and early lung growth of H-ras-transformed 10T1/2 fibroblasts in mice. - Greenberg, A H; Egan, S E; Jarolim, L; Marie-Claude Gingras; Wright, J A (Cancer Res, 1987)
We examined the relative role of the natural killer (NK) cell and H-ras gene in controlling metastasis formation using a novel assay for quantitating viable tumor cells entering and surviving in the lung for up to 13 days following i.v. tumor inoculation. This assay utilized the resistance to G418 sulfate conferred by transfection of the neoR gene into 10T1/2 fibroblasts along with activated H-ras. We had previously shown that the metastatic efficiency of T-24-H-ras-transformed 10T1/2 fibroblasts correlated with H-ras expression at the RNA level. In this paper we show that the NK cell could recognize H-ras-transformed fibroblasts in vivo and control experimental metastasis formation using NK-suppressed and -activated syngeneic C3H recipients. Evaluation of NK sensitivity in vitro of individual lines did not predict metastatic ability. However, NK susceptibility in vitro did inversely correlate with the ability of tumor cells to arrest and survive in the lung for the first 48 h after i.v. inoculation. Although the level of H-ras RNA correlated with the ultimate metastatic potential, it did not correlate with the initial rate of tumor cell pulmonary retention or clearing. Over the next 10 to 12 days, however, we detected a preferential survival and outgrowth of high H-ras-expressing variants, which correlated well with the ultimate metastatic ability but not NK susceptibility. These observations argue that the NK cell has its major effect early in the course of the disease, while subsequent tumor growth occurs preferentially in high H-ras-expressing cell lines.
Keywords: Animals; Fibroblasts; Killer Cells, Natural; Lung Neoplasms; Mice; Mice, Inbred C3H; Neoplasm Metastasis; Oncogenes; Transfection

Oncodevelopmental and hormonal regulation of alpha 1-fetoprotein gene expression. - Bélanger, L; Baril, P; Guertin, M; Marie-Claude Gingras; Gourdeau, H; Anderson, A; Hamel, D; Boucher, J M (Adv Enzyme Regul, 1983)
The main features of the oncodevelopmental biology of alpha 1-fetoprotein (AFP) are reviewed. Progress made in the molecular biology of AFP gene regulation is discussed and we present our recent data on the mechanisms of AFP suppression by glucocorticoid hormones. The relationship between AFP gene transcription and cell replication is examined, and it is suggested that the degree of methylation of the AFP gene (or of co-methylated regulatory DNA sequences) conditions its response to hormones.
Keywords: Albumins; alpha-Fetoproteins; Animals; Base Sequence; Dexamethasone; DNA Replication; Gene Expression Regulation; Hormones; Humans; Liver; Medroxyprogesterone; Methionine; Oncogenes; Rats; RNA, Messenger; Transcription, Genetic

Glucocorticosteroid suppression of alpha1-fetoprotein synthesis in developing rat liver. Evidence for selective gene repression at the transcriptional level. - Bélanger, L; Frain, M; Baril, P; Marie-Claude Gingras; Bartkowiak, J; Sala-Trepat, J M (Biochemistry, 1981)
Keywords: alpha-Fetoproteins; Animals; Dexamethasone; Genes; Kinetics; Liver; Nucleic Acid Hybridization; Prednisolone; Rats; Rats, Inbred Strains; RNA, Messenger; Serum Albumin; Transcription, Genetic